14th St. Gallen International Breast Cancer Conference 2015: Evidence, Controversies, Consensus - Primary Therapy of Early Breast Cancer: Opinions Expressed by German Experts - Jackisch, Christian; Harbeck, Nadia; Huober, Jens; Von Minckwitz, Gunter; Gerber, Bernd; Kreipe, Hans-Heinrich; Liedtke, Cornelia; Marschner, Norbert; Moebus, Volker; Scheithauer, Heike; Schneeweiss, Andreas; Thomssen, Christoph; et al. (Breast Care, 2015)
The key topics of this year's 14th St. Gallen Consensus Conference on the diagnosis and therapy of primary breast cancer were again questions about breast surgery and axillary surgery, radio-oncology and systemic therapy options in consideration of tumor biology, and the clinical application of multigene assays. This year, the consensus conference took place in Vienna. From a German perspective, it makes sense to substantiate the results of the vote of the international panel representing 19 countries in light of the updated national therapy recommendations of the AGO (Arbeitsgemeinschaft Gynäkologische Onkologie). Therefore, 14 German breast cancer experts, 3 of whom are members of the International St. Gallen Panel, have commented on the voting results of the St. Gallen Consensus Conference 2015 in relation to clinical routine in Germany.
EVALuna2:17563

2D:4D biomarker reliability and validity in a within-subject pregnancy-childhood-adolescence cohort - Eichler, Anna; Kaufmann, Franziska; Titzmann, Adriana; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Buchholz, Verena Nadine; Kornhuber, Johannes; Lenz, Bernd (Early Human Development, 2023)
Background: A lot of studies use the second-to-fourth digit length ratio (2D:4D) as a biomarker for intrauterine androgen load to predict behavioral and mental health problems. Thus, knowledge of 2D:4D's metric properties, namely reliability and validity, is essential. Method: 2D:4D handscans were available from 149 adolescents (M = 13.32 years, SD = 0.35) and their mothers. For 88 adolescents, there were also primary-school age handscans (M = 7.87 years, SD = 0.68). Prenatal risks for the 1st to 3rd trimesters were recorded during the 3rd trimester of pregnancy (alcohol exposition: meconium biomarker and maternal self-report; nicotine exposition: maternal self-report; maternal depressive symptoms and subjective stress: questionnaires). Results: The 2D:4D ratio was highly stable from childhood to early adolescence. However, both developmental and sex effects were present: The 2D:4D ratio increased with age and was higher in adolescent girls vs. boys. Significant 2D:4D mother-child associations were found for girls. Significant main effects could be found for the prenatal risk factors alcohol (self-report) and nicotine consumption. Conclusion: In line with earlier studies, the 2D:4D biomarker proved to be an inter-individually stable measure with an intra-individual increase from childhood to early adolescence. Sex differences in adolescence and associations with maternal prenatal health behaviour underline the validity of the biomarker. Findings on heritability emphasize the importance of interpreting 2D:4D results in a sex-specific manner.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 2D:4D ratio; Alcohol; Androgen load; Biomarker; Construct validity; Heritability; Nicotine; Pregnancy risk; Prenatal; Retest reliability; Stability; Testosterone exposure

2q36.3 is associated with prognosis for oestrogen receptor-negative breast cancer patients treated with chemotherapy - Li, Jingmei; Lindstroem, Linda S.; Foo, Jia N.; Rafiq, Sajjad; Schmidt, Marjanka K.; Pharoah, Paul D. P.; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Van'T Veer, Laura J.; Cornelissen, Sten; et al. (Nature Communications, 2014)
Large population-based registry studies have shown that breast cancer prognosis is inherited. Here we analyse single-nucleotide polymorphisms (SNPs) of genes implicated in human immunology and inflammation as candidates for prognostic markers of breast cancer survival involving 1,804 oestrogen receptor (ER)-negative patients treated with chemotherapy (279 events) from 14 European studies in a prior large-scale genotyping experiment, which is part of the Collaborative Oncological Gene-environment Study (COGS) initiative. We carry out replication using Asian COGS samples (n=522, 53 events) and the Prospective Study of Outcomes in Sporadic versus Hereditary breast cancer (POSH) study (n=315, 108 events). Rs4458204_A near CCL20 (2q36.3) is found to be associated with breast cancer-specific death at a genome-wide significant level (n=2,641, 440 events, combined allelic hazard ratio (HR)=1.81 (1.49-2.19); P for trend=1.90 × 10(-9)). Such survival-associated variants can represent ideal targets for tailored therapeutics, and may also enhance our current prognostic prediction capabilities.
EVALuna2:9232

ABC5 International Consensus Conference on Advanced Breast Cancer, Lisbon, 16 November 2019 - Untch, Michael; Würstlein, Rachel; Lüftner, Diana; Haidinger, Renate; Fasching, Peter; Augustin, Doris; Briest, Susanne; Ettl, Johannes; Förster, Frank; Kurbacher, Christian M.; Lück, Hans Joachim; Marschner, Norbert; et al. (Geburtshilfe und Frauenheilkunde, 2020)
The Advanced Breast Cancer Fifth International Consensus Conference (ABC5) which focuses on the diagnosis and treatment of advanced breast cancer was held in Lisbon on November 14 - 16, 2019. The aim of the conference is to standardize the treatment of advanced breast cancer worldwide using evidence-based data and to ensure that patients with advanced breast disease anywhere in the world are treated appropriately and have access to the latest therapies. This year, the emphasis was on new developments and study results from patients with advanced breast cancer as well as precision medicine. The collaboration with patient advocates from all over the globe is also an important goal of the ABC Conference, which is why the international ABC panel also included a number of patient advocates. We present a commentary on the voting results of the ABC5 panelists in Lisbon by a working group of German breast cancer specialists together with the implications for routine clinical care in Germany. The commentary is based on the recommendations of the Breast Commission of the German Gynecological Oncology Working Group (AGO). This commentary is useful, it includes country-specific features for the ABC consensus.
CRIS-Team Scopus Importer:2020-07-24
Keywords: 2019 study data; ABC5 consensus; advanced breast cancer; precision medicine

ABC6 Consensus: Assessment by a Group of German Experts - Lueftner, Diana; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Jackisch, Christian; Mueller, Volkmar; Schumacher-Wulf, Eva; Thomssen, Christoph; Untch, Michael; Wuerstlein, Rachel (Breast Care, 2022)
Background: The first International Consensus Conference for Advanced Breast Cancer (ABC1) took place 10 years ago in November 2011. The rationale was - and still is - to standardize treatment of advanced breast cancer (ABC) based on the available evidence and to ensure that worldwide all breast cancer patients receive adequate treatment and access to new therapies. Rationale for the Manuscript: The 6th International Consensus Conference for ABC (ABC6) took place from November 4 to 6, 2021 and was the first in a purely online format, due to the COVID-19 pandemic. In the present manuscript, a working group of German breast cancer experts comments on the voting results of the ABC6 panelists regarding their applicability for routine clinical practice in Germany. Method: The ABC6 votes mainly include modified or new statements. With regard to all statements not modified for the ABC6 consensus, the German experts refer to the published paper of the ABC5 consensus. The German experts base their comments on the current recommendations of the Breast Committee of the Gynecological Oncology Working Group (Arbeitsgemeinschaft Gynakologische Onkologie, AGO Mamma). Topics: ABC6 focused on new treatment options and their implications for clinical practice. Optimal therapy sequencing for example was one of the issues. To solve the challenge of a more individualized treatment, precision medicine is fundamental. Oligometastatic disease, brain metastases and adequate supportive and palliative care were also addressed. Of special interest was the treatment of inoperable locally advanced breast cancer, which was discussed as a separate topic. As in previous years, patient advocates from around the world were an integral part of the ABC6 conference and had a major input into the consensus.& nbsp;(c) 2022 S. Karger AG, Basel
CRIS-Team WoS Importer:2022-03-11

ABC7 Consensus: Assessment by a German Group of Experts - Ditsch, Nina; Untch, Michael; Fasching, Peter; Busch, Steffi; Ettl, Johannes; Haidinger, Renate; Jackisch, Christian; Lüftner, Diana; Müller, Lothar; Müller, Volkmar; Ruckhäberle, Eugen; Schumacher-Wulf, Eva; et al. (Breast Care, 2024)
Background: The "International Consensus Conference for Advanced Breast Cancer"was initiated more than 10 years ago. The rationale was to standardize treatment of advanced breast cancer (ABC) based on available evidence and to ensure that all ABC patients worldwide receive adequate treatment and access to new therapies. Topics of ABC7: The 7th International Consensus Conference for ABC (ABC7) took place from November 9 to 11, 2023 - as in previous years in Lisbon/Portugal. ABC7 focused not only on metastatic disease but also on locally advanced and inflammatory breast cancer. Special topics were the management of oligometastatic disease, leptomeningeal disease, brain metastases, and pregnant women with ABC. Due to the current situation worldwide, there was a special interest to patients living in conflict zones. As in previous years, patient advocates from around the world were integrated into the ABC conference and had a major input to the consensus. Rationale for the Manuscript: A German breast cancer expert panel comments on the voting results of the ABC7 panelists regarding their relevance for routine clinical practice in Germany. As with previous meetings, the ABC7 votes focused on modified or new statements. Regarding the statements not modified for the ABC7 consensus, they are discussed in the published manuscript from 2021 in which the German experts commented on the ABC6 consensus. The German comments are always based on the current recommendations of the "Breast Committee"of the Gynecological Oncology Working Group (Arbeitsgemeinschaft Gynäkologische Onkologie, AGO Mamma).
CRIS-Team Scopus Importer:2024-05-03
Keywords: ADCs; Advanced breast cancer and pregnancy; Brain metastases; Leptomeningeal disease; Oligometastatic disease; Systemic therapy

ABC7-Konsens zur Systemtherapie des fortgeschrittenen Mammakarzinoms - Lüftner, Diana; Ditsch, Nina; Fasching, Peter; Busch, Steffi; Ettl, Johannes; Haidinger, Renate; Jackisch, Christian; Müller, Lothar; Müller, Volkmar; Ruckhäberle, Eugen; Schumacher-Wulf, Eva; Thomssen, Christoph; et al. (Die Onkologie, 2024)
Background: The 7th “International Consensus Conference on Advanced Breast Cancer” (ABC) met from 9–12 November 2023 in Lisbon, Portugal. The consensus is organized by a group of experts from different countries and disciplines. Rationale: The rationale of the international consensus conference is to standardize the treatment of patients with primarily inoperable, locally advanced or with metastatic breast cancer worldwide on an evidence-based basis and to ensure that adequate therapy is possible in all countries. This manuscript discusses the on-site voting results of the ABC7 panel for everyday clinical practice in Germany. Basis: The discussion is related to the German guidelines of the “Arbeitsgemeinschaft Gynäkologische Onkologie” (AGO Organkommission Mamma, Version 2024.1D) which is updated annually, most recently in March 2024. Results: In this manuscript, the focus is on systemic treatment of patients with metastatic cancer. Special topics included the treatment of patients with oligometastases, leptomeningeal disease, and brain metastases and of pregnant patients. As in previous years, patient representatives from all over the world took part in the conference and were involved in reaching consensus.
CRIS-Team Scopus Importer:2024-10-25
Keywords: ABC and pregnancy; ADCs; Brain metastases; Leptomeningeal disease; Oligometastases

ABCA transporter gene expression and poor outcome in epithelial ovarian cancer - Hedditch, Ellen L.; Gao, Bo; Russell, Amanda J.; Lu, Yi; Emmanuel, Catherine; Beesley, Jonathan; Johnatty, Sharon E.; Chen, Xiaoqing; Harnett, Paul; George, Joshy; Williams, Rebekka T.; Flemming, Claudia; et al. (Journal of the National Cancer Institute, 2014)
ATP-binding cassette (ABC) transporters play various roles in cancer biology and drug resistance, but their association with outcomes in serous epithelial ovarian cancer (EOC) is unknown.The relationship between clinical outcomes and ABC transporter gene expression in two independent cohorts of high-grade serous EOC tumors was assessed with real-time quantitative polymerase chain reaction, analysis of expression microarray data, and immunohistochemistry. Associations between clinical outcomes and ABCA transporter gene single nucleotide polymorphisms were tested in a genome-wide association study. Impact of short interfering RNA-mediated gene suppression was determined by colony forming and migration assays. Association with survival was assessed with Kaplan-Meier analysis and log-rank tests. All statistical tests were two-sided.Associations with outcome were observed with ABC transporters of the "A" subfamily, but not with multidrug transporters. High-level expression of ABCA1, ABCA6, ABCA8, and ABCA9 in primary tumors was statistically significantly associated with reduced survival in serous ovarian cancer patients. Low levels of ABCA5 and the C-allele of rs536009 were associated with shorter overall survival (hazard ratio for death = 1.50; 95% confidence interval [CI] =1.26 to 1.79; P = 6.5e-6). The combined expression pattern of ABCA1, ABCA5, and either ABCA8 or ABCA9 was associated with particularly poor outcome (mean overall survival in group with adverse ABCA1, ABCA5 and ABCA9 gene expression = 33.2 months, 95% CI = 26.4 to 40.1; vs 55.3 months in the group with favorable ABCA gene expression, 95% CI = 49.8 to 60.8; P = .001), independently of tumor stage or surgical debulking status. Suppression of cholesterol transporter ABCA1 inhibited ovarian cancer cell growth and migration in vitro, and statin treatment reduced ovarian cancer cell migration.Expression of ABCA transporters was associated with poor outcome in serous ovarian cancer, implicating lipid trafficking as a potentially important process in EOC.
EVALuna2:9230

ABEMACARE: Abemaciclib in combination with endocrine therapy as first line therapy in metastatic breast cancer patients with symptomatic visceral metastases or high tumor burden - Kotzur, Franziska; Bidner, Helen; Bronger, Holger; Egert, Silvia; Fasching, Peter; Fischer, Dorothea; Kehl, Victoria; Luck, Hans-Joachim; Muller, Lothar; Reuning, Ute; Rief, Lukas; Rosch, Romina; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

A careful reassessment of anthracycline use in curable breast cancer - Hurvitz, Sara Alsterlind; Mcandrew, Nicholas P.; Bardia, Aditya; Press, Michael F.; Pegram, Mark; Crown, John P.; Fasching, Peter; Ejlertsen, Bent; Yang, Eric H.; Glaspy, John A.; Slamon, Dennis J. (npj Breast Cancer, 2021)
It has been over three decades since anthracyclines took their place as the standard chemotherapy backbone for breast cancer in the curative setting. Though the efficacy of anthracycline chemotherapy is not debatable, potentially life-threatening and long-term risks accompany this class of agents, leading some to question their widespread use, especially when newer agents with improved therapeutic indices have become available. Critically assessing when to incorporate an anthracycline is made more relevant in an era where molecular classification is enabling not only the development of biologically targeted therapeutics but also is improving the ability to better select those who would benefit from cytotoxic agents. This comprehensive analysis will present the problem of overtreatment in early-stage breast cancer, review evidence supporting the use of anthracyclines in the pre-taxane era, analyze comparative trials evaluating taxanes with or without anthracyclines in biologically unselected and selected patient populations, and explore published work aimed at defining anthracycline-sensitive tumor types.
CRIS-Team Scopus Importer:2021-10-22

Accuracy of radiological tumour size assessment and the risk for re-excision in a cohort of primary breast cancer patients - Meier-Meitinger, Martina; Rauh, Claudia; Adamietz, B.; Fasching, Peter; Schwab, Siegfried; Häberle, Lothar; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; Lux, Michael P.; Hartmann, Arndt; Wachter, David Lukas; et al. (Ejso, 2012)
Background: Re-operations after breast conserving surgery (BCS) are necessary, when specimen margins are not free of breast cancer cells. This study explored the accuracy of preoperative tumour size assessment and its influence on the rate of re-excisions and mastectomies. Methods: The study included 1591 patients with invasive breast cancer, who were planned for BCS. Patient, staging and tumor characteristics were evaluated concerning their influence on re-excision and mastectomy rates. Patient and tumor characteristics comprised histopathological tumour size, HER2 status, multifocality, in situ component, grading (G), nodal status and hormone receptor (HR) status. Staging characteristics included deviation from pathological tumour size as measured by clinical examination, sonography and mammography. Results: In 1316 patients (83%) sufficient treatment was possible with one operation. 275 patients (17%) had to undergo at least one further surgery as a result of positive specimen margins. In 138 patients (9%) mastectomy was ultimately necessary. In patients with a positive HER2 status, a larger tumour size, underestimation by ultrasound, an in situ component and multifocality, the risk for a re-operation was about doubled. Tumour size deviation in the mammogram or the clinical tumour size assessment did not have significant influence to the re-excision rates. Conclusion: Tumour size and accurate presurgical assessment of the tumour size itself are independent predictors for the need of a second surgery or even a mastectomy in patients for whom a primary BCS was planned. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Mastectomy; Re-excision; Tumour size; Ultrasound

A comprehensive evaluation of interaction between genetic variants and use of menopausal hormone therapy on mammographic density - Rudolph, Anja; Fasching, Peter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Thompson, Deborah; Czene, Kamila; Brand, Judith S.; Li, Jingmei; Scott, Christopher; Pankratz, V. Shane; et al. (Breast Cancer Research, 2015)
Mammographic density is an established breast cancer risk factor with a strong genetic component and can be increased in women using menopausal hormone therapy (MHT). Here, we aimed to identify genetic variants that may modify the association between MHT use and mammographic density.The study comprised 6,298 postmenopausal women from the Mayo Mammography Health Study and nine studies included in the Breast Cancer Association Consortium. We selected for evaluation 1327 single nucleotide polymorphisms (SNPs) showing the lowest P-values for interaction (P int) in a meta-analysis of genome-wide gene-environment interaction studies with MHT use on risk of breast cancer, 2541 SNPs in candidate genes (AKR1C4, CYP1A1-CYP1A2, CYP1B1, ESR2, PPARG, PRL, SULT1A1-SULT1A2 and TNF) and ten SNPs (AREG-rs10034692, PRDM6-rs186749, ESR1-rs12665607, ZNF365-rs10995190, 8p11.23-rs7816345, LSP1-rs3817198, IGF1-rs703556, 12q24-rs1265507, TMEM184B-rs7289126, and SGSM3-rs17001868) associated with mammographic density in genome-wide studies. We used multiple linear regression models adjusted for potential confounders to evaluate interactions between SNPs and current use of MHT on mammographic density.No significant interactions were identified after adjustment for multiple testing. The strongest SNP-MHT interaction (unadjusted P int <0.0004) was observed with rs9358531 6.5kb 5' of PRL. Furthermore, three SNPs in PLCG2 that had previously been shown to modify the association of MHT use with breast cancer risk were found to modify also the association of MHT use with mammographic density (unadjusted P int <0.002), but solely among cases (unadjusted P int SNP×MHT×case-status <0.02).The study identified potential interactions on mammographic density between current use of MHT and SNPs near PRL and in PLCG2, which require confirmation. Given the moderate size of the interactions observed, larger studies are needed to identify genetic modifiers of the association of MHT use with mammographic density.
EVALuna2:9284

A content-based review of mobile health applications for breast cancer prevention and education: Characteristics, quality and functionality analysis - Altmannshofer, Stefanie; Flaucher, Madeleine; Beierlein, Milena; Eskofier, Björn; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (Digital Health, 2024)
Objective: Mobile Health apps could be a feasible and effective tool to raise awareness for breast cancer prevention and to support women to change their behaviour to a healthier lifestyle. The aim of this study was to analyse the characteristics and quality of apps designed for breast cancer prevention and education. Methods: We conducted a systematic search for apps covering breast cancer prevention topics in the Google Play and Apple App Store accessible from Germany using search terms either in German or in English. Only apps with a last update after June 2020 were included. The apps identified were downloaded and evaluated by two independent researchers. App quality was analysed using the Mobile Application Rating Scale (MARS). Associations of app characteristics and MARS rating were analysed. Results: We identified 19 apps available in the Google Play Store and seven apps available in the Apple App Store that met all inclusion criteria. The mean MARS score was 3.07 and 3.50, respectively. Functionality was the highest-scoring domain. Operating system, developer (healthcare), download rates and time since the last update were significantly associated with overall MARS score. In addition, the presence of the following app functions significantly influenced MARS rating: breast self-examination tutorial, reminder for self-examination, documentation feature and education about breast cancer risk factors. Conclusions: Although most of the apps offer important features for breast cancer prevention, none of the analysed apps combined all functions. The absence of healthcare professionals’ expertise in developing apps negatively affects the overall quality.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Breast cancer; MARS; mHealth; mobile apps; prevention; quality; rating

Active Participation, Mind–Body Stabilization, and Coping Strategies with Integrative Medicine in Breast Cancer Patients - Theuser, Anna-Katharin; Antoniadis, Sophia; Langemann, Hanna; Wasner, Sonja; Grasruck, Katharina; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Hack, Carolin (Integrative Cancer Therapies, 2021)
Purpose: Increasing numbers of breast cancer survivors have led to a growing demand for integrative medicine. When patients have completed treatments associated with severe side effects, attention turns to reducing psychological symptoms, coping behavior, and self-care. The aim of this study was to assess patient-reported benefits in relation to active participation, mind–body stabilization, and coping strategies in breast cancer patients receiving integrative medicine. Methods: In a cross-sectional study, health counseling and treatment provided by a standardized integrative medicine consultancy service at the University Breast Center of Franconia were evaluated in 75 breast cancer patients over a 15-month period. At the baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. Patient-reported outcomes relative to active participation, mind–body stabilization, and coping strategies were analyzed. Results: A large majority of the patients had previous experience with integrative medicine (91%). Most reported that they achieved their treatment goals with integrative medicine. Ninety-one percent achieved active participation in cancer treatment, 90% mind–body stabilization, and 79% improvement in coping strategies. Besides active participation, which was greatest in patients with stable disease, the success of integrative therapy was independent of age, concomitant diseases, previous integrative medicine experience, treatment state, and systemic cancer therapy. Conclusion: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in mind–body stabilization and coping with cancer. Active participation in cancer treatment is important for the patients. Integrative treatment services should form part of routine patient care.
CRIS-Team Scopus Importer:2021-03-19
Keywords: active participation; breast cancer; complementary and alternative medicine; coping; integrative medicine; mind–body; oncology

Addition of triple negativity of breast cancer as an indicator for germline mutations in predisposing genes increases sensitivity of clinical selection criteria - Hoyer, Juliane; Vasileiou, Georgia; Uebe, Steffen; Wunderle, Marius; Kraus, Cornelia; Fasching, Peter; Thiel, Christian; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; Reis, André (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common cancer in women. 12-15% of all tumors are triple-negative breast cancers (TNBC). So far, TNBC has been mainly associated with mutations in BRCA1. The presence of other predisposing genes seems likely since DNA damage repair is a complex process that involves several genes. Therefore we investigated if mutations in other genes are involved in cancer development and whether TNBC is an additional indicator of mutational status besides family history and age of onset. METHODS: We performed a germline panel-based screening of 10 high and low-moderate penetrance breast cancer susceptibility genes (BRCA1, BRCA2, ATM, CDH1, CHEK2, NBN, PALB2, RAD51C, RAD51D and TP53) in 229 consecutive individuals affected with TNBC unselected for age, family history or bilateral disease. Within this cohort we compared the number of mutation carriers fulfilling clinical selection criteria with the total number of carriers identified. RESULTS: Age at diagnosis ranged from 23 to 80 years with an average age of 50.2 years. In 57 women (24.9%) we detected a pathogenic mutation, with a higher frequency (29.7%) in the group manifesting cancer before 60 years. Deleterious BRCA1 mutations occurred in 14.8% of TNBC patients. These were predominantly recurrent frameshift mutations (24/34, 70.6%). Deleterious BRCA2 mutations occurred in 5.7% of patients, all but one (c.1813dupA) being unique. While no mutations were found in CDH1 and TP53, 10 mutations were detected in one of the six other predisposition genes. Remarkably, neither of the ATM, RAD51D, CHEK2 and PALB2 mutation carriers had a family history. Furthermore, patients with non-BRCA1/2 mutations were not significantly younger than mutation negative women (p = 0.3341). Most importantly, among the 57 mutation carriers, ten (17.5%) would be missed using current clinical testing criteria including five (8%) with BRCA1/2 mutations. CONCLUSIONS: In summary, our data confirm and expand previous studies of a high frequency of germline mutations in genes associated with ineffective repair of DNA damage in women with TNBCs. Neither age of onset, contralateral disease nor family history were able to discern all mutation positive individuals. Therefore, TNBC should be considered as an additional criterion for panel based genetic testing.
EVALuna2:34811

A Digital Home-Based Health Care Center for Remote Monitoring of Side Effects During Breast Cancer Therapy: Prospective, Single-Arm, Monocentric Feasibility Study - Hübner, Hanna; Wurmthaler, Lena; Goossens, Chloe; Ernst, Mathias; Mocker, Alexander; Krückel, Annika; Kallert, Maximilian; Geck, Jürgen; Limpert, Milena; Seitz, Katharina; Rübner, Matthias; Kreis, Philipp; et al. (JMIR Cancer, 2025)
Background: The introduction of oral anticancer therapies has, at least partially, shifted treatment from clinician-supervised hospital care to patient-managed home regimens. However, patients with breast cancer receiving oral cyclin-dependent kinase 4/6 inhibitor therapy still require regular hospital visits to monitor side effects. Telemonitoring has the potential to reduce hospital visits while maintaining quality care. Objective: This study aims to develop a digital home-based health care center (DHHC) for acquiring electrocardiograms (ECGs), white blood cell (WBC) counts, side effect photo documentation, and patient-reported quality of life (QoL) data. Methods: The DHHC was set up using an Apple Watch Series 6 (ECG measurements), a HemoCue WBC DIFF Analyzer (WBC counts), an iPhone SE (QoL assessments and photo documentation), a TP-Link M7350-4G Wi-Fi router, and a Raspberry Pi 4 Model B. A custom-built app stored and synchronized remotely collected data with the clinic. The feasibility and acceptance of the DHHC among patients with breast cancer undergoing cyclin-dependent kinase 4/6 inhibitor therapy were evaluated in a prospective, single-arm, monocentric study. Patients (n=76) monitored side effects—ECGs, WBC counts, photo documentation, and QoL—at 3 predefined time points: study inclusion (on-site), day 14 (remote), and day 28 (remote). After the study completion, patients completed a comprehensive questionnaire on user perception and feasibility. Adherence to scheduled visits, the success rate of the data transfer, user perception and feasibility, and the clinical relevance of remote measurements were evaluated. Results: Mean adherence to the planned remote visits was 63% on day 14 and 37% on day 28. ECG measurements were performed most frequently (day 14: 57/76, 75%; day 28: 31/76, 41%). The primary patient-reported reason for nonadherence was device malfunction. The expected versus the received data transfer per patient was as follows: ECGs: 3 versus 3.04 (SD 1.9); WBC counts: 3 versus 2.14 (SD 1.14); QoL questionnaires: 3 versus 2.5 (SD 1.14); and photo documentation: 6 versus 4.4 (SD 3.36). Among patients, 81% (55/68) found ECG measurements easy, 82% (55/67) found photo documentation easy, and 48% (33/69) found WBC measurements easy. Additionally, 61% (40/66) of patients felt comfortable with self-monitoring and 79% (54/68) were willing to integrate remote monitoring into their future cancer care. Therapy-induced decreased neutrophil count was successfully detected (P<.001; mean baseline: 4.3, SD 2.2, ×109/L; on-treatment: 1.8, SD 0.8, ×109/L). All-grade neutropenia and corrected QT interval prolongations were detected in 80% (55/68) and 2% (1/42) of patients, respectively. Conclusions: Adherence to scheduled remote visits was moderate, with nonadherence primarily attributed to device-related complications, which may have also affected the success rate of data transfer. Overall, patients considered remote monitoring useful and feasible. The prevalence of reported adverse events was comparable to existing literature, suggesting clinical potential. This initial feasibility study highlights the potential of the DHHC.
CRIS-Team Scopus Importer:2025-05-30
Keywords: breast cancer; CDK4/6 inhibitor; cyclin-dependent kinase 4/6 inhibitor; digital medicine; mobile phone; remote monitoring; telehealth

ADSCs and adipocytes are the main producers in the autotaxin-lysophosphatidic acid axis of breast cancer and healthy mammary tissue in vitro - Schmid, Rafael; Wolf, Katharina; Robering, Jan Willem; Strauss, Selina; Strissel, Pamela; Strick, Reiner; Rübner, Matthias; Fasching, Peter; Horch, Raymund E.; Kremer, Andreas; Boos, Anja; Weigand, Annika (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common malignancy in women affecting one out of eight females throughout their lives. Autotaxin (ATX) is upregulated in breast cancer which results in increased lysophosphatidic acid (LPA) formation within the tumor. This study's aim was to identify the role of different mammary cell populations within the ATX-LPA axis. METHODS: Epithelial-cell-adhesion-molecule-positive (EpCAM) and -negative cells from breast tumors, adipose-derived stem cells (ADSCs) of tumor-adjacent and tumor-distant mammary fat were isolated and compared to healthy ADSCs, mammary epithelial cells (HMECs), and mesenchymal cells (MES) of healthy mammary tissue (n = 4 each) and further to well-established breast (cancer) cell lines. RESULTS: mRNA expression analyses revealed that ADSCs and MES largely expressed LPA receptor 1 (LPAR1) while epithelial cells mainly expressed LPAR6. LPA 18:1 activated all the cell populations and cell lines by rise in cytosolic free calcium concentrations. MES and ADSCs expressed ATX whereas epithelial cells did not. ADSCs revealed the highest expression in ATX with a significant decline after adipogenic differentiation in healthy ADSCs, whereas ATX expression increased in ADSCs from tumor patients. Breast (cancer) cell lines did not express ATX. Transmigration of MES was stimulated by LPA whereas an inhibitory effect was observed in epithelial cells with no differences between tumors and healthy cells. Triple-negative breast cancer (TNBC) cell lines were also stimulated and the transmigration partly inhibited using the LPA receptor antagonist Ki16425. CONCLUSIONS: We here show that each mammary cell population plays a different role in the ATX-LPA axis with ADSCs and adipocytes being the main source of ATX in tumor patients in our experimental setting. Inhibitors of this axis may therefore present a valuable target for pharmacological therapies.
EVALuna2:35125

Adult body mass index and risk of ovarian cancer by subtype: a Mendelian randomization study - Dixon, Suzanne C.; Nagle, Christina M.; Thrift, Aaron P.; Pharoah, Paul D. P.; Pearce, Celeste Leigh; Zheng, Wei; Painter, Jodie N.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; et al. (International Journal of Epidemiology, 2016)
BACKGROUND: Observational studies have reported a positive association between body mass index (BMI) and ovarian cancer risk. However, questions remain as to whether this represents a causal effect, or holds for all histological subtypes. The lack of association observed for serous cancers may, for instance, be due to disease-associated weight loss. Mendelian randomization (MR) uses genetic markers as proxies for risk factors to overcome limitations of observational studies. We used MR to elucidate the relationship between BMI and ovarian cancer, hypothesizing that genetically predicted BMI would be associated with increased risk of non-high grade serous ovarian cancers (non-HGSC) but not HGSC. METHODS: We pooled data from 39 studies (14 047 cases, 23 003 controls) in the Ovarian Cancer Association Consortium. We constructed a weighted genetic risk score (GRS, partial F-statistic = 172), summing alleles at 87 single nucleotide polymorphisms previously associated with BMI, weighting by their published strength of association with BMI. Applying two-stage predictor-substitution MR, we used logistic regression to estimate study-specific odds ratios (OR) and 95% confidence intervals (CI) for the association between genetically predicted BMI and risk, and pooled these using random-effects meta-analysis. RESULTS: Higher genetically predicted BMI was associated with increased risk of non-HGSC (pooled OR = 1.29, 95% CI 1.03-1.61 per 5 units BMI) but not HGSC (pooled OR = 1.06, 95% CI 0.88-1.27). Secondary analyses stratified by behaviour/subtype suggested that, consistent with observational data, the association was strongest for low-grade/borderline serous cancers (OR = 1.93, 95% CI 1.33-2.81). CONCLUSIONS: Our data suggest that higher BMI increases risk of non-HGSC, but not the more common and aggressive HGSC subtype, confirming the observational evidence.
EVALuna2:32972

Adult height is associated with increased risk of ovarian cancer: a Mendelian randomisation study - Dixon-Suen, Suzanne C.; Nagle, Christina M.; Thrift, Aaron P.; Pharoah, Paul D. P.; Ewing, Ailith; Pearce, Celeste Leigh; Zheng, Wei; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; et al. (British Journal of Cancer, 2018)
BACKGROUND: Observational studies suggest greater height is associated with increased ovarian cancer risk, but cannot exclude bias and/or confounding as explanations for this. Mendelian randomisation (MR) can provide evidence which may be less prone to bias. METHODS: We pooled data from 39 Ovarian Cancer Association Consortium studies (16,395 cases; 23,003 controls). We applied two-stage predictor-substitution MR, using a weighted genetic risk score combining 609 single-nucleotide polymorphisms. Study-specific odds ratios (OR) and 95% confidence intervals (CI) for the association between genetically predicted height and risk were pooled using random-effects meta-analysis. RESULTS: Greater genetically predicted height was associated with increased ovarian cancer risk overall (pooled-OR (pOR) = 1.06; 95% CI: 1.01-1.11 per 5 cm increase in height), and separately for invasive (pOR = 1.06; 95% CI: 1.01-1.11) and borderline (pOR = 1.15; 95% CI: 1.02-1.29) tumours. CONCLUSIONS: Women with a genetic propensity to being taller have increased risk of ovarian cancer. This suggests genes influencing height are involved in pathways promoting ovarian carcinogenesis.
EVALuna2:209946

Advanced Breast Cancer: AGO Recommendations 2022 Focus on ABC6 Consensus Fortgeschrittenes Mammakarzinom ABC6-Konsens im Fokus der AGO-Empfehlungen 2022 - Untch, Michael; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Jackisch, Christian; Lüftner, Diana; Müller, Volkmar; Schumacher-Wulf, Eva; Würstlein, Rachel; Thomssen, Christoph (Geburtshilfe und Frauenheilkunde, 2022)
Over the past few years, there have been many developments in the treatment of advanced breast cancer; these have been incorporated into national and international treatment guidelines, resulting in an improved prognosis for these patients. The 6th International Consensus Conference for Advanced Breast Cancer (ABC6) was held in November 2021. The aim is to standardize the treatment of advanced breast cancer based on a high level of evidence, and to make new treatment options accessible to all patients. In this article we discuss the ABC6 consensus in the context of German treatment guidelines, and compare it with clinical practice in Germany. The authors refer to the current recommendations of the Breast Cancer Working Group for Gynecological Oncology (AGO Mamma) published in March 2022. The AGO Breast Cancer Guidelines are updated annually. Since discrepancies between national and international guidelines can occur due to country-specific regulations, this is a useful comparison to make. The German authors refer to the voting results of the ABC6 panelists from 6 November 2021.
CRIS-Team Scopus Importer:2024-12-16
Keywords: advanced breast cancer; brain metastases; oligometastasis; supportive treatment; systemic therapy; treatment sequencing

Age- and Tumor Subtype-Specific Breast Cancer Risk Estimates for CHEK2*1100delC Carriers - Schmidt, Marjanka K.; Hogervorst, Frans; Van Hien, Richard; Cornelissen, Sten; Broeks, Annegien; Adank, Muriel A.; Meijers, Hanne; Waisfisz, Quinten; Hollestelle, Antoinette; Schutte, Mieke; Van Den Ouweland, Ans; Hooning, Maartje; et al. (Journal of Clinical Oncology, 2016)
PURPOSE: CHEK2*1100delC is a well-established breast cancer risk variant that is most prevalent in European populations; however, there are limited data on risk of breast cancer by age and tumor subtype, which limits its usefulness in breast cancer risk prediction. We aimed to generate tumor subtype- and age-specific risk estimates by using data from the Breast Cancer Association Consortium, including 44,777 patients with breast cancer and 42,997 controls from 33 studies genotyped for CHEK2*1100delC. PATIENTS AND METHODS: CHEK2*1100delC genotyping was mostly done by a custom Taqman assay. Breast cancer odds ratios (ORs) for CHEK2*1100delC carriers versus noncarriers were estimated by using logistic regression and adjusted for study (categorical) and age. Main analyses included patients with invasive breast cancer from population- and hospital-based studies. RESULTS: Proportions of heterozygous CHEK2*1100delC carriers in controls, in patients with breast cancer from population- and hospital-based studies, and in patients with breast cancer from familial- and clinical genetics center-based studies were 0.5%, 1.3%, and 3.0%, respectively. The estimated OR for invasive breast cancer was 2.26 (95%CI, 1.90 to 2.69; P = 2.3 × 10(-20)). The OR was higher for estrogen receptor (ER)-positive disease (2.55 [95%CI, 2.10 to 3.10; P = 4.9 × 10(-21)]) than it was for ER-negative disease (1.32 [95%CI, 0.93 to 1.88; P = .12]; P interaction = 9.9 × 10(-4)). The OR significantly declined with attained age for breast cancer overall (P = .001) and for ER-positive tumors (P = .001). Estimated cumulative risks for development of ER-positive and ER-negative tumors by age 80 in CHEK2*1100delC carriers were 20% and 3%, respectively, compared with 9% and 2%, respectively, in the general population of the United Kingdom. CONCLUSION: These CHEK2*1100delC breast cancer risk estimates provide a basis for incorporating CHEK2*1100delC into breast cancer risk prediction models and into guidelines for intensified screening and follow-up.
EVALuna2:33070

A genome-wide gene-environment interaction study of breast cancer risk for women of European ancestry - Middha, Pooja; Wang, Xiaoliang; Behrens, Sabine; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; et al. (Breast Cancer Research, 2023)
BACKGROUND: Genome-wide studies of gene-environment interactions (G×E) may identify variants associated with disease risk in conjunction with lifestyle/environmental exposures. We conducted a genome-wide G×E analysis of 7.6 million common variants and seven lifestyle/environmental risk factors for breast cancer risk overall and for estrogen receptor positive (ER +) breast cancer. METHODS: Analyses were conducted using 72,285 breast cancer cases and 80,354 controls of European ancestry from the Breast Cancer Association Consortium. Gene-environment interactions were evaluated using standard unconditional logistic regression models and likelihood ratio tests for breast cancer risk overall and for ER + breast cancer. Bayesian False Discovery Probability was employed to assess the noteworthiness of each SNP-risk factor pairs. RESULTS: Assuming a 1 × 10-5 prior probability of a true association for each SNP-risk factor pairs and a Bayesian False Discovery Probability < 15%, we identified two independent SNP-risk factor pairs: rs80018847(9p13)-LINGO2 and adult height in association with overall breast cancer risk (ORint = 0.94, 95% CI 0.92-0.96), and rs4770552(13q12)-SPATA13 and age at menarche for ER + breast cancer risk (ORint = 0.91, 95% CI 0.88-0.94). CONCLUSIONS: Overall, the contribution of G×E interactions to the heritability of breast cancer is very small. At the population level, multiplicative G×E interactions do not make an important contribution to risk prediction in breast cancer.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Breast cancer; European ancestry; Gene-environment interactions; Genetic epidemiology

Aggregation tests identify new gene associations with breast cancer in populations with diverse ancestry - Mueller, Stefanie H.; Lai, Alvina G.; Valkovskaya, Maria; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Abu-Ful, Zomoruda; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Genome Medicine, 2023)
Background: Low-frequency variants play an important role in breast cancer (BC) susceptibility. Gene-based methods can increase power by combining multiple variants in the same gene and help identify target genes. Methods: We evaluated the potential of gene-based aggregation in the Breast Cancer Association Consortium cohorts including 83,471 cases and 59,199 controls. Low-frequency variants were aggregated for individual genes’ coding and regulatory regions. Association results in European ancestry samples were compared to single-marker association results in the same cohort. Gene-based associations were also combined in meta-analysis across individuals with European, Asian, African, and Latin American and Hispanic ancestry. Results: In European ancestry samples, 14 genes were significantly associated (q < 0.05) with BC. Of those, two genes, FMNL3 (P = 6.11 × 10−6) and AC058822.1 (P = 1.47 × 10−4), represent new associations. High FMNL3 expression has previously been linked to poor prognosis in several other cancers. Meta-analysis of samples with diverse ancestry discovered further associations including established candidate genes ESR1 and CBLB. Furthermore, literature review and database query found further support for a biologically plausible link with cancer for genes CBLB, FMNL3, FGFR2, LSP1, MAP3K1, and SRGAP2C. Conclusions: Using extended gene-based aggregation tests including coding and regulatory variation, we report identification of plausible target genes for previously identified single-marker associations with BC as well as the discovery of novel genes implicated in BC development. Including multi ancestral cohorts in this study enabled the identification of otherwise missed disease associations as ESR1 (P = 1.31 × 10−5), demonstrating the importance of diversifying study cohorts.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Breast cancer susceptibility; Diverse ancestry; Gene regulation; Genome-wide association study; Rare variants

AGO Algorithms for the Treatment of Breast Cancer: Update 2021 AGO-Algorithmen zur Behandlung von Brustkrebs: Update 2021 - Schneeweiss, Andreas; Fasching, Peter; Fehm, Tanja; Gerber, Bernd; Jackisch, Christian; Loibl, Sibylle; Schmidt, Marcus; Stickeler, Elmar; Wockel, Achim; Janni, Wolfgang; Mueller, Volkmar (Geburtshilfe und Frauenheilkunde, 2021)
Therapy options shown in the algorithms are based on the current AGO recommendations, but cannot represent all evidence-based treatment options, since prior therapies, performance status, comorbidities, patient preference, etc. must be taken into account for the actual treatment choice. In individual cases, other evidence-based treatment options may also be appropriate and justified. Regardless of approval status, the algorithms only take into account drugs that were available in Germany at the time the algorithm was last updated. Here we present the 2021 update of AGO treatment algorithms for early and metastatic breast cancer, which are intended to intensify structured treatment decision by providing reproducible and evidence-based treatment paths and may be helpful for a broad treatment landscape.
CRIS-Team Scopus Importer:2021-11-05
Keywords: breast cancer guidelines; evidence-based treatment; therapy algorithms

AGO Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2019 - Ditsch, Nina; Untch, Michael; Thill, Marc; Müller, Volkmar; Janni, Wolfgang; Albert, Ute Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Diel, Ingo; Fasching, Peter; et al. (Breast Care, 2019)
CRIS-Team Scopus Importer:2019-08-23
Keywords: Early breast cancer; Local therapy; Systemic therapy; Treatment recommendations

AGO Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2021 - Ditsch, Nina; Kolberg-Liedtke, Cornelia; Friedrich, Michael; Jackisch, Christian; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva M.; Fasching, Peter; et al. (Breast Care, 2021)
CRIS-Team Scopus Importer:2021-06-18

AGO Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2022. - Ditsch, Nina; Woecke, Achim; Untch, Michael; Jackisch, Christian; Albert, Ute-Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens-Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva Maria; Fasching, Peter; et al. (Breast Care, 2022)
INTRODUCTION: The AGO (Arbeitsgemeinschaft Gynäkologische Onkologie, German Gynecological Oncology Group) Task Force on Diagnosis and Treatment of Breast Cancer as an interdisciplinary team consists of specialists from gynecological oncology, pathology, diagnostic radiology, medical oncology, and radiation oncology with a special focus on breast cancer. METHODS: The updated evidence-based treatment recommendation 2022 for early breast cancer (EBC) and metastatic breast cancer of the AGO Task Force has been released. RESULTS AND CONCLUSION: This paper captures the update of EBC.
EVALuna2:513859

AGO Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2025 - Park-Simon, Tjoung Won; Müller, Volkmar; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bartsch, Rupert; Bauerfeind, Ingo; Bjelic-Radisic, Vesna; Blohmer, Jens Uwe; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva M.; et al. (Breast Care, 2025)
The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2025 update of the evidencebased recommendations for the diagnosis and treatment of patients with early breast cancer.
CRIS-Team Scopus Importer:2025-05-09
Keywords: (Post)(neo)adjuvant; Breast surgery; Communication; Early breast cancer; Radiotherapy; Reconstruction

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2019 - Thill, Marc; Jackisch, Christian; Janni, Wolfgang; Müller, Volkmar; Albert, Ute Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Diel, Ingo; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2019)
Every year the Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO), a group of gynecological oncologists specialized in breast cancer and interdisciplinary members specialized in pathology, radiologic diagnostics, medical oncology, and radiation oncology, prepares and updates evidence-based recommendations for the diagnosis and treatment of patients with early and metastatic breast cancer. Every update is performed according to a documented rule-fixed algorithm, by thoroughly reviewing and scoring the recent publications for their scientific validity and clinical relevance. This current publication presents the 2019 update on the recommendations for metastatic breast cancer.
CRIS-Team Scopus Importer:2019-08-23
Keywords: AGO grades of recommendation; Bone health; Early and metastatic breast cancer; Locoregional recurrence; Oxford level of evidence; Therapy

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2020. - Ditsch, Nina; Untch, Michael; Kolberg-Liedtke, Cornelia; Jackisch, Christian; Krug, David; Friedrich, Michael; Janni, Wolfgang; Mueller, Volkmar; Albert, Ute-Susann; Banys-Paluchowski, Malgorzata; Bauerfeind, Ingo; Blohmer, Jens-Uwe; et al. (Breast Care, 2020)
EVALuna2:280559

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2021 - Thill, Marc; Friedrich, Michael; Kolberg-Liedtke, Cornelia; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva M.; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2021)
CRIS-Team Scopus Importer:2021-06-18

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2022. - Thill, Marc; Lueftner, Diana; Kolberg-Liedtke, Cornelia; Albert, Ute-Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens-Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva Maria; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2022)
The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2022 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer.
EVALuna2:514465

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2023. - Thill, Marc; Kolberg-Liedtke, Cornelia; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens Uwe; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva Maria; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2023)
The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2023 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer (mBC).
EVALuna2:539548

AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2025 - Thill, Marc; Janni, Wolfgang; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bartsch, Rupert; Bauerfeind, Ingo; Bjelic-Radisic, Vesna; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva Maria; et al. (Breast Care, 2025)
The Breast Committee of the Arbeitsgemeinschaft Gyn kologische Onkologie (AGO; German Gynecological Oncology Group) presents the 2025 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer (mBC).
CRIS-Team Scopus Importer:2025-05-16
Keywords: AGO; Diagnosis; Metastatic breast cancer; Recommendations; Treatment

AGO Recommendations for the Surgical Therapy of Breast Cancer: Update 2022 - Banys-Paluchowski, Maggie; Thill, Marc; Kuhn, Thorsten; Ditsch, Nina; Heil, Jorg; Woeckel, Achim; Fallenberg, Eva; Friedrich, Michael; Kuemmel, Sherko; Mueller, Volkmar; Janni, Wolfgang; Albert, Ute-Susann; et al. (Geburtshilfe und Frauenheilkunde, 2022)
The recommendations of the AGO Breast Committee on the surgical therapy of breast cancer were last updated in March 2022 (www.ago-online.de). Since surgical therapy is one of several partial steps in the treatment of breast cancer, extensive diagnostic and oncological expertise of a breast surgeon and good interdisciplinary cooperation with diagnostic radiologists is of great importance. The most important changes concern localization techniques, resection margins, axillary management in the neoadjuvant setting and the evaluation of the meshes in reconstructive surgery. Based on meta-analyses of randomized studies, the level of recommendation of an intraoperative breast ultrasound for the localization of non-palpable lesions was elevated to ++. Thus, the technique is considered to be equivalent to wire localization, provided that it is a lesion which can be well represented by sonography, the surgeon has extensive experience in breast ultrasound and has access to a suitable ultrasound device during the operation. In invasive breast cancer, the aim is to reach negative resection margins (no tumor on ink), regardless of whether an extensive intraductal component is present or not. Oncoplastic operations can also replace a mastectomy in selected cases due to the large number of existing techniques, and are equivalent to segmental resection in terms of oncological safety at comparable rates of complications. Sentinel node excision is recommended for patients with cN0 status receiving neoadjuvant chemotherapy after completion of chemotherapy. Minimally invasive biopsy is recommended for initially suspect lymph nodes. After neoadjuvant chemotherapy, patients with initially 1-3 suspicious lymph nodes and a good response (ycN0) can receive the targeted axillary dissection and the axillary dissection as equivalent options.
CRIS-Team Scopus Importer:2022-11-04
Keywords: breast cancer; breast surgery; guidelines; neoadjuvant chemotherapy; surgical therapy

AGO Recommendations for the Surgical Therapy of the Axilla After Neoadjuvant Chemotherapy: 2021 Update - Friedrich, Michael; Kühn, Thorsten; Janni, Wolfgang; Müller, Volkmar; Banys-Pachulowski, Maggie; Kolberg-Liedtke, Cornelia; Jackisch, Christian; Krug, David; Albert, Ute Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; et al. (Geburtshilfe und Frauenheilkunde, 2021)
For many decades, the standard procedure to treat breast cancer included complete dissection of the axillary lymph nodes. The aim was to determine histological node status, which was then used as the basis for adjuvant therapy, and to ensure locoregional tumour control. In addition to the debate on how to optimise the therapeutic strategies of systemic treatment and radiotherapy, the current discussion focuses on improving surgical procedures to treat breast cancer. As neoadjuvant chemotherapy is becoming increasingly important, the surgical procedures used to treat breast cancer, whether they are breast surgery or axillary dissection, are changing. Based on the currently available data, carrying out SLNE prior to neoadjuvant chemotherapy is not recommended. In contrast, surgical axillary management after neoadjuvant chemotherapy is considered the procedure of choice for axillary staging and can range from SLNE to TAD and ALND. To reduce the rate of false negatives during surgical staging of the axilla in pN+ CNBstage before NACT and ycN0 after NACT, targeted axillary dissection (TAD), the removal of > 2 SLNs (SLNE, no untargeted axillary sampling), immunohistochemistry to detect isolated tumour cells and micro-metastases, and marking positive lymph nodes before NACT should be the standard approach. This most recent update on surgical axillary management describes the significance of isolated tumour cells and micro-metastasis after neoadjuvant chemotherapy and the clinical consequences of low volume residual disease diagnosed using SLNE and TAD and provides an overview of this year's AGO recommendations for surgical management of the axilla during primary surgery and in relation to neoadjuvant chemotherapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: breast cancer; neoadjuvant chemotherapy; sentinel LNE; targeted axillary dissection

AGR3 in breast cancer: prognostic impact and suitable serum-based biomarker for early cancer detection - Garczyk, Stefan; Von Stillfried, Saskia; Antonopoulos, Wiebke; Hartmann, Arndt; Schrauder, Michael G.; Fasching, Peter; Anzeneder, Tobias; Tannapfel, Andrea; Ergoenenc, Yavuz; Knuechel, Ruth; Rose, Michael; Dahl, Edgar (PLoS ONE, 2015)
Blood-based early detection of breast cancer has recently gained novel momentum, as liquid biopsy diagnostics is a fast emerging field. In this study, we aimed to identify secreted proteins which are up-regulated both in tumour tissue and serum samples of breast cancer patients compared to normal tissue and sera. Based on two independent tissue cohorts (n = 75 and n = 229) and one serum cohort (n = 80) of human breast cancer and healthy serum samples, we characterised AGR3 as a novel potential biomarker both for breast cancer prognosis and early breast cancer detection from blood. AGR3 expression in breast tumours is significantly associated with oestrogen receptor ? (P<0.001) and lower tumour grade (P<0.01). Interestingly, AGR3 protein expression correlates with unfavourable outcome in low (G1) and intermediate (G2) grade breast tumours (multivariate hazard ratio: 2.186, 95% CI: 1.008-4.740, P<0.05) indicating an independent prognostic impact. In sera analysed by ELISA technique, AGR3 protein concentration was significantly (P<0.001) elevated in samples from breast cancer patients (n = 40, mainly low stage tumours) compared to healthy controls (n = 40). To develop a suitable biomarker panel for early breast cancer detection, we measured AGR2 protein in human serum samples in parallel. The combined AGR3/AGR2 biomarker panel achieved a sensitivity of 64.5% and a specificity of 89.5% as shown by receiver operating characteristic (ROC) curve statistics. Thus our data clearly show the potential usability of AGR3 and AGR2 as biomarkers for blood-based early detection of human breast cancer.
EVALuna2:6803

A hybrid method towards automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2014)
In clinical work-up of breast cancer, nipple position is an important marker to locate lesions. Moreover, it serves as an effective landmark to register a 3D automated breast ultrasound (ABUS) images to other imaging modalities, e.g., X-ray mammography, tomosynthesis or magnetic resonance imaging (MRI). However, the presence of speckle noises caused by the interference waves and variant imaging directions poses challenges to automatically identify nipple positions. In this work, a hybrid fully automatic method to detect nipple positions in ABUS images is presented. The method extends the multi-scale Laplacian-based method that we proposed previously, by integrating a specially designed Hessian-based method to locate the shadow area beneath the nipple and areola. Subsequently, the likelihood maps of nipple positions generated by both methods are combined to build a joint-likelihood map, where the final nipple position is extracted. To validate the efficiency and robustness, the extended hybrid method was tested on 926 ABUS images, resulting in a distance error of 7.08±10.96 mm (mean±standard deviation).
EVALuna2:14367

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Aktuelle Strategien zur Systemtherapie des frühen Mammakarzinoms von der 18. Internationalen St.-Gallen-Konsensuskonferenz - Lüftner, Diana; Banys-Paluchowski, Maggie; Ditsch, Nina; Fasching, Peter; Jackisch, Christian; Janni, Wolfgang; Krug, David; Untch, Michael; Harbeck, Nadia; Huober, Jens (Die Onkologie, 2023)
Background: For more than 30 years, The St. Gallen (SG) International Consensus Conference on the treatment of patients with primary breast cancer (SGBCC) has been taking place regularly. As the St. Gallen consensus panel consists of experts from different countries and disciplines, the votes represent an international cross-section of opinions Rationale: From the German perspective it is considered useful to discuss the results of the votes with respect to the clinical routine in Germany Basis: The discussion is related to the German guidelines of the ‚Arbeitsgemeinschaft Gynäkologische Onkologie‘ (AGO Organkommission Mamma, Version 2023.1D) which is updated every year, most recently in March 2023. Results: This year’s 18th SGBCC focused on practice-oriented issues. The individual disease situation and benefit-risk assessment were mainly based on patient cases and put in the context of current data. Here, we discuss the most important voting results on systemic therapy with a focus on endocrine therapy plus CDK4/6 inhibition, immunotherapy and PARP inhibition together with germline BRCA testing.
CRIS-Team Scopus Importer:2023-11-17
Keywords: (neo)adjuvant systemic treatment; Early breast cancer; Endocrine-based therapy; Immunotherapy; St. Gallen Consensus 2023

A large-scale assessment of two-way SNP interactions in breast cancer susceptibility using 46 450 cases and 42 461 controls from the breast cancer association consortium - Milne, Roger L.; Herranz, Jesus; Michailidou, Kyriaki; Dennis, Joe; Tyrer, Jonathan P.; Zamora, M. Pilar; Arias-Perez, Jose Ignacio; Gonzalez-Neira, Anna; Pita, Guillermo; Alonso, M. Rosario; Wang, Qin; Bolla, Manjeet K.; et al. (Human Molecular Genetics, 2014)
Part of the substantial unexplained familial aggregation of breast cancer may be due to interactions between common variants, but few studies have had adequate statistical power to detect interactions of realistic magnitude. We aimed to assess all two-way interactions in breast cancer susceptibility between 70 917 single nucleotide polymorphisms (SNPs) selected primarily based on prior evidence of a marginal effect. Thirty-eight international studies contributed data for 46 450 breast cancer cases and 42 461 controls of European origin as part of a multi-consortium project (COGS). First, SNPs were preselected based on evidence (P < 0.01) of a per-allele main effect, and all two-way combinations of those were evaluated by a per-allele (1 d.f.) test for interaction using logistic regression. Second, all 2.5 billion possible two-SNP combinations were evaluated using Boolean operation-based screening and testing, and SNP pairs with the strongest evidence of interaction (P < 10(-4)) were selected for more careful assessment by logistic regression. Under the first approach, 3277 SNPs were preselected, but an evaluation of all possible two-SNP combinations (1 d.f.) identified no interactions at P < 10(-8). Results from the second analytic approach were consistent with those from the first (P > 10(-10)). In summary, we observed little evidence of two-way SNP interactions in breast cancer susceptibility, despite the large number of SNPs with potential marginal effects considered and the very large sample size. This finding may have important implications for risk prediction, simplifying the modelling required. Further comprehensive, large-scale genome-wide interaction studies may identify novel interacting loci if the inherent logistic and computational challenges can be overcome.
EVALuna2:9207

A likelihood ratio approach for utilizing case-control data in the clinical classification of rare sequence variants: Application to BRCA1 and BRCA2 - Zanti, Maria; O'Mahony, Denise G.; Parsons, Michael T.; Li, Hongyan; Dennis, Joe; Aittomäkkiki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Aronson, Kristan J.; Augustinsson, Annelie; Becher, Heiko; Bojesen, Stig E.; et al. (Human Mutation, 2023)
A large number of variants identified through clinical genetic testing in disease susceptibility genes are of uncertain significance (VUS). Following the recommendations of the American College of Medical Genetics and Genomics (ACMG) and Association for Molecular Pathology (AMP), the frequency in case-control datasets (PS4 criterion) can inform their interpretation. We present a novel case-control likelihood ratio-based method that incorporates gene-specific age-related penetrance. We demonstrate the utility of this method in the analysis of simulated and real datasets. In the analysis of simulated data, the likelihood ratio method was more powerful compared to other methods. Likelihood ratios were calculated for a case-control dataset of BRCA1 and BRCA2 variants from the Breast Cancer Association Consortium (BCAC) and compared with logistic regression results. A larger number of variants reached evidence in favor of pathogenicity, and a substantial number of variants had evidence against pathogenicity findings that would not have been reached using other case-control analysis methods. Our novel method provides greater power to classify rare variants compared with classical case-control methods. As an initiative from the ENIGMA Analytical Working Group, we provide user-friendly scripts and preformatted Excel calculators for implementation of the method for rare variants in BRCA1, BRCA2, and other high-risk genes with known penetrance.
CRIS-Team Scopus Importer:2023-11-24

A multicenter, randomized, double-blind, phase II study to evaluate the tolerability of an induction dose escalation of everolimus in patients with metastatic breast cancer (mBC) (DESIREE) - Loibl, S.; Schmidt, M.; Luebbe, K.; Decker, T.; Thill, M.; Bauer, L.; Mueller, V.; Link, T.; Furlanetto, J.; Kuemmel, S.; Mundhenke, Christoph; Hoffmann, O.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

A multicentre, randomised, double-blind, phase II study to evaluate the tolerability of an induction dose escalation of everolimus in patients with metastatic breast cancer (DESIREE) - Schmidt, M.; Lübbe, K.; Decker, T.; Thill, M.; Bauer, L.; Müller, V.; Link, T.; Furlanetto, J.; Reinisch, M.; Mundhenke, Christoph; Hoffmann, O.; Zahn, M. O.; et al. (ESMO Open, 2022)
Background: Stomatitis is one of the main reasons to discontinue everolimus in patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) metastatic breast cancer (mBC). To decrease stomatitis and subsequently early treatment discontinuations or dose reductions, the DESIREE trial investigated the use of a stepwise dose-escalation schedule of everolimus (EVE esc). Patients and methods: DESIREE is a phase II, multicentre, randomised, double-blind, placebo-controlled trial in patients with HR+/HER2– mBC and progression/relapse after nonsteroidal aromatase inhibitor treatment. Patients were randomised to EVE esc (2.5 mg/day, week 1; 5 mg/day, week 2; 7.5 mg/day, week 3; 10 mg/day, weeks 4-24) or everolimus 10 mg/day (EVE 10mg) for 24 weeks plus exemestane. The primary endpoint was the incidence of stomatitis episodes grade ≥2 within 12 weeks of treatment. The secondary endpoints included toxicity, relative total dose intensity (RTDI) and quality of life (QoL). Results: A total of 160 patients were randomised and 156 started treatment (EVE esc: 80; EVE 10mg: 76). The median age of patients was 64 years (range 33-85), 56.3% patients in the EVE esc arm versus 42.1% in the EVE 10mg arm had liver metastasis (P = 0.081) and 62.5% versus 51.3% received over one metastatic therapy line (P = 0.196). Within 12 weeks, the incidence of stomatitis episodes grade ≥2 was significantly lower in the EVE esc arm compared with the EVE 10mg arm (28.8% versus 46.1%; odds ratio 0.47, 95% confidence interval 0.24-0.92; P = 0.026). Toxicity was in line with the known safety profile without new safety concerns. The median RTDI was 91.1% in the EVE esc arm versus 80.0% in the EVE 10mg arm (P = 0.329). Discontinuation rate in the first 3 weeks was 6.3% versus 15.8%, respectively (P = 0.073). QoL was comparable between the two treatment arms. Conclusions: A dose-escalation schema of everolimus over 3 weeks can be successfully used to reduce the incidence of high-grade stomatitis in the first 12 weeks of treatment in patients with HR+/HER2– mBC. Trial registration: ClinicalTrials.gov NCT02387099; https://clinicaltrials.gov/ct2/show/NCT02387099
CRIS-Team Scopus Importer:2022-11-25
Keywords: everolimus; exemestane; metastatic breast cancer; stomatitis

Analyses of germline variants associated with ovarian cancer survival identify functional candidates at the 1q22 and 19p12 outcome loci - Glubb, Dylan M.; Johnatty, Sharon E.; Quinn, Michael C. J.; O'Mara, Tracy A.; Tyrer, Jonathan P.; Gao, Bo; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vergote, Ignace; Edwards, Digna R. Velez; Beeghly-Fadiel, Alicia; et al. (Oncotarget, 2017)
We previously identified associations with ovarian cancer outcome at five genetic loci. To identify putatively causal genetic variants and target genes, we prioritized two ovarian outcome loci (1q22 and 19p12) for further study. Bioinformatic and functional genetic analyses indicated that MEF2D and ZNF100 are targets of candidate outcome variants at 1q22 and 19p12, respectively. At 19p12, the chromatin interaction of a putative regulatory element with the ZNF100 promoter region correlated with candidate outcome variants. At 1q22, putative regulatory elements enhanced MEF2D promoter activity and haplotypes containing candidate outcome variants modulated these effects. In a public dataset, MEF2D and ZNF100 expression were both associated with ovarian cancer progression-free or overall survival time. In an extended set of 6,162 epithelial ovarian cancer patients, we found that functional candidates at the 1q22 and 19p12 loci, as well as other regional variants, were nominally associated with patient outcome; however, no associations reached our threshold for statistical significance (p<1×10-5). Larger patient numbers will be needed to convincingly identify any true associations at these loci.
EVALuna2:36127

Analysis of GDF15 and IGFBP7 in Hyperemesis Gravidarum Support Causality - Fejzo, Marlena S.; Fasching, Peter; Schneider, Michael; Schwitulla, Judith; Beckmann, Matthias; Schwenke, Eva; Macgibbon, Kimber W.; Mullin, Patrick M. (Geburtshilfe und Frauenheilkunde, 2019)
Objective Hyperemesis gravidarum, severe nausea and vomiting in pregnancy, occurs in up to 2% of pregnancies and leads to significant weight loss, dehydration, electrolyte imbalance, and ketonuria. It is associated with both maternal and fetal morbidity. Familial aggregation studies and twin studies suggest a genetic component. In a recent GWAS, we showed that placentation, appetite, and cachexia genes GDF15 and IGFBP7 are linked to hyperemesis gravidarum (HG). The purpose of this study is to determine whether GDF15 and IGFBP7 are upregulated in HG patients. Methods We compared serum levels of GDF15 and IGFBP7 at 12 and 24 weeks' gestation in women hospitalized for HG, and two control groups, women with nausea and vomiting of pregnancy (NVP), and women with no NVP. Results We show GDF15 and IGFBP7 serum levels are significantly increased in women with HG at 12 weeks' gestation. Serum levels of hCG are not significantly different between cases and controls. At 24 weeks gestation, when symptoms have largely resolved, there is no difference in GDF15 and IGFBP7 serum levels between cases and controls. Conclusion This study supports GDF15 and IGFBP7 in the pathogenesis of HG and may be useful for prediction and diagnosis. The GDF15-GFRAL brainstem-activated pathway was recently identified and therapies to treat conditions of abnormal appetite are under intense investigation. Based on our findings, HG should be included.
CRIS-Team Scopus Importer:2019-05-02
Keywords: GDF15; GFRAL; hyperemesis gravidarum; IGFBP7; nausea and vomiting of pregnancy

Analysis of motives and patient satisfaction in oncological second opinions provided by a certified university breast and gynecological cancer center - Löhberg, Christian; Meyer, Julia; Häberle, Lothar; Hack, Carolin; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; Krebs, Jessica; et al. (Archives of Gynecology and Obstetrics, 2020)
Purpose: Second opinions in oncology are becoming increasingly important in an era of more complex treatments and a growing demand for information by patients. Therefore, we analyzed their effects and influencing factors like patients’ motives, subjective extent of information and satisfaction with communications. Methods: This prospective study evaluated second opinions for patients with breast cancer or gynecological malignancy. The patients received a questionnaire before and two months after, which inquired expectations, reasons, and satisfaction with the second opinion and the attending physicians. Results: A total of 164 patients were included and the majority had breast cancer (75.0%). Receiving the second opinion made 89.7% feel better informed, their need for information decreased (from 75.3% to 39.2%, P < 0.0001), and satisfaction with doctor–patient communications increased (from 61.9 to 91.8%, P = 0.0002). There were various reasons for requesting a second opinion, e.g., the extremely stressful situation of a cancer diagnosis, hope for change in the treatment recommendation or dissatisfaction with the initial physicians. Conclusions: Second opinions can lead to significantly greater patient satisfaction, meeting the need for information and leading to better management of patients in the extremely stressful situation of a cancer diagnosis. Doctor–patient communications play a key role.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Breast cancer; Doctor–patient communication; Gynecological malignancy; Oncology center; Patient satisfaction; Second opinion

Analysis of Oncological Second Opinions in a Certified University Breast and Gynecological Cancer Center in Relation to Complementary and Alternative Medicine - Hack, Carolin; Wasner, Sonja; Meyer, Julia; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; Beckmann, Matthias; et al. (Complementary Medicine Research, 2020)
Introduction: Oncological second opinions are becoming increasingly important given more complex treatment strategies, simultaneously more patients use complementary and alternative medicine (CAM), and many comprehensive cancer centers initiate integrative medicine programs. The present study focuses on analyzing the effects of a second opinion in relation to attitudes toward CAM. Methods: In this prospective study patients (n = 97) with a diagnosis of breast cancer or gynecological malignancies who had requested a second opinion received a questionnaire before and after the second opinion concerning their attitudes toward CAM. Results: The majority of patients had breast cancer (72.2%, n = 70). Only 6.2% (n = 6) stated that they had been informed about CAM by the doctors who treated them first, 21.6% (n = 21) had received information about it when seeking the second opinion. After the first opinion, 42.3% (n = 41) wanted to try CAM, the same proportion trusted orthodox medicine alone. After the second opinion, 24 patients (24.7%) wanted to try CAM, while 38.1% (n = 37) relied exclusively on orthodox medicine. There was a significant correlation between an increased patients' need for information and interest in CAM (p = 0.02). Conclusions: Today, aspects of CAM still are very often no part of oncological first and second opinions. This might hence lead to discouraging patients to try out CAM and therefore integrative medicine programs in comprehensive cancer centers might be problem-solving.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Breast cancer; Complementary and alternative medicine; Gynecological malignancies; Integrative medicine; Oncological center; Second opinion

Analysis of Oncological Second Opinions in a Certified University Breast and Gynecological Cancer Center Regarding Consensus between the First and Second Opinion and Conformity with the Guidelines - Lux, Michael P.; Wasner, Sonja; Meyer, Julia; Häberle, Lothar; Hack, Carolin; Jud, Sebastian; Hein, Alexander; Wunderle, Marius; Emons, Julius; Gaß, Paul; Fasching, Peter; Egloffstein, Sainab; et al. (Breast Care, 2020)
Introduction: Oncological second opinions are becoming increasingly important in the era of complex treatments and established certified cancer centers. Oncological guidelines with the highest levels of evidence are available, but these can only be effective to the extent that they are implemented. Therefore, we analyzed the effects of second opinions with regard to their agreement with first opinions and conformity with guidelines. Methods: In 164 patients with a diagnosis of breast cancer or gynecological malignancy who requested a second opinion, the first and second opinions, established at the interdisciplinary tumor conference, and conformity with the guidelines were evaluated. Results: The first opinion was not in agreement with the guidelines in 34.8% (15.2% diagnosis, 12.8% surgical therapy, 13.4% systemic therapy, and 5.5% radiotherapy), and the recommendations were optimized in the second opinion in 56.7% (28.7% diagnosis, 15.9% surgical therapy, 30.5% systemic therapy, and 8.5% radiotherapy). Conclusions: Oncological second opinions showed significant effects and one-third of first opinions were not in conformity with the guidelines. In a significant proportion of cases, the existing treatment plan was changed or supplemented to allow modern and individualized treatment approaches.
CRIS-Team Scopus Importer:2020-09-04

An Analysis of PIK3CA Hotspot Mutations and Response to Neoadjuvant Therapy in Patients with Breast Cancer from Four Prospective Clinical Trials - Jank, Paul; Karn, Thomas; van Mackelenbergh, Marion; Lindner, Judith; Treue, Denise; Huober, Jens; Engels, Knut; Solbach, Christine; Diebold, Kurt; Marmé, Frederik; Müller, Volkmar; Schneeweiss, Andreas; et al. (Clinical Cancer Research, 2024)
Purpose: The PI3K signaling pathway is frequently dysregulated in breast cancer, and mutations in PIK3CA are relevant for therapy resistance in HER2-positive (HER2pos) breast cancer. Mutations in exons 9 or 20 may have different impacts on response to neoadjuvant chemotherapy-based treatment regimens. Experimental Design: We investigated PIK3CA mutations in 1,691 patients with early breast cancer who were randomized into four neoadjuvant multicenter trials: GeparQuattro (NCT00288002), GeparQuinto (NCT00567554), GeparSixto (NCT01426880), and GeparSepto (NCT01583426). The role of different PIK3CA exons and hotspots for pathologic complete response (pCR) following neoadjuvant chemotherapy (NACT) and patient survival were evaluated for distinct molecular subgroups and anti-HER2 treatment procedures. Results: A total of 302 patients (17.9%) of the full cohort of 1,691 patients had a tumor with a PIK3CA mutation, with a different prevalence in molecular subgroups: luminal/HER2-negative (HER2neg) 95 of 404 (23.5%), HER2pos 170 of 819 (20.8%), and triple-negative breast cancer 37 of 468 patients (7.9%). We identified the mutations in PIK3CA exon 20 to be linked with worse response to anti-HER2 treatment (OR ¼ 0.507; 95% confidence interval, 0.320–0.802; P ¼ 0.004), especially in hormone receptor–positive HER2-positive breast cancer (OR ¼ 0.445; 95% confidence interval, 0.237–0.837; P ¼ 0.012). In contrast, exon 9 hotspot mutations p.E452K and p.E545K revealed no noteworthy differences in response therapy. Luminal/ HER2neg patients show a trend to have worse treatment response when PIK3CA was mutated. Interestingly, patients with residual disease following neoadjuvant treatment had better survival rates when PIK3CA was mutated. Conclusions: The PIK3CA hotspot mutation p.H1047R is associated with worse pCR rates following NACT in HER2pos breast cancer, whereas hotspot mutations in exon 9 seem to have less impact.
CRIS-Team Scopus Importer:2024-09-13

Anastrozole has an Association between Degree of Estrogen Suppression and Outcomes in Early Breast Cancer and is a Ligand for Estrogen Receptor α - Ingle, James N.; Cairns, Junmei; Suman, Vera J.; Shepherd, Lois E.; Fasching, Peter; Hoskin, Tanya L.; Singh, Ravinder J.; Desta, Zeruesenay; Kalari, Krishna R.; Ellis, Matthew J.; Goss, Paul E.; Chen, Bingshu E.; et al. (Clinical Cancer Research, 2020)
PURPOSE: To determine if the degree of estrogen suppression with aromatase inhibitors (AI: anastrozole, exemestane, letrozole) is associated with efficacy in early-stage breast cancer, and to examine for differences in the mechanism of action between the three AIs. EXPERIMENTAL DESIGN: Matched case-control studies [247 matched sets from MA.27 (anastrozole vs. exemestane) and PreFace (letrozole) trials] were undertaken to assess whether estrone (E1) or estradiol (E2) concentrations after 6 months of adjuvant therapy were associated with risk of an early breast cancer event (EBCE). Preclinical laboratory studies included luciferase activity, cell proliferation, radio-labeled ligand estrogen receptor binding, surface plasmon resonance ligand receptor binding, and nuclear magnetic resonance assays. RESULTS: Women with E1 ≥1.3 pg/mL and E2 ≥0.5 pg/mL after 6 months of AI treatment had a 2.2-fold increase in risk (P = 0.0005) of an EBCE, and in the anastrozole subgroup, the increase in risk of an EBCE was 3.0-fold (P = 0.001). Preclinical laboratory studies examined mechanisms of action in addition to aromatase inhibition and showed that only anastrozole could directly bind to estrogen receptor α (ERα), activate estrogen response element-dependent transcription, and stimulate growth of an aromatase-deficient CYP19A1-/- T47D breast cancer cell line. CONCLUSIONS: This matched case-control clinical study revealed that levels of estrone and estradiol above identified thresholds after 6 months of adjuvant anastrozole treatment were associated with increased risk of an EBCE. Preclinical laboratory studies revealed that anastrozole, but not exemestane or letrozole, is a ligand for ERα. These findings represent potential steps towards individualized anastrozole therapy.
CRIS-Team Scopus Importer:2020-06-26

Androgen receptor expression and response to chemotherapy in breast cancer patients treated in the neoadjuvant TECHNO and PREPARE trial - Witzel, Isabell; Loibl, Sibylle; Wirtz, Ralph; Fasching, Peter; Denkert, Carsten; Weber, Karsten; Lück, Hans Joachim; Huober, Jens; Karn, Thomas; Mackelenbergh, Marion von; Marmé, Frederik; Schem, Christian; et al. (British Journal of Cancer, 2019)
Background: The androgen receptor (AR) is discussed as a prognostic and/or predictive marker in breast cancer patients. Methods: AR mRNA expression was analysed by RT-qPCR in breast cancer patients treated in the neoadjuvant TECHNO (n = 118, HER2-positive) and PREPARE trial (n = 321, HER2-positive and -negative). In addition, mRNA expression of the AR transcript variants 1 (AR1) and 2 (AR2) was measured. Results: Regarding subtypes, high AR mRNA levels were frequent in HER2-positive (61.3%, 92/150) and luminal tumours (60.0%, 96/160) but almost absent in triple-negative tumours (4.3%, 3/69) (p < 0.0001). Overall, high AR mRNA levels were found to be associated with lower pathological complete remission (pCR) rates (OR 0.77 per unit, 95% CI 0.67–0.88, p = 0.0002) but also with better prognosis in terms of longer disease-free survival (DFS) (HR 0.57, 95% CI 0.39–0.85, p = 0.0054) and overall survival (OS) (HR 0.43, 95% CI, 0.26–0.71, p = 0.0011). In the PREPARE trial, a survival difference for patients with high and low AR1 mRNA levels could only be seen in the standard chemotherapy arm but not in the dose-dense treatment arm (OS: HR 0.41; 95% CI 0.22–0.74 vs. HR 1.05; 95% CI 0.52–2.13; p = 0.0459). Conclusions: We provide evidence that AR mRNA predicts response to chemotherapy in breast cancer patients.
CRIS-Team Scopus Importer:2019-11-29

An Electronic Patient-Reported Outcome Tool for the FACT-B (Functional Assessment of Cancer Therapy-Breast) Questionnaire for Measuring the Health-Related Quality of Life in Patients With Breast Cancer: Reliability Study - Matthies, Lina Maria; Taran, Florin-Andrei; Keilmann, Lucia; Schneeweiss, Andreas; Simoes, Elisabeth; Hartkopf, Andreas D.; Sokolov, Alexander N.; Walter, Christina B.; Sickenberger, Nina; Wallwiener, Stephanie; Feisst, Manuel; Gaß, Paul; et al. (Journal of Medical Internet Research, 2019)
BACKGROUND: The most frequent malignant disease in women is breast cancer. In the metastatic setting, quality of life is the primary therapeutic goal, and systematic treatment has only a limited effect on survival rates; therefore, the concept of the health-related quality of life (HRQoL) and measurement of patient-reported outcomes (PROs) are gaining more and more importance in the therapy setting of diseases such as breast cancer. One of the frequently used questionnaires for measuring the HRQoL in patients with breast cancer is the Functional Assessment of Cancer Therapy-Breast (FACT-B). Currently, paper-based surveys still predominate, as only a few reliable and validated electronic-based questionnaires are available. ePRO tools for the FACT-B questionnaire with proven reliability are missing so far. OBJECTIVE: The aim of this study was to analyze the reliability of tablet-based measurement of FACT-B in the German language in adjuvant (curative) and metastatic breast cancer patients. METHODS: Paper- and tablet-based questionnaires were completed by a total of 106 female adjuvant and metastatic breast cancer patients. All patients were required to complete the electronically based (ePRO) and paper-based version of the FACT-B. A frequency analysis was performed to determine descriptive sociodemographic characteristics. Both dimensions of reliability (parallel forms reliability using Wilcoxon test and test of internal consistency using Spearman ρ) and agreement rates for single items, Kendall tau for each subscale, and total score were analyzed. RESULTS: High correlations were shown for both dimensions of reliability (parallel forms reliability and internal consistency) in the patients' response behavior between paper-based and electronically based questionnaires. Regarding the reliability test of parallel forms, no significant differences were found in 35 of 37 single items, while significant correlations in the test for consistency were found in all 37 single items, in all 5 sum individual item subscale scores, as well as in total FACT-B score. CONCLUSIONS: The ePRO version of the FACT-B questionnaire is reliable for patients with breast cancer in both adjuvant and metastatic settings, showing highly significant correlations with the paper-based version in almost all questions all subscales and the total score.
CRIS-Team Scopus Importer:2019-05-07
Keywords: breast cancer; ePRO measurement; FACT-B; HRQoL; patient-reported outcomes; reliability of ePRO

A network analysis to identify mediators of germline-driven differences in breast cancer prognosis - Escala-Garcia, Maria; Abraham, Jean; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Ashworth, Alan; Auer, Paul L.; Auvinen, Päivi; Beckmann, Matthias; Beesley, Jonathan; Behrens, Sabine; Benitez, Javier; et al. (Nature Communications, 2020)
Identifying the underlying genetic drivers of the heritability of breast cancer prognosis remains elusive. We adapt a network-based approach to handle underpowered complex datasets to provide new insights into the potential function of germline variants in breast cancer prognosis. This network-based analysis studies 7.3 million variants in 84,457 breast cancer patients in relation to breast cancer survival and confirms the results on 12,381 independent patients. Aggregating the prognostic effects of genetic variants across multiple genes, we identify four gene modules associated with survival in estrogen receptor (ER)-negative and one in ER-positive disease. The modules show biological enrichment for cancer-related processes such as G-alpha signaling, circadian clock, angiogenesis, and Rho-GTPases in apoptosis.
CRIS-Team Scopus Importer:2020-01-24

An intergenic risk locus containing an enhancer deletion in 2q35 modulates breast cancer risk by deregulating IGFBP5 expression - Wyszynski, Asaf; Hong, Chi-Chen; Lam, Kristin; Michailidou, Kyriaki; Lytle, Christian; Yao, Song; Zhang, Yali; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Hopper, John L.; Southey, Melissa C.; et al. (Human Molecular Genetics, 2016)
Breast cancer is the most diagnosed malignancy and the second leading cause of cancer mortality in females. Previous association studies have identified variants on 2q35 associated with the risk of breast cancer. To identify functional susceptibility loci for breast cancer, we interrogated the 2q35 gene desert for chromatin architecture and functional variation correlated with gene expression. We report a novel intergenic breast cancer risk locus containing an enhancer copy number variation (enCNV; deletion) located approximately 400Kb upstream to IGFBP5, which overlaps an intergenic ERα-bound enhancer that loops to the IGFBP5 promoter. The enCNV is correlated with modified ERα binding and monoallelic-repression of IGFBP5 following oestrogen treatment. We investigated the association of enCNV genotype with breast cancer in 1,182 cases and 1,362 controls, and replicate our findings in an independent set of 62,533 cases and 60,966 controls from 41 case control studies and 11 GWAS. We report a dose-dependent inverse association of 2q35 enCNV genotype (percopy OR = 0.68 95%CI 0.55-0.83, P = 0.0002; replication OR = 0.77 95% CI 0.73-0.82, P = 2.1 × 10-19) and identify 13 additional linked variants (r2 > 0.8) in the 20Kb linkage block containing the enCNV (P = 3.2 × 10-15- 5.6 × 10-17). These associations were independent of previously reported 2q35 variants, rs13387042/rs4442975 and rs16857609, and were stronger for ER-positive than ER-negative disease. Together, these results suggest that 2q35 breast cancer risk loci may be mediating their effect through IGFBP5.
EVALuna2:33321

Anti-Müllerian hormone (AMH) levels in premenopausal breast cancer patients treated with taxane-based adjuvant chemotherapy - A translational research project of the SUCCESS A study - Trapp, Elisabeth; Steidl, J.; Rack, B.; Kupka, M. S.; Andergassen, U.; Jueckstock, J.; Kurt, A.; Vilsmaier, T.; De Gregorio, A.; De Gregorio, N.; Tzschaschel, M.; Lato, C.; et al. (BREAST, 2017)
BACKGROUND: Premenopausal women undergoing chemotherapy are at high risk for premature ovarian failure and its long-term consequences. Data on potential markers to evaluate ovarian reserve pre- and posttreatment are limited. Anti-Müllerian hormone (AMH) known for ovarian reserve in reproductive medicine could be a surrogate marker and was assessed in premenopausal breast cancer patients of the SUCCESS A study (EUDRA-CT no. 2005-000490-21). METHODS: We identified 170 premenopausal patients, age ≤ 40 years at trial entry, who received FEC-Doc as taxane-anthracylince based chemotherapy. Blood samples were taken at three time points: Before, four weeks after and two years after adjuvant chemotherapy. Serum AMH-levels were evaluated in a central laboratory by a quantitative immunoassay AMH Gen II ELISA (Beckman Coulter, Brea, USA). RESULTS: Median age was 36 years (21-40 years). Median serum AMH-level before chemotherapy was 1.37 ng/ml (range < 0.1-11.3 ng/ml). Four weeks after chemotherapy AMH-levels dropped in 98.6% of the patients to <0.1 ng/ml (range < 0.1-0.21 ng/ml). After two years, 73.3% (n = 101) showed no evidence of ovarian function recovery (AMH <0.1 ng/ml, range < 0.1-3.9 ng/ml). Permanent chemotherapy induced amenorrhea occurred only in 50.6% of the patients. CONCLUSIONS: In this analysis, premenopausal patients showed a high rate of ovarian impairment reflected by low AMH-levels after chemotherapy.
EVALuna2:36126

Antimullerian Hormone as a Serum Biomarker for Risk of Chemotherapy-Induced Amenorrhea - Ruddy, Kathryn J.; Schaid, Daniel J.; Batzler, Anthony; Cecchini, Reena S.; Partridge, Ann H.; Norman, Aaron; Fehrenbacher, Louis; Stewart, Elizabeth A.; Trabuco, Emanuel; Ginsburg, Elizabeth; Couch, Fergus J.; Fasching, Peter; et al. (Journal of the National Cancer Institute, 2021)
Antimullerian hormone (AMH) is a promising biomarker for ovarian reserve. In this study, we assessed AMH before and 1 year after initiation of adjuvant chemotherapy on National Surgical Adjuvant Breast and Bowel Project (NSABP)/NRG Oncology B-47 in female participants aged 42 years and younger (median age = 39 years). At baseline, median AMH was 1.2 ng/mL; 13 (4.7%) values were less than 0.1 ng/mL (the threshold for detectable levels, in the perimenopause and menopause range), and 57 values (20.6%) were less than 0.5 ng/mL. At 1 year, 215 (77.6%) were less than 0.1 ng/mL, and 264 (95.3%) were less than 0.5 ng/mL. Postchemotherapy menses were reported by 46.2% of participants. Multivariable logistic regression found that the odds of having postchemotherapy menses increased with younger age, higher body mass index, and higher prechemotherapy AMH, but not by trastuzumab administration or by the choice of chemotherapy (doxorubicin-cyclophosphamide followed by paclitaxel vs docetaxel-cyclophosphamide). We conclude that higher prechemotherapy AMH predicts a lower risk of chemotherapy-induced amenorrhea and that AMH 1 year after chemotherapy initiation is not informative in this setting because it is likely to be very low.
CRIS-Team Scopus Importer:2021-09-10

A phase III trial of adjuvant ribociclib plus endocrine therapy versus endocrine therapy alone in patients with HR-positive/HER2-negative early breast cancer: final invasive disease-free survival results from the NATALEE trial - Hortobagyi, G. N.; Lacko, A.; Sohn, J.; Cruz, F.; Ruiz Borrego, M.; Manikhas, A.; Hee Park, Y.; Stroyakovskiy, D.; Yardley, D. A.; Huang, C. S.; Fasching, Peter; Crown, J.; et al. (Annals of Oncology, 2025)
Background: NATALEE assessed efficacy and tolerability of 3 years of adjuvant ribociclib plus a nonsteroidal aromatase inhibitor (NSAI) compared with an NSAI alone in a broad population of patients with hormone receptor (HR)-positive/human epidermal growth factor 2 (HER2)-negative early breast cancer, including a select group without nodal involvement. This is the final preplanned analysis of invasive disease-free survival (iDFS). Patients and methods: Premenopausal/postmenopausal women and men were randomized 1 : 1 to ribociclib (n = 2549; 400 mg/day, 3 weeks on/1 week off for 36 months) plus NSAI (letrozole 2.5 mg/day or anastrozole 1 mg/day for 60 months) or NSAI alone (n = 2552). Men and premenopausal women also received goserelin (3.6 mg once every 28 days). Patients had anatomical stage IIA (N0 with additional risk factors or N1), IIB, or III disease. The primary endpoint was iDFS. Secondary efficacy endpoints were recurrence-free survival (RFS), distant DFS, and overall survival. This final iDFS analysis was planned after ∼500 events. Results: At data cut-off (21 July 2023), ribociclib was stopped for 1996 patients (78.3%); 1091 (42.8%) completed 3 years of ribociclib, and ribociclib treatment was ongoing for 528 (20.7%). Median follow-up for iDFS was 33.3 months. Overall, 226 and 283 iDFS events occurred with ribociclib plus NSAI versus NSAI alone, respectively. Ribociclib plus NSAI demonstrated significant iDFS benefit over NSAI alone [hazard ratio 0.749, 95% confidence interval (CI) 0.628-0.892; P = 0.0012]. The 3-year iDFS rates were 90.7% (95% CI 89.3% to 91.8%) versus 87.6% (95% CI 86.1% to 88.9%). A consistent benefit was observed across prespecified subgroups, including stage (II/III) and nodal status (positive/negative). Distant DFS and RFS favored ribociclib plus NSAI. Overall survival data were immature. No new safety signals were observed. Conclusions: With longer follow-up and most patients off ribociclib, NATALEE continues to demonstrate iDFS benefit with ribociclib plus NSAI over NSAI alone in the overall population and across key subgroups. Observed adverse events remained stable.
CRIS-Team Scopus Importer:2024-12-06
Keywords: breast cancer; cyclin-dependent kinase 4 and 6 inhibitors; hormone receptor-positive; human epidermal growth factor receptor 2-negative; NATALEE; ribociclib

A phase II randomized study of neoadjuvant letrozole plus alpelisib for hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer (NeO-ORB) - Mayer, Ingrid A.; Prat, Aleix; Egle, Daniel; Blau, Sibel; Alejandro Perez Fidalgo, J.; Gnant, Michael; Fasching, Peter; Colleoni, Marco; Wolff, Antonio C.; Winer, Eric P.; Singer, Christian F.; Hurvitz, Sara; et al. (Clinical Cancer Research, 2019)
Purpose: Addition of alpelisib to fulvestrant significantly extended progression-free survival in PIK3CA-mutant, hormone receptor–positive (HR þ ) advanced/metastatic breast cancer in the phase III SOLAR-1 study. The combination of alpelisib and letrozole also had promising activity in phase I studies of HR þ advanced/metastatic breast cancer. NEO-ORB aimed to determine whether addition of alpelisib to letrozole could increase response rates in the neoadjuvant setting. Patients and Methods: Postmenopausal women with HR þ , human epidermal growth factor receptor 2-negative, T1c-T3 breast cancer were assigned to the PIK3CA-wild-type or PIK3CA-mutant cohort according to their tumor PIK3CA status, and randomized (1:1) to 2.5 mg/day letrozole with 300 mg/day alpelisib or placebo for 24 weeks. Primary endpoints were objective response rate (ORR) and pathologic complete response (pCR) rate for both PIK3CA cohorts. Results: In total, 257 patients were assigned to letrozole plus alpelisib (131 patients) or placebo (126 patients). Grade 3 adverse events (5% of patients) in the alpelisib arm were hyperglycemia (27%), rash (12%), and maculopapular rash (8%). The primary objective was not met; ORR in the alpelisib versus placebo arm was 43% versus 45% and 63% versus 61% in the PIK3CA-mutant and wild-type cohorts, respectively. pCR rates were low in all groups. Decreases in Ki-67 were similar across treatment arms and cohorts. In PIK3CA-mutant tumors, alpelisib plus letrozole treatment induced a greater decrease in phosphorylated AKT versus placebo plus letrozole. Conclusions: In contrast to initial results in advanced/metastatic disease, addition of alpelisib to 24-week neoadjuvant letrozole treatment did not improve response in patients with HR þ early breast cancer.
CRIS-Team Scopus Importer:2019-05-28

A Phase II Study of Talazoparib after Platinum or Cytotoxic Nonplatinum Regimens in Patients with Advanced Breast Cancer and Germline BRCA1/2 Mutations (ABRAZO) - Turner, Nicholas C.; Telli, Melinda L.; Rugo, Hope S.; Mailliez, Audrey; Ettl, Johannes; Grischke, Eva-Maria; Mina, Lida A.; Balmana, Judith; Fasching, Peter; Hurvitz, Sara A.; Wardley, Andrew M.; Chappey, Colombe; et al. (Clinical Cancer Research, 2019)
PURPOSE: To assess talazoparib activity in germline BRCA1/2 mutation carriers with advanced breast cancer. PATIENTS AND METHODS: ABRAZO (NCT02034916) was a two-cohort, two-stage, phase II study of talazoparib (1 mg/day) in germline BRCA mutation carriers with a response to prior platinum with no progression on or within 8 weeks of the last platinum dose (cohort 1) or ≥3 platinum-free cytotoxic regimens (cohort 2) for advanced breast cancer. Primary endpoint was confirmed objective response rate (ORR) by independent radiological assessment. RESULTS: We enrolled 84 patients (cohort 1, n = 49; cohort 2, n = 35) from May 2014 to February 2016. Median age was 50 (range, 31-75) years. Triple-negative breast cancer (TNBC) incidence was 59% (cohort 1) and 17% (cohort 2). Median number of prior cytotoxic regimens for advanced breast cancer was two and four, respectively. Confirmed ORR was 21% [95% confidence interval (CI), 10-35; cohort 1] and 37% [95% CI, 22-55; cohort 2]. Median duration of response was 5.8 and 3.8 months, respectively. Confirmed ORR was 23% (BRCA1), 33% (BRCA2), 26% (TNBC), and 29% (hormone receptor-positive). The most common all-grade adverse events (AE) included anemia (52%), fatigue (45%), and nausea (42%). Talazoparib-related AEs led to drug discontinuation in 3 (4%) patients. In an exploratory analysis, longer platinum-free interval was associated with higher response rate in cohort 1 (0% ORR with interval <8 weeks; 47% ORR with interval >6 months). CONCLUSIONS: Talazoparib exhibited promising antitumor activity in patients with advanced breast cancer and germline BRCA mutation.
CRIS-Team Scopus Importer:2019-05-21

Appraising the role of previously reported risk factors in epithelial ovarian cancer risk: A Mendelian randomization analysis - Yarmolinsky, James; Relton, Caroline L.; Lophatananon, Artitaya; Muir, Kenneth; Menon, Usha; Gentry-Maharaj, Aleksandra; Walther, Axel; Zheng, Jie; Fasching, Peter; Zheng, Wei; Yin Ling, Woo; Park, Sue K.; et al. (Plos Medicine, 2019)
BACKGROUND: Various risk factors have been associated with epithelial ovarian cancer risk in observational epidemiological studies. However, the causal nature of the risk factors reported, and thus their suitability as effective intervention targets, is unclear given the susceptibility of conventional observational designs to residual confounding and reverse causation. Mendelian randomization (MR) uses genetic variants as proxies for risk factors to strengthen causal inference in observational studies. We used MR to evaluate the association of 12 previously reported risk factors (reproductive, anthropometric, clinical, lifestyle, and molecular factors) with risk of invasive epithelial ovarian cancer, invasive epithelial ovarian cancer histotypes, and low malignant potential tumours. METHODS AND FINDINGS: Genetic instruments to proxy 12 risk factors were constructed by identifying single nucleotide polymorphisms (SNPs) that were robustly (P < 5 × 10-8) and independently associated with each respective risk factor in previously reported genome-wide association studies. These risk factors included genetic liability to 3 factors (endometriosis, polycystic ovary syndrome, type 2 diabetes) scaled to reflect a 50% higher odds liability to disease. We obtained summary statistics for the association of these SNPs with risk of overall and histotype-specific invasive epithelial ovarian cancer (22,406 cases; 40,941 controls) and low malignant potential tumours (3,103 cases; 40,941 controls) from the Ovarian Cancer Association Consortium (OCAC). The OCAC dataset comprises 63 genotyping project/case-control sets with participants of European ancestry recruited from 14 countries (US, Australia, Belarus, Germany, Belgium, Denmark, Finland, Norway, Canada, Poland, UK, Spain, Netherlands, and Sweden). SNPs were combined into multi-allelic inverse-variance-weighted fixed or random effects models to generate effect estimates and 95% confidence intervals (CIs). Three complementary sensitivity analyses were performed to examine violations of MR assumptions: MR-Egger regression and weighted median and mode estimators. A Bonferroni-corrected P value threshold was used to establish strong evidence (P < 0.0042) and suggestive evidence (0.0042 < P < 0.05) for associations. In MR analyses, there was strong or suggestive evidence that 2 of the 12 risk factors were associated with invasive epithelial ovarian cancer and 8 of the 12 were associated with 1 or more invasive epithelial ovarian cancer histotypes. There was strong evidence that genetic liability to endometriosis was associated with an increased risk of invasive epithelial ovarian cancer (odds ratio [OR] per 50% higher odds liability: 1.10, 95% CI 1.06-1.15; P = 6.94 × 10-7) and suggestive evidence that lifetime smoking exposure was associated with an increased risk of invasive epithelial ovarian cancer (OR per unit increase in smoking score: 1.36, 95% CI 1.04-1.78; P = 0.02). In analyses examining histotypes and low malignant potential tumours, the strongest associations found were between height and clear cell carcinoma (OR per SD increase: 1.36, 95% CI 1.15-1.61; P = 0.0003); age at natural menopause and endometrioid carcinoma (OR per year later onset: 1.09, 95% CI 1.02-1.16; P = 0.007); and genetic liability to polycystic ovary syndrome and endometrioid carcinoma (OR per 50% higher odds liability: 0.89, 95% CI 0.82-0.96; P = 0.002). There was little evidence for an association of genetic liability to type 2 diabetes, parity, or circulating levels of 25-hydroxyvitamin D and sex hormone binding globulin with ovarian cancer or its subtypes. The primary limitations of this analysis include the modest statistical power for analyses of risk factors in relation to some less common ovarian cancer histotypes (low grade serous, mucinous, and clear cell carcinomas), the inability to directly examine the association of some ovarian cancer risk factors that did not have robust genetic variants available to serve as proxies (e.g., oral contraceptive use, hormone replacement therapy), and the assumption of linear relationships between risk factors and ovarian cancer risk. CONCLUSIONS: Our comprehensive examination of possible aetiological drivers of ovarian carcinogenesis using germline genetic variants to proxy risk factors supports a role for few of these factors in invasive epithelial ovarian cancer overall and suggests distinct aetiologies across histotypes. The identification of novel risk factors remains an important priority for the prevention of epithelial ovarian cancer.
CRIS-Team Scopus Importer:2019-09-20

A prediction model for pathological complete response after neoadjuvant chemotherapy of HER2-negative breast cancer patients - Häberle, Lothar; Erber, Ramona; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Langemann, Hanna; Rauh, C.; Hack, Caroline; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

A Preoperative Window-of-Opportunity Study of Oral SERD, Imlunestrant, in Newly Diagnosed ER-Positive, HER2-Negative Early Breast Cancer: Results from the EMBER-2 Study - Neven, Patrick; Stahl, Nicole; Vidal, Maria; Martín, Miguel; Kaufman, Peter A.; Harbeck, Nadia; Hunt, Kelly K.; Carter, Stacey; Bidard, Francois Clement; Fasching, Peter; Aftimos, Philippe; Wheatley, Duncan; et al. (Clinical Cancer Research, 2024)
Purpose: Imlunestrant is an oral selective estrogen receptor degrader with favorable safety and preliminary efficacy in patients with advanced breast cancer. Pharmacodynamic (PD) biomarker data can optimize drug dosing; in this study, we present PD data from the EMBER-2 study. Patients and Methods: Postmenopausal women with untreated, operable estrogen receptor (ER)-positive, HER2-negative early breast cancer were randomized to 400 versus 800 mg of imlunestrant daily for ∼2 weeks before surgery. A single arm study tested a daily dose of 200 mg. PD biomarker changes (ER, progesterone receptor, Ki-67 by IHC, and mRNA expression of ER-related genes) were evaluated in paired tumor samples (pre-/posttreatment). Safety and pharmacokinetics were also assessed. Results: Among evaluable paired samples (n 75), PD profiles demonstrated consistent ER targeting between 400- and 800-mg doses, with less toxicity at the 400-mg dose. Although inducing the lowest rate of complete cell-cycle arrest, PD and pharmacokinetic results were similar for the 200-mg dose. Conclusions: EMBER-2 combined with existing phase I data has identified 400 mg as the optimal imlunestrant dose.
CRIS-Team Scopus Importer:2025-02-04

A randomised phase II study investigating durvalumab in addition to an anthracycline taxane-based neoadjuvant therapy in early triple-negative breast cancer: Clinical results and biomarker analysis of GeparNuevo study - Loibl, S.; Untch, M.; Burchardi, N.; Huober, J.; Sinn, B. V.; Blohmer, J. U.; Grischke, E. M.; Furlanetto, J.; Tesch, H.; Hanusch, C.; Engels, K.; Rezai, M.; et al. (Annals of Oncology, 2019)
Background: Combining immune-checkpoint inhibitors with chemotherapy yielded an increased response rates in patients with metastatic triple-negative breast cancer (TNBC). Therefore, we evaluated the addition of durvalumab to standard neoadjuvant chemotherapy (NACT) in primary TNBC. Patients and methods: GeparNuevo is a randomised phase II double-blind placebo-controlled study randomising patients with TNBC to durvalumab or placebo given every 4 weeks in addition to nab-paclitaxel followed by standard EC. In the window-phase durvalumab/placebo alone was given 2 weeks before start of nab-paclitaxel. Randomisation was stratified by stromal tumour-infiltrating lymphocyte (sTILs). Patients with primary cT1b-cT4a-d disease, centrally confirmed TNBC and sTILs were included. Primary objective was pathological complete response (PCR) (ypT0 ypN0). Results: A total of 174 patients were randomised, 117 participated in the window-phase. Median age was 49.5 years (range 23-76); 47 patients (27%) were younger than 40 years; 113 (65%) had stage ≥IIA disease, 25 (14%) high sTILs, 138 of 158 (87%) were PD-L1-positive. PCR rate with durvalumab was 53.4% (95% CI 42.5% to 61.4%) versus placebo 44.2% (95% CI 33.5% to 55.3%; unadjusted continuity corrected χ2P = 0.287), corresponding to OR = 1.45 (95% CI 0.80-2.63, unadjusted Wald P = 0.224). Durvalumab effect was seen only in the window cohort (PCR 61.0% versus 41.4%, OR = 2.22, 95% CI 1.06-4.64, P = 0.035; interaction P = 0.048). In both arms, significantly increased PCR (P < 0.01) were observed with higher sTILs. There was a trend for increased PCR rates in PD-L1-positive tumours, which was significant for PD-L1-tumour cell in durvalumab (P = 0.045) and for PD-L1-immune cell in placebo arm (P = 0.040). The most common immune-related adverse events were thyroid dysfunction any grade in 47%. Conclusions: Our results suggest that the addition of durvalumab to anthracycline-/taxane-based NACT increases PCR rate particularly in patients treated with durvalumab alone before start of chemotherapy. Trial registration: ClinicalTrials.gov number: NCT02685059.
CRIS-Team Scopus Importer:2019-10-08
Keywords: durvalumab; immunotherapy; neoadjuvant; TNBC

A Randomized, Double-Blind, Phase III Trial of Neoadjuvant Chemotherapy (NACT) with atezolizumab/Placebo in Patients with Triple-Negative Breast Cancer (TNBC) Followed by Adjuvant Continuation of atezolizumab/Placebo (Gepardouze) - Loibl, Sibylle; Jackisch, Christian; Seiler, Sabine; Rastogi, Priya; Huober, Lens; Denkert, Carsten; Schneeweiss, Andreas; Hanusch, Claus; Fasching, Peter; Blohmer, Jens-Uwe; Untch, Michael; Rhiem, Kerstin; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

A Randomized, Open-label, Presurgical, Window-of-Opportunity Study Comparing the Pharmacodynamic Effects of the Novel Oral SERD AZD9496 with Fulvestrant in Patients with Newly Diagnosed ER+ HER2(-) Primary Breast Cancer - Robertson, John F. R.; Evans, Abigail; Henschen, Stephan; Kirwan, Cliona C.; Jahan, Ali; Kenny, Laura M.; Dixon, J. Michael; Schmid, Peter; Kothari, Ashutosh; Mohamed, Omar; Fasching, Peter; Cheung, Kwok-Leung; et al. (Clinical Cancer Research, 2020)
Purpose: Fulvestrant, the first-in-class selective estrogen receptor (ER) degrader (SERD), is clinically effective in patients with ER+ breast cancer, but it has administration and pharmacokinetic limitations. Pharmacodynamic data suggest complete ER degradation is not achieved at fulvestrant's clinically feasible dose. This presurgical study (NCT03236974) compared the pharmacodynamic effects of fulvestrant with AZD9496, a novel, orally bioavailable, nonsteroidal, potent SERD, in treatment-naive patients with ER+ HER2(-) primary breast cancer awaiting curative intent surgery.
CRIS-Team WoS Importer:2020-08-28

Arbeitsgemeinschaft Gynäkologische Onkologie Recommendations for the Diagnosis and Treatment of Patients with Early Breast Cancer: Update 2023 - Park-Simon, Tjoung Won; Müller, Volkmar; Jackisch, Christian; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens Uwe; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva Maria; Fasching, Peter; et al. (Breast Care, 2023)
Background: Each year the interdisciplinary Arbeitsgemeinschaft Gynäkologische Onkologie (AGO), German Gynecological Oncology Group Breast Committee on Diagnosis and Treatment of Breast Cancer provides updated state-of-the-art recommendations for early and metastatic breast cancer. Summary: The updated evidence-based treatment recommendation for early and metastatic breast cancer has been released in March 2023. Key Messages: This paper concisely captures the updated recommendations for early breast cancer chapter by chapter.
CRIS-Team Scopus Importer:2023-09-15
Keywords: (Post)(neo)adjuvant; Breast surgery; Communication; Early breast cancer; Radiotherapy; Reconstruction

Arbeitsgemeinschaft Gynäkologische Onkologie Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2024 - Thill, Marc; Janni, Wolfgang; Albert, Ute Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Ditsch, Nina; Fallenberg, Eva Maria; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2024)
The Breast Committee of the Arbeitsgemeinschaft Gynä- kologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2024 update of the evidencebased recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer.
CRIS-Team Scopus Importer:2024-08-30
Keywords: Arbeitsgemeinschaft Gynäkologische Onkologie; Diagnosis; Metastatic breast cancer; Recommendations; Treatment

A small hypoxia signature predicted pCR response to bevacizumab in the neoadjuvant GeparQuinto breast cancer trial - Karn, Thomas; Meissner, Tobias; Weber, Karsten E.; Solbach, Christine; Denkert, Carsten; Engels, Knut; Fasching, Peter; Sinn, Bruno V.; Schrader, Iris; Budczies, Jan; Marmé, Frederik; Müller, Volkmar; et al. (Clinical Cancer Research, 2020)
Purpose: In breast cancer, bevacizumab increased pCR rate but not long-term survival and no predictive markers are available to identify patients with long-term benefit from the drug. Experimental Design: We profiled 289 pretherapeutic formalinfixed, paraffin-embedded (FFPE) biopsies of HER2-negative patients from the GeparQuinto trial of neoadjuvant chemotherapy bevacizumab by exome-capture RNA-sequencing (RNA-seq). In a prospectively planned study, we tested molecular signatures for response prediction. IHC validation was performed using tissue microarrays. Results: We found strong agreement of molecular and pathologic parameters as hormone receptors, grading, and lymphocyte infiltration in 221 high-quality samples. Response rates (49.3% pCR overall) were higher in basal-like (68.9%) and HER2-enriched (45.5%) than in luminal B (35.7%), luminal A (17.9%), and normal-like (20.0%) subtypes. T-cell (OR = 1.60; 95% confidence interval, 1.21-2.12; P = 0.001), proliferation (OR = 2.88; 95% CI, 2.00-4.15; P < 0.001), and hypoxia signatures (OR = 1.92; 95% CI, 1.41-2.60; P < 0.001) significantly predicted pCR in univariate analysis. In a prespecified multivariate logistic regression, a small hypoxia signature predicted pCR (OR = 2.40; 95% CI, 1.28-4.51; P = 0.006) with a significant interaction with bevacizumab treatment (P = 0.020). IHC validation using NDRG1 as marker revealed highly heterogenous expression within tissue leading to profound loss of sensitivity in TMA analysis, still a significant predictive value for pCR was detected (P = 0.025). Conclusions: Exome-capture RNA-seq characterizes small FFPE core biopsies by reliably detecting factors as for example ER status, grade, and tumor-infiltrating lymphocytes levels. Beside molecular subtypes and immune signatures, a small hypoxia signature predicted pCR to bevacizumab,which could be validated by IHC. The signature can have important applications for bevacizumab treatment in different cancer types and might also have a role for novel combination therapies of bevacizumab with immune checkpoint inhibition.
CRIS-Team Scopus Importer:2020-04-28

Assessment of breast volume changes during human pregnancy using a three-dimensional surface assessment technique in the prospective CGATE study - Bayer, Christian M.; Bani, Mayada; Schneider, Michael; Dammer, Ulf; Raabe, Eva; Haeberle, Lothar; Faschingbauer, Florian; Schneeberger, Sabine; Renner, Stefan; Fischer, Dorothea; Schulz-Wendtland, Rüdiger; Fasching, Peter; et al. (European Journal of Cancer Prevention, 2014)
Pregnancies and breastfeeding are two important protective factors concerning breast cancer risk. Breast volume and breast volume changes might be a breast phenotype that could be monitored during pregnancy and breastfeeding without ionizing radiation or expensive equipment. The aim of the present study was to document changes in breast volume during pregnancy prospectively. In the prospective Clinical Gravidity Association Trial and Evaluation programme, pregnant women were followed up prospectively from gestational week 12 to birth. Three-dimensional breast surface imaging and subsequent volume assessments were performed. Factors influencing breast volume at the end of the pregnancy were assessed using linear regression models. Breast volumes averaged 420 ml at the start of pregnancy and 516 ml at the end of pregnancy. The first, second and third quartiles of the volume increase were 41, 95 and 135 ml, respectively. Breast size increased on average by 96 ml, regardless of the initial breast volume. Breast volume increases during pregnancy, but not all womens' breasts respond to pregnancy in the same way. Breast volume changes during pregnancy are an interesting phenotype that can be easily assessed in further studies to examine breast cancer risk.
EVALuna2:14487

Assessment of mammographic density before and after first full-term pregnancy - Löhberg, Christian; Heusinger, Katharina; Jud, Sebastian; Häberle, Lothar; Hein, Alexander; Rauh, Claudia; Bani, Mayada; Lux, Michael P.; Schrauder, Michael G.; Bayer, Christian M.; Helbig, Cosima; Grolik, Ronald; et al. (European Journal of Cancer Prevention, 2010)
Mammographic density (MD) has consistently been found as one of the strongest breast cancer risk factors. In our study, both qualitative and quantitative density measurements were performed in a hospital-based group of premenopausal women before and after first full-term pregnancy providing an opportunity for direct evaluation of the effects of one pregnancy on MD. Mammograms were obtained from 23 women before and after first full-term pregnancy and from 28 nulliparous controls. MD was determined by a standard qualitative assessment method using the Breast Imaging Reporting and Data System, and a quantitative computer-based threshold method (0-100%). The mean age at mammography before and after pregnancy was 31 and 34 years, respectively, with a mean difference of 40 months between mammographies. The quantitative density assessment showed a significant reduction in relative MD after pregnancy of 12 percentage points (8.6-15.4), compared with 3.1 (0.0-6.2) in the nulliparous control group (P<0.001). A reduction in MD of more than 10% was seen in 52% of the patients, compared with 18% of the controls. The qualitative density assessment confirmed a reduction in MD after pregnancy by one Breast Imaging Reporting and Data System category (P=0.02). This longitudinal study showed that MD can be influenced by one full-term pregnancy. This effect was seen with both quantitative and qualitative assessment methods. It may be hypothesized that breast cancer risk reduction associated with pregnancy is mediated through a direct reduction of MD, and MD assessment might be incorporated in individualizing risk assessment and prevention. © 2010 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; mammographic density; pregnancy

Assessment of side effects (SEs) impacting quality of life (QoL) in patients (pts) undergoing treatment (tx) for advanced breast cancer (ABC) in clinical practice: A real-world (RW) multi-country survey - Cardoso, F.; Rihani, J.; Aubel, D.; De Courcy, J.; Harmer, V.; Harbeck, N.; Casas, A.; Rugo, H. S.; Fasching, Peter; Haftchenary, S.; Pathak, P.; Schumacher-Wulf, E. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, J.; Fasching, Peter; Wunderle, M.; Heindl, F.; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, M.; Polifka, Iris; Wachter, David Lukas; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with prognosis of estrogen receptor-negative breast cancer after chemotherapy - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten B.; Rafiq, Sajjad; Behrens, Sabine; Goode, Ellen L.; Pharoah, Paul Pd; Seibold, Petra; Fasching, Peter; Andrulis, Irene L.; Kristensen, Vessela N.; Couch, Fergus J.; et al. (Breast Cancer Research, 2015)
Tumor lymphocyte infiltration is associated with clinical response to chemotherapy in estrogen receptor (ER) negative breast cancer. To identify variants in immunosuppressive pathway genes associated with prognosis after adjuvant chemotherapy for ER-negative patients, we studied stage I-III invasive breast cancer patients of European ancestry, including 9,334 ER-positive (3,151 treated with chemotherapy) and 2,334 ER-negative patients (1,499 treated with chemotherapy).We pooled data from sixteen studies from the Breast Cancer Association Consortium (BCAC), and employed two independent studies for replications. Overall 3,610 single nucleotide polymorphisms (SNPs) in 133 genes were genotyped as part of the Collaborative Oncological Gene-environment Study, in which phenotype and clinical data were collected and harmonized. Multivariable Cox proportional hazard regression was used to assess genetic associations with overall survival (OS) and breast cancer-specific survival (BCSS). Heterogeneity according to chemotherapy or ER status was evaluated with the log-likelihood ratio test.Three independent SNPs in TGFBR2 and IL12B were associated with OS (P <10?³) solely in ER-negative patients after chemotherapy (267 events). Poorer OS associated with TGFBR2 rs1367610 (G > C) (per allele hazard ratio (HR) 1.54 (95% confidence interval (CI) 1.22 to 1.95), P = 3.08 × 10??) was not found in ER-negative patients without chemotherapy or ER-positive patients with chemotherapy (P for interaction <10-3). Two SNPs in IL12B (r² = 0.20) showed different associations with ER-negative disease after chemotherapy: rs2546892 (G > A) with poorer OS (HR 1.50 (95% CI 1.21 to 1.86), P = 1.81 × 10??), and rs2853694 (A > C) with improved OS (HR 0.73 (95% CI 0.61 to 0.87), P = 3.67 × 10??). Similar associations were observed with BCSS. Association with TGFBR2 rs1367610 but not IL12B variants replicated using BCAC Asian samples and the independent Prospective Study of Outcomes in Sporadic versus Hereditary Breast Cancer Study and yielded a combined HR of 1.57 ((95% CI 1.28 to 1.94), P = 2.05 × 10??) without study heterogeneity.TGFBR2 variants may have prognostic and predictive value in ER-negative breast cancer patients treated with adjuvant chemotherapy. Our findings provide further insights into the development of immunotherapeutic targets for ER-negative breast cancer.
EVALuna2:9270

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with risk of clear cell ovarian cancer - Hampras, Shalaka S.; Sucheston-Campbell, Lara E.; Cannioto, Rikki; Chang-Claude, Jenny; Modugno, Francesmary; Doerk, Thilo; Hillemanns, Peter; Preus, Leah; Knutson, Keith L.; Wallace, Paul K.; Hong, Chi-Chen; Friel, Grace; et al. (Oncotarget, 2016)
Regulatory T (Treg) cells, a subset of CD4+ T lymphocytes, are mediators of immunosuppression in cancer, and, thus, variants in genes encoding Treg cell immune molecules could be associated with ovarian cancer.In a population of 15,596 epithelial ovarian cancer (EOC) cases and 23,236 controls, we measured genetic associations of 1,351 SNPs in Treg cell pathway genes with odds of ovarian cancer and tested pathway and gene-level associations, overall and by histotype, for the 25 genes, using the admixture likelihood (AML) method. The most significant single SNP associations were tested for correlation with expression levels in 44 ovarian cancer patients.The most significant global associations for all genes in the pathway were seen in endometrioid (p = 0.082) and clear cell (p = 0.083), with the most significant gene level association seen with TGFBR2 (p = 0.001) and clear cell EOC. Gene associations with histotypes at p < 0.05 included: IL12 (p = 0.005 and p = 0.008, serous and high-grade serous, respectively), IL8RA (p = 0.035, endometrioid and mucinous), LGALS1 (p = 0.03, mucinous), STAT5B (p = 0.022, clear cell), TGFBR1 (p = 0.021 endometrioid) and TGFBR2 (p = 0.017 and p = 0.025, endometrioid and mucinous, respectively).Common inherited gene variation in Treg cell pathways shows some evidence of germline genetic contribution to odds of EOC that varies by histologic subtype and may be associated with mRNA expression of immune-complex receptor in EOC patients.
EVALuna2:9345

Association analysis identifies 65 new breast cancer risk loci - Michailidou, Kyriaki; Lindstrom, Sara; Dennis, Joe; Beesley, Jonathan; Hui, Shirley; Kar, Siddhartha; Lemacon, Audrey; Soucy, Penny; Glubb, Dylan; Rostamianfar, Asha; Bolla, Manjeet K.; Wang, Qin; et al. (Nature, 2017)
Breast cancer risk is influenced by rare coding variants in susceptibility genes, such as BRCA1, and many common, mostly non-coding variants. However, much of the genetic contribution to breast cancer risk remains unknown. Here we report the results of a genome-wide association study of breast cancer in 122,977 cases and 105,974 controls of European ancestry and 14,068 cases and 13,104 controls of East Asian ancestry. We identified 65 new loci that are associated with overall breast cancer risk at P < 5 × 10-8. The majority of credible risk single-nucleotide polymorphisms in these loci fall in distal regulatory elements, and by integrating in silico data to predict target genes in breast cells at each locus, we demonstrate a strong overlap between candidate target genes and somatic driver genes in breast tumours. We also find that heritability of breast cancer due to all single-nucleotide polymorphisms in regulatory features was 2-5-fold enriched relative to the genome-wide average, with strong enrichment for particular transcription factor binding sites. These results provide further insight into genetic susceptibility to breast cancer and will improve the use of genetic risk scores for individualized screening and prevention.
EVALuna2:9385

Association between breast cancer risk factors and molecular type in postmenopausal patients with hormone receptor-positive early breast cancer - Wunderle, Marius; Pretscher, Jutta; Brucker, Sara Y.; Volz, Bernhard; Hartmann, Arndt; Fießler, Cornelia; Hein, Alexander; Häberle, Lothar; Jud, Sebastian; Lux, Michael P.; Janni, Wolfgang; Löhberg, Christian; et al. (Breast Cancer Research and Treatment, 2019)
PurposeEvidence shows that genetic and non-genetic risk factors for breast cancer (BC) differ relative to the molecular subtype. This analysis aimed to investigate associations between epidemiological risk factors and immunohistochemical subtypes in a cohort of postmenopausal, hormone receptor-positive BC patients.MethodsThe prospective, single-arm, multicenter phase IV PreFace study (Evaluation of Predictive Factors Regarding the Effectivity of Aromatase Inhibitor Therapy) included 3529 postmenopausal patients with hormone receptor-positive early BC. Data on their epidemiological risk factors were obtained from patients' diaries and their medical histories. Data on estrogen receptor, progesterone receptor, and HER2 receptor status were obtained from pathology reports. Patients with incomplete information were excluded. Data were analyzed using conditional inference regression analysis, analysis of variance, and the chi-squared test.ResultsIn a cohort of 3392 patients, the strongest association with the molecular subtypes of BC was found for hormone replacement therapy (HRT) before diagnosis of early BC. The analysis showed that patients who took HRT at diagnosis had luminal A-like BC more often (83.7%) than those who had never taken HRT or had stopped taking it (75.5%). Luminal B-like BC and HER2-positive BC were diagnosed more often in women who had never taken HRT or had stopped taking it (13.3% and 11.2%, respectively) than in women who were taking HRT at diagnosis of BC (8.3% and 8.0%, respectively).ConclusionsThis analysis shows an association between HRT and the distribution of molecular subtypes of BC. However, no associations between other factors (e.g., age at diagnosis, body mass index, smoking status, age at menopause, number of deliveries, age at first delivery, breastfeeding history, or family history) were noted.
CRIS-Team WoS Importer:2019-03-29

Association between event-free survival and overall survival in early-stage triple-negative breast cancer - Huang, Min; Fasching, Peter; Haiderali, Amin; Xue, Weiguang; Pan, Wilbur; Karantza, Vassiliki; Yang, Fan; Truscott, James; Xin, Yiqiao; O'Shaughnessy, Joyce (Future Oncology, 2024)
Aim: This study evaluated event-free survival (EFS) as a surrogate outcome for overall survival (OS) in neoadjuvant therapy for early-stage triple-negative breast cancer (eTNBC). Methods: Meta-regression analyses based on a targeted literature review were used to evaluate the individual- and trial-level associations between EFS and OS. Results: In the individual-level analyses, 3-year EFS was a significant predictor of 5-year OS (p < 0.01; coefficient of determinations [R2]: 0.82 [95% CI: 0.68-0.91]). Additionally, there was a statistically significant association between the treatment effect on EFS and OS at the trial level (p < 0.001; R2: 0.64 [95% CI: 0.45-0.82]). Conclusion: This study demonstrates significant associations between EFS and OS and suggests that EFS is a valid surrogate for OS following neoadjuvant therapy for eTNBC.
EVALuna2:547163

Association between mammographic density and pregnancies relative to age and BMI: a breast cancer case-only analysis - Hack, Carolin; Emons, Julius; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Gaß, Paul; Haeberle, Lothar; Heindl, Felix; Hein, Alexander; Schulz-Wendtland, Rüdiger; Uder, Michael; Hartmann, Arndt; et al. (Breast Cancer Research and Treatment, 2017)
Percentage mammographic density (PMD) is a major risk factor for breast cancer (BC). It is strongly associated with body mass index (BMI) and age, which are themselves risk factors for breast cancer. This analysis investigated the association between the number of full-term pregnancies and PMD in different subgroups relative to age and BMI.Patients were identified in the breast cancer database of the University Breast Center for Franconia. A total of 2410 patients were identified, for whom information on parity, age, and BMI, and a mammogram from the time of first diagnosis were available for assessing PMD. Linear regression analyses were conducted to investigate the influence on PMD of the number of full-term pregnancies (FTPs), age, BMI, and interaction terms between them.As in previous studies, age, number of FTPs, and BMI were found to be associated with PMD in the expected direction. However, including the respective interaction terms improved the prediction of PMD even further. Specifically, the association between PMD and the number of FTPs differed in young patients under the age of 45 (mean decrease of 0.37 PMD units per pregnancy) from the association in older age groups (mean decrease between 2.29 and 2.39 PMD units). BMI did not alter the association between PMD and the number of FTPs.The effect of pregnancies on mammographic density does not appear to become apparent before the age of menopause. The mechanism that drives the effect of pregnancies on mammographic density appears to be counter-regulated by other influences on mammographic density in younger patients.
EVALuna2:14710

Association Between Obesity and Circulating Tumor Cells in Early Breast Cancer Patients - Tzschaschel, Marie; Friedl, Thomas W.P.; Schochter, Fabienne; Schütze, Sabine; Polasik, Arkadius; Fehm, Tanja; Pantel, Klaus; Schindlbeck, Christian; Schneeweiss, Andreas; Schreier, Jörg; Tesch, Hans; Lorenz, Ralf; et al. (Clinical Breast Cancer, 2023)
Background: Obesity and the presence of circulating tumor cells (CTCs) before and/or after chemotherapy are associated with poor outcome in breast cancer (BC) patients. The activation of oncogenic pathways in fatty tissue leads to cell proliferation, suggesting a possible link between obesity and CTCs. Materials and Methods: In the phase III SUCCESS A trial, 3754 patients with early BC were randomized to 3 cycles of fluorouracil, epirubicin and cyclophosphamide followed by 3 cycles of docetaxel with or without gemcitabine. Data of 1088 patients with CTC assessments (CellSearch-System; Menarini Silicon Biosystems, Italy) and body mass index (BMI) measurements both before and after chemotherapy were available. Patients were classified according to the WHO's international definitions as underweight, normal weight, overweight, or obese, and according to their weight-change during chemotherapy into a weight-loss group (> 5% decrease), stable-weight group (≤ 5% weight-change) or weight-gain group (>5% increase). Associations between CTC positivity and, BMI or weight-change group were analyzed using frequency-table methods. Results: At study entry, 47.4% patients were underweight or normal weight, 33.6% were overweight and 18.9% were obese. Before and after chemotherapy, CTCs were detected in 20.1% and 22.6% of patients, respectively. There was no association between CTC positivity and BMI before (P = 0.104) or after (P = 0.051) chemotherapy. Furthermore, there was no association between weight-change group and CTC status before/after chemotherapy (P = 0.332). Conclusions: According to our analysis, the risk factors obesity and prevalence of CTCs are not associated and may represent independent prognostic factors.
CRIS-Team Scopus Importer:2023-06-30
Keywords: CTCs; EBC; Overweight

Association of breast cancer risk with genetic variants showing differential allelic expression: Identification of a novel breast cancer susceptibility locus at 4q21 - Hamdi, Yosr; Soucy, Penny; Adoue, Veronique; Michailidou, Kyriaki; Canisius, Sander; Lemacon, Audrey; Droit, Arnaud; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Baynes, Caroline; Blomqvist, Carl; et al. (Oncotarget, 2016)
There are significant inter-individual differences in the levels of gene expression. Through modulation of gene expression, cis-acting variants represent an important source of phenotypic variation. Consequently, cis-regulatory SNPs associated with differential allelic expression are functional candidates for further investigation as disease-causing variants. To investigate whether common variants associated with differential allelic expression were involved in breast cancer susceptibility, a list of genes was established on the basis of their involvement in cancer related pathways and/or mechanisms. Thereafter, using data from a genome-wide map of allelic expression associated SNPs, 313 genetic variants were selected and their association with breast cancer risk was then evaluated in 46,451 breast cancer cases and 42,599 controls of European ancestry ascertained from 41 studies participating in the Breast Cancer Association Consortium. The associations were evaluated with overall breast cancer risk and with estrogen receptor negative and positive disease. One novel breast cancer susceptibility locus on 4q21 (rs11099601) was identified (OR = 1.05, P = 5.6x10-6). rs11099601 lies in a 135 kb linkage disequilibrium block containing several genes, including, HELQ, encoding the protein HEL308 a DNA dependant ATPase and DNA Helicase involved in DNA repair, MRPS18C encoding the Mitochondrial Ribosomal Protein S18C and FAM175A (ABRAXAS), encoding a BRCA1 BRCT domain-interacting protein involved in DNA damage response and double-strand break (DSB) repair. Expression QTL analysis in breast cancer tissue showed rs11099601 to be associated with HELQ (P = 8.28x10-14), MRPS18C (P = 1.94x10-27) and FAM175A (P = 3.83x10-3), explaining about 20%, 14% and 1%, respectively of the variance inexpression of these genes in breast carcinomas.
EVALuna2:33314

Association of CA27.29 and Circulating Tumor Cells Before and at Different Times After Adjuvant Chemotherapy in Patients with Early-stage Breast Cancer - The SUCCESS Trial - Hepp, Philip; Andergassen, Ulrich; Jaezger, Bernadette; Trapp, Elisabeth; Alunni-Fabbroni, Marianna; Friedl, Thomas W. P.; Hecker, Nadeschda; Lorenz, Ralf; Fasching, Peter; Schneeweiss, Andreas; Fehm, Tanja; Janni, Wolfgang; et al. (Anticancer Research, 2016)
BACKGROUND: Evidence for the prognostic value of circulating tumor cells (CTCs) in early-stage breast cancer is swiftly increasing. An alternative approach for identifying patients at risk for recurrence is based on the detection of the mucin-1 (MUC1)-based tumor marker CA27.29. Here we report the association of these two prognostic markers before and immediately after chemotherapy (CHT), as well as after 2 and 5 years of follow-up. PATIENTS AND METHODS: The SUCCESS trial compared fluorouracil, epirubicin and cyclophosphamide followed by docetaxel vs. FEC followed by docetaxel plus gemcitabine, and 2 vs. 5 years of treatment with zoledronic acid in 3,754 patients with node-positive or high-risk node-negative early-stage breast cancer. CA27.29 was measured with the ST AIA-PACK CA27.29 reagent (Tosoh Bioscience, Belgium). The cutoff for CA27.29 positivity was >31 U/ml. CTCs were assessed with the CellSearch System (Veridex, USA). The cutoff for CTC positivity was ≥1 CTC/15 ml whole blood. The relationship between CTC positivity and CA27.29 positivity was assessed based on Chi-square statistics and Cramer's V, which varies from 0 (no association between the variables) to 1 (complete association). Samples for CA27.29 and CTC determinations during follow-up were only drawn from patients that had no relapse. RESULTS: Both CA27.29 and CTC data were available for 1,981, 1,602, 1,159 and 707 patients before, immediately after and at 2 and 5 years after CHT, respectively. Positivity rates for CTC were 21.3%, 22.8%, 18.6% and 8.5%, respectively. CA27.29 was positive in 7.9%, 21.0%, 2.8%and 7.5%, respectively. Positivity for both CA27.29 and CTC was found in 2.4%, 4.2%, 0.7% and 1.8% of patients, respectively. The association between CA27.29 and CTC was significant but weak before CHT (p=0.0015; Cramer's V=0.063) and 5 years after CHT (p<0.001; Cramer's V=0.164), and not significant immediately after CHT (p=0.162; Cramer's V=0.035) and 2 years after (p=0.349; Cramer's V=0.028). CONCLUSION: We showed that CTC and CA27.29 positivity were significantly, but only weakly associated before CHT and 5 years after CHT, while no significant association was found immediately or 2 years after CHT during the course of early-stage breast cancer. It, therefore, seems reasonable to further evaluate the prognostic value of CTCs and CA27.29 as a combined prognostic test of two potentially independent markers that might provide complementary prognostic information.
EVALuna2:33535

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhao, Zhiguo; Wen, Wanqing; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Zhang, Ben; Long, Jirong; Shu, Xiao-Ou; Schmidt, Marjanka K.; Milne, Roger L.; Garcia-Closas, Montserrat; Chang-Claude, Jenny; et al. (Cancer Causes & Control, 2016)
PURPOSE: Type 2 diabetes (T2D) has been reported to be associated with an elevated risk of breast cancer. It is unclear, however, whether this association is due to shared genetic factors. METHODS: We constructed a genetic risk score (GRS) using risk variants from 33 known independent T2D susceptibility loci and evaluated its relation to breast cancer risk using the data from two consortia, including 62,328 breast cancer patients and 83,817 controls of European ancestry. Unconditional logistic regression models were used to derive adjusted odds ratios (ORs) and 95 % confidence intervals (CIs) to measure the association of breast cancer risk with T2D GRS or T2D-associated genetic risk variants. Meta-analyses were conducted to obtain summary ORs across all studies. RESULTS: The T2D GRS was not found to be associated with breast cancer risk, overall, by menopausal status, or for estrogen receptor positive or negative breast cancer. Three T2D associated risk variants were individually associated with breast cancer risk after adjustment for multiple comparisons using the Bonferroni method (at p < 0.001), rs9939609 (FTO) (OR 0.94, 95 % CI = 0.92-0.95, p = 4.13E-13), rs7903146 (TCF7L2) (OR 1.04, 95 % CI = 1.02-1.06, p = 1.26E-05), and rs8042680 (PRC1) (OR 0.97, 95 % CI = 0.95-0.99, p = 8.05E-04). CONCLUSIONS: We have shown that several genetic risk variants were associated with the risk of both T2D and breast cancer. However, overall genetic susceptibility to T2D may not be related to breast cancer risk.
EVALuna2:32983

Association of genomic variants at PAX8 and PBX2 with cervical cancer risk - Ramachandran, Dhanya; Wang, Yingying; Schuermann, Peter; Huelse, Fabienne; Mao, Qianqian; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; Hirchenhain, Christine; Schmidmayr, Monika; Mueller, Florian; Runnebaum, Ingo; et al. (International Journal of Cancer, 2021)
Cervical malignancy is triggered by human papillomavirus infection but the risk for cervical cancer has a hereditary component. From a recent Genome Wide Association Study meta-analysis, 2q14.1 (PAX8) and 6p21.32 (PBX2) have been proposed as novel cervical cancer susceptibility loci. We investigated the two main signals at these loci in an independent case-control series of 2578 cases with cervical dysplasia or carcinoma and 1483 healthy females. We find significant associations for both variants, rs10175462 at PAX8 and rs2856437 at PBX2, with overall cervical disease (rs10175462: odds ratio [OR] 0.82, 95% confidence interval [CI] 0.74-0.91, P = 2.4 × 10−4; rs2856437: OR 1.52, 95% CI 1.14-2.02, P =.004). Both variants showed evidence of association with invasive squamous cervical cancer (rs10175462: OR 0.80, 95% CI 0.68-0.94, P =.006; rs2856437: OR 1.56, 95% CI 1.03-2.36, P =.036) and with high-grade dysplasia (rs10175462: OR 0.79, 95%CI 0.70-0.90, P = 1.9 × 10−4; rs2856437: OR 1.58, 95% CI 1.15-2.17, P =.005). A combined analysis of high-grade dysplasia and invasive cervical cancer also showed significant associations for both variants (rs10175462: OR 0.81, 95% CI 0.73-0.91, P = 2.4 × 10−4; rs2856437: OR 1.57, 95% CI 1.18-2.10, P =.002). No association was detected for rs2856437 with low-grade dysplasia, while rs10175462 showed weak evidence of association (P =.05). RNA analyses in cervical samples revealed that PAX8 transcripts were upregulated in HPV-positive lesions (P =.008) but this was not observed in the presence of the protective minor allele of rs10175462. The rs10175462 genotype also correlated with reduced levels of the lncRNA PAX8-AS1 (P <.001). Taken together, our results extend the evidence for a link between genomic risk variants at the HLA region (PBX2) with cervical disease and support PAX8 as the first consistent non-HLA cervical cancer susceptibility locus.
CRIS-Team Scopus Importer:2021-05-21
Keywords: association study; cervical malignancy; eQTL; HPV infection; single nucleotide polymorphism

Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk,HPVstatus and gene expression levels - Ramachandran, Dhanya; Schuermann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa-Marie; Speith, Lisa-Marie; Huelse, Fabienne; Enssen, Julia; Bousset, Kristine; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; et al. (International Journal of Cancer, 2020)
The human leukocyte antigen (HLA) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single-nucleotide polymorphisms in a large case-control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 atHLA-DQA1and rs2844511 atMICAandHCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79-0.99,P= .036; rs2844511: OR 1.17, 95% CI 1.04-1.31,P= .008) and with high-grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70-0.87,P= 7.1 x 10(-6); rs2844511: OR 1.13, 95% CI 1.01-1.26,P= .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75-0.91,P= 6.9 x 10(-5); rs2844511: OR 1.14, 95% CI 1.04-1.26,P= .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low-grade dysplasia (OR 1.26, 95% CI 1.04-1.54,P= .019). In case-only analyses, rs2844511 tended to predict HPV status (P= .044) and rs9272117 tended to associate with HPV16 (P= .022). RNA studies in cervical samples showed a significant correlation in the transcript levels ofMICA,HCP5andHLA-DQA1, suggesting extensive co-regulation. All three genes were upregulated in HPV16-positive samples. In stratified analyses, rs9272117 was associated withHLA-DQA1levels, specifically in HPV-positive samples, while rs2844511 was associated withMICAandHCP5levels. The risk allele of rs2844511 was required for correlations betweenMICAorHCP5withHLA-DQA1. Altogether, our results support 6p21.32-33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels ofHLA-DQA1,HCP5andMICA, which may contribute to tumor immune evasion.
CRIS-Team WoS Importer:2020-07-24

Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L.; Augustinsson, Annelie; Freeman, Laura E. Beane; et al. (BREAST CANCER RES, 2021)
Background Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients. Methods We performed genome-wide association analyses within 15 subgroups of breast cancer patients based on prognostic factors, including hormone receptors, tumor grade, age, and type of systemic treatment. Analyses were based on 91,686 female patients of European ancestry from the Breast Cancer Association Consortium, including 7531 breast cancer-specific deaths over a median follow-up of 8.1 years. Cox regression was used to assess associations of common germline variants with 15-year and 5-year breast cancer-specific survival. We assessed the probability of these associations being true positives via the Bayesian false discovery probability (BFDP < 0.15). Results Evidence of associations with breast cancer-specific survival was observed in three patient subgroups, with variant rs5934618 in patients with grade 3 tumors (15-year-hazard ratio (HR) [95% confidence interval (CI)] 1.32 [1.20, 1.45], P = 1.4E-08, BFDP = 0.01, per G allele); variant rs4679741 in patients with ER-positive tumors treated with endocrine therapy (15-year-HR [95% CI] 1.18 [1.11, 1.26], P = 1.6E-07, BFDP = 0.09, per G allele); variants rs1106333 (15-year-HR [95% CI] 1.68 [1.39,2.03], P = 5.6E-08, BFDP = 0.12, per A allele) and rs78754389 (5-year-HR [95% CI] 1.79 [1.46,2.20], P = 1.7E-08, BFDP = 0.07, per A allele), in patients with ER-negative tumors treated with chemotherapy. Conclusions We found evidence of four loci associated with breast cancer-specific survival within three patient subgroups. There was limited evidence for the existence of associations in other patient subgroups. However, the power for many subgroups is limited due to the low number of events. Even so, our results suggest that the impact of common germline genetic variants on breast cancer-specific survival might be limited.
CRIS-Team WoS Importer:2021-09-03

Association of Germline Variant Status with Therapy Response in High-risk Early-Stage Breast Cancer: A Secondary Analysis of the GeparOcto Randomized Clinical Trial - Pohl-Rescigno, Esther; Hauke, Jan; Loibl, Sibylle; Möbus, Volker; Denkert, Carsten; Fasching, Peter; Kayali, Mohamad; Ernst, Corinna; Weber-Lassalle, Nana; Hanusch, Claus; Tesch, Hans; Müller, Volkmar; et al. (JAMA Oncology, 2020)
Importance: The GeparOcto randomized clinical trial compared the efficacy of 2 neoadjuvant breast cancer (BC) treatment regimens: Sequential intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) vs weekly paclitaxel and nonpegylated liposomal doxorubicin (PM) in patients with different biological BC subtypes. Patients with triple-negative BC (TNBC) randomized to the PM arm received additional carboplatin (PMCb). Overall, no difference in pathologic complete response (PCR) rates was observed between study arms. It remained elusive whether the germline variant status of BRCA1/2 and further BC predisposition genes are associated with treatment outcome. Objective: To determine treatment outcome for BC according to germline variant status. Design, Setting, and Participants: This retrospective biomarker study is a secondary analysis of the GeparOcto multicenter prospective randomized clinical trial conducted between December 2014 and June 2016. Genetic analyses assessing for variants in BRCA1/2 and 16 other BC predisposition genes in 914 of 945 women were performed at the Center for Familial Breast and Ovarian Cancer, Cologne, Germany, from August 2017 through December 2018. Main Outcomes and Measures: Proportion of patients who achieved PCR (ypT0/is ypN0 definition) after neoadjuvant treatment according to germline variant status. Results: In the study sample of 914 women with different BC subtypes with a mean (range) age at BC diagnosis of 48 (21-76) years, overall higher PCR rates were observed in patients with BRCA1/2 variants than in patients without (60.4% vs 46.7%; odds ratio [OR], 1.74; 95% CI, 1.13-2.68; P =.01); variants in non-BRCA1/2 BC predisposition genes were not associated with therapy response. Patients with TNBC with BRCA1/2 variants achieved highest PCR rates. In the TNBC subgroup, a positive BRCA1/2 variant status was associated with therapy response in both the PMCb arm (74.3% vs 47.0% without BRCA1/2 variant; OR, 3.26; 95% CI, 1.44-7.39; P =.005) and the iddEPC arm (64.7% vs 45.0%; OR, 2.24; 95% CI, 1.04-4.84; P =.04). A positive BRCA1/2 variant status was also associated with elevated PCR rates in patients with ERBB2-negative, hormone receptor-positive BC (31.8% vs 11.9%; OR, 3.44; 95% CI, 1.22-9.72; P =.02). Conclusions and Relevance: Effective chemotherapy for BRCA1/2-mutated TNBC is commonly suggested to be platinum based. With a PCR rate of 64.7%, iddEPC may also be effective in these patients, though further prospective studies are needed. The elevated PCR rate in BRCA1/2-mutated ERBB2-negative, hormone receptor-positive BC suggests that germline BRCA1/2 testing should be considered prior to treatment start. Trial Registration: ClinicalTrials.gov Identifier: NCT02125344.
CRIS-Team Scopus Importer:2020-03-27

Association of Maternal Smoking during Pregnancy with Neurophysiological and ADHD-Related Outcomes in School-Aged Children - Jansone, Karina; Eichler, Anna; Fasching, Peter; Kornhuber, Johannes; Kaiser, Anna; Millenet, Sabina; Banaschewski, Tobias; Nees, Frauke; On Behalf Of The Imac-Mind Consortium, (International Journal of Environmental Research and Public Health, 2023)
Data of a longitudinal cohort study were analyzed to investigate the association between prenatal tobacco exposure and electroencephalographical (EEG) power spectrum in healthy, school-aged children as well as its relationship with attention deficit hyperactivity disorder (ADHD)-related symptoms. Group comparisons (exposed, non-exposed) were performed to test whether prenatal tobacco exposure was associated with brain activity and ADHD symptoms, with adjustments made for covariates including child's sex, child's age, maternal age, maternal smoking habit before pregnancy, alcohol consumption during pregnancy, gestation age, and maternal psychopathology. Tobacco-exposed children showed higher brain activity in the delta and theta frequency bands. This effect was independent of the considered covariates. However, the effects on hyperactivity were found to significantly depend on maternal age and alcohol consumption during pregnancy, but not on the amount of exposure. In summary, smoking during pregnancy significantly affected the resting-state brain activity in children, independent of socio-demographic factors, indicating potential long-lasting effects on brain development. Its impact on ADHD-related behavior was shown to be influenced by socio-demographic confounding factors, such as maternal alcohol consumption and the age of the mother.
CRIS-Team Scopus Importer:2023-04-07
Keywords: ADHD; EEG; hyperactivity; maternal smoking; pregnancy; resting-state brain activity

Association of molecular subtypes with breast cancer risk factors: a case-only analysis - Rauh, Claudia; Gaß, Paul; Heusinger, Katharina; Haeberle, Lothar; Jud, Sebastian; Hein, Alexander; Löhberg, Christian; Lux, Michael P.; Wachter, David; Heimrich, Jutta; Strehl, Johanna D.; Haller, Florian; et al. (European Journal of Cancer Prevention, 2015)
As breast cancer (BC) screening identifies many BCs with a good prognosis, which might be overdiagnosed and therefore overtreated, the identification of subgroups with a high risk for aggressive subtypes might be helpful. The aim of this case-case analysis was to investigate the association between epidemiological risk factors and molecular subtypes in a cohort of BC patients. Epidemiological risk factors for 2587 BC patients were obtained using a structured questionnaire and from the patients' charts. The histopathological information (estrogen and progesterone receptor, HER2 and Ki-67) used in the analysis was retrieved from the original pathology reports. Analyses using conditional inference regression trees were carried out on these data. The strongest influence factor on the distribution of the molecular subtypes was age at first diagnosis of BC. An influence of BMI was also identified in patients aged either more than 42 years or 49.6 years or less. Older patients aged more than 49.6 years and perimenopausal women with a BMI of 32.4 kg/m or less were most likely to develop luminal A-like BC. Young patients aged 42 years or less and perimenopausal patients with a BMI more than 32.4 kg/m more often developed triple-negative BC. The study confirmed that age at diagnosis is an important factor influencing the distribution of molecular subtypes. In the perimenopausal group, it may be postulated that BMI plays a critical role in the pathogenesis of BC, defining a subgroup that is more likely to develop triple-negative BC or luminal B-like disease and another group in which there is a more postmenopausal distribution pattern.
EVALuna2:5482

Association of p16 expression with prognosis varies across ovarian carcinoma histotypes: an Ovarian Tumor Tissue Analysis consortium study - Rambau, Peter F.; Vierkant, Robert A.; Intermaggio, Maria P.; Kelemen, Linda E.; Goodman, Marc T.; Herpel, Esther; Pharoah, Paul D.; Kommoss, Stefan; Jimenez-Linan, Mercedes; Karlan, Beth Y.; Gentry-Maharaj, Aleksandra; Menon, Usha; et al. (Journal of Pathology: Clinical Research, 2018)
We aimed to validate the prognostic association of p16 expression in ovarian high-grade serous carcinomas (HGSC) and to explore it in other ovarian carcinoma histotypes. p16 protein expression was assessed by clinical-grade immunohistochemistry in 6525 ovarian carcinomas including 4334 HGSC using tissue microarrays from 24 studies participating in the Ovarian Tumor Tissue Analysis consortium. p16 expression patterns were interpreted as abnormal (either overexpression referred to as block expression or absence) or normal (heterogeneous). CDKN2A (which encodes p16) mRNA expression was also analyzed in a subset (n = 2280) mostly representing HGSC (n = 2010). Association of p16 expression with overall survival (OS) was determined within histotypes as was CDKN2A expression for HGSC only. p16 block expression was most frequent in HGSC (56%) but neither protein nor mRNA expression was associated with OS. However, relative to heterogeneous expression, block expression was associated with shorter OS in endometriosis-associated carcinomas, clear cell [hazard ratio (HR): 2.02, 95% confidence (CI) 1.47-2.77, p < 0.001] and endometrioid (HR: 1.88, 95% CI 1.30-2.75, p = 0.004), while absence was associated with shorter OS in low-grade serous carcinomas (HR: 2.95, 95% CI 1.61-5.38, p = 0.001). Absence was most frequent in mucinous carcinoma (50%), and was not associated with OS in this histotype. The prognostic value of p16 expression is histotype-specific and pattern dependent. We provide definitive evidence against an association of p16 expression with survival in ovarian HGSC as previously suggested. Block expression of p16 in clear cell and endometrioid carcinoma should be further validated as a prognostic marker, and absence in low-grade serous carcinoma justifies CDK4 inhibition.
EVALuna2:50246

Association of Pathologic Complete Response with Long-Term Survival Outcomes in Triple-Negative Breast Cancer: A Meta-Analysis - Huang, Min; O'Shaughnessy, Joyce; Zhao, Jing; Haiderali, Amin; Cortes, Javier; Ramsey, Scott D.; Briggs, Andrew; Hu, Peter; Karantza, Vassiliki; Aktan, Gursel; Qi, Cynthia Z.; Gu, Chenyang; et al. (Cancer Research, 2020)
Pathologic complete response (pCR) following neoadjuvant therapy has been associated with improved event-free survival (EFS) and overall survival (OS) in early-stage breast cancer. The magnitude of this association varies by breast cancer subtype, yet further research focusing on subtype-specific populations is limited. Here we provide an updated and comprehensive evaluation of the association between pCR and survival outcomes in triple-negative breast cancer (TNBC). A literature review identified neoadjuvant studies, including clinical trials, real-world cohort studies, and studies that pooled multiple trials or cohorts, which reported EFS/OS results by pCR in patients with early-stage TNBC. Meta-analyses were performed to evaluate the association between pCR and EFS/OS and to predict long-term survival outcomes based on pCR status. Sensitivity analyses were conducted to assess the impact of cross-study variations. Twenty-five studies with over 4,000 patients with TNBC were identified. A synthesis of evidence from these studies suggested substantial improvement in EFS and OS for pCR versus non-pCR [EFS HR (95% confidence interval): 0.24 (0.20-0.29); OS: 0.19 (0.15-0.24)]; consistent results were reported in sensitivity analyses. Collectively, our findings suggest that adjuvant therapy is associated with improved EFS/OS in patients with TNBC who received neoadjuvant therapy, regardless of pCR status.
CRIS-Team WoS Importer:2021-01-29

Association of prenatal alcohol exposure and prenatal maternal depression with offspring low-grade inflammation in early adolescence - Maschke, Janina; Roetner, Jakob; Bösl, Sophia; Plank, Anne-Christine; Rohleder, Nicolas; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; et al. (International Journal of Environmental Research and Public Health, 2021)
(1) This longitudinal study aimed to investigate the link between prenatal alcohol exposure and prenatal maternal depression with the offspring’s low-grade inflammatory status. (2) Prenatal alcohol exposure was determined via maternal self-report during the 3rd trimester of pregnancy (self-report+: n = 29) and the meconium alcohol metabolite Ethyl Glucuronide (EtG), collected at birth (≥30 ng/g: n = 23). The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for prenatal maternal depressive symptoms during the 3rd trimester (≥10: n = 35). Fifteen years later, 122 adolescents (M = 13.32 years; 48.4% female) provided blood samples for the analysis of high sensitivity C-reactive protein (hsCRP; M = 0.91; SD = 1.28). (3) Higher hsCRP levels were found in EtG positive adolescents (p = 0.036, ηp2 = 0.04) and an inverse non-significant dose–response relation with hsCRP (r = −0.35, p = 0.113). For maternal self-reported prenatal alcohol consumption (p = 0.780, ηp2 = 0.00) and prenatal depressive symptoms (p = 0.360, ηp2 = 0.01) no differences for hsCRP levels between the affected and unaffected groups were found. (4) Adolescents with prenatal alcohol exposure are at risk for low-grade systemic inflammation. The EtG biomarker may be more accurate compared to self-reports. The findings suggest that prenatal maternal depression does not evoke low-grade systemic inflammation.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Early adolescence; High-sensitivity C-reactive protein (hsCRP); Low-grade systemic inflammation; Maternal self-report; Meconium ethyl glucuronide (EtG); Pregnancy; Prenatal alcohol exposure (PAE); Prenatal depression

Association of quality of life (QOL) with overall survival (OS) in patients (pts) with HR+/HER2-advanced breast cancer (ABC) treated with ribociclib (RIB) plus endocrine therapy (ET) in the MONALEESA-3 (ML-3) and ML-7 trials - Fasching, Peter; Harbeck, N.; Jerusalem, G.; Colleoni, M. A.; Neven, P.; Franke, F.; De Laurentiis, M.; Tripathy, D.; Martin, M.; Babu, G.; Yardley, D.; Wheatley-Price, P.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Association of RAD51 with homologous recombination deficiency (HRD) and clinical outcomes in untreated triple-negative breast cancer (TNBC): analysis of the GeparSixto randomized clinical trial - Llop-Guevara, A.; Loibl, S.; Villacampa, G.; Vladimirova, V.; Schneeweiss, A.; Karn, T.; Zahm, D. M.; Herencia-Ropero, A.; Jank, P.; van Mackelenbergh, M.; Fasching, Peter; Marmé, F.; et al. (Annals of Oncology, 2021)
Background: Current genetic and genomic tests measuring homologous recombination deficiency (HRD) show limited predictive value. This study compares the performance of an immunohistology-based RAD51 test with genetic/genomic tests to identify patients with HRD primary triple-negative breast cancer (TNBC) and evaluates its accuracy to select patients sensitive to platinum-based neoadjuvant chemotherapy (NACT). Patients and methods: This is a retrospective, blinded, biomarker analysis from the GeparSixto randomized clinical trial. TNBC patients received neoadjuvant paclitaxel plus Myocet®-nonpegylated liposomal doxorubicin (PM) or PM plus carboplatin (PMCb), both arms including bevacizumab. Formalin-fixed paraffin-embedded (FFPE) tumor samples were laid on tissue microarrays. RAD51, BRCA1 and γH2AX were quantified using an immunofluorescence assay. The predictive value of RAD51 was assessed by regression models. Concordance analyses were carried out between RAD51 score and tumor BRCA (tBRCA) status or genomic HRD score (Myriad myChoice®). Associations with pathological complete response (pCR) and survival were studied. Functional HRD was predefined as a RAD51 score ≤10% (RAD51-low). Results: Functional HRD by RAD51-low was evidenced in 81/133 tumors (61%). RAD51 identified 93% tBRCA-mutated tumors and 45% non-tBRCA mutant cases as functional HRD. The concordance between RAD51 and genomic HRD was 87% [95% confidence interval (CI) 79% to 93%]. In patients with RAD51-high tumors, pCR was similar between treatment arms [PMCb 31% versus PM 39%, odds ratio (OR) 0.71, 0.23-2.24, P = 0.56]. Patients with RAD51-low tumors benefited from PMCb (pCR 66% versus 33%, OR 3.96, 1.56-10.05, P = 0.004; interaction test P = 0.02). This benefit maintained statistical significance in the multivariate analysis. Carboplatin addition showed similar disease-free survival in the RAD51-high [hazard ratio (HR) 0.40, log-rank P = 0.11] and RAD51-low (0.45, P = 0.11) groups. Conclusions: The RAD51 test identifies tumors with functional HRD and is highly concordant with tBRCA mutation and genomic HRD. RAD51 independently predicts clinical benefit from adding Cb to NACT in TNBC. Our results support further development to incorporate RAD51 testing in clinical decision-making.
CRIS-Team Scopus Importer:2021-10-22
Keywords: BRCA1; BRCA2; HRD biomarkers; personalized medicine; platinum-based neoadjuvant chemotherapy; RAD51; triple-negative breast cancer

Association of RAD51 with homologous recombination deficiency (HRD) and clinical outcomes in untreated triple-negative breast cancer (TNBC): Analysis of the GeparSixto randomized clinical trial - Llop-Guevara, A.; Vladimirova, V.; Schneeweiss, A.; Villacampa, G.; Karn, T.; Zahm, D-M.; Herencia-Ropero, A.; Jank, P.; Van Mackelenbergh, M.; Fasching, Peter; Marme, F.; Stickeler, E.; et al. (Annals of Oncology, 2021)
CRIS-Team WoS Importer:2021-05-28

Association of the CHEK2 c.1100delC variant, radiotherapy, and systemic treatment with contralateral breast cancer risk and breast cancer-specific survival. - Morra, Anna; Schreurs, Maartje A.C.; Andrulis, Irene L.; Anton-Culver, Hoda; Augustinsson, Annelie; Beckmann, Matthias; Behrens, Sabine; Bojesen, Stig E.; Bolla, Manjeet K.; Brauch, Hiltrud; Broeks, Annegien; Buys, Saundra S.; et al. (Cancer Medicine, 2023)
BACKGROUND: Breast cancer (BC) patients with a germline CHEK2 c.1100delC variant have an increased risk of contralateral BC (CBC) and worse BC-specific survival (BCSS) compared to non-carriers. AIM: To assessed the associations of CHEK2 c.1100delC, radiotherapy, and systemic treatment with CBC risk and BCSS. METHODS: Analyses were based on 82,701 women diagnosed with a first primary invasive BC including 963 CHEK2 c.1100delC carriers; median follow-up was 9.1 years. Differential associations with treatment by CHEK2 c.1100delC status were tested by including interaction terms in a multivariable Cox regression model. A multi-state model was used for further insight into the relation between CHEK2 c.1100delC status, treatment, CBC risk and death. RESULTS: There was no evidence for differential associations of therapy with CBC risk by CHEK2 c.1100delC status. The strongest association with reduced CBC risk was observed for the combination of chemotherapy and endocrine therapy [HR (95% CI): 0.66 (0.55-0.78)]. No association was observed with radiotherapy. Results from the multi-state model showed shorter BCSS for CHEK2 c.1100delC carriers versus non-carriers also after accounting for CBC occurrence [HR (95% CI): 1.30 (1.09-1.56)]. CONCLUSION: Systemic therapy was associated with reduced CBC risk irrespective of CHEK2 c.1100delC status. Moreover, CHEK2 c.1100delC carriers had shorter BCSS, which appears not to be fully explained by their CBC risk.
EVALuna2:539549

Association of two genomic variants with HPV type-specific risk of cervical cancer - Seifert, Finja; Eisenblätter, Rieke; Beckmann, Julia; Schürmann, Peter; Hanel, Patricia; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Fasching, Peter; et al. (Tumour Virus Research, 2023)
Problem: Human papillomavirus infection is integral to developing invasive cervical cancer in the majority of patients. In a recent genome-wide association study, rs9357152 and rs4243652 have been associated with seropositivity for HPV16 or HPV18, respectively. It is unknown whether these variants also associate with cervical cancer triggered by either HPV16 or HPV18. Methods: We investigate whether the two HPV susceptibility variants show association with type-specific cervical cancer in a genetic case-control study with cases stratified by HPV16 or HPV18, respectively. We further tested whether rs9357152 modulates gene expression of any of 36 genes at the human leukocyte antigen locus in 256 cervical tissues. Results: rs9357152 was associated with invasive HPV16-positive cervical cancer (OR 1.33, 95%CI 1.03–1.70, p = 0.03), and rs4243652 was associated with HPV18-positive adenocarcinomas (OR 2.96, 95%CI 1.18–7.41, p = 0.02). These associations remained borderline significant after testing against different sets of controls. rs9357152 was found to be an eQTL for HLA-DRB1 in HPV-positive cervical tissues (pANOVA = 0.0009), with the risk allele lowering mRNA levels. Conclusions: We find evidence that HPV seropositivity variants at chromosome 6 and 14 may modulate type-specific cervical cancer risk. rs9357152 may exert its effect through regulating HLA-DRB1 induction in the presence of HPV. In regard of multiple testing, these results need to be confirmed in larger studies.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Association study; eQTL; HPV infection; Human leukocyte antigen; Single nucleotide polymorphism; VASH1

Associations between genetically predicted circulating protein concentrations and endometrial cancer risk - Zhu, Jingjing; O’mara, Tracy A.; Liu, Duo; Setiawan, Veronica Wendy; Glubb, Dylan; Spurdle, Amanda B.; Fasching, Peter; Lambrechts, Diether; Buchanan, Daniel; Kho, Pik Fang; Cook, Linda S.; Friedenreich, Christine; et al. (Cancers, 2021)
Endometrial cancer (EC) is the leading female reproductive tract malignancy in developed countries. Currently, genome-wide association studies (GWAS) have identified 17 risk loci for EC. To identify novel EC-associated proteins, we used previously reported protein quantitative trait loci for 1434 plasma proteins as instruments to evaluate associations between genetically predicted circulating protein concentrations and EC risk. We studied 12,906 cases and 108,979 controls of European descent included in the Endometrial Cancer Association Consortium, the Epidemiology of Endometrial Cancer Consortium, and the UK Biobank. We observed associations between genetically predicted concentrations of nine proteins and EC risk at a false discovery rate of <0.05 (p-values range from 1.14 × 10−10 to 3.04 × 10−4). Except for vascular cell adhesion protein 1, all other identified proteins were independent from known EC risk variants identified in EC GWAS. The respective odds ratios (95% confidence intervals) per one standard deviation increase in genetically predicted circulating protein concentrations were 1.21 (1.13, 1.30) for DNA repair protein RAD51 homolog 4, 1.27 (1.14, 1.42) for desmoglein-2, 1.14 (1.07, 1.22) for MHC class I polypeptide-related sequence B, 1.05 (1.02, 1.08) for histo-blood group ABO system transferase, 0.77 (0.68, 0.89) for intestinal-type alkaline phosphatase, 0.82 (0.74, 0.91) for carbohydrate sulfotransferase 15, 1.07 (1.03, 1.11) for D-glucuronyl C5-epimerase, and 1.07 (1.03, 1.10) for CD209 antigen. In conclusion, we identified nine potential EC-associated proteins. If validated by additional studies, our findings may contribute to understanding the pathogenesis of endometrial tumor development and identifying women at high risk of EC along with other EC risk factors and biomarkers.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Endometrial cancer; Genetic instrument; Protein biomarker; Risk

Associations of a Breast Cancer Polygenic Risk Score With Tumor Characteristics and Survival - Lopes Cardozo, Josephine M.N.; Andrulis, Irene L.; Bojesen, Stig E.; Dörk, Thilo; Eccles, Diana M.; Fasching, Peter; Hooning, Maartje J.; Keeman, Renske; Nevanlinna, Heli; Rutgers, Emiel J.T.; Easton, Douglas F.; Hall, Per; et al. (Journal of Clinical Oncology, 2023)
PURPOSE: A polygenic risk score (PRS) consisting of 313 common genetic variants (PRS313) is associated with risk of breast cancer and contralateral breast cancer. This study aimed to evaluate the association of the PRS313 with clinicopathologic characteristics of, and survival following, breast cancer. METHODS: Women with invasive breast cancer were included, 98,397 of European ancestry and 12,920 of Asian ancestry, from the Breast Cancer Association Consortium (BCAC), and 683 women from the European MINDACT trial. Associations between PRS313 and clinicopathologic characteristics, including the 70-gene signature for MINDACT, were evaluated using logistic regression analyses. Associations of PRS313 (continuous, per standard deviation) with overall survival (OS) and breast cancer-specific survival (BCSS) were evaluated with Cox regression, adjusted for clinicopathologic characteristics and treatment. RESULTS: The PRS313 was associated with more favorable tumor characteristics. In BCAC, increasing PRS313 was associated with lower grade, hormone receptor-positive status, and smaller tumor size. In MINDACT, PRS313 was associated with a low risk 70-gene signature. In European women from BCAC, higher PRS313 was associated with better OS and BCSS: hazard ratio (HR) 0.96 (95% CI, 0.94 to 0.97) and 0.96 (95% CI, 0.94 to 0.98), but the association disappeared after adjustment for clinicopathologic characteristics (and treatment): OS HR, 1.01 (95% CI, 0.98 to 1.05) and BCSS HR, 1.02 (95% CI, 0.98 to 1.07). The results in MINDACT and Asian women from BCAC were consistent. CONCLUSION: An increased PRS313 is associated with favorable tumor characteristics, but is not independently associated with prognosis. Thus, PRS313 has no role in the clinical management of primary breast cancer at the time of diagnosis. Nevertheless, breast cancer mortality rates will be higher for women with higher PRS313 as increasing PRS313 is associated with an increased risk of disease. This information is crucial for modeling effective stratified screening programs.
CRIS-Team Scopus Importer:2023-04-07

Associations of obesity and circulating insulin and glucose with breast cancer risk: a Mendelian randomization analysis - Shu, Xiang; Wu, Lang; Khankari, Nikhil K.; Shu, Xiao-Ou; Wang, Thomas J.; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Milne, Roger L.; Schmidt, Marjanka K.; Pharoah, Paul D. P.; et al. (International Journal of Epidemiology, 2019)
Background: In addition to the established association between general obesity and breast cancer risk, central obesity and circulating fasting insulin and glucose have been linked to the development of this common malignancy. Findings from previous studies, however, have been inconsistent, and the nature of the associations is unclear.
CRIS-Team WoS Importer:2019-10-08

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Heinrich, Hartmut; et al. (Development and Psychopathology, 2018)

Associations of prenatal depressive symptoms with DNA methylation of HPA axis-related genes and diurnal cortisol profiles in primary school-aged children - Stonawski, Valeska; Frey, Stefan; Golub, Yulia; Rohleder, Nicolas; Kriebel, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; et al. (Development and Psychopathology, 2019)
Epigenetic DNA modifications in genes related to the hypothalamic-pituitary-adrenal (HPA) axis are discussed as a mechanism underlying the association between prenatal depression and altered child HPA activity. In a longitudinal study, DNA methylation changes related to prenatal depressive symptoms were investigated in 167 children aged 6 to 9 years. At six candidate genes, 126 cytosine-guanine dinucleotides were considered without correcting for multiple testing due to the exploratory nature of the study. Further associations with the basal child HPA activity were examined. Children exposed to prenatal depressive symptoms exhibited lower bedtime cortisol (p = .003, ηp2 = 0.07) and a steeper diurnal slope (p = .023, ηp2 = 0.06). For total cortisol release, prenatal exposure was related to lower cortisol release in boys, and higher release in girls. Furthermore, prenatal depressive symptoms were associated with altered methylation in the glucocorticoid receptor gene (NR3C1), the mineralocorticoid receptor gene (NR3C2), and the serotonin receptor gene (SLC6A4), with some sex-specific effects (p = .012-.040, ηp2 = 0.03-0.04). In boys, prenatal depressive symptoms predicted bedtime cortisol mediated by NR3C2 methylation, indirect effect = -0.07, 95% confidence interval [-0.16, -0.02]. Results indicate relations of prenatal depressive symptoms to both child basal HPA activity and DNA methylation, partially fitting a mediation model, with exposed boys and girls being affected differently.
EVALuna2:36373

A Standard Mammography Unit - Standard 3D Ultrasound Probe Fusion Prototype: First Results - Schulz-Wendtland, Rüdiger; Jud, Sebastian; Fasching, Peter; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Wunderle, Marius; Gaß, Paul; Langemann, Hanna; Beckmann, Matthias; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2017)
The combination of different imaging modalities through the use of fusion devices promises significant diagnostic improvement for breast pathology. The aim of this study was to evaluate image quality and clinical feasibility of a prototype fusion device (fusion prototype) constructed from a standard tomosynthesis mammography unit and a standard 3D ultrasound probe using a new method of breast compression.Imaging was performed on 5 mastectomy specimens from patients with confirmed DCIS or invasive carcinoma (BI-RADS ((TM)) 6). For the preclinical fusion prototype an ABVS system ultrasound probe from an Acuson S2000 was integrated into a MAMMOMAT Inspiration (both Siemens Healthcare Ltd) and, with the aid of a newly developed compression plate, digital mammogram and automated 3D ultrasound images were obtained.The quality of digital mammogram images produced by the fusion prototype was comparable to those produced using conventional compression. The newly developed compression plate did not influence the applied x-ray dose. The method was not more labour intensive or time-consuming than conventional mammography. From the technical perspective, fusion of the two modalities was achievable.In this study, using only a few mastectomy specimens, the fusion of an automated 3D ultrasound machine with a standard mammography unit delivered images of comparable quality to conventional mammography. The device allows simultaneous ultrasound - the second important imaging modality in complementary breast diagnostics - without increasing examination time or requiring additional staff.
EVALuna2:6849

A Survival Analysis Approach to Predicting Severe Leukopenia in Advanced Breast Cancer Patients - Vodenčarević, Asmir; Kreuzeder, Julia; Wöckel, Achim; Fasching, Peter (Communications in Computer and Information Science, 2024)
Modern therapies for advanced breast cancer can significantly prolong survival and improve patient’s quality of life. Yet, in some patients they can be associated with different, sometimes severe toxicities. Predicting these toxicities in individual patients would enable more targeted monitoring, toxicity prevention and could help saving scarce healthcare resources. Previously we have shown that individual prediction of a cardio toxicity called QT prolongation using survival modelling algorithms is feasible. In this work we target the individual prediction of a blood toxicity called severe leukopenia using the same modelling approach. Seven statistical and machine learning survival modelling algorithms are trained, optimized, validated and compared on both clinical trial and real-world data. The statistical Cox proportional hazards model reached rather modest performance of about 0.6 (Uno’s concordance index) and slightly outperformed its machine learning counterparts. The strongest predictors include variables related to prior therapies, location of metastasis, histologic grade as well as several quality of life scores.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Advanced breast cancer; Severe leukopenia; Survival analysis

A Swedish genome-wide haplotype association analysis identifies novel candidate loci associated with endometrial cancer risk - Barnekow, Elin; Liu, Wen; Andersson, Emil; Wang, Xuemin; Helgadottir, Hafdis T.; Thutkawkorapin, Jessada; Barilla, Serena; Vermani, Litika; Mints, Miriam; Tham, Emma; Fasching, Peter; Lambrechts, Diether; et al. (PLoS ONE, 2025)
Genome-wide association studies [GWAS] have identified a limited number of endometrial cancer risk loci by analyzing single nucleotide polymorphisms [SNPs]. We hypothesized that analyzing haplotypes rather than SNPs could provide novel and more detailed information on genetic cancer susceptibility loci. To examine the association of a SNP or haplotype with endometrial cancer risk we performed a two-stage haplotype GWAS. The discovery GWAS included a sub-cohort of 1,116 Swedish endometrial cancer cases and 5,021 controls from previously published GWAS data. A sliding window analysis was employed with window sizes of 1-25 SNPs using a logistic regression model. The Swedish haplotype analysis identified 15 novel candidate risk loci (2q31.1, 4p16.1, 4p15.31, 6q13, 7p21.1, 9p13.3, 10q26.3, 11q21, 12q13.11, 13q12.11, 15q13.3, 16q24.3, 19q13.32, 20p12.3 and 22q13.2) with OR ranging from 1.6 to 3.3 and p-values from 4.25 × 10−8 to 9.86 × 10−15. A second replication haplotype analysis of the Swedish novel loci was performed using two cohorts from Belgium and Germany. In spite of small sample sizes in the replication cohorts, there was still support for most loci with positive ORs. In addition, the findings in the two European cohorts motivates further studies to search for founder haplotypes. These novel findings suggested that endometrial cancer loci, identified through haplotype analysis, conferred a higher risk compared to previous single-variant GWAS.
CRIS-Team Scopus Importer:2025-04-01

A Transcriptome-Wide Association Study Among 97,898 Women to Identify Candidate Susceptibility Genes for Epithelial Ovarian Cancer Risk - Lu, Yingchang; Beeghly-Fadiel, Alicia; Wu, Lang; Guo, Xingyi; Li, Bingshan; Schildkraut, Joellen M.; Im, Hae Kyung; Chen, Yian A.; Permuth, Jennifer B.; Reid, Brett M.; Teer, Jamie K.; Moysich, Kirsten B.; et al. (Cancer Research, 2018)
Large-scale genome-wide association studies (GWAS) have identified approximately 35 loci associated with epithelial ovarian cancer (EOC) risk. The majority of GWAS-identified disease susceptibility variants are located in noncoding regions, and causal genes underlying these associations remain largely unknown. Here, we performed a transcriptome-wide association study to search for novel genetic loci and plausible causal genes at known GWAS loci. We used RNA sequencing data (68 normal ovarian tissue samples from 68 individuals and 6,124 cross-tissue samples from 369 individuals) and high-density genotyping data from European descendants of the Genotype-Tissue Expression (GTEx V6) project to build ovarian and cross-tissue models of genetically regulated expression using elastic net methods. We evaluated 17,121 genes for their cis-predicted gene expression in relation to EOC risk using summary statistics data from GWAS of 97,898 women, including 29,396 EOC cases. With a Bonferroni-corrected significance level of P < 2.2 × 10-6, we identified 35 genes, including FZD4 at 11q14.2 (Z = 5.08, P = 3.83 × 10-7, the cross-tissue model; 1 Mb away from any GWAS-identified EOC risk variant), a potential novel locus for EOC risk. All other 34 significantly associated genes were located within 1 Mb of known GWAS-identified loci, including 23 genes at 6 loci not previously linked to EOC risk. Upon conditioning on nearby known EOC GWAS-identified variants, the associations for 31 genes disappeared and three genes remained (P < 1.47 × 10-3). These data identify one novel locus (FZD4) and 34 genes at 13 known EOC risk loci associated with EOC risk, providing new insights into EOC carcinogenesis.Significance: Transcriptomic analysis of a large cohort confirms earlier GWAS loci and reveals FZD4 as a novel locus associated with EOC risk. Cancer Res; 78(18); 5419-30. ©2018 AACR.
EVALuna2:210015

A transcriptome-wide association study of 229,000 women identifies new candidate susceptibility genes for breast cancer - Wu, Lang; Shi, Wei; Long, Jirong; Guo, Xingyi; Michailidou, Kyriaki; Beesley, Jonathan; Bolla, Manjeet K.; Shu, Xiao-Ou; Lu, Yingchang; Cai, Qiuyin; Al-Ejeh, Fares; Rozali, Esdy; et al. (Nature Genetics, 2018)
The breast cancer risk variants identified in genome-wide association studies explain only a small fraction of the familial relative risk, and the genes responsible for these associations remain largely unknown. To identify novel risk loci and likely causal genes, we performed a transcriptome-wide association study evaluating associations of genetically predicted gene expression with breast cancer risk in 122,977 cases and 105,974 controls of European ancestry. We used data from the Genotype-Tissue Expression Project to establish genetic models to predict gene expression in breast tissue and evaluated model performance using data from The Cancer Genome Atlas. Of the 8,597 genes evaluated, significant associations were identified for 48 at a Bonferroni-corrected threshold of P < 5.82 × 10, including 14 genes at loci not yet reported for breast cancer. We silenced 13 genes and showed an effect for 11 on cell proliferation and/or colony-forming efficiency. Our study provides new insights into breast cancer genetics and biology.
EVALuna2:51301

Attention, cognitive control and motivation in ADHD: Linking event-related brain potentials and DNA methylation patterns in boys at early school age - Heinrich, Hartmut; Grunitz, Juliane; Stonawski, Valeska; Frey, Silke; Wahl, Simone; Albrecht, Bjoern; Goecke, Tamme W.; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Moll, Gunther; Eichler, Anna (Scientific Reports, 2017)
In order to better understand the underpinnings of attention-deficit/hyperactivity disorder (ADHD), we targeted the relationship of attentional, cognitive control and motivational processes with DNA methylation patterns of 60 candidate genes in boys at early school age. Participants (6 to 8 years; N = 82) were selected from a German longitudinal cohort (FRANCES). ADHD-related behaviour was assessed via maternal ratings. Performance and event-related potential measures (inter alia Cue-P3 and Nogo-P3), which were recorded in a motivational go/nogo task, indicated diminished attentional orienting, reduced inhibitory response control and a larger motivational effect on performance in ADHD already at this relatively young age. Methylation patterns were analysed in buccal cell DNA with the Illumina HumanMethylation 450K array. For CpG sites at genes of the dopaminergic (COMT, ANKK1) and the neurotrophic (BDNF, NGFR) system, associations with the Nogo-P3 as well as ADHD symptom severity were found suggesting that these systems are involved in response control deficits in ADHD. Methylation effects related to both functional aspects and ADHD behaviour were also observed for DPP10 and TPH2. Epigenetic mechanisms may play a role in ADHD-associated deficits but findings need to be replicated in larger samples and are limited by the fact that only peripheral methylation could be considered.
EVALuna2:33560

Attrition in the First Three Therapy Lines in Patients with Advanced Breast Cancer in the German Real-World PRAEGNANT Registry - Hartkopf, Andreas D.; Walter, Christina B.; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Fasching, Peter; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Background With more effective therapies for patients with advanced breast cancer (aBC), therapy sequences are becoming increasingly important. However, some patients might drop out of the treatment sequence due to deterioration of their life status. Since little is known about attrition in the real-world setting, this study assessed attrition in the first three therapy lines using a real-world registry. Methods Patients with information available on the first three therapy lines were selected from the German PRAEGNANT registry (NCT02338167). Attrition was determined for each therapy line using competing risk analyses, with the start of the next therapy line or death as endpoints. Additionally, a simple attrition rate was calculated based on the proportion of patients who completed therapy but did not start the next therapy line. Results Competitive risk analyses were performed on 3988 1st line, 2651 2nd line and 1866 3rd line patients. The probabilities of not starting the next therapy line within 5 years after initiation of 1st, 2nd and 3rd line therapy were 30%, 24% and 24% respectively. Patients with HER2-positive disease had the highest risk for attrition, while patients with HRpos/HER2neg disease had the lowest risk. Attrition rates remained similar across molecular subgroups in the different therapy lines. Conclusion Attrition affects a large proportion of patients with aBC, which should be considered when planning novel therapy concepts that specifically address the sequencing of therapies. Taking attrition into account could help understand treatment effects resulting from sequential therapies and might help develop treatment strategies that specifically aim at maintaining quality of life.
CRIS-Team Scopus Importer:2024-06-14
Keywords: advanced breast cancer; clinical trials; de novo metastatic breast cancer; recurrent breast cancer metastases

Awareness of breast cancer incidence and risk factors among healthy women in Germany: an update after 10 years - Poehls, Uwe G.; Hack, Carolin; Wunderle, Marius; Renner, Stefan P.; Lux, Michael P.; Beckmann, Matthias; Fasching, Peter; Nabieva, Naiba (European Journal of Cancer Prevention, 2019)
Early breast cancer detection programs depend for effectiveness on the participation rate, which is affected by risk factor awareness. This study investigated changes in women's risk factor awareness between 2004 and 2016. Results from a 2004 survey of 2107 healthy women were compared with new data obtained using the same questionnaire in 2016, with 866 participants indicating their knowledge and perceptions regarding breast cancer incidence, risk factors, risk perceptions, and levels of concern. Logistic regression models assessed the influence of time point (2004 vs. 2016) on correct recognition of risk factors such as age at first childbirth, childlessness, lack of breastfeeding, hormone replacement therapy (HRT), and family history. Regression models were adjusted for common sociodemographic characteristics. Reproductive risk factors were regarded as influencing breast cancer risk less often. In 2004, age at first birth, childlessness, and lack of breastfeeding were regarded as risk factors by 24, 32, and 37%, respectively, in comparison with only 15, 18, and 23% in 2016. All changes were statistically significant. Awareness of HRT as a risk factor increased significantly (36-57%), and family history was recognized as a risk by 75 and 73% in 2004 and 2016, respectively. Most women recognized family history as a breast cancer risk factor. This did not change, reflecting the topic's media prominence. Awareness of HRT as a risk factor increased, probably owing to public information after the large HRT studies. It is unclear why reproductive risk factors are less frequently recognized; educational programs should address this information deficit.
CRIS-Team Scopus Importer:2019-10-08

AXSANA (AXillary Surgery After NeoAdjuvant Treatment): A European prospective multicenter cohort study to evaluate different surgical methods of axillary staging (sentinel lymph node biopsy, targeted axillary dissection, axillary dissection) in clinically node-positive breast cancer patients treated with neoadjuvant chemotherapy - Banys-Paluchowski, M.; Stickeler, E.; De Boniface, J.; Gentilini, O.; Thill, M.; Hartmann, S.; Fasching, Peter; Hübner, Hanna; Krawczyk, N.; Blohmer, J-U; Solbach, C.; Untch, M.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-07-31

BACH1 and HIF1 alpha predict response to neoadjuvant nab-paclitaxel (nP) treatment in early breast cancer (BC) - Vladimirova, V.; Schneeweiss, A.; Jackisch, C.; Weber, K. E.; Denkert, C.; Schmatloch, S.; Karn, T.; Fasching, Peter; Braun, S.; Szeto, C.; Sinn, B.; Van Mackelenbergh, M.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Baseline menopausal status, Ki-67 and stromal tumour-infiltrating lymphocytes (TILs) and association with outcome in triple-negative breast cancer (TNBC): Exploratory analysis in GeparSixto - Labidi-Galy, S. I.; Schneeweiss, A.; Sinn, H. P.; Blohmer, J-U.; Romanens, L.; Zahm, D-M.; Huober, J.; Dohnal, D.; Link, T.; Hanusch, C.; Jackisch, C.; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Biological and clinical effects of abemaciclib in a phase 2 neoadjuvant study for postmenopausal patients with HR+/HER2-breast cancer - Fasching, Peter; Fernandez Abad, M.; Garcia-Saenz, J. A.; Schneeweiss, A.; Guarneri, V.; Colleoni, M.; Petru, E.; Costigan, T. M.; Caldwell, C. W.; Barriga, S.; Hurvitz, S.; Slamon, D. (2017)
EVALuna2:36188

Biological and clinical effects of abemaciclib in a phase 2 neoadjuvant study for postmenopausal patients with HR+/HER2-breast cancer - Guarneri, V.; Fasching, Peter; Fernandez Abad, M.; Garcia-Saenz, A.; Schneeweiss, A.; Colleoni, M.; Petru, E.; Costigan, T. M.; Caldwell, C. W.; Barriga, S.; Hurvitz, S.; Slamon, D. (2017)
EVALuna2:36183

Biomarker Data from the Phase III KATHERINE Study of Adjuvant T-DM1 versus Trastuzumab for Residual Invasive Disease after Neoadjuvant Therapy for HER2-Positive Breast Cancer - Denkert, Carsten; Lambertini, Chiara; Fasching, Peter; Pogue-Geile, Katherine L.; Mano, Max S.; Untch, Michael; Wolmark, Norman; Huang, Chiun Sheng; Loibl, Sibylle; Mamounas, Eleftherios P.; Geyer, Charles E.; Lucas, Peter C.; et al. (Clinical Cancer Research, 2023)
PURPOSE: In KATHERINE, adjuvant T-DM1 reduced risk of disease recurrence or death by 50% compared with trastuzumab in patients with residual invasive breast cancer after neoadjuvant therapy (NAT) comprised of HER2-targeted therapy and chemotherapy. This analysis aimed to identify biomarkers of response and differences in biomarker expression before and after NAT. EXPERIMENTAL DESIGN: Exploratory analyses investigated the relationship between invasive disease-free survival (IDFS) and HER2 protein expression/gene amplification, PIK3CA hotspot mutations, and gene expression of HER2, PD-L1, CD8, predefined immune signatures, and Prediction Analysis of Microarray 50 intrinsic molecular subtypes, classified by Absolute Intrinsic Molecular Subtyping. HER2 expression on paired pre- and post-NAT samples was examined. RESULTS: T-DM1 appeared to improve IDFS versus trastuzumab across most biomarker subgroups, except the HER2 focal expression subgroup. High versus low HER2 gene expression in residual disease was associated with worse outcomes with trastuzumab [HR, 2.02; 95% confidence interval (CI), 1.32-3.11], but IDFS with T-DM1 was independent of HER2 expression level (HR, 1.01; 95% CI, 0.56-1.83). Low PD-L1 gene expression in residual disease was associated with worse outcomes with trastuzumab (HR, 0.66; 95% CI, 0.44-1.00), but not T-DM1 (HR, 1.05; 95% CI, 0.59-1.87). PIK3CA mutations were not prognostic. Increased variability in HER2 expression was observed in post-NAT versus paired pre-NAT samples. CONCLUSIONS: T-DM1 appears to overcome HER2 resistance. T-DM1 benefit does not appear dependent on immune activation, but these results do not rule out an influence of the tumor immune microenvironment on the degree of response.
CRIS-Team Scopus Importer:2023-04-28

Biomarkers in women's cancers, gynecology, and obstetrics - Fasching, Peter; Konecny, Gottfried E.; Spurdle, Amanda B. (BioMed Research International, 2014)
EVALuna2:17511

Body mass index and breast cancer survival: a Mendelian randomization analysis - Guo, Qi; Burgess, Stephen; Turman, Constance; Bolla, Manjeet K.; Wang, Qin; Lush, Michael; Abraham, Jean; Aittomaki, Kristiina; Andrulis, Irene L.; Apicella, Carmel; Arndt, Volker; Barrdahl, Myrto; et al. (International Journal of Epidemiology, 2017)
Background: There is increasing evidence that elevated body mass index (BMI) is associated with reduced survival for women with breast cancer. However, the underlying reasons remain unclear. We conducted a Mendelian randomization analysis to investigate a possible causal role of BMI in survival from breast cancer. Methods: We used individual-level data from six large breast cancer case-cohorts including a total of 36 210 individuals (2475 events) of European ancestry. We created a BMI genetic risk score (GRS) based on genotypes at 94 known BMI-associated genetic variants. Association between the BMI genetic score and breast cancer survival was analysed by Cox regression for each study separately. Study-specific hazard ratios were pooled using fixed-effect meta-analysis. Results: BMI genetic score was found to be associated with reduced breast cancer-specific survival for estrogen receptor (ER)-positive cases [hazard ratio (HR) = 1.11, per one-unit increment of GRS, 95% confidence interval (CI) 1.01-1.22, P = 0.03). We observed no association for ER-negative cases (HR = 1.00, per one-unit increment of GRS, 95% CI 0.89-1.13, P = 0.95). Conclusions: Our findings suggest a causal effect of increased BMI on reduced breast cancer survival for ER-positive breast cancer. There is no evidence of a causal effect of higher BMI on survival for ER-negative breast cancer cases.
EVALuna2:33863

Branch duct intraductal papillary mucinous neoplasm - contra resection - Brunner, Michaela; Kersting, S.; Grützmann, Robert; Weber, Georg (Chirurg, 2017)
Due to improvements in imaging modalities the diagnosis of branch duct intraductal papillary mucinous neoplasms (BD-IPMN) has been significantly increased in recent years. A BD-IPMN is frequently diagnosed as an incidental finding in asymptomatic patients. The optimal management of BD-IPMN is the subject of controversial discussions. Numerous studies have shown that an individualized therapeutic strategy with a follow-up observation of most BD-IPMNs is feasible and safe, considering age, comorbidities and patient preference. An accurate evaluation of BD-IPMN with a detailed anamnesis, high-resolution imaging techniques and endoscopic ultrasound is necessary. Symptomatic patients as well as patients with so-called high-risk stigmata should undergo resection. Asymptomatic patients with so-called worrisome features can either undergo surveillance or surgical resection, taking age and comorbidities into account. For BD-IPMN patients without high-risk stigmata and worrisome features and showing no symptoms, surveillance of the pancreatic lesion is the preferred approach. The high prevalence of BD-IPMN, limitations in differential diagnostics, an overestimation of the risk of malignancy due to an overrepresentation of symptomatic and suspected BD-IPMN in resected cohorts, an overestimated role of BD-IPMN as precursor lesions for pancreatic carcinoma and evidence of the safety of follow-up surveillance, underline the enormous importance of surveillance. Based on this and considering the background of a notable mortality and morbidity of pancreatic surgery, aggressive management with prophylactic surgical resection is not justified for all BD-IPMN, in particular for low-risk lesions.
EVALuna2:15288

BRCA1/2 Mutations and Bevacizumab in the Neoadjuvant Treatment of Breast Cancer: Response and Prognosis Results in Patients With Triple-Negative Breast Cancer From the GeparQuinto Study - Fasching, Peter; Loibl, Sibylle; Hu, Chunling; Hart, Steven N.; Shimelis, Hermela; Moore, Raymond; Schem, Christian; Tesch, Hans; Untch, Michael; Hilfrich, Joern; Rezai, Mahdi; Gerber, Bernd; et al. (Journal of Clinical Oncology, 2018)
Purpose BRCA1/2 mutations are frequent in patients with triple-negative breast cancer (TNBC). These patients are often treated with primary systemic chemotherapy. The aim of this study was to analyze the effects of BRCA1/2 mutations on pathologic complete response (pCR) and disease-free survival (DFS) in a cohort of patients with TNBC treated with anthracycline and taxane-containing chemotherapy, with or without bevacizumab. Patients and Methods Germline DNA was sequenced to identify mutations in BRCA1 and BRCA2 in 493 patients with TNBC from the GeparQuinto study. The pCR rates were compared in patients with and without mutation, as well as in patients treated with and without bevacizumab. In addition, the influence of BRCA1/2 mutation status and pCR status on DFS was evaluated relative to treatment. Results BRCA1/2 mutations were detected in 18.3% of patients with TNBC. Overall, patients with mutations had a pCR rate of 50%, compared with 31.5% in patients without a mutation (odds ratio [OR], 2.17; 95% CI, 1.37 to 3.46; P = .001). The pCR rate among patients treated with bevacizumab was 61.5% for BRCA1/2 mutation carriers and 35.6% for those without mutations (OR, 2.90; 95% CI, 1.43 to 5.89; P = .004). pCR was a strong predictor of DFS for patients without BRCA1/2 mutations (hazard ratio, 0.18; 95% CI, 0.11 to 0.31) but not for patients with BRCA1/2 mutations (hazard ratio, 0.74; 95% CI, 0.32 to 1.69). Conclusion The addition of bevacizumab may increase the pCR after standard neoadjuvant chemotherapy for patients with TNBC with BRCA1/2 mutations. In patients treated with anthracycline and taxane-based chemotherapy (with or without bevacizumab), pCR was a weaker predictor of DFS for BRCA1/2 mutation carriers than for patients without mutations.
EVALuna2:56158

BRCA2 Hypomorphic Missense Variants Confer Moderate Risks of Breast Cancer - Shimelis, Hermela; Mesman, Romy L. S.; Von Nicolai, Catharina; Ehlen, Asa; Guidugli, Lucia; Martin, Charlotte; Calleja, Fabienne M. G. R.; Meeks, Huong; Hallberg, Emily; Hinton, Jamie; Lilyquist, Jenna; Hu, Chunling; et al. (Cancer Research, 2017)
Breast cancer risks conferred by many germline missense variants in the BRCA1 and BRCA2 genes, often referred to as variants of uncertain significance (VUS), have not been established. In this study, associations between 19 BRCA1 and 33 BRCA2 missense substitution variants and breast cancer risk were investigated through a breast cancer case-control study using genotyping data from 38 studies of predominantly European ancestry (41,890 cases and 41,607 controls) and nine studies of Asian ancestry (6,269 cases and 6,624 controls). The BRCA2 c.9104A>C, p.Tyr3035Ser (OR = 2.52; P = 0.04), and BRCA1 c.5096G>A, p.Arg1699Gln (OR = 4.29; P = 0.009) variant were associated with moderately increased risks of breast cancer among Europeans, whereas BRCA2 c.7522G>A, p.Gly2508Ser (OR = 2.68; P = 0.004), and c.8187G>T, p.Lys2729Asn (OR = 1.4; P = 0.004) were associated with moderate and low risks of breast cancer among Asians. Functional characterization of the BRCA2 variants using four quantitative assays showed reduced BRCA2 activity for p.Tyr3035Ser compared with wild-type. Overall, our results show how BRCA2 missense variants that influence protein function can confer clinically relevant, moderately increased risks of breast cancer, with potential implications for risk management guidelines in women with these specific variants. Cancer Res; 77(11); 2789-99. ©2017 AACR.
EVALuna2:36140

BRCA2 Polymorphic Stop Codon K3326X and the Risk of Breast, Prostate, and Ovarian Cancers - Meeks, Huong D.; Song, Honglin; Michailidou, Kyriaki; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; Barrowdale, Daniel; Frost, Debra; Mcguffog, Lesley; Ellis, Steve; Feng, Bingjian; Buys, Saundra S.; et al. (Journal of the National Cancer Institute, 2016)
BACKGROUND: The K3326X variant in BRCA2 (BRCA2*c.9976A>T; p.Lys3326*; rs11571833) has been found to be associated with small increased risks of breast cancer. However, it is not clear to what extent linkage disequilibrium with fully pathogenic mutations might account for this association. There is scant information about the effect of K3326X in other hormone-related cancers. METHODS: Using weighted logistic regression, we analyzed data from the large iCOGS study including 76 637 cancer case patients and 83 796 control patients to estimate odds ratios (ORw) and 95% confidence intervals (CIs) for K3326X variant carriers in relation to breast, ovarian, and prostate cancer risks, with weights defined as probability of not having a pathogenic BRCA2 variant. Using Cox proportional hazards modeling, we also examined the associations of K3326X with breast and ovarian cancer risks among 7183 BRCA1 variant carriers. All statistical tests were two-sided. RESULTS: The K3326X variant was associated with breast (ORw = 1.28, 95% CI = 1.17 to 1.40, P = 5.9x10(-) (6)) and invasive ovarian cancer (ORw = 1.26, 95% CI = 1.10 to 1.43, P = 3.8x10(-3)). These associations were stronger for serous ovarian cancer and for estrogen receptor-negative breast cancer (ORw = 1.46, 95% CI = 1.2 to 1.70, P = 3.4x10(-5) and ORw = 1.50, 95% CI = 1.28 to 1.76, P = 4.1x10(-5), respectively). For BRCA1 mutation carriers, there was a statistically significant inverse association of the K3326X variant with risk of ovarian cancer (HR = 0.43, 95% CI = 0.22 to 0.84, P = .013) but no association with breast cancer. No association with prostate cancer was observed. CONCLUSIONS: Our study provides evidence that the K3326X variant is associated with risk of developing breast and ovarian cancers independent of other pathogenic variants in BRCA2. Further studies are needed to determine the biological mechanism of action responsible for these associations.
EVALuna2:33125

BRCA-mutated breast cancer: the unmet need, challenges and therapeutic benefits of genetic testing - Arun, Banu; Couch, Fergus J.; Abraham, Jean; Tung, Nadine; Fasching, Peter (British Journal of Cancer, 2024)
Mutations in the BRCA1 and/or BRCA2 genes (BRCAm) increase the risk of developing breast cancer (BC) and are found in 5% of unselected patients with the disease. BC resulting from a germline BRCAm (gBRCAm) has distinct clinical characteristics along with increased sensitivity to DNA-damaging agents such as poly(ADP-ribose) polymerase (PARP) inhibitors and platinum-based chemotherapies, and potentially decreased sensitivity to cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors. Given the evolving treatment landscape for gBRCAm BC in early and advanced disease settings, timely determination of gBRCAm status is fundamental to facilitate the most effective treatment strategy for patients. However, many patients with gBRCAm are not identified due to suboptimal referral rates and/or a low uptake of genetic testing. We discuss current evidence for a differential response to treatment in patients with gBRCAm in early and advanced BC settings, including outcomes with PARP inhibitors, platinum-based chemotherapies, and CDK4/6 inhibitors, as well as ongoing treatment innovations and the potential of these treatment approaches. Current genetic testing strategies are also examined, including the latest guidelines on who and when to test for gBRCAm, as well as challenges to testing and how these may be overcome.
CRIS-Team Scopus Importer:2024-09-06

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast Cancer and Genetic BRCA1/2 Testing in Routine Clinical Practice: Why, When and For Whom? - Lux, Michael P.; Fasching, Peter (Geburtshilfe und Frauenheilkunde, 2023)
Pathogenic variants of the tumor suppressor genes BRCA1 and BRCA2 are responsible for the majority of hereditary breast cancers; they are also becoming increasingly important to identify whether patients are suitable for targeted therapy with poly ADP-ribose polymerase inhibitors (PARPi). Patients with HER2-negative breast cancer and BRCA1/2 germline mutations can benefit significantly from PARPi therapy, and the findings of the OlympiAD and the EMBRACA phase III clinical trials for regulatory approval were recently expanded by the addition of the most recent OlympiA data on the treatment of patients with early disease and a high risk of recurrence. This means that BRCA1/2 germline testing to plan patient therapy is now also relevant for patients with early breast cancer and therefore has a direct impact on survival. Healthcare research data shows, however, that BRCA1/2 testing rates are strongly affected by familial history, cancer subtype (particularly triple-negative subtypes), and patient age at onset of disease (especially with regards to younger patients with breast cancer), despite the existing clear recommendations for BRCA1/2 germline testing to identify whether PARPi therapy is indicated. This article presents the clinical implications of identifying BRCA1/2 germline mutations in patients with breast cancer, the current recommendations on molecular diagnostics, and their implementation in practice. The treatment of patients with breast cancer has progressed greatly in recent years and now offers individual treatment concepts which can only be implemented after the targeted identification of individual parameters. As detection of a BRCA1/2 germline mutation is essential for planning individual therapy, where indicated, testing should be arranged as early as possible. It is the only way of identifying patients suitable for PARPi therapy and ensuring they receive the best possible treatment. This also applies to patients with a negative familial history, HR-positive disease, or who are older at onset of disease.
CRIS-Team Scopus Importer:2023-03-24
Keywords: BRCA1/2 diagnostics; breast cancer; olaparib; PARP inhibitors; talazoparib; therapy planning

Breast cancer in young women: do BRCA1 or BRCA2 mutations matter? - Fasching, Peter (Lancet Oncology, 2018)
EVALuna2:210184

Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: Complementary medicine services are nowadays usually quite heterogeneous, and little information is available on standards for running an integrative medicine consultancy service. This study aimed to assess patients' satisfaction with a standardized treatment service on integrative medicine. METHODS: Using a cross-sectional design, 75 breast cancer patients from the integrative medicine consultancy service at the University Breast Center for Franconia were evaluated between January 2016 and March 2017. At primary consultation, patients answered a standardized questionnaire on their medical history and treatment goals regarding integrative medicine. In a subsequent interview, patients evaluated their satisfaction with the treatment service and individual treatment goals. RESULTS: 72% of the patients (n = 54) reported high satisfaction with the overall approach of the treatment service. 76% of the patients (n = 57) were very satisfied or satisfied with their individual treatment plans. The most frequently reported goals were to slow tumor progression (n = 64, 85.3%), reducing the side effects of conventional cancer treatments (n = 60, 80%), and a desire to participate actively in the treatment of breast cancer (n = 64, 85.3%). CONCLUSIONS: Using a standardized procedure in integrative medicine allows a high quality level to be offered to patients. Overall, breast cancer patients report very high satisfaction with the integrative medicine consultancy service and state long-term treatment goals. Hence, long-term treatment with integrative medicine methods should be taken into consideration.
EVALuna2:209947

Breast cancer risk assessment in a mammography screening program and participation in the IBIS-II chemoprevention trial - Löhberg, Christian; Jud, Sebastian; Häberle, Lothar; Heusinger, Katharina; Dilbat, Gerhard; Hein, Alexander; Rauh, Claudia; Dall, Peter; Rix, Nadine; Heinrich, Sabrina; Buchholz, Stefan; Lex, Benno; et al. (Breast Cancer Research and Treatment, 2010)
It has been shown in several studies that antihormonal compounds can offer effective prophylactic treatment to prevent breast cancer. In view of the low participation rates in chemoprevention trials, the purpose of this study was to identify the characteristics of women taking part in a population-based mammography screening program who wished to obtain information about the risk of breast cancer and then participate in the the International Breast Cancer Intervention Study II (IBIS-II) trial, a randomized double-blind controlled chemoprevention trial comparing anastrozole with placebo. A paper-based survey was conducted in a population-based mammography screening program in Germany between 2007 and 2009. All women who met the criteria for the mammography screening program were invited to complete a questionnaire. A total of 2,524 women completed the questionnaire, and 17.7% (n = 446) met the eligibility criteria for the IBIS-II trial after risk assessment. The women who wished to receive further information about chemoprevention were significantly younger (P < 0.01) and had significantly more children (P = 0.03) and significantly more relatives with breast cancer (P < 0.001). There were no significant differences between the participants with regard to body mass index or hormone replacement therapy. Normal mammographic findings at screening were the main reason (42%) for declining to participate in the IBIS-II trial or attend risk counseling. The ultimate rate of recruitment to the IBIS-II trial was very low (three women). Offering chemoprevention to women within a mammography screening unit as part of a paper-based survey resulted in low participation rates for both, the survey and the final participation in the IBIS-II trial. More individualized approaches and communication of breast cancer risk at the time of the risk assessment might be helpful to increase the participation and the understanding of chemopreventive approaches. © 2010 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; Chemoprevention trial; IBIS-II; Mammography screening; Patient recruitment

Breast Cancer Risk Factors and Survival by Tumor Subtype: Pooled Analyses from the Breast Cancer Association Consortium - Morra, Anna; Jung, Audrey Y.; Behrens, Sabine; Keeman, Renske; Ahearn, Thomas U.; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Auvinen, Päivi K.; Beane Freeman, Laura E.; Becher, Heiko; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
BACKGROUND: It is not known whether modifiable lifestyle factors that predict survival after invasive breast cancer differ by subtype. METHODS: We analyzed data for 121,435 women diagnosed with breast cancer from 67 studies in the Breast Cancer Association Consortium with 16,890 deaths (8,554 breast cancer specific) over 10 years. Cox regression was used to estimate associations between risk factors and 10-year all-cause mortality and breast cancer-specific mortality overall, by estrogen receptor (ER) status, and by intrinsic-like subtype. RESULTS: There was no evidence of heterogeneous associations between risk factors and mortality by subtype (Padj > 0.30). The strongest associations were between all-cause mortality and BMI ≥30 versus 18.5-25 kg/m2 [HR (95% confidence interval (CI), 1.19 (1.06-1.34)]; current versus never smoking [1.37 (1.27-1.47)], high versus low physical activity [0.43 (0.21-0.86)], age ≥30 years versus <20 years at first pregnancy [0.79 (0.72-0.86)]; >0-<5 years versus ≥10 years since last full-term birth [1.31 (1.11-1.55)]; ever versus never use of oral contraceptives [0.91 (0.87-0.96)]; ever versus never use of menopausal hormone therapy, including current estrogen-progestin therapy [0.61 (0.54-0.69)]. Similar associations with breast cancer mortality were weaker; for example, 1.11 (1.02-1.21) for current versus never smoking. CONCLUSIONS: We confirm associations between modifiable lifestyle factors and 10-year all-cause mortality. There was no strong evidence that associations differed by ER status or intrinsic-like subtype. IMPACT: Given the large dataset and lack of evidence that associations between modifiable risk factors and 10-year mortality differed by subtype, these associations could be cautiously used in prognostication models to inform patient-centered care.
CRIS-Team Scopus Importer:2021-04-16

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Breast Cancer Risk Genes - Association Analysis in More than 113,000 Women - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Luccarini, Craig; Wahlstrom, Cecilia; Pooley, Karen A.; Parsons, Michael T.; Fortuno, Cristina; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; et al. (New England Journal of Medicine, 2021)
BACKGROUND
CRIS-Team WoS Importer:2021-03-26

Breast cancer risk - Genes, environment and clinics Mammakarzinomrisiko - Gene, Umwelt und Klinik - Fasching, Peter; Ekici, Arif Bülent; Adamietz, B. R.; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a casecontrol design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patients breast cancer risk. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor

Breast cancer risks associated with missense variants in breast cancer susceptibility genes - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Parsons, Michael T.; Fortuno, Cristina; Gonzalez-Neira, Anna; Heijl, Stephan M.; Adank, Muriel A.; Ahearn, Thomas U.; Andrulis, Irene L.; Auvinen, Paivi; Becher, Heiko; et al. (Genome Medicine, 2022)
Background Protein truncating variants in ATM, BRCA1, BRCA2, CHEK2, and PALB2 are associated with increased breast cancer risk, but risks associated with missense variants in these genes are uncertain. Methods We analyzed data on 59,639 breast cancer cases and 53,165 controls from studies participating in the Breast Cancer Association Consortium BRIDGES project. We sampled training (80%) and validation (20%) sets to analyze rare missense variants in ATM (1146 training variants), BRCA1 (644), BRCA2 (1425), CHEK2 (325), and PALB2 (472). We evaluated breast cancer risks according to five in silico prediction-of-deleteriousness algorithms, functional protein domain, and frequency, using logistic regression models and also mixture models in which a subset of variants was assumed to be risk-associated. Results The most predictive in silico algorithms were Helix (BRCA1, BRCA2 and CHEK2) and CADD (ATM). Increased risks appeared restricted to functional protein domains for ATM (FAT and PIK domains) and BRCA1 (RING and BRCT domains). For ATM, BRCA1, and BRCA2, data were compatible with small subsets (approximately 7%, 2%, and 0.6%, respectively) of rare missense variants giving similar risk to those of protein truncating variants in the same gene. For CHEK2, data were more consistent with a large fraction (approximately 60%) of rare missense variants giving a lower risk (OR 1.75, 95% CI (1.47-2.08)) than CHEK2 protein truncating variants. There was little evidence for an association with risk for missense variants in PALB2. The best fitting models were well calibrated in the validation set. Conclusions These results will inform risk prediction models and the selection of candidate variants for functional assays and could contribute to the clinical reporting of gene panel testing for breast cancer susceptibility.
CRIS-Team WoS Importer:2022-06-03

Breast cancer risk variants at 6q25 display different phenotype associations and regulate ESR1, RMND1 and CCDC170 - Dunning, Alison M.; Michailidou, Kyriaki; Kuchenbaecker, Karoline B.; Thompson, Deborah; French, Juliet D.; Beesley, Jonathan; Healey, Catherine S.; Kar, Siddhartha; Pooley, Karen A.; Lopez-Knowles, Elena; Dicks, Ed; Barrowdale, Daniel; et al. (Nature Genetics, 2016)
We analyzed 3,872 common genetic variants across the ESR1 locus (encoding estrogen receptor α) in 118,816 subjects from three international consortia. We found evidence for at least five independent causal variants, each associated with different phenotype sets, including estrogen receptor (ER(+) or ER(-)) and human ERBB2 (HER2(+) or HER2(-)) tumor subtypes, mammographic density and tumor grade. The best candidate causal variants for ER(-) tumors lie in four separate enhancer elements, and their risk alleles reduce expression of ESR1, RMND1 and CCDC170, whereas the risk alleles of the strongest candidates for the remaining independent causal variant disrupt a silencer element and putatively increase ESR1 and RMND1 expression.
EVALuna2:33329

Breast Cancer Update 2014 - Focus on the Patient and the Tumour - Maass, N.; Schuetz, F.; Fasching, Peter; Fehm, T.; Janni, W.; Kuemmel, S.; Kolberg, H. -C.; Lueftner, D.; Wallwiener, M.; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2015)
The therapy for patients with breast cancer has developed markedly in the past ten years. Our understanding of the molecular biology of tumours and the characteristics of the patients has shaped the recent advances. In this review we present the latest knowledge about the therapy for breast cancer. There are new tests and options not only in the field of anti-HER2 therapy but also in the management of triple negative and hormone receptor-positive patients. Comprehension of prognosis and therapeutic response to chemotherapies is little by little helping to define patient groups who will not respond to chemotherapy or who do not need treatment because their prognosis is extremely good. In the field of anti-HER2 therapy, work is continuing on the development of drugs suitable for and able to overcome trastuzumab resistance. For hormone receptor-positive cancers, we now have a better understanding of which therapy groups will benefit from which anti-endocrine drugs, and which will be able to overcome a possible resistance (treatment of the PI3K pathways, inhibition of the cell cycle). Molecular tests are still being evaluated with regard to the clinical situations in which they may have the greatest relevance for therapeutic decision-making; however, evidence is also increasing as to the fields in which good predictions for the prognosis can be obtained. On the whole, more work is needed to promote our understanding of the new developments in diagnostics and therapy and to involve both physicians and patients equally in the procedures.
EVALuna2:17560

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Breast Tumor Analysis Using Shifted-Excitation Raman Difference Spectroscopy (SERDS) - Gebrekidan, Medhanie; Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Emons, Julius; Beckmann, Matthias; Bräuer, Andreas (Technology in Cancer Research & Treatment, 2018)
We used a shifted-excitation Raman difference spectroscopy method for the ex vivo classification of resected and formalin-fixed breast tissue samples as normal (healthy) tissue, fibroadenoma, or invasive carcinoma. We analyzed 8 tissue samples containing invasive carcinoma that were surrounded by normal tissue and 3 tissue samples with fibroadenoma only. We made various measurement sites on various tissue samples, in total 240 measurements for each type of tissue. Although the acquired raw spectra contain enough information to clearly differentiate between normal and tumor (fibroadenoma and invasive carcinoma) tissue, the differentiation between fibroadenoma and invasive carcinoma was possible only after the shifted-excitation Raman difference spectroscopy isolation of pure Raman spectra from the heavily fluorescence interfered raw spectra. We used 784 and 785 nm as excitation wavelengths for the shifted-excitation Raman difference spectroscopy method. The differences in the obtained pure Raman spectra are assigned to the different chemical compositions of normal breast tissue, fibroadenoma, and invasive breast carcinoma. Principal component analysis and linear discriminant analysis showed excellent classification results in the Raman shift range between 1000 and 1800 cm-1. Invasive breast carcinoma was identified with 99.15% sensitivity, and the absence of invasive carcinoma was identified with 90.40% specificity. Tumor tissue in tumor-containing tissue was identified with 100% sensitivity, and the absence of tumor in no-tumor containing tissue was identified with 100% specificity. As gold standard for the determination of the sensitivity and the specificity, we considered the conventional histopathological classification. In summary, shifted-excitation Raman difference spectroscopy could be potentially very useful to support histopathological diagnosis in breast pathology.
EVALuna2:34855

Breast volume assessment with a smart phone device compared to MRI - Behrens, Annika; Wunderle, Marius; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Emons, Julius; Heindl, Felix; Hack, Caroline; Ohlmeyer, Sabine; Uder, Michael; Beckmann, Matthias; Fasching, Peter (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

CA27.29 as a tumour marker for risk evaluation and therapy monitoring in primary breast cancer patients - Rack, Brigitte; Jueckstock, Julia; Trapp, Elisabeth; Weissenbacher, Tobias; Alunni-Fabbroni, Marianna; Schramm, Amelie; Widschwendter, Peter; Lato, Krisztian; Zwingers, Thomas; Lorenz, Ralf; Tesch, Hans; Schneeweiss, Andreas; et al. (Tumor Biology, 2016)
Several trials showed that tumour markers are associated with an impaired prognosis for breast cancer. Whether earlier treatment can improve the course of the disease remains controversial. The SUCCESS Trial compares FEC (500/100/500)-docetaxel (100) vs. FEC (500/100/500)-docetaxel/gemcitabine (75/2000) as well as 2 vs. 5 years of zoledronate in high-risk primary breast cancer patients. In 2669 patients, CA27.29 was measured before and after chemotherapy with the ST AIA-PACK CA27.29 reagent for the AIA-600II automated enzyme immunoassay (Tosoh Bioscience, Belgium). Values above 31 U/ml were considered positive. Of the patients, 7.6 % (n = 202, mean 19, range 3-410) and 19.1 % (n = 511, mean 21, range 3-331) had elevated marker levels before and after chemotherapy, respectively. Of the patients, 4.9 and 78 % showed elevated and low CA27.29, respectively, at both time points. After treatment, 35 % of the pre-therapy positive patients were negative, and 15 % of the initially negative patients became positive. The correlation between both time points was significant (p < 0.0001). No correlations among nodal status, grading, hormonal status, HER2 status and CA27.29 levels were found. However, tumour size (p = 0.02), older age (p < 0.001) and post-menopausal status (p = 0.006) were significantly associated with higher CA27.29 levels. Before treatment, the prevalence of elevated CA27.29 was equally distributed between both treatment arms, whereas after chemotherapy, 13.7 % of the patients in the FEC-doc arm showed an increased level vs. 25.4 % of the patients in the FEC-doc/gemcitabine arm (p < 0.0001). However, we could not show a significant association between the G-CSF application (yes vs. no) and CA27.29 status before/after chemotherapy (p = 0.75). These results indicate a close relationship between CA27.29 levels and tumour mass. Increased values after the completion of chemotherapy might be attributed to treatment effects and should be considered with caution.
EVALuna2:32947

Candidate locus analysis of the TERT-CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Carvajal-Carmona, Luis G.; O'Mara, Tracy A.; Painter, Jodie N.; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Pooley, Karen; Beesley, Jonathan; et al. (Human genetics, 2015)
Several studies have reported associations between multiple cancer types and single-nucleotide polymorphisms (SNPs) on chromosome 5p15, which harbours TERT and CLPTM1L, but no such association has been reported with endometrial cancer. To evaluate the role of genetic variants at the TERT-CLPTM1L region in endometrial cancer risk, we carried out comprehensive fine-mapping analyses of genotyped and imputed SNPs using a custom Illumina iSelect array which includes dense SNP coverage of this region. We examined 396 SNPs (113 genotyped, 283 imputed) in 4,401 endometrial cancer cases and 28,758 controls. Single-SNP and forward/backward logistic regression models suggested evidence for three variants independently associated with endometrial cancer risk (P = 4.9 × 10(-6) to P = 7.7 × 10(-5)). Only one falls into a haplotype previously associated with other cancer types (rs7705526, in TERT intron 1), and this SNP has been shown to alter TERT promoter activity. One of the novel associations (rs13174814) maps to a second region in the TERT promoter and the other (rs62329728) is in the promoter region of CLPTM1L; neither are correlated with previously reported cancer-associated SNPs. Using TCGA RNASeq data, we found significantly increased expression of both TERT and CLPTM1L in endometrial cancer tissue compared with normal tissue (TERT P = 1.5 × 10(-18), CLPTM1L P = 1.5 × 10(-19)). Our study thus reports a novel endometrial cancer risk locus and expands the spectrum of cancer types associated with genetic variation at 5p15, further highlighting the importance of this region for cancer susceptibility.
EVALuna2:9280

Cardiotoxicity and Cardiovascular Biomarkers in Patients With Breast Cancer: Data From the GeparOcto-GBG 84 Trial - Rüger, Alexandra Maria; Schneeweiss, Andreas; Seiler, Sabine; Tesch, Hans; van Mackelenbergh, Marion; Marmé, Frederik; Lübbe, Kristina; Sinn, Bruno; Karn, Thomas; Stickeler, Elmar; Müller, Volkmar; Schem, Christian; et al. (Journal of the American Heart Association, 2020)
Background Patients with breast cancer can be affected by cardiotoxic reactions through cancer therapies. Cardiac biomarkers, like NT-proBNP (N-terminal pro-B-type natriuretic peptide) and high-sensitivity cardiac troponin T, might have predictive value. Methods and Results Echocardiography, ECG, hemodynamic parameters, NT-proBNP and high-sensitivity cardiac troponin T were assessed in 853 patients with early-stage breast cancer randomized in the German Breast Group GeparOcto-GBG 84 phase III trial. Patients received neo-adjuvant dose-dense, dose-intensified epirubicin, paclitaxel, and cyclophosphamide (iddEPC group, n=424) or paclitaxel, non-pegylated doxorubicin, and in triple negative breast cancer, (paclitaxel, non-pegylated doxorubicin, carboplatin group, n=429) treatment for 18 weeks. Patients positive for human epidermal growth receptor 2 (n=354, 41.5%) received monoclonal antibodies on top of allocated therapy; 119 (12.9%) of all patients showed a cardiotoxic reaction during therapy (15 [1.8%] using a more strict definition). Presence of cardiotoxic reactions was irrespective of treatment allocation (P=0.31). Small but significant increases in NT-proBNP developed early in patients with a cardiotoxic reaction as compared with those without in whom NT-proBNP rose only towards the end of therapy (P=0.04). High-sensitivity cardiac troponin T rose early in both groups. Logistic regression showed that NT-proBNP (odds ratio [OR], 1.03; 95% CI, 1.008-1.055; P=0.01) and hemoglobin (OR, 1.31; 95% CI, 1.05-1.63; P=0.02) measured at 6 weeks after treatment initiation were significantly associated with cardiotoxic reactions. Conclusions NT-proBNP and hemoglobin are significantly associated with cardiotoxic reactions in patients with early-stage breast cancer undergoing dose-dense and dose-intensified chemotherapy, but high-sensitivity cardiac troponin T is not. Registration URL: http://www.clinicaltrials.gov; Unique identifier: NCT02125344.
CRIS-Team Scopus Importer:2020-12-11
Keywords: biomarker; breast cancer; cardiotoxicity; cardio‐oncology; left ventricular ejection fraction

Categorical EHR imputation with generative adversarial nets - Yang, Yinchong; Wu, Zhiliang; Tresp, Volker; Fasching, Peter (2019 IEEE International Conference on Healthcare Informatics, ICHI 2019, 2019)
Electronic Health Records often suffer from missing data, which poses a major problem in clinical practice and clinical studies. A novel approach for dealing with missing data are Generative Adversarial Nets (GANs), which have been generating huge research interest in image generation and transformation. Recently, researchers have attempted to apply GANs to missing data generation and imputation for EHR data: a major challenge here is the categorical nature of the data. State-of-the-art solutions to the GAN-based generation of categorical data involve either reinforcement learning, or learning a bidirectional mapping between the categorical and the a real latent feature space, so that the GANs only need to generate real-valued features. However, these methods are designed to generate complete feature vectors instead of imputing only the subsets of missing features. In this paper we propose a simple and yet effective approach that is based on previous work on GANs for data imputation. We first motivate our solution by discussing the reason why adversarial training often fails in case of categorical features. Then we derive a novel way to re-code the categorical features to stabilize the adversarial training. Based on experiments on two real-world EHR data with multiple settings, we show that our imputation approach largely improves the prediction accuracy, compared to more traditional data imputation approaches.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Data Imputation; Generative Adversarial Nets; Multiple Imputation

Caveolin Gene Expression Predicts Clinical Outcomes for Early-Stage HER2-Negative Breast Cancer Treated with Paclitaxel-Based Chemotherapy in the GeparSepto Trial - Williams, Terence M.; Schneeweiss, Andreas; Jackisch, Christian; Shen, Changxian; Weber, Karsten E.; Fasching, Peter; Denkert, Carsten; Furlanetto, Jenny; Heinmöller, Ernst; Schmatloch, Sabine; Karn, Thomas; Szeto, Christopher W.; et al. (Clinical Cancer Research, 2023)
PURPOSE: Caveolin-1 and -2 (CAV1/2) dysregulation are implicated in driving cancer progression and may predict response to nab-paclitaxel. We explored the prognostic and predictive potential of CAV1/2 expression for patients with early-stage HER2-negative breast cancer receiving neoadjuvant paclitaxel-based chemotherapy regimens, followed by epirubicin and cyclophosphamide. EXPERIMENTAL DESIGN: We correlated tumor CAV1/2 RNA expression with pathologic complete response (pCR), disease-free survival (DFS), and overall survival (OS) in the GeparSepto trial, which randomized patients to neoadjuvant paclitaxel- versus nab-paclitaxel-based chemotherapy. RESULTS: RNA sequencing data were available for 279 patients, of which 74 (26.5%) were hormone receptor (HR)-negative, thus triple-negative breast cancer (TNBC). Patients treated with nab-paclitaxel with high CAV1/2 had higher probability of obtaining a pCR [CAV1 OR, 4.92; 95% confidence interval (CI), 1.70-14.22; P = 0.003; CAV2 OR, 5.39; 95% CI, 1.76-16.47; P = 0.003] as compared with patients with high CAV1/2 treated with solvent-based paclitaxel (CAV1 OR, 0.33; 95% CI, 0.11-0.95; P = 0.040; CAV2 OR, 0.37; 95% CI, 0.12-1.13; P = 0.082). High CAV1 expression was significantly associated with worse DFS and OS in paclitaxel-treated patients (DFS HR, 2.29; 95% CI, 1.08-4.87; P = 0.030; OS HR, 4.97; 95% CI, 1.73-14.31; P = 0.003). High CAV2 was associated with worse DFS and OS in all patients (DFS HR, 2.12; 95% CI, 1.23-3.63; P = 0.006; OS HR, 2.51; 95% CI, 1.22-5.17; P = 0.013), in paclitaxel-treated patients (DFS HR, 2.47; 95% CI, 1.12-5.43; P = 0.025; OS HR, 4.24; 95% CI, 1.48-12.09; P = 0.007) and in patients with TNBC (DFS HR, 4.68; 95% CI, 1.48-14.85; P = 0.009; OS HR, 10.43; 95% CI, 1.22-89.28; P = 0.032). CONCLUSIONS: Our findings indicate high CAV1/2 expression is associated with worse DFS and OS in paclitaxel-treated patients. Conversely, in nab-paclitaxel-treated patients, high CAV1/2 expression is associated with increased pCR and no significant detriment to DFS or OS compared with low CAV1/2 expression.
CRIS-Team Scopus Importer:2023-09-08

CCNE1 and survival of patients with tubo-ovarian high-grade serous carcinoma: An Ovarian Tumor Tissue Analysis consortium study - Kang, Eun Young; Weir, Ashley; Meagher, Nicola S.; Farrington, Kyo; Nelson, Gregg S.; Ghatage, Prafull; Lee, Cheng Han; Riggan, Marjorie J.; Bolithon, Adelyn; Popovic, Gordana; Leung, Betty; Tang, Katrina; et al. (Cancer, 2023)
Background: Cyclin E1 (CCNE1) is a potential predictive marker and therapeutic target in tubo-ovarian high-grade serous carcinoma (HGSC). Smaller studies have revealed unfavorable associations for CCNE1 amplification and CCNE1 overexpression with survival, but to date no large-scale, histotype-specific validation has been performed. The hypothesis was that high-level amplification of CCNE1 and CCNE1 overexpression, as well as a combination of the two, are linked to shorter overall survival in HGSC. Methods: Within the Ovarian Tumor Tissue Analysis consortium, amplification status and protein level in 3029 HGSC cases and mRNA expression in 2419 samples were investigated. Results: High-level amplification (>8 copies by chromogenic in situ hybridization) was found in 8.6% of HGSC and overexpression (>60% with at least 5% demonstrating strong intensity by immunohistochemistry) was found in 22.4%. CCNE1 high-level amplification and overexpression both were linked to shorter overall survival in multivariate survival analysis adjusted for age and stage, with hazard stratification by study (hazard ratio [HR], 1.26; 95% CI, 1.08-1.47, p =.034, and HR, 1.18; 95% CI, 1.05-1.32, p =.015, respectively). This was also true for cases with combined high-level amplification/overexpression (HR, 1.26; 95% CI, 1.09-1.47, p =.033). CCNE1 mRNA expression was not associated with overall survival (HR, 1.00 per 1-SD increase; 95% CI, 0.94-1.06; p =.58). CCNE1 high-level amplification is mutually exclusive with the presence of germline BRCA1/2 pathogenic variants and shows an inverse association to RB1 loss. Conclusion: This study provides large-scale validation that CCNE1 high-level amplification is associated with shorter survival, supporting its utility as a prognostic biomarker in HGSC.
CRIS-Team Scopus Importer:2023-02-17
Keywords: CCNE1 amplification; cyclin E1 expression; high-grade serous carcinoma; ovarian cancer; prognosis

CDK4/6 Inhibition – Therapy Sequences and the Quest to Find the Best Biomarkers – an Overview of Current Programs - Schneeweiss, Andreas; Brucker, Sara Y.; Hübner, Hanna; Volmer, Lea L.; Hack, Carolin; Seitz, Katharina; Rübner, Matthias; Heublein, Sabine; Thewes, Verena; Lüftner, Diana; Lux, Michael P.; Jurhasz-Böss, Ingolf; et al. (Geburtshilfe und Frauenheilkunde, 2024)
In recent years, new targeted therapies have been developed to treat patients with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) breast cancer. Some of these therapies have not just become the new therapy standard but also led to significantly longer overall survival rates. The cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) have become the therapeutic standard for first-line therapy. Around 70 - 80% of patients are treated with a CDK4/6i. In recent years, a number of biomarkers associated with progression, clonal selection or evolution have been reported for CDK4/6i and their endocrine combination partners. Understanding the mechanisms behind treatment efficacy and resistance is important. A better understanding could contribute to planning the most effective therapeutic sequences and utilizing basic molecular information to overcome endocrine resistance. One study with large numbers of patients which aims to elucidate these mechanisms is the Comprehensive Analysis of sPatial, TempORal and molecular patterns of ribociclib efficacy and resistance in advanced Breast Cancer patients (CAPTOR BC) trial. This overview summarizes the latest clinical research on resistance to endocrine therapies, focusing on CDK4/6 inhibitors and discussing current study concepts.
CRIS-Team Scopus Importer:2024-06-14
Keywords: breast cancer; CDK4/6; therapy

CDK4/6 Inhibitors—Overcoming Endocrine Resistance Is the Standard in Patients with Hormone Receptor-Positive Breast Cancer - Nabieva, Naiba; Fasching, Peter (Cancers, 2023)
Purpose of review: Tamoxifen and aromatase inhibitors can be considered as some of the first targeted therapies. For the past 30 years, they were the endocrine treatment standard in the advanced and early breast cancer setting. CDK4/6 inhibitors, however, are the first substances in almost two decades to broadly improve the therapeutic landscape of hormone receptor-positive breast cancer patients for the upcoming years. This review is designed to discuss the recent history, current role, future directions and opportunities of this substance class. Recent findings: The CDK4/6 inhibitors abemaciclib, dalpiciclib, palbociclib and ribociclib have all demonstrated a statistically significant improvement in progression-free survival in advanced disease. However, to date, abemaciclib and ribociclib are the only CDK4/6 inhibitors to have shown an improvement in overall survival in patients with metastatic breast cancer. Moreover, abemaciclib is the first CDK4/6 inhibitor to also reduce the risk of recurrence in those with early-stage disease. Further CDK inhibitors, treatment combinations with other drugs and different therapy sequences are in development. Summary: Achieving significant improvements in survival rates in the advanced and early breast cancer treatment setting, CDK4/6 inhibitors have set a new standard of care for patients with advanced breast cancer. It remains important to better understand resistance mechanisms to be able to develop novel substances and treatment sequences.
CRIS-Team Scopus Importer:2023-04-14
Keywords: abemaciclib; breast cancer; CDK4/6 inhibitor; dalpiciclib; endocrine treatment; palbociclib; ribociclib

Challenges and Opportunities for Real-World Evidence in Metastatic Luminal Breast Cancer - Lüftner, Diana; Hartkopf, Andreas D.; Lux, Michael P.; Overkamp, Friedrich; Tesch, Hans; Titzmann, Adriana; Pöschke, Patrik; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; Belleville, Erik; Janni, Wolfgang; et al. (Breast Care, 2021)
Background: The therapeutic armamentarium for patients with metastatic breast cancer is becoming more and more specific. Recommendations from clinical trials are not available for all treatment situations and patient subgroups, and it is therefore important to collect real-world data. Summary: To develop recommendations for up-to-date treatments and participation in clinical trials for patients with metastatic breast cancer, the Prospective Academic Translational Research PRAEGNANT Network was established to optimize the quality of oncological care in the advanced therapeutic setting. The main aim of PRAEGNANT is to systematically record medical care for patients with metastatic breast cancer in the real-life setting, including the outcome and side effects of different treatment strategies, to monitor quality-of-life changes during therapy, to identify patients eligible for participation in clinical studies, and to allow targeted therapies based on the molecular structures of breast carcinomas. Key Messages: This article describes the PRAEGNANT network and sheds light on the question of whether the various end points from clinical trials can be transferred to the real-world treatment situation.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Breast cancer; Luminal; Metastasis; PRAEGNANT; Real-world evidence

Changes in serum levels of miR-21, miR-210, and miR-373 in HER2-positive breast cancer patients undergoing neoadjuvant therapy: a translational research project within the Geparquinto trial - Mueller, Volkmar; Gade, Stephan; Steinbach, Bettina; Loibl, Sibylle; Von Minckwitz, Gunter; Untch, Michael; Schwedler, Kathrin; Luebbe, Kristina; Schem, Christian; Fasching, Peter; Mau, Christine; Pantel, Klaus; et al. (Breast Cancer Research and Treatment, 2014)
Trastuzumab and lapatinib are established treatments for patients with HER2 (human epidermal growth factor receptor 2)-positive breast cancer with different mechanisms of action. The focus of this study is to investigate, whether altered expression levels of potentially relevant microRNAs (miRs) in serum are associated with response to trastuzumab or lapatinib. Circulating miR-21, miR-210, and miR-373 were quantified with TaqMan MicroRNA assays in serum of 127 HER2-postive breast cancer patients before and after neoadjuvant therapy and in 19 healthy controls. Patients received chemotherapy combined with either trastuzumab or lapatinib within the prospectively randomized Geparquinto trial. The association between miR levels and pathological response (pCR) to therapy and type of therapy was examined. Serum levels of miR-21 (p = 5.04e-08, p = 1.43e-10), miR-210 (p = 0.00151, p = 1.6e-05), and miR-373 (p = 7.87e-06, p = 1.75e-07) were significantly higher in patients before and after chemotherapy than in healthy women. Concentrations of miR-21 (p = 5.73e-08), miR-210 (p = 0.000724), and miR-373 (p = 0.00209) increased further after chemotherapy. A significant association of higher serum levels of miR-373 with advanced clinical tumor stage could be detected (p < 0.002). An association of miR-21 levels before (p = 0.0091) and after (p = 0.037) chemotherapy with overall survival of the patients could be detected, independent of type of anti-HER2 therapy. No association of circulating miRs with pCR was found. Our findings demonstrate a specific influence of neoadjuvant therapy on the serum levels of miR-21, miR-210, and miR-373 in breast cancer patients together with a prognostic value of miR-21.
EVALuna2:17515

Characteristics and clinical outcome of breast cancer patients with asymptomatic brain metastases - Laakmann, E.; Witzel, I.; Neunhoeffer, T.; Weide, R.; Schmidt, M.; Park-Simon, T. W.; Mobus, V.; Mundhenke, Christoph; Polasik, A.; Lubbe, K.; Hesse, T.; Riecke, K.; et al. (EUROPEAN JOURNAL OF CANCER, 2020)
CRIS-Team WoS Importer:2020-11-13

Characteristics and clinical outcome of breast cancer patients with asymptomatic brain metastases - Laakmann, Elena; Witzel, Isabell; Neunhöffer, Tanja; Weide, Rudolf; Schmidt, Marcus; Park-Simon, Tjoung Won; Möbus, Volker; Mundhenke, Christoph; Polasik, Arkadius; Lübbe, Kristina; Hesse, Tobias; Riecke, Kerstin; et al. (Cancers, 2020)
Background: Brain metastases (BM) have become a major challenge in patients with metastatic breast cancer. Methods: The aim of this analysis was to characterize patients with asymptomatic BM (n = 580) in the overall cohort of 2589 patients with BM from our Brain Metastases in Breast Cancer Network Germany (BMBC) registry. Results: Compared to symptomatic patients, asymptomatic patients were slightly younger at diagnosis (median age: 55.5 vs. 57.0 years, p = 0.01), had a better performance status at diagnosis (Karnofsky index 80–100%: 68.4% vs. 57%, p < 0.001), a lower number of BM (>1 BM: 56% vs. 70%, p = 0.027), and a slightly smaller diameter of BM (median: 1.5 vs. 2.2 cm, p < 0.001). Asymptomatic patients were more likely to have extracranial metastases (86.7% vs. 81.5%, p = 0.003) but were less likely to have leptomeningeal metastasis (6.3% vs. 10.9%, p < 0.001). Asymptomatic patients underwent less intensive BM therapy but had a longer median overall survival (statistically significant for a cohort of HER2-positive patients) compared to symptomatic patients (10.4 vs. 6.9 months, p < 0.001). Conclusions: These analyses show a trend that asymptomatic patients have less severe metastatic brain disease and despite less intensive local BM therapy still have a better outcome (statistically significant for a cohort of HER2-positive patients) than patients who present with symptomatic BM, although a lead time bias of the earlier diagnosis cannot be ruled out. Our analysis is of clinical relevance in the context of potential trials examining the benefit of early detection and treatment of BM.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Asymptomatic; Brain metastases; Breast cancer

Characterization of Hormone Receptor and HER2 Status in Breast Cancer Using Mass Spectrometry Imaging - Gonçalves, Juliana Pereira Lopes; Bollwein, Christine; Noske, Aurelia; Jacob, Anne; Jank, Paul; Loibl, Sibylle; Nekljudova, Valentina; Fasching, Peter; Karn, Thomas; Marmé, Frederik; Müller, Volkmar; Schem, Christian; et al. (International Journal of Molecular Sciences, 2023)
Immunohistochemical evaluation of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2 status stratify the different subtypes of breast cancer and define the treatment course. Triple-negative breast cancer (TNBC), which does not register receptor overexpression, is often associated with worse patient prognosis. Mass spectrometry imaging transcribes the molecular content of tissue specimens without requiring additional tags or preliminary analysis of the samples, being therefore an excellent methodology for an unbiased determination of tissue constituents, in particular tumor markers. In this study, the proteomic content of 1191 human breast cancer samples was characterized by mass spectrometry imaging and the epithelial regions were employed to train and test machine-learning models to characterize the individual receptor status and to classify TNBC. The classification models presented yielded high accuracies for estrogen and progesterone receptors and over 95% accuracy for classification of TNBC. Analysis of the molecular features revealed that vimentin overexpression is associated with TNBC, supported by immunohistochemistry validation, revealing a new potential target for diagnosis and treatment.
CRIS-Team Scopus Importer:2023-02-24
Keywords: breast cancer; histopathology; mass spectrometry imaging; proteomics; tissue typing

Characterization of Molecular Subtypes of Paget Disease of the Breast Using Immunohistochemistry and In Situ Hybridization - Wachter, David; wachter, peter wolf; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Riener, Marc-Oliver; Hartmann, Arndt; Strehl, Johanna D. (Archives of Pathology & Laboratory Medicine, 2018)
CONTEXT: - Paget disease of the breast, in most cases, represents intraepidermal spread of ductal carcinoma in situ. Molecular subtypes of invasive carcinoma of the breast have prognostic and therapeutic significance and show characteristic distribution. Little is known about the distribution of molecular subtypes in Paget disease of the breast. OBJECTIVES: - To examine the distribution of molecular subtypes in Paget disease of the breast and to compare them to concurrent invasive carcinoma of the breast, if present. DESIGN: - We examined 48 cases of Paget disease of the breast with immunohistochemistry and antibodies against estrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2), and Ki-67, as well as HER2 chromogenic in situ hybridization, to classify the cases into molecular subtypes. Then, we compared the results to the molecular subtypes of associated, invasive carcinoma of the breast, if present. RESULTS: - The HER2 subtype was the most common found in Paget disease of the breast, followed by the luminal B subtype and 2 cases of the triple-negative subtype. The associated, invasive carcinoma cases were most often of the luminal B subtype, followed by the HER2 subtype and the triple-negative subtype. The molecular subtype of Paget disease and invasive carcinoma was congruent in most of the cases. CONCLUSIONS: - Molecular subtypes of invasive carcinoma of the breast can already be detected in Paget disease. The distribution of molecular subtypes of Paget disease and of Paget disease-associated, invasive carcinoma differs from invasive carcinoma without associated Paget disease, with the HER2 subtype overrepresented in Paget disease and associated, invasive carcinoma and the luminal and triple-negative subtypes underrepresented.
EVALuna2:34808

Characterizing mammographic images by using generic texture features - Häberle, Lothar; Wagner, Florian; Fasching, Peter; Jud, Sebastian; Heusinger, Katharina; Löhberg, Christian; Hein, Alexander; Bayer, Christian M.; Hack, Carolin; Lux, Michael P.; Binder, Katja; Elter, Matthias; et al. (Breast Cancer Research, 2012)
Introduction: Although mammographic density is an established risk factor for breast cancer, its use is limited in clinical practice because of a lack of automated and standardized measurement methods. The aims of this study were to evaluate a variety of automated texture features in mammograms as risk factors for breast cancer and to compare them with the percentage mammographic density (PMD) by using a case-control study design.Methods: A case-control study including 864 cases and 418 controls was analyzed automatically. Four hundred seventy features were explored as possible risk factors for breast cancer. These included statistical features, moment-based features, spectral-energy features, and form-based features. An elaborate variable selection process using logistic regression analyses was performed to identify those features that were associated with case-control status. In addition, PMD was assessed and included in the regression model.Results: Of the 470 image-analysis features explored, 46 remained in the final logistic regression model. An area under the curve of 0.79, with an odds ratio per standard deviation change of 2.88 (95% CI, 2.28 to 3.65), was obtained with validation data. Adding the PMD did not improve the final model.Conclusions: Using texture features to predict the risk of breast cancer appears feasible. PMD did not show any additional value in this study. With regard to the features assessed, most of the analysis tools appeared to reflect mammographic density, although some features did not correlate with PMD. It remains to be investigated in larger case-control studies whether these features can contribute to increased prediction accuracy. © 2012 Fasching et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Chemotherapy (CT)-induced anaemia in patients (pts) treated with dose-dense regimen: Results of the prospectively randomised anaemia substudy from the neoadjuvant GeparOcto study - Tesch, H.; Loibl, S.; Kast, K.; Jackisch, C.; Moebus, V.; Buchen, S.; Untch, M.; Hanusch, C.; Seiler, S.; Weigel, M.; Fasching, Peter; Rhiem, K.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Chemotherapy-induced ovarian failure in young women with early breast cancer: Prospective analysis of four randomised neoadjuvant/adjuvant breast cancer trials - Furlanetto, Jenny; Marmé, Frederik; Seiler, Sabine; Thode, Christian; Untch, Michael; Schmatloch, Sabine; Schneeweiss, Andreas; Bassy, Martina; Fasching, Peter; Strik, Dominika; Stickeler, Elmar; Schem, Christian; et al. (European Journal of Cancer, 2021)
Background: Young women receiving chemotherapy for early breast cancer (EBC) have a high probability for ovarian failure, defined by chemotherapy-induced amenorrhea (CIA) as a surrogate. CIA is insufficiently reliable and reproducible. We analysed chemotherapy-induced ovarian failure (CIOF) by assessing hormone parameters, CIA, and antral follicle count (AFC). Methods: Blood samples of women aged ≤45 years treated with anthracycline/taxane-based chemotherapy for EBC from four neoadjuvant/adjuvant trials were collected at baseline, at the end of treatment (EOT), and at 6, 12, 18, and 24 months after EOT. Centrally assessed oestradiol (cutoff <52.2 ng/L) and follicle-stimulating hormone (cutoff >12.4IU/L) were used to define CIOF for patients with baseline premenopausal hormone levels, anti-Müllerian hormone (AMH), and AFC to assess ovarian reserve. Further analyses included CIA, regain of premenopausal hormone levels, and disease-free survival (DFS) also in subgroups. Results: Six hundred ninety-six patients aged ≤45 years had premenopausal hormone levels at baseline. Overall, 85.1% (592/696) experienced CIOF at EOT, and 147 of 592 had further hormone measurements after EOT. Of those, 32.7% (48/147) regained premenopausal hormone levels after 6 months, 57.9% (66/114) regained premenopausal hormone levels after 12 months, 83.0% (73/88) regained premenopausal hormone levels after 18 months, and 89.2% (74/83) regained premenopausal hormone levels after 24 months. After 24 months, 72.4% (21/29) of patients without CIOF and 100% (14/14) with CIOF had low AMH levels. Four-year DFS without CIOF versus CIOF was 65.9% versus 84.6% (hazard ratio [HR] = 2.09, 95% confidence interval [CI]: 1.37–3.19; P < 0.001); in hormone receptor positive 61.8% versus 87.5% (HR = 2.69, 95% CI: 1.57–4.60; P < 0.001); in <30 years 68.3% versus 92.6% (HR = 4.87, 95% CI: 1.05–22.63; P = 0.026). Conclusion: Most premenopausal women experienced CIOF after chemotherapy for EBC. After 2 years, nearly all regain premenopausal hormone levels. CIOF was associated with better DFS, especially in patients with hormone receptor–positive EBC or aged <30 years.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Chemotherapy-induced amenorrhea; Chemotherapy-induced ovarian failure; Early breast cancer; Ovarian reserve; Young women

Circulating micro-RNAs as potential blood-based markers for early stage breast cancer detection - Schrauder, Michael G.; Strick, Reiner; Schulz-Wendtland, Rüdiger; Strissel, Pamela; Kahmann, Laura; Loehberg, Christian R.; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; et al. (PLoS ONE, 2012)
Introduction: MicroRNAs (miRNAs, miRs) are a class of small, non-coding RNA molecules with relevance as regulators of gene expression thereby affecting crucial processes in cancer development. MiRNAs offer great potential as biomarkers for cancer detection due to their remarkable stability in blood and their characteristic expression in many different diseases. We investigated whether microarray-based miRNA profiling on whole blood could discriminate between early stage breast cancer patients and healthy controls. Methods: We performed microarray-based miRNA profiling on whole blood of 48 early stage breast cancer patients at diagnosis along with 57 healthy individuals as controls. This was followed by a real-time semi-quantitative Polymerase Chain Reaction (RT-qPCR) validation in a separate cohort of 24 early stage breast cancer patients from a breast cancer screening unit and 24 age matched controls using two differentially expressed miRNAs (miR-202, miR-718). Results: Using the significance level of p<0.05, we found that 59 miRNAs were differentially expressed in whole blood of early stage breast cancer patients compared to healthy controls. 13 significantly up-regulated miRNAs and 46 significantly down-regulated miRNAs in our microarray panel of 1100 miRNAs and miRNA star sequences could be detected. A set of 240 miRNAs that was evaluated by radial basis function kernel support vector machines and 10-fold cross validation yielded a specificity of 78.8%, and a sensitivity of 92.5%, as well as an accuracy of 85.6%. Two miRNAs were validated by RT-qPCR in an independent cohort. The relative fold changes of the RT-qPCR validation were in line with the microarray data for both miRNAs, and statistically significant differences in miRNA-expression were found for miR-202. Conclusions: MiRNA profiling in whole blood has potential as a novel method for early stage breast cancer detection, but there are still challenges that need to be addressed to establish these new biomarkers in clinical use. © 2012 Schrauder et al.
CRIS-Team Scopus Importer:2021-07-19

Circulating miR-148b and miR-133a as biomarkers for breast cancer detection - Shen, Jie; Hu, Qiang; Schrauder, Michael; Yan, Li; Wang, Dan; Medico, Leonardo; Guo, Yuqing; Yao, Song; Zhu, Qianqian; Liu, Biao; Qin, Maochun; Beckmann, Matthias; et al. (Oncotarget, 2014)
Circulating microRNAs have drawn a great deal of attention as promising novel biomarkers for breast cancer. However, to date, the results are mixed. Here, we performed a three-stage microRNA analysis using plasma samples from breast cancer patients and healthy controls, with efforts taken to address several pitfalls in detection techniques and study design observed in previous studies. In the discovery phase with 122 Caucasian study subjects, we identified 43 microRNAs differentially expressed between breast cancer cases and healthy controls. When those microRNAs were compared with published data from other studies, we identified three microRNAs, including miR-148b, miR-133a and miR-409-3p, whose plasma levels were significantly higher in breast cancer cases than healthy controls and were also significant in previous independent studies. In the validation phase with 50 breast cancer cases and 50 healthy controls, we validated the associations with breast cancer detection for miR-148b and miR-133a (P = 1.5×10-6 and 1.3×10-10, respectively). In the in-vitro study phase, we found that both miR-148b and miR-133a were secreted from breast cancer cell lines, showing their secretory potential and possible tumor origin. Thus, our data suggest that both miR-148b and miR-133a have potential use as biomarkers for breast cancer detection.
EVALuna2:17449

Circulating tumor cells in metastatic breast cancer: clinical relevance and biological potential - Arkadius, Polasik; Marie, Tzschaschel; Fabienne, Schochter; Thomas, W. P. Friedl; Brigitte, Rack; Andreas, Hartkopf; Fasching, Peter; Andreas, Schneeweiss; Volkmar, Mueller; Jens, Huober; Wolfgang, Janni; Tanja, Fehm (Current Opinion in Obstetrics & Gynecology, 2019)
Purpose of review The possibility of tumor dissemination through the blood system has been known for years. Circulating tumor cells (CTCs) are detectable in the peripheral blood of patients with early as well as metastatic breast cancer. The prognostic relevance of this biomarker has already been described. By the use of repeated blood sampling along the course of disease, CTCs can be monitored in terms of a regular 'liquid biopsy'. This review aims to summarize recent research findings and actual ongoing clinical studies to demonstrate the actual and future relevance of CTCs in daily clinical routine. Recent findings Recent research results show that additional molecular analysis of CTCs might be helpful in gaining information about tumor characteristics, tumor heterogeneity and possible therapy resistance. Repetitive invasive core biopsies might be avoided. The assessment of molecular attributes may be indispensable for obtaining an optimized and personalized therapy aiming at extended survival and/or improved quality of life.
CRIS-Team WoS Importer:2019-04-12

Circulating tumor cells predict survival in early average-to-high risk breast cancer patients - Rack, Brigitte; Schindlbeck, Christian; Jueckstock, Julia; Andergassen, Ulrich; Hepp, Philip; Zwingers, Thomas; Friedl, Thomas W. P.; Lorenz, Ralf; Tesch, Hans; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; et al. (Journal of the National Cancer Institute, 2014)
Circulating tumor cells (CTCs) have been shown to predict reduced survival outcomes in metastatic breast cancer.CTCs were analyzed in 2026 patients with early breast cancer before adjuvant chemotherapy and in 1492 patients after chemotherapy using the CellSearch System. After immuno-magnetic enrichment for cells expressing the epithelial-cell adhesion molecule, CTCs were defined as nucleated cells expressing cytokeratin and lacking CD45. The patients were followed for a median of 35 months (range = 0-54). Kaplan-Meier analyses and the log-rank test were used for survival analyses. All statistical tests were two-sided.Before chemotherapy, CTCs were detected in 21.5% of patients (n = 435 of 2026), with 19.6% (n = 136 of 692) of node-negative and 22.4% (n = 299 of 1334) of node-positive patients showing CTCs (P < .001). No association was found with tumor size, grading, or hormone receptor status. After chemotherapy, 22.1% of patients (n = 330 of 1493) were CTC positive. The presence of CTCs was associated with poor disease-free survival (DFS; P < .0001), distant DFS (P < .001), breast cancer-specific survival (P = .008), and overall survival (OS; P = .0002). CTCs were confirmed as independent prognostic markers in multivariable analysis for DFS (hazard ratio [HR] = 2.11; 95% confidence interval [CI] = 1.49 to 2.99; P < .0001) and OS (HR = 2.18; 95% CI = 1.32 to 3.59; P = .002). The prognosis was worst in patients with at least five CTCs per 30 mL blood (DFS: HR = 4.51, 95% CI = 2.59 to 7.86; OS: HR = 3.60, 95% CI = 1.56 to 8.45). The presence of persisting CTCs after chemotherapy showed a negative influence on DFS (HR = 1.12; 95% CI = 1.02 to 1.25; P = .02) and on OS (HR = 1.16; 95% CI = 0.99 to 1.37; P = .06) CONCLUSIONS: These results suggest the independent prognostic relevance of CTCs both before and after adjuvant chemotherapy in a large prospective trial of patients with primary breast cancer.
EVALuna2:17454

Circulating Tumour Cells, Circulating Tumour DNA and Circulating MicroRNA in Metastatic Breast Carcinoma - What is the Role of Liquid Biopsy in Breast Cancer? - Polasik, Arkadius; Tzschaschel, Marie; Schochter, Fabienne; De Gregorio, Amelie; Friedl, Thomas W. P.; Rack, Brigitte; Hartkopf, Andreas; Fasching, Peter; Schneeweiss, Andreas; Mueller, Volkmar; Huober, Jens; Janni, Wolfgang; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Dissemination of tumour cells and the development of solid metastases occurs via blood vessels and lymphatics. Circulating tumour cells (CTCs) and circulating tumour DNA (ctDNA) can be detected in venous blood in patients with early and metastatic breast cancer, and their prognostic relevance has been demonstrated on numerous occasions. Repeated testing for CTCs and ctDNA, or regular so-called "liquid biopsy", can be performed easily at any stage during the course of disease. Additional molecular analysis allows definition of tumour characteristics and heterogeneity that may be associated with treatment resistance. This in turn makes personalised, targeted treatments possible that may achieve both improved overall survival and quality of life.
EVALuna2:36179

Cis-eQTL analysis and functional validation of candidate susceptibility genes for high-grade serous ovarian cancer - Lawrenson, Kate; Li, Qiyan; Kar, Siddhartha; Seo, Ji-Heui; Tyrer, Jonathan; Spindler, Tassja J.; Lee, Janet; Chen, Yibu; Karst, Alison; Drapkin, Ronny; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Nature Communications, 2015)
Genome-wide association studies have reported 11 regions conferring risk of high-grade serous epithelial ovarian cancer (HGSOC). Expression quantitative trait locus (eQTL) analyses can identify candidate susceptibility genes at risk loci. Here we evaluate cis-eQTL associations at 47 regions associated with HGSOC risk (P<=10(-5)). For three cis-eQTL associations (P<1.4 × 10(-3), FDR<0.05) at 1p36 (CDC42), 1p34 (CDCA8) and 2q31 (HOXD9), we evaluate the functional role of each candidate by perturbing expression of each gene in HGSOC precursor cells. Overexpression of HOXD9 increases anchorage-independent growth, shortens population-doubling time and reduces contact inhibition. Chromosome conformation capture identifies an interaction between rs2857532 and the HOXD9 promoter, suggesting this SNP is a leading causal variant. Transcriptomic profiling after HOXD9 overexpression reveals enrichment of HGSOC risk variants within HOXD9 target genes (P=6 × 10(-10) for risk variants (P<10(-4)) within 10 kb of a HOXD9 target gene in ovarian cells), suggesting a broader role for this network in genetic susceptibility to HGSOC.
EVALuna2:9265

Clinical and analytical validation of Ki-67 in 9069 patients from IBCSG VIII + IX, BIG1-98 and GeparTrio trial: systematic modulation of interobserver variance in a comprehensive in silico ring trial - Denkert, Carsten; Budczies, Jan; Regan, Meredith M.; Loibl, Sibylle; Dell’Orto, Patrizia; von Minckwitz, Gunter; Mastropasqua, Mauro G.; Solbach, Christine; Thürlimann, Beat; Mehta, Keyur; Blohmer, Jens Uwe; Colleoni, Marco; et al. (Breast Cancer Research and Treatment, 2019)
Purpose: Ki-67 has been clinically validated for risk assessment in breast cancer, but the analytical validation and cutpoint-definition remain a challenge. Intraclass correlation coefficients (ICCs) are a statistical parameter for Ki-67 interobserver performance. However, the maximum degree of variance among pathologists allowed for meaningful biomarker results has not been defined. Methods: Different amounts of variance were added to central pathology Ki-67 data (n = 9069) from three cohorts (IBCSGVIII + IX, BIG1-98, GeparTrio) by simulation of 4500 evaluations for each cohort, which were grouped by ICCs, ranging from excellent (ICC = 0.9) to poor concordance (ICC = 0.1). Endpoints were disease-free survival (DFS) and pathological complete response (pCR, GeparTrio). Results: Ki-67 was a significant continuous prognostic marker for DFS over a wide range of cutpoints between 8% and 30% in all three cohorts. In our modelling approach, Ki-67 was a stable prognostic marker despite increased interpathologist variance. Even for a poor ICC of 0.5, one or more significant Ki-67 cutoffs were detected in 86.8% (GeparTrio), 92.4% (IBCSGVIII + IX) and 100% of analyses (BIG1-98). Similarly, in GeparTrio, even with an extremely low ICC of 0.2, 99.6% of analyses were significant for pCR. Conclusions: Our study shows that Ki-67 is a continuous marker which is extremely robust to pathologist variation. Even if only 50% of variance is attributable to true Ki-67-based proliferation (ICC = 0.5), this information is sufficient to obtain statistically significant differences in clinical cohorts. This stable performance explains the observation that many Ki-67 studies achieve significant results despite relevant interobserver variance and points to a high clinical validity of this biomarker. For clinical decisions based on analysis of individual patient data, ongoing efforts to further reduce interobserver variability, including ring trials and standardized guidelines as well as image analysis approaches, should be continued.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Adjuvant; Breast cancer; Ki-67; Neoadjuvant; Prediction; Prognosis

Clinical and molecular characteristics of HER2-low-positive breast cancer: pooled analysis of individual patient data from four prospective, neoadjuvant clinical trials - Denkert, Carsten; Seither, Fenja; Schneeweiss, Andreas; Link, Theresa; Blohmer, Jens Uwe; Just, Marianne; Wimberger, Pauline; Forberger, Almuth; Tesch, Hans; Jackisch, Christian; Schmatloch, Sabine; Reinisch, Mattea; et al. (The Lancet. Oncology, 2021)
Background: The development of anti-HER2 antibody–drug conjugates opens new therapeutic options for patients with breast cancer, including patients with low expression of HER2. To characterise this new breast cancer subtype, we have compared the clinical and molecular characteristics of HER2-low-positive and HER2-zero breast cancer, including response to neoadjuvant chemotherapy and prognosis. Methods: In this pooled analysis of individual patient data, we evaluated a cohort of 2310 patients with HER2-non-amplified primary breast cancer that were treated with neoadjuvant combination chemotherapy in four prospective neoadjuvant clinical trials (GeparSepto, NCT01583426; GeparOcto, NCT02125344; GeparX, NCT02682693; Gain-2 neoadjuvant, NCT01690702) between July 30, 2012, and March 20, 2019. Central HER2 testing was done prospectively before random assignment of participants in all trials. HER2-low-positive status was defined as immunohistochemistry (IHC) 1+ or IHC2+/in-situ hybridisation negative and HER2-zero was defined as IHC0, based on the American Society of Clinical Oncology/College of American Pathologists guidelines. Disease-free survival and overall survival data were available for 1694 patients (from all trials except GeparX) with a median follow-up of 46·6 months (IQR 35·0–52·3). Bivariable and multivariable logistic regression models and Cox-proportional hazards models were performed based on a predefined statistical analysis plan for analysis of the endpoints pathological complete response, disease-free survival, and overall survival. Findings: A total of 1098 (47·5%) of 2310 tumours were HER2-low-positive and 1212 (52·5%) were HER2-zero. 703 (64·0%) of 1098 patients with HER2-low-positive tumours were hormone receptor positive, compared with 445 (36·7%) of 1212 patients with HER2-zero tumours (p<0.0001). HER2-low-positive tumours had a significantly lower pathological complete response rate than HER2-zero tumours (321 [29·2%] of 1098 vs 473 [39·0%] of 1212, p=0·0002). Pathological complete response was also significantly lower in HER2-low-positive tumours versus HER2-zero tumours in the hormone receptor-positive subgroup (123 [17·5%] of 703 vs 105 [23·6%] of 445, p=0·024), but not in the hormone receptor-negative subgroup (198 [50·1%] of 395 vs 368 [48·0%] of 767, p=0·21). Patients with HER2-low-positive tumours had significantly longer survival than did patients with HER2-zero tumours (3-year disease-free survival: 83·4% [95% CI 80·5–85·9] vs 76·1% [72·9–79·0]; stratified log-rank test p=0·0084; 3-year overall survival: 91·6% [84·9–93·4] vs 85·8% [83·0–88·1]; stratified log-rank test p=0·0016). Survival differences were also seen in patients with hormone receptor-negative tumours (3-year disease-free survival: 84·5% [95% CI 79·5–88·3] vs 74·4% [70·2–78.0]; stratified log-rank test p=0·0076; 3-year overall survival: 90·2% [86·0–93·2] vs 84·3% [80·7–87·3], stratified log-rank test p=0·016), but not in patients with hormone receptor-positive tumours (3-year disease-free survival 82·8% [79·1–85·9] vs 79·3% [73·9–83·7]; stratified log-rank test p=0·39; 3-year overall survival 92·3% [89·6–94·4] vs 88·4% [83·8–91·8]; stratified log-rank test p=0·13). Interpretation: Our results show that HER2-low-positive tumours can be identified as new subgroup of breast cancer by standardised IHC, distinct from HER2-zero tumours. HER2-low-positive tumours have a specific biology and show differences in response to therapy and prognosis, which is particularly relevant in therapy-resistant, hormone receptor-negative tumours. Our results provide a basis for a better understanding of the biology of breast cancer subtypes and the refinement of future diagnostic and therapeutic strategies. Funding: German Cancer Aid (Deutsche Krebshilfe).
CRIS-Team Scopus Importer:2021-08-20

Clinical and pathological associations of PTEN expression in ovarian cancer: a multicentre study from the Ovarian Tumour Tissue Analysis Consortium - Martins, Filipe Correia; Couturier, Dominique Laurent; Paterson, Anna; Karnezis, Anthony N.; Chow, Christine; Nazeran, Tayyebeh M.; Odunsi, Adekunle; Gentry-Maharaj, Aleksandra; Vrvilo, Aleksandra; Hein, Alexander; Talhouk, Aline; Osorio, Ana; et al. (British Journal of Cancer, 2020)
Background: PTEN loss is a putative driver in histotypes of ovarian cancer (high-grade serous (HGSOC), endometrioid (ENOC), clear cell (CCOC), mucinous (MOC), low-grade serous (LGSOC)). We aimed to characterise PTEN expression as a biomarker in epithelial ovarian cancer in a large population-based study. Methods: Tumours from 5400 patients from a multicentre observational, prospective cohort study of the Ovarian Tumour Tissue Analysis Consortium were used to evaluate associations between immunohistochemical PTEN patterns and overall survival time, age, stage, grade, residual tumour, CD8+ tumour-infiltrating lymphocytes (TIL) counts, expression of oestrogen receptor (ER), progesterone receptor (PR) and androgen receptor (AR) by means of Cox proportional hazard models and generalised Cochran–Mantel–Haenszel tests. Results: Downregulation of cytoplasmic PTEN expression was most frequent in ENOC (most frequently in younger patients; p value = 0.0001) and CCOC and was associated with longer overall survival in HGSOC (hazard ratio: 0.78, 95% CI: 0.65–0.94, p value = 0.022). PTEN expression was associated with ER, PR and AR expression (p values: 0.0008, 0.062 and 0.0002, respectively) in HGSOC and with lower CD8 counts in CCOC (p value < 0.0001). Heterogeneous expression of PTEN was more prevalent in advanced HGSOC (p value = 0.019) and associated with higher CD8 counts (p value = 0.0016). Conclusions: PTEN loss is a frequent driver in ovarian carcinoma associating distinctly with expression of hormonal receptors and CD8+ TIL counts in HGSOC and CCOC histotypes.
CRIS-Team Scopus Importer:2020-06-26

Clinical Characteristics and Prognosis of HER2-0 and HER2-Low-Positive Breast Cancer Patients: Real-World Data from Patients Treated with Neoadjuvant Chemotherapy - Pöschke, Patrik; Fasching, Peter; Adler, Werner; Rübner, Matthias; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Cancers, 2023)
In our study, we observed the long-term survival outcomes investigated for HER2-0 and HER2-low-positive breast cancer patients who received neoadjuvant chemotherapy. Between 1998 and 2020, 10,333 patients with primary breast cancer were treated, including 1373 patients with HER2-0 or HER2-low-positive disease with neoadjuvant chemotherapy. Descriptive analyses were performed, and logistic regression models and survival analyses were calculated for disease-free survival (DFS) and overall survival (OS). Among the 1373 patients, 930 (67.73%) had HER2-low-positive and 443 (32.27%) had HER2-0 tumors. Patients with HER2-0 tumors had a significantly better pathological complete response, 29.25% vs. 20.09%, and pathological complete response/in situ, 31.97% vs. 24.08%, than patients with HER2-low-positive tumors (p < 0.001; p = 0.003), regardless of the hormone receptor (HR) status. No statistically significant differences were observed for the HR-positive (p = 0.315; p = 0.43) or HR-negative subgroups (p = 0.573; p = 0.931). DFS and OS were significantly longer for HR-positive, HER2-low-positive patients (log-rank p = 0.02; p = 0.012). OS was significantly longer for HR-negative, HER2-0 patients (log-rank p = 0.032). No significant DFS differences were found for the HR-negative cohort (log-rank p = 0.232). For the overall cohort, no significant differences were noted between HER2-low-positive and HER2-0 patients, either for DFS (log-rank p = 0.220) or OS (log-rank p = 0.403). These results show different survival outcomes for HER2-0 and HER2-low-positive tumors relative to HR status. These different cohorts can be identified using standardized immunohistochemistry, even retrospectively.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast cancer; HER2; HER2-0; HER2-low-positive; neoadjuvant therapy; prognosis

Clinical effectiveness and safety of olaparib in BRCA-mutated, HER2-negative metastatic breast cancer in a real-world setting: final analysis of LUCY - Balmaña, Judith; Fasching, Peter; Couch, Fergus J.; Delaloge, Suzette; Labidi-Galy, Intidhar; O’Shaughnessy, Joyce; Park, Yeon Hee; Eisen, Andrea F.; You, Benoit; Bourgeois, Hughes; Gonçalves, Anthony; Kemp, Zoe; et al. (Breast Cancer Research and Treatment, 2023)
Purpose: The interim analysis of the phase IIIb LUCY trial demonstrated the clinical effectiveness of olaparib in patients with germline BRCA-mutated (gBRCAm), human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (mBC), with median progression-free survival (PFS) of 8.11 months, which was similar to that in the olaparib arm of the phase III OlympiAD trial (7.03 months). This prespecified analysis provides final overall survival (OS) and safety data. Methods: The open-label, single-arm LUCY trial of olaparib (300 mg, twice daily) enrolled adults with gBRCAm or somatic BRCA-mutated (sBRCAm), HER2-negative mBC. Patients had previously received a taxane or anthracycline for neoadjuvant/adjuvant or metastatic disease and up to two lines of chemotherapy for mBC. Results: Of 563 patients screened, 256 (gBRCAm, n = 253; sBRCAm, n = 3) were enrolled. In the gBRCAm cohort, median investigator-assessed PFS (primary endpoint) was 8.18 months and median OS was 24.94 months. Olaparib was clinically effective in all prespecified subgroups: hormone receptor status, previous chemotherapy for mBC, previous platinum-based chemotherapy (including by line of therapy), and previous cyclin-dependent kinase 4/6 inhibitor use. The most frequent treatment-emergent adverse events (TEAEs) were nausea (55.3%) and anemia (39.2%). Few patients (6.3%) discontinued olaparib owing to a TEAE. No deaths associated with AEs occurred during the study treatment or 30-day follow-up. Conclusion: The LUCY patient population reflects a real-world population in line with the licensed indication of olaparib in mBC. These findings support the clinical effectiveness and safety of olaparib in patients with gBRCAm, HER2-negative mBC. Clinical trial registration: Clinical trials registration number: NCT03286842.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Breast cancer; Breast cancer 1 gene product; Breast cancer 2 gene product; Kaplan–Meier survival curves; Olaparib; Overall survival; Progression-free survival

Clinical effectiveness and safety of olaparib in BRCA-mutated, HER2-negative metastatic breast cancer in a real-world setting: Phase IIIb LUCY final analysis - Balmana, J.; Fasching, Peter; Delaloge, S.; Park, Y. H.; Eisen, A.; Bourgeois, H.; Kemp, Z.; Jankowski, T.; Sohn, J.; Aksoy, S.; Timcheva, C. V.; Park-Simon, T-W.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Clinical effectiveness of olaparib monotherapy in germline BRCA-mutated, HER2-negative metastatic breast cancer in a real-world setting: phase IIIb LUCY interim analysis - Gelmon, Karen A.; Fasching, Peter; Couch, Fergus J.; Balmaña, Judith; Delaloge, Suzette; Labidi-Galy, Intidhar; Bennett, James; McCutcheon, Susan; Walker, Graham; O'Shaughnessy, Joyce; Timcheva, Constanta; Tomova, Antoaneta; et al. (European Journal of Cancer, 2021)
Background: In the phase III OlympiAD trial, olaparib significantly increased progression-free survival (PFS) compared with chemotherapy of physician's choice in patients with germline BRCA-mutated (gBRCAm), human epidermal growth factor 2 (HER2)-negative metastatic breast cancer (mBC). The phase IIIb LUCY trial assessed the clinical effectiveness of olaparib in similar patients, in a setting reflecting clinical practice. Methods: This open-label, single-arm trial of olaparib (300 mg, twice daily) enrolled patients with BRCAm, HER2-negative mBC who had received taxane and/or anthracycline in the (neo)adjuvant/metastatic setting and not more than two lines of prior chemotherapy for mBC. Patients with hormone receptor–positive mBC had progressed on at least one line of endocrine therapy in an adjuvant/metastatic setting and were unsuitable for further endocrine treatment. This interim analysis was planned after 160 PFS events. Results: Of 563 patients screened, 252 patients with gBRCAm were enrolled and received at least one dose of olaparib. The median investigator-assessed PFS was 8.11 months (95% confidence interval [CI], 6.93–8.67; 166/252 events [65.9% maturity]). The investigator-assessed clinical response rate was 48.6%, and median time to first subsequent treatment or death was 9.66 months (95% CI, 8.67–11.14). The most common treatment-emergent adverse events (TEAEs; >20% patients) were nausea, anaemia, asthenia, vomiting and fatigue. Eleven patients (4.4%) discontinued treatment because of a TEAE. Grade 3 or higher TEAEs occurred in 64 patients (25.4%), including anaemia (33 patients; 13.1%). Conclusion: Olaparib was clinically effective in patients with gBRCAm, HER2-negative mBC with safety outcomes consistent with previous findings. ClinicalTrials.gov identifier: NCT03286842.
CRIS-Team Scopus Importer:2021-06-18
Keywords: BRCA1 gene; BRCA2 gene; Breast cancer; Effectiveness; Germline mutation; Metastatic; Olaparib; Progression-free survival; Treatment outcome

Clinical Relevance of Serum HER2 and Circulating Tumor Cell Detection in Metastatic Breast Cancer Patients - Banys-Paluchowski, Malgorzata; Witzel, Isabell; Riethdorf, Sabine; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter; Solomayer, Erich-Franz; Aktas, Bahriye; Kasimir-Bauer, Sabine; Pantel, Klaus; Fehm, Tanja; Mueller, Volkmar (Anticancer Research, 2017)
BACKGROUND/AIM: Presence of circulating tumor cells (CTCs) is associated with impaired survival in metastatic breast cancer (MBC). This study was designed to evaluate whether assessment of serum HER2 (sHER2) levels provide additional prognostic information in MBC. MATERIALS AND METHODS: Two hundred and fifty-three MBC patients were enrolled in this multicentre trial. CTCs were detected before the start of first- or later-line treatment using the CellSearch system. sHER2 was determined using ELISA. RESULTS: ≥5 CTCs were detected in 122 of 245 evaluable patients (49.8%). One hundred and nineteen of 251 patients (47%) had sHER2 levels above 15 ng/ml. Median overall survival (OS) was 16.3 months in patients with elevated sHER2; median OS in patients with non-elevated sHER2 has not been reached (p=0.001). Patients with ≥5 CTCs were more likely to present with elevated sHER2 (61% vs. 33% in those with <5 CTC; p<0.001). In patients with HER2-negative tumors, elevated sHER2 was associated with shorter OS and PFS; in HER2-positive patients with OS only. Including sHER2, CTC status and established prognostic factors into a multivariate analysis, only the presence of CTCs and higher-line of therapy remained independent predictors of OS. CONCLUSION: Elevated levels of sHER2 are associated with worse survival, irrespective of the HER2 status of the tumor. However, sHER2 does not provide additional prognostic information in patients with known CTC status.
EVALuna2:36192

Clinical validation of genetic variants associated with in vitro chemotherapy-related lymphoblastoid cell toxicity - Fasching, Peter; Häberle, Lothar; Rack, Brigitte; Li, Liang; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, Julie M.; Rübner, Matthias; Jenkins, Gergory; Fridley, Brooke; et al. (Oncotarget, 2017)
Hematotoxicity is one of the major side effects of chemotherapy. The aim of this study was to examine the association between single nucleotide polymorphisms (SNPs) and hematotoxicity in breast cancer patients in a subset of patients of the SUCCESS prospective phase III chemotherapy study. All patients (n = 1678) received three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) followed by three cycles of docetaxel or docetaxel/gemcitabine, depending on randomization. Germline DNA was genotyped for 246 SNPs selected from a previous genome-wide association study (GWAS) in a panel of lymphoblastoid cell lines, with gemcitabine toxicity as the phenotype. All SNPs were tested for their value in predicting grade 3 or 4 neutropenic or leukopenic events (NLEs). Their prognostic value in relation to overall survival and disease-free survival was also tested. None of the SNPs was found to be predictive for NLEs during treatment with docetaxel/gemcitabine. Two SNPs in and close to the PIGB gene significantly improved the prediction of NLEs after FEC, in addition to the factors of age and body surface area. The top SNP (rs12050587) had an odds ratio of 1.38 per minor allele (95% confidence interval, 1.17 to 1.62). No associations were identified for predicting disease-free or overall survival. Genetic variance in the PIGB gene may play a role in determining interindividual differences in relation to hematotoxicity after FEC chemotherapy.
EVALuna2:9381

COGNITION-GUIDE - Genomics-Guided Targeted Post-Neoadjuvant Therapy in Patients with Early Breast Cancer: Study Design of a Multicenter, Open-Label, Umbrella Phase II Study - Pixberg, Constantin; Maurer, Christian; Smetanay, Katharina; Straβl, Luise; Hlevnjak, Mario; Zapatka, Marc; Wagner, Celina V.; Yazdanparast, Haniyeh; Kurzawa, Johanna; Erben, Vanessa; Feng, Fangyoumin; Hong, Chen; et al. (Geburtshilfe und Frauenheilkunde, 2025)
Background As part of the COGNITION diagnostic registry program, residual tumor material after neoadjuvant therapy (NAT) of patients with early breast cancer (eBC), who are still at high-risk for relapse after NAT, is analyzed by next generation sequencing to identify biomarkers and actionable alterations. This strategy aims to stratify patients for subsequent genomics-guided therapies to reduce the significant risk of metastatic dissemination and hence to improve disease-free survival. Patients and Methods COGNITION-GUIDE is a multicenter umbrella phase-II-trial to translate molecular biomarker profiles generated in the COGNITION platform into six molecular-guided post-neoadjuvant therapeutic options in addition to standard-of-care treatment. Patients can be allocated to immune checkpoint inhibition (PD-L1-antibody), PI3K inhibition, AKT inhibition, PARP inhibition, anti-Trop-2 antibody-drug-conjugate, HER2 inhibition or, in case of missing biomarkers, to observation for 12 months. The primary endpoint is invasive disease-free survival (IDFS) four years after surgery. Secondary endpoints include IDFS in each study arm separately, distant disease-free survival, overall survival and safety. 240 patients will be enrolled within four years. Conclusions The COGNITION-GUIDE trial, which was activated in June 2023 and will recruit in different centers in Germany, empowers a risk-adapted, biomarker-guided therapy escalation algorithm in eBC patients who are still at high risk of metastasis.
CRIS-Team Scopus Importer:2025-05-02
Keywords: clinical trial in progress; early breast cancer; precision oncology; targeted therapy

Combined Associations of a Polygenic Risk Score and Classical Risk Factors With Breast Cancer Risk - Kapoor, Pooja Middha; Mavaddat, Nasim; Choudhury, Parichoy Pal; Wilcox, Amber N.; Lindström, Sara; Behrens, Sabine; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Jung, Audrey; Abu-Ful, Zomoroda; et al. (Journal of the National Cancer Institute, 2021)
We evaluated the joint associations between a new 313-variant PRS (PRS313) and questionnaire-based breast cancer risk factors for women of European ancestry, using 72 284 cases and 80 354 controls from the Breast Cancer Association Consortium. Interactions were evaluated using standard logistic regression and a newly developed case-only method for breast cancer risk overall and by estrogen receptor status. After accounting for multiple testing, we did not find evidence that per-standard deviation PRS313 odds ratio differed across strata defined by individual risk factors. Goodness-of-fit tests did not reject the assumption of a multiplicative model between PRS313 and each risk factor. Variation in projected absolute lifetime risk of breast cancer associated with classical risk factors was greater for women with higher genetic risk (PRS313 and family history) and, on average, 17.5% higher in the highest vs lowest deciles of genetic risk. These findings have implications for risk prevention for women at increased risk of breast cancer.
CRIS-Team Scopus Importer:2021-03-26

Common Genetic Variation In Cellular Transport Genes and Epithelial Ovarian Cancer (EOC) Risk - Chornokur, Ganna; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Amankwah, Ernest K.; Qu, Xiaotao; Tsai, Ya-Yu; Jim, Heather S. L.; Chen, Zhihua; Chen, Ann Y.; Permuth-Wey, Jennifer; et al. (PLoS ONE, 2015)
Defective cellular transport processes can lead to aberrant accumulation of trace elements, iron, small molecules and hormones in the cell, which in turn may promote the formation of reactive oxygen species, promoting DNA damage and aberrant expression of key regulatory cancer genes. As DNA damage and uncontrolled proliferation are hallmarks of cancer, including epithelial ovarian cancer (EOC), we hypothesized that inherited variation in the cellular transport genes contributes to EOC risk.In total, DNA samples were obtained from 14,525 case subjects with invasive EOC and from 23,447 controls from 43 sites in the Ovarian Cancer Association Consortium (OCAC). Two hundred seventy nine SNPs, representing 131 genes, were genotyped using an Illumina Infinium iSelect BeadChip as part of the Collaborative Oncological Gene-environment Study (COGS). SNP analyses were conducted using unconditional logistic regression under a log-additive model, and the FDR q<0.2 was applied to adjust for multiple comparisons.The most significant evidence of an association for all invasive cancers combined and for the serous subtype was observed for SNP rs17216603 in the iron transporter gene HEPH (invasive: OR = 0.85, P = 0.00026; serous: OR = 0.81, P = 0.00020); this SNP was also associated with the borderline/low malignant potential (LMP) tumors (P = 0.021). Other genes significantly associated with EOC histological subtypes (p<0.05) included the UGT1A (endometrioid), SLC25A45 (mucinous), SLC39A11 (low malignant potential), and SERPINA7 (clear cell carcinoma). In addition, 1785 SNPs in six genes (HEPH, MGST1, SERPINA, SLC25A45, SLC39A11 and UGT1A) were imputed from the 1000 Genomes Project and examined for association with INV EOC in white-European subjects. The most significant imputed SNP was rs117729793 in SLC39A11 (per allele, OR = 2.55, 95% CI = 1.5-4.35, p = 5.66x10-4).These results, generated on a large cohort of women, revealed associations between inherited cellular transport gene variants and risk of EOC histologic subtypes.
EVALuna2:9283

Common germline polymorphisms associated with breast cancer-specific survival - Pirie, Ailith; Guo, Qi; Kraft, Peter; Canisius, Sander; Eccles, Diana M.; Rahman, Nazneen; Nevanlinna, Heli; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; et al. (Breast Cancer Research, 2015)
Previous studies have identified common germline variants nominally associated with breast cancer survival. These associations have not been widely replicated in further studies. The purpose of this study was to evaluate the association of previously reported SNPs with breast cancer-specific survival using data from a pooled analysis of eight breast cancer survival genome-wide association studies (GWAS) from the Breast Cancer Association Consortium.A literature review was conducted of all previously published associations between common germline variants and three survival outcomes: breast cancer-specific survival, overall survival and disease-free survival. All associations that reached the nominal significance level of P value <0.05 were included. Single nucleotide polymorphisms that had been previously reported as nominally associated with at least one survival outcome were evaluated in the pooled analysis of over 37,000 breast cancer cases for association with breast cancer-specific survival. Previous associations were evaluated using a one-sided test based on the reported direction of effect.Fifty-six variants from 45 previous publications were evaluated in the meta-analysis. Fifty-four of these were evaluated in the full set of 37,954 breast cancer cases with 2,900 events and the two additional variants were evaluated in a reduced sample size of 30,000 samples in order to ensure independence from the previously published studies. Five variants reached nominal significance (P <0.05) in the pooled GWAS data compared to 2.8 expected under the null hypothesis. Seven additional variants were associated (P <0.05) with ER-positive disease.Although no variants reached genome-wide significance (P <5 x 10(-8)), these results suggest that there is some evidence of association between candidate common germline variants and breast cancer prognosis. Larger studies from multinational collaborations are necessary to increase the power to detect associations, between common variants and prognosis, at more stringent significance levels.
EVALuna2:9296

Common non-synonymous SNPs associated with breast cancer susceptibility: findings from the Breast Cancer Association Consortium - Milne, Roger L.; Burwinkel, Barbara; Michailidou, Kyriaki; Arias-Perez, Jose-Ignacio; Pilar Zamora, M.; Menendez-Rodriguez, Primitiva; Hardisson, David; Mendiola, Marta; Gonzalez-Neira, Anna; Pita, Guillermo; Rosario Alonso, M.; Dennis, Joe; et al. (Human Molecular Genetics, 2014)
Candidate variant association studies have been largely unsuccessful in identifying common breast cancer susceptibility variants, although most studies have been underpowered to detect associations of a realistic magnitude. We assessed 41 common non-synonymous single-nucleotide polymorphisms (nsSNPs) for which evidence of association with breast cancer risk had been previously reported. Case-control data were combined from 38 studies of white European women (46 450 cases and 42 600 controls) and analyzed using unconditional logistic regression. Strong evidence of association was observed for three nsSNPs: ATXN7-K264R at 3p21 [rs1053338, per allele OR = 1.07, 95% confidence interval (CI) = 1.04-1.10, P = 2.9 × 10(-6)], AKAP9-M463I at 7q21 (rs6964587, OR = 1.05, 95% CI = 1.03-1.07, P = 1.7 × 10(-6)) and NEK10-L513S at 3p24 (rs10510592, OR = 1.10, 95% CI = 1.07-1.12, P = 5.1 × 10(-17)). The first two associations reached genome-wide statistical significance in a combined analysis of available data, including independent data from nine genome-wide association studies (GWASs): for ATXN7-K264R, OR = 1.07 (95% CI = 1.05-1.10, P = 1.0 × 10(-8)); for AKAP9-M463I, OR = 1.05 (95% CI = 1.04-1.07, P = 2.0 × 10(-10)). Further analysis of other common variants in these two regions suggested that intronic SNPs nearby are more strongly associated with disease risk. We have thus identified a novel susceptibility locus at 3p21, and confirmed previous suggestive evidence that rs6964587 at 7q21 is associated with risk. The third locus, rs10510592, is located in an established breast cancer susceptibility region; the association was substantially attenuated after adjustment for the known GWAS hit. Thus, each of the associated nsSNPs is likely to be a marker for another, non-coding, variant causally related to breast cancer risk. Further fine-mapping and functional studies are required to identify the underlying risk-modifying variants and the genes through which they act.
EVALuna2:9242

Common variants at the CHEK2 gene locus and risk of epithelial ovarian cancer - Lawrenson, Kate; Iversen, Edwin S.; Tyrer, Jonathan; Weber, Rachel Palmieri; Concannon, Patrick; Hazelett, Dennis J.; Li, Qiyuan; Marks, Jeffrey R.; Berchuck, Andrew; Lee, Janet M.; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Carcinogenesis, 2015)
Genome-wide association studies have identified 20 genomic regions associated with risk of epithelial ovarian cancer (EOC), but many additional risk variants may exist. Here, we evaluated associations between common genetic variants [single nucleotide polymorphisms (SNPs) and indels] in DNA repair genes and EOC risk. We genotyped 2896 common variants at 143 gene loci in DNA samples from 15 397 patients with invasive EOC and controls. We found evidence of associations with EOC risk for variants at FANCA, EXO1, E2F4, E2F2, CREB5 and CHEK2 genes (P <= 0.001). The strongest risk association was for CHEK2 SNP rs17507066 with serous EOC (P = 4.74 x 10(-7)). Additional genotyping and imputation of genotypes from the 1000 genomes project identified a slightly more significant association for CHEK2 SNP rs6005807 (r (2) with rs17507066 = 0.84, odds ratio (OR) 1.17, 95% CI 1.11-1.24, P = 1.1×10(-7)). We identified 293 variants in the region with likelihood ratios of less than 1:100 for representing the causal variant. Functional annotation identified 25 candidate SNPs that alter transcription factor binding sites within regulatory elements active in EOC precursor tissues. In The Cancer Genome Atlas dataset, CHEK2 gene expression was significantly higher in primary EOCs compared to normal fallopian tube tissues (P = 3.72×10(-8)). We also identified an association between genotypes of the candidate causal SNP rs12166475 (r (2) = 0.99 with rs6005807) and CHEK2 expression (P = 2.70×10(-8)). These data suggest that common variants at 22q12.1 are associated with risk of serous EOC and CHEK2 as a plausible target susceptibility gene.
EVALuna2:9297

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Comparative assessment of breast volume using a smartphone device versus MRI - Behrens, Annika; Hübner, Hanna; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Heindl, Felix; Emons, Julius; Hack, Carolin; Nabieva, Naiba; Uder, Michael; Wetzl, Matthias; Wunderle, Marius; et al. (Breast Cancer, 2024)
Background: Assessment of breast volume has a relevance for aesthetic surgery and for the prevention and prediction of breast diseases. This study investigated breast volume measurements using a three-dimensional (3D) body surface scanner integrated in a smartphone device in comparison with magnetic resonance imaging (MRI) scans. Methods: Breast volume was assessed for 22 women who underwent routine MRI imaging. 3D surface images were acquired using a smartphone’s digital texture camera (iPhone 11 Pro Max, Apple, California, USA, 2019). Breast volumes were manually outlined and calculated by two independent investigators using a 3D software tool (Meshmixer 3.5, Autodesk, Inc., 2018). Volume assessments from MRI images were performed by a radiologist using Syngo.via (Siemens Healthcare, Erlangen, Germany, VB50). The agreement between both methods and the inter-observer agreement was calculated with the concordance correlation coefficients and analysed with Bland–Altman plots. Results: The mean breast volume as determined by MRI volumetry was 771.0 ml on the left side and 763.9 ml on the right side. Utilizing the 3D body surface volume assessment method, the mean breast volume was measured as 660.3 ml (observer A) and 616.8 ml (observer B) on the left side, and 701.9 ml (observer A) and 638.6 ml (observer B) on the right side. Although a high correlation was observed, differences in volume measurements appeared more pronounced in cases of larger breast volume. Conclusions: Smartphone-based 3D assessment of breast volume sufficiently agreed with MRI-based breast volume. This new technique could be used for cosmetic breast assessments in a surgical context and possibly in breast cancer risk studies assessing breast volume as outcome parameters.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Breast volume; MRI; Smartphone; Three-dimensional (3D)

Comparative effectiveness of ribociclib plus fulvestrant (RIB plus FUL) versus palbociclib plus letrozole (PAL plus LET) as first-line (1L) treatment (Tx) of HR+/HER2L advanced breast cancer (ABC) assessed by matching-adjusted indirect comparison (MAIC) - Fasching, Peter; Delea, T.; Lu, Y-S.; Deboer, R.; Hurvitz, S. A.; Moynahan, A.; Chandiwana, D.; Lanoue, B.; Hu, H.; Thuerigen, A.; O'Shaughnessy, J. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Comparison of 6q25 breast cancer hits from Asian and European genome wide association studies in the Breast Cancer Association consortium (BCAC) - Hein, Rebecca; Maranian, Melanie; Hopper, John L.; Kapuscinski, Miroslaw K.; Southey, Melissa C.; Park, Daniel J.; Schmidt, Marjanka K.; Broeks, Annegien; Hogervorst, Frans B. L.; Bueno-De-Mesquit, H. Bas; Muir, Kenneth R.; Lophatananon, Artitaya; et al. (PLoS ONE, 2012)
The 6q25.1 locus was first identified via a genome-wide association study (GWAS) in Chinese women and marked by single nucleotide polymorphism (SNP) rs2046210, approximately 180 Kb upstream of ESR1. There have been conflicting reports about the association of this locus with breast cancer in Europeans, and a GWAS in Europeans identified a different SNP, tagged here by rs12662670. We examined the associations of both SNPs in up to 61,689 cases and 58,822 controls from forty-four studies collaborating in the Breast Cancer Association Consortium, of which four studies were of Asian and 39 of European descent. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Case-only analyses were used to compare SNP effects in Estrogen Receptor positive (ER+) versus negative (ER-) tumours. Models including both SNPs were fitted to investigate whether the SNP effects were independent. Both SNPs are significantly associated with breast cancer risk in both ethnic groups. Per-allele ORs are higher in Asian than in European studies [rs2046210: OR (A/G) = 1.36 (95% CI 1.26-1.48), p = 7.6×10-14 in Asians and 1.09 (95% CI 1.07-1.11), p = 6.8×10-18 in Europeans. rs12662670: OR (G/T) = 1.29 (95% CI 1.19-1.41), p = 1.2×10-9 in Asians and 1.12 (95% CI 1.08-1.17), p = 3.8×10-9 in Europeans]. SNP rs2046210 is associated with a significantly greater risk of ER- than ER+ tumours in Europeans [OR (ER-) = 1.20 (95% CI 1.15-1.25), p = 1.8×10-17 versus OR (ER+) = 1.07 (95% CI 1.04-1.1), p = 1.3×10-7, pheterogeneity = 5.1×10-6]. In these Asian studies, by contrast, there is no clear evidence of a differential association by tumour receptor status. Each SNP is associated with risk after adjustment for the other SNP. These results suggest the presence of two variants at 6q25.1 each independently associated with breast cancer risk in Asians and in Europeans. Of these two, the one tagged by rs2046210 is associated with a greater risk of ER- tumours. © 2012 Hein et al.
CRIS-Team Scopus Importer:2021-07-19

Comparison of C-Reactive Protein in Dried Blood Spots and Saliva of Healthy Adolescents - Plank, Anne-Christine; Maschke, Janina; Rohleder, Nicolas; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Eichler, Anna; Moll, Gunther; Kratz, Oliver (Frontiers in Immunology, 2021)
Background/AimDetermining C-reactive protein (CRP) by non-invasive methods is of great interest for research addressing inflammation in young people. However, direct comparisons of such methods applied in children and adolescents are lacking so far. This study aimed to evaluate the association between CRP measured in dried blood spots (DBS CRP) and in saliva (sCRP), two less invasive alternatives to venipuncture, in 12- to 14-year-old adolescents. To evaluate the validity of both measurements in the context of biobehavioral studies, the potential of DBS CRP and sCRP to discriminate between defined BMI subgroups was assessed. Materials and MethodsCRP levels in DBS and saliva collected from 87 healthy adolescents (M = 13.25 years, SD = 0.30, 51.7% females) were determined using high sensitive CRP ELISA for serum and salivary CRP ELISA, respectively. Characteristics and correlation of both measurements were assessed for the total sample and for three subgroups classified by BMI percentile ranges (A: <= 25; B: 26-74; C: >= 75). ResultsIn the total sample, DBS CRP and sCRP were significantly associated (r = 0.59, p < 0.001). Splitting the sample into BMI-dependent subgroups revealed similarly strong associations of DBS CRP with sCRP for all three groups (A: r = 0.51; B: r = 0.61; C: r = 0.53). However, comparing the mean CRP values per BMI subgroup, one-way ANOVA reported significant differences for DBS CRP, but not for sCRP mean values. ConclusionsThe significant correlation of DBS CRP with sCRP was independent of the investigated BMI range groups, yet BMI-dependent distinction was only provided by DBS CRP mean values. Overall, our results suggest that DBS CRP is likely to reflect systemic inflammation more precisely. Salivary CRP can be alternatively determined in studies with adolescents when conditions require it, given the oral health status is assessed. Considering that DBS CRP and sCRP share only 35% of common variance, further studies should examine their specific validity.
CRIS-Team WoS Importer:2022-01-14

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comparison of Sonography versus Digital Breast Tomosynthesis to Locate Intramammary Marker Clips - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: This study aimed to compare the accuracy of sonography versus digital breast tomosynthesis to locate intramammary marker clips placed under ultrasound guidance. Patients and Methods: Fifty patients with suspicion of breast cancer (lesion diameter less than 2 cm [cT1]) had ultrasound-guided core needle biopsy with placement of a marker clip in the center of the tumor. Intramammary marker clips were subsequently located with both sonography and digital breast tomosynthesis. Results: Sonography detected no dislocation of intrammammary marker clips in 42 of 50 patients (84 %); dislocation was reported in 8 patients (16 %) with a maximum dislocation of 7 mm along the x-, y- or z-axis. Digital breast tomosynthesis showed accurate placement without dislocation of the intramammary marker clip in 48 patients (96 %); 2 patients (4 %) had a maximum clip dislocation of 3 mm along the x-, y- or z-axis (p < 0.05). Conclusion: The use of digital breast tomosynthesis could improve the accuracy when locating intramammary marker clips compared to sonography and could, in future, be used to complement or even completely replace sonography.
EVALuna2:6724

Complementary and alternative medicine and musculoskeletal pain in the first year of adjuvant aromatase inhibitor treatment in early breast cancer patients - Hack, Caroline; Häberle, Lothar; Brucker, S. Y.; Janni, W.; Volz, B.; Löhberg, Christian; Hartkopf, A. D.; Walter, C. B.; Baake, G.; Fridman, A.; Malter, W.; Wuerstlein, R.; et al. (BREAST, 2020)
Background: Patients with breast cancer (BC) show strong interest in complementary and alternative medicine (CAM), particularly for adverse effects of adjuvant endocrine treatment — e.g., with letrozole. Letrozole often induces myalgia/limb pain and arthralgia, with potential noncompliance and treatment termination. This analysis investigated whether CAM before aromatase inhibitor (AI) therapy is associated with pain development and the intensity of AI-induced musculoskeletal syndrome (AIMSS) during the first year of treatment. Patients and methods: The multicenter phase IV PreFace study evaluated letrozole therapy in postmenopausal, hormone receptor–positive patients with early BC. Patients were asked about CAM use before, 6 months after, and 12 months after treatment started. They recorded pain every month for 1 year in a diary including questions about pain and numeric pain rating scales. Data were analyzed for patients who provided pain information for all time points. Results: Of 1396 patients included, 901 (64.5%) had used CAM before AI treatment. Throughout the observation period, patients with CAM before AI treatment had higher pain values, for both myalgia/limb pain and arthralgia, than non-users. Pain increased significantly in both groups over time, with the largest increase during the first 6 months. No significant difference of pain increase was noted regarding CAM use. Conclusions: CAM use does not prevent or improve the development of AIMSS. Pain intensity was generally greater in the CAM group. Therefore, because of the risk of non-compliance and treatment discontinuation due to the development of higher pain levels, special attention must be paid to patient education and aftercare in these patients.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Aromatase inhibitors; Arthralgia; Breast cancer; Complementary and alternative medicine; Endocrine therapy/treatment; Integrative medicine; Letrozole; Myalgia

Comprehensive characterization of endometriosis patients and disease patterns in a large clinical cohort - Blum, Simon; Fasching, Peter; Hildebrandt, Thomas; Lermann, Johannes; Heindl, Felix; Born, Tilman; Lubrich, Hannah; Antoniadis, Sophia; Becker, Karina; Fahlbusch, Christine; Heusinger, Katharina; Burghaus, Stefanie; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose In many diseases, it is possible to classify a heterogeneous group into subgroups relative to tumor biology, genetic variations, or clinical and pathological features. No such classification is available for endometriosis. In our retrospective case-case analysis we defined subgroups of endometriosis patients relative to the type and location of the endometriosis lesion and relative to basic patient characteristics. Methods From June 2013 to July 2017, a total of 1576 patients with endometriosis diagnosed at surgery were included in this study. The patients' history and clinical data were documented using a web-based remote data entry system. To build subgroups, all possible combinations of endometriosis locations/types (peritoneal; ovarian endometriosis; deeply infiltrating endometriosis; adenomyosis) were used. Due to the variation in group sizes, they were combined into five substantial larger groups. Results Age, pregnancy rate, and live birth rate were identified as characteristics that significantly differed between the five patient groups that were defined. No significant differences were noted in relation to body mass index, length of menstrual cycle, age at menarche, reason for presentation, or educational level. Conclusion This study describes basic patient characteristics in relation to common clinical subgroups in a large clinical cohort of endometriosis patients. Epidemiological information about different clinical groups may be helpful in identifying groups with specific clinical courses, potentially suggesting novel approaches to early detection and to surgical and systemic treatment.
CRIS-Team WoS Importer:2021-09-10

Comprehensive genetic assessment of the ESR1 locus identifies a risk region for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Dennis, Joe; Attia, John; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ashton, Katie; Proietto, Tony; Otton, Geoffrey; et al. (Endocrine-Related Cancer, 2015)
Excessive exposure to estrogen is a well-established risk factor for endometrial cancer (EC), particularly for cancers of endometrioid histology. The physiological function of estrogen is primarily mediated by estrogen receptor alpha, encoded by ESR1. Consequently, several studies have investigated whether variation at the ESR1 locus is associated with risk of EC, with conflicting results. We performed comprehensive fine-mapping analyses of 3633 genotyped and imputed single nucleotide polymorphisms (SNPs) in 6607 EC cases and 37 925 controls. There was evidence of an EC risk signal located at a potential alternative promoter of the ESR1 gene (lead SNP rs79575945, P=1.86×10(-5)), which was stronger for cancers of endometrioid subtype (P=3.76×10(-6)). Bioinformatic analysis suggests that this risk signal is in a functionally important region targeting ESR1, and eQTL analysis found that rs79575945 was associated with expression of SYNE1, a neighbouring gene. In summary, we have identified a single EC risk signal located at ESR1, at study-wide significance. Given SNPs located at this locus have been associated with risk for breast cancer, also a hormonally driven cancer, this study adds weight to the rationale for performing informed candidate fine-scale genetic studies across cancer types.
EVALuna2:9261

Comprehensive visualization of paresthesia in breast cancer survivors - Jud, Sebastian; Hatko, Reinhard; Maihoefner, Christian; Bani, Mayada; Schrauder, Michael G.; Lux, Michael P.; Beckmann, Matthias; Bani, Gassan; Eder, Irina; Fasching, Peter; Löhberg, Christian; Rauh, Claudia; et al. (Archives of Gynecology and Obstetrics, 2014)
As breast cancer survivors are benefiting increasingly from advanced forms of therapy, the side effects of locoregional treatment in the adjuvant setting are becoming more and more important. This article presents a new method of assessing the spatial distribution of paresthesia in breast cancer survivors after different locoregional treatments.A structured questionnaire assessing paresthesia, with body pictograms for marking paresthesia areas, was completed by 343 breast cancer survivors. The image information was digitized, generating gray-scale summation images with numbers from 0, indicating black (100 % of the patients had paresthesia), to 255, indicating white (none had paresthesia). The resulting map visualization showed the locations of paresthesia on body pictograms. The group included patients who had undergone breast-conserving surgery (BCS) and mastectomy, and also patients who had received percutaneous and interstitial radiation.A total of 56.5 % of the patients stated that they had paresthesia. The paresthesia areas were distributed within the range suggested by clinical experience. Most patients stated that they had paresthesia in the upper outer quadrant and axilla. Patients who had undergone mastectomy or percutaneous radiotherapy appeared to have more paresthesia on some areas of the body surface. Patients who had undergone mastectomy indicated larger areas of paresthesia than those with BCS-4,066 pixels (px) vs. 2,275 px. Radiotherapy did not appear to influence the spatial distribution of paresthesia.Paresthesia is a common symptom after breast cancer treatment. This paper describes a new method of assessing this side effect to improve and individualize treatment for it in the future.
EVALuna2:17450

Computerized patient identification for the EMBRACA clinical trial using real-time data from the PRAEGNANT network for metastatic breast cancer patients - Hein, Alexander; Gaß, Paul; Walter, Christina Barbara; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Wuerstlein, Rachel; Lounsbury, Debra; et al. (Breast Cancer Research and Treatment, 2016)
EVALuna2:154
Keywords: BRCA1; BRCA2; Breast cancer; Clinical trial eligibility; PARP inhibitors; Talazoparib

Concerning Dediu M, Zielinski A: A Proposal to Redefine Pathologic Complete Remission as Endpoint following Neoadjuvant Chemotherapy in Early Breast Cancer. Breast Care 2019; Doi 10.1159/000500620 - Untch, Michael; Loibl, Sibylle; Fasching, Peter (Breast Care, 2019)
CRIS-Team Scopus Importer:2019-06-18

Concurrent RB1 Loss and BRCA Deficiency Predicts Enhanced Immunologic Response and Long-term Survival in Tubo-ovarian High-grade Serous Carcinoma - Saner, Flurina A.M.; Takahashi, Kazuaki; Budden, Timothy; Pandey, Ahwan; Ariyaratne, Dinuka; Zwimpfer, Tibor A.; Meagher, Nicola S.; Fereday, Sian; Twomey, Laura; Pishas, Kathleen I.; Hoang, Therese; Bolithon, Adelyn; et al. (Clinical Cancer Research, 2024)
PURPOSE: The purpose of this study was to evaluate RB1 expression and survival across ovarian carcinoma histotypes and how co-occurrence of BRCA1 or BRCA2 (BRCA) alterations and RB1 loss influences survival in tubo-ovarian high-grade serous carcinoma (HGSC). EXPERIMENTAL DESIGN: RB1 protein expression was classified by immunohistochemistry in ovarian carcinomas of 7,436 patients from the Ovarian Tumor Tissue Analysis consortium. We examined RB1 expression and germline BRCA status in a subset of 1,134 HGSC, and related genotype to overall survival (OS), tumor-infiltrating CD8+ lymphocytes, and transcriptomic subtypes. Using CRISPR-Cas9, we deleted RB1 in HGSC cells with and without BRCA1 alterations to model co-loss with treatment response. We performed whole-genome and transcriptome data analyses on 126 patients with primary HGSC to characterize tumors with concurrent BRCA deficiency and RB1 loss. RESULTS: RB1 loss was associated with longer OS in HGSC but with poorer prognosis in endometrioid ovarian carcinoma. Patients with HGSC harboring both RB1 loss and pathogenic germline BRCA variants had superior OS compared with patients with either alteration alone, and their median OS was three times longer than those without pathogenic BRCA variants and retained RB1 expression (9.3 vs. 3.1 years). Enhanced sensitivity to cisplatin and paclitaxel was seen in BRCA1-altered cells with RB1 knockout. Combined RB1 loss and BRCA deficiency correlated with transcriptional markers of enhanced IFN response, cell-cycle deregulation, and reduced epithelial-mesenchymal transition. CD8+ lymphocytes were most prevalent in BRCA-deficient HGSC with co-loss of RB1. CONCLUSIONS: Co-occurrence of RB1 loss and BRCA deficiency was associated with exceptionally long survival in patients with HGSC, potentially due to better treatment response and immune stimulation.
CRIS-Team Scopus Importer:2024-08-23

Conditional progression-free survival in patients with metastatic hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer treated with first-line ribociclib and endocrine therapy: real-world data from the RIBANNA study - Decker, T.; Brucker, C.; Engel, A.; Fasching, Peter; Göhler, T.; Jackisch, C.; Janssen, J.; Köhler, A.; Lüdtke-Heckenkamp, K.; Lüftner, D.; Marmé, F.; van Mackelenbergh, M.; et al. (ESMO Open, 2025)
Background: Progression-free survival (PFS) for patients with metastatic hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) breast cancer significantly improved with cyclin-dependent kinase 4/6 inhibitors as part of first-line treatment. No data is available for these patients on how the risk of progression evolves. Therefore, we analyzed conditional PFS (cPFS), which reflects patient prognosis after initial management, that is, the probability of remaining free from progression in those who have already survived without progression for a given period. Patients and methods: We analyzed PFS and cPFS for patients free from progression after 12, 24, and 36 months (reference time points) treated with ribociclib and endocrine therapy (ET) as first-line treatment for advanced HR+, HER2− breast cancer (aBC) within the RIBANNA noninterventional study (NCT06311383). Relevant subgroups with established prognostic factors were additionally examined. Results: Compared with the median PFS of 35 months (95% confidence interval 32.3-38.4 months) in the overall population, the median cPFS was higher for all reference points: cPFS of 40.5 months (95% confidence interval 35.0-45.5 months) for patients who were progression-free 12 months, cPFS of 53.6 months (95% confidence interval 42.7-not reached months) for 24 months reference point, whereas for the 36 months reference point, the median cPFS was not reached. After patients had reached 2-year disease control, the initial presence of liver metastases or grade 3 disease no longer qualified as poor prognostic factors; internal organ metastases (central nervous system, liver, and lungs) showed a diminishing prognostic impact over time. A short treatment-free interval remained a relevant prognostic factor. Conclusion: For the first time, increasing cPFS was demonstrated in patients treated with ribociclib and ET. Such information is highly relevant and reassuring for patients with HR+, HER2− aBC, and could be used to aid patient counseling and treatment decision-making, including possible de-escalation strategies. It is also a starting point for identifying dynamic prognostic factors related to long-term survival.
CRIS-Team Scopus Importer:2025-05-23
Keywords: advanced breast cancer; conditional progression-free survival; conditional survival; metastatic breast cancer; RIBANNA; ribociclib

Consortium analysis of gene and gene-folate interactions in purine and pyrimidine metabolism pathways with ovarian carcinoma risk - Kelemen, Linda E.; Terry, Kathryn L.; Goodman, Marc T.; Webb, Penelope M.; Bandera, Elisa V.; Mcguire, Valerie; Rossing, Mary Anne; Wang, Qinggang; Dicks, Ed; Tyrer, Jonathan P.; Song, Honglin; Kupryjanczyk, Jolanta; et al. (Molecular Nutrition & Food Research, 2014)
We reevaluated previously reported associations between variants in pathways of one-carbon (1-C) (folate) transfer genes and ovarian carcinoma (OC) risk, and in related pathways of purine and pyrimidine metabolism, and assessed interactions with folate intake.Odds ratios (OR) for 446 genetic variants were estimated among 13,410 OC cases and 22,635 controls, and among 2281 cases and 3444 controls with folate information. Following multiple testing correction, the most significant main effect associations were for dihydropyrimidine dehydrogenase (DPYD) variants rs11587873 (OR = 0.92; p = 6 × 10(-5)) and rs828054 (OR = 1.06; p = 1 × 10(-4)). Thirteen variants in the pyrimidine metabolism genes, DPYD, DPYS, PPAT, and TYMS, also interacted significantly with folate in a multivariant analysis (corrected p = 9.9 × 10(-6)) but collectively explained only 0.2% of OC risk. Although no other associations were significant after multiple testing correction, variants in SHMT1 in 1-C transfer, previously reported with OC, suggested lower risk at higher folate (p(interaction) = 0.03-0.006).Variation in pyrimidine metabolism genes, particularly DPYD, which was previously reported to be associated with OC, may influence risk; however, stratification by folate intake is unlikely to modify disease risk appreciably in these women. SHMT1 SNP-by-folate interactions are plausible but require further validation. Polymorphisms in selected genes in purine metabolism were not associated with OC.
EVALuna2:9231

Co-observation of germline pathogenic variants in breast cancer predisposition genes: Results from analysis of the BRIDGES sequencing dataset - Davidson, Aimee L.; Michailidou, Kyriaki; Parsons, Michael T.; Fortuno, Cristina; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Naven, Marc; Abubakar, Mustapha; Ahearn, Thomas U.; Alonso, M. Rosario; Andrulis, Irene L.; et al. (American Journal of Human Genetics, 2024)
Co-observation of a gene variant with a pathogenic variant in another gene that explains the disease presentation has been designated as evidence against pathogenicity for commonly used variant classification guidelines. Multiple variant curation expert panels have specified, from consensus opinion, that this evidence type is not applicable for the classification of breast cancer predisposition gene variants. Statistical analysis of sequence data for 55,815 individuals diagnosed with breast cancer from the BRIDGES sequencing project was undertaken to formally assess the utility of co-observation data for germline variant classification. Our analysis included expected loss-of-function variants in 11 breast cancer predisposition genes and pathogenic missense variants in BRCA1, BRCA2, and TP53. We assessed whether co-observation of pathogenic variants in two different genes occurred more or less often than expected under the assumption of independence. Co-observation of pathogenic variants in each of BRCA1, BRCA2, and PALB2 with the remaining genes was less frequent than expected. This evidence for depletion remained after adjustment for age at diagnosis, study design (familial versus population-based), and country. Co-observation of a variant of uncertain significance in BRCA1, BRCA2, or PALB2 with a pathogenic variant in another breast cancer gene equated to supporting evidence against pathogenicity following criterion strength assignment based on the likelihood ratio and showed utility in reclassification of missense BRCA1 and BRCA2 variants identified in BRIDGES. Our approach has applicability for assessing the value of co-observation as a predictor of variant pathogenicity in other clinical contexts, including for gene-specific guidelines developed by ClinGen Variant Curation Expert Panels.
CRIS-Team Scopus Importer:2024-08-30
Keywords: ACMG/AMP; BP5; breast cancer; co-observation; genetics; sequencing data; variant classification

Copy Number Variants Are Ovarian Cancer Risk Alleles at Known and Novel Risk Loci - Devries, Amber A.; Dennis, Joe; Tyrer, Jonathan P.; Peng, Pei-Chen; Coetzee, Simon G.; Reyes, Alberto L.; Plummer, Jasmine T.; Davis, Brian D.; Chen, Stephanie S.; Dezem, Felipe Segato; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Journal of the National Cancer Institute, 2022)
Background Known risk alleles for epithelial ovarian cancer (EOC) account for approximately 40% of the heritability for EOC. Copy number variants (CNVs) have not been investigated as EOC risk alleles in a large population cohort. Methods Single nucleotide polymorphism array data from 13 071 EOC cases and 17 306 controls of White European ancestry were used to identify CNVs associated with EOC risk using a rare admixture maximum likelihood test for gene burden and a by-probe ratio test. We performed enrichment analysis of CNVs at known EOC risk loci and functional biofeatures in ovarian cancer-related cell types. Results We identified statistically significant risk associations with CNVs at known EOC risk genes; BRCA1 (P-EOC = 1.60E-21; OREOC = 8.24), RAD51C (Phigh-grade serous ovarian cancer [HGSOC] = 5.5E-4; odds ratio [OR](HGSOC) = 5.74 del), and BRCA2 (P-HGSOC = 7.0E-4; ORHGSOC = 3.31 deletion). Four suggestive associations (P < .001) were identified for rare CNVs. Risk-associated CNVs were enriched (P < .05) at known EOC risk loci identified by genome-wide association study. Noncoding CNVs were enriched in active promoters and insulators in EOC-related cell types. Conclusions CNVs in BRCA1 have been previously reported in smaller studies, but their observed frequency in this large population-based cohort, along with the CNVs observed at BRCA2 and RAD51C gene loci in EOC cases, suggests that these CNVs are potentially pathogenic and may contribute to the spectrum of disease-causing mutations in these genes. CNVs are likely to occur in a wider set of susceptibility regions, with potential implications for clinical genetic testing and disease prevention.
CRIS-Team WoS Importer:2022-10-21

Correction: PredictCBC-2.0: a contralateral breast cancer risk prediction model developed and validated in 200,000 patients (Breast Cancer Research, (2022), 24, 1, (69), 10.1186/s13058-022-01567-3) - Giardiello, Daniele; Hooning, Maartje J.; Hauptmann, Michael; Keeman, Renske; Heemskerk-Gerritsen, B. A.M.; Becher, Heiko; Blomqvist, Carl; Bojesen, Stig E.; Bolla, Manjeet K.; Camp, Nicola J.; Czene, Kamila; Devilee, Peter; et al. (BREAST CANCER RES, 2022)
CRIS-Team Scopus Importer:2022-12-02

Correction to: Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
In the original version of this article contained an error in figure 1. It was provided in German.
EVALuna2:209949

Correction to: Comparative assessment of breast volume using a smartphone device versus MRI (Breast Cancer, (2025), 32, 1, (166-176), 10.1007/s12282-024-01647-6) - Behrens, Annika; Hübner, Hanna; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Heindl, Felix; Emons, Julius; Hack, Carolin; Nabieva, Naiba; Uder, Michael; Wetzl, Matthias; Wunderle, Marius; et al. (Breast Cancer, 2025)
The article ‘Comparative assessment of breast volume using a smartphone device versus MRI’, written by Annika S. Behrens, Hanna Huebner, Lothar Häberle, Marc Stamminger, Daniel Zint, Felix Heindl, Julius Emons, Carolin C. Hack, Naiba Nabieva, Michael Uder, Matthias Wetzl, Marius Wunderle, Matthias W. Beckmann, Peter A. Fasching, Sabine Ohlmeyer, was originally published under exclusive license to The Author(s), under exclusive licence to The Japanese Breast Cancer Society. As a result of the subsequent decision to publish the article under the open access model, the article’s copyright notice was changed on 12 February 2025 to © The Author(s) 2025 and the article is now distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The original article has been corrected.
CRIS-Team Scopus Importer:2025-03-21

Correction to: Genetic drivers and cellular selection of female mosaic X chromosome loss (Nature, (2024), 631, 8019, (134-141), 10.1038/s41586-024-07533-7) - Liu, Aoxing; Genovese, Giulio; Zhao, Yajie; Pirinen, Matti; Zekavat, Seyedeh M.; Kentistou, Katherine A.; Yang, Zhiyu; Yu, Kai; Vlasschaert, Caitlyn; Liu, Xiaoxi; Brown, Derek W.; Hudjashov, Georgi; et al. (Nature, 2024)
Correction to: Naturehttps://doi.org/10.1038/s41586-024-07533-7 Published online 12 June 2024 In the version of this article initially published, members of the Breast Cancer Association Consortium did not appear in the full text and have now been added in the HTML and PDF versions of the article.
CRIS-Team Scopus Importer:2025-02-04

Correction to: TGFB-induced factor homeobox 1 (TGIF) expression in breast cancer (BMC Cancer, (2021), 21, 1, (920), 10.1186/s12885-021-08656-0) - Stuerken, Christine; Moebus, Volker; Milde-Langosch, Karin; Schmatloch, Sabine; Fasching, Peter; Rueschoff, Josef; Stickeler, Elmar; Henke, Rolf-Peter; Denkert, Carsten; Hanker, Lars; Schem, Christian; Vladimirova, Valentina; et al. (BMC Cancer, 2021)
CRIS-Team Scopus Importer:2021-09-24

Correction to: Understanding the genetic complexity of puberty timing across the allele frequency spectrum (Nature Genetics, (2024), 56, 7, (1397-1411), 10.1038/s41588-024-01798-4) - Kentistou, Katherine A.; Kaisinger, Lena R.; Stankovic, Stasa; Vaudel, Marc; Mendes de Oliveira, Edson; Messina, Andrea; Walters, Robin G.; Liu, Xiaoxi; Busch, Alexander S.; Helgason, Hannes; Thompson, Deborah J.; Santoni, Federico; et al. (Nature Genetics, 2024)
Correction to: Nature Geneticshttps://doi.org/10.1038/s41588-024-01798-4, published online 1 July 2024. In the version of the article initially published, in Fig. 5c, the trajectory labels now reading T01, T02, T03, T04, T05, T06, T07, T08, T09 and T10 appeared incorrectly as T-01, T-02, T-03, T-04, T-05, T-06, T-07, T-08, T-09 and T-10. The figure has now been amended in the HTML and PDF versions of the article.
CRIS-Team Scopus Importer:2024-11-01

Correlation of histological and macroscopic findings in peritoneal endometriosis - Strehl, Johanna; Hackl, Janina; Wachter, David; Klingsiek, Peter; Burghaus, Stefanie; Renner, Stefan; Fasching, Peter; Hartmann, Arndt; Beckmann, Matthias (International Journal of Clinical and Experimental Pathology, 2014)
In the last two decades, a color based concept of disease activity in peritoneal endometriosis has been in use in the clinical context, with red lesions being considered active and black or white lesions being interpreted as less active or dormant.Our aim was to analyze 4 main color categories of peritoneal endometriosis (black, white, red and brown) in one single patient group using histomorphological and immunohistochemical methods.65 endometriosis lesions (30 black, 17 white, 11 brown, 7 red) were resected from 47 premenopausal, nulliparous women which had not received exogenous hormones for at least six months prior to the operation. Specimen workup, histomorphological analysis and immunohistochemical analysis were performed in a standardized manner.The color categories showed a broad overlap in proliferative activity and hormone receptor expression. Differences were found in lesion morphology. Adjacent stromal reaction in particular showed a marked increase from red through brown and black to white lesions. Differences were also seen in gland pattern and gland content.Lesion colors in peritoneal endometriosis seem to be determined by gland content and a varying adjacent stromal reaction and more likely reflect an aging process than different levels of disease activity.
EVALuna2:6566

Correlation of mammographic density and serum calcium levels in patients with primary breast cancer - Hack, Carolin; Stoll, Martin; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Haeberle, Lothar; Ganslandt, Thomas; Heindl, Felix; Schulz-Wendtland, Rüdiger; Uder, Michael; Beckmann, Matthias; Fasching, Peter; et al. (Cancer Medicine, 2017)
Percentage mammographic breast density (PMD) is one of the most important risk factors for breast cancer (BC). Calcium, vitamin D, bisphosphonates, and denosumab have been considered and partly confirmed as factors potentially influencing the risk of BC. This retrospective observational study investigated the association between serum calcium level and PMD. A total of 982 BC patients identified in the research database at the University Breast Center for Franconia with unilateral BC, calcium and albumin values, and mammogram at the time of first diagnosis were included. PMD was assessed, using a semiautomated method by two readers. Linear regression analyses were conducted to investigate the impact on PMD of the parameters of serum calcium level adjusted for albumin level, and well-known clinical predictors such as age, body mass index (BMI), menopausal status and confounder for serum calcium like season in which the BC was diagnosed. Increased calcium levels were associated with reduced PMD (P = 0.024). Furthermore, PMD was inversely associated with BMI (P < 0.001) and age (P < 0.001). There was also an association between PMD and menopausal status (P < 0.001). The goodness-of-fit of the regression model was moderate. This is the first study assessing the association between serum calcium level and PMD. An inverse association with adjusted serum calcium levels was observed. These findings add to previously published data relating to vitamin D, bisphosphonates, denosumab, and the RANK/RANKL signaling pathway in breast cancer risk and prevention.
EVALuna2:175

Correlation of RANK and RANKL with mammographic density in primary breast cancer patients - Wunderle, Marius; Heindl, Felix; Behrens, Annika; Häberle, Lothar; Hack, Carolin; Heusinger, Katharina; Hübner, Hanna; Gaß, Paul; Rübner, Matthias; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; et al. (Archives of Gynecology and Obstetrics, 2024)
Purpose: The receptor activator of nuclear factor kappa B (RANK) and its ligand (RANKL) have been shown to promote proliferation of the breast and breast carcinogenesis. The objective of this analysis was to investigate whether tumor-specific RANK and RANKL expression in patients with primary breast cancer is associated with high percentage mammographic density (PMD), which is a known breast cancer risk factor. Methods: Immunohistochemical staining of RANK and RANKL was performed in tissue microarrays (TMAs) from primary breast cancer samples of the Bavarian Breast Cancer Cases and Controls (BBCC) study. For RANK and RANKL expression, histochemical scores (H scores) with a cut-off value of > 0 vs 0 were established. PMD was measured in the contralateral, non-diseased breast. Linear regression models with PMD as outcome were calculated using common predictors of PMD (age at breast cancer diagnosis, body mass index (BMI) and parity) and RANK and RANKL H scores. Additionally, Spearman rank correlations (ρ) between PMD and RANK and RANKL H score were performed. Results: In the final cohort of 412 patients, breast cancer-specific RANK and RANKL expression was not associated with PMD (P = 0.68). There was no correlation between PMD and RANK H score (Spearman’s ρ = 0.01, P = 0.87) or RANKL H score (Spearman’s ρ = 0.04, P = 0.41). RANK expression was highest in triple-negative tumors, followed by HER2-positive, luminal B-like and luminal A-like tumors, while no subtype-specific expression of RANKL was found. Conclusion: Results do not provide evidence for an association of RANK and RANKL expression in primary breast cancer with PMD.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Breast cancer; Immunohistochemistry; Mammographic density; RANK expression; RANKL expression

Corrigendum to “A randomised phase II study investigating durvalumab in addition to an anthracycline taxane-based neoadjuvant therapy in early triple-negative breast cancer: clinical results and biomarker analysis of GeparNuevo study”: [Annals of Oncology (2019), volume 30:1279-1288, (Annals of Oncology (2019) 30(1279-1288) (S0923753419312785)) - Loibl, S.; Untch, M.; Burchardi, N.; Huober, J.; Sinn, B. V.; Blohmer, J. U.; Grischke, E. M.; Furlanetto, J.; Tesch, H.; Hanusch, C.; Engels, K.; Rezai, M.; et al. (Annals of Oncology, 2022)
The authors regret that in the original publication Fig. 3 was incorrectly presented. The correct figure is as below. The following corrections were made: - In figure 3A, part “additional TIL parameters”, box “iTILs postTx”: The number of patients was N=82 (not N=84 as published).- In figure 3B, row “Durvalumab-arm, sTILs preTx”, column “OR”: The estimated odds ratio was 1.29 (not 1.23 as published). This correction also affects the graphical representation left to column “OR”: The diamond marker must be in the center of the line.The authors would like to apologize for any inconvenience caused.[Formula presented]
CRIS-Team Scopus Importer:2022-11-11

Corrigendum to “Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer — Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany” (The Breast (2020) 54 (88–95), (S0960977620301648), (10.1016/j.breast.2020.08.011)) - Schneeweiss, Andreas; Ettl, Johannes; Lüftner, Diana; Beckmann, Matthias; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Geberth, Matthias; Häberle, Lothar; Hadji, Peyman; Hartkopf, Andreas D.; Hielscher, Carsten; et al. (BREAST, 2021)
In Fig. 2c and f of our publication Schneeweiss et al. [1] we mistakenly placed wrong Kaplan Meier Plots. In the attached figure this was corrected. All other estimates concerning the survival including the regression models are correct. We apologize for the mistake. 1. Schneeweiss A, Ettl J, Luftner D et al. Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer - Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany. Breast 2020; 54: 88–95.Fig. 2. Progression-free survival (PFS) and overall survival (OS) for the total group analyzed. CDK4/6i, CDK4/6 inhibitors; ET, endocrine therapy; OS, overall survival; PFS, progression-free survival. [Table presented]
CRIS-Team Scopus Importer:2021-01-15

Corrigendum to Rationale and trial design of NATALEE: a Phase III trial of adjuvant ribociclib + endocrine therapy versus endocrine therapy alone in patients with HR+/HER2- early breast cancer. - Slamon, Dennis J.; Fasching, Peter; Hurvitz, Sara (Therapeutic Advances in Medical Oncology, 2023)
[This corrects the article DOI: 10.1177/17588359231178125.].
EVALuna2:547197

Corrigendum to ‘Ribociclib plus fulvestrant for postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer in the phase III randomized MONALEESA-3 trial: updated overall survival’: [Annals of Oncology Volume 32, Issue 8, August 2021, Pages 1015-1024] (Annals of Oncology (2021) 32(8) (1015–1024), (S0923753421015532), (10.1016/j.annonc.2021.05.353)) - Slamon, D. J.; Neven, P.; Chia, S.; Jerusalem, G.; De Laurentiis, M.; Im, S.; Petrakova, K.; Valeria Bianchi, G.; Martín, M.; Nusch, A.; Sonke, G. S.; De la Cruz-Merino, L.; et al. (Annals of Oncology, 2021)
The authors regret that at the time the article was published, Supplementary Table S2 contained errors. This has now been corrected. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2021-08-27

Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Csorba, Roland; Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (European Journal of Medical Research, 2019)
BACKGROUND: Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. PATIENTS AND METHODS: Real total costs of care for BRRM with and without reconstruction, RRSO, and their combinations were calculated as the sum of all personnel and technical costs. These costs calculated in a German University hospital were compared with the sum of all reimbursements in the German DRG-based health-care system. RESULTS: While sole RRSO, BRRM without reconstruction, and BRRM with secondary DIEP (deep inferior epigastric perforator)-reconstruction still result in a small benefit, we even found shortfalls for the hospital with all other prophylactic operations under consideration. The calculated deficits were especially high for BRRM with implant-based breast reconstruction and for combined operations when the risk reduction is achieved with a minimum of separate operations. CONCLUSIONS: Risk-reducing surgery in BRCA-mutation carriers is frequently not cost-covering for the executing hospitals in the German health-care system. Thus, appropriate concepts are required to ensure a nationwide care.
CRIS-Team Scopus Importer:2019-09-24
Keywords: BRCA; Breast cancer; Cost effectiveness; Genetic counseling; Ovarian cancer

Cost-Effectiveness of Neoadjuvant Pembrolizumab Plus Chemotherapy Followed by Adjuvant Single-Agent Pembrolizumab for High-Risk Early-Stage Triple-Negative Breast Cancer in the United States - Huang, Min; Fasching, Peter; Haiderali, Amin; Xue, Weiguang; Yang, Chelsey; Pan, Wilbur; Zhou, Zheng Yi; Hu, Peter; Chaudhuri, Mitashri; Le Bailly De Tilleghem, Celine; Cappoen, Nicolas; O’Shaughnessy, Joyce (Advances in Therapy, 2023)
Introduction: The randomized phase III KEYNOTE-522 trial demonstrated that addition of pembrolizumab to neoadjuvant chemotherapy provided a significant improvement in event-free survival and a favorable trend in overall survival for high-risk early-stage triple-negative breast cancer (eTNBC). This analysis evaluated the cost-effectiveness of pembrolizumab in combination with chemotherapy as neoadjuvant treatment and continued as a single-agent adjuvant treatment after surgery vs. neoadjuvant chemotherapy for patients with high-risk eTNBC in the USA. Methods: The analysis was conducted from a US third-party public healthcare payer perspective. A multistate transition model was developed using efficacy and safety data from the KEYNOTE-522 trial. The model included four mutually exclusive health states: event-free, locoregional recurrence, distant metastasis, and death to simulate patients’ lifetime disease course. Quality-adjusted life years (QALYs) were calculated on the basis of EuroQoL-5 Dimensions utility data collected in KEYNOTE-522. Costs for drug acquisition/administration, adverse events, disease management, and subsequent therapies were reported (2021 US dollars). Costs and outcomes were discounted at 3% annually. A series of sensitivity analyses were performed to test the robustness of the main results. Results: In the base case scenario, pembrolizumab plus chemotherapy followed by pembrolizumab resulted in expected gains of 3.37 life years (LYs) and 2.90 QALYs, and an incremental cost of 79,046 versus chemotherapy. The incremental cost per QALY gained was 27,285, which is lower than all commonly cited US willingness-to-pay thresholds. Sensitivity analyses showed the results were robust over plausible values of key model inputs and assumptions. Conclusions: Compared with neoadjuvant chemotherapy, pembrolizumab in combination with chemotherapy as neoadjuvant treatment and continued as a single-agent adjuvant treatment after surgery is considered a cost-effective option for high-risk eTNBC in the USA.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Adjuvant therapy; Cost-effectiveness analysis; Early-stage triple-negative breast cancer; Neoadjuvant therapy; Pembrolizumab

COST EFFECTIVENESS OF PEMBROLIZUMAB COMBINED WITH CHEMOTHERAPY VS. CHEMOTHERAPY AS FIRST-LINE TREATMENT FOR METASTATIC TNBC THAT EXPRESSES PD-L1 IN THE UNITED STATES - Huang, M.; Fasching, Peter; Haiderali, A.; Pan, W.; Gray, E.; Zhou, J.; Hu, P. H.; De Tilleghem, Le Bailly C.; Cappoen, N.; Chaudhuri, M.; O'Shaughnessy, J. (VALUE IN HEALTH, 2022)
CRIS-Team WoS Importer:2022-08-26

Cost effectiveness of pembrolizumab in combination with chemotherapy as neoadjuvant therapy and continued as a single agent as adjuvant therapy for high-risk early-stage TNBC in the United States - Fasching, Peter; Huang, M.; Haiderali, A.; Xue, W.; Pan, W.; Zhou, Z-Y.; Hu, P.; Chaudhuri, M.; De Tilleghem, C. Le Bailly; Cappoen, N.; O'Shaughnessy, J. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Cost-effectiveness of pembrolizumab plus chemotherapy as first-line treatment in PD-L1-positive metastatic triple-negative breast cancer - Huang, Min; Fasching, Peter; Haiderali, Amin; Pan, Wilbur; Gray, Emma; Zhou, Zheng-Yi; Hu, Peter; Chaudhuri, Mitashri; De Tilleghem, Celine Le Bailly; Cappoen, Nicolas; O'Shaughnessy, Joyce (Immunotherapy, 2022)
Objective: This study evaluated the cost-effectiveness of pembrolizumab/chemotherapy combinations for previously untreated metastatic triple-negative breast cancer patients in the USA with PD-L1 combined positive score >= 10. Methods: A partitioned-survival model was developed to project health outcomes and direct medical costs over a 20-year time horizon. Efficacy and safety data were from randomized clinical trials. Comparative effectiveness of indirect comparators was assessed using network meta-analyses. A series of sensitivity analyses were performed to test the robustness of the results. Results: Pembrolizumab/chemotherapy resulted in total quality-adjusted life-year (QALY) gains of 0.70 years and incremental cost-effectiveness ratio of US182,732/QALY compared with chemotherapy alone. The incremental cost-effectiveness ratio for pembrolizumab/nab-paclitaxel versus atezolizumab/nab-paclitaxel was US44,157/QALY. Sensitivity analyses showed the results were robust over plausible values of model inputs. Conclusion: Pembrolizumab/chemotherapy is cost effective compared with chemotherapy as well as atezolizumab/nab-paclitaxel as first-line treatment for PD-L1-positive metastatic triple-negative breast cancer from a US payer perspective.
CRIS-Team WoS Importer:2022-07-15

Cost-effectiveness of risk-reducing surgeries in preventing hereditary breast and ovarian cancer - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Wiesmann da Silva Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (BREAST, 2017)
Risk-reducing surgeries are a feasible option for mitigating the risk in individuals with inherited susceptibility to cancer, but are the procedures cost-effective in the current health-care system in Germany? This study compared the health-care costs for bilateral risk-reducing mastectomy (BRRM) and risk-reducing (bilateral) salpingo-oophorectomy (RRSO) with cancer treatment costs that could potentially be prevented.The analysis is based on interdisciplinary consultations with individuals with a high familial risk for breast and ovarian cancer at the University Breast Center for Franconia (Germany) between 2009 and 2013 (370 consultations; 44 patients with BRCA1 mutations and 26 with BRCA2 mutations). Health-care costs for risk-reducing surgeries in BRCA mutation carriers were calculated as reimbursements in the German diagnosis-related groups (DRG) hospital pricing system. These costs for the health-care system were compared with the potential cancer treatment costs that could possibly be prevented by risk-reducing surgeries.Long-term health-care costs can be reduced by risk-reducing surgeries after genetic testing in BRCA mutation carriers. The health-care system in Germany would have saved EUR 136,295 if BRRM had been performed and EUR 791,653 if RRSO had been performed before the development of cancer in only 50% of the 70 mutation carriers seen in our center. Moreover, in patients with combined RRSO and BRRM (without breast reconstruction), one further life-year for a 40-year-old BRCA mutation carrier would cost EUR 2,183.Intensive care, including risk-reducing surgeries in BRCA mutation carriers, is cost-effective from the point of view of the health-care system in Germany.
EVALuna2:9369

Cross-Cancer Genome-Wide Association Study of Endometrial Cancer and Epithelial Ovarian Cancer Identifies Genetic Risk Regions Associated with Risk of Both Cancers - Glubb, Dylan M.; Thompson, Deborah J.; Aben, Katja K. H.; Alsulimani, Ahmad; Amant, Frederic; Annibali, Daniela; Attia, John; Barricarte, Aurelio; Beckmann, Matthias; Berchuck, Andrew; Bermisheva, Marina; Bernardini, Marcus Q.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
Background: Accumulating evidence suggests a relationship between endometrial cancer and ovarian cancer. Independent genome-wide association studies (GWAS) for endometrial cancer and ovarian cancer have identified 16 and 27 risk regions, respectively, four of which overlap between the two cancers. We aimed to identify joint endometrial and ovarian cancer risk loci by performing a meta-analysis of GWAS summary statistics from these two cancers.
CRIS-Team WoS Importer:2021-03-12

Current landscape of hospital information systems in gynecology and obstetrics in Germany: a survey of the commission Digital Medicine of the German Society for Gynecology and Obstetrics - Pfob, André; Griewing, Sebastian; Seitz, Katharina; Hillen, Christoph; Becker, Sven; Bayer, Christian; Wagner, Uwe; Fasching, Peter; Wallwiener, Markus; Abele, Harald; Alexa, Matthias; Cieslik, Jan Philipp; et al. (Archives of Gynecology and Obstetrics, 2023)
Purpose: Hospital information systems (HIS) play a critical role in modern healthcare by facilitating the management and delivery of patient care services. We aimed to evaluate the current landscape of HIS in the specialty of gynecology and obstetrics in Germany. Methods: An anonymous questionnaire was distributed via the German Society of Gynecology and Obstetrics newsletter in December 2022. The questionnaire covered the domains baseline demographic information, satisfaction with daily use, satisfaction with implementation, and degree of digitization. Results: Ninety-one participants completed the survey. Median age was 34 years; 67.4% (60 of 89) were female, and 32.6% (29 of 89) were male. Of the survey participants, 47.7% (42 of 88) were residents, 26.1% (23 of 91) senior physicians, and 9.1% (8 of 88) medical directors. The degree of digitization of clinical documentation is mainly mixed digital and paper-based (64.0%, 57 of 89) while 16.9% (15 of 89) operate mainly paper-based. The current HIS has been in use on average for 9 years. The median number of different software systems used in daily routine is 4. About 33.7% (30 of 89) would likely or very likely recommend their current HIS to a colleague. Conclusions: The current landscape of HIS in gynecology and obstetrics in Germany is characterized by a high heterogeneity of systems with low interoperability and long service life; thus, many healthcare professionals are not satisfied. There is both a need to enhance and an interest in modernizing the technological infrastructure to meet today’s requirements for patient care.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Artificial intelligence; Digital health; eHealth; Gynecology and obstetrics; Implementation

CYP2B6*6 is associated with increased breast cancer risk - Justenhoven, Christina; Pentimalli, Daniela; Rabstein, Sylvia; Harth, Volker; Lotz, Anne; Pesch, Beate; Bruening, Thomas; Doerk, Thilo; Schuermann, Peter; Bogdanova, Natalia; Park-Simon, Tjoung-Won; Couch, Fergus J.; et al. (International Journal of Cancer, 2014)
The cytochrome P450 2B6 (CYP2B6) is involved in the metabolism of testosterone. Functional changes in this enzyme may influence endogenous hormone exposure, which has been associated with risk of breast cancer. To assess potential associations between two functional polymorphisms CYP2B6_516_G>T (rs3745274) and CYP2B6_785_A>G (rs2279343) and breast cancer risk, we established a specific matrix-assisted laser desorption/ionization time-of-flight mass spectrometry assay. The GENICA breast cancer case-control study showed associations between the variant genotypes CYP2B6_516_TT and CYP2B6_785_GG and breast cancer risk with odds ratios (ORs) of 1.34 (p = 0.001) and 1.31 (p = 0.002), respectively. A similar effect was observed for carriers of the CYP2B6_516_T allele in a validation study including four independent studies from Germany, Sweden and USA. In a pooled analysis of all five studies involving 4,638 breast cancer cases and 3,594 controls of European ancestry, carriers of the CYP2B6_516_G and the CYP2B6_785_G variant had an increased breast cancer risk with ORs of 1.10 (p = 0.027) and 1.10 (p = 0.031), respectively. We conclude that the genetic variants CYP2B6_516_G and CYP2B6_785_G (designated CYP2B6*6), which are known to decrease activity of the CYP2B6 enzyme, contribute to an increased breast cancer risk.
EVALuna2:9206

CYP2D6 genotype and adjuvant tamoxifen: meta-analysis of heterogeneous study populations - Province, M. A.; Goetz, M. P.; Brauch, H.; Flockhare, D. A.; Hebert, J. M.; Whaley, R.; Suman, V. J.; Schroth, W.; Winter, S.; Zembutsu, H.; Mushiroda, Taisei; Newman, W. G.; et al. (Clinical Pharmacology & Therapeutics, 2014)
The International Tamoxifen Pharmacogenomics Consortium was established to address the controversy regarding cytochrome P450 2D6 (CYP2D6) status and clinical outcomes in tamoxifen therapy. We performed a meta-analysis on data from 4,973 tamoxifen-treated patients (12 globally distributed sites). Using strict eligibility requirements (postmenopausal women with estrogen receptor-positive breast cancer, receiving 20 mg/day tamoxifen for 5 years, criterion 1); CYP2D6 poor metabolizer status was associated with poorer invasive disease-free survival (IDFS: hazard ratio = 1.25; 95% confidence interval = 1.06, 1.47; P = 0.009). However, CYP2D6 status was not statistically significant when tamoxifen duration, menopausal status, and annual follow-up were not specified (criterion 2, n = 2,443; P = 0.25) or when no exclusions were applied (criterion 3, n = 4,935; P = 0.38). Although CYP2D6 is a strong predictor of IDFS using strict inclusion criteria, because the results are not robust to inclusion criteria (these were not defined a priori), prospective studies are necessary to fully establish the value of CYP2D6 genotyping in tamoxifen therapy.
EVALuna2:17447

Deactivating attachment strategies associate with early processing of facial emotion and familiarity in middle childhood: an ERP study - Kungl, Melanie; Vrticka, Pascal; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Ziegler, Clara; Spangler, Gottfried (Attachment and Human Development, 2022)
Neurophysiological evidence suggests associations between attachment and the neural processing of emotion expressions. This study asks whether this relationship is also evident in middle childhood, and how it is affected by facial familiarity. Attachment strategies (deactivation, hyperactivation) were assessed in 51 9- to 11-year olds using a story stem completion task. Event-related potentials (ERPs) were recorded during children's passive viewing of mother and stranger emotional faces (angry/happy). At the stage of facial information encoding (N250), attachment deactivation was associated with a pattern pointing to increased vigilance towards angry faces. Further, the attention-driven LPP was increased to happy mother faces as highly salient stimuli overall, but not in children scoring high on deactivation. These children did not discriminate between mothers' facial emotions and showed a general attentional withdrawal from facial stimuli. While our results on attachment deactivation support a two-stage processing model, no effect of hyperactivation was found.
CRIS-Team WoS Importer:2022-10-21

DETECT III und IV - Individualisierte CTC-basierte Therapie des HER2-negativen metastasierten Mammakarzinoms - Friedl, T. W. P.; Schneeweiss, A.; Mueller,; Riethdorf, S.; Pantel, K.; Taran, F-A; Polasik, A.; Tzschaschel, M.; Schochter, F.; De Gregorio, A.; Meier-Stiegen, F.; Fasching, Peter; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-07-31

Detection of circulating tumor cells using manually performed immunocytochemistry (MICC) does not correlate with outcome in patients with early breast cancer - Results of the German SUCCESS-A- trial - Jueckstock, Julia; Rack, Brigitte; Friedl, Thomas W. P.; Scholz, Christoph; Steidl, Julia; Trapp, Elisabeth; Tesch, Hans; Forstbauer, Helmut; Lorenz, Ralf; Rezai, Mahdi; Haeberle, Lothar; Alunni-Fabbroni, Marianna; et al. (BMC Cancer, 2016)
BACKGROUND: Recently, the prognostic significance of circulating tumor cells (CTCs) in primary breast cancer as assessed using the Food-and-Drug-Administration-approved CellSearch® system has been demonstrated. Here, we evaluated the prognostic relevance of CTCs, as determined using manually performed immunocytochemistry (MICC) in peripheral blood at primary diagnosis, in patients from the prospectively randomized multicenter SUCCESS-A trial (EudraCT2005000490-21). METHODS: We analyzed 23 ml of blood from 1221 patients with node-positive or high risk node-negative breast cancer before adjuvant taxane-based chemotherapy. Cells were separated using a density gradient followed by epithelial cell labeling with the anti-cytokeratin-antibody A45-B/B3, immunohistochemical staining with new fuchsin, and cytospin preparation. All cytospins were screened for CTCs, and the cutoff for positivity was at least one CTC. The prognostic value of CTCs with regard to disease-free survival (DFS), distant disease-free survival (DDFS), breast-cancer-specific survival (BCSS), and overall survival (OS) was assessed using both univariate analyses applying the Kaplan-Meier method and log-rank tests, and using multivariate Cox regressions adjusted for other predictive factors. RESULTS: In 20.6 % of all patients (n = 251) a median of 1 (range, 1-256) CTC was detected, while 79.4 % of the patients (n = 970) were negative for CTCs before adjuvant chemotherapy. A pT1 tumor was present in 40.0 % of patients, 4.8 % had G1 grading and 34.6 % were node-negative. There was no association between CTC positivity and tumor stage, nodal status, grading, histological type, hormone receptor status, Her2 status, menopausal status or treatment. Univariate survival analyses based on a median follow-up of 64 months revealed no significant differences between CTC-positive and CTC-negative patients with regard to DFS, DDFS, BCSS, or OS. This was confirmed by fully adjusted multivariate Cox regressions, showing that the presence of CTCs (yes/no) as assessed by MICC did not predict DFS, DDFS, BCSS or OS. CONCLUSIONS: We could not demonstrate prognostic relevance regarding CTCs that were quantified using the MICC method at the time of primary diagnosis in our cohort of early breast cancer patients. Further studies are necessary to evaluate if the presence of CTCs assessed using MICC has prognostic relevance, or can be used for risk stratification and treatment monitoring in adjuvant breast cancer. TRIAL REGISTRATION: The ClinicalTrial.gov registration ID of this prospectively randomized trial is NCT02181101 ; the (retrospective) registration date was June 2014 (study start date September 2005).
EVALuna2:32969

Detection of ESR1 Mutations in Single Circulating Tumor Cells on Estrogen Deprivation Therapy but Not in Primary Tumors from Metastatic Luminal Breast Cancer Patients - Franken, André; Honisch, Ellen; Reinhardt, Florian; Meier-Stiegen, Franziska; Yang, Liwen; Jaschinski, Sandra; Esposito, Irene; Alberter, Barbara; Polzer, Bernhard; Hübner, Hanna; Fasching, Peter; Pancholi, Sunil; et al. (Journal of Molecular Diagnostics, 2020)
Mutations in the ligand-binding domain (LBD) of the ESR1 gene result in resistance to estrogen deprivation therapy (EDT) in breast cancer. Their detection might enable optimization of therapy strategies. However, the predictive utility of the primary tumor (PT) is limited, and obtaining serial biopsies of metastatic lesions is challenging. To underline their application as a liquid biopsy, single circulating tumor cells (CTCs) were analyzed with a next-generation sequencing approach for the ESR1 coding region. CTCs from 46 metastatic luminal breast cancer patients were enriched using CellSearch system and isolated by micromanipulation. Their genomic DNA was amplified and the ESR1 gene was sequenced. Furthermore, tissue samples from corresponding PTs and/or metastatic lesions were investigated. ESR1 mutations were detected in 12 patients—exclusively in patients treated with EDT (P = 0.048). In seven cases mutations were located in the hotspot regions in the LBD. Six novel mutations were identified. ESR1 mutations were absent in PT tissue samples and were detected only in metastases obtained after CTC characterization. Single-cell CTC analysis for ESR1 mutations could be of clinical value to identify patients who progress under EDT and therefore benefit from an early switch to an alternative endocrine therapy or other treatment regimens. Furthermore, our data indicate that mutations outside the LBD's hotspot regions might also contribute to resistance to EDT.
CRIS-Team Scopus Importer:2019-12-20

DETECT V/CHEVENDO - duale HER2-zielgerichteten Therapie mit Trastuzumab und Pertuzumab plus Ribociclib in Kombination mit Chemotherapie oder endokriner Therapie bei Patientinnen mit HER2-positivem und hormonrezeptor-positivem metastasierten Mammakarzinom - Friedl, T. W. P.; Polasik, A.; Tzschaschel, M.; Schochter, F.; De Gregorio, A.; Fasching, Peter; Taran, F-A; Schneeweiss, A.; Mueller,; Riethdorf, S.; Pantel, K.; Meier-Stiegen, F.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-07-31

Development and Validation of a Standardized Questionnaire and Standardized Diary for Use in Integrative Medicine Consultations in Gynecologic Oncology - Hack, Carolin; Huettner, N. B. M.; Fasching, Peter; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of complementary and alternative medicine (CAM) in diagnoses is not standardized and is very heterogeneous. There are few published standards on integrative medicine consultations or CAM-specific validated follow-up questionnaires. The aim of this study was to develop a standard for integrative medicine consultations, a patient questionnaire which could be used as a basis for medical decisions, and a diary to evaluate the course of the integrative therapy. Patients and Methods: Between June 2013 and September 2014 a standardized integrative medicine consultation in gynecologic oncology was developed and implemented at the Department of Gynecology and Obstetrics of Erlangen University Hospital. A standard operating procedure for consultations was developed; the necessary instruments were developed and validated. Results: Overall patient assessment of the integrative medicine questionnaire and the integrative medicine diary with regard to the time required for completion, comprehensibility, complexity and functionality was positive. Patients evaluated the standardized overall concept of the integrative medicine consultation and its instruments as suitable. Conclusion: Our team is one of the first study groups to develop, validate and publish a standard procedure for integrative medicine consultations. In future, the standard operating procedure for integrative medicine procedures of the Department of Gynecology and Obstetrics of Erlangen University Hospital could be introduced in other hospitals and certified breast cancer centers and gynecologic cancer centers. This would offer patients maximum security and a standardized quality of care in integrative medicine.
EVALuna2:17565

Development and validation of the gene-expression Predictor of high-grade-serous Ovarian carcinoma molecular subTYPE (PrOTYPE) - Talhouk, Aline; George, Joshy; Wang, Chen; Budden, Timothy; Tan, Tuan Zea; Chiu, Derek S.; Kommoss, Stefan; Leong, Huei San; Chen, Stephanie; Intermaggio, Maria P.; Gilks, Blake; Nazeran, Tayyebeh Mehrane; et al. (Clinical Cancer Research, 2020)
PURPOSE: Gene-expression-based molecular subtypes of high-grade serous tubo-ovarian cancer (HGSOC), demonstrated across multiple studies, may provide improved stratification for molecularly targeted trials. However, evaluation of clinical utility has been hindered by non-standardized methods which are not applicable in a clinical setting. We sought to generate a clinical-grade minimal gene-set assay for classification of individual tumor specimens into HGSOC subtypes and confirm previously reported subtype-associated features. EXPERIMENTAL DESIGN: Adopting two independent approaches, we derived and internally validated algorithms for subtype prediction using published gene-expression data from 1650 tumors. We applied resulting models to NanoString data on 3829 HGSOCs from the Ovarian Tumor Tissue Analysis Consortium. We further developed, confirmed, and validated a reduced, minimal gene-set predictor, with methods suitable for a single patient setting. RESULTS: Gene-expression data was used to derive the Predictor of high-grade-serous Ovarian carcinoma molecular subTYPE (PrOTYPE) assay. We established a de facto standard as a consensus of two parallel approaches. PrOTYPE subtypes are significantly associated with age, stage, residual disease, tumor infiltrating lymphocytes, and outcome. The locked-down clinical-grade PrOTYPE test includes a model with 55 genes that predicted gene-expression subtype with >95% accuracy that was maintained in all analytical and biological validations. CONCLUSIONS: We validated the PrOTYPE assay following the Institute of Medicine guidelines for the development of omics-based tests. This fully defined and locked-down clinical-grade assay will enable trial design with molecular subtype stratification and allow for objective assessment of the predictive value of HGSOC molecular subtypes in precision medicine applications.
CRIS-Team Scopus Importer:2020-06-30

Development of central nervous system metastases as a first site of metastatic disease in breast cancer patients treated in the neoadjuvant trials GeparQuinto and GeparSixto - Laakmann, Elena; Witzel, Isabel; Fasching, Peter; Rezai, Mandi; Schem, Christian; Solbach, Christine; Tesch, Hans; Klare, Peter; Schneeweiss, Andreas; Salat, Christoph; Zahm, Dirk-Michael; Blohmer, Jens-Uwe; et al. (Breast Cancer Research, 2019)
Background: The incidence of central nervous system (CNS) metastases in breast cancer patients is rising and has become a major clinical challenge. Only few data are published concerning risk factors for the development of CNS metastases as a first site of metastatic disease in breast cancer patients. Moreover, the incidence of CNS metastases after modern neoadjuvant treatment is not clear. Methods: We analyzed clinical factors associated with the occurrence of CNS metastases as the first site of metastatic disease in breast cancer patients after neoadjuvant treatment in the trials GeparQuinto and GeparSixto (n = 3160) where patients received targeted treatment in addition to taxane and anthracycline-based chemotherapy. Results: After a median follow-up of 61 months, 108 (3%) of a total of 3160 patients developed CNS metastases as the first site of recurrence and 411 (13%) patients had metastatic disease outside the CNS. Thirty-six patients (1%) developed both CNS metastases and other distant metastases as the first site of metastatic disease. Regarding subtypes of the primary tumor, 1% of luminal A-like (11/954), 2% of luminal B-like (7/381), 4% of HER2-positive (34/809), and 6% of triple-negative patients (56/1008) developed CNS metastases as the first site of metastatic disease. In multivariate analysis, risk factors for the development of CNS metastases were larger tumor size (cT3-4; HR 1.63, 95% CI 1.08-2.46, p = 0.021), node-positive disease (HR 2.57, 95% CI 1.64-4.04, p < 0.001), no pCR after neoadjuvant chemotherapy (HR 2.29, 95% CI 1.32-3.97, p = 0.003), and HER2-positive (HR 3.80, 95% CI 1.89-7.64, p < 0.001) or triple-negative subtype (HR 6.38, 95% CI 3.28-12.44, p < 0.001). Conclusions: Especially patients with HER2-positive and triple-negative tumors are at risk of developing CNS metastases despite effective systemic treatment. A better understanding of the underlying mechanisms is required in order to develop potential preventive strategies.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Breast cancer; Central nervous system metastases; First site of metastatic disease

Diagnosis and Therapy of Triple-Negative Breast Cancer (TNBC) - Recommendations for Daily Routine Practice - Schneeweiss, Andreas; Denkert, Carsten; Fasching, Peter; Fremd, Carlo; Gluz, Oleg; Kolberg-Liedtke, Cornelia; Loibl, Sibylle; Lück, Hans Joachim (Geburtshilfe und Frauenheilkunde, 2019)
The rapid increase in knowledge in tumour biology and tumour pathogenesis of triple-negative breast cancer (TNBC) has resulted in new therapeutic approaches and new therapeutic concepts for treatment. For years, TNBC has been considered to be a difficult-to-treat tumour due to its generally aggressive tumour biology and in view of limited therapeutic options. The risk of recurrence and metastasis is higher than in the case of other breast cancer subtypes of the same stage. In addition to surgery and radiation in the curative situation, systemic chemotherapy with anthracyclines and/or taxanes is still the therapy of choice. New therapeutic approaches are based on the knowledge that TNBC is a molecularly very heterogeneous disease. Research groups are working to classify TNBC better and better on a molecular level and use this molecular subtyping as the basis for new therapeutic strategies. The most promising new approaches and considerations regarding the therapy of TNBCs are shown below. In addition, the current therapeutic strategies are discussed using a fictitious case history, taking the current data and the resultant therapeutic consequence into account.
CRIS-Team Scopus Importer:2019-06-28
Keywords: BRCA mutation; diagnosis and therapy of TNBC; subtyping of TNBC; triple-negative breast cancer

Diagnostic Accuracy of Breast Medical Tactile Examiners (MTEs): A Prospective Pilot Study - Lux, Michael P.; Emons, Julius; Bani, Mayada; Wunderle, Marius; Sell, Charlotte; Preuss, Caroline; Rauh, Claudia; Jud, Sebastian; Heindl, Felix; Langemann, Hanna; Geyer, Thomas; Brandl, Anna-Lisa; et al. (Breast Care, 2019)
Background: The usefulness of clinical breast examination (CBE) in general and in breast cancer screening programs has been a matter of debate. This study investigated whether adding vision-impaired medical tactile examiners (MTEs) improves the predictiveness of CBE for suspicious lesions and analyzed the feasibility and acceptability of this approach. Methods: The prospective study included 104 patients. Physicians and MTEs performed CBEs, and mammography and ultrasound results were used as the gold standard. Sensitivity and specificity were calculated and logistic regression models were used to compare the predictive value of CBE by physicians alone, MTEs alone, and physicians and MTEs combined. Results: For CBEs by physicians alone, MTEs alone, and both combined, sensitivity was 71, 82, and 89% and specificity was 55, 45, and 35%, respectively. Using adjusted logistic regression models, the validated areas under the curve were 0.685, 0.692, and 0.710 (median bootstrapped p value (DeLong) = 0.381). Conclusion: The predictive value for a suspicious breast lesion in CBEs performed by MTEs in patients without prior surgery was similar to that of physician-conducted CBEs. Including MTEs in the CBE procedure in breast units thus appears feasible and could be a way of utilizing their skills. (c) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-03-22

Did you drink alcohol during pregnancy? Inaccuracy and discontinuity of women's self-reports: On the way to establish meconium ethyl glucuronide (EtG) as a biomarker for alcohol consumption during pregnancy - Eichler, Anna; Grunitz, Juliane; Grimm, Jennifer; Walz, Lisa; Raabe, Eva; Goecke, Tamme W.; Beckmann, Matthias; Kratz, Oliver; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Kornhuber, Johannes (Alcohol, 2016)
Consuming alcohol during pregnancy is one of the most verified prenatal risk factors for impaired child development. Information about the amount of alcohol consumed prenatally is needed to anticipate negative effects and to offer timely support. Women's self-reports are not reliable, often influenced by social stigmas and retrospective recall bias, causing biomarkers of intrauterine ethanol exposure to become more and more relevant. The present study compares both women's gestational and retrospective self-reports of prenatal alcohol consumption with levels of ethyl glucuronide (EtG) in meconium. Women (n = 180) gave self-reports of prenatal alcohol consumption both during their 3rd trimester (gestational self-report) and when their children were 6-8 years old (retrospective self-report). Child meconium was collected after birth and analyzed for EtG. No individual feedback of children's EtG level was given to the women. All analyses were run separately for two cut-offs: 10 ng/g (limit of detection) and 120 ng/g (established by Goecke et al., 2014). Mothers of children with EtG values above 10 ng/g (n = 42) tended to report prenatal alcohol consumption more frequently. There was no trend or significance for the EtG cut-off of 120 ng/g (n = 26) or for retrospective self-report. When focusing on women who retrospectively reported alcohol consumption during pregnancy, a claim to five or more consumed glasses per month made an EtG over the 10 ng/g and the 120 ng/g cut-off more probable. Women whose children were over the 10 ng/g EtG cut-off were the most inconsistent in their self-report behavior, whereas the consistency in the above 120 ng/g EtG group was higher than in any other group. The next step to establish EtG as a biomarker for intrauterine alcohol exposure is to correlate EtG values in meconium with child developmental impairments.
EVALuna2:23752

Die Bedeutung mütterlicher präpartaler Depression und Mutter-Kind-Bindung für die Entwicklung der kindlichen Emotionsregulation: Erste Befunde einer Längsschnittstudie - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Differential effect on different immune subsets of neoadjuvant chemotherapy in patients with TNBC - Massa, Chiara; Karn, Thomas; Denkert, Carsten; Schneeweiss, Andreas; Hanusch, Claus; Blohmer, Jens Uwe; Zahm, Dirk Michael; Jackisch, Christian; Van Mackelenbergh, Marion; Thomalla, Jörg; Marme, Frederik; Huober, Jens; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Triple-negative breast cancer (TNBC) is the most aggressive form of breast cancer (BC). Due to the absence of targets such as HER2 or hormone receptors, early TNBC is treated with surgery and chemotherapy. Since TNBC is also considered the most immunogenic type of BC with tumor infiltrating lymphocytes that are predictive for chemotherapy response and prognostic for patients′ survival, many different immunotherapeutic strategies are currently explored in clinical trials for the treatment of this disease. In order to efficiently combine chemotherapy with immunotherapy, it is important to evaluate the effect of chemotherapy on immune cells in vivo. Methods Peripheral blood was taken from 56 patients with TNBC undergoing neoadjuvant chemotherapy with nanoparticle albumin-bound paclitaxel (Nab-Pac) followed by epirubicin and cyclophosphamide (EC) at three different time points. Multicolor flow cytometry was used to characterize the immune cell composition and functional properties along neoadjuvant chemotherapy. Results Whereas the first phase of the neoadjuvant chemotherapy did not significantly alter the patients′ immune cell composition, after the second phase of chemotherapeutic administration most B cells (>90%) were lost and the frequency of natural killer (NK) cells and CD4 + T lymphocytes decreased approximately to 50%. In contrast, the frequency of CD8 + T cells were less affected. Conclusions Despite late consequences of Nab-Pac cannot be ruled out, these data suggest that different chemotherapeutics might have distinct effects on the immune cell repertoire and that different immune cell populations exhibit a specific susceptibility to these chemotherapies with B and NK cells being more affected than T cells. This might also have an impact on the combination of chemotherapies with immunotherapies. Trial registration number NCT02685059.
CRIS-Team Scopus Importer:2020-11-27
Keywords: breast neoplasms; immunocompetence

Differential prognostic relevance of patho-anatomical factors among different tumor-biological subsets of breast cancer: Results from the adjuvant SUCCESS A study - Deniz, Miriam; Degregorio, Amelie; Degregorio, Nikolaus; Bekes, Inga; Widschwendter, Peter; Schochter, Fabienne; Ernst, Kristina; Scholz, Christoph; Bauer, Emanuel C. A.; Aivazova-Fuchs, Viktoria; Weissenbacher, Tobias; Kost, Bernd; et al. (BREAST, 2019)
Objectives: In breast cancer, large tumor size, positive nodal stage and a triple-negative tumor subtype are associated with reduced survival, but the interactions between these prognostic factors are not well understood.
CRIS-Team WoS Importer:2019-03-20

DIFFERENT NUTRIENT INTAKE AND PREVALENCE OF GASTROINTESTINAL COMORBIDITIES IN WOMEN WITH ENDOMETRIOSIS - Schink, Monic; Konturek, P. C.; Herbert, S. L.; Renner, S. P.; Burghaus, Stefanie; Blum, Simon; Fasching, Peter; Neurath, Markus; Zopf, Yurdagül (Journal of Physiology and Pharmacology, 2019)
Even though endometriosis presents one of the most common gynaecological diseases, the pathogenesis is insufficiently studied. Besides immunologic, inflammatory or oxidative processes, recent studies also suggest an influence of nutrition on disease onset and progression. Because data about the actual nutrient intake of endometriosis patients are scarce, we aimed to examine the actual nutrient intake and potential influencing factors in these women. A total of 156 women with endometriosis (EM) and 52 age-matched controls were included in this retrospective case-control study. All women filled in a validated food frequency questionnaire to acquire the nutrient intake of the past 12 months and a disease-related questionnaire for the determination of disease status, clinical symptoms and comorbidities. Patients with endometriosis suffered significantly more from diet-related comorbidities like food intolerances (25.6% versus 7.7%; P = 0.009) and allergies (57% versus 31%; P < 0.001) compared to controls. Also gastrointestinal symptoms, including constipation, flatulence, pyrosis, diarrhea or frequent defecation, were higher in the EM group (77% versus 29%; P < 0.001). The nutrient intake of patients with endometriosis differed significantly compared to controls with a significantly lower ingestion of organic acids (P = 0.006), maltose (P = 0.0.16), glycogen (P = 0.035), tetradecenoic acid (P = 0.041), methionine (P = 0.046), lysine (P = 0.048), threonine (P = 0.046) and histidine (P = 0.049). The total intake of animal proteins was significantly lower in the EM group compared to the controls (P = 0.047). EM patients showed a decreased intake of vitamin C (P = 0.031), vitamin B-12 (P = 0.008) and magnesium (P = 0.043) compared to controls. This study confirms a high association of endometriosis and gastrointestinal disorders accompanied by an altered nutrient intake. A dietary intervention by a professional nutritionist may help to reduce disease burden in the affected women.
CRIS-Team WoS Importer:2019-10-18

Digitalization is not everything but everything is nothing without digitalization Digitalisierung ist nicht alles, aber alles ist nichts ohne Digitalisierung - Kiechle, Marion; Wallwiener, Stephanie; Wagner, Uwe; Fasching, Peter (Die Gynäkologie, 2024)
CRIS-Team Scopus Importer:2025-02-04

Digital Maternity Records: Motivation, Acceptance, Requirements, Usability and Prototype Evaluation of an Interface for Physicians and Midwives - Dörflinger, Luisa; Nissen, Michael; Jäger, Katharina; Wirth, Markus; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (Mensch und Computer 2021, 2021)
Maternity records (”Mutterpass”) are a central tool in Germany’s antenatal care. Its digitalisation offers advantages such as improved readability, data standardisation, analysability, digital assistance and the avoidance of media breaks. Despite the examined necessity and technical possibility, no system has been implemented yet. In this work, we address this gap by assessing physicians’ and midwives’ perception, motivation, acceptance and requirements of a digital maternity record and its user interface in particular. Nine medical professionals participated in semi-structured interviews. Based on the results, an interface prototype was subsequently developed. The prototype laid a particular focus on two different gravidogram implementations. Thirteen medical professionals participated in the interactive user interface study, which aimed to assess general acceptance, completion time, error rate and implemented assistance functions compared to the analogue counterpart. Results show that the implementation of the digital maternity logbook is of value and that its advantages are both accepted and demanded by medical professionals. Eight key requirements were identified. A tabular gravidogram prototype, inspired by the analogue maternity record, was favoured over a more novel list prototype. Users presented a clear learning curve of the digital system. Nevertheless, the digital average completion time is 30% higher than its analogue counterpart. The digital prototype lead to a lower average number of errors per entry (0.45±0.3 vs. 0.58±0.4). With respect to digital maternity records, this work underlines user acceptance, summarizes key user requirements and presents a first step on the path to a digital maternity record interface for medical professionals. On a broader scale, it delivers insights based on several metrics with respect to digitalisation in an area that is still highly dominated by long established paper-based tools.

Digit ratio (2D:4D) and behavioral symptoms in primary-school aged boys - Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Beckmann, Matthias; Goecke, Tamme W.; Fasching, Peter; Muschler, Marcel-Rene; Bouna-Pyrrou, Polyxeni; Lenz, Bernd; Kornhuber, Johannes (Early Human Development, 2018)
The second-to-forth digit length ratio (2D:4D) is considered to be a biomarker for intrauterine androgen levels. It is associated with adult and child mental health problems, primarily with behavioral symptoms and predominantly in males. Using a cross-sectional design, we examined whether 2D:4D was associated with conduct disorder (CD) symptoms in 138 primary-school aged children (54% boys, Mage = 7.70 years) and considered child sex as a moderating factor. Children's digit lengths were measured from hand scans and mothers rated the behavioral/emotional symptoms of their child. The regression analyses revealed that 2D:4D ratios were associated with behavioral symptoms in boys (β = -0.260, p = 0.026), but not in girls (β = -0.040, p = 0.762). Child emotional symptoms, analyzed as a control, were not significantly correlated with 2D:4D. In conclusion, prenatal brain hyperandrogenization - operationalized by the 2D:4D biomarker - could result in behavioral symptoms in boys at early school age, reflecting one predictor for early onset CD. Our data support the use of 2D:4D as a marker of prenatal androgen exposure.
EVALuna2:36369

Discrimination analysis of breast calcifications using x-ray dark-field radiography - Rauch, Thomas; Rieger, Jens; Pelzer, Georg; Horn, Florian; Erber, Ramona; Wunderle, Marius; Emons, Julius; Nabieva, Naiba; Fuhrich, Nicole; Michel, Thilo; Hartmann, Arndt; Fasching, Peter; et al. (Medical Physics, 2020)
Background X-ray dark-field radiography could enhance mammography by providing more information on imaged tissue and microcalcifications. The dark field signal is a measure of small angle scattering and can thus provide additional information on the imaged materials. This information can be useful for material distinction of calcifications and the diagnosis of breast cancer by classifying benign and malign association of these calcifications.
CRIS-Team WoS Importer:2020-03-06

Discussion of ABC7 Consensus and German Recommendations - Untch, Michael; Ditsch, Nina; Fasching, Peter; Busch, Steffi; Ettl, Johannes; Haidinger, Renate; Harbeck, Nadia; Jackisch, Christian; Lüftner, Diana; Müller, Lothar; Ruckhäberle, Eugen; Schumacher-Wulf, Eva; et al. (Geburtshilfe und Frauenheilkunde, 2024)
The rationale behind the International Consensus Conference for Advanced Breast Cancer (ABC) is to standardize the treatment of patients with advanced or metastatic breast cancer worldwide using an evidence-based approach. The aim is also to ensure that patients in all countries receive adequate treatment based on current treatment recommendations and standards. The 7th International Consensus Conference on Advanced Breast Cancer (ABC7) took place from November 9 to 12, 2023 in Lisbon/Portugal. ABC7 focused on metastatic disease as well as on locally advanced and inflammatory breast cancer. Special topics included the treatment of oligometastatic patients, leptomeningeal disease, treatment of brain metastases, and pregnant women with ABC. As in previous years, patient advocates from all over the world participated in the consensus conference and were involved in decision making.
CRIS-Team Scopus Importer:2024-06-14
Keywords: ABC and pregnancy; ADCs; brain metastases; leptomeningeal disease; oligometastases; systemic therapy

Disease-free survival as a surrogate for overall survival in HR+/HER2– early breast cancer: A correlation analysis - Untch, Michael; Pérol, David; Mayer, Erica L.; Cortes, Javier; Nusch, Arnd; Cameron, David; Barrios, Carlos; Delea, Thomas; Danyliv, Andrii; Mishra, Namita; Gupta, Rhea; Pathak, Purnima; et al. (European Journal of Cancer, 2024)
Background: Overall survival (OS) is a universally accepted measure of clinical benefit; however, prolonged follow-up is needed to observe sufficient events. Disease-free survival (DFS) has been widely adopted as a primary endpoint for early breast cancer (EBC) trials, as follow-up is comparatively shorter. Here, we present an analysis evaluating DFS as a surrogate for OS for adjuvant treatment of hormone receptor–positive/human epidermal growth factor receptor 2–negative (HR+/HER2–) EBC. Methods: A systematic literature review which included randomized controlled trials (RCTs) with ≥80% of adult patients with HR+/HER2– EBC was conducted. The RCTs evaluated various systemic therapeutic categories; key inclusion criteria included reporting of DFS and OS hazard ratios (HRs) and mature OS data. Spearman rank correlation and weighted linear regression analyses evaluated DFS and OS HR correlation. A scenario analysis tested base-case analysis robustness, and a parallel analysis using patient-level data was conducted. Results: The base case (N = 14 RCTs) showed an unweighted Spearman coefficient of 0.81 between OS and DFS (weighted: 0.81), with 84% of the variability in OS explained by DFS differences (R2 from weighted regression). The surrogate threshold effect (Burzykowski T, Buyse M. Pharm Stat. 2006;5:173–186) was 0.82 for DFS/OS HR. Scenario analysis (n = 9 RCTs), which excluded chemotherapy trials, and patient-level analysis using FACE trial data were consistent with the base-case analysis. Conclusions: These analyses support DFS as a reliable surrogate endpoint for OS in adjuvant HR+/HER2− EBC trials. Using DFS as a surrogate measure will permit timelier access to novel treatments for patients with HR+/HER2− EBC.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Disease-free survival; HR+/HER2– early breast cancer; Overall survival; Surrogate endpoint

Disentangling the relationships of body mass index and circulating sex hormone concentrations in mammographic density using Mendelian randomization - Haas, Cameron B.; Chen, Hongjie; Harrison, Tabitha; Fan, Shaoqi; Gago-Dominguez, Manuela; Castelao, Jose E.; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Dunning, Alison M.; Easton, Douglas F.; et al. (Breast Cancer Research and Treatment, 2024)
Purpose: Mammographic density phenotypes, adjusted for age and body mass index (BMI), are strong predictors of breast cancer risk. BMI is associated with mammographic density measures, but the role of circulating sex hormone concentrations is less clear. We investigated the relationship between BMI, circulating sex hormone concentrations, and mammographic density phenotypes using Mendelian randomization (MR). Methods: We applied two-sample MR approaches to assess the association between genetically predicted circulating concentrations of sex hormones [estradiol, testosterone, sex hormone-binding globulin (SHBG)], BMI, and mammographic density phenotypes (dense and non-dense area). We created instrumental variables from large European ancestry-based genome-wide association studies and applied estimates to mammographic density phenotypes in up to 14,000 women of European ancestry. We performed analyses overall and by menopausal status. Results: Genetically predicted BMI was positively associated with non-dense area (IVW: β = 1.79; 95% CI = 1.58, 2.00; p = 9.57 × 10−63) and inversely associated with dense area (IVW: β = − 0.37; 95% CI = − 0.51,− 0.23; p = 4.7 × 10−7). We observed weak evidence for an association of circulating sex hormone concentrations with mammographic density phenotypes, specifically inverse associations between genetically predicted testosterone concentration and dense area (β = − 0.22; 95% CI = − 0.38, − 0.053; p = 0.009) and between genetically predicted estradiol concentration and non-dense area (β = − 3.32; 95% CI = − 5.83, − 0.82; p = 0.009), although results were not consistent across a range of MR approaches. Conclusion: Our findings support a positive causal association between BMI and mammographic non-dense area and an inverse association between BMI and dense area. Evidence was weaker and inconsistent for a causal effect of circulating sex hormone concentrations on mammographic density phenotypes. Based on our findings, associations between circulating sex hormone concentrations and mammographic density phenotypes are weak at best.
CRIS-Team Scopus Importer:2024-05-03
Keywords: BMI; Breast density; Causal inference; Mendelian randomization; Sex hormones

Disseminated tumour cells from the bone marrow of early breast cancer patients: Results from an international pooled analysis - Hartkopf, Andreas D.; Brucker, Sara Y.; Taran, Florin Andrei; Harbeck, Nadia; von Au, Alexandra; Naume, Bjørn; Pierga, Jean Yves; Hoffmann, Oliver; Beckmann, Matthias; Rydén, Lisa; Fehm, Tanja; Aft, Rebecca; et al. (European Journal of Cancer, 2021)
Purpose: Presence of disseminated tumour cells (DTCs) in the bone marrow (BM) has been described as a surrogate of residual disease in patients with early breast cancer (EBC). PADDY (Pooled Analysis of DTC Detection in Early Breast Cancer) is a large international analysis of pooled data that aimed to assess the prognostic impact of DTCs in patients with EBC. Experimental design: Individual patient data were collected from 11 centres. Patients with EBC and available follow-up data in whom BM sampling was performed at the time of primary diagnosis before receiving any anticancer treatment were eligible. DTCs were identified by antibody staining against epithelial cytokeratins. Multivariate Cox regression was used to compare the survival of DTC-positive versus DTC-negative patients. Results: In total, 10,307 patients were included. Of these, 2814 (27.3%) were DTC-positive. DTC detection was associated with higher tumour grade, larger tumour size, nodal positivity, oestrogen receptor and progesterone receptor negativity, and HER2 positivity (all p < 0.001). Multivariate analyses showed that DTC detection was an independent prognostic marker for overall survival, disease-free survival and distant disease-free survival with hazard ratios (HR) and 95% confidence intervals (CI) of 1.23 (95% CI: 1.06–1.43, p = 0.006), 1.30 (95% CI: 1.12–1.52, p < 0.001) and 1.30 (95% CI: 1.08–1.56, p = 0.006), respectively. There was no association between locoregional relapse-free survival and DTC detection (HR 1.21; 95% CI 0.68–2.16; p = 0.512). Conclusions: DTCs in the BM represent an independent prognostic marker in patients with EBC. The heterogeneous metastasis-initiating potential of DTCs is consistent with the concept of cancer dormancy.
CRIS-Team Scopus Importer:2021-07-23
Keywords: Bone marrow; Disseminated tumour cells; Early breast cancer; Micrometastases; Prognosis; Tumour staging

DNA methylation outliers in normal breast tissue identify field defects that are enriched in cancer - Teschendorff, Andrew E.; Gao, Yang; Jones, Allison; Rübner, Matthias; Beckmann, Matthias; Wachter, David; Fasching, Peter; Widschwendter, Martin (Nature Communications, 2016)
Identifying molecular alterations in normal tissue adjacent to cancer is important for understanding cancer aetiology and designing preventive measures. Here we analyse the DNA methylome of 569 breast tissue samples, including 50 from cancer-free women and 84 from matched normal cancer pairs. We use statistical algorithms for dissecting intra- and inter-sample cellular heterogeneity and demonstrate that normal tissue adjacent to breast cancer is characterized by tens to thousands of epigenetic alterations. We show that their genomic distribution is non-random, being strongly enriched for binding sites of transcription factors specifying chromatin architecture. We validate the field defects in an independent cohort and demonstrate that over 30% of the alterations exhibit increased enrichment within matched cancer samples. Breast cancers highly enriched for epigenetic field defects, exhibit adverse clinical outcome. Our data support a model where clonal epigenetic reprogramming towards reduced differentiation in normal tissue is an important step in breast carcinogenesis.
EVALuna2:6810

DNA methylation profiling identifies two distinct subgroups in breast cancers with low hormone receptor expression, mainly associated with HER2 amplification status - Jurmeister, Philipp; Weber, Karsten; Villegas, Sonia; Karn, Thomas; Untch, Michael; Thieme, Anne; Mueller, Volkmar; Taube, Eliane; Fasching, Peter; Schmitt, Wolfgang D.; Marme, Frederik; Stickeler, Elmar; et al. (Clinical Epigenetics, 2021)
Background: Current clinical guidelines suggest that breast cancers with low hormone receptor expression (LowHR) in 1–10% of tumor cells should be regarded as hormone receptor positive. However, clinical data show that these patients have worse outcome compared to patients with hormone receptor expression above 10%. We performed DNA methylation profiling on 23 LowHR breast cancer specimens, including 13 samples with HER2 amplification and compared our results with a reference breast cancer cohort from The Cancer Genome Atlas to clarify the status for this infrequent but important patient subgroup. Results: In unsupervised clustering and dimensionality reduction, breast cancers with low hormone receptor expression that lacked HER2 amplification usually clustered with triple negative breast cancer (TNBC) reference samples (8/10; “LowHR TNBC-like”). In contrast, most specimens with low hormone receptor expression and HER2 amplification grouped with hormone receptor positive cancers (11/13; “LowHR HRpos-like”). We observed highly similar DNA methylation patterns of LowHR TNBC-like samples and true TNBCs. Furthermore, the Ki67 proliferation index of LowHR TNBC-like samples and clinical outcome parameters were more similar to TNBCs and differed from LowHR HRpos-like cases. Conclusions: We here demonstrate that LowHR breast cancer comprises two epigenetically distinct groups. Our data strongly suggest that LowHR TNBC-like samples are molecularly, histologically and clinically closely related to TNBC, while LowHR HRpos-like specimens are closely related to hormone receptor positive tumors.
CRIS-Team Scopus Importer:2021-10-15

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause - Perry, John R. B.; Hsu, Yi-Hsiang; Chasman, Daniel I.; Johnson, Andrew D.; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L.; Beesley, Jonathan; Berenson, Gerald S.; Bergmann, Sven; Bojesen, Stig E.; Bolla, Manjeet K.; et al. (Human Molecular Genetics, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to 50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
EVALuna2:17512

Documentation Behavior in the CANKADO eHealth-Application and Effects on observed Side Effects - An exploratory Analysis of the PreCycle-Study - Schmidt, M.; Degenhardt, T.; Fasching, Peter; Wurstlein, R.; Lueftner, D.; Kates, R. E.; Schumacher, J.; Wenzel, C.; Schinkoethe, T.; Harbeck, N. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-07-31

Documentation Time and Effort and Associated Resources for Patients with Primary Breast Cancer from Diagnosis to End of Follow-Up - Results of a Multicentre Validation - Beckmann, Matthias; Sell, C.; Aydogdu, M.; Brucker, S. Y.; Fehm, T.; Janni, W.; Kreienberg, R.; Kuemmel, S.; Neumann, M.; Scharl, A.; Schleicher, B.; Wallwiener, D.; et al. (Gesundheitswesen, 2016)
INTRODUCTION: Tumour documentation is essential for quality assurance of oncological therapies and as a source of reliable information about the in- and outpatient care. The documentation effort and the associated resource consumption were analysed for the example of breast cancer. MATERIAL AND METHODS: The different steps in the care of patients with primary breast cancer in a standardised disease situation were defined from initial diagnosis to the end of the follow-up. After the pilot phase, a multicentre validation (n=7 centres) was performed with the support of the Federal Ministry of Health. The documentation time points were horizontally collected and analysed with regard to amount, duration and personnel expenses. RESULTS: 57% of the documentation costs are caused by the physicians. Regarding the different centres, documentation costs were calculated between € 352.82 and € 1 084.08 per patient from diagnosis to completion of aftercare. Non-certified centres had a reduced documentation effort and thus lower costs. CONCLUSIONS: The results demonstrate the need for a reduction of the documentation effort - particularly for physicians - the most expensive profession in the health system. A quality improvement is expected from the certification with its special requirements. In this context, there is a justified demand for an adequate remuneration of the documentation effort for certified centres. Furthermore, it is necessary to reduce the number of variables for quality assurance and to define them centrally. A comprehensive multi-disciplinary documentation should be achieved. Investments in a single data set and interface enhancements of existing documentation systems should be realised.
EVALuna2:33544

Does anxiety impact the neural processing of child faces in mothers of school-aged children? An ERP study using an emotional Go/NoGo task - Kungl, Melanie; Rutherford, Helena J.V.; Heinisch, Christine; Beckmann, Matthias; Fasching, Peter; Spangler, Gottfried (Social Neuroscience, 2020)
Maternal anxiety during pregnancy and the early postpartum period is associated with heightened neural processing of neutral infant faces as measured by event-related potentials (ERPs). However, less is known about how anxiety shapes neural face processing in mothers of older children. In our study, 36 mothers of 8–10 year old children completed a Go/NoGo task consisting of neutral and emotional (happy, fearful) facial expressions posed by unfamiliar school-aged children while EEG was recorded. Higher levels of maternal anxiety -indexed via self-report- were associated with delayed behavioral responses to children’s fearful faces and increased N170 and LPP amplitudes elicited by children’s neutral faces. While anxiety was also positively related to the LPP elicited by children’s emotional faces, it only led to increased N170 amplitude responses to children’s fearful, but not happy, faces and only when they were NoGo cues. The study replicates and extends prior findings examining the impact of maternal anxiety on neural responses to neutral infant faces to later stages of parenting with further neural markers and emotional expressions being affected. Findings evidence the importance of studying these associations beyond infancy to increase our knowledge about processes potentially underlying the relation between anxiety and less optimal parenting across development.
CRIS-Team Scopus Importer:2020-07-24
Keywords: EEG/ERP; emotional faces; Go/NoGo task; LPP; Maternal anxiety; N170

Does differential HLA-E and -F expression cause an aberrant immune tolerance in preeclampsia and HELLP? - Würfel, Franziska; Hübner, Hanna; Strick, Reiner; Fasching, Peter; Beckmann, Matthias; Wuerfel, Wolfgang; Rübner, Matthias (2016)
EVALuna2:32977

Does the Presence of Circulating Tumor Cells in High-Risk Early Breast Cancer Patients Predict the Site of First Metastasis-Results from the Adjuvant SUCCESS A Trial - Trapp, Elisabeth K.; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Mueller, Volkmar; Harbeck, Nadia; Lorenz, Ralf; Schumacher, Claudia; Heinrich, Georg; Schochter, Fabienne; De Gregorio, Amelie; Tzschaschel, Marie; et al. (Cancers, 2022)
Simple Summary Due to recent advances in breast cancer detection and treatment strategies, the number of breast cancer survivors has increased over the past decades. However, breast cancer follow-up guidelines have not changed for years. The presence of CTCs detected during follow-up has been shown to indicate poor prognosis in high-risk breast cancer patients. Here, we evaluated if the presence of CTCs also indicates the site of metastatic disease by analyzing CTC status and metastatic location in 206 patients with distant recurrence from the large adjuvant breast cancer trial SUCCESS A. Patients who were CTC-positive both before and after chemotherapy were more likely to show bone-only first distant disease (37.5% vs. 21.0%) and first distant disease at multiple sites (31.3% vs. 12.6%) than patients without CTCs. These data indicate that CTCs might serve as a liquid biopsy surveillance-marker enabling risk-stratification for deciding on further adjuvant add-on-treatment. The prognostic relevance of circulating tumor cells (CTCs) in breast cancer is well established. However, little is known about the association of CTCs and site of first metastasis. In the SUCCESS A trial, 373 out of 3754 randomized high-risk breast cancer patients developed metastatic disease. CTC status was assessed by the FDA-approved CellSearch(R)-System (Menarini Silicon Biosystems, Bologna, Italy) in 206 of these patients before chemotherapy and additionally in 159 patients after chemotherapy. CTCs were detected in 70 (34.0%) of 206 patients before (median 2 CTCs, 1-827) and in 44 (27.7%) of 159 patients after chemotherapy (median 1 CTC, 1-124); 16 (10.1%) of 159 patients were CTC-positive at both timepoints. The site of first distant disease was bone-only, visceral-only, and other-site-only in 44 (21.4%), 60 (29.1%), and 74 (35.9%) patients, respectively, while 28 (13.6%) patients had multiple sites of first metastatic disease. Patients with CTCs at both timepoints more often showed bone-only first distant disease (37.5% vs. 21.0%) and first distant disease at multiple sites (31.3% vs. 12.6%) than patients without CTCs before and/or after chemotherapy (p = 0.027). In conclusion, the presence of CTCs before and after chemotherapy is associated with multiple-site or bone-only first-distant disease and may trigger intensified follow-up and perhaps further treatment.
CRIS-Team WoS Importer:2022-09-09

Dose-Response Association of CD8+ Tumor-Infiltrating Lymphocytes and Survival Time in High-Grade Serous Ovarian Cancer - Goode, Ellen L.; Block, Matthew S.; Kalli, Kimberly R.; Vierkant, Robert A.; Chen, Wenqian; Fogarty, Zachary C.; Gentry-Maharaj, Aleksandra; Toloczko, Aleksandra; Hein, Alexander; Bouligny, Aliecia L.; Jensen, Allan; Osorio, Ana; et al. (JAMA Oncology, 2017)
Importance: Cytotoxic CD8+ tumor-infiltrating lymphocytes (TILs) participate in immune control of epithelial ovarian cancer; however, little is known about prognostic patterns of CD8+ TILs by histotype and in relation to other clinical factors. Objective: To define the prognostic role of CD8+ TILs in epithelial ovarian cancer. Design, Setting, and Participants: This was a multicenter observational, prospective survival cohort study of the Ovarian Tumor Tissue Analysis Consortium. More than 5500 patients, including 3196 with high-grade serous ovarian carcinomas (HGSOCs), were followed prospectively for over 24 650 person-years. Exposures: Following immunohistochemical analysis, CD8+ TILs were identified within the epithelial components of tumor islets. Patients were grouped based on the estimated number of CD8+ TILs per high-powered field: negative (none), low (1-2), moderate (3-19), and high (≥20). CD8+ TILs in a subset of patients were also assessed in a quantitative, uncategorized manner, and the functional form of associations with survival was assessed using penalized B-splines. Main Outcomes and Measures: Overall survival time. Results: The final sample included 5577 women; mean age at diagnosis was 58.4 years (median, 58.2 years). Among the 5 major invasive histotypes, HGSOCs showed the most infiltration. CD8+ TILs in HGSOCs were significantly associated with longer overall survival; median survival was 2.8 years for patients with no CD8+ TILs and 3.0 years, 3.8 years, and 5.1 years for patients with low, moderate, or high levels of CD8+ TILs, respectively (P value for trend = 4.2 × 10−16). A survival benefit was also observed among women with endometrioid and mucinous carcinomas, but not for those with the other histotypes. Among HGSOCs, CD8+ TILs were favorable regardless of extent of residual disease following cytoreduction, known standard treatment, and germline BRCA1 pathogenic mutation, but were not prognostic for BRCA2 mutation carriers. Evaluation of uncategorized CD8+ TIL counts showed a near-log-linear functional form. Conclusions and Relevance: This study demonstrates the histotype-specific nature of immune infiltration and provides definitive evidence for a dose-response relationship between CD8+ TILs and HGSOC survival. That the extent of infiltration is prognostic, not merely its presence or absence, suggests that understanding factors that drive infiltration will be the key to unraveling outcome heterogeneity in this cancer.
EVALuna2:34270

Economic and Humanistic Burden of Triple-Negative Breast Cancer: A Systematic Literature Review - Huang, Min; Haiderali, Amin; Fox, Grace E.; Frederickson, Andrew; Cortes, Javier; Fasching, Peter; O'Shaughnessy, Joyce (Pharmacoeconomics, 2022)
Background Triple-negative breast cancer (TNBC) accounts for 10-20% of all breast cancers (BCs). It is more commonly diagnosed in younger women and often has a less favorable prognosis compared with other BC subtypes. Objective The objective of this study was to provide a literature-based extensive overview of the economic and humanistic burden of TNBC to assist medical decisions for healthcare payers, providers, and patients. Methods A systematic literature review was performed using multiple databases, including EMBASE, MEDLINE, Econlit, the Cochrane Central Register of Controlled Trials, and the Cochrane Database of Systematic Reviews, from database inception to 16 May 2021. In addition, a targeted search was performed in the Northern Light Life Sciences Conference Abstracts database from 2016 through June 2021. The bibliographies of included articles were reviewed to identify other potentially relevant publications. Quality assessment of the included studies was conducted. Results The review identified 19 studies assessing the economic burden and 10 studies assessing the humanistic burden of TNBC. Studies varied widely in study design, settings, patient populations, and time horizons. The estimates of mean per-patient annual direct medical costs ranged from around 20,000 to over 100,000 in stage I-III TNBC and from 100,000 to 300,000 in stage IV TNBC. Healthcare costs and resource utilization increased significantly with disease recurrence, progression, and increased cancer stage or line of therapy. Compared with the costs of systemic anticancer therapy, cancer management costs comprised a larger portion of total direct costs. The estimates of indirect costs due to productivity loss ranged from 207 to 1573 per patient per month (all costs presented above were adjusted to 2021 US dollars). Cancer recurrence led to significantly reduced productivity and greater rates of leaving the workforce. A rapid deterioration of health utility associated with disease progression was observed in TNBC patients. Treatment with pembrolizumab or talazoparib showed significantly greater improvements in health-related quality of life (HRQoL) compared with chemotherapy, as measured by EORTC QLQ-C30, QLQ-BR23, and FACT-B. Conclusion TNBC is associated with a substantial economic burden on healthcare systems and societies and considerably reduced productivity and HRQoL for patients. This study synthesized the published literature on the economic and humanistic burden of TNBC and highlighted the need for continued research due to the rapidly changing landscape of TNBC care.
CRIS-Team WoS Importer:2022-02-11

Editorial: The potential for precision medicine to improve care and speed the development of new treatments in breast and gynecologic malignancies - Konecny, Gottfried E.; Fasching, Peter (Current Opinion in Obstetrics & Gynecology, 2019)
EVALuna2:212334

Effect of Denosumab Added to 2 Different nab-Paclitaxel Regimens as Neoadjuvant Therapy in Patients with Primary Breast Cancer: The GeparX 2 × 2 Randomized Clinical Trial - Blohmer, Jens-Uwe; Link, Theresa; Reinisch, Mattea; Just, Marianne; Untch, Michael; Stotzer, Oliver; Fasching, Peter; Schneeweiss, Andreas; Wimberger, Pauline; Seiler, Sabine; Huober, Jens; Thill, Marc; et al. (JAMA Oncology, 2022)
Importance: Adjuvant denosumab might improve disease-free survival in hormone receptor (HR)-positive primary breast cancer (BC). The optimal neoadjuvant nab-paclitaxel schedule in terms of efficacy and safety is unclear. Objective: To determine whether adding denosumab to anthracycline/taxane-containing neoadjuvant chemotherapy (NACT) increases the pathological complete response (pCR) rate and which nab-paclitaxel schedule is more effective in the NACT setting. Design, Setting, and Participants: The GeparX was a multicenter, prospective, open-label, phase 2b, 2 × 2 randomized clinical trial conducted by GBG and AGO-B at 38 German sites between February 2017 and March 2019. The analysis data set was locked September 4, 2020; analysis was completed November 13, 2020. Patients had unilateral or bilateral primary BC, stage cT2-cT4a-d or cT1c, with either clinically node-positive or pathologically node-positive or HR-negative disease, or Ki-67 proliferation index greater than 20%, or ERBB2 (formerly HER2)-positive BC. Interventions: Patients were randomized to receive or not receive denosumab, 120 mg subcutaneously every 4 weeks for 6 cycles, and either nab-paclitaxel, 125 mg/m2weekly for 12 weeks or days 1 and 8 every 3 weeks for 4 cycles (8 doses), followed by 4 cycles of epirubicin/cyclophosphamide, 90/600 mg/m2(every 2 weeks or every 3 weeks). Carboplatin was given in triple-negative BC (TNBC), and trastuzumab biosimilar ABP980 plus pertuzumab was given in ERBB2-positive BC (ERBB2-positive substudy). Main Outcomes and Measures: The primary outcome was pCR rates between arms for each randomization. Results: A total of 780 female (n = 779) and male (n = 1) patients (median [range] age, 49.0 [22-80] years) were randomized to the 4 treatment groups. The pCR (ypT0 ypN0) rate was 41.0% (90% CI, 37%-45%) with denosumab vs 42.8% (90% CI, 39%-47%) (P =.58) without denosumab, irrespective of BC subtype. Nab-paclitaxel weekly resulted in a significantly (significance level of α =.10) higher pCR rate of 44.9% (90% CI, 41%-49%) vs 39.0% (90% CI, 35%-43%) (P =.06) with nab-paclitaxel days 1 and 8 every 3 weeks. The pCR rates for nab-paclitaxel schedules in subgroups were only significantly different for TNBC (60.4% vs 50.0%; P =.06). Grade 3 to 4 toxic effects did not differ with or without denosumab. Nonhematologic toxic effects of grade 3 to 4 were higher with nab-paclitaxel weekly (33.7% vs 24.1%; P =.004). Conclusions and Relevance: In this randomized clinical trial, denosumab added to anthracycline/taxane-based NACT did not improve pCR rates. Nab-paclitaxel at a dosage of 125 mg/m2weekly significantly increased the pCR rate compared with the days 1 and 8, every-3-weeks schedule overall and in TNBC, but generated higher toxicity. Trial Registration: ClinicalTrials.gov Identifier: NCT02682693.
CRIS-Team Scopus Importer:2022-06-03

Effects of an App-Based Mindfulness Intervention during Pregnancy on the Infant’s Prenatal Androgen Exposure: A Randomized Controlled Pilot Trial - Siegmann, Eva-Maria; Eichler, Anna; Buchholz, Verena Nadine; Gerlach, Jennifer; Pontones, Constanza; Titzmann, Adriana; Arnaud, Nicolas; Consortium, Imac Mind; Mühle, Christiane; Beckmann, Matthias; Fasching, Peter; Kratz, Oliver; et al. (Journal of Clinical Medicine, 2023)
Prenatal androgen exposure modulates the development of the brain, with lasting effects on its function and behavior over the infant’s life span. Environmental factors during pregnancy, in particular maternal stress, have been shown to influence the androgen load of the unborn child. We here addressed the research gap on whether a mindfulness intervention or a pregnancy education administered to pregnant women more affects the androgen exposure of the unborn child (quantified by the proxies of second-to-fourth digit length ratio (2D:4D) and anogenital distance assessed one year after delivery and at delivery, respectively). Moreover, we tested the mindfulness intervention’s effects on maternal perceived stress, anxiety, depressiveness, and mindfulness. Pregnant women (gestation weeks 8–14) were randomized to a 15-week app-based mindfulness-oriented intervention (N = 72) or a pregnancy education intervention (control condition; N = 74). The mindfulness-oriented group did not significantly differ from the pregnancy education group in infants’ 2D:4D or anogenital distance (partial η2 ≤ 0.01) or in maternal stress, anxiety, depressiveness, or mindfulness. However, the descriptive results indicate that across pregnancy, stress and anxiety decreased and mindfulness increased in both groups. Overall, this study did not show that the mindfulness intervention (relative to the pregnancy education) reduced the prenatal androgen exposure of the unborn children or improved the maternal outcomes significantly.
CRIS-Team Scopus Importer:2023-10-20
Keywords: digit ratio; mindfulness; prenatal programming

Effects of prenatal alcohol consumption on cognitive development and ADHD-related behaviour in primary-school age: a multilevel study based on meconium ethyl glucuronide - Eichler, Anna; Hudler, Linda; Grunitz, Juliane; Grimm, Jennifer; Raabe, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Heinrich, Hartmut (The journal of child psychology and psychiatry, 2018)
BACKGROUND: Alcohol intake during pregnancy is considered to be a risk factor for child development. Child biomarkers of intrauterine alcohol exposure have been rarely studied. We investigated whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with cognitive development, ADHD-related behaviour and neurophysiological markers of attention and executive control of children at primary-school age. METHODS: Mothers provided self-report on prenatal alcohol consumption during their 3rd trimester. Meconium samples were collected at birth. A total of 44 children with a meconium EtG above the detection limit (≥10 ng/g) and 44 nonexposed matched controls were compared. A second threshold (≥154 ng/g) was applied to study the dose effects. When children reached primary-school age, mothers rated ADHD-related behaviour, child cognitive development was measured using an IQ test battery, and event-related potentials were recorded during a cued go/nogo task. RESULTS: Children in both EtG-positive groups allocated fewer attentional resources than controls to the go/nogo task (reduced P3 component in go-trials). Children with a meconium EtG above 154 ng/g were also found to have an IQ that was six points lower than the other groups. Within the EtG ≥ 154 ng/g group, there was a positive correlation between EtG value and ADHD-related behaviour. These significant effects were not observed in relation to the maternal self-report data. CONCLUSIONS: Associations between EtG and cognitive deficits, attentional resource capacity and ADHD-related behaviour could be documented with effects that were partially dose-dependent. In addition to maternal self-reports, this biomarker of intrauterine alcohol exposure may be considered as a predictor of child development.
EVALuna2:33526

Efficacy and safety of everolimus plus exemestane in patients with hormone receptor-positive, HER-2-negative advanced breast cancer: Results from the open-label, multicentre, non-interventional BRAWO study - Lüftner, Diana; Schuetz, Florian; Schneeweiss, Andreas; Hartkopf, Andreas; Bloch, Wilhelm; Decker, Thomas; Uleer, Christoph; Stötzer, Oliver; Foerster, Frank; Schmidt, Marcus; Mundhenke, Christoph; Tesch, Hans; et al. (International Journal of Cancer, 2024)
BRAWO, a real-world study, assessed the efficacy, quality of life (QoL) and safety of EVE + EXE in postmenopausal women with HR+/HER2– advanced breast cancer (ABC) in routine clinical practice. Postmenopausal women with HR+/HER2-ABC with recurrence or progression after a NSAI were included. Primary Observation parameters included the evaluation of the effectiveness of EVE + EXE. A multivariate-analysis using Cox proportional hazard model was built to identify predictors of progression. Overall, 2100 patients were enrolled (August 2012–December 2017); 2074 were evaluable for efficacy and safety analyses. Majority of patients (60.6%) received EVE + EXE as first (28.7%) or second-line (31.9%) therapy. Visceral metastases were present in 54.1% patients. Median progression-free survival (mPFS) reported as 6.6 months (95%CI: 6.3–7.0). Multivariate-analysis in a subset of patients (n = 1837) found higher body mass index (BMI) and non-visceral metastases to be independent predictors of favorable PFS. Patients with a BMI of 20 to <25 had a mPFS of 6.0 (95%CI: 5.4–6.4) and those with a BMI ≥30 had mPFS of 8.5 (95%CI: 6.9–9.9). 41.2% patients achieved stable disease and 7.3% partial response. No major changes were observed QoL; 86.4% patients received stomatitis prophylaxis and 41.4% experienced EVE related AEs of stomatitis, mainly low grade. AEs occurred in 91.2% of patients, of which stomatitis (42.6%) and fatigue (19.8%) were most frequent. The BRAWO study provides real-world evidence of efficacy and safety of EVE + EXE in patients with HR+, HER2− ABC. A high BMI and the absence of visceral metastases were independent predictors of PFS in this cohort of patients.
CRIS-Team Scopus Importer:2024-05-10
Keywords: advanced breast cancer; everolimus; exemestane; HER2–; HR+

Efficacy and safety of everolimus plus exemestane in postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative locally advanced or metastatic breast cancer: Results of the single-arm, phase IIIB 4EVER trial - Tesch, Hans; Stoetzer, Oliver; Decker, Thomas; Kurbacher, Christian M.; Marme, Frederik; Schneeweiss, Andreas; Mundhenke, Christoph; Distelrath, Andrea; Fasching, Peter; Lux, Michael P.; Lueftner, Diana; Hadji, Peyman; et al. (International Journal of Cancer, 2019)
In BOLERO-2, adding everolimus to exemestane resulted in a twofold increase in median progression-free survival (PFS) vs exemestane in postmenopausal women with hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) advanced breast cancer (aBC) after progression on a non-steroidal aromatase inhibitor (NSAI). Here, we report on the open-label, single-arm, phase IIIB 4EVER trial (NCT01626222). This trial evaluated the clinical effectiveness of everolimus plus exemestane in postmenopausal women with HR+, HER2− aBC who had progressed on or after an NSAI, but with no restrictions on the time of progression after NSAI, prior chemotherapy for advanced disease or previous exemestane. The primary endpoint was overall response rate (ORR; i.e. the percentage of patients with a best overall response of complete or partial response per RECIST 1.1) within the first 24 weeks of treatment. Secondary endpoints included PFS, overall survival, safety and health-related quality of life. Between June 2012 and November 2013, 299 patients were enrolled at 82 German centers: 281 patients were evaluable for efficacy and 299 for safety. The ORR was 8.9% (95% confidence interval [CI]: 5.8–12.9%). Median PFS was 5.6 months (95% CI: 5.4–6.0 months). The most frequent grade 3/4 adverse events were stomatitis (8.4%), general physical health deterioration (6.7%), dyspnea (4.7%) and anemia (4.3%). The ORR in 4EVER was lower than in BOLERO-2, likely due to inclusion of patients with more advanced disease and extensive pretreatment. These data confirm the clinical benefits and known safety profile of everolimus plus exemestane in postmenopausal women with HR+, HER2− aBC.
CRIS-Team Scopus Importer:2019-06-18
Keywords: advanced breast cancer; estrogen receptor-positive; everolimus; exemestane; HER2-negative

Efficacy and safety of ribociclib (RIB) in combination with letrozole (LET) in patients with estrogen receptorepositive advanced breast cancer (ABC): Secondary and exploratory results of phase 3b RIBECCA study - Decker, T.; Fasching, Peter; Nusch, A.; Hartkopf, A.; Heinrich, B. J.; Kurbacher, C. M.; Fuchs, R.; Tesch, H.; Krabisch, P.; Huober, J.; Kuemmel, S.; Brucker, S. Y.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Efficacy of Lapatinib in Patients with HER2-Negative Metastatic Breast Cancer and HER2-Positive Circulating Tumor Cells - The DETECT III Clinical Trial - Fehm, Tanja; Mueller, Volkmar; Banys-Paluchowski, Maggie; Fasching, Peter; Friedl, Thomas W.P.; Hartkopf, Andreas; Huober, Jens; Löhberg, Christian; Rack, Brigitte; Riethdorf, Sabine; Schneeweiss, Andreas; Wallwiener, Diethelm; et al. (Clinical Chemistry, 2024)
Background: The phenotypes of tumor cells change during disease progression, but invasive rebiopsies of metastatic lesions are not always feasible. Here we aimed to determine whether initially HER2-negative metastatic breast cancer (MBC) patients with HER2-positive circulating tumor cells (CTCs) benefit from a HER2-targeted therapy. Methods: The open-label, interventional randomized phase III clinical trial (EudraCT Number 2010-024238-46, CliniclTrials.gov Identifier: NCT01619111) recruited from March 2012 until September 2019 with a follow-up duration of 19.5 months. It was a multicenter clinical trial with 94 participating German study centers. A total of 2137 patients with HER2-negative MBC were screened for HER2-positive CTCs with a final modified intention-to-treat population of 101 patients. Eligible patients were randomized to standard therapy with or without lapatinib. Primary study endpoints included CTC clearance (no CTCs at the end of treatment) and secondary endpoints were progression-free survival, overall survival (OS), and safety. Results: In both treatment arms CTC clearance at first follow-up visit - although not being significantly different for both arms at any time point - was significantly associated with improved OS (42.4 vs 14.1 months; P = 0.002). Patients treated additionally with lapatinib had a significantly improved OS over patients receiving standard treatment (20.5 vs 9.1 months, P = 0.009). Conclusions: DETECT III is the first clinical study indicating that phenotyping of CTCs might have clinical utility for stratification of MBC cancer patients to HER2-targeting therapies. The OS benefit could be related to lapatinib, but further studies are required to prove this clinical observation. ClinicalTrials.gov Registration Number: NCT01619111.
CRIS-Team Scopus Importer:2024-01-19

Efficacy of Margetuximab vs Trastuzumab in Patients With Pretreated ERBB2-Positive Advanced Breast Cancer A Phase 3 Randomized Clinical Trial - Rugo, Hope S.; Im, Seock-Ah; Cardoso, Fatima; Cortes, Javier; Curigliano, Giuseppe; Musolino, Antonino; Pegram, Mark D.; Wright, Gail S.; Saura, Cristina; Escriva-De-Romani, Santiago; De Laurentiis, Michelino; Levy, Christelle; et al. (JAMA Oncology, 2021)
IMPORTANCE ERRB2 (formerly HER2)-positive advanced breast cancer (ABC) remains typically incurable with optimal treatment undefined in later lines of therapy. The chimeric antibody margetuximab shares ERBB2 specificity with trastuzumab but incorporates an engineered Fc region to increase immune activation.
CRIS-Team WoS Importer:2021-01-29

Efficacy of neoadjuvant pertuzumab in addition to chemotherapy and trastuzumab in routine clinical treatment of patients with primary breast cancer: a multicentric analysis - Fasching, Peter; Hartkopf, Andreas D.; Gaß, Paul; Häberle, Lothar; Akpolat-Basci, Leyla; Hein, Alexander; Volz, Bernhard; Taran, Florin-Andrei; Nabieva, Naiba; Pott, Birgit; Overkamp, Friedrich; Einarson, Hanna; et al. (Breast Cancer Research and Treatment, 2019)
PurposeNeoadjuvant combination treatment with chemotherapy (CTX), trastuzumab (TZM), and pertuzumab (PTZ) has been shown to result in higher pathological complete response rates (pCR) in comparison with treatment with chemotherapy and trastuzumab (CTX/TZM). This analysis was aimed at real-world validation of these results from prospective randomized trials.MethodsIn a retrospective analysis conducted in the PRAEGNANT network, patients were eligible for inclusion if they had either received neoadjuvant therapy with CTX/TZM or chemotherapy, trastuzumab, and pertuzumab (CTX/TZM/PTZ) and subsequently underwent surgery for their primary breast cancer. The effect of the two neoadjuvant regimens on pCR in addition to commonly applicable predictors of pCR was analyzed in 300 patients from three study sites, using logistic regression analyses with treatment arm, age, clinical tumor stage, grading, and hormone receptor status as predictors.ResultspCR with complete disappearance of all tumor cells was seen in 30.2% (n=58) of patients treated with CTX/TZM and in 52.8% (n=57) of those treated with CTX/TZM/PTZ. CTX/TZM/PTZ was positively associated with pCR (adjusted odds ratio 2.44; 95% CI 1.49-4.02). Mastectomy rates were not influenced by the therapy.ConclusionsThe results of clinical trials were confirmed in this dataset of patients who were treated outside of clinical trials in everyday routine work. pCR rates can be improved by 20% with pertuzumab in routine clinical use.
CRIS-Team WoS Importer:2019-03-15

Efficacy of the tyrosine kinase inhibitor lapatinib in the treatment of patients with HER2-negative metastatic breast cancer and HER2-positive circulating tumor cells - results from the randomized phase III DETECT III trial - Fehm, Tanja; Mueller, Volkmar; Banys-Paluchowski, Maggie; Fasching, Peter; Friedl, Thomas W. P.; Hartkopf, Andreas; Huober, Jens; Loehberg, Christian; Rack, Brigitte; Riethdorf, Sabine; Schneeweiss, Andreas; Wallwiener, Diethelm; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Efficacy, safety, and prognosis prediction in patients treated with ribociclib in combination with letrozole: Final results of phase 3b RIBECCA study in hormone receptor positive, human epidermal growth factor receptor-2 negative, locally advanced or metastatic breast cancer - Fasching, Peter; Decker, Thomas; Hartkopf, Andreas; Nusch, Arnd; Heinrich, Bernhard J.; Kurbacher, Christian; Fuchs, Roswitha; Tesch, Hans; Krabisch, Petra; Huober, Jens; Kuemmel, Sherko; Brucker, Sara; et al. (European Journal of Cancer, 2024)
Background: In MONALEESA-2, addition of ribociclib to letrozole resulted in significantly longer progression-free survival (PFS) in postmenopausal women with HR+HER2− advanced breast cancer (ABC). RIBociclib for the treatment of advanCed breast CAncer (RIBECCA) study investigated ribociclib plus letrozole in a patient population reflecting routine clinical practice. Patients and methods: In this multicenter, open-label, single-arm, phase 3b study, patients with HR+HER2− ABC not amenable to curative therapy and ECOG performance status ≤ 2 received ribociclib plus letrozole (cohort A: postmenopausal women and men in first-line; cohort B: pre-/perimenopausal women in first-line [B1], patients pretreated for advanced disease [B2]). The primary endpoint was clinical benefit rate (CBR) by week 24; secondary endpoints included overall response rate (ORR), PFS, overall survival (OS), and safety. Association of patient and tumor characteristics with PFS was analyzed by multivariable Cox regression analysis. Results: Overall, 487 patients were evaluable for efficacy, 502 for safety. By week 24, CBR was 60.8 % (95 % CI, 56.3–65.1), ORR was 19.3 % (95 % CI, 15.9–23.1). Median PFS was 21.8 months (95 % CI, 13.9–25.3) in first-line postmenopausal patients and 11.0 months (95 % CI, 8.2–16.4) in premenopausal and pretreated patients. Median OS was not reached. Higher baseline ECOG performance status, higher histological grade, and negative progesterone receptor status showed an unfavorable effect on PFS. Most common adverse events were neutropenia (50.0 %), nausea (42.0 %), and fatigue (39.2 %). Conclusion: In this broad population of patients with HR+HER2− ABC, efficacy and safety results of ribociclib plus letrozole were similar to those observed in pivotal trials.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Advanced breast cancer; CDK4/6 inhibitor; Letrozole; RIBECCA; Ribociclib

Electronic-Based Patient-Reported Outcomes: Willingness, Needs, and Barriers in Adjuvant and Metastatic Breast Cancer Patients - Hartkopf, Andreas D.; Graf, Joachim; Simoes, Elisabeth; Keilmann, Lucia; Sickenberger, Nina; Gaß, Paul; Wallwiener, Diethelm; Matthies, Lina; Taran, Florin-Andrei; Lux, Michael P.; Wallwiener, Stephanie; Belleville, Eric; et al. (JMIR Cancer, 2017)
BACKGROUND: Patient-reported outcomes (PROs) play an increasingly important role as an adjunct to clinical outcome parameters in measuring health-related quality of life (HRQoL). In fact, PROs are already the accepted gold standard for collecting data about patients' subjective perception of their own state of health. Currently, paper-based surveys of PRO still predominate; however, knowledge regarding the feasibility of and barriers to electronic-based PRO (ePRO) acceptance remains limited. OBJECTIVE: The objective of this trial was to analyze the willingness, specific needs, and barriers of adjuvant breast cancer (aBC) and metastatic breast cancer (mBC) patients in nonexposed (no exposure to electronic assessment) and exposed (after exposure to electronic assessment decision, whether a tablet-based questionnaire is favored) settings before implementing digital ePRO assessment in relation to health status. We also investigated whether providing support can increase the patients' willingness to participate in such programs. METHODS: The nonexposed patients only answered a paper-based questionnaire, whereas the exposed patients filled out both paper- and tablet-based questionnaires. The assessment comprised socioeconomic variables, HRQoL, preexisting technical skills, general attitude toward electronic-based surveys, and potential barriers in relation to health status. Furthermore, nonexposed patients were asked about the existing need for technological support structures. In the course of data evaluation, we performed a frequency analysis as well as chi-square tests and Wilcoxon signed-rank tests. Subsequently, relative risks analysis, univariate categorical regression (CATREG), and mediation analyses (Hayes' bias-corrected bootstrap) were performed. RESULTS: A total of 202 female breast cancer patients completed the PRO assessment (nonexposed group: n=96 patients; exposed group: n=106 patients). Self-reported technical skills were higher in exposed patients (2.79 vs 2.33, P ≤.001). Significant differences were found in relation to willingness to use ePRO (92.3% in the exposed group vs 59% in the nonexposed group; P=.001). Multiple barriers were identified, and most of them showed statistically significant differences in favor of the exposed patients (ie, data security [13% in the exposed patients vs 30% in the nonexposed patients; P=.003] and no prior technology usage [5% in the exposed group vs 15% in the nonexposed group; P=.02]), whereas the differences in disease burden (somatic dimension: 4% in the exposed group vs 9% in the nonexposed group; P=.13) showed no significance. In nonexposed patients, requests for support services were identified, which could increase their ePRO willingness. CONCLUSIONS: Significant barriers in relation to HRQoL, cancer-related restrictions, and especially the setting of the survey were identified in this trial. Thus, it is necessary to address and eliminate these barriers to ensure data accuracy and reliability for future ePRO assessments. Exposure seems to be a potential option to increase willingness to use ePRO and to reduce barriers.
EVALuna2:36440

Elevated serum RAS p21 is an independent prognostic factor in metastatic breast cancer - Banys-Paluchowski, Malgorzata; Fehm, Tanja; Janni, Wolfgang; Aktas, Bahriye; Fasching, Peter; Kasimir-Bauer, Sabine; Milde-Langosch, Karin; Pantel, Klaus; Rack, Brigitte; Riethdorf, Sabine; Solomayer, Erich-Franz; Witzel, Isabell; et al. (BMC Cancer, 2018)
An important component of the RAS signalling pathway, the RAS p21 oncogene, is frequently hyperactivated in breast cancer. Its expression in tumor tissue has been linked to poor clinical outcome. This study was designed to evaluate the clinical relevance of RAS p21 levels in peripheral blood in a large cohort of metastatic breast cancer patients.Two hundred fifty-one patients with metastatic breast cancer were enrolled in this prospective, multicentre, open-label, non-randomized study. Blood samples were collected before start of first-line or later-line treatment. RAS p21 was determined using a sandwich-type ELISA immunoassay. For the determination of the cutoff, blood samples from age-matched healthy controls were analyzed. A value above 452 pg/ml was regarded as elevated (mean + 2 x SD). In the univariate survival analysis, two other cutoffs were considered as well (50th and 75th percentile of patients, i.e. 229 pg/ml and 320 pg/ml). Circulating tumor cells (CTCs) were detected using the CellSearch system.29 of 251 (12%) patients had RAS p21 levels above the cut-off level of 452 pg/ml. Clinical-pathological parameters, such as hormone receptor and HER2 status, line of therapy and CTC status, did not correlate with RAS p21 levels. Elevated RAS p21 was significantly associated with shorter progression-free and overall survival in the univariate analysis (median PFS: 3.9 months [95%-CI: 1.8-6.0] for patients with elevated RAS p21 levels versus 8.5 months [95%-CI: 7.4-9.5] with non-elevated levels [p = 0.01]; median OS: 7.1 months [95%-CI: 0.3-14.2] versus not reached [p = 0.002], respectively). When RAS p21 cutoffs other than 452 pg/ml were considered, elevated RAS p21 was significantly associated with OS but not with PFS. Classical clinical-pathological factors were included into a multivariate Cox regression analysis. In addition, factors previously shown to influence survival in a univariate analysis, such as serum HER2, CAIX and TIMP1, were included as well. In the multivariate analysis, RAS p21, presence of >=5 CTCs per 7.5 ml blood, higher grading and higher line of therapy remained independent predictors of shorter OS.Metastatic breast cancer patients with elevated levels of circulating RAS p21 have significantly worse clinical outcome. Hypothetically, these patients might benefit from therapeutic strategies targeting RAS pathway.Current Controlled Trials ISRCTN59722891 (DETECT); trial registration date: April, 17th 2010; the trial was registered retrospectively.
EVALuna2:56163

Endocrine treatment for breast cancer patients revisited—history, standard of care, and possibilities of improvement - Nabieva, Naiba; Fasching, Peter (Cancers, 2021)
Purpose of review: Due to the findings of current studies and the approval of novel substances for the therapy of hormone-receptor-positive breast cancer patients, the established standards of endocrine treatment are changing. The purpose of this review is to give an overview of the history of endocrine treatment, to clarify its role in the present standard of care, and to discuss the possibilities of improvement. Recent findings: Tamoxifen, aromatase inhibitors, and fulvestrant are the main drugs that have been used for decades in the therapy of hormone-receptor-positive breast cancer patients. However, since a relevant number of women suffer at some point from disease recurrence or progression, several novel substances are being investigated to overcome resistance mechanisms by interfering with certain signaling pathways, such as the PI3K/AKT/mTOR or the CDK4/6 pathways. mTOR and CDK4/6 inhibitors were the first drugs approved for this purpose and many more are in development. Summary: Endocrine treatment is one of the best tolerable cancer therapies available. Continuous investigation serves to improve patients’ outcomes and modernize the current standard of care. Considering the resistance mechanisms and substances analyzed against these, endocrine treatment of hormone-receptor-positive breast cancer is on the brink of a new era.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Abemaciclib; Alpelisib; Aromatase inhibitor; Breast cancer; CDK 4/6 in-hibitor; Compliance; Endocrine treatment; Fulvestrant; MTOR inhibitor; Palbociclib; PI3K inhibitor; Ribociclib; SERD; Tamoxifen

Endocrine Treatment with 2 Years of Tamoxifen versus 2 Years of Exemestane in Postmenopausal Patients with High-Risk Early Breast Cancer and Persisting Circulating Tumor Cells - First Results of the SUCCESS C Endocrine Treatment Sub-Study - Schochter, Fabienne; Rack, Brigitte; Tzschaschel, Marie; Polasik, Arkadius; Andergassen, Ulrich; Trapp, Elisabeth; Alunni-Fabbroni, Marianna; Schneeweiss, Andreas; Muller, Volkmar; Pantel, Klaus; Gade, Joerg; Lorenz, Ralf; et al. (Oncology Research and Treatment, 2018)
Optimal choice and sequence of endocrine treatment following adjuvant chemotherapy in postmenopausal early breast cancer patients are still under discussion and treatment stratification factors are missing.Postmenopausal women with HER2-negative, hormone receptor-positive tumors and persisting circulating tumor cells (CTCs; assessed using the FDA-approved CellSearch® System, Janssen Diagnostics, LLC) after chemotherapy were randomized to 2 years of tamoxifen followed by 3 years of exemestane (tamoxifen-exemestane group, n = 54) or 5 years of exemestane (exemestane-only group, n = 54). CTCs were again assessed after the first 2 years of endocrine treatment. In addition, safety data were compared between the 2 groups.The 2 groups were well-balanced with regard to baseline characteristics. The CTC clearance rate after 2 years was 89% in the exemestane-only group and 97% in the tamoxifen-exemestane group (exact Fisher test, p = 0.36). The safety profile showed good tolerability with few grade 3 or 4 adverse events in both groups.The similar CTC clearance rate after 2 years of endocrine therapy with exemestane or tamoxifen, and the safety profiles obtained may indicate comparable efficacy and tolerability of both endocrine treatment regimens. However, these results have to be confirmed by final survival and safety analysis.
EVALuna2:56172

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Enrichment of putative PAX8 target genes at serous epithelial ovarian cancer susceptibility loci - Kar, Siddhartha P.; Adler, Emily; Tyrer, Jonathan; Hazelett, Dennis; Anton-Culver, Hoda; Bandera, Elisa V.; Beckmann, Matthias; Berchuck, Andrew; Bogdanova, Natalia; Brinton, Louise; Butzow, Ralf; Campbell, Ian; et al. (British Journal of Cancer, 2017)
BACKGROUND: Genome-wide association studies (GWAS) have identified 18 loci associated with serous ovarian cancer (SOC) susceptibility but the biological mechanisms driving these findings remain poorly characterised. Germline cancer risk loci may be enriched for target genes of transcription factors (TFs) critical to somatic tumorigenesis. METHODS: All 615 TF-target sets from the Molecular Signatures Database were evaluated using gene set enrichment analysis (GSEA) and three GWAS for SOC risk: discovery (2196 cases/4396 controls), replication (7035 cases/21 693 controls; independent from discovery), and combined (9627 cases/30 845 controls; including additional individuals). RESULTS: The PAX8-target gene set was ranked 1/615 in the discovery (PGSEA<0.001; FDR=0.21), 7/615 in the replication (PGSEA=0.004; FDR=0.37), and 1/615 in the combined (PGSEA<0.001; FDR=0.21) studies. Adding other genes reported to interact with PAX8 in the literature to the PAX8-target set and applying an alternative to GSEA, interval enrichment, further confirmed this association (P=0.006). Fifteen of the 157 genes from this expanded PAX8 pathway were near eight loci associated with SOC risk at P<10-5 (including six with P<5 × 10-8). The pathway was also associated with differential gene expression after shRNA-mediated silencing of PAX8 in HeyA8 (PGSEA=0.025) and IGROV1 (PGSEA=0.004) SOC cells and several PAX8 targets near SOC risk loci demonstrated in vitro transcriptomic perturbation. CONCLUSIONS: Putative PAX8 target genes are enriched for common SOC risk variants. This finding from our agnostic evaluation is of particular interest given that PAX8 is well-established as a specific marker for the cell of origin of SOC.
EVALuna2:36153

Epigenetic regulation of the putative breast cancer metastasis suppressor gene SCN4B - Hilgers, L.; Hartmann, Arndt; Fasching, Peter; Villwock, S.; Moll, L.; Roger, S.; Knuechel-Clarke, R.; Steib, F.; Dahl, E. D. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

EPIK-B3: A phase III, randomised, double-blind (DB), placebo (PBO)-controlled study of alpelisib (ALP) plus nab-paclitaxel (nabPTX) in advanced triple-negative breast cancer (TNBC) with either PIK3CA mutation or phosphatase and tensin homolog (PTEN) loss without PIK3CA mutation - Sharma, P.; Farooki, A.; Fasching, Peter; Loi, S.; Peterson, K.; Prat, A.; Tripathy, D.; Xu, B.; Yardley, D. A.; Mills, D.; Klauss, G.; Wong, C.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Epithelial-Mesenchymal Transition (EMT) Gene Variants and Epithelial Ovarian Cancer (EOC) Risk - Amankwah, Ernest K.; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Chornokur, Ganna; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bruinsma, Fiona; Bandera, Elisa V.; Bean, Yukie T.; et al. (Genetic Epidemiology, 2015)
Epithelial-mesenchymal transition (EMT) is a process whereby epithelial cells assume mesenchymal characteristics to facilitate cancer metastasis. However, EMT also contributes to the initiation and development of primary tumors. Prior studies that explored the hypothesis that EMT gene variants contribute to epithelial ovarian carcinoma (EOC) risk have been based on small sample sizes and none have sought replication in an independent population. We screened 15,816 single-nucleotide polymorphisms (SNPs) in 296 genes in a discovery phase using data from a genome-wide association study of EOC among women of European ancestry (1,947 cases and 2,009 controls) and identified 793 variants in 278 EMT-related genes that were nominally (P < 0.05) associated with invasive EOC. These SNPs were then genotyped in a larger study of 14,525 invasive-cancer patients and 23,447 controls. A P-value <0.05 and a false discovery rate (FDR) <0.2 were considered statistically significant. In the larger dataset, GPC6/GPC5 rs17702471 was associated with the endometrioid subtype among Caucasians (odds ratio (OR) = 1.16, 95% CI = 1.07-1.25, P = 0.0003, FDR = 0.19), whereas F8 rs7053448 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), F8 rs7058826 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), and CAPN13 rs1983383 (OR = 0.79, 95% CI = 0.69-0.90, P = 0.0005, FDR = 0.12) were associated with combined invasive EOC among Asians. In silico functional analyses revealed that GPC6/GPC5 rs17702471 coincided with DNA regulatory elements. These results suggest that EMT gene variants do not appear to play a significant role in the susceptibility to EOC.
EVALuna2:9299

Erratum: AGO Recommendations for the Surgical Therapy of the Axilla after Neoadjuvant Chemotherapy: 2021 Update (Geburtshilfe Frauenheilkd (2021) 81:10 (1112-1120) DOI: 10.1055/a-1499-8431) - Friedrich, Michael; Kühn, Thorsten; Janni, Wolfgang; Müller, Volkmar; Banys-Paluchowski, Maggie; Kolberg-Liedtke, Cornelia; Jackisch, Christian; Krug, David; Albert, Ute Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; et al. (Geburtshilfe und Frauenheilkunde, 2021)
In the above article, the name of the co-author was given incorrectly. Correct is: Maggie Banys-Paluchowski
CRIS-Team Scopus Importer:2021-11-19

Erratum: Publisher Correction: Shared heritability and functional enrichment across six solid cancers (Nature communications (2019) 10 1 (431)) - Jiang, Xia; Finucane, Hilary K.; Schumacher, Fredrick R.; Schmit, Stephanie L.; Tyrer, Jonathan P.; Han, Younghun; Michailidou, Kyriaki; Lesseur, Corina; Kuchenbaecker, Karoline B.; Dennis, Joe; Conti, David V.; Casey, Graham; et al. (Nature Communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2019-10-01

Erratum: SNiPER: A novel hypermethylation biomarker panel for liquid biopsy based early breast cancer detection (Oncotarget. (2019) 10 (6494-6508) DOI: 10.18632/oncotarget.27303) - Mijnes, Jolein; Tiedemann, Janina; Eschenbruch, Julian; Gasthaus, Janina; Bringezu, Sarah; Bauerschlag, Dirk; Maass, Nicolai; Arnold, Norbert; Weimer, Jörg; Anzeneder, Tobias; Fasching, Peter; Rübner, Matthias; et al. (Oncotarget, 2020)
TThis article has been corrected: The Grant section information has been updated with the following logos: (Figure Presented).
CRIS-Team Scopus Importer:2020-11-20

Erratum to: The integrative epigenomic-transcriptomic landscape of ER positive breast cancer - Gao, Yang; Jones, Allison; Fasching, Peter; Rübner, Matthias; Beckmann, Matthias; Widschwendter, Martin; Teschendorff, Andrew E. (Clinical Epigenetics, 2016)
EVALuna2:32978

Europe-side external quality assessment (EQA) of RNA based testing of ER, PR, HER2 and Ki67 in invasive breast cancer - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Stöhr, Robert; Beckmann, Matthias; Zentgraf, M.; Rübner, Matthias; Hübner, Hanna; Fischer, J.; Guerini Rocco, E.; Viale, G.; Cayre, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Evaluating the Effectiveness of Mobile Health in Breast Cancer Care: A Systematic Review - Flaucher, Madeleine; Zakreuskaya, Anastasiya; Nissen, Michael; Mocker, Alexander; Fasching, Peter; Beckmann, Matthias; Eskofier, Björn; Leutheuser, Heike (Oncologist, 2023)

Evaluation of a Marker Clip System in Sonographically Guided Core Needle Biopsy for Breast Cancer Localization Before and After Neoadjuvant Chemotherapy - Schulz-Wendtland, Rüdiger; Dankerl, P.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Schrauder, M. G.; Beckmann, Matthias; Uder, M.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Introduction The placement of intramammary marker clips has proven to be helpful for tumor localization in patients undergoing neoadjuvant chemotherapy and breast-conserving surgery. The purpose of our study was to investigate the feasibility of using a clip marker system for breast cancer localization and its influence on the imaging assessment of treatment responses after neoadjuvant chemotherapy. Patients and Methods Between March and June 2015, a total of 25 patients (n = 25), with a suspicion of invasive breast cancer with diameters of at least 2 cm (cT2), underwent preoperative sonographically guided core needle biopsy using a single-use breast biopsy system (HistoCore(TM)) and intramammary clip marking using a directly adapted clip system based on the established O-Twist Marker(TM), before their scheduled preoperative neoadjuvant chemotherapy. Localization of the intramammary marker clip was controlled by sonography and digital breast tomosynthesis. Results Sonography detected no dislocation of intrammammary marker clips in 20 of 25 patients (80 %), while digital breast tomosynthesis showed accurate placement without dislocation in 24 patients (96 %) (p < 0.05). There was no evidence of significant clip migration during preoperative follow-up imaging after neoadjuvant chemotherapy. No complication related to the clip marking was noted and there was no difficulty in evaluating the treatment response to neoadjuvant chemotherapy. Among the breast-conserving surgeries performed, no cases were identified in which intraoperative loss of the marker clip had occurred. Conclusion Our study underscores the importance of intramammary marking clip systems before neoadjuvant chemotherapy. Placement of marker clips is advised to facilitate accurate tumor bed localization. With regard to digital breast tomosynthesis, its development continues to improve the quality of diagnostics and the therapy of breast cancer particularly for small breast cancer tumors or in neoadjuvant chemotherapy setting.
EVALuna2:14620

Evaluation of automated techniques for extraction of circulating cell-free DNA for implementation in standardized high-throughput workflows - Lehle, Sarah; Emons, Julius; Hack, Carolin; Heindl, Felix; Hein, Alexander; Preuß, Caroline; Seitz, Katharina; Zahn, Anna; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (Scientific Reports, 2023)
Analysis of circulating cell-free DNA (ccfDNA) is a suitable tool for detecting somatic mutations for the purpose of making decisions on treatment, monitoring treatment response, and predicting survival. High-throughput techniques for ccfDNA extraction are essential to implementing ccfDNA testing in the clinical setting. We set out to compare two automated techniques with regard to hands-on time, ccfDNA output and integrity, and circulating mitochondrial DNA (mtDNA). CcfDNA was isolated using the EZ1&2 ccfDNA field test kit (EZ2 kit, QIAGEN) and the Maxwell RSC ccfDNA plasma kit (Maxwell kit, Promega). DNA was extracted from plasma of 30 breast cancer patients enrolled in the iMODE-B (#325_19B; 12.10.2020) study. Real-time PCR, fluorescence-based detection and automated electrophoresis were used to assess ccfDNA concentrations. The ccfDNA yield was significantly higher when extracted with the EZ2 kit. The EZ2 kit enabled the isolation of a higher proportion of short fragments and a lower proportion of long fragments, resulting in lower DNA integrity. Significantly lower mtDNA quantities were detected in the Maxwell eluate than in the EZ2 eluate. Thus, decisions on which extraction method to use should proceed on the basis of the required input for downstream applications, the anticipated fragment size and minimum hands-on time.
CRIS-Team Scopus Importer:2023-01-20

Evaluation of ChatGPT’s Potential in Tailoring Gynecological Cancer Therapies - Krückel, Annika; Brückner, Lena; Psilopatis, Iason; Fasching, Peter; Beckmann, Matthias; Emons, Julius (In Vivo, 2024)
Background/Aim: Demographic change and increasing complexity of therapy decisions lead to a growing burden on the healthcare system, necessitating efforts to simplify and enhance the efficiency of patient care. The present study evaluates ChatGPT’s ability to provide therapy recommendations for gynecological malignancies that are both in line with the local guidelines and individually tailored to the patient. Patients and Methods: Sixteen patients with endometrial, cervical, and ovarian cancer who were treated in the gynecological clinic of the University Hospital Erlangen from January 2022 to August 2023 were included in the analysis. Data collected within clinical routine care were communicated to the chat-based AI model ChatGPT (version 3.5). ChatGPT’s performance generating treatment plans were evaluated using an answer scoring system and descriptive analysis. Results: According to the answer scoring system [range: –1 point (minimum) to 2 points (maximum)], ChatGPT demonstrated a good potential in generating therapy recommendations with an average score of 0.75 points for patients with ovarian cancer, 0.7 points for cervical and 1.5 points for endometrial cancer patients. The most common deductions in points were about incomplete therapy recommendations, whereas contraindicated treatment modalities were rarely suggested. Individual patient characteristics were regularly considered by ChatGPT. ChatGPT reliably indicated aftercare and provided detailed information on preventive measures as well as supportive treatment. Conclusion: ChatGPT is a promising tool for the generation of therapy suggestions for gynecological carcinomas with high flexibility in response to individual patient differences. At the current state, however, ChatGPT is not suitable for replacing expert panels.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Artificial intelligence; cervical cancer; ChatGPT; endometrial cancer; ovarian cancer

Evaluation of European-based polygenic risk score for breast cancer in Ashkenazi Jewish women in Israel - Levi, Hagai; Carmi, Shai; Rosset, Saharon; Yerushalmi, Rinat; Zick, Aviad; Yablonski-Peretz, Tamar; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; Ahearn, Thomas; et al. (Journal of Medical Genetics, 2023)
To date, most BC GWASs have been performed Background Polygenic risk score (PRS), calculated in individuals of European (EUR) ancestry, and based on genome-wide association studies (GWASs), the generalisation of EUR-based PRS to other can improve breast cancer (BC) risk assessment. populations is a major challenge. In this study, we examined the performance of EUR-based BC PRS models in Ashkenazi Jewish (AJ) women. Methods We generated PRSs based on data on EUR women from the Breast Cancer Association Consortium (BCAC). We tested the performance of the PRSs in a cohort of 2161 AJ women from Israel (1437 cases and 724 controls) from BCAC (BCAC cohort from Israel (BCAC-IL)). In addition, we tested the performance of these EUR-based BC PRSs, as well as the established 313-SNP EUR BC PRS, in an independent cohort of 181 AJ women from Hadassah Medical Center (HMC) in Israel. Results In the BCAC-IL cohort, the highest OR per 1 SD was 1.56 (±0.09). The OR for AJ women at the top 10% of the PRS distribution compared with the middle quintile was 2.10 (±0.24). In the HMC cohort, the OR per 1 SD of the EUR-based PRS that performed best in the BCAC-IL cohort was 1.58±0.27. The OR per 1 SD of the commonly used 313-SNP BC PRS was 1.64 (±0.28). Conclusions Extant EUR GWAS data can be used for generating PRSs that identify AJ women with markedly elevated risk of BC and therefore hold promise for improving BC risk assessment in AJ women.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Genomics; Polymorphism; Genetic

Evaluation of event-free survival as a surrogate for overall survival in early-stage triple-negative breast cancer following neoadjuvant therapy - Fasching, Peter; Huang, M.; Haiderali, A.; Xue, W.; Pan, W.; Karantza, V.; Yang, F.; Truscott, J.; Xin, Y.; O'Shaughnessy, J. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-23

Evaluation of newly adapted clip marker system in ultrasound-guided core needle biopsy for suspicion of breast cancer - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, Claudia; Bayer, Christian M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: A newly adapted clip system for intramammary marking during ultrasound-guided core needle biopsy for suspicion of breast cancer is described and evaluated here. Material and Method: Fifty patients with suspicion of breast cancer (cT2) had ultrasound-guided core needle biopsy using a newly adapted clip marker system (HistoCore™ and O-Twist Marker™). Subsequently, ultrasound follow-up and tomosynthesis scans were done to determine the location of the marker clips. Results: No dislocation of the marker clip was detected on ultrasound in 45 of 50 patients (90%), and 5 patients (10%) had a maximum dislocation of 5 mm along the x-, y- or z-axis. Tomosynthesis scans demonstrated precise placement without dislocation of the clip markers in 48 patients (96%); 2 patients (4%) had a maximum dislocation of 3 mm along the x-, y- or z-axis. Conclusion: The newly developed clip marker system, a combination of a single-use breast biopsy needle and a precise, length-adapted intramammary marker clip, represents a further improvement in oncological therapy. This is of particular importance for patients requiring subsequent neoadjuvant chemotherapy, as in cases with complete tumour remission, there is no target point for preoperative, ultrasound-guided wire marking. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biopsy; breast; breast cancer; ultrasound

Evaluation of pathological complete response as a trial-level surrogate for long-term survival outcomes among triple-negative breast cancer patients receiving neoadjuvant therapy - Huang, M.; Qi, C. Z.; Ramsey, S.; Briggs, A.; Zhao, J.; Haiderali, A.; Karantza, V.; Xie, J.; Gu, C.; Fasching, Peter (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-13

Evaluation of Pathologic Complete Response as a Surrogate for Long-Term Survival Outcomes in Triple-Negative Breast Cancer - Huang, Min; O'Shaughnessy, Joyce; Zhao, Jing; Haiderali, Amin; Cortes, Javier; Ramsey, Scott; Briggs, Andrew; Karantza, Vassiliki; Aktan, Gursel; Qi, Cynthia Z.; Gu, Chenyang; Xie, Jipan; et al. (Journal of the National Comprehensive Cancer Network : JNCCN, 2020)
BACKGROUND: Pathologic complete response (pCR) is a common efficacy endpoint in neoadjuvant therapy trials for triple-negative breast cancer (TNBC). Previous studies have shown that pCR is strongly associated with improved long-term survival outcomes, including event-free survival (EFS) and overall survival (OS). However, the trial-level associations between treatment effect on pCR and long-term survival outcomes are not well established. This study sought to evaluate these associations by incorporating more recent clinical trials in TNBC. METHODS: A literature review identified published randomized controlled trials (RCTs) of neoadjuvant therapy for TNBC that reported results for both pCR and EFS/OS. Meta-regression models were performed to evaluate the association of treatment effect on pCR and EFS/OS. Sensitivity analyses were conducted to assess the impact of divergent study designs. RESULTS: Ten comparisons from 8 RCTs (N=2,478 patients) were identified from the literature review. The log (odds ratio) of pCR was a significant predictor of the log (hazard ratio) of EFS (P=.003), with a coefficient of determination of 0.68 (95% CI, 0.41-0.95). There was a weaker association between pCR and OS (P=.18), with a coefficient of determination of 0.24 (95% CI, 0.01-0.77). Consistent results were found in the exploratory analysis and sensitivity analyses. CONCLUSIONS: This is the first study that has shown a trial-level association between pCR and survival outcomes in TNBC. By incorporating the most up-to-date RCTs, this study showed a significant trial-level association between pCR and EFS. A positive association between pCR and OS was also recorded.
CRIS-Team Scopus Importer:2020-08-14

Evaluation of serum epidermal growth factor receptor (EGFR) in correlation to circulating tumor cells in patients with metastatic breast cancer - Banys-Paluchowski, Malgorzata; Witzel, Isabell; Riethdorf, Sabine; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter; Solomayer, Erich-Franz; Aktas, Bahriye; Kasimir-Bauer, Sabine; Pantel, Klaus; Fehm, Tanja; Mueller, Volkmar (Scientific Reports, 2017)
Overexpression of epidermal growth factor receptor in breast cancer is associated with estrogen receptor negativity, higher histological grade and larger tumors. The aim of the present study was to evaluate the clinical significance of serum EGFR (sEGFR) in relation to circulating tumor cells (CTCs) in metastatic breast cancer. 252 patients were enrolled in this prospective multicentre study. Blood was drawn before start of a new line of therapy. sEGFR was determined using a sandwich-type ELISA. CTCs were detected using CellSearch. sEGFR was determined in 48 healthy controls and 252 patients, with no significant differences between the two groups. Clinical-pathological parameters did not correlate with sEGFR, irrespective of the cutoff chosen. Patients with sEGFR levels above the 50th and 75th percentile were more likely to present with <5 CTCs per 7.5 ml blood (p = 0.007; p = 0.003). Patients with sEGFR ≥73 ng/ml had significantly longer overall survival than those with sEGFR <73 ng/ml (19.7 vs. 15.2 months; p = 0.007). In the multivariate analysis, presence of ≥5 CTCs, higher grading and higher line of therapy remained independent predictors of shorter OS, while only higher line of therapy and presence of ≥5 CTCs were independent predictors of shorter PFS.
EVALuna2:36177

Evaluation of soluble carbonic anhydrase IX as predictive marker for efficacy of bevacizumab: A biomarker analysis from the geparquinto phase III neoadjuvant breast cancer trial - Janning, Melanie; Müller, Volkmar; Vettorazzi, Eik; Cubas-Cordova, Miguel; Gensch, Victoria; Ben-Batalla, Isabel; zu Eulenburg, Christine; Schem, Christian; Fasching, Peter; Schnappauf, Benjamin; Karn, Thomas; Fehm, Tanja; et al. (International Journal of Cancer, 2019)
We analyzed the predictive potential of pretreatment soluble carbonic anhydrase IX levels (sCAIX) for the efficacy of bevacizumab in the phase III neoadjuvant GeparQuinto trial. sCAIX was determined by enzyme-linked immunosorbent assay (ELISA). Correlations between sCAIX and pathological complete response (pCR), disease-free and overall survival (DFS, OS) were assessed with logistic and Cox proportional hazard regression models using bootstrapping for robust estimates and internal validation. 1,160 HER2-negative patient sera were analyzed, of whom 577 received bevacizumab. Patients with low pretreatment sCAIX had decreased pCR rates (12.1 vs. 20.1%, p = 0.012) and poorer DFS (adjusted 5-year DFS 71.4 vs. 80.5 months, p = 0.010) compared to patients with high sCAIX when treated with neoadjuvant chemotherapy (NCT). For patients with low sCAIX, pCR rates significantly improved upon addition of bevacizumab to NCT (12.1 vs. 20.4%; p = 0.017), which was not the case in patients with high sCAIX (20.1% for NCT vs. 17.0% for NCT-B, p = 0.913). When analyzing DFS we found that bevacizumab improved 5-year DFS for patients with low sCAIX numerically but not significantly (71.4 vs. 78.5 months; log rank 0.234). In contrast, addition of bevacizumab worsened 5-year DFS for patients with high sCAIX (81 vs. 73.6 months, log-rank 0.025). By assessing sCAIX levels we identified a patient cohort in breast cancer that is potentially undertreated with NCT alone. Bevacizumab improved pCR rates in this group, suggesting sCAIX is a predictive biomarker for bevacizumab with regards to treatment response. Our data also show that bevacizumab is not beneficial in patients with high sCAIX.
CRIS-Team Scopus Importer:2019-05-03
Keywords: bevacizumab; breast cancer; carbonic anhydrase IX; neoadjuvant treatment; predictive biomarker

Evaluation of the MammaTyperVR as a molecular predictor for pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) and outcome in patients with different breast cancer (BC) subtypes - Fasching, Peter; Laible, M.; Weber, K. E.; Wirtz, R. M.; Denkert, C.; Schlombs, K.; Schmatloch, S.; Camara, O.; Lueck, H. J.; Huober, J.; Karn, T.; Van Mackelenbergh, M. T.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Evaluation of Therapy Management and Patient Compliance in Postmenopausal Patients with Hormone Receptor-positive Breast Cancer Receiving Letrozole Treatment: The EvaluateTM Study - Fasching, Peter; Fehm, T.; Kellner, S.; De Waal, J.; Rezal, M.; Baler, B.; Baake, G.; Kolberg, H. -C; Guggenberger, M.; Warm, N.; Harbeck, N.; Wuerstlein, R.; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The EvaluateTM study (Evaluation of therapy management and patient compliance in postmenopausal hormone receptor-positive breast cancer patients receiving letrozole treatment) is a prospective, non-interventional study for the assessment of therapy management and compliance in the routine care of postmenopausal women with invasive hormone receptor-positive breast cancer receiving letrozole. The parameters for inclusion in the study are presented and discussed here. Material and Methods: Between January 2008 and December 2009 a total of 5045 patients in 310 study centers were recruited to the EvaluateTM study. Inclusion criteria were hormone receptor-positive breast cancer and adjuvant treatment or metastasis. 373 patients were excluded from the analysis for various reasons. Results: A total of 4420 patients receiving adjuvant treatment and 252 patients with metastasis receiving palliative treatment were included in the study. For 4181 patients receiving adjuvant treatment, treatment with the aromatase inhibitor letrozole commenced immediately after surgery (upfront). Two hundred patients had initially received tamoxifen and started aromatase inhibitor treatment with letrozole at 1-5 years after diagnosis (switch), und 39 patients only commenced letrozole treatment 5-10 years after diagnosis (extended endocrine therapy). Patient and tumor characteristics were within expected ranges, as were comorbidities and concurrent medication. Conclusion: The data from the EvaluateTM study will offer a good overview of therapy management in the routine care of postmenopausal women with hormone receptor-positive breast cancer. Planned analyses will look at therapy compliance and patient satisfaction with how information is conveyed and the contents of the conveyed informatio
EVALuna2:17459

Event-free survival by residual cancer burden with pembrolizumab in early-stage TNBC: exploratory analysis from KEYNOTE-522 - Pusztai, L.; Denkert, C.; O'Shaughnessy, J.; Cortes, J.; Dent, R.; McArthur, H.; Kümmel, S.; Bergh, J.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; et al. (Annals of Oncology, 2024)
Background: KEYNOTE-522 demonstrated statistically significant improvements in pathological complete response (pCR) with neoadjuvant pembrolizumab plus chemotherapy and event-free survival (EFS) with neoadjuvant pembrolizumab plus chemotherapy followed by adjuvant pembrolizumab in patients with high-risk, early-stage triple-negative breast cancer (TNBC). Prior studies have shown the prognostic value of the residual cancer burden (RCB) index to quantify the extent of residual disease after neoadjuvant chemotherapy. In this preplanned exploratory analysis, we assessed RCB distribution and EFS within RCB categories by treatment group. Patients and methods: A total of 1174 patients with stage T1c/N1-2 or T2-4/N0-2 TNBC were randomized 2 : 1 to pembrolizumab 200 mg or placebo every 3 weeks given with four cycles of paclitaxel + carboplatin, followed by four cycles of doxorubicin or epirubicin + cyclophosphamide. After surgery, patients received pembrolizumab or placebo for nine cycles or until recurrence or unacceptable toxicity. Primary endpoints are pCR and EFS. RCB is a prespecified exploratory endpoint. The association between EFS and RCB was assessed using a Cox regression model. Results: Pembrolizumab shifted patients into lower RCB categories across the entire spectrum compared with placebo. There were more patients in the pembrolizumab group with RCB-0 (pCR), and fewer patients in the pembrolizumab group with RCB-1, RCB-2, and RCB-3. The corresponding hazard ratios (95% confidence intervals) for EFS were 0.70 (0.38-1.31), 0.92 (0.39-2.20), 0.52 (0.32-0.82), and 1.24 (0.69-2.23). The most common first EFS events were distant recurrences, with fewer in the pembrolizumab group across all RCB categories. Among patients with RCB-0/1, more than half [21/38 (55.3%)] of all events were central nervous system recurrences, with 13/22 (59.1%) in the pembrolizumab group and 8/16 (50.0%) in the placebo group. Conclusions: Addition of pembrolizumab to chemotherapy resulted in fewer EFS events in the RCB-0, RCB-1, and RCB-2 categories, with the greatest benefit in RCB-2. These findings demonstrate that pembrolizumab not only increased pCR rates, but also improved EFS among most patients who do not have a pCR.
CRIS-Team Scopus Importer:2024-04-12
Keywords: chemotherapy; event-free survival; immunotherapy; pembrolizumab; residual cancer burden; triple-negative breast cancer

Event Report 11th Scientific Symposium of the AGO TraFo - Banys-Paluchowski, Malgorzata; Wunderle, Marius; Fehm, Tanja N.; Arnold, Norbert; Fasching, Peter (Geburtshilfe und Frauenheilkunde, 2019)
CRIS-Team WoS Importer:2020-01-17

Event Report 7th Scientific Symposium of AGO-TraFo - Niederacher, Dieter; Fasching, Peter; Fehm, Tanja N. (Geburtshilfe und Frauenheilkunde, 2016)
EVALuna2:33100

Event Report 8th Scientific Symposium of the AGO-TraFo - Banys-Paluchowski, Malgorzata; Hein, Alexander; Niederacher, Dieter; Fasching, Peter; Fehm, Tanja N. (Geburtshilfe und Frauenheilkunde, 2017)
EVALuna2:36207

EVI1 expression in early-stage breast cancer patients treated with neoadjuvant chemotherapy - Leichsenring, J.; Vladimirova, V.; Solbach, C.; Karn, T.; Ataseven, B.; Sinn, B.; Barinoff, J.; Mueller, V.; Blohmer, J-U.; Schem, C.; Engels, K.; Marme, F.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

EVI1 expression in early-stage breast cancer patients treated with neoadjuvant chemotherapy - Leichsenring, Jonas; Vladimirova, Valentina; Solbach, Christine; Karn, Thomas; Ataseven, Beyhan; Sinn, Bruno Valentin; Barinoff, Jana; Mueller, Volkmar; Blohmer, Jens-Uwe; Schem, Christian; Engels, Knut; Marme, Frederik; et al. (BMC Cancer, 2022)
Background: Overexpression of the EVI1 (ecotropic viral integration site 1) oncogene has recently been implicated as a prognostic factor in breast cancer (BC), particularly in triple-negative BC (TNBC). In this study we aimed to investigate frequency and clinical relevance of EVI1 expression in newly diagnosed BC treated with neoadjuvant chemotherapy. Methods: EVI1 expression was determined by immunohistochemistry using H-score as a cumulative measurement of protein expression in pretherapeutic biopsies of BC patients treated with anthracycline/taxane based neoadjuvant chemotherapy within the GeparTrio trial. EVI1 was analyzed as a continuous variable and dichotomized into low or high based on median expression. Endpoints were pathological complete response (pCR), disease-free survival (DFS) and overall survival (OS). Results: Of the 993 tumors analyzed, 882 had available subtype information: 50.8% were HR + /HER2-, 15% HR + /HER2 + , 9.8% HR-/HER2 + , and 24.5% TNBC. Median EVI1 H-score was 112.16 (range 0.5–291.4). High EVI1 expression was significantly associated with smaller tumor size (p = 0.002) but not with BC subtype. Elevated EVI1 levels were not significantly associated with therapy response and survival in the entire cohort or within BC subtypes. However, TNBC patients with high EVI1 showed a trend towards increased pCR rates compared to low group (37.7% vs 27.5%, p = 0.114; odds ratio 1.60 (95%CI 0.90–2.85, p = 0.110) and numerically better DFS (HR = 0.77 [95%CI 0.48–1.23], log-rank p = 0.271) and OS (HR = 0.76 [95% 0.44–1.31], log-rank p = 0.314) without reaching statistical significance. Conclusion: EVI1 was not associated with response to neoadjuvant therapy or patient survival in the overall cohort. Further analyses are needed to verify our findings especially in the pathological work-up of early-stage HER2-negative BC patients. Trial registration: NCT00544765.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Breast cancer; EVI1; Neoadjuvant chemotherapy

Evidence for a shared genetic basis between breast cancer and mammographic density phenotypes - Chen, Hongjie; Douglas, Julie; Gordon, William; Thompson, Deborah; Couch, Fergus; Fasching, Peter; Hall, Per; Hopper, John; Maskarenic, Gertraud; Pollan, Marina; Stone, Jennifer; Tamimi, Rulla; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Evidence for a time-dependent association between FOLR1 expression and survival from ovarian carcinoma: implications for clinical testing. An Ovarian Tumour Tissue Analysis consortium study - Koebel, M.; Madore, J.; Ramus, S. J.; Clarke, B. A.; Pharoah, P. D. P.; Deen, S.; Bowtell, D. D.; Odunsi, K.; Menon, U.; Morrison, C.; Lele, S.; Bshara, W.; et al. (British Journal of Cancer, 2014)
Folate receptor 1 (FOLR1) is expressed in the majority of ovarian carcinomas (OvCa), making it an attractive target for therapy. However, clinical trials testing anti-FOLR1 therapies in OvCa show mixed results and require better understanding of the prognostic relevance of FOLR1 expression. We conducted a large study evaluating FOLR1 expression with survival in different histological types of OvCa.Tissue microarrays composed of tumour samples from 2801 patients in the Ovarian Tumour Tissue Analysis (OTTA) consortium were assessed for FOLR1 expression by centralised immunohistochemistry. We estimated associations for overall (OS) and progression-free (PFS) survival using adjusted Cox regression models. High-grade serous ovarian carcinomas (HGSC) from The Cancer Genome Atlas (TCGA) were evaluated independently for association between FOLR1 mRNA upregulation and survival.FOLR1 expression ranged from 76% in HGSC to 11% in mucinous carcinomas in OTTA. For HGSC, the association between FOLR1 expression and OS changed significantly during the years following diagnosis in OTTA (Pinteraction=0.01, N=1422) and TCGA (Pinteraction=0.01, N=485). In OTTA, particularly for FIGO stage I/II tumours, patients with FOLR1-positive HGSC showed increased OS during the first 2 years only (hazard ratio=0.44, 95% confidence interval=0.20-0.96) and patients with FOLR1-positive clear cell carcinomas (CCC) showed decreased PFS independent of follow-up time (HR=1.89, 95% CI=1.10-3.25, N=259). In TCGA, FOLR1 mRNA upregulation in HGSC was also associated with increased OS during the first 2 years following diagnosis irrespective of tumour stage (HR: 0.48, 95% CI: 0.25-0.94).FOLR1-positive HGSC tumours were associated with an increased OS in the first 2 years following diagnosis. Patients with FOLR1-negative, poor prognosis HGSC would be unlikely to benefit from anti-FOLR1 therapies. In contrast, a decreased PFS interval was observed for FOLR1-positive CCC. The clinical efficacy of FOLR1-targeted interventions should therefore be evaluated according to histology, stage and time following diagnosis.
EVALuna2:6660

Evidence that breast cancer risk at the 2q35 locus is mediated through IGFBP5 regulation - Ghoussaini, Maya; Edwards, Stacey L.; Michailidou, Kyriaki; Nord, Silje; Lari, Richard Cowper-Sal; Desai, Kinjal; Kar, Siddhartha; Hillman, Kristine M.; Kaufmann, Susanne; Glubb, Dylan M.; Beesley, Jonathan; Dennis, Joe; et al. (Nature Communications, 2014)
GWAS have identified a breast cancer susceptibility locus on 2q35. Here we report the fine mapping of this locus using data from 101,943 subjects from 50 case-control studies. We genotype 276 SNPs using the 'iCOGS' genotyping array and impute genotypes for a further 1,284 using 1000 Genomes Project data. All but two, strongly correlated SNPs (rs4442975 G/T and rs6721996 G/A) are excluded as candidate causal variants at odds against >100:1. The best functional candidate, rs4442975, is associated with oestrogen receptor positive (ER+) disease with an odds ratio (OR) in Europeans of 0.85 (95% confidence interval=0.84-0.87; P=1.7 × 10(-43)) per t-allele. This SNP flanks a transcriptional enhancer that physically interacts with the promoter of IGFBP5 (encoding insulin-like growth factor-binding protein 5) and displays allele-specific gene expression, FOXA1 binding and chromatin looping. Evidence suggests that the g-allele confers increased breast cancer susceptibility through relative downregulation of IGFBP5, a gene with known roles in breast cell biolog
EVALuna2:9236

Evidence that the 5p12 Variant rs10941679 Confers Susceptibility to Estrogen-Receptor-Positive Breast Cancer through FGF10 and MRPS30 Regulation - Ghoussaini, Maya; French, Juliet D.; Michailidou, Kyriaki; Nord, Silje; Beesley, Jonathan; Canisus, Sander; Hillman, Kristine M.; Kaufmann, Susanne; Sivakumaran, Haran; Marjaneh, Mandi Moradi; Lee, Jason S.; Dennis, Joe; et al. (American Journal of Human Genetics, 2016)
Genome-wide association studies (GWASs) have revealed increased breast cancer risk associated with multiple genetic variants at 5p12. Here, we report the fine mapping of this locus using data from 104,660 subjects from 50 case-control studies in the Breast Cancer Association Consortium (BCAC). With data for 3,365 genotyped and imputed SNPs across a 1 Mb region (positions 44,394,495-45,364,167; NCBI build 37), we found evidence for at least three independent signals: the strongest signal, consisting of a single SNP rs10941679, was associated with risk of estrogen-receptor-positive (ER+) breast cancer (per-g allele OR ER+= 1.15; 95% CI 1.13-1.18; p = 8.35 × 10-30). After adjustment for rs10941679, we detected signal 2, consisting of 38 SNPs more strongly associated with ER-negative (ER-) breast cancer (lead SNP rs6864776: per-a allele OR ER-= 1.10; 95% CI 1.05-1.14; p conditional = 1.44 × 10-12), and a single signal 3 SNP (rs200229088: per-t allele OR ER+= 1.12; 95% CI 1.09-1.15; p conditional = 1.12 × 10-05). Expression quantitative trait locus analysis in normal breast tissues and breast tumors showed that the g (risk) allele of rs10941679 was associated with increased expression of FGF10 and MRPS30. Functional assays demonstrated that SNP rs10941679 maps to an enhancer element that physically interacts with the FGF10 and MRPS30 promoter regions in breast cancer cell lines. FGF10 is an oncogene that binds to FGFR2 and is overexpressed in ∼10% of human breast cancers, whereas MRPS30 plays a key role in apoptosis. These data suggest that the strongest signal of association at 5p12 is mediated through coordinated activation of FGF10 and MRPS30, two candidate genes for breast cancer pathogenesis.
EVALuna2:33316

Expression of disialoganglioside GD2 in breast cancer subtypes - Gaß, Paul; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Schulz-Wendtland, Rüdiger; Farwick, Nicole; Roessig, Claudia; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Expression of neuroendocrine markers in different molecular subtypes of breast carcinoma - Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Hein, Alexander; Bayer, Christian M.; Agaimy, Abbas (BioMed Research International, 2014)
Carcinomas of the breast with neuroendocrine features are incorporated in the World Health Organization classification since 2003 and include well-differentiated neuroendocrine tumors, poorly differentiated neuroendocrine carcinomas/small cell carcinomas, and invasive breast carcinomas with neuroendocrine differentiation. Neuroendocrine differentiation is known to be more common in certain low-grade histologic special types and has been shown to mainly cluster to the molecular (intrinsic) luminal A subtype.We analyzed the frequency of neuroendocrine differentiation in different molecular subtypes of breast carcinomas of no histologic special type using immunohistochemical stains with specific neuroendocrine markers (chromogranin A and synaptophysin).We found neuroendocrine differentiation in 20% of luminal B-like carcinomas using current WHO criteria (at least 50% of tumor cells positive for synaptophysin or chromogranin A). In contrast, no neuroendocrine differentiation was seen in luminal A-like, HER2 amplified and triple-negative carcinomas. Breast carcinomas with neuroendocrine differentiation presented with advanced stage disease and showed aggressive behavior.We conclude that neuroendocrine differentiation is more common than assumed in poorly differentiated luminal B-like carcinomas. Use of specific neuroendocrine markers is thus encouraged in this subtype to enhance detection of neuroendocrine differentiation and hence characterize the biological and therapeutic relevance of this finding in future studies.
EVALuna2:6612

Expression of secreted protein acidic and rich in cysteine (SPARC) in breast cancer and response to neoadjuvant chemotherapy - Lindner, J. L.; Loibl, S.; Denkert, Carsten; Ataseven, B.; Fasching, Peter; Pfitzner, B. M.; Gerber, B.; Gade, S.; Darb-Esfahani, S.; Sinn, B. V.; Huober, J.; Engels, K.; et al. (Annals of Oncology, 2015)
Secreted protein acidic and rich in cysteine (SPARC) has been suggested as a new biomarker and therapeutic target in breast cancer, as well as other tumor types.We evaluated the frequency of SPARC expression among different molecular breast cancer subtypes and its role for therapy response after neoadjuvant chemotherapy. In this study, pretherapeutic core biopsies of 667 patients from the neoadjuvant GeparTrio trial were evaluated for SPARC expression by immunohistochemistry using a standardized immunoreactive score (IRS).An increased SPARC expression (IRS >=6) was observed in 26% of all tumors. In triple-negative tumors, SPARC expression was increased in 37% of tumors, compared with other molecular subtypes (23% HR+/HER2-, 29% HR+/HER2+ and 22% HR-/HER2+; P = 0.038). Increased SPARC expression was associated with an increased pathological complete response (pCR) rate of 27%, compared with 15% in tumors with low SPARC expression (P < 0.001). In the triple-negative subgroup, pCR rates were 47% in tumors with high SPARC expression, compared with 26% in tumors with low SPARC expression (P = 0.032). In multivariable analysis, SPARC was independently predictive in the overall population (P = 0.010) as well as the triple-negative subgroup (P = 0.036).SPARC is frequently expressed in breast cancer with triple-negative breast cancer revealing the highest expression rate. High SPARC expression of the primary tumor is associated with a higher chance of achieving a pathological complete remission after TAC or TAC-NX chemotherapy. As SPARC is an albumin-binding protein and might mediate intratumoral accumulation of albumin bound drugs, SPARC should be further evaluated as a predictive marker especially for response to albumin-bound drugs like nab-paclitaxel.NCT00544765.
EVALuna2:17559

Expression of the Immunohistochemical Markers CK5, CD117, and EGFR in Molecular Subtypes of Breast Cancer Correlated with Prognosis - Schulmeyer, Carla; Fasching, Peter; Häberle, Lothar; Meyer, Julia; Schneider, Michael; Wachter, David; Rübner, Matthias; Pöschke, Patrik; Beckmann, Matthias; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Diagnostics, 2023)
Molecular-based subclassifications of breast cancer are important for identifying treatment options and stratifying the prognosis in breast cancer. This study aimed to assess the prognosis relative to disease-free survival (DFS) and overall survival (OS) in patients with triple-negative breast cancer (TNBC) and other subtypes, using a biomarker panel including cytokeratin 5 (CK5), cluster of differentiation 117 (CD117), and epidermal growth factor receptor (EGFR). This cohort–case study included histologically confirmed breast carcinomas as cohort arm. From a total of 894 patients, 572 patients with early breast cancer, sufficient clinical data, and archived tumor tissue were included. Using the immunohistochemical markers CK5, CD117, and EGFR, two subgroups were formed: one with all three biomarkers negative (TBN) and one with at least one of those three biomarkers positive (non-TBN). There were significant differences between the two biomarker subgroups (TBN versus non-TBN) in TNBC for DFS (p = 0.04) and OS (p = 0.02), with higher survival rates (DFS and OS) in the non-TBN subgroup. In this study, we found the non-TBN subgroup of TNBC lesions with at least one positive biomarker of CK5, CD117, and/or EGFR, to be associated with longer DFS and OS.
CRIS-Team Scopus Importer:2023-02-24
Keywords: CD117; CK5; early breast cancer; EGFR; prognosis; therapy; triple-negative breast cancer

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

Factors Influencing Decision-Making for or against Adjuvant and Neoadjuvant Chemotherapy in Postmenopausal Hormone Receptor-Positive Breast Cancer Patients in the EvAluate-TM Study - Gaß, Paul; Fasching, Peter; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; Wuerstlein, Rachel; et al. (Breast Care, 2016)
BACKGROUND: Decision-making for or against neoadjuvant or adjuvant chemotherapy in postmenopausal patients with hormone receptor-positive breast cancer does not follow any clear guidelines, and some patients may unnecessarily undergo chemotherapy and be exposed to the associated toxicity. The aim of this study was to identify the patient population for whom this issue may bear relevance. METHODS: Patients being treated with letrozole in the prospective multicenter noninterventional EvAluate-TM study were recruited. The percentage of patients receiving chemotherapy and factors associated with chemotherapy administration were identified. RESULTS: In all, 3,924 (37.4%) patients received chemotherapy before treatment with letrozole. Of these, 293 (20%) underwent neoadjuvant therapy. Younger age was predictive for both adjuvant and neoadjuvant therapy. Overall, decisions in favor of administering chemotherapy are more likely to be made in patients with a higher body mass index (BMI), and neoadjuvant chemotherapy is administered at a higher rate in women with a lower BMI. Concomitant medication influenced the overall decision-making regarding chemotherapy, irrespective of whether it was given on a neoadjuvant or adjuvant basis. CONCLUSION: There is an ongoing debate as to whether all of the many patients who receive chemotherapy actually benefit from it. Neoadjuvant chemotherapy is frequently administered in this patient population, and this should encourage further research to resolve current clinical and research issues.
EVALuna2:33331

Factors Predicting Discordance in HER2 Phenotype between Primary Tumor and Circulating Tumor Cells in Women with Metastatic Breast Cancer - Janni, W.; Schramm, A.; Friedl, T. W. P.; Schochter, E.; Huober, J.; Rack, B.; Alunni-Fabbroni, M.; Fasching, Peter; Taran, F-A.; Hortkopf, A.; Schneeweiss, A.; Mueller, V.; et al. (2016)
EVALuna2:33105

FANCM missense variants and breast cancer risk: a case-control association study of 75,156 European women - Figlioli, Gisella; Billaud, Amandine; Ahearn, Thomas U.; Antonenkova, Natalia N.; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Benitez, Javier; Bermisheva, Marina; Blok, Marinus J.; Bogdanova, Natalia; Bonanni, Bernardo; et al. (European Journal of Human Genetics, 2023)
Evidence from literature, including the BRIDGES study, indicates that germline protein truncating variants (PTVs) in FANCM confer moderately increased risk of ER-negative and triple-negative breast cancer (TNBC), especially for women with a family history of the disease. Association between FANCM missense variants (MVs) and breast cancer risk has been postulated. In this study, we further used the BRIDGES study to test 689 FANCM MVs for association with breast cancer risk, overall and in ER-negative and TNBC subtypes, in 39,885 cases (7566 selected for family history) and 35,271 controls of European ancestry. Sixteen common MVs were tested individually; the remaining rare 673 MVs were tested by burden analyses considering their position and pathogenicity score. We also conducted a meta-analysis of our results and those from published studies. We did not find evidence for association for any of the 16 variants individually tested. The rare MVs were significantly associated with increased risk of ER-negative breast cancer by burden analysis comparing familial cases to controls (OR = 1.48; 95% CI 1.07-2.04; P = 0.017). Higher ORs were found for the subgroup of MVs located in functional domains or predicted to be pathogenic. The meta-analysis indicated that FANCM MVs overall are associated with breast cancer risk (OR = 1.22; 95% CI 1.08-1.38; P = 0.002). Our results support the definition from previous analyses of FANCM as a moderate-risk breast cancer gene and provide evidence that FANCM MVs could be low/moderate risk factors for ER-negative and TNBC subtypes. Further genetic and functional analyses are necessary to clarify better the increased risks due to FANCM MVs.
CRIS-Team WoS Importer:2023-04-07

Fatal events during clinical trials: an evaluation of deaths during breast cancer studies - Furlanetto, Jenny; von Minckwitz, Gunter; Lederer, Bianca; Möbus, Volker; Schneeweiss, Andreas; Huober, Jens; Fasching, Peter; Gerber, Bernd; Bauerfeind, Ingo; Nitz, Ulrike; Lück, Hans Joachim; Hanusch, Claus; et al. (Breast Cancer, 2019)
Background: Information on deaths occurring during oncological clinical trials has never been systematically assessed. Here, we examine the incidence of death and the profile of patients who died during randomized clinical breast cancer (BC) trials. Methods: Information on fatal events during German Breast Group (GBG) led BC trials was prospectively captured. Data were derived from the trial databases and death narratives. All deaths were evaluated for possible causes, underlying conditions, treatment relatedness, time point and rate of autopsies. Results: From 12/1996 to 01/2017, 23,387 patients were treated within 32 trials. Of those 88 (0.4%) died on therapy within 17 trials. Median age was 64 [range 35–84] years, 63.2% of patients had a body mass index (BMI) ≥ 25 kg/m2; 65.9% 1–3 and 22.7% ≥ 4 comorbidities; 61.4% 1–2 cardiovascular risk factors (CRFs); 26.4% took > 3 drugs; 81.7% had ECOG 0; 50.0% stage III, 76.7% luminal BC. The main causes of death were infection (38.6%; of those, 82.3% sepsis, 17.6% pneumonia), heart failure (14.8%), and pulmonary embolism (13.6%). Fatal events mainly occurred within the first 4 therapy cycles (55.7%), in the investigational arm (66.7%) and under anthracycline–taxane-based chemotherapy (51.1%). A relationship with the treatment was declared in 27.3% of the cases. An autopsy was performed in 13.6% of patients. Conclusions: Death during study treatment was mainly related to infections, and patients with advanced disease, high BMI, underlying comorbidities, CRFs and concomitant medications. If considered for study participation these patients need careful monitoring due to their higher risk for death on study.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Cause of death; Chemotherapy-related death; Death in clinical trial; Rate of autopsy; Serious adverse events

Favorable impact of therapy management by an interactive eHealth system on severe adverse events in patients with hormone receptor-positive, HER2-negative locally advanced or metastatic breast cancer treated by palbociclib and endocrine therapy - Harbeck, Nadia; Kates, Ronald; Schinköthe, Timo; Schumacher, Johannes; Wuerstlein, Rachel; Degenhardt, Tom; Lüftner, Diana; Räth, Philip; Hoffmann, Oliver; Lorenz, Ralf; Decker, Thomas; Reinisch, Mattea; et al. (Cancer Treatment Reviews, 2023)
Background: Oral cancer medications offer advantages but also pose challenges for therapy management and adherence. An eHealth-based platform such as CANKADO can help to support therapy management by probing the patient's quality of life (QoL) continuously throughout the course of treatment. Material and Methods: AGO-B WSG PreCycle (NCT03220178) is a multicenter, randomized phase IV intergroup trial evaluating the impact of eHealth-based Patient-Reported Outcome (ePRO) assessment on QoL in patients with hormone receptor-positive (HR + )/HER2-negative (HER2-) advanced breast cancer treated with palbociclib and endocrine therapy. Patients were randomized (2:1) to CANKADO-active arm (supported by CANKADO PRO-React) or CANKADO-inform arm (drug intake documentation only) This exploratory analysis reports the impact of CANKADO PRO-React on safety. Time to first serious adverse event (SAE) was estimated taking competing risks into account. Results: While distributions of adverse events (AEs) were similar by arm overall, patients in the CANKADO-active arm had a favorable hazard ratio of 0.67 (95%CI 0.46–0.97; p = 0.04) for time to first SAE and were significantly less likely overall to suffer an SAE than patients in the inform arm. At 24 months, 22.9% [17.9%-27.8%] of patients in CANKADO-active had suffered an SAE vs. 30.3% [22.6%-38.0%] in CANKADO-inform. AE-related dose reductions affected approximately 20% of patients (CANKADO-active: 18.2%, CANKADO-inform: 21.1%). Conclusion: Exploratory safety analysis of PreCycle demonstrates for the first time in a randomized prospective trial that interactive autonomous eHealth-based support has a substantial favorable impact on the risk of SAEs and mitigates their severity for patients with advanced HR+/HER2- breast cancer on oral tumor therapy.
CRIS-Team Scopus Importer:2023-10-27
Keywords: CANKADO; CDK4/6 inhibitor; eHealth; Endocrine therapy; Metastatic breast cancer; Patient-reported outcomes; Quality of life; Serious adverse events

Feasibility and Acceptance of Self-Guided Mobile Ultrasound among Pregnant Women in Routine Prenatal Care - Pontones, Constanza; Titzmann, Adriana; Hübner, Hanna; Danzberger, Nina; Rübner, Matthias; Häberle, Lothar; Eskofier, Björn; Nissen, Michael; Kehl, Sven; Faschingbauer, Florian; Beckmann, Matthias; Fasching, Peter; et al. (Journal of Clinical Medicine, 2023)
Background and objectives: Mobile and remote ultrasound devices are becoming increasingly available. The benefits and possible risks of self-guided ultrasound examinations conducted by pregnant women at home have not yet been well explored. This study investigated aspects of feasibility and acceptance, as well as the success rates of such examinations. Methods: In this prospective, single-center, interventional study, forty-six women with singleton pregnancies between 17 + 0 and 29 + 6 weeks of gestation were included in two cohorts, using two different mobile ultrasound systems. The participants examined the fetal heartbeat, fetal profile and amniotic fluid. Aspects of feasibility and acceptance were evaluated using a questionnaire. Success rates in relation to image and video quality were evaluated by healthcare professionals. Results: Two thirds of the women were able to imagine performing the self-guided examination at home, but 87.0% would prefer live support by a professional. Concerns about their own safety and that of the child were expressed by 23.9% of the women. Success rates for locating the target structure were 52.2% for videos of the fetal heartbeat, 52.2% for videos of the amniotic fluid in all four quadrants and 17.9% for videos of the fetal profile. Conclusion: These results show wide acceptance of self-examination using mobile systems for fetal ultrasonography during pregnancy. Image quality was adequate for assessing the amniotic fluid and fetal heartbeat in most participants. Further studies are needed to determine whether ultrasound self-examinations can be implemented in prenatal care and how this would affect the fetomaternal outcome.
CRIS-Team Scopus Importer:2023-07-28
Keywords: acceptance; feasibility; mobile ultrasound; pregnancy; prenatal care; self-guided ultrasound

FemZone trial: a randomized phase II trial comparing neoadjuvant letrozole and zoledronic acid with letrozole in primary breast cancer patients - Fasching, Peter; Jud, Sebastian; Hauschild, Maik; Kuemmel, Sherko; Schuette, Martin; Warm, Matthias; Hanf, Volker; Grab, Dieter; Krocker, Jutta; Stickeler, Elmar; Kreienberg, Rolf; Mueller, Thomas; et al. (BMC Cancer, 2014)
The objective of this prospectively randomized phase II trial (Trial registration: EUCTR2004-004007-37-DE) was to compare the clinical response of primary breast cancer patients to neoadjuvant therapy with letrozole alone (LET) or letrozole and zoledronic acid (LET + ZOL).Patients were randomly assigned to receive either LET 2.5 mg/day (n = 79) or the combination of LET 2.5 mg/day and a total of seven infusions of ZOL 4 mg every 4 weeks (n = 89) for 6 months. Primary endpoint was clinical response rate as assessed by mammogram readings. The study was terminated prematurely due to insufficient recruitment. We report here on an exploratory analysis of this data.Central assessment of tumor sizes during the treatment period was available for 131 patients (66 LET, 65 LET + ZOL). Clinical responses (complete or partial) were seen in 54.5% (95% CI: 41.8-66.9) of the patients in the LET arm and 69.2% (95% CI: 56.6-80.1) of those in the LET + ZOL arm (P = 0.106). A multivariate model showed an OR of 1.72 (95% CI: 0.83-3.59) for the experimental arm.No increase in the clinical response rate was observed with the addition of ZOL to a neoadjuvant treatment regimen with LET. However a trend towards a better reponse in the LET + ZOL arm could be observed. This trend is consistent with previous studies that have investigated the addition of ZOL to chemotherapy, and it may support the evidence for a direct antitumor action of zoledronic acid.
EVALuna2:14433

Fetal Re-Identification in Multiple Pregnancy Ultrasound Images Using Deep Learning - Gabler, Elisabeth; Nissen, Michael; Altstidl, Thomas Robert; Titzmann, Adriana; Packhäuser, Kai; Maier, Andreas; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Ultrasound examinations during pregnancy can detect abnormal fetal development, which is a leading cause of perinatal mortality. In multiple pregnancies, the position of the fetuses may change between examinations. The individual fetus cannot be clearly identified. Fetal re-identification may improve diagnostic capabilities by tracing individual fetal changes. This work evaluates the feasibility of fetal re-identification on FETAL-PLANES-DB, a publicly available dataset of singleton pregnancy ultrasound images. Five dataset subsets with 6,491 images from 1,088 pregnant women and two re-identification frameworks (Torchreid, FastReID) are evaluated. FastReID achieves a mean average precision of 68.77% (68.42%) and mean precision at rank 10 score of 89.60% (95.55%) when trained on images showing the fetal brain (abdomen). Visualization with gradient-weighted class activation mapping shows that the classifiers appear to rely on anatomical features. We conclude that fetal re-identification in ultrasound images may be feasible. However, more work on additional datasets, including images from multiple pregnancies and several subsequent examinations, is required to ensure and investigate performance stability and explainability.Clinical relevance - To date, fetuses in multiple pregnancies cannot be distinguished between ultrasound examinations. This work provides the first evidence for feasibility of fetal re-identification in pregnancy ultrasound images. This may improve diagnostic capabilities in clinical practice in the future, such as longitudinal analysis of fetal changes or abnormalities.
Created from Fastlane, Scopus look-up
Keywords: Pregnancy; Deep learning; Visualization; Ultrasonic imaging; Fetus; Stability analysis; Biology

FGF receptor genes and breast cancer susceptibility: results from the Breast Cancer Association Consortium - Agarwal, D.; Pineda, S.; Michailidou, K.; Herranz, J.; Pita, G.; Moreno, L. T.; Alonso, M. R.; Dennis, J.; Wang, Q.; Bolla, M. K.; Meyer, K. B.; Menendez-Rodriguez, P.; et al. (British Journal of Cancer, 2014)
Breast cancer is one of the most common malignancies in women. Genome-wide association studies have identified FGFR2 as a breast cancer susceptibility gene. Common variation in other fibroblast growth factor (FGF) receptors might also modify risk. We tested this hypothesis by studying genotyped single-nucleotide polymorphisms (SNPs) and imputed SNPs in FGFR1, FGFR3, FGFR4 and FGFRL1 in the Breast Cancer Association Consortium.Data were combined from 49 studies, including 53 835 cases and 50 156 controls, of which 89 050 (46 450 cases and 42 600 controls) were of European ancestry, 12 893 (6269 cases and 6624 controls) of Asian and 2048 (1116 cases and 932 controls) of African ancestry. Associations with risk of breast cancer, overall and by disease sub-type, were assessed using unconditional logistic regression.Little evidence of association with breast cancer risk was observed for SNPs in the FGF receptor genes. The strongest evidence in European women was for rs743682 in FGFR3; the estimated per-allele odds ratio was 1.05 (95% confidence interval=1.02-1.09, P=0.0020), which is substantially lower than that observed for SNPs in FGFR2.Our results suggest that common variants in the other FGF receptors are not associated with risk of breast cancer to the degree observed for FGFR2.
EVALuna2:9221

Filtration based assessment of CTCs and CellSearch® based assessment are both powerful predictors of prognosis for metastatic breast cancer patients - Hübner, Hanna; Fasching, Peter; Gumbrecht, Walter; Jud, Sebastian; Rauh, Claudia; Matzas, Mark; Paulicka, Peter; Friedrich, Katja; Lux, Michael P.; Volz, Bernhard; Gaß, Paul; Häberle, Lothar; et al. (BMC Cancer, 2018)
The assessment of circulating tumor cells (CTCs) has been shown to enable monitoring of treatment response and early detection of metastatic breast cancer (MBC) recurrence. The aim of this study was to compare a well-established CTC detection method based on immunomagnetic isolation with a new, filtration-based platform.In this prospective study, two 7.5 ml blood draws were obtained from 60 MBC patients and CTC enumeration was assessed using both the CellSearch® and the newly developed filtration-based platform. We analyzed the correlation of CTC-positivity between both methods and their ability to predict prognosis. Overall survival (OS) was calculated and Kaplan-Meier curves were estimated with thresholds of >=1 and >=5 detected CTCs.The CTC positivity rate of the CellSearch® system was 56.7% and of the filtration-based platform 66.7%. There was a high correlation of CTC enumeration obtained with both methods. The OS for patients without detected CTCs, regardless of the method used, was significantly higher compared to patients with one or more CTCs (p < 0.001). The median OS of patients with no CTCs vs. >= 1 CTC assessed by CellSearch® was 1.83 years (95% CI: 1.63-2.02) vs. 0.74 years (95% CI: 0.51-1.52). If CTCs were detected by the filtration-based method the median OS times were 1.88 years (95% CI: 1.74-2.03) vs. 0.59 years (95% CI: 0.38-0.80).The newly established EpCAM independently filtration-based system is a suitable method to determine CTC counts for MBC patients. Our study confirms CTCs as being strong predictors of prognosis in our population of MBC patients.
EVALuna2:51529

Fine-mapping identifies two additional breast cancer susceptibility loci at 9q31.2 - Orr, Nick; Dudbridge, Frank; Dryden, Nicola; Maguire, Sarah; Novo, Daniela; Perrakis, Eleni; Johnson, Nichola; Ghoussaini, Maya; Hopper, John L.; Southey, Melissa C.; Apicella, Carmel; Stone, Jennifer; et al. (Human Molecular Genetics, 2015)
We recently identified a novel susceptibility variant, rs865686, for estrogen-receptor positive breast cancer at 9q31.2. Here, we report a fine-mapping analysis of the 9q31.2 susceptibility locus using 43 160 cases and 42 600 controls of European ancestry ascertained from 52 studies and a further 5795 cases and 6624 controls of Asian ancestry from nine studies. Single nucleotide polymorphism (SNP) rs676256 was most strongly associated with risk in Europeans (odds ratios [OR] = 0.90 [0.88-0.92]; P-value = 1.58 × 10(-25)). This SNP is one of a cluster of highly correlated variants, including rs865686, that spans 14.5 kb. We identified two additional independent association signals demarcated by SNPs rs10816625 (OR = 1.12 [1.08-1.17]; P-value = 7.89 × 10(-09)) and rs13294895 (OR = 1.09 [1.06-1.12]; P-value = 2.97 × 10(-11)). SNP rs10816625, but not rs13294895, was also associated with risk of breast cancer in Asian individuals (OR = 1.12 [1.06-1.18]; P-value = 2.77 × 10(-05)). Functional genomic annotation using data derived from breast cancer cell-line models indicates that these SNPs localise to putative enhancer elements that bind known drivers of hormone-dependent breast cancer, including ER-?, FOXA1 and GATA-3. In vitro analyses indicate that rs10816625 and rs13294895 have allele-specific effects on enhancer activity and suggest chromatin interactions with the KLF4 gene locus. These results demonstrate the power of dense genotyping in large studies to identify independent susceptibility variants. Analysis of associations using subjects with different ancestry, combined with bioinformatic and genomic characterisation, can provide strong evidence for the likely causative alleles and their functional basi
EVALuna2:9279

Fine-Mapping of the 1p11.2 Breast Cancer Susceptibility Locus - Horne, Hisani N.; Chung, Charles C.; Zhang, Han; Yu, Kai; Prokunina-Olsson, Ludmila; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Hopper, John L.; Southey, Melissa C.; Schmidt, Marjanka K.; et al. (PLoS ONE, 2016)
The Cancer Genetic Markers of Susceptibility genome-wide association study (GWAS) originally identified a single nucleotide polymorphism (SNP) rs11249433 at 1p11.2 associated with breast cancer risk. To fine-map this locus, we genotyped 92 SNPs in a 900kb region (120,505,799-121,481,132) flanking rs11249433 in 45,276 breast cancer cases and 48,998 controls of European, Asian and African ancestry from 50 studies in the Breast Cancer Association Consortium. Genotyping was done using iCOGS, a custom-built array. Due to the complicated nature of the region on chr1p11.2: 120,300,000-120,505,798, that lies near the centromere and contains seven duplicated genomic segments, we restricted analyses to 429 SNPs excluding the duplicated regions (42 genotyped and 387 imputed). Per-allelic associations with breast cancer risk were estimated using logistic regression models adjusting for study and ancestry-specific principal components. The strongest association observed was with the original identified index SNP rs11249433 (minor allele frequency (MAF) 0.402; per-allele odds ratio (OR) = 1.10, 95% confidence interval (CI) 1.08-1.13, P = 1.49 x 10-21). The association for rs11249433 was limited to ER-positive breast cancers (test for heterogeneity P≤8.41 x 10-5). Additional analyses by other tumor characteristics showed stronger associations with moderately/well differentiated tumors and tumors of lobular histology. Although no significant eQTL associations were observed, in silico analyses showed that rs11249433 was located in a region that is likely a weak enhancer/promoter. Fine-mapping analysis of the 1p11.2 breast cancer susceptibility locus confirms this region to be limited to risk to cancers that are ER-positive.
EVALuna2:33323

Fine-scale mapping of 8q24 locus identifies multiple independent risk variants for breast cancer - Shi, Jiajun; Zhang, Yanfeng; Zheng, Wei; Michailidou, Kyriaki; Ghoussaini, Maya; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Milne, Roger L.; Shu, Xiao-Ou; Beesley, Jonathan; et al. (International Journal of Cancer, 2016)
Previous genome-wide association studies among women of European ancestry identified two independent breast cancer susceptibility loci represented by single nucleotide polymorphisms (SNPs) rs13281615 and rs11780156 at 8q24. A fine-mapping study across 2.06 Mb (chr8:127,561,724-129,624,067, hg19) in 55,540 breast cancer cases and 51,168 controls within the Breast Cancer Association Consortium was conducted. Three additional independent association signals in women of European ancestry, represented by rs35961416 (OR = 0.95, 95% CI = 0.93-0.97, conditional p = 5.8 × 10(-6) ), rs7815245 (OR = 0.94, 95% CI = 0.91-0.96, conditional p = 1.1 × 10(-6) ) and rs2033101 (OR = 1.05, 95% CI = 1.02-1.07, conditional p = 1.1 × 10(-4) ) were found. Integrative analysis using functional genomic data from the Roadmap Epigenomics, the Encyclopedia of DNA Elements project, the Cancer Genome Atlas and other public resources implied that SNPs rs7815245 in Signal 3, and rs1121948 in Signal 5 (in linkage disequilibrium with rs11780156, r(2) = 0.77), were putatively functional variants for two of the five independent association signals. The results highlighted multiple 8q24 variants associated with breast cancer susceptibility in women of European ancestry.
EVALuna2:33319

Fine scale mapping of the 17q22 breast cancer locus using dense SNPs, genotyped within the Collaborative Oncological Gene-Environment Study (COGs) - Darabi, Hatef; Beesley, Jonathan; Droit, Arnaud; Kar, Siddhartha; Nord, Silje; Marjaneh, Mahdi Moradi; Soucy, Penny; Michailidou, Kyriaki; Ghoussaini, Maya; Wahl, Hanna Fues; Bolla, Manjeet K.; Wang, Qin; et al. (Scientific Reports, 2016)
Genome-wide association studies have found SNPs at 17q22 to be associated with breast cancer risk. To identify potential causal variants related to breast cancer risk, we performed a high resolution fine-mapping analysis that involved genotyping 517 SNPs using a custom Illumina iSelect array (iCOGS) followed by imputation of genotypes for 3,134 SNPs in more than 89,000 participants of European ancestry from the Breast Cancer Association Consortium (BCAC). We identified 28 highly correlated common variants, in a 53 Kb region spanning two introns of the STXBP4 gene, that are strong candidates for driving breast cancer risk (lead SNP rs2787486 (OR = 0.92; CI 0.90-0.94; P = 8.96 × 10(-15))) and are correlated with two previously reported risk-associated variants at this locus, SNPs rs6504950 (OR = 0.94, P = 2.04 × 10(-09), r(2) = 0.73 with lead SNP) and rs1156287 (OR = 0.93, P = 3.41 × 10(-11), r(2) = 0.83 with lead SNP). Analyses indicate only one causal SNP in the region and several enhancer elements targeting STXBP4 are located within the 53 kb association signal. Expression studies in breast tumor tissues found SNP rs2787486 to be associated with increased STXBP4 expression, suggesting this may be a target gene of this locus.
EVALuna2:33320

Fine-scale mapping of the 4q24 locus identifies two independent loci associated with breast cancer risk - Guo, Xingyi; Long, Jirong; Zeng, Chenjie; Michailidou, Kyriaki; Ghoussaini, Maya; Bolla, Manjeet K.; Wang, Qin; Milne, Roger L.; Shu, Xiao-Ou; Cai, Qiuyin; Beesley, Jonathan; Kar, Siddhartha P.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
A recent association study identified a common variant (rs9790517) at 4q24 to be associated with breast cancer risk. Independent association signals and potential functional variants in this locus have not been explored.We conducted a fine-mapping analysis in 55,540 breast cancer cases and 51,168 controls from the Breast Cancer Association Consortium.Conditional analyses identified two independent association signals among women of European ancestry, represented by rs9790517 [conditional P = 2.51 × 10(-4); OR, 1.04; 95% confidence interval (CI), 1.02-1.07] and rs77928427 (P = 1.86 × 10(-4); OR, 1.04; 95% CI, 1.02-1.07). Functional annotation using data from the Encyclopedia of DNA Elements (ENCODE) project revealed two putative functional variants, rs62331150 and rs73838678 in linkage disequilibrium (LD) with rs9790517 (r(2) >= 0.90) residing in the active promoter or enhancer, respectively, of the nearest gene, TET2. Both variants are located in DNase I hypersensitivity and transcription factor-binding sites. Using data from both The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC), we showed that rs62331150 was associated with level of expression of TET2 in breast normal and tumor tissue.Our study identified two independent association signals at 4q24 in relation to breast cancer risk and suggested that observed association in this locus may be mediated through the regulation of TET2.Fine-mapping study with large sample size warranted for identification of independent loci for breast cancer risk.
EVALuna2:17572

Fine-scale mapping of the 5q11.2 breast cancer locus reveals at least three independent risk variants regulating MAP3K1 - Glubb, Dylan M.; Maranian, Mel J.; Michailidou, Kyriaki; Pooley, Karen A.; Meyer, Kerstin B.; Kar, Siddhartha; Carlebur, Saskia; O'Reilly, Martin; Betts, Joshua A.; Hillman, Kristine M.; Kaufmann, Susanne; Beesley, Jonathan; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies (GWASs) have revealed SNP rs889312 on 5q11.2 to be associated with breast cancer risk in women of European ancestry. In an attempt to identify the biologically relevant variants, we analyzed 909 genetic variants across 5q11.2 in 103,991 breast cancer individuals and control individuals from 52 studies in the Breast Cancer Association Consortium. Multiple logistic regression analyses identified three independent risk signals: the strongest associations were with 15 correlated variants (iCHAV1), where the minor allele of the best candidate, rs62355902, associated with significantly increased risks of both estrogen-receptor-positive (ER(+): odds ratio [OR] = 1.24, 95% confidence interval [CI] = 1.21-1.27, ptrend = 5.7 × 10(-44)) and estrogen-receptor-negative (ER(-): OR = 1.10, 95% CI = 1.05-1.15, ptrend = 3.0 × 10(-4)) tumors. After adjustment for rs62355902, we found evidence of association of a further 173 variants (iCHAV2) containing three subsets with a range of effects (the strongest was rs113317823 [pcond = 1.61 × 10(-5)]) and five variants composing iCHAV3 (lead rs11949391; ER(+): OR = 0.90, 95% CI = 0.87-0.93, pcond = 1.4 × 10(-4)). Twenty-six percent of the prioritized candidate variants coincided with four putative regulatory elements that interact with the MAP3K1 promoter through chromatin looping and affect MAP3K1 promoter activity. Functional analysis indicated that the cancer risk alleles of four candidates (rs74345699 and rs62355900 [iCHAV1], rs16886397 [iCHAV2a], and rs17432750 [iCHAV3]) increased MAP3K1 transcriptional activity. Chromatin immunoprecipitation analysis revealed diminished GATA3 binding to the minor (cancer-protective) allele of rs17432750, indicating a mechanism for its action. We propose that the cancer risk alleles act to increase MAP3K1 expression in vivo and might promote breast cancer cell surviva
EVALuna2:9276

First Results of the Detect IVA Study -Everolimus Treatment in Patients with HER2-Negative, Hormone-Receptor Positive Metastatic Breast (MBC) Cancer and Circulating Tumor Cells (CTC) - Friedl, Thomas W. P.; Krause, Sabrina; Fasching, Peter; Schneeweiss, Andreas; Mueller, Volkmar; Riethdorf, Sabine; Taran, Florin-Andrei; Schochter, Fabienne; Polasik, Arkadius; Tzschaschel, Marie; De Gregorio, Amelie; Meier-Stiegen, Franziska; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Five endometrial cancer risk loci identified through genome-wide association analysis - Cheng, Timothy H. T.; Thompson, Deborah J.; O'Mara, Tracy A.; Painter, Jodie N.; Glubb, Dylan M.; Flach, Susanne; Lewis, Annabelle; French, Juliet D.; Freeman-Mills, Luke; Church, David; Gorman, Maggie; Martin, Lynn; et al. (Nature Genetics, 2016)
We conducted a meta-analysis of three endometrial cancer genome-wide association studies (GWAS) and two follow-up phases totaling 7,737 endometrial cancer cases and 37,144 controls of European ancestry. Genome-wide imputation and meta-analysis identified five new risk loci of genome-wide significance at likely regulatory regions on chromosomes 13q22.1 (rs11841589, near KLF5), 6q22.31 (rs13328298, in LOC643623 and near HEY2 and NCOA7), 8q24.21 (rs4733613, telomeric to MYC), 15q15.1 (rs937213, in EIF2AK4, near BMF) and 14q32.33 (rs2498796, in AKT1, near SIVA1). We also found a second independent 8q24.21 signal (rs17232730). Functional studies of the 13q22.1 locus showed that rs9600103 (pairwise r(2) = 0.98 with rs11841589) is located in a region of active chromatin that interacts with the KLF5 promoter region. The rs9600103[T] allele that is protective in endometrial cancer suppressed gene expression in vitro, suggesting that regulation of the expression of KLF5, a gene linked to uterine development, is implicated in tumorigenesis. These findings provide enhanced insight into the genetic and biological basis of endometrial cancer.
EVALuna2:9326

Frühes Mammakarzinom: Aktuelle Strategien in der System- und Radiotherapie: 17. Internationale St.-Gallen-Konsensuskonferenz vor dem Hintergrund deutscher Therapieempfehlungen diskutiert - Schneeweiss, Andreas; Huober, Jens; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Jackisch, Christian; Janni, Wolfgang; Krug, David; Kühn, Thorsten; et al. (Onkologe, 2021)
Background: The St. Gallen (SG) International Consensus Conference on the treatment of patients with primary breast cancer (SG-BCC) has been held regularly for more than 30 years. As the international panel of the St. Gallen conference consists of experts from different countries and different disciplines, the consensus voting that results from these meetings represents an international cross-section of opinions. Rationale: From the German perspective it is considered useful to discuss the results of the consensus voting with respect to the clinical routine in Germany. Basis: The discussion is based on the German treatment guidelines of the Working Group of Gynecologic Oncology of the German Cancer Society (AGO 2021) which are updated annually and the German S3 guideline. Results: The topic of this year’s 17th St. Gallen Consensus Conference was “Customizing local and systemic therapies for women with early breast cancer”. The rationale behind this is that each treatment decision must also consider the cancer-specific situation of the individual patient. In this article, the most important results of the SG-BCC in systemic treatment and radiotherapy are discussed.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Consensus recommendations 2021; Local treatment; Systemic treatment; Treatment de-escalation; Treatment of early breast cancer

Full field digital mammography (FFDM) versus cmos technology, specimen radiography system (SRS) and tomosynthesis (DBT) - Which system can optimise surgical therapy? - Schulz-Wendtland, Rüdiger; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Brehm, Barbara; Hammon, Matthias; Saake, Marc; Dankerl, Peter; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: This prospective clinical study aimed to evaluate whether it would be possible to reduce the rate of re-excisions using CMOS technology, a specimen radiography system (SRS) or digital breast tomosynthesis (DBT) compared to a conventional full field digital mammography (FFDM) system. Material and Method: Between 12/2012 and 2/2013 50 patients were diagnosed with invasive breast cancer (BI-RADS™ 5). After histological verification, all patients underwent breast-conserving therapy with intraoperative imaging using 4 different systems and differing magnifications: 1. Inspiration™ (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm; 2. BioVision™ (Bioptics, Tucson, AZ, USA), CMOS technology, photodiode array, flat panel, tungsten source, focus 0.05, resolution 50 m pixel pitch, 12 lp/mm; 3. the Trident™ specimen radiography system (SRS) (Hologic, Bedford, MA, USA), amorphous selenium, tungsten source, focus 0.05, resolution 70 m pixel pitch, 7.1 lp/mm; 4. tomosynthesis (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm, angular range 50 degrees, 25 projections, scan time > 20 s, geometry: uniform scanning, reconstruction: filtered back projection. The 600 radiographs were prospectively shown to 3 radiologists. Results: Of the 50 patients with histologically proven breast cancer (BI-RADS™ 6), 39 patients required no further surgical therapy (re-excision) after breast-conserving surgery. A retrospective analysis (n = 11) showed a significant (p < 0.05) increase of sensitivity with the BioVision™, the Trident™ and tomosynthesis compared to the Inspiration™ at a magnification of 1.0: 2.0 or 1.0: 1.0 (tomosynthesis) (2.6, 3.3 or 3.6 %), i.e. re-excision would not have been necessary in 2, 3 or 4 patients, respectively, compared to findings obtained with a standard magnification of 1.0: 1.0. Conclusion: The sensitivity of the BioVision™, the Trident™ and tomosynthesis was significantly (p < 0.05) higher and the rate of re-excisions was reduced compared to FFDM using a conventional detector at a magnification of 2.0 but without zooming. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast; breast cancer; breast malignancy; mammography

Fully automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
Nipple position provides useful diagnostic informations in reading automated 3D breast ultrasound (ABUS) images. The identification of nipples is required to localize and determine the quadrants of breast lesions. Additionally, the nipple position serves as an effective landmark to register an ABUS image to other imaging modalities, such as digital mammography, breast magnet resonance imaging (MRI), or tomosynthesis. Nevertheless, the presence of speckle noise induced by interference waves and variant imaging directions in ultrasonography poses challenges to the task. In this work, we propose a fast and automated algorithm to detect nipples in 3D breast ultrasound images. The method fully takes advantages of the consistent characteristics of ultrasonographic signals observed at nipples and employs a multi-scale Laplacian-based blob detector to eventually identify nipple positions. The accuracy of the proposed method was tested on 113 ABUS images, resulting in a distance error of 6.6±8.9 mm (mean ±std). © 2014 Springer International Publishing.
CRIS-Team Scopus Importer:2023-03-08

Fully automatic HER2 tissue segmentation for interpretable HER2 scoring - Öttl, Mathias; Steenpaß, Jana; Wilm, Frauke; Qiu, Jingna; Rübner, Matthias; Lang-Schwarz, Corinna; Taverna, Cecilia; Tava, Francesca; Hartmann, Arndt; Hübner, Hanna; Beckmann, Matthias; Fasching, Peter; et al. (Journal of Pathology Informatics, 2025)
Breast cancer is the most common cancer in women, with HER2 (human epidermal growth factor receptor 2) overexpression playing a critical role in regulating cell growth and division. HER2 status, assessed according to established scoring guidelines, offers important information for treatment selection. However, the complexity of the task leads to variability in human rater assessments. In this work, we propose a fully automated, interpretable HER2 scoring pipeline based on pixel-level semantic segmentations, designed to align with clinical guidelines. Using polygon annotations, our method balances annotation effort with the ability to capture fine-grained details and larger structures, such as non-invasive tumor tissue. To enhance HER2 segmentation, we propose the use of a Wasserstein Dice loss to model class relationships, ensuring robust segmentation and HER2 scoring performance. Additionally, based on observations of pathologists' behavior in clinical practice, we propose a calibration step to the scoring rules, which positively impacts the accuracy and consistency of automated HER2 scoring. Our approach achieves an F1 score of 0.832 on HER2 scoring, demonstrating its effectiveness. This work establishes a potent segmentation pipeline that can be further leveraged to analyze HER2 expression in breast cancer tissue.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Deep learning; HER2; HER2 scoring; Histopathology; Semantic segmentation

Functional Analysis and Fine Mapping of the 9p22.2 Ovarian Cancer Susceptibility Locus - Buckley, Melissa A.; Woods, Nicholas T.; Tyrer, Jonathan P.; Mendoza-Fandino, Gustavo; Lawrenson, Kate; Hazelett, Dennis J.; Najafabadi, Hamed S.; Gjyshi, Anxhela; Carvalho, Renato S.; Lyra, Paulo C.; Coetzee, Simon G.; Shen, Howard C.; et al. (Cancer Research, 2019)
Genome-wide association studies have identified 40 ovarian cancer risk loci. However, the mechanisms underlying these associations remain elusive. In this study, we conducted a two-pronged approach to identify candidate causal SNPs and assess underlying biological mechanisms at chromosome 9p22.2, the first and most statistically significant associated locus for ovarian cancer susceptibility. Three transcriptional regulatory elements with allele-specific effects and a scaffold/matrix attachment region were characterized and, through physical DNA interactions, BNC2 was established as the most likely target gene. We determined the consensus binding sequence for BNC2 in vitro, verified its enrichment in BNC2 ChIP-seq regions, and validated a set of its downstream target genes. Fine-mapping by dense regional genotyping in over 15,000 ovarian cancer cases and 30,000 controls identified SNPs in the scaffold/ matrix attachment region as among the most likely causal variants. This study reveals a comprehensive regulatory landscape at 9p22.2 and proposes a likely mechanism of susceptibility to ovarian cancer.
CRIS-Team WoS Importer:2019-02-21

Functional mechanisms underlying pleiotropic risk alleles at the 19p13.1 breast-ovarian cancer susceptibility locus - Lawrenson, Kate; Kar, Siddhartha; Mccue, Karen; Kuchenbaeker, Karoline; Michailidou, Kyriaki; Tyrer, Jonathan; Beesley, Jonathan; Ramus, Susan J.; Li, Qiyuan; Delgado, Melissa K.; Lee, Janet M.; Aittomaki, Kristiina; et al. (Nature Communications, 2016)
A locus at 19p13 is associated with breast cancer (BC) and ovarian cancer (OC) risk. Here we analyse 438 SNPs in this region in 46,451 BC and 15,438 OC cases, 15,252 BRCA1 mutation carriers and 73,444 controls and identify 13 candidate causal SNPs associated with serous OC (P=9.2 × 10(-20)), ER-negative BC (P=1.1 × 10(-13)), BRCA1-associated BC (P=7.7 × 10(-16)) and triple negative BC (P-diff=2 × 10(-5)). Genotype-gene expression associations are identified for candidate target genes ANKLE1 (P=2 × 10(-3)) and ABHD8 (P<2 × 10(-3)). Chromosome conformation capture identifies interactions between four candidate SNPs and ABHD8, and luciferase assays indicate six risk alleles increased transactivation of the ADHD8 promoter. Targeted deletion of a region containing risk SNP rs56069439 in a putative enhancer induces ANKLE1 downregulation; and mRNA stability assays indicate functional effects for an ANKLE1 3'-UTR SNP. Altogether, these data suggest that multiple SNPs at 19p13 regulate ABHD8 and perhaps ANKLE1 expression, and indicate common mechanisms underlying breast and ovarian cancer risk.
EVALuna2:33322

Galactography with Tomosynthesis Technique (Galactomosynthesis) - Renaissance of a Method? - Schulz-Wendtland, Rüdiger; Preuss, Caroline; Fasching, Peter; Löhberg, Christian; Lux, Michael P.; Emons, Julius; Beckmann, Matthias; Uder, Michael; Mueller-Schimpfle, Markus (Geburtshilfe und Frauenheilkunde, 2018)
Introduction: For decades, conventional galactography was the only imaging technique capable of showing the mammary ducts. Today, diagnosis is based on a multimodal concept which combines high-resolution ultrasound with magnetic resonance (MR) mammography and ductoscopy/galactoscopy and has a sensitivity and specificity of up to 95%. This study used tomosynthesis in galactography for the first time and compared the synthetic digital 2D full-field mammograms generated with this technique with the images created using the established method of ductal sonography. Both methods should be able to detect invasive breast cancers and their precursors such as ductal carcinoma in situ (DCIS) as well as being able to identify benign findings. Material and Methods: Five patients with pathological nipple discharge were examined using ductal sonography, contrast-enhanced 3D galactography with tomosynthesis and the synthetic digital 2D full-field mammograms generated with the latter method. Evaluation of the images created with the different imaging modalities was done by three investigators with varying levels of experience with complementary breast diagnostics (1, 5 and 15 years), and their evaluations were compared with the histological findings. Results: All 3 investigators independently evaluated the images created with ductal sonography, contrast-enhanced 3D galactography with tomosynthesis, and generated synthetic digital 2D full-field mammograms. Their evaluations were compared with the histopathological assessment of the surgical specimens resected from the 5 patients. There was 1 case of invasive breast cancer, 2 cases with ductal carcinoma in situ and 2 cases with benign findings. All 3 investigators made more mistakes when they used the standard imaging technique of ductal sonography to diagnose suspicious lesions than when they used contrast-enhanced galactography with tomosynthesis and the generated synthetic digital 2D full-field mammograms. Conclusion: This is the first time breast tomosynthesis was used in galactography (galactomosynthesis) to create digital 3-dimensional images of suspicious findings. When used together with the generated synthetic digital 2D full-field mammograms, it could be a useful complementary procedure for the diagnosis of breast anomalies and could herald a renaissance of this method. Compared with high-resolution ductal ultrasound, the investigators achieved better results with contrast-enhanced galactography using tomosynthesis and the generated synthetic digital 2D full-field mammograms, as confirmed by histopathological findings.
EVALuna2:34697

Gemcitabine as adjuvant chemotherapy in patients with high-risk early breast cancer—results from the randomized phase III SUCCESS-A trial - de Gregorio, Amelie; Häberle, Lothar; Fasching, Peter; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Friedl, Thomas W.P.; Bauer, Emanuel; de Gregorio, Nikolaus; Deniz, Miriam; Fink, Visnja; et al. (Breast Cancer Research, 2020)
Background: When chemotherapy is indicated in patients with early breast cancer, regimens that contain anthracyclines and taxanes are established standard treatments. Gemcitabine has shown promising effects on the response and prognosis in patients with metastatic breast cancer. The SUCCESS-A trial (NCT02181101) examined the addition of gemcitabine to a standard chemotherapy regimen in high-risk early breast cancer patients. Methods: A total of 3754 patients with at least one of the following characteristics were randomly assigned to one of the two treatment arms: nodal positivity, tumor grade 3, age ≤ 35 years, tumor larger than 2 cm, or negative hormone receptor status. The treatment arms received either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide, followed by three cycles of docetaxel (FEC → Doc); or three cycles of FEC followed by three cycles of docetaxel and gemcitabine (FEC → Doc/Gem). The primary study aim was disease-free survival (DFS), and the main secondary objectives were overall survival (OS) and safety. Results: No differences were observed in the 5-year DFS or OS between FEC → Doc and FEC → Doc/Gem. The hazard ratio was 0.93 (95% CI, 0.78 to 1.12; P = 0.47) for DFS and 0.94 (95% CI, 0.74 to 1.19; P = 0.60) for OS. For patients treated with FEC → Doc and FEC → Doc/Gem, the 5-year probabilities of DFS were 86.6% and 87.2%, and the 5-year probabilities of OS were 92.8% and 92.5%, respectively. Conclusion: Adding gemcitabine to a standard chemotherapy does not improve the outcomes in patients with high-risk early breast cancer and should therefore not be included in the adjuvant treatment setting. Trial registration: Clinicaltrials.gov NCT02181101 and EU Clinical Trials Register EudraCT 2005-000490-21. Registered September 2005.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Chemotherapy; Early breast cancer; Gemcitabine

Gene-environment interactions involving functional variants: Results from the Breast Cancer Association Consortium - Barrdahl, Myrto; Rudolph, Anja; Hopper, John L.; Southey, Melissa C.; Broeks, Annegien; Fasching, Peter; Beckmann, Matthias; Gago-Dominguez, Manuela; Castelao, J. Esteban; Guenel, Pascal; Truong, Therese; Bojesen, Stig E.; et al. (International Journal of Cancer, 2017)
Investigating the most likely causal variants identified by fine-mapping analyses may improve the power to detect gene-environment interactions. We assessed the interplay between 70 single nucleotide polymorphisms identified by genetic fine-scale mapping of susceptibility loci and 11 epidemiological breast cancer risk factors in relation to breast cancer. Analyses were conducted on up to 58,573 subjects (26,968 cases and 31,605 controls) from the Breast Cancer Association Consortium, in one of the largest studies of its kind. Analyses were carried out separately for estrogen receptor (ER) positive (ER+) and ER negative (ER-) disease. The Bayesian False Discovery Probability (BFDP) was computed to assess the noteworthiness of the results. Four potential gene-environment interactions were identified as noteworthy (BFDP < 0.80) when assuming a true prior interaction probability of 0.01. The strongest interaction result in relation to overall breast cancer risk was found between CFLAR-rs7558475 and current smoking (ORint = 0.77, 95% CI: 0.67-0.88, pint = 1.8 × 10-4 ). The interaction with the strongest statistical evidence was found between 5q14-rs7707921 and alcohol consumption (ORint =1.36, 95% CI: 1.16-1.59, pint = 1.9 × 10-5 ) in relation to ER- disease risk. The remaining two gene-environment interactions were also identified in relation to ER- breast cancer risk and were found between 3p21-rs6796502 and age at menarche (ORint = 1.26, 95% CI: 1.12-1.43, pint =1.8 × 10-4 ) and between 8q23-rs13267382 and age at first full-term pregnancy (ORint = 0.89, 95% CI: 0.83-0.95, pint = 5.2 × 10-4 ). While these results do not suggest any strong gene-environment interactions, our results may still be useful to inform experimental studies. These may in turn, shed light on the potential interactions observed.
EVALuna2:36122

Gene-Environment Interactions Relevant to Estrogen and Risk of Breast Cancer: Can Gene-Environment Interactions Be Detected Only among Candidate SNPs from Genome-Wide Association Studies? - Park, Jooyong; Choi, Ji-Yeob; Choi, Jaesung; Chung, Seokang; Song, Nan; Park, Sue K.; Han, Wonshik; Noh, Dong-Young; Ahn, Sei-Hyun; Lee, Jong Won; Kim, Mi Kyung; Jee, Sun Ha; et al. (Cancers, 2021)
Simple Summary
CRIS-Team WoS Importer:2021-06-04

Gene-Expression Profiling of Mucinous Ovarian Tumors and Comparison with Upper and Lower Gastrointestinal Tumors Identifies Markers Associated with Adverse Outcomes. - Meagher, Nicola S.; Gorringe, Kylie L.; Wakefield, Matthew J.; Bolithon, Adelyn; Pang, Chi Nam Ignatius; Chiu, Derek S.; Anglesio, Michael S.; Mallitt, Kylie-Ann; Doherty, Jennifer A.; Harris, Holly R.; Schildkraut, Joellen M.; Berchuck, Andrew; et al. (Clinical Cancer Research, 2022)
PURPOSE: Advanced-stage mucinous ovarian carcinoma (MOC) has poor chemotherapy response and prognosis and lacks biomarkers to aid stage I adjuvant treatment. Differentiating primary MOC from gastrointestinal (GI) metastases to the ovary is also challenging due to phenotypic similarities. Clinicopathologic and gene-expression data were analyzed to identify prognostic and diagnostic features. EXPERIMENTAL DESIGN: Discovery analyses selected 19 genes with prognostic/diagnostic potential. Validation was performed through the Ovarian Tumor Tissue Analysis consortium and GI cancer biobanks comprising 604 patients with MOC (n = 333), mucinous borderline ovarian tumors (MBOT, n = 151), and upper GI (n = 65) and lower GI tumors (n = 55). RESULTS: Infiltrative pattern of invasion was associated with decreased overall survival (OS) within 2 years from diagnosis, compared with expansile pattern in stage I MOC [hazard ratio (HR), 2.77; 95% confidence interval (CI), 1.04-7.41, P = 0.042]. Increased expression of THBS2 and TAGLN was associated with shorter OS in MOC patients (HR, 1.25; 95% CI, 1.04-1.51, P = 0.016) and (HR, 1.21; 95% CI, 1.01-1.45, P = 0.043), respectively. ERBB2 (HER2) amplification or high mRNA expression was evident in 64 of 243 (26%) of MOCs, but only 8 of 243 (3%) were also infiltrative (4/39, 10%) or stage III/IV (4/31, 13%). CONCLUSIONS: An infiltrative growth pattern infers poor prognosis within 2 years from diagnosis and may help select stage I patients for adjuvant therapy. High expression of THBS2 and TAGLN in MOC confers an adverse prognosis and is upregulated in the infiltrative subtype, which warrants further investigation. Anti-HER2 therapy should be investigated in a subset of patients. MOC samples clustered with upper GI, yet markers to differentiate these entities remain elusive, suggesting similar underlying biology and shared treatment strategies.
EVALuna2:513963

Gene Expression Signatures of BRCAness and Tumor Inflammation Define Subgroups of Early-Stage Hormone Receptor-Positive Breast Cancer Patients - Schroth, Werner; Buettner, Florian A.; Kandabarau, Siarhei; Hoppe, Reiner; Fritz, Peter; Kumbrink, Joerg; Kirchner, Thomas; Brauer, Heather A.; Ren, Yuqi; Henderson, David; Madden, Stephen F.; Sauer, Georg; et al. (Clinical Cancer Research, 2020)
Purpose: Patients with estrogen receptor- and/or progesterone receptor-positive, early breast cancer benefit from hormonal treatment, yet high global death burdens due to high prevalence and long-term recurrence risk call for biomarkers to guide additional treatment approaches.
CRIS-Team WoS Importer:2021-02-05

Gene panel sequencing in familial breast/ovarian cancer patients identifies multiple novel mutations also in genes others than BRCA1/2 - Kraus, Cornelia; Hoyer, Juliane; Vasileiou, Georgia; Wunderle, Marius; Lux, Michael P.; Fasching, Peter; Krumbiegel, Mandy; Uebe, Steffen; Reuter, Miriam; Beckmann, Matthias; Reis, André (International Journal of Cancer, 2017)
Breast and ovarian cancer (BC/OC) predisposition has been attributed to a number of high- and moderate to low-penetrance susceptibility genes. With the advent of next generation sequencing (NGS) simultaneous testing of these genes has become feasible. In this monocentric study, we report results of panel-based screening of 14 BC/OC susceptibility genes (BRCA1, BRCA2, RAD51C, RAD51D, CHEK2, PALB2, ATM, NBN, CDH1, TP53, MLH1, MSH2, MSH6 and PMS2) in a group of 581 consecutive individuals from a German population with BC and/or OC fulfilling diagnostic criteria for BRCA1 and BRCA2 testing including 179 with a triple-negative tumor. Altogether we identified 106 deleterious mutations in 105 (18%) patients in 10 different genes, including seven different exon deletions. Of these 106 mutations, 16 (15%) were novel and only six were found in BRCA1/2. To further characterize mutations located in or nearby splicing consensus sites we performed RT-PCR analysis which allowed confirmation of pathogenicity in 7 of 9 mutations analyzed. In PALB2, we identified a deleterious variant in six cases. All but one were associated with early onset BC and a positive family history indicating that penetrance for PALB2 mutations is comparable to BRCA2. Overall, extended testing beyond BRCA1/2 identified a deleterious mutation in further 6% of patients. As a downside, 89 variants of uncertain significance were identified highlighting the need for comprehensive variant databases. In conclusion, panel testing yields more accurate information on genetic cancer risk than assessing BRCA1/2 alone and wide-spread testing will help improve penetrance assessment of variants in these risk genes.
EVALuna2:9340

Generalization of a deep learning model for HER2 status predictions on H&E-stained whole slide images derived from 3 neoadjuvant clinical studies - Haegele, M.; Mueller, K-R.; Denkert, C.; Schneeweiss, Andreas; Sinn, B. V.; Untch, M.; Van Mackelenbergh, M. T.; Jackisch, C.; Nekljudova, V.; Karn, T.; Alber, M.; Marme, F.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-23

Genetically Predicted Body Mass Index and Breast Cancer Risk: Mendelian Randomization Analyses of Data from 145,000 Women of European Descent - Guo, Yan; Andersen, Shaneda Warren; Shu, Xiao-Ou; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Garcia-Closas, Montserrat; Milne, Roger L.; Schmidt, Marjanka K.; Chang-Claude, Jenny; Dunning, Allison; Bojesen, Stig E.; et al. (Plos Medicine, 2016)
BACKGROUND: Observational epidemiological studies have shown that high body mass index (BMI) is associated with a reduced risk of breast cancer in premenopausal women but an increased risk in postmenopausal women. It is unclear whether this association is mediated through shared genetic or environmental factors. METHODS: We applied Mendelian randomization to evaluate the association between BMI and risk of breast cancer occurrence using data from two large breast cancer consortia. We created a weighted BMI genetic score comprising 84 BMI-associated genetic variants to predicted BMI. We evaluated genetically predicted BMI in association with breast cancer risk using individual-level data from the Breast Cancer Association Consortium (BCAC) (cases = 46,325, controls = 42,482). We further evaluated the association between genetically predicted BMI and breast cancer risk using summary statistics from 16,003 cases and 41,335 controls from the Discovery, Biology, and Risk of Inherited Variants in Breast Cancer (DRIVE) Project. Because most studies measured BMI after cancer diagnosis, we could not conduct a parallel analysis to adequately evaluate the association of measured BMI with breast cancer risk prospectively. RESULTS: In the BCAC data, genetically predicted BMI was found to be inversely associated with breast cancer risk (odds ratio [OR] = 0.65 per 5 kg/m2 increase, 95% confidence interval [CI]: 0.56-0.75, p = 3.32 × 10-10). The associations were similar for both premenopausal (OR = 0.44, 95% CI:0.31-0.62, p = 9.91 × 10-8) and postmenopausal breast cancer (OR = 0.57, 95% CI: 0.46-0.71, p = 1.88 × 10-8). This association was replicated in the data from the DRIVE consortium (OR = 0.72, 95% CI: 0.60-0.84, p = 1.64 × 10-7). Single marker analyses identified 17 of the 84 BMI-associated single nucleotide polymorphisms (SNPs) in association with breast cancer risk at p < 0.05; for 16 of them, the allele associated with elevated BMI was associated with reduced breast cancer risk. CONCLUSIONS: BMI predicted by genome-wide association studies (GWAS)-identified variants is inversely associated with the risk of both pre- and postmenopausal breast cancer. The reduced risk of postmenopausal breast cancer associated with genetically predicted BMI observed in this study differs from the positive association reported from studies using measured adult BMI. Understanding the reasons for this discrepancy may reveal insights into the complex relationship of genetic determinants of body weight in the etiology of breast cancer.
EVALuna2:33324

Genetic Breast Cancer Susceptibility Variants and Prognosis in the Prospectively Randomized SUCCESS A Study - Hein, Alexander; Rack, B.; Li, L.; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, J. M.; Rübner, Matthias; Fridley, B. L.; Schneeweiss, A.; Tesch, H.; Lichtenegger, W.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Large-scale genotyping studies have identified over 70 single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. However, knowledge regarding genetic risk factors associated with the prognosis is limited. The aim of this study was therefore to investigate the prognostic effect of nine known breast cancer risk SNPs. BC patients (n = 1687) randomly sampled in an adjuvant, randomized phase III trial (SUCCESS A study) were genotyped for nine BC risk SNPs: rs17468277 (CASP8) , rs2981582 (FGFR2) , rs13281615(8q24), rs3817198 (LSP1) , rs889312 (MAP3K1) , rs3803662 (TOX3) , rs13387042(2q35), rs4973768 (SLC4A7) , rs6504950 (COX11) . Cox proportional hazards models were used to test the SNPs' association with overall survival (OS) and progression-free survival (PFS). Additional analyses were carried out for molecular subgroups. rs3817198 in LSP1 (lymphocyte-specific protein 1) was the only SNP that significantly influenced OS (p = 0.01) and PFS (p < 0.01) in the likelihood ratio test comparing the genetic survival model with the clinical survival model. In the molecular subgroups, triple-negative patients with two minor alleles in rs3817198 had a much better prognosis relative to OS (adjusted HR 0.03; 95% CI 0.002 - 0.279) and PFS (HR 0.09; 95% CI 0.02 - 0.36) than patients with the common alleles. The same effect on PFS was shown for patients with luminal A tumors (HR 0.19; 95% CI 0.05 - 0.84), whereas patients with luminal B tumors had a poorer PFS with two minor alleles (HR 2.13; 95% CI 1.02 - 4.40). The variant in rs3817198 has a prognostic effect particularly in the subgroup of patients with triple-negative BC, suggesting a possible link with immunomodulation and BC.
EVALuna2:9355

Genetic Data from Nearly 63,000 Women of European Descent Predicts DNA Methylation Biomarkers and Epithelial Ovarian Cancer Risk - Yang, Yaohua; Wu, Lang; Shu, Xiang; Lu, Yingchang; Shu, Xiao-Ou; Cai, Qiuyin; Beeghly-Fadiel, Alicia; Li, Bingshan; Ye, Fei; Berchuck, Andrew; Anton-Culver, Hoda; Banerjee, Susana; et al. (Cancer Research, 2019)
DNA methylation is instrumental for gene regulation. Global changes in the epigenetic landscape have been recognized as a hallmark of cancer. However, the role of DNA methylation in epithelial ovarian cancer (EOC) remains unclear. In this study, high-density genetic and DNA methylation data in white blood cells from the Framingham Heart Study (N = 1,595) were used to build genetic models to predict DNA methylation levels. These prediction models were then applied to the summary statistics of a genome-wide association study (GWAS) of ovarian cancer including 22,406 EOC cases and 40,941 controls to investigate genetically predicted DNA methylation levels in association with EOC risk. Among 62,938 CpG sites investigated, genetically predicted methylation levels at 89 CpG were significantly associated with EOC risk at a Bonferroni-corrected threshold of P < 7.94 x 10(-7). Of them, 87 were located at GWAS-identified EOC susceptibility regions and two resided in a genomic region not previously reported to be associated with EOC risk. Integrative analyses of genetic, methylation, and gene expression data identified consistent directions of associations across 12 CpG, five genes, and EOC risk, suggesting that methylation at these 12 CpG may influence EOC risk by regulating expression of these five genes, namely MAPT, HOXB3, ABHD8, ARHGAP27, and SKAP1. We identified novel DNA methylation markers associated with EOC risk and propose that methylation at multiple CpG may affect EOC risk via regulation of gene expression.
CRIS-Team WoS Importer:2019-02-21

Genetic modifiers of CHEK2*1100delC-associated breast cancer risk - Muranen, Taru A.; Greco, Dario; Blomqvist, Carl; Aittomaki, Kristiina; Khan, Sofia; Hogervorst, Frans; Verhoef, Senno; Pharoah, Paul D. P.; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Bojesen, Stig E.; et al. (Genetics in Medicine, 2017)
PURPOSE: CHEK2*1100delC is a founder variant in European populations that confers a two- to threefold increased risk of breast cancer (BC). Epidemiologic and family studies have suggested that the risk associated with CHEK2*1100delC is modified by other genetic factors in a multiplicative fashion. We have investigated this empirically using data from the Breast Cancer Association Consortium (BCAC). METHODS: Using genotype data from 39,139 (624 1100delC carriers) BC patients and 40,063 (224) healthy controls from 32 BCAC studies, we analyzed the combined risk effects of CHEK2*1100delC and 77 common variants in terms of a polygenic risk score (PRS) and pairwise interaction. RESULTS: The PRS conferred odds ratios (OR) of 1.59 (95% CI: 1.21-2.09) per standard deviation for BC for CHEK2*1100delC carriers and 1.58 (1.55-1.62) for noncarriers. No evidence of deviation from the multiplicative model was found. The OR for the highest quintile of the PRS was 2.03 (0.86-4.78) for CHEK2*1100delC carriers, placing them in the high risk category according to UK NICE guidelines. The OR for the lowest quintile was 0.52 (0.16-1.74), indicating a lifetime risk close to the population average. CONCLUSION: Our results confirm the multiplicative nature of risk effects conferred by CHEK2*1100delC and the common susceptibility variants. Furthermore, the PRS could identify carriers at a high lifetime risk for clinical actions.Genet Med advance online publication 06 October 2016.
EVALuna2:36144

Genetic overlap between endometriosis and endometrial cancer: evidence from cross-disease genetic correlation and GWAS meta-analyses - Painter, Jodie N.; O'Mara, Tracy A.; Morris, Andrew P.; Cheng, Timothy H. T.; Gorman, Maggie; Martin, Lynn; Hodson, Shirley; Jones, Angela; Martin, Nicholas G.; Gordon, Scott; Henders, Anjali K.; Attia, John; et al. (Cancer Medicine, 2018)
Epidemiological, biological, and molecular data suggest links between endometriosis and endometrial cancer, with recent epidemiological studies providing evidence for an association between a previous diagnosis of endometriosis and risk of endometrial cancer. We used genetic data as an alternative approach to investigate shared biological etiology of these two diseases. Genetic correlation analysis of summary level statistics from genomewide association studies (GWAS) using LD Score regression revealed moderate but significant genetic correlation (rg = 0.23, P = 9.3 × 10-3 ), and SNP effect concordance analysis provided evidence for significant SNP pleiotropy (P = 6.0 × 10-3 ) and concordance in effect direction (P = 2.0 × 10-3 ) between the two diseases. Cross-disease GWAS meta-analysis highlighted 13 distinct loci associated at P ≤ 10-5 with both endometriosis and endometrial cancer, with one locus (SNP rs2475335) located within PTPRD associated at a genomewide significant level (P = 4.9 × 10-8 , OR = 1.11, 95% CI = 1.07-1.15). PTPRD acts in the STAT3 pathway, which has been implicated in both endometriosis and endometrial cancer. This study demonstrates the value of cross-disease genetic analysis to support epidemiological observations and to identify biological pathways of relevance to multiple diseases.
EVALuna2:34631

Genetic Polymorphisms and Correlation with Treatment-Induced Cardiotoxicity and Prognosis in Patients with Breast Cancer - Peddi, Parvin F.; Fasching, Peter; Liu, Duan; Quinaux, Emmanuel; Robert, Nicholas J.; Valero, Vicente; Crown, John; Falkson, Carla; Brufsky, Adam; Cunningham, Julie M.; Weinshilboum, Richard M.; Pienkowski, Tadeusz; et al. (Clinical Cancer Research, 2022)
PURPOSE: Cardiac toxicity is a serious potential complication of HER2-directed therapies and anthracyclines. HER2 codon 655 and SLC28A3 gene polymorphisms have been reported to be associated with cardiac toxicity from anti-HER2 and anthracycline therapy, respectively. Association of the polymorphism at HER2 codon 655 with prognosis has also been reported. EXPERIMENTAL DESIGN: Whole blood samples from patients treated on a randomized adjuvant breast cancer trial (BCIRG-006) that compared chemotherapy with or without trastuzumab plus either anthracycline or nonanthracycline chemotherapy were tested for genetic polymorphisms in HER2 codon 655 and SLC28A3. Genotypes were correlated with cardiac function and disease-free survival (DFS) outcomes. RESULTS: Of 3,222 patients enrolled in BCIRG-006, 662 patient samples were successfully genotyped for the rs1136201 allele in HER2 (codon 655): 424 (64%) were AA, 30 (4.5%) were GG, and 208 (31%) were AG genotype. In addition, 665 patient samples were successfully genotyped for the rs7853758 allele in the SLC28A3 gene: 19 (3%) were AA, 475 (71%) were GG, and 171 (26%) were AG genotype. Follow-up time was 10 years. No correlation between DFS, cardiac event rate, or mean left ventricular ejection fraction (LVEF) and rs1136201 genotype was seen in the trastuzumab-treated or non-trastuzumab-treated patients. Moreover, mean LVEF and cardiac event rates were similar in all rs7853758 genotype groups treated with anthracycline-based therapy. CONCLUSIONS: In the largest study to date to evaluate whether two polymorphisms are associated with DFS and/or cardiac toxicity in HER2-positive breast cancer treated with trastuzumab and/or anthracyclines, we observed no correlation.
CRIS-Team Scopus Importer:2022-05-20

Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity

Genetic predisposition to ductal carcinoma in situ of the breast - Petridis, Christos; Brook, Mark N.; Shah, Vandna; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; Levi, Dina; Papouli, Efterpi; Orr, Nick; Cox, Angela; Cross, Simon S.; Dos-Santos-Silva, Isabel; et al. (Breast Cancer Research, 2016)
BACKGROUND: Ductal carcinoma in situ (DCIS) is a non-invasive form of breast cancer. It is often associated with invasive ductal carcinoma (IDC), and is considered to be a non-obligate precursor of IDC. It is not clear to what extent these two forms of cancer share low-risk susceptibility loci, or whether there are differences in the strength of association for shared loci. METHODS: To identify genetic polymorphisms that predispose to DCIS, we pooled data from 38 studies comprising 5,067 cases of DCIS, 24,584 cases of IDC and 37,467 controls, all genotyped using the iCOGS chip. RESULTS: Most (67 %) of the 76 known breast cancer predisposition loci showed an association with DCIS in the same direction as previously reported for invasive breast cancer. Case-only analysis showed no evidence for differences between associations for IDC and DCIS after considering multiple testing. Analysis by estrogen receptor (ER) status confirmed that loci associated with ER positive IDC were also associated with ER positive DCIS. Analysis of DCIS by grade suggested that two independent SNPs at 11q13.3 near CCND1 were specific to low/intermediate grade DCIS (rs75915166, rs554219). These associations with grade remained after adjusting for ER status and were also found in IDC. We found no novel DCIS-specific loci at a genome wide significance level of P < 5.0x10(-8). CONCLUSION: In conclusion, this study provides the strongest evidence to date of a shared genetic susceptibility for IDC and DCIS. Studies with larger numbers of DCIS are needed to determine if IDC or DCIS specific loci exist.
EVALuna2:33330

Genetic predisposition to in situ and invasive lobular carcinoma of the breast - Sawyer, Elinor; Roylance, Rebecca; Petridis, Christos; Brook, Mark N.; Nowinski, Salpie; Papouli, Efterpi; Fletcher, Olivia; Pinder, Sarah; Hanby, Andrew; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; et al. (PLoS Genetics, 2014)
Invasive lobular breast cancer (ILC) accounts for 10-15% of all invasive breast carcinomas. It is generally ER positive (ER+) and often associated with lobular carcinoma in situ (LCIS). Genome-wide association studies have identified more than 70 common polymorphisms that predispose to breast cancer, but these studies included predominantly ductal (IDC) carcinomas. To identify novel common polymorphisms that predispose to ILC and LCIS, we pooled data from 6,023 cases (5,622 ILC, 401 pure LCIS) and 34,271 controls from 36 studies genotyped using the iCOGS chip. Six novel SNPs most strongly associated with ILC/LCIS in the pooled analysis were genotyped in a further 516 lobular cases (482 ILC, 36 LCIS) and 1,467 controls. These analyses identified a lobular-specific SNP at 7q34 (rs11977670, OR (95%CI) for ILC = 1.13 (1.09-1.18), P = 6.0 × 10(-10); P-het for ILC vs IDC ER+ tumors = 1.8 × 10(-4)). Of the 75 known breast cancer polymorphisms that were genotyped, 56 were associated with ILC and 15 with LCIS at P<0.05. Two SNPs showed significantly stronger associations for ILC than LCIS (rs2981579/10q26/FGFR2, P-het = 0.04 and rs889312/5q11/MAP3K1, P-het = 0.03); and two showed stronger associations for LCIS than ILC (rs6678914/1q32/LGR6, P-het = 0.001 and rs1752911/6q14, P-het = 0.04). In addition, seven of the 75 known loci showed significant differences between ER+ tumors with IDC and ILC histology, three of these showing stronger associations for ILC (rs11249433/1p11, rs2981579/10q26/FGFR2 and rs10995190/10q21/ZNF365) and four associated only with IDC (5p12/rs10941679; rs2588809/14q24/RAD51L1, rs6472903/8q21 and rs1550623/2q31/CDCA7). In conclusion, we have identified one novel lobular breast cancer specific predisposition polymorphism at 7q34, and shown for the first time that common breast cancer polymorphisms predispose to LCIS. We have shown that many of the ER+ breast cancer predisposition loci also predispose to ILC, although there is some heterogeneity between ER+ lobular and ER+ IDC tumors. These data provide evidence for overlapping, but distinct etiological pathways within ER+ breast cancer between morphological subtypes.
EVALuna2:9234

Genetic risk factors for ovarian cancer and their role for endometriosis risk - Burghaus, Stefanie; Fasching, Peter; Haeberle, Lothar; Rübner, Matthias; Buechner, Kathrin; Blum, Simon; Engel, Anne; Ekici, Arif Bülent; Hartmann, Arndt; Hein, Alexander; Beckmann, Matthias; Renner, Stefan (Gynecologic Oncology, 2017)
Several genetic variants have been validated as risk factors for ovarian cancer. Endometriosis has also been described as a risk factor for ovarian cancer. Identifying genetic risk factors that are common to the two diseases might help improve our understanding of the molecular pathogenesis potentially linking the two conditions.In a hospital-based case-control analysis, 12 single nucleotide polymorphisms (SNPs), validated by the Ovarian Cancer Association Consortium (OCAC) and the Collaborative Oncological Gene-environment Study (COGS) project, were genotyped using TaqMan® OpenArray(TM) analysis. The cases consisted of patients with endometriosis, and the controls were healthy individuals without endometriosis. A total of 385 cases and 484 controls were analyzed. Odds ratios and P values were obtained using simple logistic regression models, as well as from multiple logistic regression models with adjustment for clinical predictors.rs11651755 in HNF1B was found to be associated with endometriosis in this case-control study. The OR was 0.66 (95% CI, 0.51 to 0.84) and the P value after correction for multiple testing was 0.01. None of the other genotypes was associated with a risk for endometriosis.As rs11651755 in HNF1B modified both the ovarian cancer risk and also the risk for endometriosis, HNF1B may be causally involved in the pathogenetic pathway leading from endometriosis to ovarian cancer.
EVALuna2:6871

Genetic Risk Score Mendelian Randomization Shows that Obesity Measured as Body Mass Index, but not Waist:Hip Ratio, Is Causal for Endometrial Cancer - Painter, Jodie N.; O'Mara, Tracy A.; Marquart, Louise; Webb, Penelope M.; Attia, John; Medland, Sarah E.; Cheng, Timothy; Dennis, Joe; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ahmed, Shahana; et al. (Cancer Epidemiology Biomarkers & Prevention, 2016)
The strongest known risk factor for endometrial cancer is obesity. To determine whether SNPs associated with increased body mass index (BMI) or waist-hip ratio (WHR) are associated with endometrial cancer risk, independent of measured BMI, we investigated relationships between 77 BMI and 47 WHR SNPs and endometrial cancer in 6,609 cases and 37,926 country-matched controls.Logistic regression analysis and fixed effects meta-analysis were used to test for associations between endometrial cancer risk and (i) individual BMI or WHR SNPs, (ii) a combined weighted genetic risk score (wGRS) for BMI or WHR. Causality of BMI for endometrial cancer was assessed using Mendelian randomization, with BMIwGRS as instrumental variable.The BMIwGRS was significantly associated with endometrial cancer risk (P = 3.4 × 10(-17)). Scaling the effect of the BMIwGRS on endometrial cancer risk by its effect on BMI, the endometrial cancer OR per 5 kg/m(2) of genetically predicted BMI was 2.06 [95% confidence interval (CI), 1.89-2.21], larger than the observed effect of BMI on endometrial cancer risk (OR = 1.55; 95% CI, 1.44-1.68, per 5 kg/m(2)). The association attenuated but remained significant after adjusting for BMI (OR = 1.22; 95% CI, 1.10-1.39; P = 5.3 × 10(-4)). There was evidence of directional pleiotropy (P = 1.5 × 10(-4)). BMI SNP rs2075650 was associated with endometrial cancer at study-wide significance (P < 4.0 × 10(-4)), independent of BMI. Endometrial cancer was not significantly associated with individual WHR SNPs or the WHRwGRS.BMI, but not WHR, is causally associated with endometrial cancer risk, with evidence that some BMI-associated SNPs alter endometrial cancer risk via mechanisms other than measurable BMI.The causal association between BMI SNPs and endometrial cancer has possible implications for endometrial cancer risk modeling. Cancer Epidemiol Biomarkers Prev; 25(11); 1503-10. ©2016 AACR.
EVALuna2:9342

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the genes of the stress hormone signalling pathway and depressive symptoms during and after pregnancy - Schneider, Michael; Engel, Anne; Fasching, Peter; Haeberle, Lothar; Binder, Elisabeth B.; Voigt, Franziska; Grimm, Jennifer; Faschingbauer, Florian; Eichler, Anna; Dammer, Ulf; Rebhan, Dirk; Amann, Manuela; et al. (BioMed Research International, 2014)
The aim of this study was to investigate whether single nucleotide polymorphisms (SNPs) in genes of the stress hormone signaling pathway, specifically FKBP5, NR3C1, and CRHR1, are associated with depressive symptoms during and after pregnancy.The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health including the assessment of depressiveness. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of the pregnancy, visit 2 was shortly after birth, and visit 3 was 6-8 months after birth. Germline DNA was collected from 361 pregnant women. Nine SNPs in the above mentioned genes were genotyped. After construction of haplotypes for each gene, a multifactorial linear mixed model was performed to analyse the depression values over time.EPDS values were within expected ranges and comparable to previously published studies. Neither did the depression scores differ for comparisons among haplotypes at fixed time points nor did the change over time differ among haplotypes for the examined genes. No haplotype showed significant associations with depressive symptoms severity during pregnancy or the postpartum period.The analysed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show an association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
EVALuna2:17356

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variants in VEGF pathway genes in neoadjuvant breast cancer patients receiving bevacizumab: Results from the randomized phase III GeparQuinto study - Hein, Alexander; Lambrechts, Diether; Von Minckwitz, Gunter; Haeberle, Lothar; Eidtmann, Holger; Tesch, Hans; Untch, Michael; Hilfrich, Joern; Schem, Christian; Rezai, Mahdi; Gerber, Bernd; Costa, Serban Dan; et al. (International Journal of Cancer, 2015)
Studies assessing the effect of bevacizumab (BEV) on breast cancer (BC) outcome have shown different effects on progression-free and overall survival, suggesting that a subgroup of patients may benefit from this treatment. Unfortunately, no biomarkers exist to identify these patients. Here, we investigate whether single nucleotide polymorphisms (SNPs) in VEGF pathway genes correlate with pathological complete response (pCR) in the neoadjuvant GeparQuinto trial. HER2-negative patients were randomized into treatment arms receiving either BEV combined with standard chemotherapy or chemotherapy alone. In a pre-planned biomarker study, DNA was collected from 729 and 724 patients, respectively from both treatment arms, and genotyped for 125 SNPs. Logistic regression assessed interaction between individual SNPs and both treatment arms to predict pCR. Five SNPs may be associated with a better response to BEV, but none of them remained significant after correction for multiple testing. The two SNPs most strongly associated, rs833058 and rs699947, were located upstream of the VEGF-A promoter. Odds ratios for the homozygous common, heterozygous and homozygous rare rs833058 genotypes were 2.36 (95% CI, 1.49-3.75), 1.20 (95% CI, 0.88-1.64) and 0.61 (95% CI, 0.34-1.12). Notably, some SNPs in VEGF-A exhibited a more pronounced effect in the triple-negative subgroup. Several SNPs in VEGF-A may be associated with improved pCR when receiving BEV in the neoadjuvant setting. Although none of the observed effects survived correction for multiple testing, our observations are consistent with previous studies on BEV efficacy in BC. Further research is warranted to clarify the predictive value of these markers.
EVALuna2:9285

Genetic variation at CYP3A is associated with age at menarche and breast cancer risk: a case-control study - Johnson, Nichola; Dudbridge, Frank; Orr, Nick; Gibson, Lorna; Jones, Michael E.; Schoemaker, Minouk J.; Folkerd, Elizabeth J.; Haynes, Ben P.; Hopper, John L.; Southey, Melissa C.; Dite, Gillian S.; Apicella, Carmel; et al. (Breast Cancer Research, 2014)
We have previously shown that a tag single nucleotide polymorphism (rs10235235), which maps to the CYP3A locus (7q22.1), was associated with a reduction in premenopausal urinary estrone glucuronide levels and a modest reduction in risk of breast cancer in women age <=50 years.We further investigated the association of rs10235235 with breast cancer risk in a large case control study of 47,346 cases and 47,570 controls from 52 studies participating in the Breast Cancer Association Consortium. Genotyping of rs10235235 was conducted using a custom Illumina Infinium array. Stratified analyses were conducted to determine whether this association was modified by age at diagnosis, ethnicity, age at menarche or tumor characteristics.We confirmed the association of rs10235235 with breast cancer risk for women of European ancestry but found no evidence that this association differed with age at diagnosis. Heterozygote and homozygote odds ratios (ORs) were OR = 0.98 (95% CI 0.94, 1.01; P = 0.2) and OR = 0.80 (95% CI 0.69, 0.93; P = 0.004), respectively (P(trend) = 0.02). There was no evidence of effect modification by tumor characteristics. rs10235235 was, however, associated with age at menarche in controls (P(trend) = 0.005) but not cases (P(trend) = 0.97). Consequently the association between rs10235235 and breast cancer risk differed according to age at menarche (P(het) = 0.02); the rare allele of rs10235235 was associated with a reduction in breast cancer risk for women who had their menarche age >=15 years (OR(het) = 0.84, 95% CI 0.75, 0.94; OR(hom) = 0.81, 95% CI 0.51, 1.30; P(trend) = 0.002) but not for those who had their menarche age <=11 years (OR(het) = 1.06, 95% CI 0.95, 1.19, OR(hom) = 1.07, 95% CI 0.67, 1.72; P(trend) = 0.29).To our knowledge rs10235235 is the first single nucleotide polymorphism to be associated with both breast cancer risk and age at menarche consistent with the well-documented association between later age at menarche and a reduction in breast cancer risk. These associations are likely mediated via an effect on circulating hormone levels.
EVALuna2:9240

Genetic variation in mitotic regulatory pathway genes is associated with breast tumor grade - Purrington, Kristen S.; Slettedahl, Seth; Bolla, Manjeet K.; Michailidou, Kyriaki; Czene, Kamila; Nevanlinna, Heli; Bojesen, Stig E.; Andrulis, Irene L.; Cox, Angela; Hall, Per; Carpenter, Jane; Yannoukakos, Drakoulis; et al. (Human Molecular Genetics, 2014)
Mitotic index is an important component of histologic grade and has an etiologic role in breast tumorigenesis. Several small candidate gene studies have reported associations between variation in mitotic genes and breast cancer risk. We measured associations between 2156 single nucleotide polymorphisms (SNPs) from 194 mitotic genes and breast cancer risk, overall and by histologic grade, in the Breast Cancer Association Consortium (BCAC) iCOGS study (n = 39 067 cases; n = 42 106 controls). SNPs in TACC2 [rs17550038: odds ratio (OR) = 1.24, 95% confidence interval (CI) 1.16-1.33, P = 4.2 × 10(-10)) and EIF3H (rs799890: OR = 1.07, 95% CI 1.04-1.11, P = 8.7 × 10(-6)) were significantly associated with risk of low-grade breast cancer. The TACC2 signal was retained (rs17550038: OR = 1.15, 95% CI 1.07-1.23, P = 7.9 × 10(-5)) after adjustment for breast cancer risk SNPs in the nearby FGFR2 gene, suggesting that TACC2 is a novel, independent genome-wide significant genetic risk locus for low-grade breast cancer. While no SNPs were individually associated with high-grade disease, a pathway-level gene set analysis showed that variation across the 194 mitotic genes was associated with high-grade breast cancer risk (P = 2.1 × 10(-3)). These observations will provide insight into the contribution of mitotic defects to histological grade and the etiology of breast cancer.
EVALuna2:6629

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten B.; Behrens, Sabine; Goode, Ellen L.; Bolla, Manjeet K.; Dennis, Joe; Dunning, Alison M.; Easton, Douglas F.; Wang, Qin; Benitez, Javier; Hopper, John L.; et al. (Human genetics, 2016)
Immunosuppression plays a pivotal role in assisting tumors to evade immune destruction and promoting tumor development. We hypothesized that genetic variation in the immunosuppression pathway genes may be implicated in breast cancer tumorigenesis. We included 42,510 female breast cancer cases and 40,577 controls of European ancestry from 37 studies in the Breast Cancer Association Consortium (2015) with available genotype data for 3595 single nucleotide polymorphisms (SNPs) in 133 candidate genes. Associations between genotyped SNPs and overall breast cancer risk, and secondarily according to estrogen receptor (ER) status, were assessed using multiple logistic regression models. Gene-level associations were assessed based on principal component analysis. Gene expression analyses were conducted using RNA sequencing level 3 data from The Cancer Genome Atlas for 989 breast tumor samples and 113 matched normal tissue samples. SNP rs1905339 (A>G) in the STAT3 region was associated with an increased breast cancer risk (per allele odds ratio 1.05, 95 % confidence interval 1.03-1.08; p value = 1.4 × 10(-6)). The association did not differ significantly by ER status. On the gene level, in addition to TGFBR2 and CCND1, IL5 and GM-CSF showed the strongest associations with overall breast cancer risk (p value = 1.0 × 10(-3) and 7.0 × 10(-3), respectively). Furthermore, STAT3 and IL5 but not GM-CSF were differentially expressed between breast tumor tissue and normal tissue (p value = 2.5 × 10(-3), 4.5 × 10(-4) and 0.63, respectively). Our data provide evidence that the immunosuppression pathway genes STAT3, IL5, and GM-CSF may be novel susceptibility loci for breast cancer in women of European ancestry.
EVALuna2:33106

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Genome-wide Analysis Identifies Novel Loci Associated with Ovarian Cancer Outcomes: Findings from the Ovarian Cancer Association Consortium - Johnatty, Sharon E.; Tyrer, Jonathan P.; Kar, Siddhartha; Beesley, Jonathan; Lu, Yi; Gao, Bo; Fasching, Peter; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; et al. (Clinical Cancer Research, 2015)
Chemotherapy resistance remains a major challenge in the treatment of ovarian cancer. We hypothesize that germline polymorphisms might be associated with clinical outcome.We analyzed approximately 2.8 million genotyped and imputed SNPs from the iCOGS experiment for progression-free survival (PFS) and overall survival (OS) in 2,901 European epithelial ovarian cancer (EOC) patients who underwent first-line treatment of cytoreductive surgery and chemotherapy regardless of regimen, and in a subset of 1,098 patients treated with >=4 cycles of paclitaxel and carboplatin at standard doses. We evaluated the top SNPs in 4,434 EOC patients, including patients from The Cancer Genome Atlas. In addition, we conducted pathway analysis of all intragenic SNPs and tested their association with PFS and OS using gene set enrichment analysis.Five SNPs were significantly associated (P <= 1.0 × 10(-5)) with poorer outcomes in at least one of the four analyses, three of which, rs4910232 (11p15.3), rs2549714 (16q23), and rs6674079 (1q22), were located in long noncoding RNAs (lncRNAs) RP11-179A10.1, RP11-314O13.1, and RP11-284F21.8, respectively (P <= 7.1 × 10(-6)). ENCODE ChIP-seq data at 1q22 for normal ovary show evidence of histone modification around RP11-284F21.8, and rs6674079 is perfectly correlated with another SNP within the super-enhancer MEF2D, expression levels of which were reportedly associated with prognosis in another solid tumor. YAP1- and WWTR1 (TAZ)-stimulated gene expression and high-density lipoprotein (HDL)-mediated lipid transport pathways were associated with PFS and OS, respectively, in the cohort who had standard chemotherapy (pGSEA <=6 × 10(-3)).We have identified SNPs in three lncRNAs that might be important targets for novel EOC therapies. Clin Cancer Res; 21(23); 5264-76. ©2015 AACR.
EVALuna2:9298

Genome-wide and transcriptome-wide association studies of mammographic density phenotypes reveal novel loci - Chen, Hongjie; Fan, Shaoqi; Stone, Jennifer; Thompson, Deborah J.; Douglas, Julie; Li, Shuai; Scott, Christopher; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Li, Christopher; et al. (Breast Cancer Research, 2022)
BACKGROUND: Mammographic density (MD) phenotypes, including percent density (PMD), area of dense tissue (DA), and area of non-dense tissue (NDA), are associated with breast cancer risk. Twin studies suggest that MD phenotypes are highly heritable. However, only a small proportion of their variance is explained by identified genetic variants. METHODS: We conducted a genome-wide association study, as well as a transcriptome-wide association study (TWAS), of age- and BMI-adjusted DA, NDA, and PMD in up to 27,900 European-ancestry women from the MODE/BCAC consortia. RESULTS: We identified 28 genome-wide significant loci for MD phenotypes, including nine novel signals (5q11.2, 5q14.1, 5q31.1, 5q33.3, 5q35.1, 7p11.2, 8q24.13, 12p11.2, 16q12.2). Further, 45% of all known breast cancer SNPs were associated with at least one MD phenotype at p < 0.05. TWAS further identified two novel genes (SHOX2 and CRISPLD2) whose genetically predicted expression was significantly associated with MD phenotypes. CONCLUSIONS: Our findings provided novel insight into the genetic background of MD phenotypes, and further demonstrated their shared genetic basis with breast cancer.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Breast cancer; Genome-wide association study (GWAS); Mammographic density; Transcriptome-wide association study (TWAS)

Genome-Wide Association Analyses of HPV16 and HPV18 Seropositivity Identify Susceptibility Loci for Cervical Cancer - Beckhaus, Theresa; Kachuri, Linda; Nakase, Taishi; Schürmann, Peter; Eisenblätter, Rieke; Geerts, Maya; Böhmer, Gerd; Strauß, Hans Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Fasching, Peter; et al. (Journal of Medical Virology, 2025)
Infection by high-risk human papillomavirus is known to exacerbate cervical cancer development. The host immune response is crucial in disease regression. Large-scale genetic association studies for cervical cancer have identified few susceptibility variants, mainly at the human leukocyte antigen locus on chromosome 6. We hypothesized that the host immune response modifies cervical cancer risk and performed three genome-wide association analyses for HPV16, HPV18 and HPV16/18 seropositivity in 7814, 7924, and 7924 samples from the UK Biobank, followed by validation genotyping in the German Cervigen case-control series of cervical cancer and dysplasia. In GWAS analyses, we identified two loci associated with HPV16 seropositivity (6p21.32 and 15q26.2), two loci associated with HPV18 seropositivity (5q31.2 and 14q24.3), and one locus for HPV16 and/or HPV18 seropositivity (at 6p21.32). MAGMA gene-based analysis identified HLA-DQA1 and HLA-DQB1 as genome-wide significant (GWS) genes. In validation genotyping, the genome-wide significant lead variant at 6p21.32, rs9272293 associated with overall cervical disease (OR = 0.86, p = 0.004, 95% CI = 0.78–0.95, n = 3710) and HPV16 positive invasive cancer (OR = 0.73, p = 0.005, 95% CI = 0.59–0.91, n = 1431). This variant was found to be a robust eQTL for HLA-DRB1, HLA-DQB1-AS1, C4B, HLA-DRB5, HLA-DRB6, HLA-DQB1, and HLA-DPB1 in a series of cervical epithelial tissue samples. We additionally genotyped twenty-four HPV seropositivity variants below the GWS threshold out of which eleven variants were found to be associated with cervical disease in our cohort, suggesting that further seropositivity variants may determine cervical disease outcome. Our study identifies novel genomic risk loci that associate with HPV type-specific cervical cancer and dysplasia risk and provides evidence for candidate genes at one of the risk loci.
CRIS-Team Scopus Importer:2025-02-14
Keywords: cervical carcinoma; eQTL; human papillomavirus; infection; SNP

Genome-wide association analyses of ovarian cancer patients undergoing primary debulking surgery identify candidate genes for residual disease - Ramachandran, Dhanya; Tyrer, Jonathan P.; Kommoss, Stefan; DeFazio, Anna; Riggan, Marjorie J.; Webb, Penelope M.; Fasching, Peter; Lambrechts, Diether; García, María J.; Rodríguez-Antona, Cristina; Goodman, Marc T.; Modugno, Francesmary; et al. (npj Genomic Medicine, 2024)
Survival from ovarian cancer depends on the resection status after primary surgery. We performed genome-wide association analyses for resection status of 7705 ovarian cancer patients, including 4954 with high-grade serous carcinoma (HGSOC), to identify variants associated with residual disease. The most significant association with resection status was observed for rs72845444, upstream of MGMT, in HGSOC (p = 3.9 × 10−8). In gene-based analyses, PPP2R5C was the most strongly associated gene in HGSOC after stage adjustment. In an independent set of 378 ovarian tumours from the AGO-OVAR 11 study, variants near MGMT and PPP2R5C correlated with methylation and transcript levels, and PPP2R5C mRNA levels predicted progression-free survival in patients with residual disease. MGMT encodes a DNA repair enzyme, and PPP2R5C encodes the B56γ subunit of the PP2A tumour suppressor. Our results link heritable variation at these two loci with resection status in HGSOC.
CRIS-Team Scopus Importer:2024-06-14

Genome-wide association analysis identifies three new breast cancer susceptibility loci - Ghoussaini, Maya; Fletcher, Olivia; Michailidou, Kyriaki; Turnbull, Clare; Schmidt, Marjanka K.; Dicks, Ed; Dennis, Joe; Wang, Qin; Humphreys, Manjeet K.; Luccarini, Craig; Baynes, Caroline; Conroy, Don; et al. (Nature Genetics, 2012)
Breast cancer is the most common cancer among women. To date, 22 common breast cancer susceptibility loci have been identified accounting for 8% of the heritability of the disease. We attempted to replicate 72 promising associations from two independent genome-wide association studies (GWAS) in 70,000 cases and 68,000 controls from 41 case-control studies and 9 breast cancer GWAS. We identified three new breast cancer risk loci at 12p11 (rs10771399; P = 2.7 × 10(-35)), 12q24 (rs1292011; P = 4.3 × 10(-19)) and 21q21 (rs2823093; P = 1.1 × 10(-12)). rs10771399 was associated with similar relative risks for both estrogen receptor (ER)-negative and ER-positive breast cancer, whereas the other two loci were associated only with ER-positive disease. Two of the loci lie in regions that contain strong plausible candidate genes: PTHLH (12p11) has a crucial role in mammary gland development and the establishment of bone metastasis in breast cancer, and NRIP1 (21q21) encodes an ER cofactor and has a role in the regulation of breast cancer cell growth.
EVALuna2:9145

Genome-wide association analysis of more than 120,000 individuals identifies 15 new susceptibility loci for breast cancer - Michailidou, Kyriaki; Beesley, Jonathan; Lindstrom, Sara; Canisius, Sander; Dennis, Joe; Lush, Michael J.; Maranian, Mel J.; Bolla, Manjeet K.; Wang, Qin; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) and large-scale replication studies have identified common variants in 79 loci associated with breast cancer, explaining 14% of the familial risk of the disease. To identify new susceptibility loci, we performed a meta-analysis of 11 GWAS, comprising 15,748 breast cancer cases and 18,084 controls together with 46,785 cases and 42,892 controls from 41 studies genotyped on a 211,155-marker custom array (iCOGS). Analyses were restricted to women of European ancestry. We generated genotypes for more than 11 million SNPs by imputation using the 1000 Genomes Project reference panel, and we identified 15 new loci associated with breast cancer at P < 5 × 10(-8). Combining association analysis with ChIP-seq chromatin binding data in mammary cell lines and ChIA-PET chromatin interaction data from ENCODE, we identified likely target genes in two regions: SETBP1 at 18q12.3 and RNF115 and PDZK1 at 1q21.1. One association appears to be driven by an amino acid substitution encoded in EXO
EVALuna2:17570

Genome-wide association and transcriptome studies identify target genes and risk loci for breast cancer - Ferreira, Manuel A.; Gamazon, Eric R.; Al-Ejeh, Fares; Aittomaki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Arason, Adalgeir; Arndt, Volker; Aronson, Kristan J.; Arun, Banu K.; Asseryanis, Ella; Azzollini, Jacopo; et al. (Nature Communications, 2019)
Genome-wide association studies (GWAS) have identified more than 170 breast cancer susceptibility loci. Here we hypothesize that some risk-associated variants might act in non-breast tissues, specifically adipose tissue and immune cells from blood and spleen. Using expression quantitative trait loci (eQTL) reported in these tissues, we identify 26 previously unreported, likely target genes of overall breast cancer risk variants, and 17 for estrogen receptor (ER)-negative breast cancer, several with a known immune function. We determine the directional effect of gene expression on disease risk measured based on single and multiple eQTL. In addition, using a gene-based test of association that considers eQTL from multiple tissues, we identify seven (and four) regions with variants associated with overall (and ER-negative) breast cancer risk, which were not reported in previous GWAS. Further investigation of the function of the implicated genes in breast and immune cells may provide insights into the etiology of breast cancer.
CRIS-Team WoS Importer:2019-04-30

Genome-wide association study and functional follow-up identify 14q12 as a candidate risk locus for cervical cancer - Ramachandran, Dhanya; Dennis, Joe; Fachal, Laura; Schurmann, Peter; Bousset, Kristine; Huelse, Fabienne; Mao, Qianqian; Wang, Yingying; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; Hirchenhain, Christine; et al. (Human Molecular Genetics, 2022)
Cervical cancer is among the leading causes of cancer-related death in females worldwide. Infection by human papillomavirus (HPV) is an established risk factor for cancer development. However, genetic factors contributing to disease risk remain largely unknown. We report on a genome-wide association study (GWAS) on 375 German cervical cancer patients and 866 healthy controls, followed by a replication study comprising 658 patients with invasive cervical cancer, 1361 with cervical dysplasia and 841 healthy controls. Functional validation was performed for the top GWAS variant on chromosome 14q12 (rs225902, close to PRKD1). After bioinformatic annotation and in silico predictions, we performed transcript analysis in a cervical tissue series of 317 samples and demonstrate rs225902 as an expression quantitative trait locus (eQTL) for FOXG1 and two tightly co-regulated long non-coding RNAs at this genomic region, CTD-2251F13 (lnc-PRKD1-1) and CTD-2503I6 (lnc-FOXG1-6). We also show allele-specific effects of the 14q12 variants via luciferase assays. We propose a combined effect of genotype, HPV status and gene expression at this locus on cervical cancer progression. Taken together, this work uncovers a potential candidate locus with regulatory functions and contributes to the understanding of genetic susceptibility to cervical cancer.
CRIS-Team WoS Importer:2022-05-06

Genome-wide association study identifies multiple loci associated with both mammographic density and breast cancer risk - Lindstroem, Sara; Thompson, Deborah J.; Paterson, Andrew D.; Li, Jingmei; Gierach, Gretchen L.; Scott, Christopher; Stone, Jennifer; Douglas, Julie A.; Dos-Santos-Silva, Isabel; Fernandez-Navarro, Pablo; Verghase, Jajini; Smith, Paula; et al. (Nature Communications, 2014)
Mammographic density reflects the amount of stromal and epithelial tissues in relation to adipose tissue in the breast and is a strong risk factor for breast cancer. Here we report the results from meta-analysis of genome-wide association studies (GWAS) of three mammographic density phenotypes: dense area, non-dense area and percent density in up to 7,916 women in stage 1 and an additional 10,379 women in stage 2. We identify genome-wide significant (P<5 × 10(-8)) loci for dense area (AREG, ESR1, ZNF365, LSP1/TNNT3, IGF1, TMEM184B and SGSM3/MKL1), non-dense area (8p11.23) and percent density (PRDM6, 8p11.23 and TMEM184B). Four of these regions are known breast cancer susceptibility loci, and four additional regions were found to be associated with breast cancer (P<0.05) in a large meta-analysis. These results provide further evidence of a shared genetic basis between mammographic density and breast cancer and illustrate the power of studying intermediate quantitative phenotypes to identify putative disease-susceptibility loci.
EVALuna2:17508

Genome-wide association study of germline variants and breast cancer-specific mortality - Escala-Garcia, Maria; Guo, Qi; Doerk, Thilo; Canisius, Sander; Keeman, Renske; Dennis, Joe; Beesley, Jonathan; Lecarpentier, Julie; Bolla, Manjeet K.; Wang, Qin; Abraham, Jean; Andrulis, Irene L.; et al. (British Journal of Cancer, 2019)
BACKGROUND: We examined the associations between germline variants and breast cancer mortality using a large meta-analysis of women of European ancestry.
CRIS-Team WoS Importer:2019-03-29

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Earp, Madalene A.; Kelemen, Linda E.; Magliocco, Anthony M.; Swenerton, Kenneth D.; Chenevix-Trench, Georgia; Lu, Yi; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Lambrechts, Diether; Despierre, Evelyn; et al. (Human genetics, 2014)
Epithelial ovarian cancer (EOC) is a heterogeneous cancer with both genetic and environmental risk factors. Variants influencing the risk of developing the less-common EOC subtypes have not been fully investigated. We performed a genome-wide association study (GWAS) of EOC according to subtype by pooling genomic DNA from 545 cases and 398 controls of European descent, and testing for allelic associations. We evaluated for replication 188 variants from the GWAS [56 variants for mucinous, 55 for endometrioid and clear cell, 53 for low-malignant potential (LMP) serous, and 24 for invasive serous EOC], selected using pre-defined criteria. Genotypes from 13,188 cases and 23,164 controls of European descent were used to perform unconditional logistic regression under the log-additive genetic model; odds ratios (OR) and 95 % confidence intervals are reported. Nine variants tagging six loci were associated with subtype-specific EOC risk at P < 0.05, and had an OR that agreed in direction of effect with the GWAS results. Several of these variants are in or near genes with a biological rationale for conferring EOC risk, including ZFP36L1 and RAD51B for mucinous EOC (rs17106154, OR = 1.17, P = 0.029, n = 1,483 cases), GRB10 for endometrioid and clear cell EOC (rs2190503, P = 0.014, n = 2,903 cases), and C22orf26/BPIL2 for LMP serous EOC (rs9609538, OR = 0.86, P = 0.0043, n = 892 cases). In analyses that included the 75 GWAS samples, the association between rs9609538 (OR = 0.84, P = 0.0007) and LMP serous EOC risk remained statistically significant at P < 0.0012 adjusted for multiple testing. Replication in additional samples will be important to verify these results for the less-common EOC subtypes.
EVALuna2:9208

Genome-Wide DNA Methylation Patterns in Children Exposed to Nonpharmacologically Treated Prenatal Depressive Symptoms: Results From 2 Independent Cohorts - Stonawski, Valeska; Roetner, Jakob; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna; Heinrich, Hartmut; Frey, Stefan (Epigenetics Insights, 2020)
Background: Maternal depressive symptoms are a common phenomenon during pregnancy and are related to negative outcomes for child development and health. Modifications in child DNA methylation are discussed as an underlying mechanism for the association between prenatal depressive symptoms and alterations in child outcomes. However, formerly reported genome-wide associations have yet to be replicated. Methods: In an epigenome-wide association study (EWAS), alterations of DNA methylation related to maternal prenatal depressive symptoms were investigated in buccal cell samples from 174 children (n = 52 exposed to prenatal depressive symptoms; 6-9 years old) of the German longitudinal study FRAMES-FRANCES. Whole blood samples from the independent, age-comparable ARIES subsample of the ARIES/ALSPAC study (n = 641; n = 159 exposed to prenatal depressive symptoms; 7-8 years old) were examined as a confirmation sample. Depressive symptoms were assessed with the Edinburgh Postnatal Depression Scale. DNA methylation was analyzed with the Infinium Human Methylation 450k BeadChip. Modifications in single CpGs, regions, and biological pathways were investigated. Results were adjusted for age and birth outcomes as well as postnatal and current maternal depressive symptoms. Analyses were performed for the whole sample as well as separated for sex. Results: The EWAS yielded no differentially methylated CpG or region as well as no accordance between samples withstanding correction for multiple testing. In pathway analyses, no overlapping functional domain was found to be enriched for either sample. A comparison of current and former findings suggests some overlapping methylation modifications from infancy to childhood. Results suggest that there might be sex-specific differential methylation, which should be further investigated in additional studies. Conclusions: The current, mainly nonsignificant, results challenge the assumption of consistent modifications of DNA methylation in children exposed to prenatal depressive symptoms. Despite the relatively small sample size used in this study, this lack of significant results may reflect diverse issues of environmental epigenetic studies, which need to be addressed in future research.
CRIS-Team Scopus Importer:2020-06-26
Keywords: ALSPAC; ARIES; DNA methylation; epigenetics; FRANCES; Pregnancy; prenatal depression

Genome-Wide Meta-Analyses of Breast, Ovarian, and Prostate Cancer Association Studies Identify Multiple New Susceptibility Loci Shared by at Least Two Cancer Types - Kar, Siddhartha P.; Beesley, Jonathan; Al Olama, Ali Amin; Michailidou, Kyriaki; Tyrer, Jonathan; Kote-Jarai, Zsofi A.; Lawrenson, Kate; Lindstrom, Sara; Ramus, Susan J.; Thompson, Deborah J.; Kibel, Adam S.; Dansonka-Mieszkowska, Agnieszka; et al. (Cancer Discovery, 2016)
Breast, ovarian, and prostate cancers are hormone-related and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association (GWA) studies. Meta-analyses combining the largest GWA meta-analysis data sets for these cancers totaling 112,349 cases and 116,421 controls of European ancestry, all together and in pairs, identified at P < 10(-8) seven new cross-cancer loci: three associated with susceptibility to all three cancers (rs17041869/2q13/BCL2L11; rs7937840/11q12/INCENP; rs1469713/19p13/GATAD2A), two breast and ovarian cancer risk loci (rs200182588/9q31/SMC2; rs8037137/15q26/RCCD1), and two breast and prostate cancer risk loci (rs5013329/1p34/NSUN4; rs9375701/6q23/L3MBTL3). Index variants in five additional regions previously associated with only one cancer also showed clear association with a second cancer type. Cell-type-specific expression quantitative trait locus and enhancer-gene interaction annotations suggested target genes with potential cross-cancer roles at the new loci. Pathway analysis revealed significant enrichment of death receptor signaling genes near loci with P < 10(-5) in the three-cancer meta-analysis.We demonstrate that combining large-scale GWA meta-analysis findings across cancer types can identify completely new risk loci common to breast, ovarian, and prostate cancers. We show that the identification of such cross-cancer risk loci has the potential to shed new light on the shared biology underlying these hormone-related cancers. Cancer Discov; 6(9); 1052-67. ©2016 AACR.This article is highlighted in the In This Issue feature, p. 932.
EVALuna2:9322

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk - Day, Felix R.; Thompson, Deborah J.; Helgason, Hannes; Chasman, Daniel I.; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S.; Whalen, Sean; Sarkar, Abhishek K.; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nature Genetics, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10-8) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
EVALuna2:36141

Genomic analysis of advanced breast cancer tumors from talazoparib-treated gBRCA1/2mut carriers in the ABRAZO study - Turner, Nicholas C.; Laird, A. Douglas; Telli, Melinda L.; Rugo, Hope S.; Mailliez, Audrey; Ettl, Johannes; Grischke, Eva Maria; Mina, Lida A.; Balmaña, Judith; Fasching, Peter; Hurvitz, Sara A.; Hopkins, Julia F.; et al. (npj Breast Cancer, 2023)
These analyses explore the impact of homologous recombination repair gene mutations, including BRCA1/2 mutations and homologous recombination deficiency (HRD), on the efficacy of the poly(ADP-ribose) polymerase (PARP) inhibitor talazoparib in the open-label, two-cohort, Phase 2 ABRAZO trial in germline BRCA1/2-mutation carriers. In the evaluable intent-to-treat population (N = 60), 58 (97%) patients harbor ≥1 BRCA1/2 mutation(s) in tumor sequencing, with 95% (53/56) concordance between germline and tumor mutations, and 85% (40/47) of evaluable patients have BRCA locus loss of heterozygosity indicating HRD. The most prevalent non-BRCA tumor mutations are TP53 in patients with BRCA1 mutations and PIK3CA in patients with BRCA2 mutations. BRCA1- or BRCA2-mutated tumors show comparable clinical benefit within cohorts. While low patient numbers preclude correlations between HRD and efficacy, germline BRCA1/2 mutation detection from tumor-only sequencing shows high sensitivity and non-BRCA genetic/genomic events do not appear to influence talazoparib sensitivity in the ABRAZO trial. ClinicalTrials.gov identifier: NCT02034916.
CRIS-Team Scopus Importer:2023-10-20

GeparPiPPa- A randomized, open-label, phase II trial comparing neoadjuvant trastuzumab, pertuzumab and endocrine therapy +/- the PI3K inhibitor inavolisib in patients (pts) with HER2+/HR+, PIK3CA mutant early breast cancer (BC) - Loibl, Sibylle; Reinisch, Mattea; Denkert, Carsten; Schneeweiss, Andreas; Seiler, Sabine; Fasching, Peter; Hanusch, Claus; Link, Theresa; Bjelic-Radisic, Vesna; Huober, Jens; Untch, Michael; Jackisch, Christian; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

GeparX: Denosumab (Dmab) as add-on to different regimen of nab-paclitaxel (nP)-anthracycline based neoadjuvant chemotherapy (NACT) in early breast cancer (BC): Subgroup analyses by RANK expression and HR status - Link, T.; Blohmer, J-U.; Just, M.; Untch, M.; Stoetzer, O.; Fasching, Peter; Schneeweiss, A.; Wimberger, P.; Seiler, S.; Huober, J.; Schmitt, W. D.; Jackisch, C.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Germline BRCA1/2 mutations and severe haematological toxicities in patients with breast cancer treated with neoadjuvant chemotherapy - Furlanetto, Jenny; Möbus, Volker; Schneeweiss, Andreas; Rhiem, Kerstin; Tesch, Hans; Blohmer, Jens Uwe; Lübbe, Kristina; Untch, Michael; Salat, Christoph; Huober, Jens; Klare, Peter; Schmutzler, Rita; et al. (European Journal of Cancer, 2021)
Background: BRCA1 and BRCA2 play a central role in DNA repair. Therefore, patients harbouring germline (g) BRCA1/2 mutations (m) treated with chemotherapy might be at higher risk of haematological toxicities. Methods: Patients from German Breast Group (GBG) and Arbeitsgemeinschaft Gynäkologische Onkologie-breast group studies with early triple-negative breast cancer (TNBC) and known gBRCA1/2m status treated with anthracycline-taxane-based neoadjuvant chemotherapy were analysed. Primary objective was the rate of neutropenia grade (G)III–IV in cycle 1 (C1). Secondary objectives included effects on overall and other haematological toxicities GIII-IV in C1, cumulative haematological toxicity across all cycles, relative total dose intensity, and granulocyte-colony stimulating factor prophylaxis. Haematological toxicities under taxanes, carboplatin, and cyclophosphamide were explored. Results: Two hundred nine of 1171 (17.8%) evaluated patients had gBRCA1/2m. In C1, 37.4% gBRCA1/2m versus 35.7% wild-type patients had neutropenia GIII-IV (P = 0.683). For C1, gBRCA1/2m predicted neither for neutropenia GIII-IV (odds ratio [OR]: 1.26, 95% confidence intervals [CI]: 0.87–1.82, P = 0.226) nor for other haematological toxicities GIII-IV (OR: 0.91, 95% CI: 0.64–1.31, P = 0.625) in multivariable regression models. Analyses of cumulative toxicities across all cycles yielded similar results except thrombocytopaenia GIII-IV, which was increased in gBRCA1m patients. In patients treated with taxanes, the rate of haematological toxicities GIII-IV was higher in gBRCA1/2m compared with wild-type (59.5% versus 43.1%; p < 0.001). No difference was seen under cyclophosphamide or platinum-containing chemotherapies. Conclusions: gBRCA1/2m was not associated with higher risk of overall severe haematological toxicities in the first cycle or cumulatively across all cycles under standard chemotherapy for TNBC. Under taxane, patients with gBRCA1/2m might have a higher risk of haematological toxicities GIII-IV, requiring further research.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Carboplatin; gBRCA1/2 mutation; Hematological toxicities; Neoadjuvant chemotherapy; Neutropenia; Taxanes

Germline copy number variants and endometrial cancer risk - Stylianou, Cassie E.; Wiggins, George A.R.; Lau, Vanessa L.; Dennis, Joe; Shelling, Andrew N.; Wilson, Michelle; Sykes, Peter; Amant, Frederic; Annibali, Daniela; De Wispelaere, Wout; Easton, Douglas F.; Fasching, Peter; et al. (Human genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls (p = 4.4 × 10–63). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated (p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.
CRIS-Team Scopus Importer:2024-11-15

Germline (G)BRCA1/2 Mutations (M) and Hematological Toxicities in Patients (PTS) with Triple Negative Breast Cancer (TNBC) Treated with Neoadjuvant Chemotherapy (NACT) - Furlanetto, Jenny; Moebus, Volker; Schneeweiss, Andreas; Rhiem, Kerstin; Tesch, Hans; Blohmer, Jens-Uwe; Luebbe, Kristina; Untch, Michael; Salat, Christoph; Huober, Jens; Klare, Peter; Schmutzler, Rita; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Germline genome-wide association studies in women receiving neoadjuvant chemotherapy with or without bevacizumab - Ingle, James N.; Kalari, Krishna R.; Wickerham, Donald Lawrence; Von Minckwitz, Gunter; Fasching, Peter; Furukawa, Yoichi; Mushiroda, Taisei; Goetz, Matthew P.; Barman, Poulami; Carlson, Erin E.; Rastogi, Priya; Costantino, Joseph P.; et al. (Pharmacogenetics and Genomics, 2018)
Neoadjuvant chemotherapy (NAC) for breast cancer is widely utilized, and we performed genome-wide association studies (GWAS) to determine whether germ-line genetic variability was associated with benefit in terms of pathological complete response (pCR), disease-free survival, and overall survival in patients entered on the NSABP B-40 NAC trial, wherein patients were randomized to receive, or not, bevacizumab in addition to chemotherapy. Patient DNA samples were genotyped with the Illumina OmniExpress BeadChip. Replication was attempted with genotyping data from 1398 HER2-negative patients entered on the GeparQuinto NAC study in which patients were also randomized to receive, or not, bevacizumab in addition to chemotherapy. A total of 920 women from B-40 were analyzed, and 237 patients achieved a pCR. GWAS with three phenotypes (pCR, disease-free survival, overall survival) revealed no single nucleotide polymorphisms (SNPs) that were genome-wide significant (i.e. P≤5E-08) signals; P values for top SNPs were 2.04E-07, 5.61E-08, and 5.63E-08, respectively, and these SNPs were not significant in the GeparQuinto data. An ad-hoc GWAS was performed in the patients randomized to bevacizumab (457 patients with 128 pCR) who showed signals on chromosome 6, located within a gene, CDKAL1, that approached, but did not reach, genome-wide significance (top SNP rs7453577, P=2.97E-07). However, this finding was significant when tested in the GeparQuinto data set (P=0.04). In conclusion, we identified no SNPs significantly associated with NAC. The observation, in a hypothesis-generating GWAS, of an SNP in CDKAL1 associated with pCR in the bevacizumab arm of both B-40 and GeparQuinto requires further validation and study.
EVALuna2:210016

Germline HOXB13 mutations p.G84E and p.R217C do not confer an increased breast cancer risk - Liu, Jingjing; Prager-van der Smissen, Wendy J.C.; Collée, J. Margriet; Bolla, Manjeet K.; Wang, Qin; Michailidou, Kyriaki; Dennis, Joe; Ahearn, Thomas U.; Aittomäki, Kristiina; Ambrosone, Christine B.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Scientific Reports, 2020)
In breast cancer, high levels of homeobox protein Hox-B13 (HOXB13) have been associated with disease progression of ER-positive breast cancer patients and resistance to tamoxifen treatment. Since HOXB13 p.G84E is a prostate cancer risk allele, we evaluated the association between HOXB13 germline mutations and breast cancer risk in a previous study consisting of 3,270 familial non-BRCA1/2 breast cancer cases and 2,327 controls from the Netherlands. Although both recurrent HOXB13 mutations p.G84E and p.R217C were not associated with breast cancer risk, the risk estimation for p.R217C was not very precise. To provide more conclusive evidence regarding the role of HOXB13 in breast cancer susceptibility, we here evaluated the association between HOXB13 mutations and increased breast cancer risk within 81 studies of the international Breast Cancer Association Consortium containing 68,521 invasive breast cancer patients and 54,865 controls. Both HOXB13 p.G84E and p.R217C did not associate with the development of breast cancer in European women, neither in the overall analysis (OR = 1.035, 95% CI = 0.859-1.246, P = 0.718 and OR = 0.798, 95% CI = 0.482-1.322, P = 0.381 respectively), nor in specific high-risk subgroups or breast cancer subtypes. Thus, although involved in breast cancer progression, HOXB13 is not a material breast cancer susceptibility gene.
CRIS-Team Scopus Importer:2020-06-26

Germline mutations in new susceptibility genes for non-high-grade serous ovarian cancer. - Pavanello, Marina; Dicks, Ed; Song, Honglin; Ariff, Amir; Bolithon, Adelyn; Intermaggio, Maria P.; Pinese, Mark; Moysich, Kirsten; Odunsi, Kunle O.; Goode, Ellen; Bowtell, David D.; Fasching, Peter; et al. (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-07-24

Germline Mutation Status and Therapy Response in High-Risk Early-Stage Breast Cancer: a Secondary Analysis of the Geparocto Randomized Clinical Trial (NCT02125344) - Pohl-Rescigno, Esther; Hauke, Jan; Rhiem, Kerstin; Moebus, Volker; Furlanetto, Jenny; Denkert, Carsten; Fasching, Peter; Hanusch, Claus; Tesch, Hans; Weber-Lassalle, Nana; Mueller, Volkmar; Untch, Michael; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Germline mutation status and therapy response in patients with homologous recombination deficient, HER2-negative early breast cancer: Results of the GeparOLA study (NCT02789332) - Hauke, J.; Ernst, C.; Fasching, Peter; Jackisch, C.; Seither, F.; Klare, P.; Rhiem, K. E.; Schmatloch, S.; Huober, J.; Stefek, A.; Seiler, S.; Uleer, C.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Germline mutation status and therapy response in patients with triple-negative breast cancer (TNBC): Results of the GeparOcto study - Pohl, E.; Schneeweiss, A.; Hauke, J.; Moebus, V.; Furlanetto, J.; Denkert, C.; Fasching, Peter; Hanusch, C.; Tesch, H.; Weber-Lassalle, N.; Mueller, V.; Rhiem, K.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Germline Mutation Status, Pathological Complete Response, and Disease-Free Survival in Triple-Negative Breast Cancer: Secondary Analysis of the GeparSixto Randomized Clinical Trial - Hahnen, Eric; Lederer, Bianca; Hauke, Jan; Loibl, Sibylle; Kroeber, Sandra; Schneeweiss, Andreas; Denkert, Carsten; Fasching, Peter; Blohmer, Jens U.; Jackisch, Christian; Paepke, Stefan; Gerber, Bernd; et al. (JAMA Oncology, 2017)
Importance: The GeparSixto trial provided evidence that the addition of neoadjuvant carboplatin to a regimen consisting of anthracycline, taxane, and bevacizumab increases pathological complete response (pCR) rates in patients with triple-negative breast cancer (TNBC). Whether BRCA1 and BRCA2 germline mutation status affects treatment outcome remains elusive. Objective: To determine whether BRCA1 and BRCA2 germline mutation status affects therapy response in patients with TNBC. Design, Setting, and Participants: This secondary analysis of a randomized clinical trial used archived DNA samples and cancer family history of 315 patients with TNBC enrolled between August 1, 2011, and December 31, 2012, in the GeparSixto trial. In all, 291 participants (92.4%) were included in this multicenter prospective investigation. DNA samples were analyzed for germline mutations in BRCA1, BRCA2, and 16 other cancer predisposition genes. The pCR rates between the carboplatin and noncarboplatin arms were compared. Genetic analyses were performed at the Center for Familial Breast and Ovarian Cancer in Cologne, Germany; data analysis, November 1 through December 31, 2015. Main Outcomes and Measures: Proportion of patients who achieved pCR and disease-free survival after neoadjuvant treatment according to BRCA1 and BRCA2 germline mutation status. For pCR rates, the ypT0/is ypN0 definition was used as a primary end point. Results: Of the 291 patients with TNBC, all were women; the mean (SD) age was 48 (11) years. The pCR rate in the carboplatin group was 56.8% (83 of 146) and 41.4% (60 of 145) in the noncarboplatin group (odds ratio [OR], 1.87; 95% CI, 1.17-2.97; P = .009). Pathogenic BRCA1 and BRCA2 germline mutations were present in 50 of the 291 patients (17.2%). In the noncarboplatin arm, the pCR rate was 66.7% (16 of 24) for patients with BRCA1 and BRCA2 mutations and 36.4% (44 of 121) for patients without (OR, 3.50; 95% CI, 1.39-8.84; P = .008). The high pCR rate observed in BRCA1 and BRCA2 mutation carriers (16 of 24 [66.7%]) was not increased further by adding carboplatin (17 of 26 [65.4%]). In contrast, carboplatin increased response rates in patients without BRCA1 and BRCA2 mutations: 66 of the 120 patients (55%) without BRCA1 and BRCA2 mutations achieved pCR in the carboplatin arm vs 44 of the 121 patients (36.4%) in the noncarboplatin arm (OR, 2.14; 95% CI, 1.28-3.58; P = .004). Patients without pathogenic BRCA1 and BRCA2 alterations showed elevated disease-free survival rates when carboplatin was added (without carboplatin, 73.5%; 95% CI, 64.1%-80.8% vs with carboplatin, 85.3%; 95% CI, 77.0%-90.8%; hazard ratio, 0.53; 95% CI, 0.29-0.96; P = .04). Conclusions and Relevance: Under the nonstandard GeparSixto polychemotherapy regimen, patients without BRCA1 and BRCA2 germline mutations benefited from the addition of carboplatin and those with BRCA1 and BRCA2 mutations showed superior response rates without additive effects observed for carboplatin. Trial Registration: clinicaltrials.gov Identifier: NCT01426880.
EVALuna2:36184

Germline polymorphisms in an enhancer of PSIP1 are associated with progression-free survival in epithelial ovarian cancer - French, Juliet D.; Johnatty, Sharon E.; Lu, Yi; Beesley, Jonathan; Gao, Bo; Kalimutho, Murugan; Henderson, Michelle J.; Russell, Amanda J.; Kar, Siddhartha; Chen, Xiaoqing; Hillman, Kristine M.; Kaufmann, Susanne; et al. (Oncotarget, 2016)
Women with epithelial ovarian cancer (EOC) are usually treated with platinum/taxane therapy after cytoreductive surgery but there is considerable inter-individual variation in response. To identify germline single-nucleotide polymorphisms (SNPs) that contribute to variations in individual responses to chemotherapy, we carried out a multi-phase genome-wide association study (GWAS) in 1,244 women diagnosed with serous EOC who were treated with the same first-line chemotherapy, carboplatin and paclitaxel. We identified two SNPs (rs7874043 and rs72700653) in TTC39B (best P=7x10-5, HR=1.90, for rs7874043) associated with progression-free survival (PFS). Functional analyses show that both SNPs lie in a putative regulatory element (PRE) that physically interacts with the promoters of PSIP1, CCDC171 and an alternative promoter of TTC39B. The C allele of rs7874043 is associated with poor PFS and showed increased binding of the Sp1 transcription factor, which is critical for chromatin interactions with PSIP1. Silencing of PSIP1 significantly impaired DNA damage-induced Rad51 nuclear foci and reduced cell viability in ovarian cancer lines. PSIP1 (PC4 and SFRS1 Interacting Protein 1) is known to protect cells from stress-induced apoptosis, and high expression is associated with poor PFS in EOC patients. We therefore suggest that the minor allele of rs7874043 confers poor PFS by increasing PSIP1 expression.
EVALuna2:9320

Germline variants and breast cancer survival in patients with distant metastases at primary breast cancer diagnosis - Escala-Garcia, Maria; Canisius, Sander; Keeman, Renske; Beesley, Jonathan; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Bermisheva, Marina; Bojesen, Stig E.; et al. (Scientific Reports, 2021)
Breast cancer metastasis accounts for most of the deaths from breast cancer. Identification of germline variants associated with survival in aggressive types of breast cancer may inform understanding of breast cancer progression and assist treatment. In this analysis, we studied the associations between germline variants and breast cancer survival for patients with distant metastases at primary breast cancer diagnosis. We used data from the Breast Cancer Association Consortium (BCAC) including 1062 women of European ancestry with metastatic breast cancer, 606 of whom died of breast cancer. We identified two germline variants on chromosome 1, rs138569520 and rs146023652, significantly associated with breast cancer-specific survival (P = 3.19 x 10(-8) and 4.42 x 10(-8)). In silico analysis suggested a potential regulatory effect of the variants on the nearby target genes SDE2 and H3F3A. However, the variants showed no evidence of association in a smaller replication dataset. The validation dataset was obtained from the SNPs to Risk of Metastasis (StoRM) study and included 293 patients with metastatic primary breast cancer at diagnosis. Ultimately, larger replication studies are needed to confirm the identified associations.
CRIS-Team WoS Importer:2021-10-15

Germline variants of homology-directed repair or mismatch repair genes in cervical cancer - Kokemüller, Lara; Ramachandran, Dhanya; Schürmann, Peter; Geffers, Robert; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Fasching, Peter; Luyten, Alexander; et al. (International Journal of Cancer, 2024)
While cervical cancer is associated with a persistent human papillomavirus (HPV) infection, the progression to cancer is influenced by genomic risk factors that have remained largely obscure. Pathogenic variants in genes of the homology-directed repair (HDR) or mismatch repair (MMR) are known to predispose to diverse tumour entities including breast and ovarian cancer (HDR) or colon and endometrial cancer (MMR). We here investigate the spectrum of HDR and MMR germline variants in cervical cancer, with particular focus on the HPV status and histological subgroups. We performed targeted next-generation sequencing for 5 MMR genes and 12 HDR genes on 728 German patients with cervical dysplasia or invasive cancer. In total, 4% of our patients carried a pathogenic germline variant, based on ClinVar classifications and additional ESM1b and AlphaMissense predictions. These included 15 patients with truncating variants in HDR genes (BARD1, BRCA1, BRCA2, BRIP1, FANCM, RAD51D and SLX4). MMR-related gene variants were less prevalent and mainly of the missense type. While MMR-related gene variants tended to associate with adenocarcinomas, HDR gene variants were commonly observed in squamous cancers. While one patient with HPV-negative cancer carried a pathogenic MMR gene variant (in MSH6), the HDR germline variants were found in patients with HPV-positive cancers and tended to associate with HPV18. Taken together, our study supports a potentially risk-modifying role of MMR and HDR germline variants in cervical cancer but no association with HPV-negative status. These variants may be exploitable in future therapeutic managements.
CRIS-Team Scopus Importer:2024-11-01
Keywords: cervical carcinoma; homologous recombination; human papillomavirus; mismatch repair; targeted sequencing

Germline variation in ADAMTSL1 is associated with prognosis following breast cancer treatment in young women - Kadalayil, Latha; Khan, Sofia; Nevanlinna, Heli; Fasching, Peter; Couch, Fergus J.; Hopper, John L.; Liu, Jianjun; Maishman, Tom; Durcan, Lorraine; Gerty, Sue; Blomqvist, Carl; Rack, Brigitte; et al. (Nature Communications, 2017)
To identify genetic variants associated with breast cancer prognosis we conduct a meta-analysis of overall survival (OS) and disease-free survival (DFS) in 6042 patients from four cohorts. In young women, breast cancer is characterized by a higher incidence of adverse pathological features, unique gene expression profiles and worse survival, which may relate to germline variation. To explore this hypothesis, we also perform survival analysis in 2315 patients aged ≤ 40 years at diagnosis. Here, we identify two SNPs associated with early-onset DFS, rs715212 (P meta = 3.54 × 10-5) and rs10963755 (P meta = 3.91 × 10-4) in ADAMTSL1. The effect of these SNPs is independent of classical prognostic factors and there is no heterogeneity between cohorts. Most importantly, the association with rs715212 is noteworthy (FPRP <0.2) and approaches genome-wide significance in multivariable analysis (P multivariable = 5.37 × 10-8). Expression quantitative trait analysis provides tentative evidence that rs715212 may influence AREG expression (P eQTL = 0.035), although further functional studies are needed to confirm this association and determine a mechanism.
EVALuna2:36180

Global Phase 3 Study of Adagloxad Simolenin (OBI-822) and OBI-821 Versus Placebo Treatment for High Risk Early Stage Triple Negative Breast Cancer Patients (TNBC) Following Neoadjuvant or Adjuvant Chemotherapy - Rugo, Hope; Chow, Louis W. C.; Cortes, Javier; Fasching, Peter; He, Xu-Bing; Hsu, Pei; Huang, Chiun-Sheng; Kim, Sung-Bae; Lu, Yen-Shen; Melisko, Michelle; Nanda, Rita; Pearce, Tillman E.; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Going Digital: A Survey on Digitalization and Large-Scale Data Analytics in Healthcare - Tresp, Volker; Overhage, J. Marc; Bundschus, Markus; Rabizadeh, Shahrooz; Fasching, Peter; Yu Shipeng, (Proceedings of the IEEE, 2016)
We provide an overview of the recent trends toward digitalization and large-scale data analytics in healthcare. It is expected that these trends are instrumental in the dramatic changes in the way healthcare will be organized in the future. We discuss the recent political initiatives designed to shift care delivery processes from paper to electronic, with the goals of more effective treatments with better outcomes; cost pressure is a major driver of innovation. We describe newly developed networks of healthcare providers, research organizations, and commercial vendors to jointly analyze data for the development of decision support systems. We address the trend toward continuous healthcare where health is monitored by wearable and stationary devices; a related development is that patients increasingly assume responsibility for their own health data. Finally, we discuss recent initiatives toward a personalized medicine, based on advances in molecular medicine, data management, and data analytics.
EVALuna2:33056

GWAS meta-analysis and replication identifies three new susceptibility loci for ovarian cancer - Pharoah, Paul D. P.; Tsai, Ya-Yu; Ramus, Susan J.; Phelan, Catherine M.; Goode, Ellen L.; Lawrenson, Kate; Buckley, Melissa; Fridley, Brooke L.; Tyrer, Jonathan P.; Shen, Howard; Weber, Rachel; Karevan, Rod; et al. (Nature Genetics, 2013)
Genome-wide association studies (GWAS) have identified four susceptibility loci for epithelial ovarian cancer (EOC), with another two suggestive loci reaching near genome-wide significance. We pooled data from a GWAS conducted in North America with another GWAS from the UK. We selected the top 24,551 SNPs for inclusion on the iCOGS custom genotyping array. We performed follow-up genotyping in 18,174 individuals with EOC (cases) and 26,134 controls from 43 studies from the Ovarian Cancer Association Consortium. We validated the two loci at 3q25 and 17q21 that were previously found to have associations close to genome-wide significance and identified three loci newly associated with risk: two loci associated with all EOC subtypes at 8q21 (rs11782652, P = 5.5 × 10-9) and 10p12 (rs1243180, P = 1.8 × 10-8) and another locus specific to the serous subtype at 17q12 (rs757210, P = 8.1 × 10-10). An integrated molecular analysis of genes and regulatory regions at these loci provided evidence for functional mechanisms underlying susceptibility and implicated CHMP4C in the pathogenesis of ovarian cancer.
CRIS-Team Scopus Importer:2021-07-19

Health-related Quality of Life in Metastatic and Adjuvant Breast Cancer Patients - Wallwiener, M.; Simoes, E.; Sokolov, A. N.; Brucker, S. Y.; Fasching, Peter; Graf, J. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: When cancer patients have advanced disease and a primary cure is no longer possible, the focus is on maintaining the patient's quality of life. Recent therapeutic advances in breast cancer treatment mean that even patients with metastatic disease can remain stable for long periods of time. The aim of this study was to look at the health-related quality of life (HRQL) of these patients and compare it with data for the general population and to show the differences in outcomes for different survey instruments used to measure quality of life.Material and Methods:A total of 96 breast cancer patients with metastatic disesae or receiving adjuvant therapy were questioned about their quality of life. Patients were investigated using the established survey instruments EORTC QLQ-C30, EORTC QLQ-BR23, EQ-5D-5L and EQ VAS. All patients filled out questionnaires. Statistical analysis was done using MS Excel and SPSS.Results:Although the questionnaires were completed at the same time, the different questionnaires showed significant differences with regard to the level of stress experienced by the patient. When the EQ VAS questionnaire was used, the patient's current state of health was assessed as significantly better than with the EORTC QLQ-C30. Overall, all aspects of patients' quality of life were found to be in need of optimization and HRQL of patients was significantly poorer in all areas compared to the reference population.Conclusion:To improve the quality of life of patients with metastatic disease, it is necessary to continuously monitor the success of therapy. The choice of survey tools is highly relevant as assessments differ considerably depending on the choice of questionnaire.
EVALuna2:33061

Health utilities in gynecological oncology and mastology in Germany - Hildebrandt, Thomas; Thiel, Falk; Fasching, Peter; Graf, Christiane; Bani, Mayada; Löhberg, Christian; Schrauder, Michael G.; Jud, Sebastian; Hack, Carolin; Beckmann, Matthias; Lux, Michael P. (Anticancer Research, 2014)
Cost increases in the healthcare system are leading to a need to distribute financial resources in accordance with the value of each service performed. Health-economic decision-making models can support these decisions. Due to the previous unavailability of health utilities in Germany (scored states of health as a basis for calculating quality-adjusted life-years, QALYs) for women undergoing treatment, international data are often used for such models. However, these may widely deviate from the values for a woman actually living in Germany. It is, therefore, necessary to collect and analyze health utilities in Germany.In a questionnaire survey, health utilities were collected, along with data for a healthy control group, for 580 female patients receiving treatment in the fields of mastology and gynecological oncology using a German version of the EuroQol questionnaire (EQ-5D) and a visual analogue scale (VAS). Data were also collected for the patients' medical history, tumor disease, and treatment.Significant differences with regard to quality of life were measured in relation to the individual tumor entities and in comparison to the controls. Apart from the healthy control group, patients with breast or cervical carcinoma had the best quality of life. In patients with recurrent and metastatic disease, those with breast carcinoma experienced the greatest impairment of their quality of life. According to current treatment, the most important impairment of life quality occurred in patients under radiotherapy and after surgical treatment. There are significant differences from the health utilities recorded for other countries - for example, the state of health declines much more markedly in patients with metastatic disease among American women with breast carcinoma than among German women, in whom recurrent disease and a first diagnosis of metastasis were comparable. Overall, the VAS was able to distinguish more adequately than the EQ-5D questionnaire between the different situations and impairments resulting from diagnosis and therapy.Health utilities are now, for the first time, available for further health-economics analyses in the field of gynecological oncology and mastology for women living in Germany. Important differences in these utilities from those of other countries are evident.
EVALuna2:17453

Heart Rate Measurement Accuracy of Fitbit Charge 4 and Samsung Galaxy Watch Active2: Device Evaluation Study - Nissen, Michael; Slim, Syrine; Jäger, Katharina; Flaucher, Madeleine; Hübner, Hanna; Danzberger, Nina; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (JMIR Formative Research, 2022)
Background: Fitness trackers and smart watches are frequently used to collect data in longitudinal medical studies. They allow continuous recording in real-life settings, potentially revealing previously uncaptured variabilities of biophysiological parameters and diseases. Adequate device accuracy is a prerequisite for meaningful research. Objective: This study aims to assess the heart rate recording accuracy in two previously unvalidated devices: Fitbit Charge 4 and Samsung Galaxy Watch Active2. Methods: Participants performed a study protocol comprising 5 resting and sedentary, 2 low-intensity, and 3 high-intensity exercise phases, lasting an average of 19 minutes 27 seconds. Participants wore two wearables simultaneously during all activities: Fitbit Charge 4 and Samsung Galaxy Watch Active2. Reference heart rate data were recorded using a medically certified Holter electrocardiogram. The data of the reference and evaluated devices were synchronized and compared at 1-second intervals. The mean, mean absolute error, mean absolute percentage error, Lin concordance correlation coefficient, Pearson correlation coefficient, and Bland-Altman plots were analyzed. Results: A total of 23 healthy adults (mean age 24.2, SD 4.6 years) participated in our study. Overall, and across all activities, the Fitbit Charge 4 slightly underestimated the heart rate, whereas the Samsung Galaxy Watch Active2 overestimated it (−1.66 beats per minute [bpm]/3.84 bpm). The Fitbit Charge 4 achieved a lower mean absolute error during resting and sedentary activities (seated rest: 7.8 vs 9.4; typing: 8.1 vs 11.6; laying down [left]: 7.2 vs 9.4; laying down [back]: 6.0 vs 8.6; and walking slowly: 6.8 vs 7.7 bpm), whereas the Samsung Galaxy Watch Active2 performed better during and after low- and high-intensity activities (standing up: 12.3 vs 9.0; walking fast: 6.1 vs 5.8; stairs: 8.8 vs 6.9; squats: 15.7 vs 6.1; resting: 9.6 vs 5.6 bpm). Conclusions: Device accuracy varied with activity. Overall, both devices achieved a mean absolute percentage error of just <10%. Thus, they were considered to produce valid results based on the limits established by previous work in the field. Neither device reached sufficient accuracy during seated rest or keyboard typing. Thus, both devices may be eligible for use in respective studies; however, researchers should consider their individual study requirement
Keywords: wearable validation; heart rate validation; Fitbit Charge 4; Samsung Galaxy Watch Active2; heart rate accuracy; fitness tracker accuracy; wearable accuracy; wearable (21); Fitbit (10); heart rate (14); fitness tracker (3); fitness (2); cardiovascular (8)

Height and Breast Cancer Risk: Evidence From Prospective Studies and Mendelian Randomization - Zhang, Ben; Shu, Xiao-Ou; Delahanty, Ryan J.; Zeng, Chenjie; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wen, Wanqing; Long, Jirong; Li, Chun; Dunning, Alison M.; et al. (Journal of the National Cancer Institute, 2015)
Epidemiological studies have linked adult height with breast cancer risk in women. However, the magnitude of the association, particularly by subtypes of breast cancer, has not been established. Furthermore, the mechanisms of the association remain unclear.We performed a meta-analysis to investigate associations between height and breast cancer risk using data from 159 prospective cohorts totaling 5216302 women, including 113178 events. In a consortium with individual-level data from 46325 case patients and 42482 control patients, we conducted a Mendelian randomization analysis using a genetic score that comprised 168 height-associated variants as an instrument. This association was further evaluated in a second consortium using summary statistics data from 16003 case patients and 41335 control patients.The pooled relative risk of breast cancer was 1.17 (95% confidence interval [CI] = 1.15 to 1.19) per 10cm increase in height in the meta-analysis of prospective studies. In Mendelian randomization analysis, the odds ratio of breast cancer per 10cm increase in genetically predicted height was 1.22 (95% CI = 1.13 to 1.32) in the first consortium and 1.21 (95% CI = 1.05 to 1.39) in the second consortium. The association was found in both premenopausal and postmenopausal women but restricted to hormone receptor-positive breast cancer. Analyses of height-associated variants identified eight new loci associated with breast cancer risk after adjusting for multiple comparisons, including three loci at 1q21.2, DNAJC27, and CCDC91 at genome-wide significance level P < 5×10(-8).Our study provides strong evidence that adult height is a risk factor for breast cancer in women and certain genetic factors and biological pathways affecting adult height have an important role in the etiology of breast cancer.
EVALuna2:9301

Heregulin (HRG) assessment for clinical trial eligibility testing in a molecular registry (PRAEGNANT) in Germany - Hübner, Hanna; Kurbacher, Christian M.; Kuesters, Geoffrey; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Volz, Bernhard; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; Lüftner, Diana; et al. (BMC Cancer, 2020)
Background: Eligibility criteria are a critical part of clinical trials, as they define the patient population under investigation. Besides certain patient characteristics, clinical trials often include biomarker testing for eligibility. However, patient-identification mostly relies on the trial site itself and is often a time-consuming procedure, which could result in missing out on potentially eligible patients. Pre-selection of those patients using a registry could facilitate the process of eligibility testing and increase the number of identified patients. One aim with the PRAEGNANT registry (NCT02338167) is to identify patients for therapies based on clinical and molecular data. Here, we report eligibility testing for the SHERBOC trial using the German PRAEGNANT registry. Methods: Heregulin (HRG) has been reported to identify patients with better responses to therapy with the anti-HER3 monoclonal antibody seribantumab (MM-121). The SHERBOC trial investigated adding seribantumab (MM-121) to standard therapy in patients with advanced HER2-negative, hormone receptor–positive (HR-positive) breast cancer and HRG overexpression. The PRAEGNANT registry was used for identification and tumor testing, helping to link potential HRG positive patients to the trial. Patients enrolled in PRAEGNANT have invasive and metastatic or locally advanced, inoperable breast cancer. Patients eligible for SHERBOC were identified by using the registry. Study aims were to describe the HRG positivity rate, screening procedures, and patient characteristics associated with inclusion and exclusion criteria. Results: Among 2769 unselected advanced breast cancer patients, 650 were HER2-negative, HR-positive and currently receiving first- or second-line treatment, thus potentially eligible for SHERBOC at the end of current treatment; 125 patients also met further clinical eligibility criteria (e.g. menopausal status, ECOG). In the first/second treatment lines, patients selected for SHERBOC based on further eligibility criteria had a more favorable prognosis than those not selected. HRG status was tested in 38 patients, 14 of whom (36.8%) proved to be HRG-positive. Conclusion: Using a real-world breast cancer registry allowed identification of potentially eligible patients for SHERBOC focusing on patients with HER3 overexpressing, HR-positive, HER2-negative metastatic breast cancer. This approach may provide insights into differences between patients eligible or non-eligible for clinical trials. Trial registration: Clinicaltrials, NCT02338167, Registered 14 January 2015 - retrospectively registered.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Advanced breast cancer; Antihormone therapy; Heregulin; Metastatic; MM-121; Seribantumab

High Ki-67 as a biomarker for identifying patients with high risk early breast cancer treated in monarchE - Harbeck, Nadia; Johnston, Stephen; Fasching, Peter; Martin, Miguel; Toi, Masakazu; Rastogi, Priya; Song, Chuangui; Molthrop, David; Vuky, Jacqueline; Yamashita, Toshinari; Jaliffe, Georgina Garnica; Gumus, Mahmut; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

History of Comorbidities and Survival of Ovarian Cancer Patients, Results from the Ovarian Cancer Association Consortium - Minlikeeva, Albina N.; Freudenheim, Jo L.; Eng, Kevin H.; Cannioto, Rikki A.; Friel, Grace; Szender, J. Brian; Segal, Brahm; Odunsi, Kunle; Mayor, Paul; Diergaarde, Brenda; Zsiros, Emese; Kelemen, Linda E.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2017)
Background: Comorbidities can affect survival of ovarian cancer patients by influencing treatment efficacy. However, little evidence exists on the association between individual concurrent comorbidities and prognosis in ovarian cancer patients.Methods: Among patients diagnosed with invasive ovarian carcinoma who participated in 23 studies included in the Ovarian Cancer Association Consortium, we explored associations between histories of endometriosis; asthma; depression; osteoporosis; and autoimmune, gallbladder, kidney, liver, and neurological diseases and overall and progression-free survival. Using Cox proportional hazards regression models adjusted for age at diagnosis, stage of disease, histology, and study site, we estimated pooled HRs and 95% confidence intervals to assess associations between each comorbidity and ovarian cancer outcomes.Results: None of the comorbidities were associated with ovarian cancer outcome in the overall sample nor in strata defined by histologic subtype, weight status, age at diagnosis, or stage of disease (local/regional vs. advanced).Conclusions: Histories of endometriosis; asthma; depression; osteoporosis; and autoimmune, gallbladder, kidney, liver, or neurologic diseases were not associated with ovarian cancer overall or progression-free survival.Impact: These previously diagnosed chronic diseases do not appear to affect ovarian cancer prognosis. Cancer Epidemiol Biomarkers Prev; 26(9); 1470-3. ©2017 AACR.
EVALuna2:36128

HLA-G and HLA-F protein isoform expression in breast cancer patients receiving neoadjuvant treatment - Würfel, Franziska; Hübner, Hanna; Häberle, Lothar; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Hack, Carolin; Wunderle, Marius; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; Ekici, Arif Bülent; et al. (Scientific Reports, 2020)
The immunosuppressive human leukocyte antigens HLA-G and HLA-F are expressed on trophoblast and malignant cells. Four membrane-bound and three soluble HLA-G protein isoforms have been described, which have different immunosuppressive potentials. HLA-F has three transcript variants, resulting in three different protein isoforms. The aim of this study was to evaluate the prognostic and predictive value of HLA-G and HLA-F protein isoform expression patterns in patients with breast cancer. Core biopsies were taken at diagnosis in patients with HER2+ (n = 28), luminal B-like (n = 49) and triple-negative (n = 38) breast cancers who received neoadjuvant chemotherapy. Expression levels of HLA-F and -G were correlated with the pathological complete response (pCR). Protein expression was determined by Western blot analysis, using two antibodies for each HLA, specific for different isoforms. The protein expression of HLA isoforms did not significantly differ between breast cancer subtypes. However, some initial indications were found for an association between the soluble HLA-G6 protein isoform and pCR in HER2+ breast cancer. The study provides preliminary evidence for the evaluation of HLA-G isoform expression, in particular HLA-G6, as a possible new marker for pCR in HER2+ breast cancer.
CRIS-Team Scopus Importer:2020-10-02

HLA-J, a Non-Pseudogene as a New Prognostic Marker for Therapy Response and Survival in Breast Cancer - Würfel, Franziska M.; Wirtz, Ralph M.; Winterhalter, Christoph; Taffurelli, Mario; Santini, Donatella; Mandrioli, Anna; Veltrup, Elke; Rübner, Matthias; Fasching, Peter; Würfel, Wolfgang; Zamagni, Claudio (Geburtshilfe und Frauenheilkunde, 2020)
The human leukocyte antigen (HLA) genes are cell-surface proteins, essential for immune cell interaction. HLA-G is known for their high immunosuppressive effect and its potential as predictive marker in breast cancer. However, nothing is known about the HLA-J and its immunosuppressive, prognostic and predictive features, as it is assumed to be a pseudogene by in silico sequence interpretation. HLA-J, ESR1, ERBB2, KRT5 and KRT20 mRNA expression were analysed in 29 fresh frozen breast cancer biopsies and their corresponding resectates obtained from patients treated with neoadjuvant chemotherapy (NACT). mRNA was analysed with gene specific TaqMan-based Primer/Probe sets and normalized to Calmodulin 2. All breast cancer samples did express HLA-J and frequently increased HLA-J mRNA levels after NACT. HLA-J mRNA was significantly associated with overexpression of the ESR1 mRNA status (Spearman ρ 0,5679; p = 0.0090) and KRT5 mRNA (Spearman ρ 0,6121; p = 0.0041) in breast cancer core biopsies and dominated in luminal B subtype. Kaplan Meier analysis revealed that an increase of HLA-J mRNA expression after NACT had worse progression free survival (p = 0,0096), indicating a counterreaction of tumor tissues presumably to prevent elimination by enhanced immune infiltration induced by NACT. This counterreaction is associated with worse prognosis. To our knowledge this is the first study identifying HLA-J as a new predictive marker in breast cancer being involved in immune evasion mechanisms.
CRIS-Team Scopus Importer:2020-11-20
Keywords: breast cancer subtypes; HLA-J; MHC1; RT-qPCR

Hormone replacement therapy and prognosis in ovarian cancer patients - Hein, Alexander; Thiel, Falk; Bayer, Christian M.; Fasching, Peter; Häberle, Lothar; Lux, Michael P.; Renner, Stefan; Jud, Sebastian; Schrauder, Michael G.; Müller, Andreas; Wachter, David; Strehl, Johanna; et al. (European Journal of Cancer Prevention, 2013)
Estrogen exposure has at least a moderate effect on the risk for ovarian cancer, and antiestrogen therapy may be helpful in treating the disease. It is known from breast cancer that previous hormone replacement therapy (HRT) may influence the molecular profile and prognostic behavior of these tumors. The aim of this study was therefore to investigate the influence of previous HRT on the prognosis in a cohort of patients with invasive epithelial ovarian cancer. Among 547 patients who were treated for ovarian malignancies at a single institution from 1995 to 2008, a total of 244 postmenopausal patients with epithelial cancer and under the age of 75 were identified for whom information about HRT before the onset of the disease was available. HRT was correlated with tumor and patient characteristics. Analyses of overall survival and progression-free survival were carried out using Cox proportional hazards models. Age, tumor stage, and resection status correlated significantly with HRT in the univariate analysis. Patients with previous HRT were more likely to have a lower stage, to be younger, and to have optimal debulking. With regard to survival, HRT had a positive effect on overall survival, specifically in the subgroup of patients with optimal debulking. No correlation was seen in relation to progression-free survival. Sex hormone exposure through HRT may influence the behavior of ovarian cancers after the onset of the disease. This study supports the hypothesis that ovarian cancer is a hormonally influenced tumor. © 2012 Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: estrogen; hormone replacement therapy; ovarian cancer; pathogenesis; prognosis

Hormone Therapy and its Effect on the Prognosis in Breast Cancer Patients - Rauh, C.; Schuetz, F.; Rack, B.; Stickeler, E.; Klar, M.; Orlowska-Volk, M.; Windfuhr-Blum, M.; Heil, J.; Rom, J.; Sohn, C.; Andergassen, U.; Jueckstock, J.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of hormone therapy (HT) has declined dramatically in recent years. Some studies have reported that HT use before a diagnosis of breast cancer (BC) may be a prognostic factor in postmenopausal patients. This study aimed to examine the prognostic relevance of HT use before BC diagnosis. Methods: Four BC cohort studies in Germany were pooled, and 4492 postmenopausal patients with HT use data were identified. Patient data and tumor characteristics were compared between users and nonusers, along with overall survival (OS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS). Cox proportional hazards models were stratified by study center and adjusted for age at diagnosis, tumor stage, grading, nodal status, and hormone receptors. Results: Women with HT use before the diagnosis of BC were more likely to have a lower tumor stage, to be estrogen receptor-negative, and to have a lower grading. With regard to prognosis there were effects seen for OS, DMFS and LRFS, specifically in the subgroup of women with a positive hormone receptor. In these subgroups, BC patients had a better prognosis with previous HT use. Conclusions: HT use before a diagnosis of BC is associated with a more favorable prognosis in women with a positive hormone receptor status. It may be recommended that the prognostic factor HT should be documented and analyzed as a confounder for prognosis in studies of postmenopausal hormone-responsive breast cancers.
EVALuna2:6745

HRQoL with neoadjuvant pembrolizumab plus chemotherapy vs placebo plus chemotherapy, followed by adjuvant pembrolizumab vs placebo for early-stage TNBC: Results from KEYNOTE-522 - Dent, R. A.; Cortes, J.; Pusztai, L.; Mcarthur, H. L.; Kuemmel, S.; Bergh, J.; Denkert, C.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; Untch, M.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-23

Human leucocyte antigen class i in hormone receptor-positive, HER2-negative breast cancer: Association with response and survival after neoadjuvant chemotherapy - Sinn, Bruno Valentin; Weber, Karsten E.; Schmitt, Wolfgang Daniel; Fasching, Peter; Symmans, William Fraser; Blohmer, Jens Uwe; Karn, Thomas; Taube, Eliane Tabea; Klauschen, Frederick; Marmé, Frederik; Schem, Christian; Stickeler, Elmar; et al. (BREAST CANCER RES, 2019)
Background: Clinical application of cancer immunotherapy requires a better understanding of tumor immunogenicity and the tumor microenvironment. HLA class I molecules present antigens to CD8+ cytotoxic cells. Their loss or downregulation is frequently found in tumors resulting in reduced T cell responses and worse prognosis. Methods: We evaluated HLA class I heavy chain expression by immunohistochemistry in 863 biopsies (GeparTrio trial). Patients received neoadjuvant chemotherapy and adjuvant endocrine treatment if tumors were hormone receptor-positive (HR+). In parallel, the expression of HLA-A was analyzed using a microarray cohort of 320 breast cancer patients from the MD Anderson Cancer Center. We evaluated its association with clinical outcome, tumor-infiltrating lymphocytes (TILs), and immune cell metagenes. Results: In HR+/HER2- breast cancer, HLA class I heavy chain expression was associated with increased TILs and better response to chemotherapy (7% vs. 14% pCR rate, P = 0.029), but worse disease-free survival (hazard ratio (HR) 1.6 (1.1-2.4); P = 0.024). The effect was significant in a multivariate model adjusted for clinical and pathological variables (HR 1.7 (1.1-2.6); P = 0.016) and was confirmed by analysis of HLA-A in a microarray cohort. HLA-A was correlated to most immune cell metagenes. There was no association with response or survival in triple-negative or HER2+ disease. Conclusions: The study confirms the negative prognostic role of lymphocytes in HR+ breast cancer and points at a complex interaction between chemotherapy, endocrine treatment, and tumor immunogenicity. The results point at a subtype-specific and potentially treatment-specific role of tumor-immunological processes in breast cancer with different implications in triple-negative and hormone receptor-positive disease.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Breast cancer; HLA; Tumor-infiltrating lymphocytes

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Identification and characterization of novel associations in the CASP8/ALS2CR12 region on chromosome 2 with breast cancer risk - Lin, Wei-Yu; Camp, Nicola J.; Ghoussaini, Maya; Beesley, Jonathan; Michailidou, Kyriaki; Hopper, John L.; Apicella, Carmel; Southey, Melissa C.; Stone, Jennifer; Schmidt, Marjanka K.; Broeks, Annegien; Van'T Veer, Laura J.; et al. (Human Molecular Genetics, 2015)
Previous studies have suggested that polymorphisms in CASP8 on chromosome 2 are associated with breast cancer risk. To clarify the role of CASP8 in breast cancer susceptibility, we carried out dense genotyping of this region in the Breast Cancer Association Consortium (BCAC). Single-nucleotide polymorphisms (SNPs) spanning a 1 Mb region around CASP8 were genotyped in 46 450 breast cancer cases and 42 600 controls of European origin from 41 studies participating in the BCAC as part of a custom genotyping array experiment (iCOGS). Missing genotypes and SNPs were imputed and, after quality exclusions, 501 typed and 1232 imputed SNPs were included in logistic regression models adjusting for study and ancestry principal components. The SNPs retained in the final model were investigated further in data from nine genome-wide association studies (GWAS) comprising in total 10 052 case and 12 575 control subjects. The most significant association signal observed in European subjects was for the imputed intronic SNP rs1830298 in ALS2CR12 (telomeric to CASP8), with per allele odds ratio and 95% confidence interval [OR (95% confidence interval, CI)] for the minor allele of 1.05 (1.03-1.07), P = 1 × 10(-5). Three additional independent signals from intronic SNPs were identified, in CASP8 (rs36043647), ALS2CR11 (rs59278883) and CFLAR (rs7558475). The association with rs1830298 was replicated in the imputed results from the combined GWAS (P = 3 × 10(-6)), yielding a combined OR (95% CI) of 1.06 (1.04-1.08), P = 1 × 10(-9). Analyses of gene expression associations in peripheral blood and normal breast tissue indicate that CASP8 might be the target gene, suggesting a mechanism involving apoptosi
EVALuna2:9254

Identification and validation of expressed HLA-binding breast cancer neoepitopes for potential use in individualized cancer therapy - Reimann, Hannah; Nguyen, Andrew; Sanborn, J. Zachary; Vaske, Charles J.; Benz, Stephen C.; Niazi, Kayvan; Rabizadeh, Shahrooz; Spilman, Patricia; Mackensen, Andreas; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Therapeutic regimens designed to augment the immunological response of a patient with breast cancer (BC) to tumor tissue are critically informed by tumor mutational burden and the antigenicity of expressed neoepitopes. Herein we describe a neoepitope and cognate neoepitope-reactive T-cell identification and validation program that supports the development of next-generation immunotherapies. Methods Using GPS Cancer, NantOmics research, and The Cancer Genome Atlas databases, we developed a novel bioinformatic-based approach which assesses mutational load, neoepitope expression, human leukocyte antigen (HLA)-binding prediction, and in vitro confirmation of T-cell recognition to preferentially identify targetable neoepitopes. This program was validated by application to a BC cell line and confirmed using tumor biopsies from two patients with BC enrolled in the Tumor-Infiltrating Lymphocytes and Genomics (TILGen) study. Results The antigenicity and HLA-A2 restriction of the BC cell line predicted neoepitopes were determined by reactivity of T cells from HLA-A2-expressing healthy donors. For the TILGen subjects, tumor-infiltrating lymphocytes (TILs) recognized the predicted neoepitopes both as peptides and on retroviral expression in HLA-matched Epstein-Barr virus-lymphoblastoid cell line and BC cell line MCF-7 cells; PCR clonotyping revealed the presence of T cells in the periphery with T-cell receptors for the predicted neoepitopes. These high-avidity immune responses were polyclonal, mutation-specific and restricted to either HLA class I or II. Interestingly, we observed the persistence and expansion of polyclonal T-cell responses following neoadjuvant chemotherapy. Conclusions We demonstrate our neoepitope prediction program allows for the successful identification of neoepitopes targeted by TILs in patients with BC, providing a means to identify tumor-specific immunogenic targets for individualized treatment, including vaccines or adoptively transferred cellular therapies.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Antigens; Breast neoplasms; Neoplasm

Identification of 12 new susceptibility loci for different histotypes of epithelial ovarian cancer - Phelan, Catherine M.; Kuchenbaecker, Karoline B.; Tyrer, Jonathan P.; Kar, Siddhartha P.; Lawrenson, Kate; Winham, Stacey J.; Dennis, Joe; Pirie, Ailith; Riggan, Marjorie J.; Chornokur, Ganna; Earp, Madalene A.; Lyra, Paulo C.; et al. (Nature Genetics, 2017)
To identify common alleles associated with different histotypes of epithelial ovarian cancer (EOC), we pooled data from multiple genome-wide genotyping projects totaling 25,509 EOC cases and 40,941 controls. We identified nine new susceptibility loci for different EOC histotypes: six for serous EOC histotypes (3q28, 4q32.3, 8q21.11, 10q24.33, 18q11.2 and 22q12.1), two for mucinous EOC (3q22.3 and 9q31.1) and one for endometrioid EOC (5q12.3). We then performed meta-analysis on the results for high-grade serous ovarian cancer with the results from analysis of 31,448 BRCA1 and BRCA2 mutation carriers, including 3,887 mutation carriers with EOC. This identified three additional susceptibility loci at 2q13, 8q24.1 and 12q24.31. Integrated analyses of genes and regulatory biofeatures at each locus predicted candidate susceptibility genes, including OBFC1, a new candidate susceptibility gene for low-grade and borderline serous EOC.
EVALuna2:9375

Identification of four novel susceptibility loci for oestrogen receptor negative breast cancer - Couch, Fergus J.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Mendoza-Fandino, Gustavo A.; Nord, Silje; Lilyquist, Janna; Olswold, Curtis; Hallberg, Emily; Agata, Simona; Ahsan, Habibul; Aittomaeki, Kristiina; Ambrosone, Christine; et al. (Nature Communications, 2016)
Common variants in 94 loci have been associated with breast cancer including 15 loci with genome-wide significant associations (P<5 × 10(-8)) with oestrogen receptor (ER)-negative breast cancer and BRCA1-associated breast cancer risk. In this study, to identify new ER-negative susceptibility loci, we performed a meta-analysis of 11 genome-wide association studies (GWAS) consisting of 4,939 ER-negative cases and 14,352 controls, combined with 7,333 ER-negative cases and 42,468 controls and 15,252 BRCA1 mutation carriers genotyped on the iCOGS array. We identify four previously unidentified loci including two loci at 13q22 near KLF5, a 2p23.2 locus near WDR43 and a 2q33 locus near PPIL3 that display genome-wide significant associations with ER-negative breast cancer. In addition, 19 known breast cancer risk loci have genome-wide significant associations and 40 had moderate associations (P<0.05) with ER-negative disease. Using functional and eQTL studies we implicate TRMT61B and WDR43 at 2p23.2 and PPIL3 at 2q33 in ER-negative breast cancer aetiology. All ER-negative loci combined account for 11% of familial relative risk for ER-negative disease and may contribute to improved ER-negative and BRCA1 breast cancer risk prediction.
EVALuna2:9317

Identification of independent association signals and putative functional variants for breast cancer risk through fine-scale mapping of the 12p11 locus - Zeng, Chenjie; Guo, Xingyi; Long, Jirong; Kuchenbaecker, Karoline B.; Droit, Arnaud; Michailidou, Kyriaki; Ghoussaini, Maya; Kar, Siddhartha; Freeman, Adam; Hopper, John L.; Milne, Roger L.; Bolla, Manjeet K.; et al. (Breast Cancer Research, 2016)
BACKGROUND: Multiple recent genome-wide association studies (GWAS) have identified a single nucleotide polymorphism (SNP), rs10771399, at 12p11 that is associated with breast cancer risk. METHOD: We performed a fine-scale mapping study of a 700 kb region including 441 genotyped and more than 1300 imputed genetic variants in 48,155 cases and 43,612 controls of European descent, 6269 cases and 6624 controls of East Asian descent and 1116 cases and 932 controls of African descent in the Breast Cancer Association Consortium (BCAC; http://bcac.ccge.medschl.cam.ac.uk/ ), and in 15,252 BRCA1 mutation carriers in the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA). Stepwise regression analyses were performed to identify independent association signals. Data from the Encyclopedia of DNA Elements project (ENCODE) and the Cancer Genome Atlas (TCGA) were used for functional annotation. RESULTS: Analysis of data from European descendants found evidence for four independent association signals at 12p11, represented by rs7297051 (odds ratio (OR) = 1.09, 95 % confidence interval (CI) = 1.06-1.12; P = 3 × 10(-9)), rs805510 (OR = 1.08, 95 % CI = 1.04-1.12, P = 2 × 10(-5)), and rs1871152 (OR = 1.04, 95 % CI = 1.02-1.06; P = 2 × 10(-4)) identified in the general populations, and rs113824616 (P = 7 × 10(-5)) identified in the meta-analysis of BCAC ER-negative cases and BRCA1 mutation carriers. SNPs rs7297051, rs805510 and rs113824616 were also associated with breast cancer risk at P < 0.05 in East Asians, but none of the associations were statistically significant in African descendants. Multiple candidate functional variants are located in putative enhancer sequences. Chromatin interaction data suggested that PTHLH was the likely target gene of these enhancers. Of the six variants with the strongest evidence of potential functionality, rs11049453 was statistically significantly associated with the expression of PTHLH and its nearby gene CCDC91 at P < 0.05. CONCLUSION: This study identified four independent association signals at 12p11 and revealed potentially functional variants, providing additional insights into the underlying biological mechanism(s) for the association observed between variants at 12p11 and breast cancer risk.
EVALuna2:33326

Identification of new genetic susceptibility Loci for breast cancer through consideration of gene-environment interactions - Schoeps, Anja; Rudolph, Anja; Seibold, Petra; Dunning, Alison M.; Milne, Roger L.; Bojesen, Stig E.; Swerdlow, Anthony; Andrulis, Irene; Brenner, Hermann; Behrens, Sabine; Orr, Nicholas; Jones, Michael; et al. (Genetic Epidemiology, 2014)
Genes that alter disease risk only in combination with certain environmental exposures may not be detected in genetic association analysis. By using methods accounting for gene-environment (G × E) interaction, we aimed to identify novel genetic loci associated with breast cancer risk. Up to 34,475 cases and 34,786 controls of European ancestry from up to 23 studies in the Breast Cancer Association Consortium were included. Overall, 71,527 single nucleotide polymorphisms (SNPs), enriched for association with breast cancer, were tested for interaction with 10 environmental risk factors using three recently proposed hybrid methods and a joint test of association and interaction. Analyses were adjusted for age, study, population stratification, and confounding factors as applicable. Three SNPs in two independent loci showed statistically significant association: SNPs rs10483028 and rs2242714 in perfect linkage disequilibrium on chromosome 21 and rs12197388 in ARID1B on chromosome 6. While rs12197388 was identified using the joint test with parity and with age at menarche (P-values = 3 × 10(-07) ), the variants on chromosome 21 q22.12, which showed interaction with adult body mass index (BMI) in 8,891 postmenopausal women, were identified by all methods applied. SNP rs10483028 was associated with breast cancer in women with a BMI below 25 kg/m(2) (OR = 1.26, 95% CI 1.15-1.38) but not in women with a BMI of 30 kg/m(2) or higher (OR = 0.89, 95% CI 0.72-1.11, P for interaction = 3.2 × 10(-05) ). Our findings confirm comparable power of the recent methods for detecting G × E interaction and the utility of using G × E interaction analyses to identify new susceptibility loci.
EVALuna2:9203

Identification of nine new susceptibility loci for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Bolla, Manjeet K.; Brauch, Hiltrud; Brenner, Hermann; et al. (Nature Communications, 2018)
Endometrial cancer is the most commonly diagnosed cancer of the female reproductive tract in developed countries. Through genome-wide association studies (GWAS), we have previously identified eight risk loci for endometrial cancer. Here, we present an expanded meta-analysis of 12,906 endometrial cancer cases and 108,979 controls (including new genotype data for 5624 cases) and identify nine novel genome-wide significant loci, including a locus on 12q24.12 previously identified by meta-GWAS of endometrial and colorectal cancer. At five loci, expression quantitative trait locus (eQTL) analyses identify candidate causal genes; risk alleles at two of these loci associate with decreased expression of genes, which encode negative regulators of oncogenic signal transduction proteins (SH2B3 (12q24.12) and NF1 (17q11.2)). In summary, this study has doubled the number of known endometrial cancer risk loci and revealed candidate causal genes for future study.
EVALuna2:34618

Identification of novel genetic markers of breast cancer survival - Guo, Qi; Schmidt, Marjanka K.; Kraft, Peter; Canisius, Sander; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; et al. (Journal of the National Cancer Institute, 2015)
Survival after a diagnosis of breast cancer varies considerably between patients, and some of this variation may be because of germline genetic variation. We aimed to identify genetic markers associated with breast cancer-specific survival.We conducted a large meta-analysis of studies in populations of European ancestry, including 37954 patients with 2900 deaths from breast cancer. Each study had been genotyped for between 200000 and 900000 single nucleotide polymorphisms (SNPs) across the genome; genotypes for nine million common variants were imputed using a common reference panel from the 1000 Genomes Project. We also carried out subtype-specific analyses based on 6881 estrogen receptor (ER)-negative patients (920 events) and 23059 ER-positive patients (1333 events). All statistical tests were two-sided.We identified one new locus (rs2059614 at 11q24.2) associated with survival in ER-negative breast cancer cases (hazard ratio [HR] = 1.95, 95% confidence interval [CI] = 1.55 to 2.47, P = 1.91 x 10(-8)). Genotyping a subset of 2113 case patients, of which 300 were ER negative, provided supporting evidence for the quality of the imputation. The association in this set of case patients was stronger for the observed genotypes than for the imputed genotypes. A second locus (rs148760487 at 2q24.2) was associated at genome-wide statistical significance in initial analyses; the association was similar in ER-positive and ER-negative case patients. Here the results of genotyping suggested that the finding was less robust.This is currently the largest study investigating genetic variation associated with breast cancer survival. Our results have potential clinical implications, as they confirm that germline genotype can provide prognostic information in addition to standard tumor prognostic factors.
EVALuna2:9260

Identification of Patients with Early HR+ HER2- Breast Cancer at High Risk of Recurrence - Fasching, Peter; Kreipe, Hans; Del Mastro, Lucia; Ciruelos, Eva; Freyer, Gilles; Korfel, Agnieszka; Chouaki, Nadia; Stoffregen, Clemens; Sapunar, Francisco; Cameron, David (Geburtshilfe und Frauenheilkunde, 2024)
Breast cancer incidence has increased in the last two decades and, simultaneously, survival has improved due to earlier detection and improved treatment options. Despite this improvement, locoregional recurrences and distant metastases occur in up to 10 and 30% of women diagnosed with early breast cancer, respectively. Around 70% of breast cancers are hormone receptor positive (HR+), human epidermal growth factor receptor 2 negative (HER2-), and associated with a persistent risk of relapse up to 20 years after diagnosis/initial treatment. We conducted a narrative review by combining PubMed searches with our clinical experience to describe patient characteristics, biomarkers, and genomic profiling tools available to clinicians for the identification of patients with HR+, HER2- early breast cancer at high risk of recurrence and to provide recommendations to classify patients into recurrence risk categories. National and international treatment guidelines are also summarised. Accurate assessment of the risk of recurrence in these patients is crucial as the predicted risk guides treatment decisions; imprecise estimations can result in over- or undertreatment, with either scenario having negative consequences for patients. Multiple prognostic tools and factors are recommended for early breast cancer, and no single test provides accurate prognosis in isolation. Since no single test can provide accurate prognosis in isolation, a combination of tools should be used. Risk thresholds are important to guide optimised and balanced therapeutic decisions in HR+, HER2- early breast cancer. However, prognostic assessment should be performed on a case-by-case basis, making patient-specific prognostic approaches essential to avoid over- or undertreatment.
CRIS-Team Scopus Importer:2024-12-16
Keywords: early breast cancer; HER2-; HR+; prediction of risk; risk of recurrence

Identification of Predictive Markers for Response to Neoadjuvant Chemoradiation in Rectal Carcinomas by Proteomic Isotope Coded Protein Label (ICPL) Analysis - Croner, Roland S.; Sevim, Muezeyyen; Metodiev, Metodi V.; Jo, Peter; Ghadimi, Michael; Schellerer, Vera; Brunner, Michaela; Geppert, Carol-Immanuel; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth; Matzel, Klaus E.; et al. (International Journal of Molecular Sciences, 2016)
Neoadjuvant chemoradiation (nCRT) is an established procedure in stage union internationale contre le cancer (UICC) II/III rectal carcinomas. Around 53% of the tumours present with good tumor regression after nCRT, and 8%-15% are complete responders. Reliable selection markers would allow the identification of poor or non-responders prior to therapy. Tumor biopsies were harvested from 20 patients with rectal carcinomas, and stored in liquid nitrogen prior to therapy after obtaining patients' informed consent (Erlangen-No.3784). Patients received standardized nCRT with 5-Fluoruracil (nCRT I) or 5-Fluoruracil ± Oxaliplatin (nCRT II) according to the CAO/ARO/AIO-04 protocol. After surgery, regression grading (Dworak) of the tumors was performed during histopathological examination of the specimens. Tumors were classified as poor (Dworak 1 + 2) or good (Dworak 3 + 4) responders. Laser capture microdissection (LCM) for tumor enrichment was performed on preoperative biopsies. Differences in expressed proteins between poor and good responders to nCRT I and II were identified by proteomic analysis (Isotope Coded Protein Label, ICPL(TM)) and selected markers were validated by immunohistochemistry. Tumors of 10 patients were classified as histopathologically poor (Dworak 1 or 2) and the other 10 tumor samples as histopathologically good (Dworak 3 or 4) responders to nCRT after surgery. Sufficient material in good quality was harvested for ICPL analysis by LCM from all biopsies. We identified 140 differentially regulated proteins regarding the selection criteria and the response to nCRT. Fourteen of these proteins were synchronously up-regulated at least 1.5-fold after nCRT I or nCRT II (e.g., FLNB, TKT, PKM2, SERINB1, IGHG2). Thirty-five proteins showed a complete reciprocal regulation (up or down) after nCRT I or nCRT II and the rest was regulated either according to nCRT I or II. The protein expression of regulated proteins such as PLEC1, TKT, HADHA and TAGLN was validated successfully by immunohistochemistry. ICPL is a valid method to identify differentially expressed proteins in rectal carcinoma tissue between poor vs. good responders to nCRT. The identified protein markers may act as selection criteria for nCRT in the future, but our preliminary findings must be reproduced and validated in a prospective cohort.
EVALuna2:6749

Identification of six new susceptibility loci for invasive epithelial ovarian cancer - Kuchenbaecker, Karoline B.; Ramus, Susan J.; Tyrer, Jonathan; Lee, Andrew; Shen, Howard C.; Beesley, Jonathan; Lawrenson, Kate; Mcguffog, Lesley; Healey, Sue; Lee, Janet M.; Spindler, Tassja J.; Lin, Yvonne G.; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) have identified 12 epithelial ovarian cancer (EOC) susceptibility alleles. The pattern of association at these loci is consistent in BRCA1 and BRCA2 mutation carriers who are at high risk of EOC. After imputation to 1000 Genomes Project data, we assessed associations of 11 million genetic variants with EOC risk from 15,437 cases unselected for family history and 30,845 controls and from 15,252 BRCA1 mutation carriers and 8,211 BRCA2 mutation carriers (3,096 with ovarian cancer), and we combined the results in a meta-analysis. This new study design yielded increased statistical power, leading to the discovery of six new EOC susceptibility loci. Variants at 1p36 (nearest gene, WNT4), 4q26 (SYNPO2), 9q34.2 (ABO) and 17q11.2 (ATAD5) were associated with EOC risk, and at 1p34.3 (RSPO1) and 6p22.1 (GPX6) variants were specifically associated with the serous EOC subtype, all with P < 5 × 10(-8). Incorporating these variants into risk assessment tools will improve clinical risk predictions for BRCA1 and BRCA2 mutation carriers.
EVALuna2:9273

Identification of ten variants associated with risk of estrogen-receptor-negative breast cancer - Milne, Roger L.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Beesley, Jonathan; Kar, Siddhartha; Lindstrom, Sara; Hui, Shirley; Lemacon, Audrey; Soucy, Penny; Dennis, Joe; Jiang, Xia; Rostamianfar, Asha; et al. (Nature Genetics, 2017)
Most common breast cancer susceptibility variants have been identified through genome-wide association studies (GWAS) of predominantly estrogen receptor (ER)-positive disease. We conducted a GWAS using 21,468 ER-negative cases and 100,594 controls combined with 18,908 BRCA1 mutation carriers (9,414 with breast cancer), all of European origin. We identified independent associations at P < 5 × 10-8 with ten variants at nine new loci. At P < 0.05, we replicated associations with 10 of 11 variants previously reported in ER-negative disease or BRCA1 mutation carrier GWAS and observed consistent associations with ER-negative disease for 105 susceptibility variants identified by other studies. These 125 variants explain approximately 16% of the familial risk of this breast cancer subtype. There was high genetic correlation (0.72) between risk of ER-negative breast cancer and breast cancer risk for BRCA1 mutation carriers. These findings may lead to improved risk prediction and inform further fine-mapping and functional work to better understand the biological basis of ER-negative breast cancer.
EVALuna2:9391

Identification of Two Genetic Loci Associated with Leukopenia after Chemotherapy in Patients with Breast Cancer - Fasching, Peter; Liu, Duan; Scully, Steve; Ingle, James N.; Lyra, Paulo C.; Rack, Brigitte; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Schneeweiss, Andreas; Tesch, Hans; Fehm, Tanja N.; et al. (Clinical Cancer Research, 2022)
Purpose: To identify molecular predictors of grade 3/4 neutropenic or leukopenic events (NLE) after chemotherapy using a genome-wide association study (GWAS). Experimental Design: A GWAS was performed on patients in the phase III chemotherapy study SUCCESS-A (n = 3,322). Genotyping was done using the Illumina HumanOmniExpress-12v1 array. Findings were functionally validated with cell culture models and the genotypes and gene expression of possible causative genes were correlated with clinical treatment response and prognostic outcomes. Results: One locus on chromosome 16 (rs4784750; NLRC5; P = 1.56E-8) and another locus on chromosome 13 (rs16972207; TNFSF13B; P = 3.42E-8) were identified at a genome-wide significance level. Functional validation revealed that expression of these two genes is altered by genotype-dependent and chemotherapy-dependent activity of two transcription factors. Genotypes also showed an association with disease-free survival in patients with an NLE. Conclusions: Two loci in NLRC5 and TNFSF13B are associated with NLEs. The involvement of theMHCI regulator NLRC5 implies the possible involvement of immuno-oncological pathways.
CRIS-Team Scopus Importer:2022-08-19

Identifying breast cancer patients at risk of relapse despite pathological complete response after neoadjuvant therapy - Huober, Jens; van Mackelenbergh, Marion; Schneeweiss, Andreas; Seither, Fenja; Blohmer, Jens Uwe; Denkert, Carsten; Tesch, Hans; Hanusch, Claus; Salat, Christoph; Rhiem, Kerstin; Solbach, Christine; Fasching, Peter; et al. (npj Breast Cancer, 2023)
This retrospective pooled analysis aims to identify factors predicting relapse despite a pathologic complete response (pCR) in patients with breast cancer (BC). 2066 patients with a pCR from five neoadjuvant GBG/AGO-B trials fulfill the inclusion criteria of this analysis. Primary endpoint is disease-free survival (DFS); secondary endpoints is distant DFS (DDFS) and overall survival (OS). After a median follow-up of 57.6 months, DFS is significantly worse for patients with positive lymph nodes (cN+ vs cN0 hazard ratio [HR] 1.94, 95%CI 1.48–2.54; p < 0.001). In patients with triple-negative tumors, lobular histology (lobular vs other HR 3.55, 95%CI 1.53–8.23; p = 0.003), and clinical nodal involvement (cN+ vs cN0 HR 2.45, 95%CI 1.59–3.79; p < 0.001) predict a higher risk of DFS events. Patients with HER2-positive cT3/4 tumors have a significantly higher risk of relapse (cT3/4 vs cT1 HR 2.07, 95%CI 1.06–4.03; p = 0.033). Initial tumor load and histological type predict relapse in patients with a pCR.
CRIS-Team Scopus Importer:2023-04-28

Immune-related gene expression predicts response to neoadjuvant chemotherapy but not additional benefit from pd-l1 inhibition in women with early triple-negative breast cancer - Sinn, Bruno V.; Loibl, Sibylle; Hanusch, Claus A.; Zahm, Dirk Michael; Sinn, Hans Peter; Untch, Michael; Weber, Karsten; Karn, Thomas; Becker, Clemens; Marme, Frederik; Schmitt, Wolfgang D.; Muller, Volkmar; et al. (Clinical Cancer Research, 2021)
Purpose: We evaluated mRNA signatures to predict response to neoadjuvant PD-L1 inhibition in combination with chemotherapy in early triple-negative breast cancer. Experimental Design: Targeted mRNA sequencing of 2,559 transcripts was performed in formalin-fixed, paraffin-embedded samples from 162 patients of the GeparNuevo trial. We focused on validation of four predefined gene signatures and differential gene expression analyses for new predictive markers. Results: Two signatures [GeparSixto signature (G6-Sig) and IFN signature (IFN-Sig)] were predictive for treatment response in a multivariate model including treatment arm [G6-Sig: OR, 1.558; 95% confidence interval (CI), 1.130–2.182; P ¼ 0.008 and IFN-Sig: OR, 1.695; 95% CI, 1.234–2.376; P ¼ 0.002), while the CYT metric predicted pathologic complete response (pCR) in the durvalumab arm, and the proliferation-associated gene signature in the placebo arm. Expression of PD-L1 mRNA was associated with better response in both arms, indicating that increased levels of PD-L1 are a general predictor of neoadjuvant therapy response. In an exploratory analysis, we identified seven genes that were higher expressed in responders in the durvalumab arm, but not the placebo arm: HLA-A, HLA-B, TAP1, GBP1, CXCL10, STAT1, and CD38. These genes were associated with cellular antigen processing and presentation and IFN signaling. Conclusions: Immune-associated signatures are associated with pCR after chemotherapy, but might be of limited use for the prediction of response to additional immune checkpoint blockade. Gene expressions related to antigen presentation and IFN signaling might be interesting candidates for further evaluation.
CRIS-Team Scopus Importer:2021-05-21

Immunological and molecular features of the tumor microenvironment of long-term survivors of ovarian cancer - Nelson, Brad H.; Hamilton, Phineas; Phung, Minh Tung; Milne, Katy; Harris, Bronwyn; Thornton, Shelby; Stevens, Donald; Kalaria, Shreena; Singh, Karanvir; Laumont, Céline M.; Moss, Elena; Alimujiang, Aliya; et al. (Journal of Clinical Investigation, 2024)
BACKGROUND. Despite an overall poor prognosis, about 15% of patients with advanced-stage tubo-ovarian high-grade serous carcinoma (HGSC) survive 10 or more years after standard treatment. METHODS. We evaluated the tumor microenvironment of this exceptional, understudied group using a large international cohort enriched for long-term survivors (LTS; 10+ years; n = 374) compared with mid-term (MTS; 5–7.99 years; n = 433) and short-term survivors (STS; 2–4.99 years; n = 416). Primary tumor samples were immunostained and scored for intraepithelial and intrastromal densities of 10 immune-cell subsets (including T cells, B cells, plasma cells, myeloid cells, PD-1+ cells, and PD-L1+ cells) and epithelial content. RESULTS. Positive associations with LTS compared with STS were seen for 9 of 10 immune-cell subsets. In particular, the combination of intraepithelial CD8+ T cells and intrastromal B cells showed near 5-fold increased odds of LTS compared with STS. All of these associations were stronger in tumors with high epithelial content and/or the C4/Differentiated molecular subtype, despite immune-cell densities generally being higher in tumors with low epithelial content and/or the C2/ Immunoreactive molecular subtype. CONCLUSION. The tumor microenvironment of HGSC LTS is distinguished by the intersection of T and B cell coinfiltration, high epithelial content, and C4/differentiated molecular subtype, features which may inspire new approaches to immunotherapy.
CRIS-Team Scopus Importer:2025-02-04

Impact - Implementing Patients' Competence in Oral Breast Cancer Therapy - A Randomized, Controlled Study of Standardized Patient Coaching Versus Patient Management According to Local Practice for Patients with HR Positive HER2 Negative Metastatic Breast Cancer Treated with Abemaciclib - Welslau, Manfred; Nabieva, Naiba; Decker, Thomas; Belleville, Erik; Knapp, Oliver; Häberle, Lothar; Fasching, Peter; Tesch, Hans (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Impact of body mass index (BMI) on prognostic and predictive value of stromal tumour-infiltrating lymphocytes (sTILs) in triple-negative breast cancer (TNBC): A pooled analysis of six neoadjuvant trials - Furlanetto, J.; Denkert, C.; Untch, M.; Sinn, B.; Lederer, B.; Schneeweiss, A.; Mueller, V.; Van Mackelenbergh, M.; Stickeler, E.; Fasching, Peter; Schem, C.; Karn, T.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Impact of CCND1 amplification on the prognosis of hormone receptor–positive, HER2-negative breast cancer patients—correlation of clinical and pathological markers - Hanf, Dorothea; Fasching, Peter; Gaß, Paul; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Häberle, Lothar; John, Nelson; Erber, Ramona; Press, Michael F.; Rübner, Matthias; Pöschke, Patrik (Breast Cancer Research and Treatment, 2024)
Purpose: The cyclin D1 gene (CCND1) encodes a key cell-cycle regulatory protein. Resistance to endocrine therapy is reportedly observed more often in patients with CCND1-amplified tumors. CCND1 amplification is known to be a driving event in breast cancer, but contradictory findings are reported for its association with prognosis. This study therefore investigated the prognostic value of CCND1 amplification in hormone receptor (HR)-positive breast cancer patients. Methods: A cohort of 894 unselected breast cancer patients from the Bavarian Breast Cancer Cases and Controls (BBCC) study was included. The CCND1 amplification rate was evaluated in tissue microarrays using fluorescence in situ hybridization. A CCND1/CEP11 ratio ≥ 2.0 was considered amplified. Statistical analysis was conducted on cases with ratios based on a range of 20–100 nuclei analyzed per case. A univariable Cox regression model was fitted with disease-free survival (DFS) and overall survival (OS). Results: CCND1 gene status was assessable in 511 patients. The CCND1 amplification rate was 12.9% (66 patients). Most patients with CCND1 amplification had luminal B-Like—(51.5%, n = 34) or luminal A-Like tumors (25.8%, n = 17), 13 patients with HER2-positive disease (19.7%) and only two patients had triple-negative tumors (3.0%). Survival analysis, focused on HR-positive, HER2-negative patients, showed no statistically significant differences in the DFS and OS with and without CCND1 amplification (P = 0.20 and 0.14, respectively, in the unadjusted analysis). Conclusions: CCND1 amplification is a recurring event in breast cancer, occurring most frequently in luminal B-like and HER2-amplified subtypes. A trend toward less favorable outcomes was observed among CCND1-amplified HR-positive, HER2-negative tumors.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Amplification; Breast cancer; CCND1; FISH; Prognosis

Impact of chemotherapy-induced ovarian failure (CIOF) on disease-free survival (DFS) and overall survival (OS) in young women with early breast cancer (EBC) - Furlanetto, J.; Nekljudova, V.; Schneeweiss, A.; Thode, C.; Denkert, C.; Untch, M.; Bassy, M.; Karn, T.; Fasching, Peter; Stickeler, E.; Schem, C.; Marme, F.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Impact of disease progression on health-related quality of life in patients with metastatic breast cancer in the PRAEGNANT breast cancer registry - Mueller, Volkmar; Nabieva, Naiba; Häberle, Lothar; Taran, Florin-Andrei; Hartkopf, Andreas D.; Volz, Bernhard; Overkamp, Friedrich; Brandl, Anna; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; et al. (BREAST, 2018)
OBJECTIVES: Improved progression-free survival is considered as treatment goal for patients with metastatic breast cancer (MBC) since it is assumed to delay or prevent deterioration of quality of life. Aim of our analysis was to examine the influence of disease progression on health-related quality of life (HRQoL). MATERIALS AND METHODS: The PRAEGNANT study comprises a real-life registry for patients with MBC. HRQoL was assessed with the EORTC-QLQ-C30 Version 3.0 questionnaire at study entry and every 3 months thereafter. The primary endpoint was minimally important deterioration (MID) in global HRQoL score by ≥ five points between baseline and any follow-up assessment. A logistic regression model was built with MID (yes/no) at a follow-up timepoint as outcome variable and several covariates as predictors. RESULTS: In total, 329 patients were included in this analysis, with disease progression in 63 patients. Concerning the primary study aim, progression status predicted MID of global HRQoL status in addition to the other covariates. The adjusted odds ratio for the effect of progression status on MID was 2.22 (95% CI: 1.04 - 4.73). Comparisons of mean differences of QoL domains/scales yielded no differences. CONCLUSIONS: We provide evidence that disease progression in patients with metastatic breast cancer in a real-world registry has a significant negative impact on HRQoL as measured by MID of HRQoL. This study emphasizes the relevance of avoiding progression and prolonging PFS to maintain QoL.
EVALuna2:36438

Impact of fibroblast growth factor receptor 1 (FGFR1) amplification on the prognosis of breast cancer patients - Erber, Ramona; Rübner, Matthias; Davenport, Simon; Hauke, Sven; Beckmann, Matthias; Hartmann, Arndt; Häberle, Lothar; Gaß, Paul; Press, Michael F.; Fasching, Peter (Breast Cancer Research and Treatment, 2020)
Purpose: Various aberrations in the fibroblast growth factor receptor genes FGFR1, FGFR2, and FGFR3 are found in different cancers, including breast cancer (BC). This study analyzed the impact of FGFR amplification on the BC prognosis. Methods: The study included 894 BC patients. The amplification rates of FGFR1, FGFR2, and FGFR3 were evaluated on tissue microarrays using fluorescence in situ hybridization (FISH). Associations between these parameters and prognosis were analyzed using multivariate Cox regression analyses. Results: FGFR1 FISH was assessable in 503 samples, FGFR2 FISH in 447, and FGFR3 FISH in 562. The FGFR1 amplification rate was 6.6% (n = 33). Increased FGFR2 copy numbers were seen in 0.9% (n = 4); only one patient had FGFR3 amplification (0.2%). Most patients with FGFR1 amplification had luminal B-like tumors (69.7%, n = 23); only 32.6% (n = 153) of patients without FGFR1 amplification had luminal B-like BC. Other patient and tumor characteristics appeared similar between these two groups. Observed outcome differences between BC patients with and without FGFR1 amplification did not achieve statistical significance; however, there was a trend toward poorer distant metastasis-free survival in BC patients with FGFR1 amplification (HR = 2.08; 95% CI 0.98 to 4.39, P = 0.05). Conclusion: FGFR1 amplification occurs most frequently in patients with luminal B-like BC. The study showed a nonsignificant correlation with the prognosis, probably due to the small sample size. Further research is therefore needed to address the role of FGFR1 amplifications in early BC patients. FGFR2 and FGFR3 amplifications are rare in patients with primary BC.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Amplification; Breast cancer; FGFR1; FGFR2; FGFR3; FISH; Prognosis

Impact of nab-paclitaxel dose reduction on survival of the randomized phase III GeparSepto trial comparing neoadjuvant chemotherapy of weekly nab-paclitaxel (nP) with solvent-based paclitaxel (P) followed by anthracycline/cyclophosphamide for patients with early breast cancer (BC) - Untch, M.; Jackisch, C.; Schneeweiss, A.; Schmatloch, S.; Aktas, B.; Denkert, C.; Schem, C.; Wiebringhaus, H.; Kuemmel, S.; Rhiem, K.; Warm, M.; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Impact of objective response (OR) on patient-reported outcomes (PRO) in patients (pts) with advanced breast cancer (ABC) and a germline BRCA1/2 (gBRCA) mutation in the phase III EMBRACA trial - Fasching, Peter; Quek, R. G. W.; Bhattacharyya, H.; Hurvitz, S. A.; Rugo, H. S.; Ettl, J. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-13

Implementation and Feasibility of Electronic Patient-Reported Outcome (ePRO) Data Entry in the PRAEGNANT Real-Time Advanced and Metastatic Breast Cancer Registry - Wallwiener, Markus; Heindl, Felix; Brucker, Sara Y.; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer.As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three standardized Internet-based questionnaires (EQ 5D 5 L, CES-D and IPAQ). Feasibility was assessed by the staff members who assigned the user accounts by the patients. The completeness of the questionnaires was also assessed.Fifteen of 17 patients who were asked agreed to participate to complete the PRO questionnaires (EQ-5D-5L and CES-D). However, the IPAQ (physical activity) questionnaire was only validly completed by 9 patients. Feasibility was ranked better by the physicians and dedicated clinical trial staff than by the nursing staff.Incorporating ePRO questionnaires into an advanced breast cancer registry is feasible, and no major hurdles were reported. Involving stakeholders from the start, the application is tailored to the capacities and abilities of both patients and clinical staff. The patients' compliance was better with some questionnaires, but others may present difficulties.
EVALuna2:176

Implementation of an Electronic Patient-Reported Outcome App for Health-Related Quality of Life in Breast Cancer Patients: Evaluation and Acceptability Analysis in a Two-Center Prospective Trial - Graf, Joachim; Sickenberger, Nina; Brusniak, Katharina; Matthies, Lina Maria; Deutsch, Thomas M.; Simoes, Elisabeth; Plappert, Claudia; Keilmann, Lucia; Hartkopf, Andreas; Walter, Christina Barbara; Hahn, Markus; Engler, Tobias; et al. (Journal of Medical Internet Research, 2022)
Background: One in eight women is diagnosed with breast cancer in the course of their life. As systematic palliative treatment has only a limited effect on survival rates, the concept of health-related quality of life (HRQoL) was developed for measurement of patient-centered outcomes. Various studies have already demonstrated the reliability of paper-based patient-reported outcome (pPRO) and electronic patient-reported outcome (ePRO) surveys and that the 2 means of assessment are equally valid. Objective: The aim of this study was to analyze the acceptance and evaluation of a tablet-based ePRO app for breast cancer patients and to examine its suitability, effort, and difficulty in the context of HRQoL and sociodemographic factors. Methods: Overall, 106 women with adjuvant or advanced breast cancer were included in a 2-center study at 2 major university hospitals in Germany. Patients were asked to answer HRQoL and PRO questionnaires both on a tablet on-site using a specific eHealth assessment website and on paper. The suitability, effort, and difficulty of the app and self-reported technical skills were also assessed. Only the results of the electronically acquired data are presented here. The results of the reliability of the pPRO data have already been published elsewhere. Results: Patients regarded the ePRO assessment as more suitable (80/106, 75.5%), less stressful (73/106, 68.9%), and less difficult (69/106, 65.1%) than pPRO. The majority of patients stated that ePRO assessment improves health care in hospitals (87/106, 82.1%). However, evaluation of ePROs depended on the level of education (P=.003) in the dimensions of effort and difficulty (regression analysis). The app was rated highly in all categories. HRQoL data and therapy setting did not show significant correlations with the app’s evaluation parameters. Conclusions: The results indicate that ePRO surveys are feasible for measuring HRQoL in breast cancer patients and that those patients prefer ePRO assessment to pPRO assessment. It can also be seen that patients consider ePRO assessment to improve hospital health care. However, studies with larger numbers of patients are needed to develop apps that address the needs of patients with lower levels of education and technical skills.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Acceptability; Breast cancer; EHealth; Electronic patient-reported outcomes; Evaluation

Implementation of CDK4/6 Inhibitors and its Influence on the Treatment Landscape of Advanced Breast Cancer Patients – Data from the Real-World Registry PRAEGNANT - Engler, Tobias; Fasching, Peter; Lueftner, Diana; Hartkopf, Andreas D.; Mueller, Volkmar; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Wallwiener, Markus; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Background Comprehensive data from prospective clinical trials have led to a high level of evidence establishing CDK4/6 inhibitors in combination with endocrine treatment (CDK4/6i + ET) as a standard for the treatment of HER2-negative, hormone receptor-positive (HER2- HR+) breast cancer patients in the first-line advanced therapy setting. Data on patient populations that have been treated in the real-world setting may provide an insight into changes of patient characteristics and prognosis over time. Methods The data were extracted from the prospective real-world registry PRAEGNANT (NCT02338167). Patients had to have HER2- HR+ advanced breast cancer in the first-line metastatic setting. The chosen therapies were described as well as progression-free survival (PFS) and overall survival (OS) in relation to the given therapies and time periods during which they were indicated. Results CDK4/6 inhibitors have been rapidly implemented since their introduction in November 2016. In recent years (2018-2022), about 70-80% of the patient population have been treated with CDK4/6 inhibitors, while endocrine monotherapy was given to about 10% and chemotherapy to about 15% of all patients. The prognosis was worst in patients treated with chemotherapy. Recently, mainly patients with a good prognosis are being treated with endocrine monotherapy, and patients who are treated with chemotherapy have an unfavorable prognosis. The PFS and OS of patients treated with CDK4/6i + ET have remained similar over time despite changes in patient characteristics. Conclusion A treatment with CDK4/6i + ET has rapidly become the therapy standard for patients in the first-line advanced breast cancer setting. After the implementation of CDK4/6i + ET, endocrine monotherapy is only given to patients with a very favorable prognosis, while chemotherapy is provided to patients with a rather unfavorable prognosis. These changes in patient characteristics did not seem to influence the prognosis of patients treated with CDK4/6i + ET.
CRIS-Team Scopus Importer:2022-07-22
Keywords: advanced breast cancer; CDK4/6 inhibitor; chemotherapy; endocrine treatment; real world data

Implementation of machine learning into clinical breast MRI: Potential for objective and accurate decision-making in suspicious breast masses - Ellmann, Stephan; Wenkel, Evelyn; Dietzel, Matthias; Bielowski, Christian; Vesal, Sulaiman; Maier, Andreas; Hammon, Matthias; Janka, Rolf Matthias; Fasching, Peter; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Uder, Michael; et al. (PLoS ONE, 2020)
We investigated whether the integration of machine learning (ML) into MRI interpretation can provide accurate decision rules for the management of suspicious breast masses. A total of 173 consecutive patients with suspicious breast masses upon complementary assessment (BI-RADS IV/V: n = 100/76) received standardized breast MRI prior to histological verification. MRI findings were independently assessed by two observers (R1/R2: 5 years of experience/no experience in breast MRI) using six (semi-)quantitative imaging parameters. Interobserver variability was studied by ICC (intraclass correlation coefficient). A polynomial kernel function support vector machine was trained to differentiate between benign and malignant lesions based on the six imaging parameters and patient age. Ten-fold cross-validation was applied to prevent overfitting. Overall diagnostic accuracy and decision rules (rule-out criteria) to accurately exclude malignancy were evaluated. Results were integrated into a web application and published online. Malignant lesions were present in 107 patients (60.8%). Imaging features showed excellent interobserver variability (ICC: 0.81–0.98) with variable diagnostic accuracy (AUC: 0.65–0.82). Overall performance of the ML algorithm was high (AUC = 90.1%; BI-RADS IV: AUC = 91.6%). The ML algorithm provided decision rules to accurately rule-out malignancy with a false negative rate <1% in 31.3% of the BI-RADS IV cases. Thus, integration of ML into MRI interpretation can provide objective and accurate decision rules for the management of suspicious breast masses, and could help to reduce the number of potentially unnecessary biopsies.<br

Improved HER2 Tumor Segmentation with Subtype Balancing Using Deep Generative Networks - Öttl, Mathias; Steenpaß, Jana; Rübner, Matthias; Geppert, Carol-Immanuel; Qiu, Jingna; Wilm, Frauke; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Proceedings - International Symposium on Biomedical Imaging, 2023)
Tumor segmentation in histopathology images is often complicated by its composition of different histological subtypes and class imbalance. Oversampling subtypes with low prevalence features is not a satisfactory solution since it eventually leads to overfitting. We propose to create synthetic images with semantically-conditioned deep generative networks and to combine subtype-balanced synthetic images with the original dataset to achieve better segmentation performance. We show the suitability of Generative Adversarial Networks (GANs) and especially diffusion models to create realistic images based on subtype-conditioning for the use case of HER2-stained histopathology. Additionally, we show the capability of diffusion models to conditionally inpaint HER2 tumor areas with modified subtypes. Combining the original dataset with the same amount of diffusion-generated images increased the tumor Dice score from 0.833 to 0.854 and almost halved the variance between the HER2 subtype recalls. These results create the basis for more reliable automatic HER2 analysis with lower performance variance between individual HER2 subtypes.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Diffusion Models; Generative Models; HER2; Histopathology; Segmentation; Subtypes

Improving quality of care for cancer patients through oncological second opinions in a Comprehensive Cancer Center: adherence to second-opinion therapy recommendations - Schulmeyer, Carla; Fasching, Peter; Beckmann, Matthias; Häberle, Lothar; Golcher, Henriette; Goebell, Peter; Pöschke, Patrik; Emons, Julius (Journal of Cancer Research and Clinical Oncology, 2025)
Purpose: Receiving treatment in certified oncological centers and obtaining a second medical opinion has been proven to enhance both the quality and cost-effectiveness of care for oncological patients. Interdisciplinary care optimizes the treatment of oncological patients by validating the diagnosis and treatment recommendation, emphasizes translational research, and applies oncological therapies in a more target-oriented manner. This study aims to examine the extent of patient adherence to second medical opinions provided at the Comprehensive Cancer Center Erlangen–Metropolitan Area Nuremberg (CCC Erlangen-EMN) and investigates how specific patient characteristics such as age, gender, and type of cancer diagnosis influence the likelihood of adhering to a second opinion. Methods: This is a prospective, single-center observational study supported by the local statutory health-insurance body (Allgemeine Ortskrankenkasse, AOK). A total of 584 male and female patients with cancer in the fields of urology, gynecology, gastroenterology, or sarcoma, seeking a second medical opinion were assessed for their adherence to the second opinion. Levels of adherence in patient subgroups were compared using appropriate statistical tests. Correction for multiple testing was not performed, due to the exploratory nature of the study. Results: Almost 75% of the patients adhered to the second opinion recommendations and an additional 10% partially followed them. Men adhered to the second opinion recommendation slightly more often (79.1%) than women (70.7%; chi-square test, P = 0.01). At 83%, second-opinion adherence was highest among patients who had received an incomplete but guideline-compliant first opinion. If the first opinion was not guideline-compliant, about 67% adhered to the second opinion. Adherence to second opinions was not significantly influenced by whether the initial therapy recommendation adhered to guidelines (Fisher’s test, P = 0.16 for all departments, P = 0.27 for the gynecology department). Most patients adhered to the second opinion after primary therapy (92.9%). Conclusions: More than two-thirds of patients ultimately followed the recommendation provided in the second opinion. The results of this study enhance our understanding of patient adherence to medical advice and treatment regimens. This study demonstrated that the majority of patients adhere to second opinions and highlighted the feasibility of easy access to second opinions from a certified cancer center. Women adhered slightly less to second opinions than men. More detailed and comprehensive therapy recommendations could potentially enhance adherence rates in the future.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Adherence; Guideline; Gynecological cancer; Second medical opinion

Improving the Quality of Care for Cancer Patients through Oncological Second Opinions in a Comprehensive Cancer Center: Feasibility of Patient-Initiated Second Opinions through a Health-Insurance Service Point - Schulmeyer, Carla; Beckmann, Matthias; Fasching, Peter; Häberle, Lothar; Golcher, Henriette; Kunath, Frank; Wullich, Bernd; Emons, Julius (Diagnostics, 2023)
Background: To improve the quality and cost-effectiveness of care, cancer patients can obtain a second medical opinion on their treatment. Validation of the diagnostic procedure (e.g., imaging), diagnosis, and treatment recommendation allows oncological therapy to be applied in a more targeted way, optimizing interdisciplinary care. This study describes patients who received second opinions at the Comprehensive Cancer Center for Erlangen–Nuremberg metropolitan area in Germany over a 6-year period, as well as the amount of time spent on second-opinion counseling. Methods: This prospective, descriptive, single-center observational study included 584 male and female cancer patients undergoing gynecological, urologic, or general surgery who sought a second medical opinion. The extent to which the first opinion complied with standard guidelines was assessed solely descriptively. Results: The first opinion was in accordance with the guidelines and complete in 54.5% of the patients, and guideline compliant but incomplete in 13.2%. The median time taken to form a second opinion was 225 min, and the cancer information service was contacted by patients an average of eight times. Conclusions: The initial opinion was guideline compliant and complete in every second case. Without a second opinion, the remaining patients would have been denied a guideline-compliant treatment recommendation. Obtaining a second opinion gives patients an opportunity to receive a guideline-compliant treatment recommendation and enables them to benefit from newer, individualized therapeutic approaches in clinical trials. Establishing patient-initiated second opinions via central contact points appears to be a feasible option for improving guideline compliance.
CRIS-Team Scopus Importer:2023-11-24
Keywords: gastrointestinal cancer; gynecologic cancer; sarcoma; second medical opinion; urologic cancer

Indirect Treatment Comparison between Ribociclib Combined with Non-Steroidal Aromatase Inhibitors and Ovarian Function Suppression vsTamoxifen in Premenopausal Women with Early Breast Cancer Indirekter Behandlungsvergleich von Ribociclib kombiniert mit nichtsteroidalen Aromatasehemmern und ovarieller Funktionsunterdrückung mit Tamoxifen bei prämenopausalen Frauen mit Brustkrebs im Frühstadium - Lüftner, Diana; Banys-Paluchowski, Maggie; Hartkopf, Andreas D.; Hörner, Manuel; Janni, Wolfgang; Langanke, Dagmar; Müller, Volkmar; Schneeweiss, Andreas; Schmidt, Marcus; Thill, Marc; Untch, Michael; Wöckel, Achim; et al. (Geburtshilfe und Frauenheilkunde, 2025)
Background This study provides an indirect treatment comparison of ribociclib combined with non-steroidal aromatase inhibitors and ovarian function suppression (ribociclib + NSAI + OFS) vs. a frequently used treatment option in German clinical routine (tamoxifen ± OFS) in premenopausal patients with HR-positive (HR+), HER2-negative (HER2-) early breast cancer (BC). Material and Methods Data on premenopausal women treated with ribociclib and tamoxifen were derived from the NATALEE clinical trial (NCT03701334) and the retrospective German data collection CLEAR-B, respectively. NATALEE trial eligibility criteria were applied to the CLEAR-B dataset. Standardized mortality ratio weights were used for propensity score (PS) adjustment to balance study populations. All hazard ratios (HR) were calculated based on a 4-year-observation period for both treatment arms. Effectiveness endpoints comprised invasive and distant disease-free survival (iDFS, dDFS), recurrence-free survival (RFS), and overall survival (OS). Safety-related endpoints were treatment termination (TT) and toxicity-related TT (TTtox). For safety comparisons, the ribociclib arm was divided into groups that discontinued ribociclib + NSAI + OFS or ribociclib only. Results Significant beneficial effects favoring ribociclib + NSAI + OFS (n = 1115) over tamoxifen ± OFS (n = 822) were observed for all effectiveness outcomes (iDFS [HR = 0.5 (95% CI 0.35; 0.71); p < 0.01]; dDFS [HR = 0.52 (95% CI 0.35; 0.77); p = 0.01], RFS [HR = 0.42 (95% CI 0.29; 0.62); p < 0.01], OS [HR = 0.34 (95% CI 0.18; 0.63); p = 0.01]) during the 4-year-observation period. The effect of early treatment discontinuation showed no significant differences between ribociclib + NSAI + OFS and tamoxifen ± OFS (TT-a: HR = 1.2 [95% CI: 0.71; 2.01], p = 0.48; TTtox-a: HR = 0.54 [95% CI 0.22; 1.30], p = 0.23). Conclusion In this retrospective analysis, ribociclib + NSAI + OFS demonstrated advantages across all effectiveness endpoints, including OS, in premenopausal women with HR+, HER2- early BC, without increasing overall treatment discontinuation rates compared to tamoxifen ± OFS.
CRIS-Team Scopus Importer:2025-04-18
Keywords: early breast cancer; HER2-negative; HR-positive; indirect treatment comparison; ribociclib

Inferred Immune-Cell Activity Is an Independent Predictor of HER2-Negative Breast Cancer Prognosis and Response to Paclitaxel-Based Therapy in the GeparSepto Trial - Fasching, Peter; Szeto, Christopher; Denkert, Carsten; Benz, Stephen; Weber, Karsten; Spilman, Patricia; Budczies, Jan; Schneeweiss, Andreas; Stickeler, Elmar; Schmatloch, Sabine; Jackisch, Christian; Karn, Thomas; et al. (Clinical Cancer Research, 2023)
PURPOSE: Tumor microenvironment (TME) immune markers have been correlated with both response to neoadjuvant therapy and prognosis in patients with breast cancer. Here, immune-cell activity of breast cancer tumors was inferred by expression-based analysis to determine if it is prognostic and/or predictive of response to neoadjuvant paclitaxel-based therapy in the GeparSepto (G7) trial (NCT01583426). EXPERIMENTAL DESIGN: Pre-study biopsies from 279 patients with HER2-negative breast cancer in the G7 trial underwent RNA-seq-based profiling of 104 immune-cell-specific genes to assess inferred Immune Cell Activity (iICA) of 23 immune-cell types. Hierarchical clustering was used to classify tumors as iICA "hot," "warm," or "cold" by comparison of iICA in the G7 cohort relative to that of 1,467 samples from a tumor database established by Nantomics LLC. Correlations between iICA cluster, pathology-assessed tumor-infiltrating lymphocytes (TIL), and hormone receptor (HR) status for pathologic complete response (pCR), disease-free survival (DFS), and overall survival (OS) were determined. RESULTS: iICA cluster correlated with TIL levels. The highest pCR rates were observed in hot cluster tumors, and those with relatively higher TILs. Greater inferred activity of several T-cell types was significantly associated with pCR and survival. DFS and OS were prolonged in patients with hot or warm cluster tumors, the latter particularly for HR negative tumors, even if TILs were relatively low. CONCLUSIONS: Overall, TIL level better predicted pCR, but iICA cluster better predicted survival. Differences in associations between TILs, cluster, pCR, and survival were observed for HR-positive tumors versus HR-negative tumors, suggesting expanded study of the implication of these findings is warranted.
CRIS-Team Scopus Importer:2023-07-21

Influence of CDK4/6 inhibitors on the peripheral immune response in hormone receptor-positive breast cancer - Peuker, C. A.; Yaghobramzi, S.; Grunert, C.; Keilholz, L.; Hennig, S.; Schaper, S.; Brucker, S.; Decker, T.; Fasching, Peter; Fehm, T.; Janni, W.; Kuemmel, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Influence of Family History of Breast or Ovarian Cancer on Pathological Complete Response and Long-Term Prognosis in Breast Cancer Patients Treated with Neoadjuvant Chemotherapy - Wunderle, Marius; Häberle, Lothar; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Emons, Julius; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (Breast Care, 2020)
Purpose: In breast cancer, a pathological complete response (pCR) has been described as generally resulting in a favorable prognosis. However, there are subgroups, such as patients with a mutation in BRCA1 or BRCA2,in which the effect of pCR on the prognosis is suspected to be weaker. Patients with a family history of breast and/or ovarian cancer may therefore react differently in relation to pCR and prognosis, and this is investigated in this study. Patients and Methods: Breast cancer patients were identified from a clinical breast cancer registry. The study subjects had been treated with neoadjuvant chemotherapy from 2001 to 2018 and their pathological and clinical information as well as medical family history were available. They were considered to have a positive family history if they had at least 1 first-degree relative with breast and/or ovarian cancer. Multivariate logistic regression analyses were performed to study the association between family history, pCR (ypT0; ypN0), and disease-free survival (DFS). Results: Of 1,480 patients, 228 (15.4%) had a positive family history. The pCR rates were 24.9% in all patients, and 24.4% and 27.6% in those without/with a family history, respectively. Family history was not associated with a higher pCR rate (adjusted odds ratio [OR] 1.23; 95% confidence interval [CI] 0.85-1.76; p = 0.27) or a different disease-free survival (DFS; adjusted hazard ratio [HR] 1.15; 95% CI 0.88-1.52; p = 0.30). pCR did not affect the prognosis differently in relation to family history. Conclusions: In this retrospective analysis, family history was not associated with pCR and DFS. pCR improved survival, independently of family history.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Breast cancer; Family history; Neoadjuvant chemotherapy; Ovarian cancer; Pathological complete response; Prognosis

Influence of patient and tumor characteristics on early therapy persistence with letrozole in postmenopausal women with early breast cancer: results of the prospective Evaluate-TM study with 3941 patients - Nabieva, Naiba; Kellner, S.; Fehm, T.; Häberle, Lothar; De Waal, J.; Rezai, M.; Baier, B.; Baake, G.; Kolberg, H. -C.; Guggenberger, M.; Warm, M.; Harbeck, N.; et al. (Annals of Oncology, 2018)
Patients' compliance and persistence with endocrine treatment has a significant effect on the prognosis in early breast cancer (EBC). The purpose of this analysis was to identify possible reasons for non-persistence, defined as premature cessation of therapy, on the basis of patient and tumor characteristics in individuals receiving adjuvant treatment with letrozole.The EvAluate-TM study is a prospective, multicenter, noninterventional study in which treatment with the aromatase inhibitor letrozole was evaluated in postmenopausal women with hormone receptor-positive EBC in the early therapy phase. Treatment persistence was evaluated at two pre-specified study visits after 6 and 12 months. As a measure of early therapy persistence the time from the start to the end of treatment (TTEOT) was analyzed. Cox regression analyses were carried out to identify patient characteristics and tumor characteristics predicting TTEOT.Out of the total population of 3941 patients with EBC, 540 (13.7%) events involving treatment cessation unrelated to disease progression were observed. This was due to drug-related toxicity in the majority of cases (73.5%). Persistence rates were 92.2%, 86.9%, and 86.3% after 6, 12, and 15 months, respectively. The main factors influencing premature treatment discontinuation were older age [hazard ratio (HR) 1.02/year], comorbidities (HR 1.06 per comorbidity), low body mass index, and lower tumor grade (HR 0.85 per grade unit).These results support the view that older, multimorbid patients with low tumor grade and low body mass index are at the greatest risk for treatment discontinuation and might benefit from compliance and support programs.
EVALuna2:51618

Influence of patient and tumor characteristics on therapy persistence with letrozole in postmenopausal women with advanced breast cancer: results of the prospective observational EvAluate-TM study - Wallwiener, Markus; Nabieva, Naiba; Feisst, Manuel; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; et al. (BMC Cancer, 2019)
BackgroundTreatment of postmenopausal, hormone receptor-positive metastatic breast cancer (MBC) patients varies despite clear therapy guidelines, favoring endocrine treatment (ET). Aim of this study was to analyze persistence of palliative aromatase inhibitor (AI) monotherapy in MBC patients.MethodsEvAluate-TM is a prospective, multicenter, noninterventional study to evaluate treatment with letrozole in postmenopausal women with hormone receptor-positive breast cancer. To assess therapy persistence, defined as the time from therapy start to the end of the therapy (TTEOT), two pre-specified study visits took place after 6 and 12months. Competing risk survival analyses were performed to identify patient and tumor characteristics that predict TTEOT.ResultsOut of 200 patients, 66 patients terminated treatment prematurely, 26 (13%) of them due to causes other than disease progression. Persistence rate for reasons other than progression at 12months was 77.7%. Persistence was lower in patients who reported any adverse event (AE) in the first 30days of ET (89.5% with no AE and 56% with AE). Furthermore, patients had a lower persistence if they reported compliance problems in the past before letrozole treatment.ConclusionsDespite suffering from a life-threatening disease, AEs of an AI will result in a relevant number of treatment terminations that are not related to progression. Some subgroups of patients have very low persistence rates. Especially with regard to novel endocrine combination therapies, these data imply that some groups of patients will need special attention to guide them through the therapy process.Trial registrationClinical Trials Number: CFEM345DDE19
CRIS-Team WoS Importer:2019-07-09

Influence of PIK3CA mutations on breast cancer proliferation, lymphocyte infiltration and clinical outcome: Pooled analysis of 484 patients from three prospective multicentre GBG trials - Jank, P.; Loibl, S.; Fasching, Peter; Karn, T.; Marme, F.; Mueller, V.; Schem, C.; Stickeler, E.; Lederer, B.; Denkert, C. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-13

Influence of side-effects on early therapy persistence with letrozole in post-menopausal patients with early breast cancer: Results of the prospective EvAluate-TM study - Nabieva, Naiba; Fehm, T.; Häberle, Lothar; De Waal, J.; Rezai, M.; Baier, B.; Baake, G.; Kolberg, H. -C.; Guggenberger, M.; Warm, M.; Harbeck, N.; Wuerstlein, R.; et al. (European Journal of Cancer, 2018)
Endocrine treatment (ET) with an aromatase inhibitor (AI) is the treatment of choice in post-menopausal patients with hormone receptor-positive early breast cancer (EBC). However, adverse events (AEs) often lead to treatment discontinuation. This analysis aimed to identify side-effects that lead to patients failing to persist with letrozole treatment.Post-menopausal hormone receptor-positive EBC patients starting ET with letrozole were enroled in EvAluate-TM, a non-interventional study. Information regarding treatment compliance and persistence was gathered in months 6 and 12. Persistence was defined as the time from 30 d after the start to the end of treatment. The influence on persistence of musculoskeletal syndrome, menopausal disorder, sleep disorder and other AEs within the first 30 d was analysed using Cox regression analyses.Among 3887 patients analysed, the persistence rate after 12 months was >85%. In all, 568 patients (14.6%) discontinued the treatment, 358 of whom (63.0%) did so only because of side-effects. The main AEs influencing persistence were musculoskeletal symptoms (hazard ratio [HR] 2.55; 95% confidence interval [CI], 1.90-3.42), sleep disorders (HR 1.95; 95% CI, 1.41-2.70) and other AEs (HR 2.03; 95% CI, 1.51-2.73). Menopausal disorder was not associated with non-persistence (HR 1.17; 95% CI, 0.74-1.84).These results suggest that side-effects of AIs such as musculoskeletal syndrome and sleep disorder lead to ET discontinuation within the first treatment year in significant numbers of EBC patients. Compliance programmes adapted for subgroups that are at risk for early non-persistence might help to ensure the recommended therapy duration.CFEM345DDE19.
EVALuna2:51279

Influence of the Family Anamnesis of Breast or Ovarian Cancer on the pathological Complete Remission and the Prognosis in Patients with Breast Cancer after neoadjuvant Chemotherapy - Gaß, Paul; Haberle, L.; Hein, Alexander; Jud, Sebastian; Lux, M. P.; Hack, Caroline; Emons, J.; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Inherited mutations in 17 breast cancer susceptibility genes among a large triple-negative breast cancer cohort unselected for family history of breast cancer - Couch, Fergus J.; Hart, Steven N.; Sharma, Priyanka; Toland, Amanda Ewart; Wang, Xianshu; Miron, Penelope; Olson, Janet E.; Godwin, Andrew K.; Pankratz, V. Shane; Olswold, Curtis; Slettedahl, Seth; Hallberg, Emily; et al. (Journal of Clinical Oncology, 2015)
Recent advances in DNA sequencing have led to the development of breast cancer susceptibility gene panels for germline genetic testing of patients. We assessed the frequency of mutations in 17 predisposition genes, including BRCA1 and BRCA2, in a large cohort of patients with triple-negative breast cancer (TNBC) unselected for family history of breast or ovarian cancer to determine the utility of germline genetic testing for those with TNBC.Patients with TNBC (N = 1,824) unselected for family history of breast or ovarian cancer were recruited through 12 studies, and germline DNA was sequenced to identify mutations.Deleterious mutations were identified in 14.6% of all patients. Of these, 11.2% had mutations in the BRCA1 (8.5%) and BRCA2 (2.7%) genes. Deleterious mutations in 15 other predisposition genes were detected in 3.7% of patients, with the majority observed in genes involved in homologous recombination, including PALB2 (1.2%) and BARD1, RAD51D, RAD51C, and BRIP1 (0.3% to 0.5%). Patients with TNBC with mutations were diagnosed at an earlier age (P < .001) and had higher-grade tumors (P = .01) than those without mutations.Deleterious mutations in predisposition genes are present at high frequency in patients with TNBC unselected for family history of cancer. Mutation prevalence estimates suggest that patients with TNBC, regardless of age at diagnosis or family history of cancer, should be considered for germline genetic testing of BRCA1 and BRCA2. Although mutations in other predisposition genes are observed among patients with TNBC, better cancer risk estimates are needed before these mutations are used for clinical risk assessment in relatives.
EVALuna2:9246

Inherited variants affecting RNA editing may contribute to ovarian cancer susceptibility: results from a large-scale collaboration - Permuth, Jennifer B.; Reid, Brett; Earp, Madalene; Chen, Y. Ann; Monteiro, Alvaro N. A.; Chen, Zhihua; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Lambrechts, Diether; Vanderstichele, Adriaan; Van Niewenhuyse, Els; et al. (Oncotarget, 2016)
RNA editing in mammals is a form of post-transcriptional modification in which adenosine is converted to inosine by the adenosine deaminases acting on RNA (ADAR) family of enzymes. Based on evidence of altered ADAR expression in epithelial ovarian cancers (EOC), we hypothesized that single nucleotide polymorphisms (SNPs) in ADAR genes modify EOC susceptibility, potentially by altering ovarian tissue gene expression. Using directly genotyped and imputed data from 10,891 invasive EOC cases and 21,693 controls, we evaluated the associations of 5,303 SNPs in ADAD1, ADAR, ADAR2, ADAR3, and SND1. Unconditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI), with adjustment for European ancestry. We conducted gene-level analyses using the Admixture Maximum Likelihood (AML) test and the Sequence-Kernel Association test for common and rare variants (SKAT-CR). Association analysis revealed top risk-associated SNP rs77027562 (OR (95% CI)= 1.39 (1.17-1.64), P=1.0x10-4) in ADAR3 and rs185455523 in SND1 (OR (95% CI)= 0.68 (0.56-0.83), P=2.0x10-4). When restricting to serous histology (n=6,500), the magnitude of association strengthened for rs185455523 (OR=0.60, P=1.0x10-4). Gene-level analyses revealed that variation in ADAR was associated (P<0.05) with EOC susceptibility, with PAML=0.022 and PSKAT-CR=0.020. Expression quantitative trait locus analysis in EOC tissue revealed significant associations (P<0.05) with ADAR expression for several SNPs in ADAR, including rs1127313 (G/A), a SNP in the 3' untranslated region. In summary, germline variation involving RNA editing genes may influence EOC susceptibility, warranting further investigation of inherited and acquired alterations affecting RNA editing.
EVALuna2:33315

Inherited variants in the inner centromere protein (INCENP) gene of the chromosomal passenger complex contribute to the susceptibility of ER-negative breast cancer - Kabisch, Maria; Bermejo, Justo Lorenzo; Duennebier, Thomas; Ying, Shibo; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; Darabi, Hatef; et al. (Carcinogenesis, 2015)
The chromosomal passenger complex (CPC) plays a pivotal role in the regulation of cell division. Therefore, inherited CPC variability could influence tumor development. The present candidate gene approach investigates the relationship between single nucleotide polymorphisms (SNPs) in genes encoding key CPC components and breast cancer risk. Fifteen SNPs in four CPC genes (INCENP, AURKB, BIRC5 and CDCA8) were genotyped in 88 911 European women from 39 case-control studies of the Breast Cancer Association Consortium. Possible associations were investigated in fixed-effects meta-analyses. The synonymous SNP rs1675126 in exon 7 of INCENP was associated with overall breast cancer risk [per A allele odds ratio (OR) 0.95, 95% confidence interval (CI) 0.92-0.98, P = 0.007] and particularly with estrogen receptor (ER)-negative breast tumors (per A allele OR 0.89, 95% CI 0.83-0.95, P = 0.0005). SNPs not directly genotyped were imputed based on 1000 Genomes. The SNPs rs1047739 in the 3' untranslated region and rs144045115 downstream of INCENP showed the strongest association signals for overall (per T allele OR 1.03, 95% CI 1.00-1.06, P = 0.0009) and ER-negative breast cancer risk (per A allele OR 1.06, 95% CI 1.02-1.10, P = 0.0002). Two genotyped SNPs in BIRC5 were associated with familial breast cancer risk (top SNP rs2071214: per G allele OR 1.12, 95% CI 1.04-1.21, P = 0.002). The data suggest that INCENP in the CPC pathway contributes to ER-negative breast cancer susceptibility in the European population. In spite of a modest contribution of CPC-inherited variants to the total burden of sporadic and familial breast cancer, their potential as novel targets for breast cancer treatment should be further investigated.
EVALuna2:9268

Inhibition of adhesion, proliferation, and invasion of primary endometriosis and endometrial stromal and ovarian carcinoma cells by a nonhyaluronan adhesion barrier gel - Renner, Stefan; Strissel, Pamela; Beckmann, Matthias; Lermann, Johannes; Burghaus, Stefanie; Hackl, Janina; Fasching, Peter; Strick, Reiner (BioMed Research International, 2015)
Endometriosis is a chronic disease of women in the reproductive age, defined as endometrial cells growing outside of the uterine cavity and associated with relapses. Relapses are hypothesized to correlate with incomplete surgical excision or result from nonrandom implantation of new endometrial implants in adjacent peritoneum. Thus, surgical excision could lead to free endometriotic cells or tissue residues, which readhere, grow, and invade into recurrent lesions. Barrier agents are frequently used to prevent postoperative adhesions. We tested if the absorbable cell adhesion barrier gel Intercoat consisting of polyethylene oxide and sodium carboxymethyl cellulose could inhibit cellular adhesion, proliferation, and invasion of primary endometriosis and endometrial cells. Due to an association of endometriosis with ovarian carcinoma, we tested two ovarian carcinoma cell lines. Prior to cell seeding, a drop of the barrier gel was placed in cell culture wells in order to test inhibition of adherence and proliferation or coated over a polymerized collagen gel to assay for prevention of invasion. Results showed that the barrier gel significantly inhibited cell adherence, proliferation, and invasion of endometriosis and endometrial stromal cells as well as ovarian carcinoma cells in culture. Our findings could help to prevent local cell growth/invasion and possible consequent recurrences.
EVALuna2:17548

Initial clinical results with a fusion prototype for mammography and three-dimensional ultrasound with a standard mammography system and a standard ultrasound probe - Emons, Julius; Wunderle, Marius; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Gaß, Paul; Fasching, Peter; Langemann, Hanna; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Jud, Sebastian (Acta Radiologica, 2018)
BACKGROUND: Combinations *Equal contributors. of different imaging techniques in fusion devices appear to be associated with improvements in diagnostic assessment. PURPOSE: The aim of this study was to test the feasibility of using an automated standard three-dimensional (3D) ultrasound (US) device fused with standard mammography for the first time in breast cancer patients. MATERIAL AND METHODS: Digital mammograms and 3D automated US images were obtained in 23 patients with highly suspicious breast lesions. A recently developed fusion machine consisting of an ABVS 3D US transducer from an Acuson S2000 machine and a conventional Mammomat Inspiration device (both Siemens Healthcare GmbH, Erlangen, Germany) were used for the purpose. The feasibility of the examinations, imaging coverage, and patients' experience of the procedure were examined. RESULTS: In 15 out of 19 patients, the region of interest (ROI) with the tumor marked in the mammogram was visible on US. The examination was experienced positively by the patients, with no unexpected pain or injury. The examination was time-saving and well tolerated. CONCLUSION: In conclusion, we have shown initial clinical feasibility of an US/radiography fusion prototype with good localization and evaluation of the ROIs. The combined examination was well tolerated. The simultaneous evaluation with mammography and US imaging may be able to improve detection and reduce examiner-related variability.
EVALuna2:34810

Initial experience with CDK4/6 inhibitor-based therapies compared to antihormone monotherapies in routine clinical use in patients with hormone receptor positive, HER2 negative breast cancer — Data from the PRAEGNANT research network for the first 2 years of drug availability in Germany - Schneeweiss, Andreas; Ettl, Johannes; Lüftner, Diana; Beckmann, Matthias; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Geberth, Matthias; Häberle, Lothar; Hadji, Peyman; Hartkopf, Andreas D.; Hielscher, Carsten; et al. (BREAST, 2020)
Purpose: Treatment with CDK4/6 inhibitors and endocrine therapy (CDK4/6i + ET) is a standard for patients with advanced hormone receptor–positive, HER2-negative (HR + HER2–) breast cancer (BC). However, real-world data on the implementation of therapy usage, efficacy, and toxicity have not yet been reported. Methods: The PRAEGNANT registry was used to identify advanced HR + HER2– BC patients (n = 1136). The use of chemotherapy, ET, everolimus + ET, and CDK4/6i + ET was analyzed for first-line, second-line, and third-line therapy. Progression-free survival (PFS) and overall survival (OS) were also compared between patients treated with CDK4/6i + ET and ET monotherapy. Also toxicity was assessed. Results: CDK4/6i + ET use increased from 38.5% to 62.7% in the first 2 years after CDK4/6i treatment became available (November 2016). Chemotherapy and ET monotherapy use decreased from 2015 to 2018 from 42.2% to 27.2% and from 53% to 9.5%, respectively. In this early analysis no statistically significant differences were found comparing CDK4/6i + ET and ET monotherapy patients with regard to PFS and OS. Leukopenia was was seen in 11.3% of patients under CDK4/6i + ET and 0.5% under ET monotherapy. Conclusions: In clinical practice, CDK4/6i + ET has been rapidly implemented. A group of patients with a more unfavorable prognosis was possibly treated in the real-world setting than in the reported randomized clinical trials. The available data suggest that longer follow-up times and a larger sample size are required in order to identify differences in survival outcomes. Studies should be supported that investigate whether chemotherapy can be avoided or delayed in this patient population by using CDK4/6i + ET.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Abemaciclib; Advanced breast cancer; CDK4/6; Chemotherapy; Endocrine therapy; Metastatic; Palbociclib; Ribociclib

Initial Treatment of Patients with Primary Breast Cancer: Evidence, Controversies, Consensus: Spectrum of Opinion of German Specialists at the 15th International St. Gallen Breast Cancer Conference (Vienna 2017) - Untch, Michael; Huober, Jens; Jackisch, Christian; Schneeweiss, Andreas; Brucker, Sara Y.; Dall, Peter; Denkert, Carsten; Fasching, Peter; Fehm, Tanja; Gerber, Bernd; Janni, Wolfgang; Kuehn, Thorsten; et al. (Geburtshilfe und Frauenheilkunde, 2017)
The St. Gallen International Consensus Conference on the treatment of patients with primary breast cancer has been held regularly (every second year in the last six years) for more than 30 years. This year, the findings of the International St. Gallen Consensus Panel and their implications for clinical practice were again discussed by a German working group of leading breast cancer specialists. Five of the breast cancer specialists from Germany were also members of this year's St. Gallen panel. A comparison between the St. Gallen recommendations and the annually updated treatment guidelines of the Gynecologic Oncology Group (AGO 2017) and the S3-guideline agreed upon in 2017 is useful. The recommendations of the St. Gallen panel represent an international cross-section of opinions of experts from different countries and different disciplines, while the S3-guideline and AGO guidelines are evidence-based. The motto of this year's 15th St. Gallen Conference was "Escalating and De-Escalating". The rationale behind this concept was to promote more individualized treatment and thereby reduce overtreatment as well as undertreatment.
EVALuna2:36191

Integrated Analysis of PTEN and p4EBP1 Protein Expression as Predictors for pCR in HER2-Positive Breast Cancer - Loibl, Sibylle; Darb-Esfahani, Silvia; Huober, Jens; Klimowicz, Alexander; Furlanetto, Jenny; Lederer, Bianca; Hartmann, Arndt; Eidtmann, Holger; Pfitzner, Berit; Fasching, Peter; Tiemann, Katharina; Jackisch, Christian; et al. (Clinical Cancer Research, 2016)
The PI3K/AKT pathway and phosphatase and tensin homolog (PTEN) aberrations are common in breast cancer. We investigated the correlation between phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), PTEN, p4EBP1 (phosphorylated E4 binding protein 1), and pathologic complete response (pCR) in patients receiving neoadjuvant therapy.We retrospectively evaluated PIK3CA, PTEN, and p4EBP1 protein expression in centrally HER2-positive patients (n = 181) who received epirubicin cyclophosphamide/trastuzumab followed by docetaxel/trastuzumab alone or concomitant/followed by capecitabine within the GeparQuattro study. PTEN was assessed using the automated quantitative immunofluorescence analysis and was analyzed as a dichotomic variable. p4EBP1 was assessed by immunohistochemistry and used as a continuous and dichotomic variable.p4EBP1 was available from 137, PTEN from 108, and PIK3CA genotype from 83 patients. Overall, the pCR rate in PTEN-low tumors was 27.6%, and in PTEN-high tumors, it was 57.1% (P = 0.010). pCR rates were not statistically different between PIK3CA wild-type and mutant (35% vs. 22%) or p4EBP1 IRS <= 4 and IRS > 4 (39% vs. 33%). pCR rate was 57.1% (8/14) in PTEN-high/PIK3CA wild-type and decreased to 15.4% in PTEN-low/PIK3CA-mutant tumors (P = 0.023). In multivariable analysis adjusted for baseline parameters, PTEN independently predicted pCR in the following cohorts: overall [OR, 7.54; 95% confidence interval (CI), 2.03-28.06; P = 0.003], PIK3CA wild-type (OR, 23.81; 95% CI, 1.75-324.05; P = 0.017), p4EBP1 IRS > 4 (OR, 11.53; 95% CI, 1.84-72.24; P = 0.009), and hormone receptor-positive (OR, 40.91; 95% CI, 2.93-570.44; P = 0.006). p4EBP1 was independently predictive for pCR in PIK3CA wild-type tumors (OR, 0.14; 95% CI, 0.03-0.78; P = 0.025).The study showed the potential role of PIK3CA genotype, PTEN, and p4EBP in predicting pCR after anthracycline-taxane-based chemotherapy and anti-HER2 treatment. Clin Cancer Res; 22(11); 2675-83. ©2016 AACR.
EVALuna2:6794

Integrative multi-omics analyses to identify the genetic and functional mechanisms underlying ovarian cancer risk regions - Dareng, Eileen O.; Coetzee, Simon G.; Tyrer, Jonathan P.; Peng, Pei Chen; Rosenow, Will; Chen, Stephanie; Davis, Brian D.; Dezem, Felipe Segato; Seo, Ji Heui; Nameki, Robbin; Reyes, Alberto L.; Aben, Katja K.H.; et al. (American Journal of Human Genetics, 2024)
To identify credible causal risk variants (CCVs) associated with different histotypes of epithelial ovarian cancer (EOC), we performed genome-wide association analysis for 470,825 genotyped and 10,163,797 imputed SNPs in 25,981 EOC cases and 105,724 controls of European origin. We identified five histotype-specific EOC risk regions (p value <5 × 10−8) and confirmed previously reported associations for 27 risk regions. Conditional analyses identified an additional 11 signals independent of the primary signal at six risk regions (p value <10−5). Fine mapping identified 4,008 CCVs in these regions, of which 1,452 CCVs were located in ovarian cancer-related chromatin marks with significant enrichment in active enhancers, active promoters, and active regions for CCVs from each EOC histotype. Transcriptome-wide association and colocalization analyses across histotypes using tissue-specific and cross-tissue datasets identified 86 candidate susceptibility genes in known EOC risk regions and 32 genes in 23 additional genomic regions that may represent novel EOC risk loci (false discovery rate <0.05). Finally, by integrating genome-wide HiChIP interactome analysis with transcriptome-wide association study (TWAS), variant effect predictor, transcription factor ChIP-seq, and motifbreakR data, we identified candidate gene-CCV interactions at each locus. This included risk loci where TWAS identified one or more candidate susceptibility genes (e.g., HOXD-AS2, HOXD8, and HOXD3 at 2q31) and other loci where no candidate gene was identified (e.g., MYC and PVT1 at 8q24) by TWAS. In summary, this study describes a functional framework and provides a greater understanding of the biological significance of risk alleles and candidate gene targets at EOC susceptibility loci identified by a genome-wide association study.
CRIS-Team Scopus Importer:2024-05-31
Keywords: epithelial ovarian cancer risk; fine mapping; functional mechanisms; GWAS

Intense dose-dense epirubicin, paclitaxel, cyclophosphamide versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triple-negative breast cancer) for neoadjuvant treatment of high-risk early breast cancer (GeparOcto—GBG 84): A randomised phase III trial - Schneeweiss, Andreas; Moebus, Volker; Tesch, Hans; Hanusch, Claus; Denkert, Carsten; Luebbe, Kristina; Huober, Jens; Klare, Peter; Kuemmel, Sherko; Untch, Michael; Kast, Karin; Jackisch, Christian; et al. (European Journal of Cancer, 2019)
Background: GeparOcto compared efficacy and safety of two chemotherapy regimens in high-risk early breast cancer (BC): sequential treatment with intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) and weekly treatment with paclitaxel plus non-pegylated liposomal doxorubicin (M, Myocet®) with additional carboplatin (PM(Cb)) in triple-negative BC (TNBC). Patients and methods: Patients with cT1c-cT4a-d and centrally assessed human epidermal growth factor receptor (HER)2-positive BC or TNBC were eligible, irrespective of nodal status, luminal B-like tumours only if pN+. Patients were randomised (stratified by BC subtype, Ki67, lymphocyte-predominant BC) to receive 18 weeks of E (150 mg/m 2 ) followed by P (225 mg/m 2 ) followed by C (2000 mg/m 2 ), each q2w for 3 cycles or weekly P (80 mg/m 2 ) plus M (20 mg/m 2 ) plus, in TNBC, Cb (area under curve (AUC) 1.5). HER2-positive BC patients additionally received trastuzumab (6 [loading dose 8]mg/kg q3w) and pertuzumab (420 [840]mg q3w) with all P and C cycles. Primary end-point was pathological complete response (pCR, ypT0/is ypN0), secondary end-points included other pCR definitions, pCR in stratified subpopulations, tolerability and compliance. This trial is registered with ClinicalTrials.gov number NCT02125344. Results: 945/961 randomised patients started treatment. The median age was 48 years; 7.6% had cT3-4, 46% cN+, 66% G3, 40% HER2-positive, 43% TNBC. pCR rate with iddEPC was 48.3%, with PM(Cb) 48.0%, respectively (PM(Cb) versus iddEPC odds ratio 0.99; 95% confidence interval 0.77–1.28, P = 0.979) with no significant differences observed in TNBC, HER2-positive, luminal B-like subtypes. 16.4% with iddEPC and 34.1% with PM(Cb) discontinued treatment (P < 0.001), mainly due to adverse events; two patients on PM(Cb) died. Conclusions: In high-risk early BC there is no difference in pCR rates following neoadjuvant treatment with iddEPC or weekly PM(Cb), respectively. iddEPC is one of the effective dose-dense regimens feasible in daily practice.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Carboplatin; Dose-dense; High-risk early breast cancer; Neoadjuvant

Interdisciplinary Screening, Diagnosis, Therapy and Follow-up of Breast Cancer. Guideline of the DGGG and the DKG (S3-Level, AWMF Registry Number 032/045OL, December 2017) - Part 1 with Recommendations for the Screening, Diagnosis and Therapy of Breast Cancer - Woeckel, Achim; Festl, Jasmin; Stueber, Tanja; Brust, Katharina; Stangl, Stephanie; Heuschmann, Peter U.; Albert, Ute-Susann; Budach, Wilfried; Follmann, Markus; Janni, Wolfgang; Kopp, Ina; Kreienberg, Rolf; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Purpose The aim of this official guideline coordinated and published by the German Society for Gynecology and Obstetrics (DGGG) and the German Cancer Society (DKG) was to optimize the screening, diagnosis, therapy and follow-up care of breast cancer. Methods The process of updating the S3 guideline dating from 2012 was based on the adaptation of identified source guidelines which were combined with reviews of evidence compiled using PICO (Patients/Interventions/Control/Outcome) questions and the results of a systematic search of literature databases and the selection and evaluation of the identified literature. The interdisciplinary working groups took the identified materials as their starting point to develop recommendations and statements which were modified and graded in a structured consensus procedure. Recommendations Part 1 of this short version of the guideline presents recommendations for the screening, diagnosis and follow-up care of breast cancer. The importance of mammography for screening is confirmed in this updated version of the guideline and forms the basis for all screening. In addition to the conventional methods used to diagnose breast cancer, computed tomography (CT) is recommended for staging in women with a higher risk of recurrence. The follow-up concept includes suggested intervals between physical, ultrasound and mammography examinations, additional high-tech diagnostic procedures, and the determination of tumor markers for the evaluation of metastatic disease.
EVALuna2:36235

Interdisciplinary Screening, Diagnosis, Therapy and Follow-up of Breast Cancer. Guideline of the DGGG and the DKG (S3-Level, AWMF Registry Number 032/045OL, December 2017) - Part 2 with Recommendations for the Therapy of Primary, Recurrent and Advanced Breast Cancer - Woeckel, Achim; Festl, Jasmin; Stueber, Tanja; Brust, Katharina; Krockenberger, Mathias; Heuschmann, Peter U.; Jiru-Hillmann, Steffi; Albert, Ute-Susann; Budach, Wilfried; Follmann, Markus; Janni, Wolfgang; Kopp, Ina; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Purpose The aim of this official guideline coordinated and published by the German Society for Gynecology and Obstetrics (DGGG) and the German Cancer Society (DKG) was to optimize the screening, diagnosis, therapy and follow-up care of breast cancer. Method The process of updating the S3 guideline published in 2012 was based on the adaptation of identified source guidelines. They were combined with reviews of evidence compiled using PICO (Patients/Interventions/Control/Outcome) questions and with the results of a systematic search of literature databases followed by the selection and evaluation of the identified literature. The interdisciplinary working groups took the identified materials as their starting point and used them to develop suggestions for recommendations and statements, which were then modified and graded in a structured consensus process procedure. Recommendations Part 2 of this short version of the guideline presents recommendations for the therapy of primary, recurrent and metastatic breast cancer. Loco-regional therapies are de-escalated in the current guideline. In addition to reducing the safety margins for surgical procedures, the guideline also recommends reducing the radicality of axillary surgery. The choice and extent of systemic therapy depends on the respective tumor biology. New substances are becoming available, particularly to treat metastatic breast cancer.
EVALuna2:36231

Interest in Integrative Medicine Among Postmenopausal Hormone Receptor-Positive Breast Cancer Patients in the EvAluate-TM Study - Hack, Carolin; Fasching, Peter; Fehm, Tanja; De Waal, Johann; Rezai, Mahdi; Baier, Bernd; Baake, Gerold; Kolberg, Hans-Christian; Guggenberger, Martin; Warm, Mathias; Harbeck, Nadia; Wuerstlein, Rachel; et al. (Integrative Cancer Therapies, 2017)
BACKGROUND: Breast cancer patients often use complementary and alternative medicine, but few prospectively collected data on the topic are available specifically for postmenopausal breast cancer patients. A large prospective study was therefore conducted within a noninterventional study in order to identify the characteristics of patients interested in integrative medicine. METHODS: The EvAluate-TM study is a prospective, multicenter noninterventional study in which treatment with the aromatase inhibitor letrozole was evaluated in postmenopausal women with hormone receptor-positive primary breast cancer. Between 2008 and 2009, 5045 postmenopausal patients were enrolled at 339 certified breast centers in Germany. As part of the data collection process, patients were asked at the baseline about their interest in and information needs relating to integrative medicine. RESULTS: Of the 5045 patients recruited, 3411 responded to the questionnaire on integrative medicine and took part in the analysis, 1583 patients expressed an interest in integrative medicine, and 1828 patients declared no interest. Relevant predictors of interest in integrative medicine were age, body mass index, tumor size, previous chemotherapy, and use of concomitant medications for other medical conditions. Interest in integrative medicine declined highly significantly ( P < .001) with age (<50 years, 74.1%; 50-60 years, 54.1%; >65 years, 38.0%). Patients in favor of integrative medicine were significantly less satisfied with the information received about individual treatments and antihormonal therapy. Patients with interest in integrative medicine were more often interested in rehabilitation and fitness, nutritional counseling, and additional support from self-help organizations. These women were mostly interested in receiving information about their disease and integrative medicine from a physician, rather than from other sources. CONCLUSIONS: This study shows that a considerable proportion of postmenopausal breast cancer patients are interested in integrative medicine. Information about integrative medicine should therefore be provided as part of patient care for this group. It was found that receiving concomitant medication for other medical conditions is one of the main predictors for women not being interested in integrative medicine. This group of patients may need special attention and individualized information about integrative medicine. Additionally, most patients were interested in obtaining the relevant information from their doctor.
EVALuna2:36142

Intermediate biopsies during neoadjuvant chemotherapy for breast cancer to predict patient outcome - Sinn, B. V.; Untch, M.; Karn, T.; Van Mackelenbergh, M.; Huober, J.; Sychra, K.; Schmitt, W. D.; Marme, F.; Schem, C.; Solbach, C.; Stickeler, E.; Tesch, H.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

International Consensus Conference for Advanced Breast Cancer, Lisbon 2019: ABC5 Consensus - Assessment by a German Group of Experts - Thomssen, Christoph; Lüftner, Diana; Untch, Michael; Haidinger, Renate; Würstlein, Rachel; Harbeck, Nadia; Augustin, Doris; Briest, Susanne; Ettl, Johannes; Fasching, Peter; Förster, Frank; Kurbacher, Christian M.; et al. (Breast Care, 2020)
The 5th International Consensus Conference for Advanced Breast Cancer (ABC5) took place on November 14-16, 2019, in Lisbon, Portugal. Its aim is to standardize the treatment of advanced breast cancer based on the available evidence and to ensure that all breast cancer patients worldwide receive adequate treatment and access to new therapies. This year, the conference focused on developments and study results in the treatment of patients with hormone receptor-positive/HER2-negative breast cancer as well as precision medicine. As in previous years, patient advocates from around the world were integrated into the ABC conference and had seats on the ABC consensus panel. In the present paper, a working group of German breast cancer experts comments on the results of the on-site ABC5 consensus votes by ABC panelists regarding their applicability for routine treatment in Germany. These comments take the recommendations of the Breast Committee of the Gynecological Oncology Working Group (Arbeitsgemeinschaft Gynäkologische Onkologie; AGO) into account. The report and assessment presented here pertain to the preliminary results of the ABC5 consensus. The final version of the statements will be published in Annals of Oncology and The Breast.
CRIS-Team Scopus Importer:2020-02-25

Investigation of gene-environment interactions between 47 newly identified breast cancer susceptibility loci and environmental risk factors - Rudolph, Anja; Milne, Roger L.; Truong, Therese; Knight, Julia A.; Seibold, Petra; Flesch-Janys, Dieter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; et al. (International Journal of Cancer, 2015)
A large genotyping project within the Breast Cancer Association Consortium (BCAC) recently identified 41 associations between single nucleotide polymorphisms (SNPs) and overall breast cancer (BC) risk. We investigated whether the effects of these 41 SNPs, as well as six SNPs associated with estrogen receptor (ER) negative BC risk are modified by 13 environmental risk factors for BC. Data from 22 studies participating in BCAC were pooled, comprising up to 26,633 cases and 30,119 controls. Interactions between SNPs and environmental factors were evaluated using an empirical Bayes-type shrinkage estimator. Six SNPs showed interactions with associated p-values (pint ) <1.1 × 10(-3) . None of the observed interactions was significant after accounting for multiple testing. The Bayesian False Discovery Probability was used to rank the findings, which indicated three interactions as being noteworthy at 1% prior probability of interaction. SNP rs6828523 was associated with increased ER-negative BC risk in women >=170 cm (OR = 1.22, p = 0.017), but inversely associated with ER-negative BC risk in women <160 cm (OR = 0.83, p = 0.039, pint = 1.9 × 10(-4) ). The inverse association between rs4808801 and overall BC risk was stronger for women who had had four or more pregnancies (OR = 0.85, p = 2.0 × 10(-4) ), and absent in women who had had just one (OR = 0.96, p = 0.19, pint = 6.1 × 10(-4) ). SNP rs11242675 was inversely associated with overall BC risk in never/former smokers (OR = 0.93, p = 2.8 × 10(-5) ), but no association was observed in current smokers (OR = 1.07, p = 0.14, pint = 3.4 × 10(-4) ). In conclusion, recently identified BC susceptibility loci are not strongly modified by established risk factors and the observed potential interactions require confirmation in independent studies.
EVALuna2:9245

Joint association of mammographic density adjusted for age and body mass index and polygenic risk score with breast cancer risk - Vachon, Celine M.; Scott, Christopher G.; Tamimi, Rulla M.; Thompson, Deborah J.; Fasching, Peter; Stone, Jennifer; Southey, Melissa C.; Winham, Stacey; Lindstrom, Sara; Lilyquist, Jenna; Giles, Graham G.; Milne, Roger L.; et al. (Breast Cancer Research, 2019)
Background: Mammographic breast density, adjusted for age and body mass index, and a polygenic risk score (PRS), comprised of common genetic variation, are both strong risk factors for breast cancer and increase discrimination of risk models. Understanding their joint contribution will be important to more accurately predict risk.
CRIS-Team WoS Importer:2019-06-07

Joint associations of a polygenic risk score and environmental risk factors for breast cancer in the Breast Cancer Association Consortium - Rudolph, Anja; Song, Minsun; Brook, Mark N.; Milne, Roger L.; Mavaddat, Nasim; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wilcox, Amber N.; Hopper, John L.; Southey, Melissa C.; et al. (International Journal of Epidemiology, 2018)
Background: Polygenic risk scores (PRS) for breast cancer can be used to stratify the population into groups at substantially different levels of risk. Combining PRS and environmental risk factors will improve risk prediction; however, integrating PRS into risk prediction models requires evaluation of their joint association with known environmental risk factors. Methods: Analyses were based on data from 20 studies; datasets analysed ranged from 3453 to 23 104 invasive breast cancer cases and similar numbers of controls, depending on the analysed environmental risk factor. We evaluated joint associations of a 77-single nucleotide polymorphism (SNP) PRS with reproductive history, alcohol consumption, menopausal hormone therapy (MHT), height and body mass index (BMI). We tested the null hypothesis of multiplicative joint associations for PRS and each of the environmental factors, and performed global and tail-based goodness-of-fit tests in logistic regression models. The outcomes were breast cancer overall and by estrogen receptor (ER) status. Results: The strongest evidence for a non-multiplicative joint associations with the 77-SNP PRS was for alcohol consumption (P-interaction = 0.009), adult height (P-interaction = 0.025) and current use of combined MHT (P-interaction = 0.038) in ER-positive disease. Risk associations for these factors by percentiles of PRS did not follow a clear dose-response. In addition, global and tail-based goodness of fit tests showed little evidence for departures from a multiplicative risk model, with alcohol consumption showing the strongest evidence for ER-positive disease (P = 0.013 for global and 0.18 for tail-based tests). Conclusions: The combined effects of the 77-SNP PRS and environmental risk factors for breast cancer are generally well described by a multiplicative model. Larger studies are required to confirm possible departures from the multiplicative model for individual risk factors, and assess models specific for ER-negative disease.
EVALuna2:209951

Joint genome-wide association study of endometrial cancer and ovarian cancer identifies a novel genetic risk region at 14q23.3 - O'Mara, Tracy A.; Glubb, Dylan M.; Buchanan, Daniel D.; Lambrechts, Diether; Hall, Per; Tham, Emma; Trovik, Jone; Goode, Ellen L.; Fasching, Peter; Doerk, Thilo; Scott, Rodney J.; Auer, Paul L.; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

KATHERINE: Trastuzumab emtansine vs trastuzumab as adjuvant therapy in patients with HER2-positive early breast cancer - Mamounas, Eleftherios P.; Geyer, Charles E.; Huang, Chiun-Sheng; Mano, Max S.; Loibl, Sibylle; Untch, Michael; Wolmark, Norman; Rastogi, Priya; Schneeweiss, Andreas; Redondo, Andres; Fischer, Hans H.; Jacot, William; et al. (SWISS MEDICAL WEEKLY, 2019)
CRIS-Team WoS Importer:2019-07-19

KEYNOTE-522 Asian subgroup: Phase III study of neoadjuvant pembrolizumab (pembro) vs placebo (pbo) plus chemotherapy (chemo) followed by adjuvant pembro vs pbo for early triple-negative breast cancer (TNBC) - Dent, R.; Cortes, J.; Pusztai, L.; Mcarthur, H. L.; Kuemmel, S.; Bergh, J.; Denkert, C.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; Foukakis, T.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

KEYNOTE-522: Neoadjuvant Pembrolizumab plus Chemotherapy vs Placebo plus Chemotherapy Followed by Adjuvant Pembrolizumab vs Placebo for Early-stage Triple Negative Breast Cancer - Mcarthur, Heather; Cortes, Javier; Dent, Rebecca; Pusztai, Lajos; Kuemmel, Sherko; Bergh, Jonas; Denkert, Carsten; Park, Yeon Hee; Hui, Rina; Harbeck, Nadia; Takahashi, Masato; Untch, Michael; et al. (ANNALS OF SURGICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-05-20

KEYNOTE-522: Phase III study of neoadjuvant pembrolizumab D chemotherapy vs. placebo D chemotherapy, followed by adjuvant pembrolizumab vs. placebo for earlystage TNBC - Schmid, P.; Cortes, J.; Dent, R.; Pusztai, L.; Mcarthur, H.; Kummel, S.; Bergh, J.; Denkert, C.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-09-03

KEYNOTE-522: Phase III study of pembrolizumab (pembro) plus chemotherapy (chemo) vs placebo (pbo) plus chemo as neoadjuvant treatment, followed by pembro vs pbo as adjuvant treatment for early triple-negative breast cancer (TNBC) - Schmid, P.; Cortes, J.; Dent, R.; Pusztai, L.; Mcarthur, H. L.; Kuemmel, S.; Bergh, J.; Denkert, C.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Ki67, chemotherapy response, and prognosis in breast cancer patients receiving neoadjuvant treatment - Fasching, Peter A.; Heusinger, Katharina; Haeberle, Lothar; Niklos, Melitta; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Schulz-Wendtland, Rüdiger; Bani, Mayada; Schrauder, Michael; Kahmann, Laura; Lux, Michael P.; et al. (BMC Cancer, 2011)
Background: The pathological complete response (pCR) after neoadjuvant chemotherapy is a surrogate marker for a favorable prognosis in breast cancer patients. Factors capable of predicting a pCR, such as the proliferation marker Ki67, may therefore help improve our understanding of the drug response and its effect on the prognosis. This study investigated the predictive and prognostic value of Ki67 in patients with invasive breast cancer receiving neoadjuvant treatment for breast cancer.Methods: Ki67 was stained routinely from core biopsies in 552 patients directly after the fixation and embedding process. HER2/neu, estrogen and progesterone receptors, and grading were also assessed before treatment. These data were used to construct univariate and multivariate models for predicting pCR and prognosis. The tumors were also classified by molecular phenotype to identify subgroups in which predicting pCR and prognosis with Ki67 might be feasible.Results: Using a cut-off value of > 13% positively stained cancer cells, Ki67 was found to be an independent predictor for pCR (OR 3.5; 95% CI, 1.4, 10.1) and for overall survival (HR 8.1; 95% CI, 3.3 to 20.4) and distant disease-free survival (HR 3.2; 95% CI, 1.8 to 5.9). The mean Ki67 value was 50.6 ± 23.4% in patients with pCR. Patients without a pCR had an average of 26.7 ± 22.9% positively stained cancer cells.Conclusions: Ki67 has predictive and prognostic value and is a feasible marker for clinical practice. It independently improved the prediction of treatment response and prognosis in a group of breast cancer patients receiving neoadjuvant treatment. As mean Ki67 values in patients with a pCR were very high, cut-off values in a high range above which the prognosis may be better than in patients with lower Ki67 values may be hypothesized. Larger studies will be needed in order to investigate these findings further. © 2011 Fasching et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Klinische Endpunkte in Real-World-Register-Studien - Hartkopf, Andreas D.; Emons, Julius; Lux, Michael P.; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Titzmann, Adriana; Pöschke, Patrik; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; et al. (Onkologe, 2020)
Background: The therapeutic options for the individual patient with metastatic breast cancer are becoming more and more specific. Evidence for therapeutic recommendations from clinical trials is not available for all treatment situations and patient subgroups. This makes the collection and evaluation of real-world data meaningful. Methods and aims: To provide recommendations for up-to-date treatments and participation in clinical trials for patients with metastatic breast cancer, the Prospective Academic Translational Research Network (PREAGNANT) has been established to optimize the oncological quality of care in the advanced therapeutic setting. The main aim is to systematically record medical care of patients with metastatic breast cancer in real life including the therapeutic effects and side effects of the different treatment strategies, to monitor the quality of life changes during therapy, to identify patients who could participate in a clinical drug study and to enable a targeted therapy based on molecular structures of breast cancer patients. Conclusion: This article presents a summary of the PRAEGNANT network and sheds light on the question of the portability of the various endpoints from clinical trials into the real world treatment situation.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Artificial intelligence; Big data; Clinical decision-making; Evidence-based medicine; Information systems

Knowledge and attitudes regarding medical research studies among patients with breast cancer and gynecological diseases - Lux, Michael P.; Hildebrandt, Thomas; Knetzger, Sandra-Maria; Schrauder, Michael G.; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Fasching, Peter; Beckmann, Matthias; Thiel, Falk (BMC Cancer, 2015)
Medical research studies are becoming increasingly important for optimizing the prevention, diagnosis and treatment of illnesses. Participation in research studies can have many benefits for patients. In randomized and controlled clinical studies, they can receive the best possible medical care currently available. However, only a small proportion of patients nowadays are treated within the framework of medical research. The primary endpoint of this study was to discover what level of knowledge patients have about clinical studies and how they currently perceive them, in order to identify ways of optimizing the information provided about studies from the patients' point of view.The study included 2546 patients (breast cancer 21.6%, gynecological cancer 8.3%, obstetrics 32.7%, endometriosis 7.8%, fertility treatment 3.2%, other benign gynecological illnesses 19.2%, no information for 7.2%) in the outpatient clinic (45.2%) and in the in-patient sector (54.8%) at the Department of Gynecology at Erlangen University Hospital and associated centers. In the single-center study, conducted between January 2011 and January 2012, the patients were asked about their level of knowledge regarding the background to medical research studies and the ways in which they are carried out and used. The patients were also asked how they perceived medical studies and how they thought study conditions might be optimized. The three-page questionnaire was included in the feedback sheet received by patients as part of the hospital's quality management system.As a whole, the group only had moderate knowledge about clinical studies. A majority of the respondents considered that studies were valuable (91.6%), but only a few were also willing to take part in them (58.4%). Knowledge and willingness to participate strongly depended on age (P < 0.001), educational level (P < 0.001) and patient group (P < 0.001). Most patients would prefer to decide about participating in studies through a discussion with their outpatient physicians.The information that patients have about clinical studies affects whether they participate in them. It is therefore extremely important for patients to be well informed, for their anxieties about participation to be relieved, and for the benefits of participation to be explained to them.
EVALuna2:17441

Korrelate der Depressivität von Müttern von Grundschulkindern - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (50. Jahreskongress der Deutschen Gesellschaft für Psychologie, 2016)

Large-scale evaluation of common variation in regulatory T cell-related genes and ovarian cancer outcome - Charbonneau, Bridget; Moysich, Kirsten B.; Kalli, Kimberly R.; Oberg, Ann L.; Vierkant, Robert A.; Fogarty, Zachary C.; Block, Matthew S.; Maurer, Matthew J.; Goergen, Krista M.; Fridley, Brooke L.; Cunningham, Julie M.; Rider, David N.; et al. (Cancer Immunology Research, 2014)
The presence of regulatory T cells (Treg) in solid tumors is known to play a role in patient survival in ovarian cancer and other malignancies. We assessed inherited genetic variations via 749 tag single-nucleotide polymorphisms (SNP) in 25 Treg-associated genes (CD28, CTLA4, FOXP3, IDO1, IL10, IL10RA, IL15, 1L17RA, IL23A, IL23R, IL2RA, IL6, IL6R, IL8, LGALS1, LGALS9, MAP3K8, STAT5A, STAT5B, TGFB1, TGFB2, TGFB3, TGFBR1, TGRBR2, and TGFBR3) in relation to ovarian cancer survival. We analyzed genotype and overall survival in 10,084 women with invasive epithelial ovarian cancer, including 5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous carcinoma cases of European descent across 28 studies from the Ovarian Cancer Association Consortium (OCAC). The strongest associations were found for endometrioid carcinoma and IL2RA SNPs rs11256497 [HR, 1.42; 95% confidence interval (CI), 1.22-1.64; P = 5.7 × 10(-6)], rs791587 (HR, 1.36; 95% CI, 1.17-1.57; P = 6.2 × 10(-5)), rs2476491 (HR, = 1.40; 95% CI, 1.19-1.64; P = 5.6 × 10(-5)), and rs10795763 (HR, 1.35; 95% CI, 1.17-1.57; P = 7.9 × 10(-5)), and for clear cell carcinoma and CTLA4 SNP rs231775 (HR, 0.67; 95% CI, 0.54-0.82; P = 9.3 × 10(-5)) after adjustment for age, study site, population stratification, stage, grade, and oral contraceptive use. The rs231775 allele associated with improved survival in our study also results in an amino acid change in CTLA4 and previously has been reported to be associated with autoimmune conditions. Thus, we found evidence that SNPs in genes related to Tregs seem to play a role in ovarian cancer survival, particularly in patients with clear cell and endometrioid epithelial ovarian cance
EVALuna2:9223

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair - Day, Felix R.; Ruth, Katherine S.; Thompson, Deborah J.; Lunetta, Kathryn L.; Pervjakova, Natalia; Chasman, Daniel I.; Stolk, Lisette; Finucane, Hilary K.; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tonu; Johnson, Andrew D.; et al. (Nature Genetics, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in 70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk ( 6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
EVALuna2:17562

Lessons learned from a candidate gene study investigating aromatase inhibitor treatment outcome in breast cancer - Hoppe, Reiner; Winter, Stefan; Lo, Wing Yee; Michailidou, Kyriaki; Bolla, Manjeet K.; Keeman, Renske; Wang, Qin; Dennis, Joe; Lush, Michael; Kalari, Krishna R.; Goetz, Matthew P.; Wang, Liewei; et al. (npj Breast Cancer, 2025)
The role of germline genetics in adjuvant aromatase inhibitor (AI) treatment efficacy in ER-positive breast cancer is poorly understood. We employed a two-stage candidate gene approach to examine associations between survival endpoints and common germline variants in 753 endocrine resistance-related genes. For a discovery cohort, we screened the Breast Cancer Association Consortium database (n ≥ 90,000 cases) and retrieved 2789 AI-treated patients. Cox model-based analysis revealed 125 variants associated with overall, distant relapse-free, and relapse-free survival (p-value ≤ 1E-04). In validation analysis using five independent cohorts (n = 8857), none of the six selected candidates representing major linkage blocks at CELA2B/CASP9, NR1I2/GSK3B, LRP1B, and MIR143HG (CARMN) were validated. We discuss potential reasons for the failed validation and replication of published findings, including study/treatment heterogeneity and other limitations inherent to genomic treatment outcome studies. For the future, we envision prospective longitudinal studies with sufficiently long follow-up and endpoints that reflect the dynamic nature of endocrine resistance.
CRIS-Team Scopus Importer:2025-03-07

Lifestyle and personal factors associated with having macroscopic residual disease after ovarian cancer primary cytoreductive surgery - Phung, Minh Tung; Webb, Penelope M.; DeFazio, Anna; Fereday, Sian; Lee, Alice W.; Bowtell, David D.L.; Fasching, Peter; Goode, Ellen L.; Goodman, Marc T.; Karlan, Beth Y.; Lester, Jenny; Matsuo, Keitaro; et al. (Gynecologic Oncology, 2023)
Objective: The presence of macroscopic residual disease after primary cytoreductive surgery (PCS) is an important factor influencing survival for patients with high-grade serous ovarian cancer (HGSC). More research is needed to identify factors associated with having macroscopic residual disease. We analyzed 12 lifestyle and personal exposures known to be related to ovarian cancer risk or inflammation to identify those associated with having residual disease after surgery. Methods: This analysis used data on 2054 patients with advanced stage HGSC from the Ovarian Cancer Association Consortium. The exposures were body mass index, breastfeeding, oral contraceptive use, depot-medroxyprogesterone acetate use, endometriosis, first-degree family history of ovarian cancer, incomplete pregnancy, menopausal hormone therapy use, menopausal status, parity, smoking, and tubal ligation. Logistic regression models were fit to assess the association between these exposures and having residual disease following PCS. Results: Menopausal estrogen-only therapy (ET) use was associated with 33% lower odds of having macroscopic residual disease compared to never use (OR = 0.67, 95%CI 0.46–0.97, p = 0.033). Compared to nulliparous women, parous women who did not breastfeed had 36% lower odds of having residual disease (OR = 0.64, 95%CI 0.43–0.94, p = 0.022), while there was no association among parous women who breastfed (OR = 0.90, 95%CI 0.65–1.25, p = 0.53). Conclusions: The association between ET and having no macroscopic residual disease is plausible given a strong underlying biologic hypothesis between this exposure and diagnosis with HGSC. If this or the parity finding is replicated, these factors could be included in risk stratification models to determine whether HGSC patients should receive PCS or neoadjuvant chemotherapy.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Lifestyle; Ovarian cancer; Primary cytoreductive surgery; Residual disease

Lifetime ovulatory years and risk of epithelial ovarian cancer: a multinational pooled analysis - Fu, Zhuxuan; Brooks, Maria Mori; Irvin, Sarah; Jordan, Susan; Aben, Katja K. H.; Anton-Culver, Hoda; Bandera, Elisa; Beckmann, Matthias; Berchuck, Andrew; Brooks-Wilson, Angela; Chang-Claude, Jenny; Cook, Linda S.; et al. (Journal of the National Cancer Institute, 2023)
Background The role of ovulation in epithelial ovarian cancer (EOC) is supported by the consistent protective effects of parity and oral contraceptive use. Whether these factors protect through anovulation alone remains unclear. We explored the association between lifetime ovulatory years (LOY) and EOC. Methods LOY was calculated using 12 algorithms. Odds ratios (ORs) and 95% confidence intervals (CIs) estimated the association between LOY or LOY components and EOC among 26 204 control participants and 21 267 case patients from 25 studies. To assess whether LOY components act through ovulation suppression alone, we compared beta coefficients obtained from regression models with expected estimates assuming 1 year of ovulation suppression has the same effect regardless of source. Results LOY was associated with increased EOC risk (OR per year increase = 1.014, 95% CI = 1.009 to 1.020 to OR per year increase = 1.044, 95% CI = 1.041 to 1.048). Individual LOY components, except age at menarche, also associated with EOC. The estimated model coefficient for oral contraceptive use and pregnancies were 4.45 times and 12- to 15-fold greater than expected, respectively. LOY was associated with high-grade serous, low-grade serous, endometrioid, and clear cell histotypes (ORs per year increase = 1.054, 1.040, 1.065, and 1.098, respectively) but not mucinous tumors. Estimated coefficients of LOY components were close to expected estimates for high-grade serous but larger than expected for low-grade serous, endometrioid, and clear cell histotypes. Conclusions LOY is positively associated with nonmucinous EOC. Differences between estimated and expected model coefficients for LOY components suggest factors beyond ovulation underlie the associations between LOY components and EOC in general and for non-HGSOC.
CRIS-Team WoS Importer:2023-04-21

Locoregional recurrence risk after neoadjuvant chemotherapy: A pooled analysis of nine prospective neoadjuvant breast cancer trials - Werutsky, Gustavo; Untch, Michael; Hanusch, Claus; Fasching, Peter; Blohmer, Jens Uwe; Seiler, Sabine; Denkert, Carsten; Tesch, Hans; Jackisch, Christian; Gerber, Bernd; Schneeweiss, Andreas; Link, Theresa; et al. (European Journal of Cancer, 2020)
Aim: This pooled analysis aimed to evaluate locoregional recurrence (LRR) rates of breast cancer (BC) after neoadjuvant chemotherapy (NACT) and to identify independent LRR predictors. Methods: 10,075 women with primary BC from nine neoadjuvant trials were included. The primary outcome was the cumulative incidence rate of LRR as the first event after NACT. Distant recurrence, secondary malignancy or death were defined as competing events. For identifying LRR predictors, surgery type, pathological complete response (pCR), BC subtypes and other potential risk factors were evaluated. Results: Median followup was 67 months (range 0–215), overall LRR rate was 9.5%, 4.1% in pCR versus 9.5% in non-pCR patients. Younger age, clinically positive lymph nodes, G3 tumours, non-pCR and TNBC but not surgery type were independent LRR predictors in multivariate analysis. Among BC subtypes, 5-year cumulative LRR rates were associated with higher risk in non-pCR versus pCR patients, which was significant for HR+/HER2- (5.9% vs 3.9%; HR = 2.32 [95%CI 1.22–4.43]; p = 0.011); HR-/HER2+ (14.8% vs 3.1%; HR = 4.26 [94%CI 2.35–7.71]; p < 0.001) and TNBC (18.5% vs 4.2%; HR = 4.10 [95%CI 2.88–5.82]; p < 0.001) but not for HR+/HER2+ (8.1% vs 4.8%; HR = 1.56 [95%CI 0.85–2.85]; p = 0.150). Within non-pCR subgroup, LRR risk was higher for HR-/HER2+ and TNBC vs HR+/HER2- (HR = 2.05 [95%CI 1.54–2.73]; p < 0.001 and HR = 2.77 [95%CI 2.27–3.39]; p < 0.001, respectively). Conclusions: This pooled analysis demonstrated that young age, node-positive and G3 tumours, as well as TNBC, and non-pCR significantly increased the risk of LRR after NACT. Hence, there is a clear need to investigate better multimodality therapies in the post-neoadjuvant setting for high-risk patients.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Breast cancer; Locoregional recurrence; Neoadjuvant therapy; Prognostic factors; Survival

Long-term Follow-up and Safety of Patients after an Upfront Therapy with Letrozole for Early Breast Cancer in Routine Clinical Care – The PreFace Study - Hack, Carolin; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; Schneeweiss, Andreas; Marme, Frederik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Adjuvant treatment of patients with early-stage breast cancer (BC) should include an aromatase inhibitor (AI). Especially patients with a high recurrence risk might benefit from an upfront therapy with an AI for a minimum of five years. Nevertheless, not much is known about the patient selection for this population in clinical practice. Therefore, this study analyzed the prognosis and patient characteristics of postmenopausal patients selected for a five-year upfront letrozole therapy. Patients and Methods From 2009 to 2011, 3529 patients were enrolled into the adjuvant phase IV PreFace clinical trial (NCT01908556). Postmenopausal hormone receptor-positive BC patients, for whom an upfront five-year therapy with letrozole (2.5 mg/day) was indicated, were eligible. Disease-free survival (DFS), overall survival (OS) and safety in relation to patient and tumor characteristics were assessed. Results 3297 patients started letrozole therapy. The majority of patients (n = 1639, 57%) completed the five-year treatment. 34.5% of patients continued with endocrine therapy after the mandated five-year endocrine treatment. Five-year DFS rates were 89% (95% CI: 88-90%) and five-year OS rates were 95% (95% CI: 94-96%). In subgroup analyses, DFS rates were 83%, 84% and 78% for patients with node-positive disease, G3 tumor grading, and pT3 tumors respectively. The main adverse events (any grade) were pain and hot flushes (66.8% and 18.3% of patients). Conclusions The risk profile of postmenopausal BC patients selected for a five-year upfront letrozole therapy showed a moderate recurrence and death risk. However, in subgroups with unfavorable risk factors, prognosis warrants an improvement, which might be achieved with novel targeted therapies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: aromatase inhibitors; early breast cancer; hormone therapy; letrozole; prognosis

Long-term outcomes of a randomized, open-label, phase II study comparing cabazitaxel versus paclitaxel as neoadjuvant treatment in patients with triple-negative or luminal B/HER2-negative breast cancer (GENEVIEVE) - Meyer-Wilmes, P.; Huober, J.; Untch, M.; Blohmer, J. U.; Janni, W.; Denkert, C.; Klare, P.; Link, T.; Rhiem, K.; Bayer, C.; Reinisch, M.; Bjelic-Radisic, V.; et al. (ESMO Open, 2024)
Background: The GENEVIEVE study, comparing neoadjuvant cabazitaxel versus paclitaxel in triple-negative breast cancer (TNBC) and luminal B/human epidermal growth factor receptor 2 (HER2)-negative breast cancer (BC), previously reported significant differences in pathological complete response (pCR) rates. Effects on long-term outcome are unknown. Patients and methods: GENEVIEVE randomized patients with cT2-3, any cN or cT1, cN+/pNSLN+, centrally confirmed TNBC or luminal B/HER2-negative BC (latter defined as estrogen/progesterone receptor-positive and >14% Ki-67-stained cells) to receive either cabazitaxel 25 mg/m2 q3w for four cycles or paclitaxel 80 mg/m2 weekly for 12 weeks. Anthracycline-containing chemotherapy was allowed in case of histologically proven invasive residuals as neoadjuvant treatment or after surgery as adjuvant treatment. Here we report the secondary endpoints invasive disease-free survival (iDFS), distant disease-free survival (DDFS), and overall survival (OS). Results: Of the 333 patients randomized, 74.7% and 83.2% completed treatment in the cabazitaxel and paclitaxel arms, respectively. After a median follow-up of 89.3 months (interquartile range 68.8-97.3 months), 80 iDFS events (43 after cabazitaxel and 37 after paclitaxel) and 47 deaths (23 after cabazitaxel and 24 after paclitaxel) were reported. IDFS rates were not significantly different between the cabazitaxel and paclitaxel arms after a 3-year (83.6% versus 85.0%) and 5-year follow-up (76.2% versus 78.3%) [hazard ratio (HR) = 1.27, 95% confidence interval 0.82-1.96, P = 0.294], respectively. DDFS rates at 3 years (88.6% versus 87.8%) and 5 years (82.1% versus 82.8%) for cabazitaxel and paclitaxel were comparable (HR = 1.15, P = 0.573). Similarly, OS rates at 3 years (91.6% versus 91.8%) and 5 years (89.2% versus 86.8%) showed no significant differences (HR = 1.05, P = 0.872). Subgroup analysis for TNBC and luminal B/HER2-negative BCs indicated no significant variations in 3- or 5-year iDFS, DDFS, or OS. Conclusions: The significant differences in pCR rates observed in both treatment arms did not significantly impact long-term outcomes for patients treated with cabazitaxel versus paclitaxel in the GENEVIEVE trial.
CRIS-Team Scopus Importer:2024-05-03
Keywords: breast cancer; cabazitaxel; HER2-negative; paclitaxel; survival

Long-term survival analysis of the randomized phase II trial investigating the addition of carboplatin to neoadjuvant therapy for triple-negative (TNBC) and HER2-positive early breast cancer (GeparSixto) - Untch, M.; Schneeweiss, A.; Salat, C.; Rezai, M.; Zahm, D-M.; Klare, P.; Blohmer, J-U.; Tesch, H.; Khandan, F.; Fasching, Peter; Jackisch, C.; Nekljudova, V.; et al. (2017)
EVALuna2:36186

Long-term survival of HER2-positive breast cancer patients with brain metastases: subanalysis of the BMBC Registry - Laakmann, E.; Riecke, K.; Neunhoeffer, T.; Park-Simon, T-Wp; Weide, R.; Polasik, A.; Schmidt, M.; Puppe, J.; Fasching, Peter; Hesse, T.; Decker, T.; Denkert, C.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Machine Learning-based Detection of In-Utero Fetal Presentation from Non-Invasive Fetal ECG - Jäger, Katharina; Nissen, Michael; Richer, Robert; Rahm, Simone; Titzmann, Adriana; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (2022 IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI), 2022)
Preterm births account for more than 10 % of all newborns. An adverse fetal presentation is a risk factor for intrapartum and neonatal mortality. To date, no technology enables a longitudinal, ubiquitous, and unobtrusive monitoring of fetal presentation. This study presents a first approach to fetal orientation detection based on non-invasive fetal electrocardiography (NI-fECG) using the non-invasive multi-modal foetal ECG-Doppler data set for antenatal cardiology research. The data set contains 60 recordings from 39 pregnant women (21–27 weeks), including NI-fECG and ultrasound position ground truth. We evaluated both handcrafted and generic features for five different classifiers (k-Nearest-Neighbor, Decision Tree Classifier, Support Vector Classification, AdaBoost Classifier, and Multilayer Perceptron) using cross-validation on subject splits on a cleaned subset. Best results for the distinction between vertex (head down) and breech (head up) were achieved using an AdaBoost classifier with a balanced accuracy of 86.5 ± 15.0 %. With this work, we take a first step towards longitudinal fetal presentation monitoring, which contributes to a better understanding of reduced fetal movements and extends the potential applications of NI-fECG in prenatal care. In future work, we will expand our classification system to detect more detailed fetal presentations using a newly created data set.<br

Maintenance olaparib plus bevacizumab in patients with newly diagnosed advanced high-grade ovarian cancer: Main analysis of second progression-free survival in the phase III PAOLA-1/ENGOT-ov25 trial - González-Martín, Antonio; Desauw, Christophe; Heitz, Florian; Cropet, Claire; Gargiulo, Piera; Berger, Regina; Ochi, Hiroyuki; Vergote, Ignace; Colombo, Nicoletta; Mirza, Mansoor R.; Tazi, Youssef; Canzler, Ulrich; et al. (European Journal of Cancer, 2022)
Background: PAOLA-1/ENGOT-ov25 (NCT02477644) demonstrated a significant progression-free survival (PFS) benefit with maintenance olaparib plus bevacizumab versus placebo plus bevacizumab in newly diagnosed, advanced ovarian cancer. We report the prespecified main second progression-free survival (PFS2) analysis for PAOLA-1. Methods: This randomised, double-blind, phase III trial was conducted in 11 countries. Eligible patients had newly diagnosed, advanced, high-grade ovarian cancer and were in response after first-line platinum-based chemotherapy plus bevacizumab. Patients were randomised 2:1 to olaparib (300 mg twice daily) or placebo for up to 24 months; all patients received bevacizumab (15 mg/kg every 3 weeks) for up to 15 months. Primary PFS end-point was reported previously. Time from randomisation to second disease progression or death was a key secondary end-point included in the hierarchical-testing procedure. Results: After a median follow-up of 35.5 months and 36.5 months, respectively, median PFS2 was 36.5 months (olaparib plus bevacizumab) and 32.6 months (placebo plus bevacizumab), hazard ratio 0.78; 95% confidence interval (CI) 0.64–0.95; P = 0.0125. Median time to second subsequent therapy or death was 38.2 months (olaparib plus bevacizumab) and 31.5 months (placebo plus bevacizumab), hazard ratio 0.78; 95% CI 0.64–0.95; P = 0.0115. Seventy-two (27%) patients in the placebo plus bevacizumab group received a poly(ADP-ribose) polymerase inhibitor as first subsequent therapy. No new safety signals were observed for olaparib plus bevacizumab. Conclusion: In newly diagnosed, advanced ovarian cancer, maintenance olaparib plus bevacizumab provided continued benefit beyond first progression, with a significant PFS2 improvement and a time to second subsequent therapy or death delay versus placebo plus bevacizumab.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Antiangiogenic agent; Bevacizumab; Olaparib; Ovarian cancer; PARP inhibitor; Second progression-free survival

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor

Mammographic Density and Prognosis in Patients with primary Breast Cancer - Loss of Risk with increasing Age - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Caroline; Heusinger, K.; Gaß, Paul; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; Meyer, J.; Häberle, Lothar; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Mammographic density and prognosis in primary breast cancer patients - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Carolin; Heusinger, Katharina; Gaß, Paul; Pöschke, Patrik; Stübs, Frederik; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; et al. (BREAST, 2021)
Purpose: Mammographic density (MD) is one of the strongest risk factors for breast cancer (BC). However, the influence of MD on the BC prognosis is unclear. The objective of this study was therefore to investigate whether percentage MD (PMD) is associated with a difference in disease-free or overall survival in primary BC patients. Methods: A total of 2525 patients with primary, metastasis-free BC were followed up retrospectively for this analysis. For all patients, PMD was evaluated by two readers using a semi-automated method. The association between PMD and prognosis was evaluated using Cox regression models with disease-free survival (DFS) and overall survival (OS) as the outcome, and the following adjustments: age at diagnosis, year of diagnosis, body mass index, tumor stage, grading, lymph node status, hormone receptor and HER2 status. Results: After median observation periods of 9.5 and 10.0 years, no influence of PMD on DFS (p = 0.46, likelihood ratio test (LRT)) or OS (p = 0.22, LRT), respectively, was found. In the initial unadjusted analysis higher PMD was associated with longer DFS and OS. The effect of PMD on DFS and OS disappeared after adjustment for age and was caused by the underlying age effect. Conclusions: Although MD is one of the strongest independent risk factors for BC, in our collective PMD is not associated with disease-free and overall survival in patients with BC.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Breast cancer; Breast cancer risk; Mammographic breast density; Mammographic density; Prognosis

Mammographic density is the main correlate of tumors detected on ultrasound but not on mammography - Haeberle, Lothar; Fasching, Peter; Brehm, Barbara; Heusinger, Katharina; Jud, Sebastian; Löhberg, Christian; Hack, Carolin; Preuss, Caroline; Lux, Michael P.; Hartmann, Arndt; Vachon, Celine M.; Meier-Meitinger, Martina; et al. (International Journal of Cancer, 2016)
Although mammography screening programs do not include ultrasound examinations, some diagnostic units do provide women with both mammography and ultrasonography. This article is concerned with estimating the risk of a breast cancer patient diagnosed in a hospital-based mammography unit having a tumor that is visible on ultrasound but not on mammography. A total of 1,399 women with invasive breast cancer from a hospital-based diagnostic mammography unit were included in this retrospective study. For inclusion, mammograms from the time of the primary diagnosis had to be available for computer-assisted assessment of percentage mammographic density (PMD), as well as Breast Imaging Reporting and Data System (BIRADS) assessment of mammography. In addition, ultrasound findings were available for the complete cohort as part of routine diagnostic procedures, regardless of any patient or imaging characteristics. Logistic regression analyses were conducted to identify predictors of mammography failure, defined as BIRADS assessment 1 or 2. The probability that the visibility of a tumor might be masked at diagnosis was estimated using a regression model with the identified predictors. Tumors were only visible on ultrasound in 107 cases (7.6%). PMD was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery also influenced the risk, independently of the PMD. Risk probabilities ranged from 1% for a defined low-risk group up to 40% for a high-risk group. These findings might help identify women who should be offered ultrasound examinations in addition to mammography.
EVALuna2:6818

Margetuximab Versus Trastuzumab in Patients With Previously Treated HER2-Positive Advanced Breast Cancer (SOPHIA): Final Overall Survival Results From a Randomized Phase 3 Trial - Rugo, Hope S.; Im, Seock Ah; Cardoso, Fatima; Cortes, Javier; Curigliano, Giuseppe; Musolino, Antonino; Pegram, Mark D.; Bachelot, Thomas; Wright, Gail S.; Saura, Cristina; Escrivá-de-Romaní, Santiago; De Laurentiis, Michelino; et al. (Journal of Clinical Oncology, 2023)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported.Final overall survival (OS) in SOPHIA (ClinicalTrials.gov identifier: NCT02492711), a study of margetuximab versus trastuzumab, both with chemotherapy, in patients with previously treated human epidermal growth factor receptor 2-positive advanced breast cancer, is reported with updated safety. Overall, 536 patients in the intention-to-treat population were randomly assigned to margetuximab (15 mg/kg intravenously once every 3 weeks; n = 266) plus chemotherapy or trastuzumab (6 mg/kg intravenously once every 3 weeks after a loading dose of 8 mg/kg; n = 270) plus chemotherapy. Primary end points were progression-free survival, previously reported, and OS. Final OS analysis was triggered by 385 prespecified events. The median OS was 21.6 months (95% CI, 18.89 to 25.07) with margetuximab versus 21.9 months (95% CI, 18.69 to 24.18) with trastuzumab (hazard ratio [HR], 0.95; 95% CI, 0.77 to 1.17; P = .620). Preplanned, exploratory analysis of CD16A genotyping suggested a possible improvement in OS for margetuximab in CD16A-158FF patients versus trastuzumab (median OS, 23.6 v 19.2 months; HR, 0.72; 95% CI, 0.52 to 1.00) and a possible improvement in OS for trastuzumab in CD16A-158VV patients versus margetuximab (median OS, 31.1 v 22.0 months; HR, 1.77; 95% CI, 1.01 to 3.12). Margetuximab safety was comparable with trastuzumab. Final overall OS analysis did not demonstrate margetuximab advantage over trastuzumab. Margetuximab studies in patients with human epidermal growth factor receptor 2-positive breast cancer with different CD16A allelic variants are warranted.
CRIS-Team Scopus Importer:2023-01-13

Matching adjusted indirect comparison of PFS & OS comparing ribociclib plus letrozole vs palbociclib plus letrozole as first-line treatment of HR+/HER2-ABC: Analysis based on updated PFS & final OS results of MONALEESA-2 & PALOMA-2 - Jhaveri, K.; O'Shaughnessy, J.; Fasching, Peter; Cardoso, F.; Tolaney, S.; Hamilton, E.; Sharma, V. K.; Biswas, C.; Haftchenary, S.; Pathak, P.; Rugo, H. (EUROPEAN JOURNAL OF CANCER, 2022)
CRIS-Team WoS Importer:2023-03-10

Matching-Adjusted Indirect Comparison of Ribociclib Plus Fulvestrant versus Palbociclib Plus Letrozole as First-Line Treatment of HR+/HER2-Advanced Breast Cancer - Fasching, Peter; Delea, Thomas E.; Lu, Yen-Shen; De Boer, Richard; Hurvitz, Sara A.; Moynahan, Aaron; Chandiwana, David; Lanoue, Brad; Hu, Huilin; Thuerigen, Astrid; O'Shaughnessy, Joyce (Cancer Management and Research, 2021)
Purpose: Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) plus endocrine therapy are recommended for first-line treatment of hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-) advanced breast cancer (ABC). However, not all CDK4/6i trials have reported significant overall survival (OS) benefit, and there have been no head-to-head trials. Two trials have reported OS outcomes in first-line patients: MONALEESA-3 reported significant OS benefit with first-or second-line ribociclib plus fulvestrant (RIB+FUL) versus placebo plus fulvestrant (PBO+FUL), while PALOMA-1 reported no significant OS benefit for palbociclib plus letrozole (PAL+LET) versus LET in first-line postmenopausal patients. Matched-adjusted indirect comparisons (MAICs) are an established method for comparing efficacy of treatments from different trials. We used an MAIC to compare first-line patients from MONALEESA-3 and PALOMA-1. Patients and Methods: An unanchored MAIC of progression-free survival (PFS) and OS in first-line patients with HR+/HER2- ABC treated with RIB+FUL versus PAL+LET was con-ducted using individual patient data from MONALEESA-3 and aggregated data from PALOMA-1. To match patients in PALOMA-1, patients in MONALEESA-3 were limited to those with no prior endocrine therapy for ABC and no (neo) adjuvant LET <= 12 months before enrollment. PFS and OS were compared using Kaplan-Meier estimators and Cox regression. Results: A total of 329 and 178 patients from RIB+FUL and PBO+FUL arms, respectively, of MONALEESA-3 were matched to 84 and 81 patients from PAL+LET and LET arms of PALOMA-1. After weighting, OS was significantly longer for RIB+FUL versus PAL+LET (hazard ratio [HR], 0.50; 95% CI, 0.32-0.77; p = 0.0020). PFS favored RIB+FUL versus PAL+LET, although the difference was not statistically significant (HR, 0.77; 95% CI, 0.54-1.10; p = 0.1553). Conclusion: Using MAIC to adjust for trial differences, OS comparisons favored RIB+FUL over PAL+LET as first-line treatment in postmenopausal patients with HR+/HER2- ABC. These exploratory results suggest a significant increase in OS benefit with RIB treatment compared with PAL.
CRIS-Team WoS Importer:2021-11-26

Maternal depression and child development: A prospective analysis of consequences, risk and protective factors - Roetner, Jakob; Petry, Janna; Niekamp, Julia; Maschkel, Janina; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2022)
Maternal depression and child development: A prospective analysis of consequences, risk and protective factors Abstract. Objective: Maternal stress, specifically maternal mental health problems, are considered risk factors for child development. The literature suggests that prenatal depressive symptoms as well as depressive symptoms are a widespread phenomenon during the further development of the child and have repeatedly been shown to have adverse effects on child mental health outcomes. The present study examined the longitudinal relationships between maternal depression (prenatal, postnatal, during childhood and adolescence) and child mental health from childhood to adolescence. Possible risk and protective factors were also considered. Method: N = 112 mothers were assessed for depressive symptoms via a questionnaire at four different timepoints (prenatal, T1; postnatal, T2; during childhood, T3; during adolescence, T4). Children's externalizing and internalizing symptoms (50.9 % girls) were assessed by their mothers both during childhood (M = 7.68, SD = 0.76 years) and during adolescence (M = 13.23, SD = 0.27 years). We evaluated the relationships between maternal depressive symptoms and children's externalizing/internalizing symptoms using multiple regression models and analyzed possible risk and protective factors using moderation analysis. Results: Externalizing/Internalizing symptoms were not directly associated with maternal depressive symptoms, while associations between such symptoms and maladaptive behavior were found in adolescents. The socioeconomic status of families showed a different risk profile for prenatal and postnatal depressive symptoms. The IQ of the children proved to be a risk factor for internalizing symptoms. Conclusions: Maternal depressive symptoms at any time during child development - in combination with further risk factors - have an impact on child mental health. The early identification of maternal symptoms followed by interventions to differentiate between prenatal and postnatal depression - especially in the context of socioeconomic status - are highly relevant for child development.
CRIS-Team WoS Importer:2022-04-08
Keywords: Pränatale Depressivität; kindliche Erlebens- und Verhaltensauffälligkeiten; Risiko- und Schutzfaktoren; sozioökonomischer Status; Intelligenzquotient; Prenatal depression; child behavior; risk and protective factors; socioeconomic status; intelligence quotient

Maternal perinatal or current depressive symptoms and parenting behavior in middle childhood - Zalan, Vera; Ziegler, Clara; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

MCM3 is a novel proliferation marker associated with longer survival for patients with tubo-ovarian high-grade serous carcinoma - Kang, Eun-Young; Millstein, Joshua; Popovic, Gordana; Meagher, Nicola S.; Bolithon, Adelyn; Talhouk, Aline; Chiu, Derek S.; Anglesio, Michael S.; Leung, Betty; Tang, Katrina; Lambie, Neil; Pavanello, Marina; et al. (Virchows Archiv, 2021)
Tubo-ovarian high-grade serous carcinomas (HGSC) are highly proliferative neoplasms that generally respond well to platinum/taxane chemotherapy. We recently identified minichromosome maintenance complex component 3 (MCM3), which is involved in the initiation of DNA replication and proliferation, as a favorable prognostic marker in HGSC. Our objective was to further validate whether MCM3 mRNA expression and possibly MCM3 protein levels are associated with survival in patients with HGSC. MCM3 mRNA expression was measured using NanoString expression profiling on formalin-fixed and paraffin-embedded tissue (N = 2355 HGSC) and MCM3 protein expression was assessed by immunohistochemistry (N = 522 HGSC) and compared with Ki-67. Kaplan-Meier curves and the Cox proportional hazards model were used to estimate associations with survival. Among chemotherapy-naive HGSC, higher MCM3 mRNA expression (one standard deviation increase in the score) was associated with longer overall survival (HR = 0.87, 95% CI 0.81-0.92, p < 0.0001, N = 1840) in multivariable analysis. MCM3 mRNA expression was highest in the HGSC C5.PRO molecular subtype, although no interaction was observed between MCM3, survival and molecular subtypes. MCM3 and Ki-67 protein levels were significantly lower after exposure to neoadjuvant chemotherapy compared to chemotherapy-naive tumors: 37.0% versus 46.4% and 22.9% versus 34.2%, respectively. Among chemotherapy-naive HGSC, high MCM3 protein levels were also associated with significantly longer disease-specific survival (HR = 0.52, 95% CI 0.36-0.74, p = 0.0003, N = 392) compared to cases with low MCM3 protein levels in multivariable analysis. MCM3 immunohistochemistry is a promising surrogate marker of proliferation in HGSC.
CRIS-Team WoS Importer:2021-11-26

Meconium indicators of maternal alcohol abuse during pregnancy and association with patient characteristics - Goecke, Tamme W.; Burger, Pascal; Fasching, Peter; Bakdash, Abdulsallam; Engel, Anne; Haeberle, Lothar; Voigt, Franziska; Faschingbauer, Florian; Raabe, Eva; Maass, Nicolai; Rothe, Michael; Beckmann, Matthias; et al. (BioMed Research International, 2014)
Identification of women with moderate alcohol abuse during pregnancy is difficult. We correlated self-reported alcohol consumption during pregnancy and patient characteristics with objective alcohol indicators measured in fetal meconium.A total of 557 women singleton births and available psychological tests, obstetric data and meconium samples were included in statistical analysis. Alcohol metabolites (fatty acid ethyl esters (FAEEs) and ethyl glucuronide (EtG)), were determined from meconium and correlated with patient characteristics.We found that 21.2% of the 557 participants admitted low-to-moderate alcohol consumption during pregnancy. Of the parameters analyzed from meconium, only EtG showed an association with alcohol history (P < 0.01). This association was inverse in cases with EtG value above 120 ng/g. These values indicate women with most severe alcohol consumption, who obviously denied having consumed alcohol during pregnancy. No other associations between socioeconomic or psychological characteristics and the drinking status (via meconium alcohol metabolites) could be found.Women who drink higher doses of ethanol during pregnancy, according to metabolite measures in meconium, might be less likely to admit alcohol consumption. No profile of socioeconomic or psychological characteristics of those women positively tested via meconium could be established.
EVALuna2:17357

Mendelian randomization analyses suggest a role for cholesterol in the development of endometrial cancer - Kho, Pik Fang; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Brinton, Louise; Buchanan, Daniel D.; Chanock, Stephen J.; Chen, Chu; et al. (International Journal of Cancer, 2020)
Blood lipids have been associated with the development of a range of cancers, including breast, lung and colorectal cancer. For endometrial cancer, observational studies have reported inconsistent associations between blood lipids and cancer risk. To reduce biases from unmeasured confounding, we performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids (low-density lipoprotein [LDL] and high-density lipoprotein [HDL] cholesterol, and triglycerides) and endometrial cancer risk. Genetic variants associated with each of these blood lipid levels (P < 5 × 10−8) were identified as instrumental variables, and assessed using genome-wide association study data from the Endometrial Cancer Association Consortium (12 906 cases and 108 979 controls) and the Global Lipids Genetic Consortium (n = 188 578). Mendelian randomization analyses found genetically raised LDL cholesterol levels to be associated with lower risks of endometrial cancer of all histologies combined, and of endometrioid and non-endometrioid subtypes. Conversely, higher genetically predicted HDL cholesterol levels were associated with increased risk of non-endometrioid endometrial cancer. After accounting for the potential confounding role of obesity (as measured by genetic variants associated with body mass index), the association between genetically predicted increased LDL cholesterol levels and lower endometrial cancer risk remained significant, especially for non-endometrioid endometrial cancer. There was no evidence to support a role for triglycerides in endometrial cancer development. Our study supports a role for LDL and HDL cholesterol in the development of non-endometrioid endometrial cancer. Further studies are required to understand the mechanisms underlying these findings.
CRIS-Team Scopus Importer:2020-08-14
Keywords: endometrial cancer risk; HDL cholesterol; LDL cholesterol; Mendelian randomization; triglycerides

Meta-analysis on association of pathological complete response with long-term survival outcomes in triple-negative breast cancer - Fasching, Peter; Huang, M.; Cortes, J.; Zhao, J.; O'Shaughnessy, J.; Hu, P.; Haiderali, A.; Karantza, V.; Aktan, G.; Briggs, A.; Ramsey, S.; Qi, C. Z.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Methodological Establishment of an in-vitro ADCC Assay by using patient-specific Immune Cells - Lehle, Sarah; Völkl, Simon; Rübner, Matthias; Emons, Julius; Seitz, Katharina; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

MGMT promoter methylation in triple negative breast cancer of the GeparSixto trial - Jank, Paul; Gehlhaar, Claire; Bianca, Lederer; Caterina, Fontanella; Andreas, Schneeweiss; Karn, Thomas; Marmé, Frederik; Sinn, Hans Peter; van Mackelenbergh, Marion; Sinn, Bruno; Zahm, Dirk Michael; Ingold-Heppner, Barbara; et al. (PLoS ONE, 2020)
Triple-negative breast cancer (TNBC) is typically treated with chemotherapeutic agents, including carboplatin (Cb), an DNA platinating agent. The O6-methylguanine-DNA-methyltransferase gene (MGMT) encodes for the protein O6-alkylguanine-DNA-alkyltransferase (MGMT protein). MGMT protein is involved in DNA repair mechanisms to remove mutagenic and cytotoxic adducts from O6-guanine in DNA. In glioblastoma multiforme, MGMT methylation status is a predictive biomarker for increased response to temozolomide therapy. It has been suggested, that MGMT protein may have relevance for cellular adaptation and could have an influence on resistance to carboplatin therapy. We investigated the influence of MGMT promoter methylation on pathologic complete response and survival of patients with TNBC treated in the neoadjuvant GeparSixto trial. In 174 of 210 available TNBC tumors a valid MGMT promoter methylation status was determined by pyrosequencing of 5 CpG islands. In 21.8%, we detected a mean MGMT promoter methylation >10%. Overall, MGMT promoter methylation was not significantly associated with pathological complete response (pCR) rate. After stratification for the two therapy arms with and without Cb no statistically significant differences in therapy response rates between the two MGMT promoter methylation groups could be observed. Our results show that different MGMT promoter methylation status is not related to different chemotherapy response rates in the TNBC setting in GeparSixto.
CRIS-Team Scopus Importer:2020-09-04

MicroRNA in diagnosis and therapy monitoring of early-stage triple-negative breast cancer - Kahraman, Mustafa; Roeske, Anne; Laufer, Thomas; Fehlmann, Tobias; Backes, Christina; Kern, Fabian; Kohlhaas, Jochen; Schroers, Hannah; Saiz, Anna; Zabler, Cassandra; Ludwig, Nicole; Fasching, Peter; et al. (Scientific Reports, 2018)
Breast cancer is a heterogeneous disease with distinct molecular subtypes including the aggressive subtype triple-negative breast cancer (TNBC). We compared blood-borne miRNA signatures of early-stage basal-like (cytokeratin-CK5-positive) TNBC patients to age-matched controls. The miRNAs of TNBC patients were assessed prior to and following platinum-based neoadjuvant chemotherapy (NCT). After an exploratory genome-wide study on 21 cases and 21 controls using microarrays, the identified signatures were verified independently in two laboratories on the same and a new cohort by RT-qPCR. We differentiated the blood of TNBC patients before NCT from controls with 84% sensitivity. The most significant miRNA for this diagnostic classification was miR-126-5p (two tailed t-test p-value of 1.4 × 10-5). Validation confirmed the microarray results for all tested miRNAs. Comparing cancer patients prior to and post NCT highlighted 321 significant miRNAs (among them miR-34a, p-value of 1.2 × 10-23). Our results also suggest that changes in miRNA expression during NCT may have predictive potential to predict pathological complete response (pCR). In conclusion we report that miRNA expression measured from blood facilitates early and minimally-invasive diagnosis of basal-like TNBC. We also demonstrate that NCT has a significant influence on miRNA expression. Finally, we show that blood-borne miRNA profiles monitored over time have potential to predict pCR.
EVALuna2:209952

MicroRNA Related Polymorphisms and Breast Cancer Risk - Khan, Sofia; Greco, Dario; Michailidou, Kyriaki; Milne, Roger L.; Muranen, Taru A.; Heikkinen, Tuomas; Aaltonen, Kirsimari; Dennis, Joe; Bolla, Manjeet K.; Liu, Jianjun; Hall, Per; Irwanto, Astrid; et al. (PLoS ONE, 2014)
Genetic variations, such as single nucleotide polymorphisms (SNPs) in microRNAs (miRNA) or in the miRNA binding sites may affect the miRNA dependent gene expression regulation, which has been implicated in various cancers, including breast cancer, and may alter individual susceptibility to cancer. We investigated associations between miRNA related SNPs and breast cancer risk. First we evaluated 2,196 SNPs in a case-control study combining nine genome wide association studies (GWAS). Second, we further investigated 42 SNPs with suggestive evidence for association using 41,785 cases and 41,880 controls from 41 studies included in the Breast Cancer Association Consortium (BCAC). Combining the GWAS and BCAC data within a meta-analysis, we estimated main effects on breast cancer risk as well as risks for estrogen receptor (ER) and age defined subgroups. Five miRNA binding site SNPs associated significantly with breast cancer risk: rs1045494 (odds ratio (OR) 0.92; 95% confidence interval (CI): 0.88-0.96), rs1052532 (OR 0.97; 95% CI: 0.95-0.99), rs10719 (OR 0.97; 95% CI: 0.94-0.99), rs4687554 (OR 0.97; 95% CI: 0.95-0.99, and rs3134615 (OR 1.03; 95% CI: 1.01-1.05) located in the 3' UTR of CASP8, HDDC3, DROSHA, MUSTN1, and MYCL1, respectively. DROSHA belongs to miRNA machinery genes and has a central role in initial miRNA processing. The remaining genes are involved in different molecular functions, including apoptosis and gene expression regulation. Further studies are warranted to elucidate whether the miRNA binding site SNPs are the causative variants for the observed risk effects.
EVALuna2:9235

Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias; Heinrich, Hartmut; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programme's effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
EVALuna2:36366

Mitomycin C and Capecitabine (MiX Trial) for Therapy of Patients with Metastasized, Breast Cancer Pretreated with Anthracycline - Almstedt, Katrin; Fasching, Peter; Scharl, Anton; Rauh, Claudia; Rack, Brigitte; Hein, Alexander; Hack, Carolin; Bayer, Christian M.; Jud, Sebastian; Schrauder, Michael G.; Beckmann, Matthias; Lux, Michael P. (Anticancer Research, 2016)
BACKGROUND/AIM: The aim of this single-arm, prospective, multicenter phase II trial (MiX) was to increase treatment options for women with metastatic breast cancer pretreated with anthracycline and taxane by evaluation of the efficacy and toxicity of the combination of mitomycin C and capecitabine. PATIENTS AND METHODS: From 03/2004 to 06/2007, a total of 39 patients were recruited and received mitomycin C in combination with capecitabine. The primary end-point was to determinate the tumor response according to Response Evaluation Criteria in Solid Tumors and the rate of toxicities (safety). The secondary study objective was the evaluation of the time to progression (i.e. efficacy). RESULTS: The median time to progression was 9.3 months (95% confidence interval=6.6-12.0 months) and the median survival was 12.8 months (95% confidence interval=6.8-18.8 months). Most treatment-related adverse events were mild to moderate. CONCLUSION: Mitomycin C and capecitabine is a good taxane-free option in patients with metastatic breast cancer previously treated with anthracycline.
EVALuna2:33006

Molecular adaptation to neoadjuvant immunotherapy in triple-negative breast cancer - Denkert, Carsten; Schneeweiss, Andreas; Rey, Julia; Karn, Thomas; Hattesohl, Akira; Weber, Karsten E.; Rachakonda, Sivaramakrishna; Braun, Michael; Huober, Jens; Jank, Paul; Sinn, Hans Peter; Zahm, Dirk Michael; et al. (Cell Reports Medicine, 2024)
Therapy-induced molecular adaptation of triple-negative breast cancer is crucial for immunotherapy response and resistance. We analyze tumor biopsies from three different time points in the randomized neoadjuvant GeparNuevo trial (NCT02685059), evaluating the combination of durvalumab with chemotherapy, for longitudinal alterations of gene expression. Durvalumab induces an activation of immune and stromal gene expression as well as a reduction of proliferation-related gene expression. Immune genes are positive prognostic factors irrespective of treatment, while proliferation genes are positive prognostic factors only in the durvalumab arm. We identify stromal-related gene expression as a contributor to immunotherapy resistance and poor therapy response. The results provide evidence from clinical trial cohorts suggesting a role for stromal reorganization in therapy resistance to immunotherapy and in the generation of an immune-suppressive microenvironment, which might be relevant for future therapy approaches targeting the tumor stroma parallel to immunotherapy, such as combinations of immunotherapy with anti-angiogenic therapy.
CRIS-Team Scopus Importer:2024-11-22
Keywords: gene expression; immunotherapy; neoadjuvant; pathway analysis; PD-L1; triple-negative breast cancer

Molecular profiling of single circulating tumor cells with diagnostic intention - Polzer, Bernhard; Medoro, Gianni; Pasch, Sophie; Fontana, Francesca; Zorzino, Laura; Pestka, Aurelia; Andergassen, Ulrich; Meier-Stiegen, Franziska; Czyz, Zbigniew T.; Alberter, Barbara; Treitschke, Steffi; Schamberger, Thomas; et al. (Embo Molecular Medicine, 2014)
Several hundred clinical trials currently explore the role of circulating tumor cell (CTC) analysis for therapy decisions, but assays are lacking for comprehensive molecular characterization of CTCs with diagnostic precision. We therefore combined a workflow for enrichment and isolation of pure CTCs with a non-random whole genome amplification method for single cells and applied it to 510 single CTCs and 189 leukocytes of 66 CTC-positive breast cancer patients. We defined a genome integrity index (GII) to identify single cells suited for molecular characterization by different molecular assays, such as diagnostic profiling of point mutations, gene amplifications and whole genomes of single cells. The reliability of > 90% for successful molecular analysis of high-quality clinical samples selected by the GII enabled assessing the molecular heterogeneity of single CTCs of metastatic breast cancer patients. We readily identified genomic disparity of potentially high relevance between primary tumors and CTCs. Microheterogeneity analysis among individual CTCs uncovered pre-existing cells resistant to ERBB2-targeted therapies suggesting ongoing microevolution at late-stage disease whose exploration may provide essential information for personalized treatment decisions and shed light into mechanisms of acquired drug resistance.
EVALuna2:6669

Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26

MUC1 (CA27.29) before and after Chemotherapy and Prognosis in High-Risk Early Breast Cancer Patients - Hübner, Hanna; Häberle, Lothar; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Fink, Visnja; Schochter, Fabienne; Bekes, Inga; Mahner, Sven; Jückstock, Julia; Nabieva, Naiba; et al. (Cancers, 2022)
Soluble MUC1 has been discussed as a biomarker for predicting prognosis, treatment efficacy, and monitoring disease activity in breast cancer (BC) patients. Most studies in adjuvant settings have used preoperative assessment. This study, part of the SUCCESS-A trial (NCT02181101), assessed the prognostic value of soluble MUC1 before and after standard adjuvant chemotherapy. Patients with high-risk BC were treated within the SUCCESS-A trial with either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide followed by three cycles of docetaxel or three cycles of FEC followed by three cycles of docetaxel and gemcitabine. Cox regression analyses were performed to investigate the prognostic value of CA27.29 before and after chemotherapy relative to disease-free survival (DFS), along with established BC prognostic factors such as age, body mass index, tumor size, nodal status, estrogen receptor, progesterone receptor, HER2 status, and grading. Pre-chemotherapy and post-chemotherapy CA27.29 assessments were available for 2687 patients of 3754 randomized patients. Pre-chemotherapy CA27.29 assessment was associated with DFS in addition to established prognostic factors. It had no prognostic value in node-negative patients, but there was a clear association in node-positive patients. Post-chemotherapy CA27.29 assessment did not add any prognostic value, either on its own or in addition to pre-chemotherapy CA27.29 assessment.
CRIS-Team Scopus Importer:2022-04-08
Keywords: anthracycline; CA15-3; CA27.29; chemotherapy; early breast cancer; MUC1; taxane; tumor marker

Multicenter evaluation of blood-based biomarkers for the detection of endometriosis and adenomyosis: A prospective non-interventional study - Burghaus, Stefanie; Drazic, Predrag; Wölfler, Monika; Mechsner, Sylvia; Zeppernick, Magdalena; Meinhold-Heerlein, Ivo; Mueller, Michael D.; Rothmund, Ralf; Vigano, Paola; Becker, Christian M.; Zondervan, Krina T.; Beckmann, Matthias; et al. (International Journal of Gynecology & Obstetrics, 2023)
Objective: To evaluate blood-based biomarkers to detect endometriosis and/or adenomyosis across nine European centers (June 2014–April 2018). Methods: This prospective, non-interventional study assessed the diagnostic accuracy of 54 blood-based biomarker immunoassays in samples from 919 women (aged 18–45 years) with suspicion of endometriosis and/or adenomyosis versus symptomatic controls. Endometriosis was stratified by revised American Society for Reproductive Medicine stage. Symptomatic controls were “pathologic symptomatic controls” or “pathology-free symptomatic controls”. The main outcome measure was receiver operating characteristic-area under the curve (ROC-AUC) and Wilcoxon P values corrected for multiple testing (q values). Results: CA-125 performed best in “all endometriosis cases” versus “all symptomatic controls” (AUC 0.645, 95% confidence interval [CI] 0.600–0.690, q < 0.001) and increased (P < 0.001) with disease stage. In “all endometriosis cases” versus “pathology-free symptomatic controls”, S100-A12 performed best (AUC 0.692, 95% CI 0.614–0.769, q = 0.001) followed by CA-125 (AUC 0.649, 95% CI 0.569–0.729, q = 0.021). In “adenomyosis only cases” versus “symptomatic controls” or “pathology-free symptomatic controls”, respectively, the top-performing biomarkers were sFRP-4 (AUC 0.615, 95% CI 0.551–0.678, q = 0.045) and S100-A12 (AUC 0.701, 95% CI 0.611–0.792, q = 0.004). Conclusion: This study concluded that no biomarkers tested could diagnose or rule out endometriosis/adenomyosis with high certainty.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adenomyosis; blood-based biomarkers; CA-125; diagnosis; endometriosis; S100-A12; sFRP-4

Mutational diversity and therapy response in breast cancer-a sequencing analysis in the neoadjuvant GeparSepto trial - Loibl, Sibylle; Treue, Denise; Budczies, Jan; Weber, Karsten; Stenzinger, Albrecht; Schmitt, Wolfgang D.; Weichert, Wilko; Jank, Paul; Furlanetto, Jenny; Klauschen, Frederick; Karn, Thomas; Pfarr, Nicole; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Mutational diversity and therapy response in breast cancer: A sequencing analysis in the neoadjuvant geparsepto trial - Loibl, Sibylle; Treue, Denise; Budczies, Jan; Weber, Karsten; Stenzinger, Albrecht; Schmitt, Wolfgang D.; Weichert, Wilko; Jank, Paul; Furlanetto, Jenny; Klauschen, Frederick; Karn, Thomas; Pfarr, Nicole; et al. (Clinical Cancer Research, 2019)
Purpose: Next-generation sequencing (NGS) can be used for comprehensive investigation of molecular events in breast cancer. We evaluated the relevance of genomic alterations for response to neoadjuvant chemotherapy (NACT) in the GeparSepto trial. Experimental Design: Eight hundred fifty-one pretherapeutic formalin-fixed paraffin-embedded (FFPE) core biopsies from GeparSepto study were sequenced. The panel included 16 genes for mutational (AKT1, BRAF, CDH1, EGFR, ERBB2, ESR1, FBXW7, FGFR2, HRAS, KRAS, NRAS, SF3B1, TP53, HNF1A, PIK3CA, and PTEN) and 8 genes for copy-number alteration analysis (CCND1, ERBB2, FGFR1, PAK1, PIK3CA, TOP2A, TP53, and ZNF703). Results: The most common genomic alterations were mutations of TP53 (38.4%) and PIK3CA (21.5%), and 8 different amplifications (TOP2A 34.9%; ERBB2 30.6%; ZNF703 30.1%; TP53 21.9%; PIK3CA 24.1%; CCND1 17.7%; PAK1 14.9%; FGFR 12.6%). All other alterations had a prevalence of less than 5%. The genetic heterogeneity in different breast cancer subtypes [lum/HER2neg vs. HER2pos vs. triple-negative breast cancer (TNBC)] was significantly linked to differences in NACT response. A significantly reduced pathologic complete response rate was observed in PIK3CAmutated breast cancer [PIK3CAmut: 23.0% vs. wild-type (wt) 38.8%, P < 0.0001] in particular in the HER2pos subcohort [multivariate OR = 0.43 (95% CI, 0.24-0.79), P = 0.006]. An increased response to nab-paclitaxel was observed only in PIK3CAwt breast cancer, with univariate significance for the complete cohort (P = 0.009) and the TNBC (P = 0.013) and multivariate significance in the HER2pos subcohort (test for interaction P = 0.0074). Conclusions: High genetic heterogeneity was observed in different breast cancer subtypes. Our study shows that FFPE-based NGS can be used to identify markers of therapy resistance in clinical study cohorts. PIK3CA mutations could be a major mediator of therapy resistance in breast cancer.
CRIS-Team Scopus Importer:2019-07-12

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

MyD88 and TLR4 Expression in Epithelial Ovarian Cancer - Block, Matthew S.; Vierkant, Robert A.; Rambau, Peter F.; Winham, Stacey J.; Wagner, Philipp; Traficante, Nadia; Toloczko, Aleksandra; Tiezzi, Daniel G.; Taran, Florin Andrei; Sinn, Peter; Sieh, Weiva; Sharma, Raghwa; et al. (Mayo Clinic Proceedings, 2018)
To evaluate myeloid differentiation primary response gene 88 (MyD88) and Toll-like receptor 4 (TLR4) expression in relation to clinical features of epithelial ovarian cancer, histologic subtypes, and overall survival.We conducted centralized immunohistochemical staining, semi-quantitative scoring, and survival analysis in 5263 patients participating in the Ovarian Tumor Tissue Analysis consortium. Patients were diagnosed between January 1, 1978, and December 31, 2014, including 2865 high-grade serous ovarian carcinomas (HGSOCs), with more than 12,000 person-years of follow-up time. Tissue microarrays were stained for MyD88 and TLR4, and staining intensity was classified using a 2-tiered system for each marker (weak vs strong).Expression of MyD88 and TLR4 was similar in all histotypes except clear cell ovarian cancer, which showed reduced expression compared with other histotypes (P<.001 for both). In HGSOC, strong MyD88 expression was modestly associated with shortened overall survival (hazard ratio [HR], 1.13; 95% CI, 1.01-1.26; P=.04) but was also associated with advanced stage (P<.001). The expression of TLR4 was not associated with survival. In low-grade serous ovarian cancer (LGSOC), strong expression of both MyD88 and TLR4 was associated with favorable survival (HR [95% CI], 0.49 [0.29-0.84] and 0.44 [0.21-0.89], respectively; P=.009 and P=.02, respectively).Results are consistent with an association between strong MyD88 staining and advanced stage and poorer survival in HGSOC and demonstrate correlation between strong MyD88 and TLR4 staining and improved survival in LGSOC, highlighting the biological differences between the 2 serous histotypes.
EVALuna2:50245

Nab-paclitaxel improves disease-free survival in early breast cancer: GBG 69–Geparsepto - Untch, Michael; Jackisch, Christian; Schneeweiss, Andreas; Schmatloch, Sabine; Aktas, Bahriye; Denkert, Carsten; Schem, Christian; Wiebringhaus, Hermann; Kümmel, Sherko; Warm, Mathias; Fasching, Peter; Just, Marianne; et al. (Journal of Clinical Oncology, 2019)
PURPOSE The GeparSepto trial demonstrated that weekly nanoparticle albumin-bound (NAB)–paclitaxel significantly improves the pathologic complete remission rate compared with weekly solvent-based (sb) paclitaxel followed by epirubicin plus cyclophosphamide as neoadjuvant treatment in patients with primary breast cancer (BC). Here, we report data on long-term outcomes. METHODS Patients with histologically confirmed primary BC were randomly assigned in a 1:1 ratio to 12 times weekly NAB-paclitaxel 150 mg/m2 (after study amendment, 125 mg/m2) or weekly sb-paclitaxel 80 mg/m2 followed in both arms by four times epirubicin 90 mg/m2 plus cyclophosphamide 600 mg/m2 every 3 weeks. Patients with human epidermal growth factor receptor 2 (HER2)-positive BC received dual antibody treatment with trastuzumab (8 mg/kg loading dose followed by 6 mg/kg every 3 weeks) and pertuzumab (840 mg loading dose followed by 420 mg every 3 weeks) concurrently to chemotherapy and continued for 1 year. RESULTS A total of 1,206 patients started treatment, 606 with NAB-paclitaxel and 600 with sb-paclitaxel. After a median follow-up of 49.6 months (range, 0.5 to 64.0 months), 243 invasive disease–free survival (iDFS) events were reported (143 in the sb-paclitaxel and 100 in the NAB-paclitaxel arm). At 4 years, overall patients treated with NAB-paclitaxel had a significantly better iDFS compared with sb-paclitaxel (84.0% v 76.3%; hazard ratio, 0.66; 95% CI, 0.51 to 0.86; P = .002), whereas overall survival did not significantly differ between the two treatment arms (89.7% v 87.2%, respectively; hazard ratio, 0.82; 95% CI, 0.59 to 1.16; P = .260). Long-term follow-up of the treatment-related peripheral sensory neuropathy (PSN) showed a significant decrease of the median time to resolve PSN after NAB-paclitaxel 125 mg/m2 compared with NAB-paclitaxel 150 mg/m2. CONCLUSION The significantly higher pathologic complete response rate with NAB-paclitaxel translated into a significantly improved iDFS in patients with early BC as compared with sb-paclitaxel. PSN improved much faster under NAB-paclitaxel 125 mg/m2 compared with NAB-paclitaxel 150 mg/m2.
CRIS-Team Scopus Importer:2019-09-03

(Neo-)Adjuvant and first-line therapy: Prognostic and predictive factors (Neo-)Adjuvanten und First-Line-Therapie: Prognostische und prädiktive Faktoren - Lux, Michael P.; Oenuegoeren, Onur; Wunderle, Marius; Hein, Alexander; Rauh, Claudia; Schrauder, Michael G.; Fasching, Peter; Beckmann, Matthias (Gynäkologe, 2015)
The number of cancer cases is increasing steadily. In Germany, 97,480 women are diagnosed with a gynecological malignancy each year, which represents 43 % of all cancer cases in women. Furthermore, gynecological malignancies are responsible for 28 % of cancer deaths. These numbers highlight the need for optimal, individualized treatment decisions in order to achieve maximum effectiveness, prevent recurrence and metastatic progression, and avoid overtreatment. Reliable and validated prognostic and predictive factors are required for the therapy decision of (neo-)adjuvant or first-line treatment of patients with gynecological cancers or breast cancer. In the era of individualized and targeted therapy there are fewer predictive factors available than originally thought. Nevertheless, future perspectives for various tumor entities present promising approaches which can support therapeutic decisions for adjuvant systemic therapy, e.g. gene expression analyses, studies of gene copy variations or the detection of single mutations which play an important role in signaling pathways of tumor cells.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Antineoplastic agents; Biomarkers; Breast neoplasms; Decision making; Gene expression

Neoadjuvant carboplatin in patients with triple-negative and HER2-positive early breast cancer (GeparSixto; GBG 66): a randomised phase 2 trial - Von Minckwitz, Gunter; Schneeweiss, Andreas; Loibl, Sibylle; Salat, Christoph; Denkert, Carsten; Rezai, Mahdi; Blohmer, Jens U.; Jackisch, Christian; Paepke, Stefan; Gerber, Bernd; Zahm, Dirk M.; Kummel, Sherko; et al. (Lancet Oncology, 2014)
Preclinical data suggest that triple-negative breast cancers are sensitive to interstrand crosslinking agents, and that synergy may exist for the combination of a taxane, trastuzumab, and a platinum salt for HER2-positive breast cancer. We therefore aimed to assess the efficacy of the addition of carboplatin to neoadjuvant therapy for triple-negative and HER2-positive breast cancer.Patients with previously untreated, non-metastatic, stage II-III, triple-negative breast cancer and HER2-positive breast cancer were enrolled. Patients were treated for 18 weeks with paclitaxel (80 mg/m(2) once a week) and non-pegylated liposomal doxorubicin (20 mg/m(2) once a week). Patients with triple-negative breast cancer received simultaneous bevacizumab (15 mg/kg intravenously every 3 weeks). Patients with HER2-positive disease received simultaneous trastuzumab (8 mg/kg initial dose with subsequent doses of 6 mg/kg intravenously every 3 weeks) and lapatinib (750 mg daily). Patients were randomly assigned in a 1:1 ratio with dynamic allocation and minimisation, stratified by biological subtype and Ki-67 level to receive, at the same time as the backbone regimens, either carboplatin (AUC 1·5 [2·0 for the first 329 patients] once a week) or no carboplatin. The primary endpoint the proportion of patients who achieved a pathological complete response (defined as ypT0 ypN0), analysed for all patients who started treatment; a p value of less than 0·2 was deemed significant for the primary endpoint. This trial is registered with ClinicalTrials.gov, number NCT01426880.296 patients were randomly assigned to receive carboplatin and 299 to no additional carboplatin, of whom 295 and 293 started treatment, respectively. In this final analysis, 129 patients (43·7%, 95% CI 38·1-49·4) in the carboplatin group achieved a pathological complete response, compared with 108 patients (36·9%, 31·3-42·4) without carboplatin (odds ratio 1·33, 95% CI 0·96-1·85; p=0·107). Of the patients with triple-negative breast cancer, 84 (53·2%, 54·4-60·9) of 158 patients achieved a pathological complete response with carboplatin, compared with 58 (36·9%, 29·4-44·5) of 157 without (p=0·005). Of the patients with HER2-positive tumours, 45 (32·8%, 25·0-40·7) of 137 patients achieved a pathological complete response with carboplatin compared with 50 (36·8%, 28·7-44·9) of 136 without (p=0·581; test for interaction p=0·015). Haematological and non-haematological toxic effects that were significantly more common in the carboplatin group than in the no-carboplatin group included grade 3 or 4 neutropenia (192 [65%] vs 79 [27%]), grade 3 or 4 anaemia (45 [15%] vs one [<1%]), grade 3 or 4 thrombocytopenia (42 [14%] vs one [<1%]), and grade 3 or 4 diarrhoea (51 [17%] vs 32 [11%]); carboplatin was more often associated with dose discontinuations (141 [48%] with carboplatin and 114 [39%] without carboplatin; p=0·031). The frequency of grade 3 or 4 haematological events decreased from 82% (n=135) to 70% (n=92) and grade 3 or 4 non-haematological events from 78% (n=128) to 59% (n=77) in the carboplatin arm when the dose of carboplatin was reduced from AUC 2·0 to 1·5.The addition of neoadjuvant carboplatin to a regimen of a taxane, an anthracycline, and targeted therapy significantly increases the proportion of patients achieving a pathological complete response. This regimen seems to increase responses in patients with triple-negative breast cancer, but not in those with HER2-positive breast cancer.GlaxoSmithKline, Roche, and Tev
EVALuna2:17513

Neoadjuvant chemotherapy in breast cancer: Which diagnostic procedures can be used? - Löhberg, Christian; Lux, Michael P.; Ackermann, Sven; Pöhls, Uwe G.; Bani, Mayada; Schulz-Wendtland, Rüdiger; Papadopoulos, Thomas; Schmucker, Martin; Beckmann, Matthias; Fasching, Peter (Anticancer Research, 2005)
BACKGROUND To improve breast cancer treatment, the evaluation of predictive factors is in the focus of clinical research. Significant discrepancies between the clinical assessment of response to neoadjuvant chemotherapy (NACT) and the pathological assessment of response from post-therapy surgical specimens have been demonstrated. We focused on comparing the value of various diagnostic methods used in medical routine. PATIENTS AND METHODS A clinical evaluation of the primary tumour and regional lymph nodes before and after NACT was performed in 139 patients by physical examination, sonography and mammography. RESULTS Mammography and physical examination correlated best with pathological findings in the measurement of the tumour, whereas sonography was the most accurate predictor of the status for axillary lymph nodes. CONCLUSION Mammography and physical examination are the best non-invasive predictors of the real size of the primary breast cancer, whereas sonography correlates better with the proven status of axillary lymph nodes.
Keywords: Neoadjuvant chemotherapy; breast cancer; mammography; sonography

Neoadjuvant durvalumab improves survival in early triple-negative breast cancer independent of pathological complete response - Loibl, S.; Schneeweiss, A.; Huober, J.; Braun, M.; Rey, J.; Blohmer, J. U.; Furlanetto, J.; Zahm, D. M.; Hanusch, C.; Thomalla, J.; Jackisch, C.; Staib, P.; et al. (Annals of Oncology, 2022)
BACKGROUND: Addition of immune checkpoint inhibitors to neoadjuvant chemotherapy (NACT) is a promising strategy in early breast cancer, but the optimal duration of therapy is currently unknown. In the GeparNuevo (NCT02685059) trial, addition of durvalumab to NACT as previously reported led to a moderate increase in pathological complete response (pCR) rate by an absolute 9% (P = 0.287). PATIENTS AND METHODS: Patients with cT1b-cT4a-d triple-negative breast cancer (TNBC) received durvalumab 1.5 g or placebo every 4 weeks added to nab-paclitaxel 125 mg/m2 weekly for 12 weeks, followed by durvalumab/placebo every 4 weeks plus epirubicin/cyclophosphamide every 2 weeks followed by surgery. Durvalumab was not continued after surgery. The primary objective was pCR. Secondary endpoints included invasive disease-free survival (iDFS), distant disease-free survival (DDFS) and overall survival (OS). RESULTS: A total of 174 patients were randomised between June 2016 and October 2017. After a median follow-up of 43.7 months, 34 events had occurred. Despite a non-significant increase in the pCR rate, significant differences were observed for 3-year iDFS, DDFS and OS: iDFS was 85.6% with durvalumab versus 77.2% with placebo [hazard ratio (HR) 0.48, 95% confidence interval (CI) 0.24-0.97, stratified log-rank P = 0.036]; DDFS 91.7% versus 78.4% (HR 0.31, 95% CI 0.13-0.74, P = 0.005); OS 95.2% versus 83.5% (HR 0.24, 95% CI 0.08-0.72, P = 0.006). pCR patients had 3-year iDFS of 95.5% with durvalumab and 86.1% without (HR 0.22, 95% CI 0.05-1.06). In the non-pCR cohort 3-year iDFS was 76.3% versus 69.7% (HR 0.67, 95% CI 0.29-1.54). Multivariable analysis confirmed a durvalumab effect independent of the pCR effect. No new safety signals occurred. CONCLUSIONS: Durvalumab added to NACT in TNBC significantly improved survival despite a modest pCR increase and no adjuvant component of durvalumab. Additional studies are needed to clarify the optimal duration and sequence of checkpoint inhibitors in the treatment of early TNBC.
CRIS-Team Scopus Importer:2022-11-11
Keywords: checkpoint inhibitor; durvalumab; early triple-negative breast cancer; neoadjuvant chemotherapy; survival

Neoadjuvant giredestrant (GDC-9545) + palbociclib (palbo) vs anastrozole (A) plus palbo in post-menopausal women with oestrogen receptor-positive, HER2-negative, untreated early breast cancer (ER+/HER2-eBC): Interim analysis of the randomised, open-label, phase II coopERA BC study - Hurvitz, S. A.; Park, Y. H.; Bardia, A.; Quiroga, V.; Lopez-Valverde, V.; Steinseifer, J.; Moore, H. M.; Spera, G.; Xue, C.; Fasching, Peter (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Neoadjuvant immunotherapy and chemotherapy regimens for the treatment of high-risk, early-stage triple-negative breast cancer: a systematic review and network meta-analysis - Cortes, Javier; Haiderali, Amin; Huang, Min; Pan, Wilbur; Schmid, Peter; Akers, Katherine G.; Park, Julie E.; Frederickson, Andrew M.; Fasching, Peter; O’Shaughnessy, Joyce (BMC Cancer, 2023)
Background: Patients with triple-negative breast cancer (TNBC) are generally younger and more likely to experience disease recurrence and have the shortest survival among all breast cancer patients. Recently, neoadjuvant delivery of the programmed cell death protein-1 inhibitor pembrolizumab plus chemotherapy followed by adjuvant pembrolizumab was approved for patients with high-risk, early-stage TNBC, but this treatment regimen has not been evaluated in head-to-head trials with other neoadjuvant treatment regimens. Therefore, the objective of this study was to estimate the relative efficacy of neoadjuvant pembrolizumab + chemotherapy followed by adjuvant pembrolizumab versus other neoadjuvant treatments for early-stage TNBC through a systematic review and network meta-analysis (NMA). Methods: EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, conference abstracts, and clinical trial registries were searched for randomized controlled trials evaluating neoadjuvant treatments for early-stage TNBC. NMA was performed to estimate relative treatment effects among evaluated interventions. Results: Five trials met the inclusion criteria and were included in the NMA. The relative efficacy of neoadjuvant pembrolizumab + chemotherapy followed by adjuvant pembrolizumab was favorable to paclitaxel followed by anthracycline + cyclophosphamide in terms of pathologic complete response (pCR), event-free survival (EFS), and overall survival; paclitaxel + carboplatin followed by anthracycline + cyclophosphamide in terms of pCR and EFS; paclitaxel + bevacizumab followed by anthracycline + cyclophosphamide + bevacizumab in terms of pCR; and paclitaxel + carboplatin + veliparib followed by anthracycline + cyclophosphamide in terms of EFS. Conclusions: Neoadjuvant pembrolizumab + chemotherapy followed by adjuvant pembrolizumab confers benefits in response and survival outcomes versus alternative neoadjuvant treatments for early-stage TNBC.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Chemotherapy; Immunotherapy; Neoadjuvant therapy; Network meta-analysis; PD-1; PD-L1; Triple-negative breast cancer

Neoadjuvant Paclitaxel/Olaparib in Comparison to Paclitaxel/Carboplatin in Patients with HER2-Negative Breast Cancer and HRD-Long-term Survival of the GeparOLA Study - Fasching, Peter; Schmatloch, Sabine; Hauke, Jan; Rey, Julia; Jackisch, Christian; Klare, Peter; Link, Theresa; Hanusch, Claus; Huober, Jens; Stefek, Andrea; Holtschmidt, Johannes; Schneeweiss, Andreas; et al. (Clinical Cancer Research, 2025)
PURPOSE: The GeparOLA study evaluated paclitaxel plus olaparib (PO) in neoadjuvant chemotherapy for patients with HER2-negative early breast cancer with homologous recombination deficiency (HRD). HRD was defined by high HRD score or germline (g)/tumor (t) BRCA1/2 mutations (g/tBRCA1/2mut). In this study, we report long-term outcome data. PATIENTS AND METHODS: GeparOLA (NCT02789332) was a randomized, multicenter, prospective, open-label, phase II trial. Patients with HER2-negative early breast cancer with HRD with an indication for chemotherapy (cT2-cT4a-d or cT1c and cN+ or cT1c and pNSLN+ or cT1c and triple-negative breast cancer, or cT1c and Ki-67 >20%) were randomly assigned to PO or paclitaxel + carboplatin (PCb), both followed by epirubicin + cyclophosphamide. Long-term efficacy endpoints were secondary endpoints and included invasive disease-free survival (iDFS), distant disease-free survival (DDFS), and overall survival, with a planned median follow-up of >4 years. RESULTS: Between September 2016 and July 2018, 107 patients were randomized and 106 (PO N = 69 and PCb N = 37) started treatment. The median age was 47.0 years; of all patients, 35.8% had cT1 tumors, 31.4% were cN+, 86.8% had G3 tumors, 89.6% had Ki-67 >20%, and 72.6% were triple negative. After a median follow-up of 49.8 months, 18 (15 in PO and three in PCb) iDFS events and seven (six in PO and one in PCb) deaths were reported. The 4-year iDFS (76.0% PO vs. 88.5% PCb, hazard ratio = 2.86; 95% CI, 0.83-9.90; log-rank P = 0.081), DDFS (81.2% PO vs. 93.4% PCb, hazard ratio = 3.03; 95% CI, 0.67-13.67; log-rank P = 0.129), and overall survival (89.2% PO vs. 96.9% PCb, hazard ratio = 3.27; 95% CI, 0.39-27.20; log-rank P = 0.244) tended to be inferior with olaparib. Patients without g/tBRCA1/2mut benefited from Cb (seven of 30 patients had iDFS/DDFS events in PO vs. 0/16 in PCb; log-rank P = 0.037), whereas no difference for patients with g/tBRCA1/2mut was observed (hazard ratio = 1.16, log-rank P = 0.83). CONCLUSIONS: For HER2-negative early breast cancer with HRD, olaparib showed a tendency for inferior outcomes compared with Cb, particularly in patients without g/tBRCA1/2mut. In patients with g/tBRCA1/2mut, olaparib may replace Cb.
CRIS-Team Scopus Importer:2025-05-23

Neoadjuvant paclitaxel/olaparib in comparison to paclitaxel/carboplatinum in patients with HER2-negative breast cancer and homologous recombination deficiency (GeparOLA study) - Fasching, Peter; Link, T.; Hauke, J.; Seither, F.; Jackisch, C.; Klare, P.; Schmatloch, S.; Hanusch, C.; Huober, J.; Stefek, A.; Seiler, S.; Schmitt, W. D.; et al. (Annals of Oncology, 2020)
Background: The efficacy and toxicity of olaparib as combination therapy in early breast cancer (BC) patients with homologous recombinant deficiency (HRD) [score high and/or germline (g) or tumour (t) BRCA1/2 mutation] is not well described. GeparOLA (ClinicalTrials.gov, NCT02789332) investigated olaparib in combination with paclitaxel in HER2-negative early BC with HRD. Patients and methods: Patients with untreated primary HER2-negative cT2-cT4a-d or cT1c with either cN+ or pNSLN+ or cT1c and triple-negative breast cancer (TNBC) or cT1c and Ki-67>20% BC with HRD were randomised either to paclitaxel (P) 80 mg/m2 weekly plus olaparib (O) 100 mg twice daily for 12 weeks or P plus carboplatinum (Cb) area under the curve 2 weekly for 12 weeks, both followed by epirubicin/cyclophosphamide (EC). Stratification factors were hormone receptor (HR) status (HR+ versus HR−) and age (<40 versus ≥40 years). The primary endpoint was pathological complete response (pCR; ypT0/is ypN0). A two-sided one-group χ2-test was planned to exclude a pCR rate of ≤55% in the PO-EC arm. Secondary end points were other pCR definitions, breast conservation rate, clinical/imaging response, tolerability and safety. Results: A total of 107 patients were randomised between September 2016 and July 2018; 106 (PO N = 69; PCb N = 37) started treatment. Median age was 47.0 years (range 25.0-71.0); 36.2% had cT1, 61.0% cT2, 2.9% cT3, and 31.8% cN-positive tumours; grade 3 tumours: 86.8%; Ki-67>20%: 89.6%; TNBC: 72.6%; confirmed gBRCA1/2 mutation: 56.2%. The pCR rate with PO was 55.1% [90% confidence interval (CI) 44.5% to 65.3%] versus PCb 48.6% (90% CI 34.3% to 63.2%). Analysis for the stratified subgroups showed higher pCR rates with PO in the cohorts of patients <40 years and HR+ patients. Conclusion: GeparOLA could not exclude a pCR rate of ≤55% in the PO arm. PO was significantly better tolerated and the combination merits further evaluation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: carboplatinum; HER2-negative breast cancer; HRD; neoadjuvant therapy; olaparib; PARP inhibitor

Neoadjuvant palbociclib plus either giredestrant or anastrozole in oestrogen receptor-positive, HER2-negative, early breast cancer (coopERA Breast Cancer): an open-label, randomised, controlled, phase 2 study - Hurvitz, Sara A.; Bardia, Aditya; Quiroga, Vanesa; Park, Yeon Hee; Blancas, Isabel; Alonso-Romero, José Luis; Vasiliev, Aleksandr; Adamchuk, Hryhoriy; Salgado, Marcelo; Yardley, Denise A.; Berzoy, Oleksandr; Zamora-Auñón, Pilar; et al. (Lancet Oncology, 2023)
BACKGROUND: The development of more potent selective oestrogen receptor antagonists and degraders (SERDs) that can be orally administered could help to address the limitations of current endocrine therapies. We report the primary and final analyses of the coopERA Breast Cancer study, designed to test whether giredestrant, a highly potent, non-steroidal, oral SERD, would show a stronger anti-proliferative effect than anastrozole after 2 weeks for oestrogen receptor-positive, HER2-negative, untreated early breast cancer. METHODS: In this open-label, randomised, controlled, phase 2 study, postmenopausal women were eligible if they were aged 18 years or older; had clinical T stage (cT)1c to cT4a-c (≥1·5 cm within cT1c) oestrogen receptor-positive, HER2-negative, untreated early breast cancer; an Eastern Cooperative Oncology Group performance status of 0-1; and baseline Ki67 score of at least 5%. The study was conducted at 59 hospital or clinic sites in 11 countries globally. Participants were randomly assigned (1:1) to giredestrant 30 mg oral daily or anastrozole 1 mg oral daily on days 1-14 (window-of-opportunity phase) via an interactive web-based system with permuted-block randomisation with block size of four. Randomisation was stratified by cT stage, baseline Ki67 score, and progesterone receptor status. A 16-week neoadjuvant phase comprised the same regimen plus palbociclib 125 mg oral daily on days 1-21 of a 28-day cycle, for four cycles. The primary endpoint was geometric mean relative Ki67 score change from baseline to week 2 in patients with complete central Ki67 scores at baseline and week 2 (window-of-opportunity phase). Safety was assessed in all patients who received at least one dose of study drug. The study is registered with ClinicalTrials.gov (NCT04436744) and is complete. FINDINGS: Between Sept 4, 2020, and June 22, 2021, 221 patients were enrolled and randomly assigned to the giredestrant plus palbociclib group (n=112; median age 62·0 years [IQR 57·0-68·5]) or anastrozole plus palbociclib group (n=109; median age 62·0 [57·0-67·0] years). 15 (7%) of 221 patients were Asian, three (1%) were Black or African American, 194 (88%) were White, and nine (4%) were unknown races. At data cutoff for the primary analysis (July 19, 2021), the geometric mean relative reduction of Ki67 from baseline to week 2 was -75% (95% CI -80 to -70) with giredestrant and -67% (-73 to -59) with anastrozole (p=0·043), meeting the primary endpoint. At the final analysis (data cutoff Nov 24, 2021), the most common grade 3-4 adverse events were neutropenia (29 [26%] of 112 in the giredestrant plus palbociclib group vs 29 [27%] of 109 in the anastrozole plus palbociclib group) and decreased neutrophil count (17 [15%] vs 16 [15%]). Serious adverse events occurred in five (4%) patients in the giredestrant plus palbociclib group and in two (2%) patients in the anastrozole plus palbociclib group. There were no treatment-related deaths. One patient died due to an adverse event in the giredestrant plus palbociclib group (myocardial infarction). INTERPRETATION: Giredestrant offers encouraging anti-proliferative and anti-tumour activity and was well tolerated, both as a single agent and in combination with palbociclib. Results justify further investigation in ongoing trials. FUNDING: F Hoffmann-La Roche.
CRIS-Team Scopus Importer:2023-09-08

Neoadjuvant pembrolizumab plus chemotherapy/adjuvant pembrolizumab for early-stage triple-negative breast cancer: Quality-of-life results from the randomized KEYNOTE-522 study - Dent, Rebecca; Cortés, Javier; Pusztai, Lajos; McArthur, Heather; Kümmel, Sherko; Bergh, Jonas; Denkert, Carsten; Park, Yeon Hee; Hui, Rina; Harbeck, Nadia; Takahashi, Masato; Untch, Michael; et al. (Journal of the National Cancer Institute, 2024)
Background: In KEYNOTE-522 (NCT03036488), neoadjuvant pembrolizumab plus chemotherapy and then adjuvant pembrolizumab significantly improved pathological complete response and event-free survival vs neoadjuvant chemotherapy in early-stage triple-negative breast cancer (TNBC). We report patient-reported outcomes (PROs) from KEYNOTE-522. Methods: Patients were randomized 2:1 to neoadjuvant pembrolizumab 200 mg or placebo every 3 weeks, plus 4 cycles of paclitaxel plus carboplatin and then 4 cycles of doxorubicin (or epirubicin) plus cyclophosphamide. After surgery, patients received adjuvant pembrolizumab or placebo for up to 9 cycles. European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) and EORTC Breast Cancer-Specific Quality of Life Questionnaire (EORTC QLQ-BR23) were prespecified secondary objectives. Between-group differences in least squares (LS) mean change from baseline (day 1 of cycle 1 in both neoadjuvant and adjuvant phases) to the prespecified latest time point with at least 60% completion and at least 80% compliance were assessed using a longitudinal model (no alpha error assigned). Results: Week 21 (neoadjuvant phase) and week 24 (adjuvant phase) were the latest time points at which completion/compliance rates were ≥60%/80%. In the neoadjuvant phase, between-group differences (pembrolizumab plus chemotherapy [n = 762] vs placebo plus chemotherapy [n = 383]) in LS mean change from baseline to week 21 in QLQ-C30 global health status/quality of life (GHS/QoL), emotional functioning, and physical functioning were -1.04 (95% confidence interval = -3.46 to 1.38), -0.69 (95% CI = -3.13 to 1.75), and -2.85 (95% CI = -5.11 to -0.60), respectively. In the adjuvant phase, between-group differences (pembrolizumab [n = 539] vs placebo [n = 308]) in LS mean change from baseline to week 24 were -0.41 (95% CI = -2.60 to 1.77), -0.60 (95% CI = -2.99 to 1.79), and -1.57 (95% CI = -3.36 to 0.21). Conclusions: No substantial differences in PRO assessments were observed between neoadjuvant pembrolizumab plus chemotherapy followed by adjuvant pembrolizumab vs neoadjuvant placebo plus chemotherapy in early-stage TNBC.
CRIS-Team Scopus Importer:2024-11-01
Keywords: cancer; chemotherapy regimen; emotions; immunologic adjuvants; pharmaceutical adjuvants; neoadjuvant therapy; organizations; european continental ancestry group; world health; quality of life; european organization for research and treatment of cancer; triple-negative breast cancer; patient self-report; chemotherapy; neoadjuvant; physical function; pembrolizumab; pik3ca-related overgrowth spectrum

Neoadjuvant pembrolizumab plus chemotherapy followed by adjuvant pembrolizumab for treatment of high-risk, early-stage triple-negative breast cancer: A network meta-analysis - Cortes, J.; Haiderali, A.; Huang, M.; Pan, W.; Fox, G. E.; Park, J.; Frederickson, A. M.; Fasching, Peter; O'Shaughnessy, J. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-23

Neoadjuvant pembrolizumab plus chemotherapy versus placebo plus chemotherapy, followed by adjuvant pembrolizumab versus placebo for early-stage TNBC: Event-free survival sensitivity and subgroup analyses from KEYNOTE-522 - Schmid, Peter; Cortes, Javier; Dent, Rebecca; Pusztai, Lajos; Mcarthur, Heather; Kuemmel, Sherko; Bergh, Jonas; Denkert, Carsten; Park, Yeon Hee; Hui, Rina; Harbeck, Nadia; Takahashi, Masato; et al. (ASIA-PACIFIC JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-11

Neoadjuvant trastuzumab emtansine and pertuzumab in human epidermal growth factor receptor 2–positive breast cancer: Three-year outcomes from the phase III KristinE study - Hurvitz, Sara A.; Martin, Miguel; Jung, Kyung Hae; Huang, Chiun Sheng; Harbeck, Nadia; Valero, Vicente; Stroyakovskiy, Daniil; Wildiers, Hans; Campone, Mario; Boileau, Jean François; Fasching, Peter; Afenjar, Karen; et al. (Journal of Clinical Oncology, 2019)
PURPOSE The KRISTINE study compared neoadjuvant trastuzumab emtansine plus pertuzumab (T-DM1+P) with docetaxel, carboplatin, trastuzumab plus P (TCH+P) for the treatment human epidermal growth factor receptor 2–positive stage II to III breast cancer. T-DM1+P led to a lower pathologic complete response rate (44.4% v 55.7%; P = .016), but fewer grade 3 or greater and serious adverse events (AEs). Here, we present 3-year outcomes from KRISTINE. METHODS Patients were randomly assigned to neoadjuvant T-DM1+P or TCH+P every 3 weeks for six cycles. Patients who received T-DM1+P continued adjuvant T-DM1+P, and patients who received TCH+P received adjuvant trastuzumab plus pertuzumab. Secondary end points included event-free survival (EFS), overall survival, patient-reported outcomes (measured from random assignment), and invasive disease-free survival (IDFS; measured from surgery). RESULTS Of patients, 444 were randomly assigned (T-DM1+P, n = 223; TCH+P, n = 221). Median follow-up was 37 months. Risk of an EFS event was higher with TDM-1+P (hazard ratio [HR], 2.61 [95% CI, 1.36 to 4.98]) with more locoregional progression events before surgery (15 [6.7%] v 0). Risk of an IDFS event after surgery was similar between arms (HR, 1.11 [95% CI, 0.52 to 2.40]). Pathologic complete response was associated with a reduced risk of an IDFS event (HR, 0.24 [95% CI, 0.09 to 0.60]) regardless of treatment arm. Overall, grade 3 or greater AEs (31.8% v 67.7%) were less common with T-DM1+P. During adjuvant treatment, grade 3 or greater AEs (24.5% v 9.9%) and AEs leading to treatment discontinuation (18.4% v 3.8%) were more common with T-DM1+P. Patient-reported outcomes favored T-DM1+P during neoadjuvant treatment and were similar to trastuzumab plus pertuzumab during adjuvant treatment. CONCLUSION Compared with TCH+P, T-DM1+P resulted in a higher risk of an EFS event owing to locoregional progression events before surgery, a similar risk of an IDFS event, fewer grade 3 or greater AEs during neoadjuvant treatment, and more AEs leading to treatment discontinuation during adjuvant treatment.
CRIS-Team Scopus Importer:2019-09-03

Neoadjuvant Treatment of Breast Cancer - Advances and Limitations - Fasching, Peter; Gaß, Paul; Hein, Alexander (Breast Care, 2016)
EVALuna2:33102

Network-Based Integration of GWAS and Gene Expression Identifies a HOX-Centric Network Associated with Serous Ovarian Cancer Risk - Kar, Siddhartha P.; Tyrer, Jonathan P.; Li, Qiyuan; Lawrenson, Kate; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Chenevix-Trench, Georgia; Baker, Helen; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
Genome-wide association studies (GWAS) have so far reported 12 loci associated with serous epithelial ovarian cancer (EOC) risk. We hypothesized that some of these loci function through nearby transcription factor (TF) genes and that putative target genes of these TFs as identified by coexpression may also be enriched for additional EOC risk associations.We selected TF genes within 1 Mb of the top signal at the 12 genome-wide significant risk loci. Mutual information, a form of correlation, was used to build networks of genes strongly coexpressed with each selected TF gene in the unified microarray dataset of 489 serous EOC tumors from The Cancer Genome Atlas. Genes represented in this dataset were subsequently ranked using a gene-level test based on results for germline SNPs from a serous EOC GWAS meta-analysis (2,196 cases/4,396 controls).Gene set enrichment analysis identified six networks centered on TF genes (HOXB2, HOXB5, HOXB6, HOXB7 at 17q21.32 and HOXD1, HOXD3 at 2q31) that were significantly enriched for genes from the risk-associated end of the ranked list (P < 0.05 and FDR < 0.05). These results were replicated (P < 0.05) using an independent association study (7,035 cases/21,693 controls). Genes underlying enrichment in the six networks were pooled into a combined network.We identified a HOX-centric network associated with serous EOC risk containing several genes with known or emerging roles in serous EOC development.Network analysis integrating large, context-specific datasets has the potential to offer mechanistic insights into cancer susceptibility and prioritize genes for experimental characterization. Cancer Epidemiol Biomarkers Prev; 24(10); 1574-84. ©2015 AACR.
EVALuna2:9287

Next-generation DNA sequencing (NGS) results for tumours from phase II ABRAZO study of talazoparib after platinum or cytotoxic non-platinum regimens in patients (pts) with advanced breast cancer (ABC) and germline BRCA1/2 (gBRCA) mutations - Turner, N. C.; Laird, A. D.; Telli, M. L.; Rugo, H. S.; Mailliez, A.; Ettl, J.; Grischke, E. -M.; Mina, L. A.; Balmana, J.; Fasching, Peter; Hurvitz, S. A.; Albacker, L. A.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

NGS zur Selektion innovativer Therapien – Was bringt das? - Schulmeyer, Carla; Bader, Simon; Hübner, Hanna; Rübner, Matthias; Fasching, Peter (Gynäkologe, 2021)
Next generation sequencing (NGS) describes a technology for sequencing the entire human genome, exome and transcriptome and has revolutionized genomic research. In comparison to Sanger sequencing NGS is able to sequence a whole human genome within 1 day. The results can be aligned with reference human genomes. Through DNA fragmentation, ligation of adaptors on the ends of fragments and amplification of the fragments a bioinformatics analysis is carried out, which is stored in the form of a chip and sequenced. The NGS can be used in multiple applications, especially in genetic, microbiological and oncologic research and has not yet become comprehensively established within the clinical routine. In obstetrics and gynecology, NGS is especially used in noninvasive prenatal testing (NIPT), reproductive medicine and oncology.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Breast cancer; DNA fragmentation; Genome; human; Genomics; Prenatal diagnostics

No clinical utility of KRAS variant rs61764370 for ovarian or breast cancer - Hollestelle, Antoinette; Van Der Baan, Frederieke H.; Berchuck, Andrew; Johnatty, Sharon E.; Aben, Katja K.; Agnarsson, Bjarni A.; Aittomaki, Kristiina; Alducci, Elisa; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Antoniou, Antonis C.; et al. (Gynecologic Oncology, 2016)
Clinical genetic testing is commercially available for rs61764370, an inherited variant residing in a KRAS 3' UTR microRNA binding site, based on suggested associations with increased ovarian and breast cancer risk as well as with survival time. However, prior studies, emphasizing particular subgroups, were relatively small. Therefore, we comprehensively evaluated ovarian and breast cancer risks as well as clinical outcome associated with rs61764370.Centralized genotyping and analysis were performed for 140,012 women enrolled in the Ovarian Cancer Association Consortium (15,357 ovarian cancer patients; 30,816 controls), the Breast Cancer Association Consortium (33,530 breast cancer patients; 37,640 controls), and the Consortium of Modifiers of BRCA1 and BRCA2 (14,765 BRCA1 and 7904 BRCA2 mutation carriers).We found no association with risk of ovarian cancer (OR=0.99, 95% CI 0.94-1.04, p=0.74) or breast cancer (OR=0.98, 95% CI 0.94-1.01, p=0.19) and results were consistent among mutation carriers (BRCA1, ovarian cancer HR=1.09, 95% CI 0.97-1.23, p=0.14, breast cancer HR=1.04, 95% CI 0.97-1.12, p=0.27; BRCA2, ovarian cancer HR=0.89, 95% CI 0.71-1.13, p=0.34, breast cancer HR=1.06, 95% CI 0.94-1.19, p=0.35). Null results were also obtained for associations with overall survival following ovarian cancer (HR=0.94, 95% CI 0.83-1.07, p=0.38), breast cancer (HR=0.96, 95% CI 0.87-1.06, p=0.38), and all other previously-reported associations.rs61764370 is not associated with risk of ovarian or breast cancer nor with clinical outcome for patients with these cancers. Therefore, genotyping this variant has no clinical utility related to the prediction or management of these cancers.
EVALuna2:9251

No Evidence That Genetic Variation in the Myeloid-Derived Suppressor Cell Pathway Influences Ovarian Cancer Survival - Sucheston-Campbell, Lara E.; Cannioto, Rikki; Clay, Alyssa I.; Etter, John Lewis; Eng, Kevin H.; Liu, Song; Battaglia, Sebastiano; Hu, Qiang; Szender, J. Brian; Minlikeeva, Albina; Joseph, Janine M.; Mayor, Paul; et al. (Cancer Epidemiology Biomarkers & Prevention, 2017)
Background: The precise mechanism by which the immune system is adversely affected in cancer patients remains poorly understood, but the accumulation of immunosuppressive/protumorigenic myeloid-derived suppressor cells (MDSCs) is thought to be a prominent mechanism contributing to immunologic tolerance of malignant cells in epithelial ovarian cancer (EOC). To this end, we hypothesized genetic variation in MDSC pathway genes would be associated with survival after EOC diagnoses.Methods: We measured the hazard of death due to EOC within 10 years of diagnosis, overall and by invasive subtype, attributable to SNPs in 24 genes relevant in the MDSC pathway in 10,751 women diagnosed with invasive EOC. Versatile Gene-based Association Study and the admixture likelihood method were used to test gene and pathway associations with survival.Results: We did not identify individual SNPs that were significantly associated with survival after correction for multiple testing (P < 3.5 × 10-5), nor did we identify significant associations between the MDSC pathway overall, or the 24 individual genes and EOC survival.Conclusions: In this well-powered analysis, we observed no evidence that inherited variations in MDSC-associated SNPs, individual genes, or the collective genetic pathway contributed to EOC survival outcomes.Impact: Common inherited variation in genes relevant to MDSCs was not associated with survival in women diagnosed with invasive EOC. Cancer Epidemiol Biomarkers Prev; 26(3); 420-4. ©2016 AACR.
EVALuna2:36152

No evidence that protein truncating variants in BRIP1 are associated with breast cancer risk: implications for gene panel testing - Easton, Douglas F.; Lesueur, Fabienne; Decker, Brennan; Michailidou, Kyriaki; Li, Jun; Allen, Jamie; Luccarini, Craig; Pooley, Karen A.; Shah, Mitul; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; et al. (Journal of Medical Genetics, 2016)
BACKGROUND: BRCA1 interacting protein C-terminal helicase 1 (BRIP1) is one of the Fanconi Anaemia Complementation (FANC) group family of DNA repair proteins. Biallelic mutations in BRIP1 are responsible for FANC group J, and previous studies have also suggested that rare protein truncating variants in BRIP1 are associated with an increased risk of breast cancer. These studies have led to inclusion of BRIP1 on targeted sequencing panels for breast cancer risk prediction. METHODS: We evaluated a truncating variant, p.Arg798Ter (rs137852986), and 10 missense variants of BRIP1, in 48 144 cases and 43 607 controls of European origin, drawn from 41 studies participating in the Breast Cancer Association Consortium (BCAC). Additionally, we sequenced the coding regions of BRIP1 in 13 213 cases and 5242 controls from the UK, 1313 cases and 1123 controls from three population-based studies as part of the Breast Cancer Family Registry, and 1853 familial cases and 2001 controls from Australia. RESULTS: The rare truncating allele of rs137852986 was observed in 23 cases and 18 controls in Europeans in BCAC (OR 1.09, 95% CI 0.58 to 2.03, p=0.79). Truncating variants were found in the sequencing studies in 34 cases (0.21%) and 19 controls (0.23%) (combined OR 0.90, 95% CI 0.48 to 1.70, p=0.75). CONCLUSIONS: These results suggest that truncating variants in BRIP1, and in particular p.Arg798Ter, are not associated with a substantial increase in breast cancer risk. Such observations have important implications for the reporting of results from breast cancer screening panels.
EVALuna2:33328

Novel Associations between Common Breast Cancer Susceptibility Variants and Risk-Predicting Mammographic Density Measures - Stone, Jennifer; Thompson, Deborah J.; Silva, Isabel Dos Santos; Scott, Christopher; Tamimi, Rulla M.; Lindstrom, Sara; Kraft, Peter; Hazra, Aditi; Li, Jingmei; Eriksson, Louise; Czene, Kamila; Hall, Per; et al. (Cancer Research, 2015)
Mammographic density measures adjusted for age and body mass index (BMI) are heritable predictors of breast cancer risk, but few mammographic density-associated genetic variants have been identified. Using data for 10,727 women from two international consortia, we estimated associations between 77 common breast cancer susceptibility variants and absolute dense area, percent dense area and absolute nondense area adjusted for study, age, and BMI using mixed linear modeling. We found strong support for established associations between rs10995190 (in the region of ZNF365), rs2046210 (ESR1), and rs3817198 (LSP1) and adjusted absolute and percent dense areas (all P < 10(-5)). Of 41 recently discovered breast cancer susceptibility variants, associations were found between rs1432679 (EBF1), rs17817449 (MIR1972-2: FTO), rs12710696 (2p24.1), and rs3757318 (ESR1) and adjusted absolute and percent dense areas, respectively. There were associations between rs6001930 (MKL1) and both adjusted absolute dense and nondense areas, and between rs17356907 (NTN4) and adjusted absolute nondense area. Trends in all but two associations were consistent with those for breast cancer risk. Results suggested that 18% of breast cancer susceptibility variants were associated with at least one mammographic density measure. Genetic variants at multiple loci were associated with both breast cancer risk and the mammographic density measures. Further understanding of the underlying mechanisms at these loci could help identify etiologic pathways implicated in how mammographic density predicts breast cancer risk.
EVALuna2:17571

Obesity and survival among women with ovarian cancer: results from the Ovarian Cancer Association Consortium - Nagle, C. M.; Dixon, S. C.; Jensen, A.; Kjaer, S. K.; Modugno, F.; Defazio, A.; Fereday, S.; Hung, J.; Johnatty, S. E.; Fasching, Peter; Beckmann, Matthias; Lambrechts, D.; et al. (British Journal of Cancer, 2015)
Observational studies have reported a modest association between obesity and risk of ovarian cancer; however, whether it is also associated with survival and whether this association varies for the different histologic subtypes are not clear. We undertook an international collaborative analysis to assess the association between body mass index (BMI), assessed shortly before diagnosis, progression-free survival (PFS), ovarian cancer-specific survival and overall survival (OS) among women with invasive ovarian cancer.We used original data from 21 studies, which included 12 390 women with ovarian carcinoma. We combined study-specific adjusted hazard ratios (HRs) using random-effects models to estimate pooled HRs (pHR). We further explored associations by histologic subtype.Overall, 6715 (54%) deaths occurred during follow-up. A significant OS disadvantage was observed for women who were obese (BMI: 30-34.9, pHR: 1.10 (95% confidence intervals (CIs): 0.99-1.23); BMI: ?35, pHR: 1.12 (95% CI: 1.01-1.25)). Results were similar for PFS and ovarian cancer-specific survival. In analyses stratified by histologic subtype, associations were strongest for women with low-grade serous (pHR: 1.12 per 5 kg m(-2)) and endometrioid subtypes (pHR: 1.08 per 5 kg m(-2)), and more modest for the high-grade serous (pHR: 1.04 per 5 kg m(-2)) subtype, but only the association with high-grade serous cancers was significant.Higher BMI is associated with adverse survival among the majority of women with ovarian cancer.
EVALuna2:17568

Occurrence and characteristics of patients with de novo advanced breast cancer according to patient and tumor characteristics – A retrospective analysis of a real world registry - Muller, Volkmar; Hein, Alexander; Hartkopf, Andreas D.; Fasching, Peter; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Luftner, Diana; Wallwiener, Markus; Beckmann, Matthias; et al. (European Journal of Cancer, 2022)
Background: Patients with de novo metastatic breast cancer (dnMBC) may have different clinical and pathological characteristics. In studies concerned with first-line metastatic patients, the proportion of these patients without secondary resistance mechanisms may have a large influence ont the study results. The aim of this study was to identify patient and tumor characteristics that are associated with dnMBC vs. recurrent MBC (rMBC). Methods: This is a retrospective analysis of data prospectively collected in the PRAEGNANT metastatic breast cancer registry (NCT02338167). Firs line treated patients were eligible. Patient and tumor characteristics were compared with common disease and tumor characteristics relative to de novo metastatic status, as well as early and late recurrences after primary disease without metastases. Results: Among the 947 patients identified, 355 were included with de novo metastatic disease (37.5%). Older age and HER2-positive disease were significantly associated with a higher frequency of dnMBC. Patients younger than 50, 50–69, or 70 years or older had dnMBC frequencies of 22.7%, 44.0%, and 57.6%, respectively. HER2-positive patients had dnMBC at initial presentation in 49.1% of cases, in comparison with 21.9%, 35.5%, and 37.6% in patients with triple-negative, luminal A–like and luminal B–like breast cancer, respectively. Conclusion: Age and breast cancer subtype are associated with the frequency of first-line MBC patients. Inclusion criteria concerning age or breast cancer subtype can influence the frequency of these patients in a selected patient population and can therefore modify the number of patients with secondary resistance to specific therapies in clinical trials.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Advanced breast cancer; Clinical trials; de novo metastatic breast cancer; Recurrent breast cancer metastases

OLAPARIB IN GERMAN ROUTINE CLINICAL PRACTICE - INTERIM RESULTS OF THE NON-INTERVENTIONAL STUDY C-PATROL - Marme, F.; Sehouli, J.; Welslau, M.; Schinkoethe, T.; El-Balat, A.; Fasching, Peter; Glowik, R.; Hilpert, F. (2017)
EVALuna2:36181

On-treatment biopsies to predict response to neoadjuvant chemotherapy for breast cancer - Sinn, Bruno Valentin; Sychra, Katharina; Untch, Michael; Karn, Thomas; van Mackelenbergh, Marion; Huober, Jens; Schmitt, Wolfgang; Marmé, Frederik; Schem, Christian; Solbach, Christine; Stickeler, Elmar; Tesch, Hans; et al. (Breast Cancer Research, 2024)
Background: Patients with pathologic complete response (pCR) to neoadjuvant chemotherapy for invasive breast cancer (BC) have better outcomes, potentially warranting less extensive surgical and systemic treatments. Early prediction of treatment response could aid in adapting therapies. Methods: On-treatment biopsies from 297 patients with invasive BC in three randomized, prospective neoadjuvant trials were assessed (GeparQuattro, GeparQuinto, GeparSixto). BC quantity, tumor-infiltrating lymphocytes (TILs), and the proliferation marker Ki-67 were compared to pre-treatment samples. The study investigated the correlation between residual cancer, changes in Ki-67 and TILs, and their impact on pathologic complete response (pCR) and disease-free survival (DFS). Results: Among the 297 samples, 138 (46%) were hormone receptor-positive (HR+)/human epidermal growth factor 2-negative (HER2−), 87 (29%) were triple-negative (TNBC), and 72 (24%) were HER2+. Invasive tumor cells were found in 70% of on-treatment biopsies, with varying rates across subtypes (HR+/HER2−: 84%, TNBC: 62%, HER2+: 51%; p < 0.001). Patients with residual tumor on-treatment had an 8% pCR rate post-treatment (HR+/HER2−: 3%, TNBC: 19%, HER2+: 11%), while those without any invasive tumor had a 50% pCR rate (HR+/HER2−: 27%; TNBC: 48%, HER2+: 66%). Sensitivity for predicting residual disease was 0.81, with positive and negative predictive values of 0.92 and 0.50, respectively. Increasing TILs from baseline to on-treatment biopsy (if residual tumor was present) were linked to higher pCR likelihood in the overall cohort (OR 1.034, 95% CI 1.013–1.056 per % increase; p = 0.001) and with a longer DFS in TNBC (HR 0.980, 95% CI 0.963–0.997 per % increase; p = 0.026). Persisting or increased Ki-67 was associated with with lower pCR probability in the overall cohort (OR 0.957, 95% CI 0.928–0.986; p = 0.004) and shorter DFS in TNBC (HR 1.023, 95% CI 1.001–1.047; p = 0.04). Conclusion: On-treatment biopsies can predict patients unlikely to achieve pCR post-therapy. This could facilitate therapy adjustments for TNBC or HER2 + BC. They also might offer insights into therapy resistance mechanisms. Future research should explore whether standardized or expanded sampling enhances the accuracy of on-treatment biopsy procedures. Trial registration GeparQuattro (EudraCT 2005-001546-17), GeparQuinto (EudraCT 2006-005834-19) and GeparSixto (EudraCT 2011-000553-23).
CRIS-Team Scopus Importer:2024-10-04
Keywords: Breast cancer; Ki-67; Neoadjuvant therapy; Serial biopsies; TILs

Optimizing R with SparkR on a commodity cluster for biomedical research - Sedlmayr, Martin; Würfl, Tobias; Maier, Christian; Haeberle, Lothar; Fasching, Peter; Prokosch, Hans-Ulrich; Christoph, Jan (Computer Methods and Programs in Biomedicine, 2016)
Medical researchers are challenged today by the enormous amount of data collected in healthcare. Analysis methods such as genome-wide association studies (GWAS) are often computationally intensive and thus require enormous resources to be performed in a reasonable amount of time. While dedicated clusters and public clouds may deliver the desired performance, their use requires upfront financial efforts or anonymous data, which is often not possible for preliminary or occasional tasks. We explored the possibilities to build a private, flexible cluster for processing scripts in R based on commodity, non-dedicated hardware of our department.For this, a GWAS-calculation in R on a single desktop computer, a Message Passing Interface (MPI)-cluster, and a SparkR-cluster were compared with regards to the performance, scalability, quality, and simplicity.The original script had a projected runtime of three years on a single desktop computer. Optimizing the script in R already yielded a significant reduction in computing time (2 weeks). By using R-MPI and SparkR, we were able to parallelize the computation and reduce the time to less than three hours (2.6 h) on already available, standard office computers. While MPI is a proven approach in high-performance clusters, it requires rather static, dedicated nodes. SparkR and its Hadoop siblings allow for a dynamic, elastic environment with automated failure handling. SparkR also scales better with the number of nodes in the cluster than MPI due to optimized data communication.R is a popular environment for clinical data analysis. The new SparkR solution offers elastic resources and allows supporting big data analysis using R even on non-dedicated resources with minimal change to the original code. To unleash the full potential, additional efforts should be invested to customize and improve the algorithms, especially with regards to data distribution.
EVALuna2:174

Outcome after neoadjuvant chemotherapy in elderly breast cancer patients - a pooled analysis of individual patient data from eight prospectively randomized controlled trials - von Waldenfels, Gabriel; Loibl, Sibylle; Furlanetto, Jenny; Machleidt, Anna; Lederer, Bianca; Denkert, Carsten; Hanusch, Claus; Kümmel, Sherko; von Minckwitz, Gunter; Schneeweiss, Andreas; Untch, Michael; Rhiem, Kerstin; et al. (Oncotarget, 2018)
Introduction: Recent studies showed the high and independent impact of age (<40 years) on pathologic complete response (pCR) and prognosis for patients undergoing neoadjuvant chemotherapy (NACT). Some physicians might not consider elderly patients (>65 years) for NACT due to poor prognosis or higher toxicity. The aim of this analysis is to help selecting appropriately elderly women who would benefit from NACT. Secondly, survival parameters are investigated in several histological subgroups. Methods: From 1998 to 2010, eight prospectively randomized German Breast Group (GBG) trials of anthracycline- and taxane-based NACT were performed and analyzed in this study. Results: Compared to the overall average, elderly women had significant larger tumors and more overall lymph node involvement. Histologically, they had more G2 tumors, more estrogen-receptor positive tumors. pCR (ypT0 ypN0) was strongly associated with age. The multivariable logistic regression analysis of clinical parameters showed that young age, clinical stage T4, invasive ductal cancer and poor differentiated breast cancer are predictive for high pCR. The multivariate analyses of molecular subgroups showed that age >65years is a predictor of significant lower pCR in HER2- breast cancers. Nonetheless, HER2+ patients showed pCR rates as high- and HR+/HER2+ even higher - pCR rates compared to younger patients. Discussion: This study underlines the unfavorable impact of higher age on pCR, but it shows a realistic chance for pCR if NACT is applied - especially for HER2+ patients. Furthermore, elderly patients with non-TNBC showed a good prognosis (comparable to younger patients) regarding overall survival, even if they do not have pCR.
EVALuna2:210017

Outcome after neoadjuvant chemotherapy in estrogen receptor-positive and progesterone receptor-negative breast cancer patients: a pooled analysis of individual patient data from ten prospectively randomized controlled neoadjuvant trials - Van Mackelenbergh, Marion T.; Denkert, Carsten; Nekljudova, Valentina; Karn, Thomas; Schem, Christian; Marme, Frederik; Stickeler, Elmar; Jackisch, Christian; Hanusch, Claus; Huober, Jens; Fasching, Peter; Blohmer, Jens-Uwe; et al. (Breast Cancer Research and Treatment, 2018)
The estrogen receptor (ER) is involved in control of progesterone receptor (PgR) expression and lack of PgR may be also a surrogate of altered growth factor signaling. The aim of this study was therefore to investigate PgR expression as predictive factor for response to neoadjuvant therapy and long-term outcome.Five thousand and six hundred and thirteen patients with primary breast cancer and positive ER expression from ten German neoadjuvant trials of anthracycline and taxane-based chemotherapy were included. Pathologic complete response (pCR), disease-free survival (DFS), distant disease-free survival (DDFS), overall survival (OS), and local recurrence-free survival (LRFS) were compared according to PgR expression.The lack of PgR expression (1172 patients) was associated with grade 3 (38.4 vs. 26.3%; p < 0.001), nodal involvement (>cN2) (6.8% vs. 4.7%; p = 0.004), and HER2 positivity (36.2 vs. 22.3%; p < 0.001). pCR rates of PgR-negative tumors were higher in the entire cohort (13.8 vs. 7.5%; p < 0.001) and in the HER2-negative subgroup (11.2 vs. 5.8%; p < 0.001). In multivariable logistic regression, PgR negativity was an independent predictive factor for pCR overall (OR 1.76; p < 0.001) and in the HER2-negative patients (OR 1.99; p < 0.001). Patients with PgR-negative disease had significantly worse outcome (p < 0.001, respectively). Multivariable Cox regression analysis revealed that PgR was an independent prognostic factor for DFS, OS, DDFS, and LRFS.ER-positive/PgR-negative breast carcinomas are associated with higher response but also worse long-term outcome after neoadjuvant therapy. PgR negativity is an independent predictive factor for pCR after neoadjuvant chemotherapy in ER-positive HER2-negative breast cancer.
EVALuna2:56119

Ovarian function in young patients (pts) treated with postneoadjuvant palbociclib (PAL) and endocrine therapy (ET) for hormone receptor (HR)-positive, HER2-negative early breast cancer (BC): Explorative analysis in Penelope-B - Furlanetto, J.; Marme, F.; Thode, C.; Nekljudova, V.; Liu, Y.; Jimenez, M. Martin; Reimer, T.; Knudsen, E.; Denkert, C.; Bassy, M.; Martin, L-A.; Karn, T.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Overall survival (OS) results of the phase III MONALEESA-3 trial of postmenopausal patients (pts) with hormone receptor-positive (HR plus ), human epidermal growth factor 2-negative (HER2-) advanced breast cancer (ABC) treated with fulvestrant (FUL) (+) ribociclib (RIB) - Slamon, D. J.; Neven, P.; Chia, S.; Fasching, Peter; De Laurentiis, M.; Im, S-A.; Petrakova, K.; Bianchi, G. V.; Esteva, F. J.; Martin, M.; Nusch, A.; Sonke, G. S.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Overall Survival with Ribociclib plus Fulvestrant in Advanced Breast Cancer - Slamon, Dennis J.; Neven, Patrick; Chia, Stephen; Fasching, Peter; De Laurentiis, Michelino; Im, Seock-Ah; Petrakova, Katarina; Bianchi, Giulia V.; Esteva, Francisco J.; Martin, Miguel; Nusch, Arnd; Sonke, Gabe S.; et al. (New England Journal of Medicine, 2020)
BACKGROUND In an earlier analysis of this phase 3 trial, ribociclib plus fulvestrant showed a greater benefit with regard to progression-free survival than fulvestrant alone in postmenopausal patients with hormone-receptor positive, human epidermal growth factor receptor 2 (HER2) negative advanced breast cancer. Here we report the results of a protocol-specified second interim analysis of overall survival. METHODS Patients were randomly assigned in a 2;1 ratio to receive either ribociclib or placebo in addition to fulvestrant as first-line or second-line treatment. Survival was evaluated by means of a stratified log-rank test and summarized with the use of Kaplan Meier methods. RES U ITS This analysis was based on 275 deaths: 167 among 484 patients (34.5%) receiving ribociclib and 108 among 242 (44.6 /o) receiving placebo. Ribociclib plus fulvestrant showed a significant overall survival benefit over placebo plus fulvestrant. The estimated overall survival at 42 months was 57.8% (95% confidence interval [CI], 52.0 to 63.2) in the ribociclib group and 45.9% (95% CI, 36.9 to 54.5) in the placebo group, for a 28 /0 difference in the relative risk of death (hazard ratio, 0.72; 95% Cl, 0.57 to 0.92; P=0.00455). The benefit was consistent across most subgroups. In a descriptive update, median progression-free survival among patients receiving first-line treatment was 33.6 months (95% CI, 27.1 to 41.3) in the ribociclib group and 19.2 months (95% Cl, 14.9 to 23.6) in the placebo group. No new safety signals were observed. CONCLUSIONS Ribociclib plus fulvestrant showed a significant overall survival benefit over placebo plus fulvestrant in patients with hormone-receptor positive, HER2-negative advanced breast cancer. (Funded by Novartis; MONALEESA-3 ClinicalTrials.gov number, NCT02422615.)
CRIS-Team WoS Importer:2020-02-21

Oxytocin receptor DNA methylation in postpartum depression - Kimmel, Mary; Clive, Makena; Gispen, Fiona; Guintivano, Jerry; Brown, Tori; Cox, Olivia; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Osborne, Lauren M.; Binder, Elisabeth; Payne, Jennifer L.; et al. (Psychoneuroendocrinology, 2016)
The oxytocin receptor (OXTR) is a key regulator of stress and anxiety and may be regulated by both psychosocial risk factors and gonadal hormones, making it an attractive candidate for study in postpartum depression (PPD). The objective of this study was to investigate both serum hormone and PPD specific DNA methylation variation in the OXTR. Illumina HM450 microarray data generated in a prospective PPD cohort identified significant associations (P=0.014) with PPD in an intronic region in the OXTR located 4bp proximal to an estrogen receptor (ER) binding region. Pyrosequencing confirmed moderate evidence for an interaction of CpGs in the region with childhood abuse status to mediate PPD. These CpGs located on chr3 at positions 8810078 and 8810069 exhibited significant associations with postpartum depression scores from an independent cohort of 240 women with no prior psychiatric history. Hormone analysis suggested a PPD specific negative correlation of DNA methylation in the region with serum estradiol levels. Estradiol levels and OXTR DNA methylation exhibited a significant interaction to associate with the ratio of allopregnanolone to progesterone. Cumulatively, the data corroborate our previous hypotheses of a PPD specific increased sensitivity of epigenetic reprogramming at estrogen target genes and suggests that OXTR epigenetic variation may be an important mediator of mood relevant neuroactive steroid production.
EVALuna2:23775

p53 and ovarian carcinoma survival: an Ovarian Tumor Tissue Analysis consortium study - Köbel, Martin; Kang, Eun-Young; Weir, Ashley; Rambau, Peter F.; Lee, Cheng-Han; Nelson, Gregg S.; Ghatage, Prafull; Meagher, Nicola S.; Riggan, Marjorie J.; Alsop, Jennifer; Anglesio, Michael S.; Beckmann, Matthias; et al. (Journal of Pathology: Clinical Research, 2023)
Our objective was to test whether p53 expression status is associated with survival for women diagnosed with the most common ovarian carcinoma histotypes (high-grade serous carcinoma [HGSC], endometrioid carcinoma [EC], and clear cell carcinoma [CCC]) using a large multi-institutional cohort from the Ovarian Tumor Tissue Analysis (OTTA) consortium. p53 expression was assessed on 6,678 cases represented on tissue microarrays from 25 participating OTTA study sites using a previously validated immunohistochemical (IHC) assay as a surrogate for the presence and functional effect of TP53 mutations. Three abnormal expression patterns (overexpression, complete absence, and cytoplasmic) and the normal (wild type) pattern were recorded. Survival analyses were performed by histotype. The frequency of abnormal p53 expression was 93.4% (4,630/4,957) in HGSC compared to 11.9% (116/973) in EC and 11.5% (86/748) in CCC. In HGSC, there were no differences in overall survival across the abnormal p53 expression patterns. However, in EC and CCC, abnormal p53 expression was associated with an increased risk of death for women diagnosed with EC in multivariate analysis compared to normal p53 as the reference (hazard ratio [HR] = 2.18, 95% confidence interval [CI] 1.36-3.47, p = 0.0011) and with CCC (HR = 1.57, 95% CI 1.11-2.22, p = 0.012). Abnormal p53 was also associated with shorter overall survival in The International Federation of Gynecology and Obstetrics stage I/II EC and CCC. Our study provides further evidence that functional groups of TP53 mutations assessed by abnormal surrogate p53 IHC patterns are not associated with survival in HGSC. In contrast, we validate that abnormal p53 IHC is a strong independent prognostic marker for EC and demonstrate for the first time an independent prognostic association of abnormal p53 IHC with overall survival in patients with CCC.
EVALuna2:530730

PALB2, CHEK2 and ATM rare variants and cancer risk: data from COGS - Southey, Melissa C.; Goldgar, David E.; Winqvist, Robert; Pylkas, Katri; Couch, Fergus; Tischkowitz, Marc; Foulkes, William D.; Dennis, Joe; Michailidou, Kyriaki; Van Rensburg, Elizabeth J.; Heikkinen, Tuomas; Nevanlinna, Heli; et al. (Journal of Medical Genetics, 2016)
The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study.We genotyped 10 rare mutations using the custom iCOGS array: PALB2 c.1592delT, c.2816T>G and c.3113G>A, CHEK2 c.349A>G, c.538C>T, c.715G>A, c.1036C>T, c.1312G>T, and c.1343T>G and ATM c.7271T>G. We assessed associations with breast cancer risk (42 671 cases and 42 164 controls), as well as prostate (22 301 cases and 22 320 controls) and ovarian (14 542 cases and 23 491 controls) cancer risk, for each variant.For European women, strong evidence of association with breast cancer risk was observed for PALB2 c.1592delT OR 3.44 (95% CI 1.39 to 8.52, p=7.1×10(-5)), PALB2 c.3113G>A OR 4.21 (95% CI 1.84 to 9.60, p=6.9×10(-8)) and ATM c.7271T>G OR 11.0 (95% CI 1.42 to 85.7, p=0.0012). We also found evidence of association with breast cancer risk for three variants in CHEK2, c.349A>G OR 2.26 (95% CI 1.29 to 3.95), c.1036C>T OR 5.06 (95% CI 1.09 to 23.5) and c.538C>T OR 1.33 (95% CI 1.05 to 1.67) (p<=0.017). Evidence for prostate cancer risk was observed for CHEK2 c.1343T>G OR 3.03 (95% CI 1.53 to 6.03, p=0.0006) for African men and CHEK2 c.1312G>T OR 2.21 (95% CI 1.06 to 4.63, p=0.030) for European men. No evidence of association with ovarian cancer was found for any of these variants.This report adds to accumulating evidence that at least some variants in these genes are associated with an increased risk of breast cancer that is clinically important.
EVALuna2:6832

Palliative therapy concepts for pancreatic carcinoma - Brunner, Michaela; Grützmann, Robert; Weber, Georg (Chirurg, 2018)
The majority of patients with ductal pancreatic adenocarcinoma are already in a locally advanced or metastatic stage at the time of diagnosis and require palliative therapy. Interventional and operative measures are available for the restoration of biliary outflow in bile duct obstruction and the continuity of the upper intestinal lumen in duodenal or gastric outlet obstruction. In the presence of tumor-related pain, pain therapy according to the World Health Organization (WHO) scheme or a truncus coeliacus blockade, in cachexia a nutritional therapy and in thromboembolic events an anticoagulant therapy are used. An individualized palliative chemotherapy regimen should be selected for each patient, taking into account the patient's general condition and the side effects profile of the chemotherapeutic agents. Radiochemotherapy and local ablative therapies should currently only be used within the framework of studies. A palliative resection is not recommended according to current knowledge.
EVALuna2:212624

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche - Perry, John R. B.; Day, Felix; Elks, Cathy E.; Sulem, Patrick; Thompson, Deborah J.; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I.; Esko, Toenu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q.; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and ?-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
EVALuna2:17437

Pathological complete response and long-term clinical benefit in breast cancer: the CTNeoBC pooled analysis - Cortazar, Patricia; Zhang, Lijun; Untch, Michael; Mehta, Keyur; Costantino, Joseph P.; Wolmark, Norman; Bonnefoi, Herve; Cameron, David; Gianni, Luca; Valagussa, Pinuccia; Swain, Sandra M.; Prowell, Tatiana; et al. (Lancet, 2014)
Pathological complete response has been proposed as a surrogate endpoint for prediction of long-term clinical benefit, such as disease-free survival, event-free survival (EFS), and overall survival (OS). We had four key objectives: to establish the association between pathological complete response and EFS and OS, to establish the definition of pathological complete response that correlates best with long-term outcome, to identify the breast cancer subtypes in which pathological complete response is best correlated with long-term outcome, and to assess whether an increase in frequency of pathological complete response between treatment groups predicts improved EFS and OS.We searched PubMed, Embase, and Medline for clinical trials of neoadjuvant treatment of breast cancer. To be eligible, studies had to meet three inclusion criteria: include at least 200 patients with primary breast cancer treated with preoperative chemotherapy followed by surgery; have available data for pathological complete response, EFS, and OS; and have a median follow-up of at least 3 years. We compared the three most commonly used definitions of pathological complete response–ypT0 ypN0, ypT0/is ypN0, and ypT0/is–for their association with EFS and OS in a responder analysis. We assessed the association between pathological complete response and EFS and OS in various subgroups. Finally, we did a trial-level analysis to assess whether pathological complete response could be used as a surrogate endpoint for EFS or OS.We obtained data from 12 identified international trials and 11 955 patients were included in our responder analysis. Eradication of tumour from both breast and lymph nodes (ypT0 ypN0 or ypT0/is ypN0) was better associated with improved EFS (ypT0 ypN0: hazard ratio [HR] 0·44, 95% CI 0·39-0·51; ypT0/is ypN0: 0·48, 0·43-0·54) and OS (0·36, 0·30-0·44; 0·36, 0·31-0·42) than was tumour eradication from the breast alone (ypT0/is; EFS: HR 0·60, 95% CI 0·55-0·66; OS 0·51, 0·45-0·58). We used the ypT0/is ypN0 definition for all subsequent analyses. The association between pathological complete response and long-term outcomes was strongest in patients with triple-negative breast cancer (EFS: HR 0·24, 95% CI 0·18-0·33; OS: 0·16, 0·11-0·25) and in those with HER2-positive, hormone-receptor-negative tumours who received trastuzumab (EFS: 0·15, 0·09-0·27; OS: 0·08, 0·03, 0·22). In the trial-level analysis, we recorded little association between increases in frequency of pathological complete response and EFS (R(2)=0·03, 95% CI 0·00-0·25) and OS (R(2)=0·24, 0·00-0·70).Patients who attain pathological complete response defined as ypT0 ypN0 or ypT0/is ypN0 have improved survival. The prognostic value is greatest in aggressive tumour subtypes. Our pooled analysis could not validate pathological complete response as a surrogate endpoint for improved EFS and OS.US Food and Drug Administration.
EVALuna2:17518

Pathological Response in the Breast and Axillary Lymph Nodes after Neoadjuvant Systemic Treatment in Patients with Initially Node-Positive Breast Cancer Correlates with Disease Free Survival: An Exploratory Analysis of the GeparOcto Trial - Gerber, Bernd; Schneeweiss, Andreas; Möbus, Volker; Golatta, Michael; Tesch, Hans; Krug, David; Hanusch, Claus; Denkert, Carsten; Lübbe, Kristina; Heil, Jörg; Huober, Jens; Ataseven, Beyhan; et al. (Cancers, 2022)
Background: The conversion of initially histologically confirmed axillary lymph node-positive (pN+) to ypN0 after neoadjuvant systemic treatment (NAST) is an important prognostic factor in breast cancer (BC) patients and may influence surgical de-escalation strategies. We aimed to determine pCR rates in lymph nodes (pCR-LN), the breast (pCR-B), and both (tpCR) in women who present with pN+ BC, to assess predictors for response and the impact of pCR-LN, pCR-B, and tpCR on invasive disease-free survival (iDFS). Methods: Retrospective, exploratory analysis of 242 patients with pN+ at diagnosis from the multicentric, randomized GeparOcto trial. Results: Of 242 patients with initially pN+ disease, 134 (55.4%) had a pCR-LN, and 109 (45.0%) a pCR-B. Of the 109 pCR-B patients, 9 (8.3%) patients had involved LN, and 100 (41.3%) patients had tpCR. Those with involved LN still had a bad prognosis. As expected, pCR-B and intrinsic subtypes (TNBC and HER2+) were identified as independent predictors of pCR-LN. pCR-LN (ypN0; hazard ratio 0.42; 95%, CI 0.23–0.75; p = 0.0028 for iDFS) was the strongest independent prognostic factor. Conclusions: In initially pN+ patients undergoing NAST, the conversion to ypN0 is of high prognostic value. Surgical axillary staging after NAST is still essential in these patients to offer tailored treatment.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Axillary surgery; Breast cancer; Lymph node; Neoadjuvant therapy; Pathological complete response; Prognosis

Pathology of Tumors Associated With Pathogenic Germline Variants in 9 Breast Cancer Susceptibility Genes - Mavaddat, Nasim; Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Keeman, Renske; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; Ahearn, Thomas U.; Andrulis, Irene L.; Beckmann, Matthias; et al. (JAMA Oncology, 2022)
IMPORTANCE Rare germline genetic variants in several genes are associated with increased breast cancer (BC) risk, but their precise contributions to different disease subtypes are unclear. This information is relevant to guidelines for gene panel testing and risk prediction.
CRIS-Team WoS Importer:2022-02-11

Pathway-Based Analysis of Genome-Wide Association Data Identified SNPs in as Biomarker for Chemotherapy- Induced Neutropenia in Breast Cancer Patients - Bidadi, Behzad; Liu, Duan; Kalari, Krishna R.; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter; Weinshilboum, Richard M.; Wang, Liewei (Frontiers in Pharmacology, 2018)
Neutropenia secondary to chemotherapy in breast cancer patients can be life-threatening and there are no biomarkers available to predict the risk of drug-induced neutropenia in those patients. We previously performed a genome-wide association study (GWAS) for neutropenia events in women with breast cancer who were treated with 5-fluorouracil, epirubicin and cyclophosphamide and recruited to the SUCCESS-A trial. A genome-wide significant single-nucleotide polymorphism (SNP) signal in the tumor necrosis factor superfamily member 13B () gene, encoding the cytokine B-cell activating factor (BAFF), was identified in that GWAS. Taking advantage of these existing GWAS data, in the present study we utilized a pathway-based analysis approach by leveraging knowledge of the pharmacokinetics and pharmacodynamics of drugs and breast cancer pathophysiology to identify additional SNPs/genes associated with the underlying etiology of chemotherapy-induced neutropenia. We identified three SNPs in the hyaluronan mediated motility receptor ( gene that were significantly associated with neutropenia ( < 1.0E-04). Those three SNPs were trans-expression quantitative trait loci for the expression of ( < 1.0E-04). The minor allele of these SNPs was associated with a decreased mRNA level. Additional functional studies performed with lymphoblastoid cell lines (LCLs) demonstrated that LCLs possessing the minor allele for the SNPs were more sensitive to drug treatment. Knock-down of in LCLs and HL-60 promyelocytic cells and treatment of those cells with BAFF modulated the cell sensitivity to chemotherapy treatment. These results demonstrate that SNP-dependent cytotoxicity of these chemotherapeutic agents might be related to expression level. In summary, utilizing a pathway-based approach for the analysis of GWAS data, we identified additional SNPs in the gene that were associated with neutropenia and also were correlated with expression.
EVALuna2:56169

Patient quality of life (QoL) from the GeparX trial on the addition of denosumab (Dmab) added to two different nab-paclitaxel (nP) regimens as neoadjuvant chemotherapy (NACT) in primary breast cancer (BC) - Reinisch, M.; Blohmer, J-U.; Link, T.; Just, M.; Untch, M.; Stoetzer, O.; Fasching, Peter; Schneeweiss, A.; Wimberger, P.; Seiler, S.; Huober, J.; Thill, M.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Patient-reported outcomes and hospitalization data in patients with HER2-positive metastatic breast cancer receiving trastuzumab deruxtecan or trastuzumab emtansine in the phase III DESTINY-Breast03 study - Curigliano, G.; Dunton, K.; Rosenlund, M.; Janek, M.; Cathcart, J.; Liu, Y.; Fasching, Peter; Iwata, H. (Annals of Oncology, 2023)
Background: In the DESTINY-Breast03 clinical trial, trastuzumab deruxtecan (T-DXd) showed superior progression-free survival and overall survival versus trastuzumab emtansine (T-DM1) and manageable safety in patients with human epidermal growth factor receptor 2 (HER2)-positive (HER2+) metastatic breast cancer. Here, patient-reported outcomes (PROs) are reported along with hospitalization data. Patients and methods: Patients in DESTINY-Breast03 were assessed for prespecified PRO measures, including European Organization for Research and Treatment of Cancer quality of life (EORTC-QoL) questionnaires [the oncology-specific EORTC Quality of Life Questionnaire Core 30 (QLQ-C30) and breast cancer-specific EORTC QLQ-BR45] and the generic EuroQol 5-dimension 5-level questionnaire (EQ-5D-5L) visual analogue scale. Analyses included change from baseline, time to definitive deterioration (TDD), and hospitalization-related endpoints. Results: EORTC QLQ-C30 baseline global health status (GHS) scores for T-DXd (n = 253) and T-DM1 (n = 260) were similar, with no clinically meaningful change (<10-point change from baseline) while on either treatment (median treatment duration: T-DXd, 14.3 months; T-DM1, 6.9 months). TDD analyses of QLQ-C30 GHS (primary PRO variable) and all other prespecified PROs (QLQ-C30 subscales, the QLQ-BR45 arm symptoms scale, and the EQ-5D-5L visual analogue scale) suggested T-DXd was numerically favored over T-DM1 based on TDD hazard ratios. Of all randomized patients, 18 (6.9%) receiving T-DXd versus 19 (7.2%) receiving T-DM1 were hospitalized, and the median time to first hospitalization was 219.5 versus 60.0 days, respectively. Conclusions: In DESTINY-Breast03, EORTC GHS/QoL was maintained on both therapies throughout treatment, indicating that despite the longer treatment duration with T-DXd versus T-DM1, health-related QoL did not worsen on T-DXd. Furthermore, TDD hazard ratios numerically favored T-DXd over T-DM1 in all prespecified variables of interest including pain, suggesting T-DXd may delay time until health-related QoL deterioration compared with T-DM1. Median time to first hospitalization was three times longer with T-DXd versus T-DM1. Together with reported improved efficacy and manageable toxicity, these results support the overall benefit of T-DXd for patients with HER2+ metastatic breast cancer.
CRIS-Team Scopus Importer:2023-06-30
Keywords: breast cancer; hospitalization; quality of life; trastuzumab deruxtecan; trastuzumab emtansine

Patient-reported outcomes (PRO) focused on adverse events (PRO-AEs) in adjuvant and metastatic breast cancer: clinical and translational implications - Stefanovic, Stefan; Wallwiener, Markus; Karic, Uros; Domschke, Christoph; Katic, Luka; Taran, Florin-Andrei; Pesic, Aleksandra; Hartkopf, Andreas; Hadji, Peyman; Teufel, Martin; Schuetz, Florian; Sohn, Christof; et al. (Supportive Care in Cancer, 2017)
PURPOSE: The capture of adequate treatment outcomes and quality of life (QOL) of advanced breast cancer patients in clinical routine represents a great challenge. Patient-reported outcomes (PROs) are data elements directly reported by patients about experiences with care, including symptoms, functional status, or quality of life. There is growing interest in the medical community for the evaluation and implementation of PROs of adverse events (PRO-AEs). Recent interest in PROs in health care has evolved in the context of patient centeredness. Our primary objective was to identify trials that had implemented PRO-AEs in the breast cancer treatment setting, thereby demonstrating its feasibility. We aimed to identify published studies that used patient reports to assess AEs during and after breast cancer treatment, to identify clinician underreported and modifiable AEs that are important to patients, and to analyze the feasibility and usefulness of PRO instrument implementation in everyday oncological practice with special attention given to electronic-based PRO instruments. METHODS: We conducted a systematic search of PubMed for studies that used PRO instruments to assess AEs of breast cancer treatment in the metastatic and adjuvant settings. Two authors independently reviewed the search results and decided which studies fully met the predefined inclusion criteria. RESULTS: The search yielded 606 publications. The two reviewers found that 9 studies met the inclusion criteria. Three AEs were identified as important to patients but inadequately reported by health care providers, namely hot flushes, vaginal dryness, and weight gain. CONCLUSIONS: PROs and PRO-AEs are the consequence of contemporary concepts of patient-centered medicine and the growing feasibility, utility, and implications of collecting data using modern technology. Furthermore, the willingness of patients to utilize innovative applications for their own health has been increasing in parallel to the enhanced impact of the World Wide Web. Especially, the coverage of the metastatic situation promises numerous findings on the structure and quality of health care, enabling implementation of individually tailored interventions. Remote electronic self-reporting (i.e., home reporting) is feasible and is associated with high compliance levels.
EVALuna2:36208

Patient-reported outcomes (PROs) from DESTINY-Breast03, a randomized phase III study of trastuzumab deruxtecan (T-DXd) vs trastuzumab emtansine (T-DM1) in patients (pts) with HER2-positive (HER2+) metastatic breast cancer (MBC) - Curigliano, G.; Dunton, K.; Rosenlund, M.; Janek, M.; Cathcart, J.; Liu, Y.; Fasching, Peter; Iwata, H. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Patient-reported outcomes (PROs) in advanced breast cancer (ABC) treated with ribociclib plus fulvestrant: Results from MONALEESA-3 - Fasching, Peter; Esteva, F. J.; Pivot, X.; Nusch, A.; Beck, J. T.; Chan, A.; Pieris-Gunatilaka, A.; Wang, Y.; Lanoue, B.; Chandiwana, D.; Neven, P. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Patient-reported outcomes (PROs) in advanced breast cancer (ABC) treated with ribociclib (RIB) plus fulvestrant (FUL) as first-line (1L) and second-line (2L) therapy in MONALEESA-3 (ML-3) - Fasching, Peter; Neven, P.; Jerusalem, G.; Beck, J. T.; Chan, A.; De Laurentiis, M.; Bianchi, G. V.; Martin Jimenez, M.; Chia, S.; Gaur, A.; Sondhi, M.; Rodriguez-Lorenc, K.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Patient survival and tumor characteristics associated with CHEK2:p.I157T - findings from the Breast Cancer Association Consortium - Muranen, Taru A.; Blomqvist, Carl; Doerk, Thilo; Jakubowska, Anna; Heikkila, Paivi; Fagerholm, Rainer; Greco, Dario; Aittomaki, Kristiina; Bojesen, Stig E.; Shah, Mitul; Dunning, Alison M.; Rhenius, Valerie; et al. (Breast Cancer Research, 2016)
BACKGROUND: P.I157T is a CHEK2 missense mutation associated with a modest increase in breast cancer risk. Previously, another CHEK2 mutation, the protein truncating c.1100delC has been associated with poor prognosis of breast cancer patients. Here, we have investigated patient survival and characteristics of breast tumors of germ line p.I157T carriers. METHODS: We included in the analyses 26,801 European female breast cancer patients from 15 studies participating in the Breast Cancer Association Consortium. We analyzed the association between p.I157T and the clinico-pathological breast cancer characteristics by comparing the p.I157T carrier tumors to non-carrier and c.1100delC carrier tumors. Similarly, we investigated the p.I157T associated risk of early death, breast cancer-associated death, distant metastasis, locoregional relapse and second breast cancer using Cox proportional hazards models. Additionally, we explored the p.I157T-associated genomic gene expression profile using data from breast tumors of 183 Finnish female breast cancer patients (ten p.I157T carriers) (GEO: GSE24450). Differential gene expression analysis was performed using a moderated t test. Functional enrichment was investigated using the DAVID functional annotation tool and gene set enrichment analysis (GSEA). The tumors were classified into molecular subtypes according to the St Gallen 2013 criteria and the PAM50 gene expression signature. RESULTS: P.I157T was not associated with increased risk of early death, breast cancer-associated death or distant metastasis relapse, and there was a significant difference in prognosis associated with the two CHEK2 mutations, p.I157T and c.1100delC. Furthermore, p.I157T was associated with lobular histological type and clinico-pathological markers of good prognosis, such as ER and PR expression, low TP53 expression and low grade. Gene expression analysis suggested luminal A to be the most common subtype for p.I157T carriers and CDH1 (cadherin 1) target genes to be significantly enriched among genes, whose expression differed between p.I157T and non-carrier tumors. CONCLUSIONS: Our analyses suggest that there are fundamental differences in breast tumors of CHEK2:p.I157T and c.1100delC carriers. The poor prognosis associated with c.1100delC cannot be generalized to other CHEK2 mutations.
EVALuna2:32945

Pattern of invasion in stage I mucinous ovarian cancer is prognostic within 2-years of diagnosis - Meagher, Nicola; Koebel, Martin; Anderson, Lyndal; Tan, Adeline; Bolithon, Adelyn; Anglesio, Michael; Cohen, Paul; Crowe, Philip; Doherty, Jennifer; Fasching, Peter; Harris, Holly; Hogdall, Estrid; et al. (ASIA-PACIFIC JOURNAL OF CLINICAL ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-09-24

Patterns and Trends of Herbal Medicine Use among Patients with Gynecologic Cancer - Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Antoniadis, Sophia; Grasruck, Katharina; Wasner, Sonja; Knoll, Stefanie; Sievers, Hartwig; Beckmann, Matthias; Thiel, Falk C. (Geburtshilfe und Frauenheilkunde, 2021)
Background More and more information about complementary and integrative medicine is becoming available, especially among cancer patients. However, little is known about the use of herbal medicine by patients with gynecologic cancers. This study aimed to assess the use of herbal products by gynecologic cancer patients compared with healthy controls. Methods This cross-sectional study was conducted at the Department for Gynecology and Obstetrics of Erlangen University Hospital and included 201 patients with gynecologic cancer and 212 healthy controls. Use of herbal medicines was evaluated using a standardized questionnaire. Medical information on cancer patients was collected from hospital records. Group comparisons were done using a logistic regression model. Risk ratios were assessed using a Poisson regression model. Results Gynecologic cancer patients used herbal medicine significantly less often than healthy persons. 69% of gynecologic cancer patients and 81% of healthy participants reported using herbal products. 40% of cancer patients and 56% of healthy persons reported using plants for medicinal purposes. Motives of cancer patients for using herbal medicine included treatment of cancer-related symptoms. The major source of information for both groups was family and friends. Conclusions Although herbal medicine was used less by patients with gynecologic cancer, herbal products were used by both cancer patients and healthy individuals. To provide cancer patients with optimal therapy, oncologists should be informed about the herbal products used by their patients as this will allow them to take their patients' self-medication with herbal medicine into account. Counseling by oncologists on the use of herbal medicine should be encouraged.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cancer; complementary and alternative medicine; gynecologic oncology; herbal medicine; integrative medicine

Patterns of Associations with Epidemiologic Factors by High-Grade Serous Ovarian Cancer Gene Expression Subtypes - Collin, Lindsay J.; Cushing-Haugen, Kara L.; Terry, Kathryn L.; Goode, Ellen L.; Wu, Anna H.; Harris, Holly R.; Sasamoto, Naoko; Cramer, Daniel W.; Modugno, Francesmary; Elishaev, Esther; Fu, Zhuxuan; Moysich, Kirsten B.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2025)
Background: Ovarian high-grade serous carcinomas (HGSC) comprise four distinct molecular subtypes based on mRNA expression patterns, with differential survival. Understanding risk factor associations is important to elucidate the etiology of HGSC. We investigated associations between different epidemiologic risk factors and HGSC molecular subtypes. Methods: We pooled data from 11 case-control studies with epidemiologic and tumor gene expression data from custom NanoString CodeSets developed through a collaboration within the Ovarian Tumor Tissue Analysis consortium. The PrOTYPEvalidated NanoString-based 55-gene classifier was used to assign HGSC gene expression subtypes. We examined associations between epidemiologic factors and HGSC subtypes in 2,070 cases and 16,633 controls using multivariable-adjusted polytomous regression models. Results: Among the 2,070 HGSC cases, 556 (27%) were classified as C1.MES, 340 (16%) as C5.PRO, 538 (26%) as C2.IMM, and 636 (31%) as C4.DIF. The key factors, including oral contraceptive use, parity, breastfeeding, and family history of ovarian cancer, were similarly associated with all subtypes. Heterogeneity was observed for several factors. Former smoking [OR = 1.25; 95% confidence interval (CI) = 1.03, 1.51] and genital powder use (OR = 1.42; 95% CI = 1.08, 1.86) were uniquely associated with C2.IMM. History of endometriosis was associated with C5.PRO (OR = 1.46; 95% CI = 0.98, 2.16) and C4.DIF (OR = 1.27; 95% CI = 0.94, 1.71) only. Family history of breast cancer (OR = 1.44; 95% CI = 1.16, 1.78) and current smoking (OR = 1.40; 95% CI = 1.11, 1.76) were associated with C4.DIF only. Conclusions: This study observed heterogeneous associations of epidemiologic and modifiable factors with HGSC molecular subtypes. Impact: The different patterns of associations may provide key information about the etiology of the four subtypes.
CRIS-Team Scopus Importer:2025-05-16

Pembrolizumab for early triple-negative breast cancer - Schmid, P.; Cortes, J.; Pusztai, L.; McArthur, H.; Kümmel, S.; Bergh, J.; Denkert, C.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; Foukakis, T.; et al. (New England Journal of Medicine, 2020)
Background: Previous trials showed promising antitumor activity and an acceptable safety profile associated with pembrolizumab in patients with early triple-negative breast cancer. Whether the addition of pembrolizumab to neoadjuvant chemotherapy would significantly increase the percentage of patients with early triple-negative breast cancer who have a pathological complete response (defined as no invasive cancer in the breast and negative nodes) at definitive surgery is unclear. Methods: In this phase 3 trial, we randomly assigned (in a 2:1 ratio) patients with previously untreated stage II or stage III triple-negative breast cancer to receive neoadjuvant therapy with four cycles of pembrolizumab (at a dose of 200 mg) every 3 weeks plus paclitaxel and carboplatin (784 patients; the pembrolizumab-chemotherapy group) or placebo every 3 weeks plus paclitaxel and carboplatin (390 patients; the placebo-chemotherapy group); the two groups then received an additional four cycles of pembrolizumab or placebo, and both groups received doxorubicin-cyclophosphamide or epirubicin-cyclophosphamide. After definitive surgery, the patients received adjuvant pembrolizumab or placebo every 3 weeks for up to nine cycles. The primary end points were a pathological complete response at the time of definitive surgery and event-free survival in the intention-to-treat population. Results: At the first interim analysis, among the first 602 patients who underwent randomization, the percentage of patients with a pathological complete response was 64.8% (95% confidence interval [CI], 59.9 to 69.5) in the pembrolizumab-chemotherapy group and 51.2% (95% CI, 44.1 to 58.3) in the placebo-chemotherapy group (estimated treatment difference, 13.6 percentage points; 95% CI, 5.4 to 21.8; P<0.001). After a median follow-up of 15.5 months (range, 2.7 to 25.0), 58 of 784 patients (7.4%) in the pembrolizumab-chemotherapy group and 46 of 390 patients (11.8%) in the placebo-chemotherapy group had disease progression that precluded definitive surgery, had local or distant recurrence or a second primary tumor, or died from any cause (hazard ratio, 0.63; 95% CI, 0.43 to 0.93). Across all treatment phases, the incidence of treatment-related adverse events of grade 3 or higher was 78.0% in the pembrolizumab-chemotherapy group and 73.0% in the placebo-chemotherapy group, including death in 0.4% (3 patients) and 0.3% (1 patient), respectively. Conclusions: Among patients with early triple-negative breast cancer, the percentage with a pathological complete response was significantly higher among those who received pembrolizumab plus neoadjuvant chemotherapy than among those who received placebo plus neoadjuvant chemotherapy.
CRIS-Team Scopus Importer:2020-03-17

Pembrolizumab in combination with nab-paclitaxel for the treatment of patients with early-stage triple-negative breast cancer – A single-arm phase II trial (NeoImmunoboost, AGO-B-041) - Fasching, Peter; Hein, Alexander; Kolberg, Hans Christian; Häberle, Lothar; Uhrig, Sabrina; Rübner, Matthias; Belleville, Erik; Hack, Carolin; Fehm, Tanja N.; Janni, Wolfang; Hartmann, Arndt; Erber, Ramona; et al. (European Journal of Cancer, 2023)
Background: Pembrolizumab is approved for the neoadjuvant/adjuvant treatment of early triple-negative breast cancer (TNBC) patients in combination with chemotherapy. The Keynote-522 trial used platinum chemotherapy. As neoadjuvant nab-paclitaxel (nP) is also highly effective in triple-negative breast cancer patients, this study investigates the response to nP-containing neoadjuvant chemotherapy in combination with pembrolizumab. Patients and methods: NeoImmunoboost (AGO-B-041/NCT03289819) is a multicenter, prospective single-arm phase II trial. Patients were treated with 12 weekly cycles of nP followed by four three-weekly cycles of epirubicin/cyclophosphamide. Pembrolizumab was given three-weekly in combination with these chemotherapies. The study was planned for 50 patients. After 25 patients, the study was amended to include a pre-chemotherapy single application of pembrolizumab. The primary aim was pathological complete response (pCR), and the secondary aims were safety and quality of life. Results: Of 50 included patients, 33 (66.0%; 95%confidence interval: 51.2%–78.8%) had a (ypT0/is ypN0) pCR. The pCR rate in the per-protocol population (n = 39) was 71.8% (95%confidence interval: 55.1%–85.0%). The most common adverse events of any grade were fatigue (58.5%), peripheral sensory neuropathy (54.7%) and neutropenia (52.8%). The pCR rate in the cohort of 27 patients with a pre-chemotherapy pembrolizumab dose was 59.3%, and 73.9% in the 23 patients without pre-chemotherapy dose. Conclusions: pCR rates after NACT with nP and anthracycline combined with pembrolizumab are encouraging. With acceptable side-effect profiles, this treatment might be a reasonable alternative to platinum-containing chemotherapy in cases of contraindications. However, without data from randomised trials and long-term follow up, platinum/anthracycline/taxane-based chemotherapy remains the standard combination chemotherapy for pembrolizumab.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Neoadjuvant chemotherapy; PD-L1; Pembrolizumab; Triple-negative

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

Permacol collagen paste for cryptoglandular and Crohn's anal fistula - Brunner, Michaela; Schneider, Ignaz Hans Friedrich; Guenther, K.; Grützmann, Robert; Matzel, Klaus (Techniques in Coloproctology, 2019)
BackgroundPermacol collagen paste, an acellular crosslinked porcine dermal collagen matrix suspension, is a new treatment option for anal fistula. Data remain limited, however, and as yet only the results of one case of Crohn's fistula treated with Permacol paste has been reported. The aim of this study was to assess the use of Permacol collagen paste in patients with cryptoglandular and Crohn's perianal fistulae.MethodsA prospective study was conducted on patients with anal fistula, treated with Permacol paste. Patients were followed at 1week, 6 and 12months, and on demand thereafter. The main focus was on fistula healing and postoperative continence. The former was defined as the absence of signs of recurrence on clinical examination, proctoscopy and rigid rectoscopy. Fecal incontinence was assessed before surgery and at each follow-up.ResultsThirty patients (19 women, 11 men; mean age 46years), 12 (40%) of whom had Crohn's disease were included. The average number of previous fistula operations was 6. All patients had 6months of follow-up, and 24 patients (80%) had 12months of follow-up. The healing rate in all patients was 57% (17 of 30 patients) at 6months and 63% (15 of 24 patients) at 12months. One patient reported a worsening of fecal incontinence at 12 months; 2 patients had adverse events (perianal pain: n=1, fluid accumulation n=1) requiring fistula drainage. Patient characteristics, healing, incontinence, and adverse events did not differ significantly between patients with and without Crohn's disease.ConclusionsOur data indicate that Permacol paste is a safe and moderately effective treatment for cryptoglandular and Crohn's fistulae.
CRIS-Team WoS Importer:2019-04-12

Personal Profiling im Bereich der Senologie - Behrens, Annika; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna; Emons, Julius (Die Radiologie, 2025)
Background: The concept of personalized medicine is becoming increasingly important. The possibilities of diagnostics include not only genetic and molecular tumor profiles, but also the use of precise and individual imaging techniques. Objectives: The development and implementation of suitable diagnostic procedures with high sensitivity and specificity, which are at the same time tailored to the individual risk factors and biological characteristics of the patient, remain a challenge. Materials and methods: To enable personalized profiling, comprehensive diagnostics must be established that take into account all parameters such as imaging, molecular and genetic markers as well as real-world data and the use of artificial intelligence. This article sheds light on different approaches to personalized diagnostics in breast cancer and highlights the current clinical standard, innovative areas of research and the resulting challenges. Conclusion: The highest hurdles for newer imaging techniques are the standardization of image analysis and the validation of these techniques in large clinical trials. The use of artificial intelligence requires not only appropriate technical and medical expertise, but also a sensitive approach to issues such as data protection and patient privacy. Real-world registries offer insights into real world treatment situations and are therefore of great importance.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Artificial intelligence; Big data—mammography; Breast cancer; Breast diagnostics; Early detection

Perspectives of patients and clinicians on big data and AI in health: a comparative empirical investigation - Hummel, Patrik; Braun, Matthias; Bischoff, Serena; Samhammer, David; Seitz, Katharina; Fasching, Peter; Dabrock, Peter (AI and Society, 2024)
Background: Big data and AI applications now play a major role in many health contexts. Much research has already been conducted on ethical and social challenges associated with these technologies. Likewise, there are already some studies that investigate empirically which values and attitudes play a role in connection with their design and implementation. What is still in its infancy, however, is the comparative investigation of the perspectives of different stakeholders. Methods: To explore this issue in a multi-faceted manner, we conducted semi-structured interviews as well as focus group discussions with patients and clinicians. These empirical methods were used to gather interviewee’s views on the opportunities and challenges of medical AI and other data-intensive applications. Results: Different clinician and patient groups are exposed to medical AI to differing degrees. Interviewees expect and demand that the purposes of data processing accord with patient preferences, and that data are put to effective use to generate social value. One central result is the shared tendency of clinicians and patients to maintain individualistic ascriptions of responsibility for clinical outcomes. Conclusions: Medical AI and the proliferation of data with import for health-related inferences shape and partially reconfigure stakeholder expectations of how these technologies relate to the decision-making of human agents. Intuitions about individual responsibility for clinical outcomes could eventually be disrupted by the increasing sophistication of data-intensive and AI-driven clinical tools. Besides individual responsibility, systemic governance will be key to promote alignment with stakeholder expectations in AI-driven and data-intensive health settings.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Big data; Ethics; Health; Interviews; Privacy; Self-determination; Stakeholder

Phase III post-neoadjuvant study evaluating sacituzumab govitecan (SG), an antibody drug conjugate in primary HER2-negative breast cancer patients with high relapse risk after standard neoadjuvant treatment: SASCIA - Marme, F.; Hanusch, C.; Furlanetto, J.; Denkert, C.; Link, T.; Untch, M.; Blohmer, J-U.; Jackisch, C.; Reinisch, M.; Rhiem, K. E.; Schneeweiss, A.; Solbach, C.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-15

Phase III Randomized Study of Ribociclib and Fulvestrant in Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor 2-Negative Advanced Breast Cancer: MONALEESA-3 - Slamon, Dennis J.; Neven, Patrick; Chia, Stephen; Fasching, Peter; De Laurentiis, Michelino; Im, Seock-Ah; Petrakova, Katarina; Bianchi, Giulia Val; Esteva, Francisco J.; Martin, Miguel; Nusch, Arnd; Sonke, Gabe S.; et al. (Journal of Clinical Oncology, 2018)
Purpose This phase III study evaluated ribociclib plus fulvestrant in patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer who were treatment naïve or had received up to one line of prior endocrine therapy in the advanced setting. Patients and Methods Patients were randomly assigned at a two-to-one ratio to ribociclib plus fulvestrant or placebo plus fulvestrant. The primary end point was locally assessed progression-free survival. Secondary end points included overall survival, overall response rate, and safety. Results A total of 484 postmenopausal women were randomly assigned to ribociclib plus fulvestrant, and 242 were assigned to placebo plus fulvestrant. Median progression-free survival was significantly improved with ribociclib plus fulvestrant versus placebo plus fulvestrant: 20.5 months (95% CI, 18.5 to 23.5 months) versus 12.8 months (95% CI, 10.9 to 16.3 months), respectively (hazard ratio, 0.593; 95% CI, 0.480 to 0.732; P < .001). Consistent treatment effects were observed in patients who were treatment naïve in the advanced setting (hazard ratio, 0.577; 95% CI, 0.415 to 0.802), as well as in patients who had received up to one line of prior endocrine therapy for advanced disease (hazard ratio, 0.565; 95% CI, 0.428 to 0.744). Among patients with measurable disease, the overall response rate was 40.9% for the ribociclib plus fulvestrant arm and 28.7% for placebo plus fulvestrant. Grade 3 adverse events reported in ≥ 10% of patients in either arm (ribociclib plus fulvestrant v placebo plus fulvestrant) were neutropenia (46.6% v 0%) and leukopenia (13.5% v 0%); the only grade 4 event reported in ≥ 5% of patients was neutropenia (6.8% v 0%). Conclusion Ribociclib plus fulvestrant might represent a new first- or second-line treatment option in hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer.
EVALuna2:210018

Phase II neoadjuvant study of GDC-9545+palbociclib (palbo) vs anastrozole (A) plus palbo in postmenopausal women with estrogen receptor-positive, HER2-negative, untreated early breast cancer (ER+/HER2-eBC) - Hurvitz, Sara A.; Fasching, Peter; Park, Yeon Hee; Quiroga, Vanesa; Crnjevic, Tanja Badovinac; Fresco, Rodrigo; Lopez-Valverde, Vanesa; Steinseifer, Jutta; Ye, Chenglin; Bardia, Aditya (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

PHIP - a novel candidate breast cancer susceptibility locus on 6q14.1 - Jiao, Xiang; Aravidis, Christos; Marikkannu, Rajeshwari; Rantala, Johanna; Picelli, Simone; Adamovic, Tatjana; Liu, Tao; Maguire, Paula; Kremeyer, Barbara; Luo, Liping; Von Holst, Susanna; Kontham, Vinaykumar; et al. (Oncotarget, 2017)
Most non-BRCA1/2 breast cancer families have no identified genetic cause. We used linkage and haplotype analyses in familial and sporadic breast cancer cases to identify a susceptibility locus on chromosome 6q. Two independent genome-wide linkage analysis studies suggested a 3 Mb locus on chromosome 6q and two unrelated Swedish families with a LOD >2 together seemed to share a haplotype in 6q14.1. We hypothesized that this region harbored a rare high-risk founder allele contributing to breast cancer in these two families. Sequencing of DNA and RNA from the two families did not detect any pathogenic mutations. Finally, 29 SNPs in the region were analyzed in 44,214 cases and 43,532 controls from BCAC, and the original haplotypes in the two families were suggested as low-risk alleles for European and Swedish women specifically. There was also some support for one additional independent moderate-risk allele in Swedish familial samples. The results were consistent with our previous findings in familial breast cancer and supported a breast cancer susceptibility locus at 6q14.1 around the PHIP gene.
EVALuna2:36117

Physical activity levels are positively related to progression-free survival and reduced adverse events in advanced ER+ breast cancer - Zimmer, Philipp; Esser, Tobias; Lueftner, Diana; Schuetz, Florian; Baumann, Freerk T.; Rody, Achim; Schneeweiss, Andreas; Hartkopf, Andreas D.; Decker, Thomas; Uleer, Christoph; Stoetzer, Oliver J.; Foerster, Frank; et al. (BMC Medicine, 2024)
Background : Increased levels of physical activity are associated with a reduction of breast cancer mortality, especially in postmenopausal women with positive hormone receptor status. So far, previous observational case–control and cohort studies have focused on associations between overall leisure time physical activity and survival of women with breast cancer in general. Methods: In this multicenter prospective cohort study, conducted in Germany between 30th August 2012 to 29th December 2017, we investigated general physical activity in a homogenous sample of n = 1440 postmenopausal women with advanced (inoperable locally advanced or metastatic), hormone receptor-positive breast cancer receiving the same therapy (everolimus and exemestane). Self-reported physical activity was assessed using the Godin Leisure Time Exercise Questionnaire (GLTEQ) before and every 3 months during treatment. Participants were then classified into “active” and “insufficiently active” to screen their activity behavior the week prior to medical treatment. In addition, changes in physical activity patterns were assessed. Adjusted Cox regression analyses were performed for the activity categories to determine hazard ratios (HR). Besides progression-free survival (PFS), adverse events (AEs), QoL, and fatigue were assessed every 3 months until study termination. Results: Compared to “insufficiently active” patients, “active” individuals indicated a significantly longer PFS (HR: 0.84 [0.74; 0.984], p =.0295). No significant differences were observed for changes of physical activity behavior. Patients who reported to be “active” at baseline revealed significantly fewer AEs compared to “insufficiently” active patients. In detail, both severe and non-severe AEs occurred less frequently in the “active” patients group. In line with that, QoL and fatigue were better in physical “active” patients compared to their insufficient active counterparts at the last post-baseline assessment. Participants who remained or become active indicated less AEs, a higher QoL, and reduced fatigue levels. Conclusions: Physical activity behavior prior to medical treatment might have prognostic value in patients with advanced breast cancer in terms of extending the PFS. Moreover, physical activity before and during treatment may reduce treatment-related side effects and improve patients’ QoL and fatigue. Trial registration: EUPAS9462. Registered 30th October 2012 “retrospectively registered.”
CRIS-Team Scopus Importer:2024-10-18
Keywords: Adverse events; Breast cancer; Exercise; Fatigue; Physical activity; Quality of life; Survival

PIK3CA mutations are associated with lower rates of pathologic complete response to anti-human epidermal growth factor receptor 2 (her2) therapy in primary HER2-overexpressing breast cancer - Loibl, Sibylle; Von Minckwitz, Gunter; Schneeweiss, Andreas; Paepke, Stefan; Lehmann, Annika; Rezai, Mahdi; Zahm, Dirk M.; Sinn, Peter; Khandan, Fariba; Eidtmann, Holger; Dohnal, Karel; Heinrichs, Clemens; et al. (Journal of Clinical Oncology, 2014)
Phosphatidylinositol 3-kinase (PI3K)/AKT pathway aberrations are common in breast cancer, with mutations in PIK3CA being the most common. This study investigated the association between PIK3CA genotype and pathologic complete response (pCR) rates in human epidermal growth factor receptor 2 (HER2)-positive breast cancer treated with either dual or single anti-HER2 treatment in addition to neoadjuvant chemotherapy.PIK3CA mutations in 504 tumor samples from participants in the neoadjuvant GeparQuattro, GeparQuinto, and GeparSixto studies were evaluated. All HER2-positive patients received either trastuzumab or lapatinib or the combination plus anthracycline-taxane chemotherapy. PIK3CA mutations were evaluated in formalin-fixed, paraffin-embedded tissues from core biopsies with a tumor cell content of >= 20% by using classical Sanger sequencing of exon 9 and exon 20.Overall, 21.4% of the patients harbored a PIK3CA mutation. Detection of a PIK3CA mutation was significantly associated with a lower pCR rate (19.4% with PIK3CA mutation v 32.8% with PIK3CA wild-type; odds ratio [OR], 0.49; 95% CI, 0.29 to 0.83; P = .008). In the 291 hormone receptor (HR) -positive tumors, pCR rate was 11.3% with a PIK3CA mutation compared with 27.5% with PIK3CA wild-type (OR, 0.34; 95% CI, 0.15 to 0.78; P = .011). In 213 patients with HR-negative tumors, pCR rate was 30.4% with PIK3CA mutation and 40.1% without (OR, 0.65; 95% CI, 0.32 to 1.32; P = .233; interaction test P = .292). In multivariable analysis, HR status and PIK3CA status provided independent predictive information. In patients with PIK3CA mutation, the pCR rates were 16%, 24.3%, and 17.4% with lapatinib, trastuzumab, and the combination, respectively (P = .654) and in the wild-type group, they were 18.2%, 33.%, and 37.1%, respectively (P = .017). Disease-free survival and overall survival were not statistically significantly different between patients with mutant and wild-type PIK3CA.HER2-positive breast carcinomas with a PIK3CA mutation are less likely to achieve a pCR after neoadjuvant anthracycline-taxane-based chemotherapy plus anti-HER2 treatment, even if a dual anti-HER2 treatment is given.
EVALuna2:17509

Piwi-like 1 and piwi-like 2 expression in breast cancer - Erber, Ramona; Meyer, Julia; Taubert, Helge; Fasching, Peter; Wach, Sven; Häberle, Lothar; Gaß, Paul; Schulz-Wendtland, Rüdiger; Landgraf, Laura; Olbricht, Sabrina; Jung, Rudolf; Beckmann, Matthias; et al. (Cancers, 2020)
PIWI-like 1 and PIWI-like 2 play a role in stem cell self-renewal, and enhanced expression has been reported for several tumor entities. However, few studies have investigated PIWI-like 1 and PIWI-like 2 expressions in breast cancer subtypes regarding prognosis. Therefore, we examined protein expression in a large consecutive cohort of breast cancer patients and correlated it to breast cancer subtypes and survival outcome. PIWI-like 1 and PIWI-like 2 expressions were evaluated using immunohistochemistry in a cohort of 894 breast cancer patients, of whom 363 were eligible for further analysis. Percentage and intensity of stained tumor cells were analyzed and an immunoreactive score (IRS) was calculated. The interaction of PIWI-like 1 and PIWI-like 2 showed a prognostic effect on survival. For the combination of high PIWI-like 1 and low PIWI-like 2 expressions, adjusted hazard ratios (HRs) were significantly higher with regard to overall survival (OS) (HR 2.92; 95% confidence interval (CI) 1.24, 6.90), disease-free survival (DFS) (HR 3.27; 95% CI 1.48, 7.20), and distant disease-free survival (DDFS) (HR 7.64; 95% CI 2.35, 24.82). Both proteins were significantly associated with molecular-like and PAM50 subgroups. Combining high PIWI-like 1 and low PIWI-like 2 expressions predicted poorer prognosis and both markers were associated with aggressive molecular subtypes.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Breast cancer; HER2; Luminal A; Luminal B; Molecular breast cancer subtypes; PIWI-like 1; PIWI-like 2; PIWIL1; PIWIL2; TNBC

PML-nuclear bodies decrease with age and their stress response is impaired in aged individuals - Wenger, Barbara; Schwegler, Manuela; Brunner, Michaela; Daniel, Christoph; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (BMC Geriatrics, 2014)
Promyelocytic leukemia nuclear bodies (PML-NBs) have been depicted as structures which are involved in processing cell damages and DNA double-strand break repairs. The study was designed to evaluate differences in patients' PML-NBs response to stress factors like a cancerous disease and ionizing radiation exposure dependent on age.In order to clarify the role of PML-NBs in the aging process, we examined peripheral blood monocytes of 134 cancer patients and 41 healthy individuals between 22 and 92 years of age, both before and after in vitro irradiation. Additionally, we analyzed the samples of the cancer patients after in vivo irradiation. Cells were immunostained and about 1600 cells per individual were analyzed for the presence of PML- and ?H2AX foci.The number of existing PML-NBs per nucleus declined with age, while the number of ?H2AX foci increased with age. There was a non-significant trend that in vivo irradiation increased the number of PML-NBs in cells of young study participants, while in older individuals PML-NBs tended to decrease. It can be assumed that PML-NBs decrease in number during the process of aging.The findings suggest that there is a dysfunctional PML-NBs stress response in aged cells.
EVALuna2:18179

Polygenic risk modeling for prediction of epithelial ovarian cancer risk - Dareng, Eileen O.; Tyrer, Jonathan P.; Barnes, Daniel R.; Jones, Michelle R.; Yang, Xin; Aben, Katja K. H.; Adank, Muriel A.; Agata, Simona; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Aravantinos, Gerasimos; et al. (European Journal of Human Genetics, 2022)
Polygenic risk scores (PRS) for epithelial ovarian cancer (EOC) have the potential to improve risk stratification. Joint estimation of Single Nucleotide Polymorphism (SNP) effects in models could improve predictive performance over standard approaches of PRS construction. Here, we implemented computationally efficient, penalized, logistic regression models (lasso, elastic net, stepwise) to individual level genotype data and a Bayesian framework with continuous shrinkage, "select and shrink for summary statistics" (S4), to summary level data for epithelial non-mucinous ovarian cancer risk prediction. We developed the models in a dataset consisting of 23,564 non-mucinous EOC cases and 40,138 controls participating in the Ovarian Cancer Association Consortium (OCAC) and validated the best models in three populations of different ancestries: prospective data from 198,101 women of European ancestries; 7,669 women of East Asian ancestries; 1,072 women of African ancestries, and in 18,915 BRCA1 and 12,337 BRCA2 pathogenic variant carriers of European ancestries. In the external validation data, the model with the strongest association for non-mucinous EOC risk derived from the OCAC model development data was the S4 model (27,240 SNPs) with odds ratios (OR) of 1.38 (95% CI: 1.28-1.48, AUC: 0.588) per unit standard deviation, in women of European ancestries; 1.14 (95% CI: 1.08-1.19, AUC: 0.538) in women of East Asian ancestries; 1.38 (95% CI: 1.21-1.58, AUC: 0.593) in women of African ancestries; hazard ratios of 1.36 (95% CI: 1.29-1.43, AUC: 0.592) in BRCA1 pathogenic variant carriers and 1.49 (95% CI: 1.35-1.64, AUC: 0.624) in BRCA2 pathogenic variant carriers. Incorporation of the S4 PRS in risk prediction models for ovarian cancer may have clinical utility in ovarian cancer prevention programs.
CRIS-Team WoS Importer:2022-01-28

Polygenic Risk Scores for Prediction of Breast Cancer and Breast Cancer Subtypes - Mavaddat, Nasim; Michailidou, Kyriaki; Dennis, Joe; Lush, Michael; Fachal, Laura; Lee, Andrew; Tyrer, Jonathan P.; Chen, Ting-Huei; Wang, Qin; Bolla, Manjeet K.; Yang, Xin; Adank, Muriel A.; et al. (American Journal of Human Genetics, 2019)
Stratification of women according to their risk of breast cancer based on polygenic risk scores (PRSs) could improve screening and prevention strategies. Our aim was to develop PRSs, optimized for prediction of estrogen receptor (ER)-specific disease, from the largest available genome-wide association dataset and to empirically validate the PRSs in prospective studies. The development dataset comprised 94,075 case subjects and 75,017 control subjects of European ancestry from 69 studies, divided into training and validation sets. Samples were genotyped using genome-wide arrays, and single-nucleotide polymorphisms (SNPs) were selected by stepwise regression or lasso penalized regression. The best performing PRSs were validated in an independent test set comprising 11,428 case subjects and 18,323 control subjects from 10 prospective studies and 190,040 women from UK Biobank (3,215 incident breast cancers). For the best PRSs (313 SNPs), the odds ratio for overall disease per 1 standard deviation in ten prospective studies was 1.61 (95%CI: 1.57-1.65) with area under receiver-operator curve (AUC) = 0.630 (95%CI: 0.628-0.651). The lifetime risk of overall breast cancer in the top centile of the PRSs was 32.6%. Compared with women in the middle quintile, those in the highest 1% of risk had 4.37- and 2.78-fold risks, and those in the lowest 1% of risk had 0.16- and 0.27-fold risks, of developing ER-positive and ER-negative disease, respectively. Goodness-of-fit tests indicated that this PRS was well calibrated and predicts disease risk accurately in the tails of the distribution. This PRS is a powerful and reliable predictor of breast cancer risk that may improve breast cancer prevention programs.
EVALuna2:35122

Polygenic score distribution differences across European ancestry populations: implications for breast cancer risk prediction - Yiangou, Kristia; Mavaddat, Nasim; Dennis, Joe; Zanti, Maria; Wang, Qin; Bolla, Manjeet K.; Abubakar, Mustapha; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Arndt, Volker; et al. (Breast Cancer Research, 2024)
Background: The 313-variant polygenic risk score (PRS313) provides a promising tool for clinical breast cancer risk prediction. However, evaluation of the PRS313 across different European populations which could influence risk estimation has not been performed. Methods: We explored the distribution of PRS313 across European populations using genotype data from 94,072 females without breast cancer diagnosis, of European-ancestry from 21 countries participating in the Breast Cancer Association Consortium (BCAC) and 223,316 females without breast cancer diagnosis from the UK Biobank. The mean PRS was calculated by country in the BCAC dataset and by country of birth in the UK Biobank. We explored different approaches to reduce the observed heterogeneity in the mean PRS across the countries, and investigated the implications of the distribution variability in risk prediction. Results: The mean PRS313 differed markedly across European countries, being highest in individuals from Greece and Italy and lowest in individuals from Ireland. Using the overall European PRS313 distribution to define risk categories, leads to overestimation and underestimation of risk in some individuals from these countries. Adjustment for principal components explained most of the observed heterogeneity in the mean PRS. The mean estimates derived when using an empirical Bayes approach were similar to the predicted means after principal component adjustment. Conclusions: Our results demonstrate that PRS distribution differs even within European ancestry populations leading to underestimation or overestimation of risk in specific European countries, which could potentially influence clinical management of some individuals if is not appropriately accounted for. Population-specific PRS distributions may be used in breast cancer risk estimation to ensure predicted risks are correctly calibrated across risk categories.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Breast cancer; Polygenic risk scores; Risk calibration; Risk prediction

Polymorphisms in a Putative Enhancer at the 10q21.2 Breast Cancer Risk Locus Regulate NRBF2 Expression - Darabi, Hatef; Mccue, Karen; Beesley, Jonathan; Michailidou, Kyriaki; Nord, Silje; Kar, Siddhartha; Humphreys, Keith; Thompson, Deborah; Ghoussaini, Maya; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies have identified SNPs near ZNF365 at 10q21.2 that are associated with both breast cancer risk and mammographic density. To identify the most likely causal SNPs, we fine mapped the association signal by genotyping 428 SNPs across the region in 89,050 European and 12,893 Asian case and control subjects from the Breast Cancer Association Consortium. We identified four independent sets of correlated, highly trait-associated variants (iCHAVs), three of which were located within ZNF365. The most strongly risk-associated SNP, rs10995201 in iCHAV1, showed clear evidence of association with both estrogen receptor (ER)-positive (OR = 0.85 [0.82-0.88]) and ER-negative (OR = 0.87 [0.82-0.91]) disease, and was also the SNP most strongly associated with percent mammographic density. iCHAV2 (lead SNP, chr10: 64,258,684:D) and iCHAV3 (lead SNP, rs7922449) were also associated with ER-positive (OR = 0.93 [0.91-0.95] and OR = 1.06 [1.03-1.09]) and ER-negative (OR = 0.95 [0.91-0.98] and OR = 1.08 [1.04-1.13]) disease. There was weaker evidence for iCHAV4, located 5' of ADO, associated only with ER-positive breast cancer (OR = 0.93 [0.90-0.96]). We found 12, 17, 18, and 2 candidate causal SNPs for breast cancer in iCHAVs 1-4, respectively. Chromosome conformation capture analysis showed that iCHAV2 interacts with the ZNF365 and NRBF2 (more than 600 kb away) promoters in normal and cancerous breast epithelial cells. Luciferase assays did not identify SNPs that affect transactivation of ZNF365, but identified a protective haplotype in iCHAV2, associated with silencing of the NRBF2 promoter, implicating this gene in the etiology of breast cancer.
EVALuna2:9266

Polymorphisms in inflammation pathway genes and endometrial cancer risk - Delahanty, Ryan J.; Xiang, Yong-Bing; Spurdle, Amanda; Beeghly-Fadiel, Alicia; Long, Jirong; Thompson, Deborah; Tomlinson, Ian; Yu, Herbert; Lambrechts, Diether; Doerk, Thilo; Goodman, Marc T.; Zheng, Ying; et al. (Cancer Epidemiology Biomarkers & Prevention, 2013)
Background: Experimental and epidemiologic evidence have suggested that chronic inflammation may play a critical role in endometrial carcinogenesis. Methods: To investigate this hypothesis, a two-stage study was carried out to evaluate single-nucleotide polymorphisms (SNP) in inflammatory pathway genes in association with endometrial cancer risk. In stage I, 64 candidate pathway genes were identified and 4,542 directly genotyped or imputed SNPs were analyzed among 832 endometrial cancer cases and 2,049 controls, using data from the Shanghai Endometrial Cancer Genetics Study. Linkage disequilibrium of stage I SNPs significantly associated with endometrial cancer (P < 0.05) indicated that the majority of associations could be linked to one of 24 distinct loci. One SNP from each of the 24 loci was then selected for follow-up genotyping. Of these, 21 SNPs were successfully designed and genotyped in stage II, which consisted of 10 additional studies including 6,604 endometrial cancer cases and 8,511 controls. Results: Five of the 21 SNPs had significant allelic odds ratios (ORs) and 95% confidence intervals (CI) as follows: FABP1, 0.92 (0.85-0.99); CXCL3, 1.16 (1.05-1.29); IL6, 1.08 (1.00-1.17); MSR1, 0.90 (0.82-0.98); and MMP9, 0.91 (0.87-0.97). Two of these polymorphisms were independently significant in the replication sample (rs352038 in CXCL3 and rs3918249 in MMP9). The association for the MMP9 polymorphism remained significant after Bonferroni correction and showed a significant association with endometrial cancer in both Asian- and European-ancestry samples. Conclusions: These findings lend support to the hypothesis that genetic polymorphisms in genes involved in the inflammatory pathway may contribute to genetic susceptibility to endometrial cancer. Impact statement: This study adds to the growing evidence that inflammation plays an important role in endometrial carcinogenesis. © 2012 American Association for Cancer Research.
CRIS-Team Scopus Importer:2021-07-19

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients - Hein, Alexander; Bayer, Christian M.; Schrauder, Michael G.; Haeberle, Lothar; Heusinger, Katharina; Strick, Reiner; Ruebner, Matthias; Lux, Michael P.; Renner, Stefan; Schulz-Wendtland, Rüdiger; Ekici, Arif Bülent; Hartmann, Arndt; et al. (BioMed Research International, 2014)
The receptor activator of NF-?B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in RANK(L) (rs1054016/rs1805034/rs35211496) were genotyped and analyzed with regard to bone metastasis-free survival (BMFS), disease-free survival, and overall survival for a retrospective cohort of 1251 patients. Cox proportional hazard models were built to examine the prognostic influence in addition to commonly established prognostic factors. The SNP rs1054016 seems to influence BMFS. Patients with two minor alleles had a more favorable prognosis than patients with at least one common allele (HR 0.37 (95% CI: 0.17, 0.84)), whereas other outcome parameters remained unaffected. rs1805034 and rs35211496 had no prognostic relevance. The effect of rs1054016(RANKL) adds to the evidence that the RANK pathway plays a role in BC pathogenesis and progression with respect to BMFS, emphasizing the connection between BC and bone health.
EVALuna2:6628

Pooled analysis of patient (pt)-reported outcomes (PROs) in the MONALEESA (ML)-2,-3, and-7 trials: Additional results and key subgroup findings - Fasching, Peter; Bardia, A.; Nusch, A.; Jerusalem, G.; Chan, A.; El Saghir, N. S.; Conejo, E. Alba; Im, S-A.; Janni, W.; Chandiwana, D.; Lanoue, B. R.; Thuerigen, A.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Pooled analysis of patient (pt)-reported quality of life (QOL) in the MONALEESA (ML)-2,-3, and-7 trials of ribociclib (RIB) plus endocrine therapy (ET) to treat hormone receptore-positive, HER2-negative (HR+/HER2L) advanced breast cancer (ABC) - Fasching, Peter; Bardia, A.; Nusch, A.; Jerusalem, G.; Chan, A.; El Saghir, N.; Alba, E.; Im, S-A.; Janni, W.; Chandiwana, D.; Lanoue, B.; Thuerigen, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Pooled Analysis of the Prognostic Relevance of Circulating Tumor Cells in Primary Breast Cancer - Janni, Wolfgang J.; Rack, Brigitte; Terstappen, Leon W. M. M.; Pierga, Jean-Yves; Taran, Florin-Andrei; Fehm, Tanja; Hall, Carolyn; De Groot, Marco R.; Bidard, Francois-Clement; Friedl, Thomas W. P.; Fasching, Peter; Brucker, Sara Y.; et al. (Clinical Cancer Research, 2016)
PURPOSE: Although unequivocal evidence has shown the prognostic relevance of circulating tumor cells (CTC) in the peripheral blood of patients with metastatic breast cancer, less evidence is available for the prognostic relevance of CTCs at the time of primary diagnosis. EXPERIMENTAL DESIGN: We conducted a pooled analysis of individual data from 3,173 patients with nonmetastatic (stage I-III) breast cancer from five breast cancer institutions. The prevalence and numbers of CTCs were assessed at the time of primary diagnosis with the FDA-cleared CellSearch System (Janssen Diagnostics, LLC). Patient outcomes were analyzed using meta-analytic procedures, univariate log-rank tests, and multivariate Cox proportional hazard regression analyses. The median follow-up duration was 62.8 months. RESULTS: One or more CTCs were detected in 20.2% of the patients. CTC-positive patients had larger tumors, increased lymph node involvement, and a higher histologic tumor grade than did CTC-negative patients (all P < 0.002). Multivariate Cox regressions, which included tumor size, nodal status, histologic tumor grade, and hormone receptor and HER2 status, confirmed that the presence of CTCs was an independent prognostic factor for disease-free survival [HR, 1.82; 95% confidence interval (CI), 1.47-2.26], distant disease-free survival (HR, 1.89; 95% CI, 1.49-2.40), breast cancer-specific survival (HR, 2.04; 95% CI, 1.52-2.75), and overall survival (HR, 1.97; 95% CI, 1.51-2.59). CONCLUSIONS: In patients with primary breast cancer, the presence of CTCs was an independent predictor of poor disease-free, overall, breast cancer-specific, and distant disease-free survival. Clin Cancer Res; 22(10); 2583-93. ©2016 AACR.
EVALuna2:33080

Pooled analysis of the prognostic relevance of progesterone receptor status in five German cohort studies - Salmen, Jessica; Neugebauer, Julia; Fasching, Peter; Häberle, Lothar; Huober, Jens; Woeckel, Achim; Rauh, Claudia; Schuetz, Florian; Weissenbacher, Tobias; Kost, Bernd; Stickeler, Elmar; Klar, Maximilian; et al. (Breast Cancer Research and Treatment, 2014)
The progesterone receptor (PR) has been increasingly well described as an important mediator of the pathogenesis and progression of breast cancer. The aim of this study was to assess the role of PR status as a prognostic factor in addition to other well-established prognostic factors. Data from five independent German breast cancer centers were pooled. A total of 7,965 breast cancer patients were included for whom information about their PR status was known, as well as other patient and tumor characteristics commonly used as prognostic factors. Cox proportional hazards models were built to compare the predictive value of PR status in addition to age at diagnosis, tumor size, nodal status, grading, and estrogen receptor (ER) status. PR status significantly increased the accuracy of prognostic predictions with regard to overall survival, distant disease-free survival, and local recurrence-free survival. There were differences with regard to its prognostic value relative to subgroups such as nodal status, ER status, and grading. The prognostic value of PR status was greatest in patients with a positive nodal status, negative ER status, and low grading. The PR-status adds prognostic value in addition to ER status and should not be omitted from clinical routine testing. The significantly greater prognostic value in node-positive and high-grade tumors suggests a greater role in the progression of advanced and aggressive tumors.
EVALuna2:6666

Population distribution of lifetime risk of ovarian cancer in the United States - Pearce, Celeste Leigh; Stram, Daniel O.; Ness, Roberta B.; Stram, Douglas A.; Roman, Lynda D.; Templeman, Claire; Lee, Alice W.; Menon, Usha; Fasching, Peter; Mcalpine, Jessica N.; Doherty, Jennifer A.; Modugno, Francesmary; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
In U.S. women, lifetime risk of ovarian cancer is 1.37%, but some women are at a substantially lower or higher risk than this average.We have characterized the distribution of lifetime risk in the general population. Published data on the relative risks and their variances for five well-accepted risk and protective factors for ovarian cancer, oral contraceptive use, parity, tubal ligation, endometriosis, and first-degree family history of ovarian cancer in conjunction with a genetic risk score using genome-wide significant common, low penetrance variants were used. The joint distribution of these factors (i.e., risk/protective factor profiles) was derived using control data from four U.S. population-based studies, providing a broad representation of women in the United States.A total of 214 combinations of risk/protective factors were observed, and the lifetime risk estimates ranged from 0.35% [95% confidence interval (CI), 0.29-0.42] to 8.78% (95% CI, 7.10-10.9). Among women with lifetime risk ranging from 4% to 9%, 73% had no family history of ovarian cancer; most of these women had a self-reported history of endometriosis.Profiles including the known modifiable protective factors of oral contraceptive use and tubal ligation were associated with a lower lifetime risk of ovarian cancer. Oral contraceptive use and tubal ligation were essentially absent among the women at 4% to 9% lifetime risk.This work demonstrates that there are women in the general population who have a much higher than average lifetime risk of ovarian cancer. Preventive strategies are available. Should effective screening become available, higher than average risk women can be identified.
EVALuna2:17564

Power-MF: Robust fetal QRS detection from non-invasive fetal electrocardiogram recordings - Jäger, Katharina; Nissen, Michael; Rahm, Simone; Titzmann, Adriana; Fasching, Peter; Beilner, Janina; Eskofier, Björn; Leutheuser, Heike (Physiological Measurement, 2024)
Objective. Perinatal asphyxia poses a significant risk to neonatal health, necessitating accurate fetal heart rate monitoring for effective detection and management. The current gold standard, cardiotocography, has inherent limitations, highlighting the need for alternative approaches. The emerging technology of non-invasive fetal electrocardiography shows promise as a new sensing technology for fetal cardiac activity, offering potential advancements in the detection and management of perinatal asphyxia. Although algorithms for fetal QRS detection have been developed in the past, only a few of them demonstrate accurate performance in the presence of noise and artifacts. Approach. In this work, we propose Power-MF, a new algorithm for fetal QRS detection combining power spectral density and matched filter techniques. We benchmark Power-MF against three open-source algorithms on two recently published datasets (Abdominal and Direct Fetal ECG Database: ADFECG, subsets B1 Pregnancy and B2 Labour; Non-invasive Multimodal Foetal ECG-Doppler Dataset for Antenatal Cardiology Research: NInFEA). Main results. Our results show that Power-MF outperforms state-of-the-art algorithms on ADFECG (B1 Pregnancy: 99.5 % ± 0.5 % F1-score, B2 Labour: 98.0 % ± 3.0 % F1-score) and on NInFEA in three of six electrode configurations by being more robust against noise. Significance. Through this work, we contribute to improving the accuracy and reliability of fetal cardiac monitoring, an essential step toward early detection of perinatal asphyxia with the long-term goal of reducing costs and making prenatal care more accessible.<br

Practice-Changing Perspectives regarding Systemic Therapy in Early Breast Cancer: Opinions of German Experts regarding the 17th St. Gallen International Consensus Conference - Kolberg-Liedtke, Cornelia; Lueftner, Diana; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; Krug, David; et al. (Breast Care, 2022)
The general topic of this year's 17th St. Gallen (SG) International Consensus Conference on the treatment of patients with early breast cancer (SG-BCC) was "Customizing local and systemic therapies for women with early breast cancer. " This topic considers that each treatment decision must also consider the cancer-specific situation of the individual patient. This year, the votes of the SG-BCC were again discussed taking into account the multidisciplinary German S3 Guidelines and the recommendations of the Breast Cancer Working Group of the AGO (Arbeitsgemeinschaft Gynakologische Onkologie; AGO Mamma). As the international panel of the SG-BCC consists of experts from different countries, the votes do represent an international cross-section of opinions. Therefore, it is useful to discuss the voting results with respect to the German evidence-based treatment guidelines. This publication focuses mainly on systemic treatment.
CRIS-Team WoS Importer:2022-06-17

PRECYCLE Impact of CANKADO-based eHealth-support on quality of life in metastatic breast cancer patients treated with palbociclib and endocrine therapy - Degenhardt, T.; Fasching, Peter; Lueftner, D.; Mueller, V.; Thomssen, C.; Schem, C.; Witzel, I.; Decker, T.; Tesch, H.; Kuemmel, S.; Uleer, C.; Wuerstlein, R.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

PRECYCLE: multicenter, randomized phase IV intergroup trial to evaluate the impact of eHealth-based patient-reported outcome (PRO) assessment on quality of life in patients with hormone receptor positive, HER2 negative locally advanced or metastatic breast cancer treated with palbociclib and an aromatase inhibitor or palbociclib and fulvestrant - Degenhardt, Tom; Fasching, Peter; Lüftner, Diana; Müller, Volkmar; Thomssen, Christoph; Schem, Christian; Witzel, Isabell; Decker, Thomas; Tesch, Hans; Kümmel, Sherko; Uleer, Christoph; Wuerstlein, Rachel; et al. (Trials, 2023)
Background: Efficacy and quality of life (QoL) are key criteria for therapy selection in metastatic breast cancer (MBC). In hormone receptor positive (HR +) human epidermal growth factor receptor 2 negative (HER2 −) MBC, addition of targeted oral agents such as everolimus or a cycline-dependent kinase 4/6 (CDK 4/6) inhibitor (e.g., palbociclib, ribociclib, abemaciclib) to endocrine therapy substantially prolongs progression-free survival and in the case of a CDK 4/6i also overall survival. However, the prerequisite is adherence to therapy over the entire course of treatment. However, particularly with new oral drugs, adherence presents a challenge to disease management. In this context, factors influencing adherence include maintaining patients’ satisfaction and early detection/management of side effects. New strategies for continuous support of oncological patients are needed. An eHealth-based platform can help to support therapy management and physician–patient interaction. Methods: PreCycle is a multicenter, randomized, phase IV trial in HR + HER2 − MBC. All patients (n = 960) receive the CDK 4/6 inhibitor palbociclib either in first (62.5%) or later line (37.5%) together with endocrine therapy (AI, fulvestrant) according to national guidelines. PreCycle evaluates and compares the time to deterioration (TTD) of QoL in patients supported by eHealth systems with substantially different functionality: CANKADO active vs. inform. CANKADO active is the fully functional CANKADO-based eHealth treatment support system. CANKADO inform is a CANKADO-based eHealth service with a personal login, documentation of daily drug intake, but no further functions. To evaluate QoL, the FACT-B questionnaire is completed at every visit. As little is known about relationships between behavior (e.g., adherence), genetic background, and drug efficacy, the trial includes both patient-reported outcome and biomarker screening for discovery of forecast models for adherence, symptoms, QoL, progression free survival (PFS), and overall survival (OS). Discussion: The primary objective of PreCycle is to test the hypothesis of superiority for time to deterioration (TTD) in terms of DQoL = “Deterioration of quality of life” (FACT-G scale) in patients supported by an eHealth therapy management system (CANKADO active) versus in patients merely receiving eHealth-based information (CANKADO inform). EudraCT Number: 2016–004191-22
CRIS-Team Scopus Importer:2023-06-02
Keywords: CDK 4/6 inhibitor; eHealth; Endocrine therapy; Metastatic breast cancer; Patient-reported outcome; Quality of life

PredictCBC-2.0: a contralateral breast cancer risk prediction model developed and validated in 200,000 patients - Giardiello, Daniele; Hooning, Maartje J.; Hauptmann, Michael; Keeman, Renske; Heemskerk-Gerritsen, B. A. M.; Becher, Heiko; Blomqvist, Carl; Bojesen, Stig E.; Bolla, Manjeet K.; Camp, Nicola J.; Czene, Kamila; Devilee, Peter; et al. (Breast Cancer Research, 2022)
Background: Prediction of contralateral breast cancer (CBC) risk is challenging due to moderate performances of the known risk factors. We aimed to improve our previous risk prediction model (PredictCBC) by updated follow-up and including additional risk factors. Methods: We included data from 207,510 invasive breast cancer patients participating in 23 studies. In total, 8225 CBC events occurred over a median follow-up of 10.2 years. In addition to the previously included risk factors, PredictCBC-2.0 included CHEK2 c.1100delC, a 313 variant polygenic risk score (PRS-313), body mass index (BMI), and parity. Fine and Gray regression was used to fit the model. Calibration and a time-dependent area under the curve (AUC) at 5 and 10 years were assessed to determine the performance of the models. Decision curve analysis was performed to evaluate the net benefit of PredictCBC-2.0 and previous PredictCBC models. Results: The discrimination of PredictCBC-2.0 at 10 years was higher than PredictCBC with an AUC of 0.65 (95% prediction intervals (PI) 0.56–0.74) versus 0.63 (95%PI 0.54–0.71). PredictCBC-2.0 was well calibrated with an observed/expected ratio at 10 years of 0.92 (95%PI 0.34–2.54). Decision curve analysis for contralateral preventive mastectomy (CPM) showed the potential clinical utility of PredictCBC-2.0 between thresholds of 4 and 12% 10-year CBC risk for BRCA1/2 mutation carriers and non-carriers. Conclusions: Additional genetic information beyond BRCA1/2 germline mutations improved CBC risk prediction and might help tailor clinical decision-making toward CPM or alternative preventive strategies. Identifying patients who benefit from CPM, especially in the general breast cancer population, remains challenging.
CRIS-Team Scopus Importer:2022-11-04
Keywords: BCAC; BRCA1/2 germline mutation; Breast Cancer Association Consortium; Breast cancer genetic predisposition; Clinical decision-making; Contralateral breast cancer; Contralateral preventive mastectomy; Polygenic risk score; Prediction performance; Risk prediction

Predicting attention deficit hyperactivity disorder using pregnancy and birth characteristics - Schwenke, Eva; Fasching, Peter; Faschingbauer, Florian; Pretscher, Jutta; Kehl, Sven; Peretz, Roberta; Keller, Andrea; Häberle, Lothar; Eichler, Anna; Irlbauer-Müller, Viktoria; Dammer, Ulf; Beckmann, Matthias; et al. (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: The aim of this study was to evaluate maternal, prenatal, perinatal, and postpartum parameters as risk factors for the later development of an attention deficit hyperactivity disorder (ADHD) in the child. METHODS: Women who had given birth at Erlangen University Hospital between 1996 and 1999 were sent a questionnaire in 2009. The results of the questionnaire were correlated with the prospectively collected data for the births in 1996-1999. RESULTS: A total of 573 mother and child pairs were analyzed. Forty-four of the mothers reported that their child had ADHD (7.7%). No significant associations were found for the following parameters: mother's age; mother's educational level; number of the pregnancy; maternal weight before and at the end of pregnancy; mother's height; alcohol consumption during pregnancy; mode of delivery; gestational week; birthweight; umbilical artery blood values; Apgar score at 5 and 10 min; or breastfeeding. The parameters of smoking in pregnancy and an Apgar score lower than 7 after 1 min were significantly associated with a risk for later development of ADHD. CONCLUSIONS: This analysis of maternal, prenatal, perinatal, and postnatal parameters found that smoking in pregnancy and a low Apgar score 1 min after birth are associated with a significantly greater risk for the development of ADHD. Beyond the question of the causal mechanism involved, this is a relevant finding, since smoking during pregnancy is a preventable risk factor.
EVALuna2:36367

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Predicting prognosis of breast cancer patients with brain metastases in the BMBC registry: Comparison of three different - Riecke, K.; Mueller, V.; Neunhoeffer, T.; Weide, R.; Schmidt, M.; Park-Simon, T. -W.; Mundhenke, Christoph; Polasik, A.; Hesse, T.; Luebbe, K.; Laakmann, E.; Thill, M.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Predicting prognosis of breast cancer patients with brain metastases in the BMBC registry—comparison of three different GPA prognostic scores - Riecke, Kerstin; Müller, Volkmar; Weide, Rudolf; Schmidt, Marcus; Park‐simon, Tjoung Won; Möbus, Volker; Mundhenke, Christoph; Polasik, Arkadius; Lübbe, Kristina; Hesse, Tobias; Laakmann, Elena; Thill, Marc; et al. (Cancers, 2021)
Several scores have been developed in order to estimate the prognosis of patients with brain metastases (BM) by objective criteria. The aim of this analysis was to validate all three published graded‐prognostic‐assessment (GPA)‐scores in a subcohort of 882 breast cancer (BC) patients with BM in the Brain Metastases in the German Breast Cancer (BMBC) registry. The median age at diagnosis of BM was 57 years. All in all, 22.3% of patients (n = 197) had triple‐negative, 33.4% (n = 295) luminal A like, 25.1% (n = 221) luminal B/HER2‐enriched like and 19.2% (n = 169) HER2 positive like BC. Age ≥60 years, evidence of extracranial metastases (ECM), higher number of BM, triple‐negative subtype and low Karnofsky‐Performance‐Status (KPS) were all associated with worse overall survival (OS) in univariate analysis (p < 0.001 each). All three GPA‐scores were associated with OS. The breast‐GPA showed the highest probability of classifying patients with survival above 12 months in the best prognostic group (specificity 68.7% compared with 48.1% for the updated breast‐GPA and 21.8% for the original GPA). Sensitivities for predicting 3 months survival were very low for all scores. In this analysis, all GPA‐scores showed only moderate diagnostic accuracy in predicting the OS of BC patients with BM.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Brain metastases; Breast cancer; Prognostic scores

Predicting prognosis of breast cancer patients with brain metastases in the BMBC registry - comparison of three different prognostic scores - Riecke, K.; Mueller,; Neunhoeffer, T.; Weide, R.; Schmidt, M.; Park-Simon, T. W.; Mundhenke, Christoph; Polasik, A.; Hesse, T.; Luebbe, K.; Laakmann, E.; Thill, M.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction and clinical utility of a contralateral breast cancer risk model - Giardiello, Daniele; Steyerberg, Ewout W.; Hauptmann, Michael; Adank, Muriel A.; Akdeniz, Delal; Blomqvist, Carl; Bojesen, Stig E.; Bolla, Manjeet K.; Brinkhuis, Mariël; Chang-Claude, Jenny; Czene, Kamila; Devilee, Peter; et al. (Breast Cancer Research, 2019)
BACKGROUND: Breast cancer survivors are at risk for contralateral breast cancer (CBC), with the consequent burden of further treatment and potentially less favorable prognosis. We aimed to develop and validate a CBC risk prediction model and evaluate its applicability for clinical decision-making. METHODS: We included data of 132,756 invasive non-metastatic breast cancer patients from 20 studies with 4682 CBC events and a median follow-up of 8.8 years. We developed a multivariable Fine and Gray prediction model (PredictCBC-1A) including patient, primary tumor, and treatment characteristics and BRCA1/2 germline mutation status, accounting for the competing risks of death and distant metastasis. We also developed a model without BRCA1/2 mutation status (PredictCBC-1B) since this information was available for only 6% of patients and is routinely unavailable in the general breast cancer population. Prediction performance was evaluated using calibration and discrimination, calculated by a time-dependent area under the curve (AUC) at 5 and 10 years after diagnosis of primary breast cancer, and an internal-external cross-validation procedure. Decision curve analysis was performed to evaluate the net benefit of the model to quantify clinical utility. RESULTS: In the multivariable model, BRCA1/2 germline mutation status, family history, and systemic adjuvant treatment showed the strongest associations with CBC risk. The AUC of PredictCBC-1A was 0.63 (95% prediction interval (PI) at 5 years, 0.52-0.74; at 10 years, 0.53-0.72). Calibration-in-the-large was -0.13 (95% PI: -1.62-1.37), and the calibration slope was 0.90 (95% PI: 0.73-1.08). The AUC of Predict-1B at 10 years was 0.59 (95% PI: 0.52-0.66); calibration was slightly lower. Decision curve analysis for preventive contralateral mastectomy showed potential clinical utility of PredictCBC-1A between thresholds of 4-10% 10-year CBC risk for BRCA1/2 mutation carriers and non-carriers. CONCLUSIONS: We developed a reasonably calibrated model to predict the risk of CBC in women of European-descent; however, prediction accuracy was moderate. Our model shows potential for improved risk counseling, but decision-making regarding contralateral preventive mastectomy, especially in the general breast cancer population where limited information of the mutation status in BRCA1/2 is available, remains challenging.
CRIS-Team Scopus Importer:2019-12-31
Keywords: BRCA mutation carriers; Clinical decision-making; Contralateral breast cancer; Risk prediction model

Prediction of breast cancer risk based on profiling with common genetic variants - Mavaddat, Nasim; Pharoah, Paul D. P.; Michailidou, Kyriaki; Tyrer, Jonathan; Brook, Mark N.; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Brown, Judith; et al. (Journal of the National Cancer Institute, 2015)
Data for multiple common susceptibility alleles for breast cancer may be combined to identify women at different levels of breast cancer risk. Such stratification could guide preventive and screening strategies. However, empirical evidence for genetic risk stratification is lacking.We investigated the value of using 77 breast cancer-associated single nucleotide polymorphisms (SNPs) for risk stratification, in a study of 33 673 breast cancer cases and 33 381 control women of European origin. We tested all possible pair-wise multiplicative interactions and constructed a 77-SNP polygenic risk score (PRS) for breast cancer overall and by estrogen receptor (ER) status. Absolute risks of breast cancer by PRS were derived from relative risk estimates and UK incidence and mortality rates.There was no strong evidence for departure from a multiplicative model for any SNP pair. Women in the highest 1% of the PRS had a three-fold increased risk of developing breast cancer compared with women in the middle quintile (odds ratio [OR] = 3.36, 95% confidence interval [CI] = 2.95 to 3.83). The ORs for ER-positive and ER-negative disease were 3.73 (95% CI = 3.24 to 4.30) and 2.80 (95% CI = 2.26 to 3.46), respectively. Lifetime risk of breast cancer for women in the lowest and highest quintiles of the PRS were 5.2% and 16.6% for a woman without family history, and 8.6% and 24.4% for a woman with a first-degree family history of breast cancer.The PRS stratifies breast cancer risk in women both with and without a family history of breast cancer. The observed level of risk discrimination could inform targeted screening and prevention strategies. Further discrimination may be achievable through combining the PRS with lifestyle/environmental factors, although these were not considered in this repor
EVALuna2:9271

Prediction of contralateral breast cancer: external validation of risk calculators in 20 international cohorts - Giardiello, Daniele; Hauptmann, Michael; Steyerberg, Ewout W.; Adank, Muriel A.; Akdeniz, Delal; Blom, Jannet C.; Blomqvist, Carl; Bojesen, Stig E.; Bolla, Manjeet K.; Brinkhuis, Mariel; Chang-Claude, Jenny; Czene, Kamila; et al. (Breast Cancer Research and Treatment, 2020)
Background Three tools are currently available to predict the risk of contralateral breast cancer (CBC). We aimed to compare the performance of the Manchester formula, CBCrisk, and PredictCBC in patients with invasive breast cancer (BC). Methods We analyzed data of 132,756 patients (4682 CBC) from 20 international studies with a median follow-up of 8.8 years. Prediction performance included discrimination, quantified as a time-dependent Area-Under-the-Curve (AUC) at 5 and 10 years after diagnosis of primary BC, and calibration, quantified as the expected-observed (E/O) ratio at 5 and 10 years and the calibration slope. Results The AUC at 10 years was: 0.58 (95% confidence intervals [CI] 0.57-0.59) for CBCrisk; 0.60 (95% CI 0.59-0.61) for the Manchester formula; 0.63 (95% CI 0.59-0.66) and 0.59 (95% CI 0.56-0.62) for PredictCBC-1A (for settings where BRCA1/2 mutation status is available) and PredictCBC-1B (for the general population), respectively. The E/O at 10 years: 0.82 (95% CI 0.51-1.32) for CBCrisk; 1.53 (95% CI 0.63-3.73) for the Manchester formula; 1.28 (95% CI 0.63-2.58) for PredictCBC-1A and 1.35 (95% CI 0.65-2.77) for PredictCBC-1B. The calibration slope was 1.26 (95% CI 1.01-1.50) for CBCrisk; 0.90 (95% CI 0.79-1.02) for PredictCBC-1A; 0.81 (95% CI 0.63-0.99) for PredictCBC-1B, and 0.39 (95% CI 0.34-0.43) for the Manchester formula. Conclusions Current CBC risk prediction tools provide only moderate discrimination and the Manchester formula was poorly calibrated. Better predictors and re-calibration are needed to improve CBC prediction and to identify low- and high-CBC risk patients for clinical decision-making.
CRIS-Team WoS Importer:2020-04-24

Prediction of pathological complete response after neoadjuvant chemotherapy for HER2-negative breast cancer patients with routine immunohistochemical markers. - Häberle, Lothar; Erber, Ramona; Gaß, Paul; Hein, Alexander; Niklos, Melitta; Volz, Bernhard; Hack, Carolin; Schulz-Wendtland, Rüdiger; Hübner, Hanna; Goossens, Chloe; Christgen, Matthias; Dörk, Thilo; et al. (Breast Cancer Research, 2025)
BACKGROUND: Pathological complete response (pCR) is an established surrogate marker for prognosis in patients with breast cancer (BC) after neoadjuvant chemotherapy. Individualized pCR prediction based on clinical information available at biopsy, particularly immunohistochemical (IHC) markers, may help identify patients who could benefit from preoperative chemotherapy. METHODS: Data from patients with HER2-negative BC who underwent neoadjuvant chemotherapy from 2002 to 2020 (n = 1166) were used to develop multivariable prediction models to estimate the probability of pCR (pCR-prob). The most precise model identified using cross-validation was implemented in an online calculator and a nomogram. Associations among pCR-prob, prognostic IHC3 distant recurrence and disease-free survival were studied using Cox regression and Kaplan-Meier analyses. The model's utility was further evaluated in independent external validation cohorts. RESULTS: 273 patients (23.4%) achieved a pCR. The most precise model had across-validated area under the curve (AUC) of 0.84, sensitivity of 0.82, and specificity of 0.71. External validation yielded AUCs between 0.75 (95% CI, 0.70-0.81) and 0.83 (95% CI, 0.78-0.87). The higher the pCR-prob, the greater the prognostic impact of pCR status (presence/absence): hazard ratios decreased from 0.55 (95% central range, 0.07-1.77) at 0% to 0.20 (0.11-0.31) at 50% pCR-prob. Combining pCR-prob and IHC3 score further improved the precision of disease-free survival prognosis. CONCLUSIONS: A pCR prediction model for neoadjuvant therapy decision-making was established. Combining pCR and recurrence prediction allows identification of not only patients who benefit most from neoadjuvant chemotherapy, but also patients with a very unfavorable prognosis for whom alternative treatment strategies should be considered.
EVALuna2:585357

Prediction of pathological complete response and prognosis in patients with neoadjuvant treatment for triple-negative breast cancer - Gaß, Paul; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bani, Mayada; Fießler, Cornelia; Hartmann, Arndt; Häberle, Lothar; Pretscher, Jutta; Erber, Ramona; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (BMC Cancer, 2018)
BACKGROUND: It has been reported that pathological complete response is an important surrogate marker for disease-free survival and overall survival in patients with triple-negative breast cancer. This study investigates predictors of the response to neoadjuvant platinum-based or anthracycline-based treatment, and of the prognosis, in patients with triple-negative breast cancer. METHODS: A total of 121 patients with triple-negative breast cancer received neoadjuvant treatment with either platinum or anthracycline between 2008 and 2013. Pathological complete response was assessed relative to different treatments using logistic regression models with age, clinical tumor stage, grading, and Ki-67 as predictors and interaction terms, to obtain adjusted and subgroup-specific results. The impact of the pathological complete response rate on disease-free survival and overall survival was also analyzed. RESULTS: The pathological complete response rate was higher after platinum/taxane treatment compared with anthracycline/taxane (50.0% vs. 41.8%), but this was not significant in the adjusted analysis (OR 1.44; 95% CI, 0.68 to 3.09). A high histological grade (G3) was a predictor for higher pathological complete response in platinum-based therapy (OR 2.27; 95% CI, 1.00 to 5.30). The effect of neoadjuvant chemotherapy on pathological complete response was significantly different for G1-2 vs. G3 (Pinteraction = 0.013), and additional subgroup-specific differences were noted. Pathological complete response was a predictor for improved disease-free survival and overall survival in both treatment groups, with and without platinum chemotherapy. CONCLUSIONS: This retrospective study of patients with triple-negative breast cancer adds to the evidence that the treatment effect of platinum may be greatest particularly in G3 tumors. In addition, the effect of pathological complete response on the prognosis does not depend on the treatment used.
EVALuna2:34850

Preexisting musculoskeletal burden and its development under letrozole treatment in early breast cancer patients - Nabieva, Naiba; Häberle, Lothar; Brucker, Sara Y.; Janni, Wolfgang; Volz, Bernhard; Löhberg, Christian; Hartkopf, Andreas D.; Walter, Christina Barbara; Baake, Gerold; Fridman, Alexander; Malter, Wolfram; Wuerstlein, Rachel; et al. (International Journal of Cancer, 2019)
One of the most common adverse events (AEs) occurring during treatment with aromatase inhibitors (AIs) is musculoskeletal pain. The aim of our study was to analyze the influence of preexisting muscle/limb pain and joint pain on the development of AI-induced musculoskeletal AEs. Women eligible for upfront adjuvant endocrine therapy with letrozole were included in the PreFace study, a multicenter phase IV trial. During the first treatment year, they were asked to record musculoskeletal AEs monthly by answering questions regarding pain symptoms and rating the pain intensity on a numeric rating scale from 0 (no pain) to 10 (very strong pain). Pain values were compared using nonparametric statistical tests. Overall, 1,416 patients were evaluable. The average pain value over all time points in women with preexisting muscle/limb pain was 4.3 (median 4.3); in those without preexisting pain, it was 2.0 (median 1.7). In patients without preexisting muscle/limb pain, pain levels increased relatively strongly within the first 6 months (mean increase +0.9, p < 0.00001) in comparison with those with preexisting pain (mean increase +0.3, p < 0.001), resulting in a statistically significant difference (p < 0.00001) between the two groups. The development of joint pain was similar in the two groups. Women without preexisting muscle/limb pain or joint pain have the greatest increase in pain after the start of adjuvant AI therapy. Women with preexisting pain have significantly higher pain values. The main increase in pain values takes place during the first 6 months of treatment.
Keywords: aromatase inhibitor; arthralgia/joint pain; breast cancer; endocrine treatment/therapy; letrozole; myalgia/muscle and limb pain

Prenatal alcohol exposure and the facial phenotype in adolescents: A study based on meconium ethyl glucuronide - Maschke, Janina; Roetner, Jakob; Goecke, Tamme; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (Brain Sciences, 2021)
Here, we explore the effects of prenatal alcohol exposure (PAE) in adolescence. We investigated associations between meconium ethyl glucoronide (EtG) and facial malformation. For 29 children (66/63 male/female; M = 13.3, SD = 0.32, 12–14 years), PAE was implemented by newborn meconium EtG and maternal self-reports during the third trimester. Cognitive development was operationalized by standardized scores (WISC V). The EtG cut-off values were set at ≥10 ng/g (n = 32, 24.8% EtG10+) and ≥112 ng/g (n = 20, 15.5% EtG112+). The craniofacial shape was measured using FAS Facial Photographic Analysis Software. EtG10+− and EtG112+-affected children exhibited a shorter palpebral fissure length (p = 0.031/p = 0.055). Lip circularity was smaller in EtG112+-affected children (p = 0.026). Maternal self-reports were not associated (p > 0.164). Lip circularity correlated with fluid reasoning (EtG10+ p = 0.031; EtG112+ p = 0.298) and working memory (EtG10+ p = 0.084; EtG112+ p = 0.144). The present study demonstrates visible effects of the facial phenotype in exposed adolescents. Facial malformation was associated with a child’s cognitive performance in the alcohol-exposed group. The EtG biomarker was a better predictor than maternal self-reports.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alcohol; Biomarker; Craniofacial shape; Ethyl glucuronide (EtG); Facial malformations; Inner canthal distance; Intrauterine alcohol exposure; Lip circularity; Meconium; Palpebral fissure length

Prenatal and adult androgen activities in alcohol dependence - Lenz, Bernd; Mühle, Christiane; Braun, B.; Weinland, C.; Bouna-Pyrrou, Polyxeni; Behrens, Juliane; Kubis, S.; Mikolaiczik, Katrin; Muschler, M. -R.; Saigali, Sarah; Sibach, M.; Tanovska, P.; et al. (Acta Psychiatrica Scandinavica, 2017)
OBJECTIVE: Alcohol dependence is more prevalent in men than in women. The evidence for how prenatal and adult androgens influence alcohol dependence is limited. We investigated the effects of prenatal and adult androgen activity on alcohol dependence. Moreover, we studied how the behaviours of pregnant women affect their children's prenatal androgen load. METHOD: We quantified prenatal androgen markers (e.g., second-to-fourth finger length ratio [2D : 4D]) and blood androgens in 200 early-abstinent alcohol-dependent in-patients and 240 controls (2013-2015, including a 12-month follow-up). We also surveyed 134 women during pregnancy (2005-2007) and measured the 2D : 4D of their children (2013-2016). RESULTS: The prenatal androgen loads were higher in the male alcohol-dependent patients compared to the controls (lower 2D : 4D, P = 0.004) and correlated positively with the patients' liver transaminase activities (P < 0.001) and alcohol withdrawal severity (P = 0.019). Higher prenatal androgen loads and increasing androgen levels during withdrawal predicted earlier and more frequent 12-month hospital readmission in alcohol-dependent patients (P < 0.005). Moreover, stress levels (P = 0.002), alcohol (P = 0.010) and tobacco consumption (P = 0.017), and lifetime stressors (P = 0.019) of women during pregnancy related positively to their children's prenatal androgen loads (lower 2D : 4D). CONCLUSION: Androgen activities in alcohol-dependent patients and behaviours of pregnant women represent novel preventive and therapeutic targets of alcohol dependence.
EVALuna2:33408

Prenatal Androgen Influence on Addictive Behaviour in Adolescence Vorgeburtlicher Androgen- einfluss auf süchtiges Verhalten in der Adoleszenz - Lenz, Bernd; Eichler, Anna; Buchholz, Verena Nadine; Fasching, Peter; Kornhuber, Johannes (Sucht, 2021)
Background: Men consume alcohol, tobacco, and illicit drugs more often than women, and they are more prone to pathological gambling and addictive internet gaming. These sex differences are already found during adolescence. The consumption patterns are related to externalizing behavior. In addition to social influences, biological factors play a central role in the development of these differences between men and women. Prenatal exposure to androgens and estrogens shape the brain development with functional and structural effects that persist into adulthood. Intrauterine sex hormone exposure is related to maternal risk factors such as stress and substance use. Aim: In this narrative review, we discuss the potential impact of prenatal androgen exposure in the womb on the development of addictive behaviors and self-regulation in later life. In recent years, this issue has been addressed by animal experiments with direct modulation of prenatal androgenization and clinical association studies based on biomarkers such as the second-to-fourth finger lengths ratio (2D:4D). Results: The available body of literature suggests that reinforced brain androgenization during the intrauterine development increases the risk for addictive behaviors and deficits in self-regulation capacity in later life. Finally, we also discuss prevention strategies during pregnancy targeting this model and refer to the Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention study. This investigation is a subproject of the IMAC-Mind research collaborative project to improve mental health and reduce addiction risk in childhood and adolescence through mindfulness.
CRIS-Team Scopus Importer:2021-12-24
Keywords: addiction; adolescence; dependence; prenatal development; testosterone

Presence of circulating tumor cells in high-risk early breast cancer during follow-up and prognosis - Trapp, Elisabeth; Janni, Wolfgang; Schindlbeck, Christian; Jückstock, Julia; Andergassen, Ulrich; De Gregorio, Amelie; Alunni-Fabbroni, Marianna; Tzschaschel, Marie; Polasik, Arkadius; Koch, Julian G.; Friedl, Thomas W.P.; Fasching, Peter; et al. (Journal of the National Cancer Institute, 2019)
Background: The prognostic relevance of circulating tumor cells (CTCs) at the time of primary diagnosis has been well established. However, little information is available regarding their prognostic relevance to follow-up care. Methods: The multicenter, open-label, phase III SUCCESS A trial compared two adjuvant chemotherapy regimens followed by 2 vs 5 years of zoledronate for early-stage, high-risk breast cancer patients. The presence of CTCs was assessed before and 2 years after chemotherapy using the FDA-approved CellSearch System. Overall survival (OS) and disease-free survival (DFS) were analyzed using univariate log-rank tests and multivariable Cox regressions. OS and DFS were measured starting from an assessment of CTCs 2 years after the completion of chemotherapy. All statistical tests were two-sided. Results: The sample included 1087 patients who participated in the translational research program of the SUCCESS A trial and for whom sufficient translational data were available regarding CTC status at baseline and at the 2-year follow-up visit. Two years after chemotherapy, 198 (18.2%) patients were CTC-positive. The median follow-up after this timepoint was 37 months. Cox regressions that included CTC status at baseline revealed that CTC status 2 years after chemotherapy had statistically significant and independent prognostic relevance for OS (hazard ratio [HR] ¼ 3.91, 95% confidence interval [CI] ¼ 2.04 to 7.52, P < .001) and DFS (HR ¼ 2.31, 95% CI ¼ 1.50 to 3.55, P < .001). Conclusion: The presence of CTCs 2 years after chemotherapy was associated with decreased OS and DFS. Based on these results, active individualized surveillance strategies for breast cancer survivors based on biomarkers should be reconsidered.
CRIS-Team Scopus Importer:2019-09-24

Prevalence and course of pregnancy symptoms using self-reported pregnancy app symptom tracker data - Nissen, Michael; Barrios Campo, Nuria; Flaucher, Madeleine; Jäger, Katharina; Titzmann, Adriana; Blunck, Dominik; Fasching, Peter; Engelhardt, Victoria; Eskofier, Björn; Leutheuser, Heike (npj Digital Medicine, 2023)
During pregnancy, almost all women experience pregnancy-related symptoms. The relationship between symptoms and their association with pregnancy outcomes is not well understood. Many pregnancy apps allow pregnant women to track their symptoms. To date, the resulting data are primarily used from a commercial rather than a scientific perspective. In this work, we aim to examine symptom occurrence, course, and their correlation throughout pregnancy. Self-reported app data of a pregnancy symptom tracker is used. In this context, we present methods to handle noisy real-world app data from commercial applications to understand the trajectory of user and patient-reported data. We report real-world evidence from patient-reported outcomes that exceeds previous works: 1,549,186 tracked symptoms from 183,732 users of a smartphone pregnancy app symptom tracker are analyzed. The majority of users track symptoms on a single day. These data are generalizable to those users who use the tracker for at least 5 months. Week-by-week symptom report data are presented for each symptom. There are few or conflicting reports in the literature on the course of diarrhea, fatigue, headache, heartburn, and sleep problems. A peak in fatigue in the first trimester, a peak in headache reports around gestation week 15, and a steady increase in the reports of sleeping difficulty throughout pregnancy are found. Our work highlights the potential of secondary use of industry data. It reveals and clarifies several previously unknown or disputed symptom trajectories and relationships. Collaboration between academia and industry can help generate new scientific knowledge.
CRIS-Team Scopus Importer:2023-10-20

Prevalence of Circulating Tumor Cells After Adjuvant Chemotherapy With or Without Anthracyclines in Patients With HER2-negative, Hormone Receptor-positive Early Breast Cancer - Schramm, Amelie; Schochter, Fabienne; Friedl, Thomas W. P.; De Greqorio, Nikolaus; Andergassen, Ulrich; Alunni-Fabbroni, Marianna; Trapp, Elisabeth; Jaeger, Bernadette; Heinrich, Georg; Camara, Oumar; Decker, Thomas; Ober, Angelika; et al. (Clinical Breast Cancer, 2017)
BACKGROUND: Use of anthracycline-based chemotherapy in patients with early breast cancer (EBC) has been well-established but is often associated with cardiotoxicity. Based on data suggesting a limited benefit of anthracyclines in human epidermal growth factor receptor 2 (HER2)-negative patients, the Simultaneous Study of Docetaxel Based Anthracycline Free Adjuvant Treatment Evaluation, as well as Life Style Intervention Strategies (SUCCESS) C study randomized patients to either anthracycline-containing or anthracycline-free chemotherapy. Given the proven prognostic value of circulating tumor cells (CTCs) in EBC, we compared the prevalence of CTCs after chemotherapy between both treatment arms for a preliminary efficacy assessment. METHODS: The SUCCESS C trial (NCT00847444) is an open-label, phase III study randomizing 3547 patients with HER2-negative EBC to either 3 cycles of epirubicin, 5-fluorouracil, and cyclophosphamide followed by 3 cycles of docetaxel (FEC-DOC) or 6 cycles of docetaxel and cyclophosphamide (DOC-C). CTC status was prospectively evaluated in hormone receptor-positive patients at the time of last chemotherapy cycle using the US Food and Drug Administration-approved CellSearch System (Janssen Diagnostics). RESULTS: Data on CTC status were available for 1766 patients. Overall, CTCs were found in 221 (12.5%) patients. Univariate analyses revealed that presence of CTCs at time of last chemotherapy cycle was not significantly associated with tumor or patient characteristics (all P > .1). There was no significant difference with respect to presence of CTCs between patients randomized to FEC-DOC or DOC-C (11.5% vs. 13.6%; P = .18). CONCLUSIONS: The comparable prevalence of CTCs at the time of last chemotherapy cycle may indicate that anthracycline-free chemotherapy is equally effective to anthracycline-containing chemotherapy in HER2-negative, hormone receptor-positive EBC. However, efficacy data from the final survival analysis of SUCCESS C have to be awaited to confirm these preliminary findings.
EVALuna2:36189

Prevalence of circulating tumor cells in early breast cancer patients 2 and 5 years after adjuvant treatment - Bauer, Emanuel C. A.; Schochter, Fabienne; Widschwendter, Peter; Degregorio, Amelie; Andergassen, Ulrich; Friedl, Thomas W. P.; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Beckmann, Matthias; Pantel, Klaus; Janni, Wolfgang; et al. (Breast Cancer Research and Treatment, 2018)
Several studies have provided evidence on the prognostic relevance of circulating tumor cells (CTCs) detected before and after chemotherapy regarding overall survival (OS) and progression-free survival (PFS) in early breast cancer (EBC). We provide data on the prevalence of CTCs 2 and 5 years after primary diagnosis in a cohort of patients with EBC.The SUCCESS study is a multicenter, prospective, randomized trial comparing PFS in primary breast cancer patients undergoing one of two adjuvant chemotherapy regimens followed by 2 versus 5 years of treatment with zoledronate. CTCs from patients without signs of breast cancer recurrence were analyzed in peripheral blood using the FDA cleared CellSearch® System (Veridex, USA) 2 and 5 years after primary diagnosis.CTCs were detected at 2 and 5 years after primary diagnosis in 96 (16.7%) and 47 (8.2%) of the 574 patients, respectively. There were no associations between CTC status and patient and tumor characteristics or treatment regimens. In 442 (77.0%) patients, no CTCs were detected at either of the two time points, and in 11 patients (1.9%), CTCs were found at both 2 and 5 years after primary diagnosis. In 85 (14.8%) patients, CTCs were present 2 years after primary diagnosis but not after 5 years, while 36 (6.3%) patients had CTCs in their blood only at the 5-year follow-up.In patients with EBC, CTCs can be detected even 5 years after primary diagnosis without clinical signs of disease recurrence.
EVALuna2:56145

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

Primary results of the AGO-Zervix-1 Study: A prospective, randomized phase III study to compare the effects of paclitaxel and topotecan with those of cisplatin and topotecan in the treatment of patients with recurrent and persistent cervical cancer - Gaß, Paul; Thiel, Falk C.; Häberle, Lothar; Ackermann, Sven; Theuser, Anna Katharin; Hummel, Nadine; Boehm, Sibylle; Kimmig, Rainer; Reinthaller, Alexander; Becker, Sven; Hilpert, Felix; Janni, Wolfgang; et al. (Gynecologic Oncology, 2024)
Background: Before the era of immunotherapies and antibody–drug conjugates, there were limited chemotherapeutic options for patients with recurrent and metastatic cervical cancer. Combination therapies with cisplatin have shown some superiority over monotherapy. This study examined platinum-free treatment regimens, comparing a combination of topotecan and paclitaxel (TP) with topotecan and cisplatin (TC) in patients with recurrent or metastatic cervical cancer, with or without prior platinum-based treatment. Methods: The AGO-Zervix-1 Study (NCT01405235) is a prospective, randomized phase III study in which patients were randomly assigned at a 1:1 ratio to treatment within the control arm with topotecan (0.75 mg/m2) on days 1–3 and cisplatin (50 mg/m2) on day 1 every 3 weeks and in the study arm topotecan (1.75 mg/m2) and paclitaxel (70 mg/m2) on days 1, 8, and 15 every 4 weeks or treatment. The primary study aim was overall survival; progression-free survival, toxicity, and quality of life were secondary aims. The interim and final analysis is here reported after recruitment of 173 of 312 planned patients. Results: Median overall survival in the TP arm was 9.6 months, compared with 12.0 months in the TC arm (log-rank test, P = 0.33). Median progression-free survival rates were 4.4 months with TP and 4.2 months with TC (log-rank test, P = 0.47). Leukopenia and nausea/vomiting were more frequent in the cisplatin-containing arm. Otherwise, toxicity profiles were comparable. There were no differences in FACT-G–assessed quality of life. Conclusion: Platinum-based combination chemotherapy remains the standard of care chemotherapy regimen for patients with recurrent or metastatic cervical cancer.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Cervical cancer; Cisplatin; Metastatic; Paclitaxel; Recurrent; Topotecan

Primary Therapy of Early Breast Cancer: Evidence, Controversies, Consensus - Untch, Michael; Thomssen, Christoph; Bauerfeind, Ingo; Braun, Michael; Brucker, Sara Y.; Felberbaum, Ricardo; Hagemann, Friederike; Haidinger, Renate; Hönig, Arnd; Huober, Jens; Jackisch, Christian; Kolberg, Hans Christian; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The results of the international St. Gallen Consensus Conference for the treatment of patients with primary breast cancer were discussed this year by a working group of leading breast cancer experts in view of the therapy recommendations for everyday clinical practice in Germany. Three of the breast cancer experts are also members of this year's St. Gallen panel. The comparison of the St. Gallen recommendations with the annually updated treatment recommendations of the AGO 2019 as well as the S3 guideline is useful, since the recommendations of the St. Gallen panel represent the opinions of experts from various countries and disciplines. The recommendations of the S3 guideline and AGO are based on evidence-based research of the literature. This year's 16th St. Gallen conference featured the motto Magnitude of clinical benefit. In addition to the evidence-based data, each therapeutic decision must also undergo a benefit/risk assessment of the patient's individual situation and be discussed with the patient.
CRIS-Team Scopus Importer:2019-06-28
Keywords: axilla; early breast cancer; locoregional therapy; neoadjuvant treatment; St. Gallen consensus 2019; systemic therapy

Primary Therapy of Patients with Early Breast Cancer: Evidence, Controversies, Consensus: Opinions of German Specialists to the 14th St. Gallen International Breast Cancer Conference 2015 (Vienna 2015) - Untch, M.; Harbeck, N.; Huober, J.; Von Minckwitz, G.; Gerber, B.; Kreipe, H. -H.; Liedtke, C.; Marschner, N.; Moebus, V.; Scheithauer, H.; Schneeweiss, A.; Thomssen, C.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
For the first time, this year's St. Gallen International Consensus Conference on the treatment of patients with primary breast cancer, which takes place every two years, was held not in St. Gallen (Switzerland) but - for logistical reasons - in Vienna (Austria) under its usual name. The 2015 St. Gallen International Consensus Conference was the 14th of its kind. As the international panel of the St. Gallen conference consists of experts from different countries, the consensus mirrors an international cross-section of opinions. From a German perspective, it was considered useful to translate the results of the votes of the St. Gallen conference into practical suggestions, particularly in light of the recently updated treatment guideline of the Gynecologic Oncology Group (AGO-Mamma 2015) in Germany. A German group consisting of 14 breast cancer experts, three of whom are members of the international St. Gallen panel, has therefore provided comments on the results of this year's votes at the 2015 St. Gallen Consensus Conference and their impact on clinical care in Germany. The 14th St. Gallen conference once again focused on surgery of the breast and the axilla, radio-oncologic and systemic treatment options for primary breast cancer depending on tumor biology, and the clinical use of multigene assays. The conference also considered targeted therapies for older and for younger patients, including the diagnosis/treatment of breast cancer during and after pregnancy and the preservation of fertility.
EVALuna2:17567

Prioritization and Resource Allocation in the Context of the COVID-19 Pandemic: Recommendations for Colorectal and Pancreatic Cancer in Germany - Lugnier, Celine; Sommerlatte, Sabine; Attenberger, Ulrike; Beer, Ambros J.; Bentz, Martin; Benz, Stefan R.; Birkner, Thomas; Büntzel, Jens; Ebert, Matthias P.A.; Fasching, Peter; Fischbach, Wolfgang; Fokas, Emmanouil; et al. (Oncology Research and Treatment, 2024)
In the context of the COVID-19 pandemic, there has been a scarcity of resources with various effects on the care of cancer patients. This paper provides an English summary of a German guideline on prioritization and resource allocation for colorectal and pancreatic cancer in the context of the pandemic. Based on a selective literature review as well as empirical and ethical analyses, the research team of the CancerCOVID Consortium drafted recommendations for prioritizing diagnostic and treatment measures for both entities. The final version of the guideline received consent from the executive boards of nine societies of the Association of Scientific Medical Societies in Germany (AWMF), 20 further professional organizations and 22 other experts from various disciplines as well as patient representatives. The guiding principle for the prioritization of decisions is the minimization of harm. Prioritization decisions to fulfill this overall goal should be guided by (1) the urgency relevant to avoid or reduce harm, (2) the likelihood of success of the diagnostic or therapeutic measure advised, and (3) the availability of alternative treatment options. In the event of a relevant risk of harm as a result of prioritization, these decisions should be made by means of a team approach. Gender, age, disability, ethnicity, origin, and other social characteristics, such as social or insurance status, as well as the vehemence of a patient's treatment request and SARS-CoV-2 vaccination status should not be used as prioritization criteria. The guideline provides concrete recommendations for (1) diagnostic procedures, (2) surgical procedures for cancer, and (3) systemic treatment and radiotherapy in patients with colorectal or pancreatic cancer within the context of the German healthcare system.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Colorectal cancer; Guideline; Pancreatic cancer; Pandemic; Resource allocation

Prognosis of Patients with Early Breast Cancer Receiving 5 Years vs 2 Years of Adjuvant Bisphosphonate Treatment: A Phase 3 Randomized Clinical Trial - Friedl, Thomas W. P.; Fehm, Tanja; Mueller, Volkmar; Lichtenegger, Werner; Blohmer, Jens; Lorenz, Ralf; Forstbauer, Helmut; Fink, Visnja; Bekes, Inga; Huober, Jens; Jueckstock, Julia; Schneeweiss, Andreas; et al. (JAMA Oncology, 2021)
Importance: Bisphosphonate treatment in patients with early breast cancer has become part of care, but the optimal treatment duration is still unclear. Objective: To compare 2 vs 5 years of zoledronate treatment following adjuvant chemotherapy in patients with early breast cancer. Design, Setting, and Participants: The SUCCESS A phase 3 multicenter randomized open-label clinical trial with a 2 × 2 factorial design enrolled 3754 patients from September 21, 2005, to March 12, 2007 (last patient out, May 7, 2014). Final data analysis was conducted from September 2019 to October 2020. In 250 German study centers, patients were eligible for participation in the SUCCESS A trial if they had either node-positive or high-risk node-negative (defined as at least 1 of the following: tumor size ≥ pT2, histologic grade 3, negative hormone receptor status, or age ≤35 years) primary invasive breast cancer. Interventions: Patients were first randomized to adjuvant chemotherapy with 3 cycles of fluorouracil, epirubicin, and cyclophosphamide followed by 3 cycles of docetaxel with or without gemcitabine (not presented in this report). After chemotherapy, patients underwent a second randomization of 5 years of zoledronate treatment (4 mg intravenously every 3 months for 2 years, followed by 4 mg intravenously every 6 months for 3 years) vs 2 years of zoledronate treatment (4 mg intravenously every 3 months for 2 years). Main Outcomes and Measures: The primary end point of the study was disease-free survival; secondary end points were overall survival, distant disease-free survival, and the incidence of skeletal-related adverse events. Survival times were measured from 2 years after the start of zoledronate treatment (landmark analysis). Results: Overall, data on 2987 patients were available for analysis; median age was 53 (range, 21-86) years. Disease-free survival, overall survival, and distant disease-free survival did not differ significantly between the 2 treatment arms (5 vs 2 years) as shown by adjusted multivariable Cox proportional hazards regression models (disease-free survival: hazard ratio [HR], 0.97; 95% CI, 0.75-1.25; P =.81; overall survival: HR, 0.98; 95% CI, 0.67-1.42; P =.90; distant disease-free survival: HR, 0.87; 95% CI, 0.65-1.18; P =.38). Adverse events were observed more often in the 5-year (46.2%) vs 2-year (27.2%) zoledronate treatment arm, which was particularly true for the skeletal-related events bone pain (5 years, 8.3% vs 2 years, 3.7%) and arthralgia (5 years, 5.1% vs 2 years, 3.1%). Conclusions and Relevance: The results of this phase 3 randomized clinical trial indicate that extending the zoledronate treatment beyond 2 years does not improve the prognosis of high-risk patients with early breast cancer receiving chemotherapy, suggesting that the currently recommended bisphosphonate treatment duration of 3 to 5 years could be reduced. Trial Registration: ClinicalTrials.gov Identifier: NCT02181101.
CRIS-Team Scopus Importer:2021-07-09

Prognosis prediction with the IHC3 score in patients with node-negative, hormone receptor-positive, HER2-negative early breast cancer - Seitz, Katharina; Goossens, Chloe; Hübner, Hannah; Gaß, Paul; Uhrig, Sabrina; Heindl, Felix; Emons, Julius; Rübner, Matthias; Anetsberger, Daniel; Hartmann, Arndt; Beckmann, Matthias; Erber, Ramona; et al. (ESMO Open, 2024)
Background: Prognostication has been used to identify patient populations that could potentially benefit from treatment de-escalation. In patients with hormone receptor-positive (HRpos), human epidermal growth factor receptor 2-negative (HER2neg) early breast cancer (eBC), treatment de-escalation classically involved omitting chemotherapy. With recently developed specialized therapies that require hands-on side-effect management, the therapeutic landscape is changing and therapy decisions are no longer based only on prognosis, but also consider potential side-effects. Therefore, identification of patient groups based on prognostication has gained importance. Materials and methods: In this retrospective analysis, a population of 2359 node-negative HRpos/HER2neg eBC patients was selected from all patients treated at the University Breast Center of Franconia, Germany between 2002 and 2021. The prognostic value of the IHC3 score (incorporating immunohistochemical measurements of the estrogen and progesterone receptor status and Ki-67) with clinical parameters (lymph node status, tumor stage, grading) regarding invasive disease-free survival (iDFS) and overall survival (OS) was assessed. Results: IHC3 positively correlated with Ki-67 expression and inversely correlated with hormone receptor expression. IHC3 categorized into quartiles identified patients with a more unfavorable prognosis: 5-year and 10-year iDFS rates for patients in the highest versus the lowest quartile were 84% versus 95% and 70% versus 88%, respectively. A sensitivity analysis of distant disease-free survival showed similar results to those of iDFS. Five-year and 10-year OS rates for patients in the highest versus the lowest quartile were, respectively, 92% versus 97% and 81% versus 92%. Conclusions: IHC3 is able to define prognostic groups in patients with node-negative, HRpos/HER2neg eBC. Node-negative patients with a high IHC3 score had the worst prognosis, which was comparable to that of node-positive patients described in recent trials. This simple and cost-effective tool could thus potentially aid in identifying patient groups for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2024-11-01
Keywords: early breast cancer; hormone receptor-positive; IHC3; molecular marker; prognosis

Prognostic effect of Ki-67 in common clinical subgroups of patients with HER2-negative, hormone receptor-positive early breast cancer - Fasching, Peter; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hein, Alexander; Hack, Carolin; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Erber, Ramona (Breast Cancer Research and Treatment, 2019)
Purpose: Several clinical trials have investigated the prognostic and predictive usefulness of molecular markers. With limited predictive value, molecular markers have mainly been used to identify prognostic subgroups in which the indication for chemotherapy is doubtful and the prognosis is favorable enough for chemotherapy to be avoided. However, limited information is available about which groups of patients may benefit from additional therapy. This study aimed to describe the prognostic effects of Ki-67 in several common subgroups of patients with early breast cancer. Methods: This retrospective study analyzed a single-center cohort of 3140 patients with HER2−, hormone receptor-positive breast cancer. Five-year disease-free survival (DFS) rates were calculated for low (< 10%), intermediate (10–19%), and high (≥ 20%) Ki-67 expression levels, as assessed by immunohistochemistry, and for subgroups relative to age, body mass index, disease stage, tumor grade, and (neo-)adjuvant chemotherapy. It was also investigated whether Ki-67 had different effects on DFS in these subgroups. Results: The 5-year DFS rates for patients with low, intermediate, and high levels of Ki-67 expression were 0.90, 0.89, and 0.77, respectively. Ki-67 was able to further differentiate patients with an intermediate prognosis into different prognostic groups relative to common clinical parameters. Patients with stage II breast cancer had 5-year DFS rates of 0.84, 0.88, and 0.79 for low, intermediate, and high levels of Ki-67 expression. Ki-67 had different prognostic effects in subgroups defined by age and tumor grade. Conclusions: Ki-67 may help identify patients in intermediate prognostic groups with an unfavorable prognosis who may benefit from further therapy.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Breast cancer; Ki-67; Molecular marker; Prognosis; Proliferation

Prognostic effect of low-level HER2 expression in patients with clinically negative HER2 status - Hein, Alexander; Hartkopf, Andreas D.; Emons, Julius; Lux, Michael P.; Volz, Bernhard; Taran, Florin Andrei; Overkamp, Friedrich; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (European Journal of Cancer, 2021)
Purpose: Assessment of HER2 overexpression using immunohistochemistry (IHC) and/or in situ hybridisation (ISH) for the detection of HER2 amplifications is standard to identify patients for established HER2-directed treatments. Patients with lower HER2 expression levels have recently also become candidates for novel therapies targeting HER2. This study aimed to assess tumour and patient characteristics and prognosis in patients with advanced breast cancer (aBC), relative to low HER2 expression levels. Methods: PRAEGNANT is a prospective aBC registry (NCT02338167), focusing on molecular biomarkers. Patients in all therapy lines receiving any kind of treatment are eligible. This analysis includes patients with conventionally HER2-negative aBC. Clinical outcome was compared in the groups with no (IHC score 0) or with low HER2 expression (IHC 1+, or IHC 2+/ISH negative). Results: Low HER2 expression levels in triple-negative aBC patients did not influence progression-free survival. Overall survival appeared poorer in patients with IHC 2+ compared with patients with no HER2 expression in the unadjusted analysis (hazard ratio 2.24, 95% confidence interval 0.1.12–4.47). However, this effect was not maintained in the adjusted analysis. In HER2-negative, hormone receptor–positive patients, low HER2 expression appeared to have no effect on prognosis, neither progression-free survival nor overall survival. Conclusions: We could not demonstrate that HER2 expression at a low level and assessed in clinical routine can differentiate patients into prognostic groups. However, the prevalence of patients with a low expression makes this population interesting for clinical trials with potentially active treatments using HER2 as a target.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Advanced breast cancer; Antihormone therapy; Chemotherapy; HER2; HER2/neu; Lapatinib; Metastatic; Pertuzumab; TDM-1; Trastuzumab

Prognostic gene expression signature for high-grade serous ovarian cancer - Millstein, J.; Budden, T.; Goode, E. L.; Anglesio, M. S.; Talhouk, A.; Intermaggio, M. P.; Leong, H. S.; Chen, S.; Elatre, W.; Gilks, B.; Nazeran, T.; Volchek, M.; et al. (Annals of Oncology, 2020)
Background: Median overall survival (OS) for women with high-grade serous ovarian cancer (HGSOC) is ∼4 years, yet survival varies widely between patients. There are no well-established, gene expression signatures associated with prognosis. The aim of this study was to develop a robust prognostic signature for OS in patients with HGSOC. Patients and methods: Expression of 513 genes, selected from a meta-analysis of 1455 tumours and other candidates, was measured using NanoString technology from formalin-fixed paraffin-embedded tumour tissue collected from 3769 women with HGSOC from multiple studies. Elastic net regularization for survival analysis was applied to develop a prognostic model for 5-year OS, trained on 2702 tumours from 15 studies and evaluated on an independent set of 1067 tumours from six studies. Results: Expression levels of 276 genes were associated with OS (false discovery rate < 0.05) in covariate-adjusted single-gene analyses. The top five genes were TAP1, ZFHX4, CXCL9, FBN1 and PTGER3 (P < 0.001). The best performing prognostic signature included 101 genes enriched in pathways with treatment implications. Each gain of one standard deviation in the gene expression score conferred a greater than twofold increase in risk of death [hazard ratio (HR) 2.35, 95% confidence interval (CI) 2.02–2.71; P < 0.001]. Median survival [HR (95% CI)] by gene expression score quintile was 9.5 (8.3 to –), 5.4 (4.6–7.0), 3.8 (3.3–4.6), 3.2 (2.9–3.7) and 2.3 (2.1–2.6) years. Conclusion: The OTTA-SPOT (Ovarian Tumor Tissue Analysis consortium - Stratified Prognosis of Ovarian Tumours) gene expression signature may improve risk stratification in clinical trials by identifying patients who are least likely to achieve 5-year survival. The identified novel genes associated with the outcome may also yield opportunities for the development of targeted therapeutic approaches.
CRIS-Team Scopus Importer:2020-07-17
Keywords: formalin-fixed paraffin-embedded; gene expression; high-grade serous ovarian cancer; overall survival; prognosis

Prognostic impact of selection criteria of current adjuvant endocrine therapy trials NATALEE and monarchE in postmenopausal HRpos/HER2neg breast cancer patients treated with upfront letrozole - Fasching, Peter; Hack, Carolin; Nabieva, Naiba; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (European Journal of Cancer, 2024)
Background: The monarchE and NATALEE trials demonstrated the benefit of CDK4/6 inhibitor (CDK4/6i) therapy in adjuvant breast cancer (BC) treatment. Patient selection, based on clinical characteristics, delineated those at high (monarchE) and high/intermediate recurrence risk (NATALEE). This study employed a historical patient cohort to describe the proportion and prognosis of patients eligible for adjuvant CDK4/6i trials. Methods: Between 2009 and 2011, 3529 patients were enrolled in the adjuvant PreFace clinical trial (NCT01908556). Eligibility criteria included postmenopausal patients with hormone receptor-positive (HRpos) BC for whom a five-year upfront therapy with letrozole was indicated. Patients were categorized into prognostic groups according to monarchE and NATALEE inclusion criteria, and their invasive disease-free survival (iDFS) and overall survival (OS) were assessed. Results: Among 2891 HRpos patients, 384 (13.3 %) met the primary monarchE inclusion criteria. The majority (n = 261) qualified due to having ≥ 4 positive lymph nodes. For NATALEE, 915 out of 2886 patients (31.7 %) met the eligibility criteria, with 126 patients (13.7 %) being node-negative. Patients from monarchE with ≥ 4 positive lymph nodes and NATALEE with stage III BC exhibited the poorest prognosis (3-year iDFS rate 0.87). Patients ineligible for the trials demonstrated prognoses similar to the most favorable patient groups within the eligibility criteria. Conclusion: Patient populations eligible for monarchE and NATALEE trials differed. Nearly a third of the postmenopausal HRpos population, previously under upfront letrozole treatment, met the NATALEE prognostic eligibility criteria. As certain eligible groups had a prognosis similar to non-eligible patients, it might be interesting to explore additional patient groups for CDK4/6i therapy.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Aromatase inhibitors; CDK4/6 inhibitors; Early breast cancer; Hormone therapy; Letrozole; Prognosis

Prognostic Impact of Weight Change During Adjuvant Chemotherapy in Patients With High-Risk Early Breast Cancer: Results From the ADEBAR Study - Mutschler, Nikola S.; Scholz, Christoph; Friedl, Thomas W. P.; Zwingers, Thomas; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Mohrmann, Svjetlana; Salmen, Jessica; Ziegler, Carola; Jaeger, Bernadette; Widschwendter, Peter; et al. (Clinical Breast Cancer, 2018)
In addition to established prognostic factors, individual lifestyle-associated factors, such as obesity, physical activity, and diet, seem to modulate the course of breast cancer. The aim of this analysis was to evaluate the influence of weight changes during adjuvant chemotherapy on outcome in a large multicenter prospectively randomized trial.The ADEBAR trial compares a sequential chemotherapy consisting of epirubicin/cyclophosphamide followed by docetaxel to an epirubicin/5-fluorouracil/cyclophosphamide regimen in patients with lymph node-positive early breast cancer. Body weight was measured before each cycle of chemotherapy. According to the relative weight change (>= 5%) between the first and the last cycle, patients were categorized into the weight gain, weight loss, or stable weight group. Overall survival (OS) and disease-free survival were assessed by univariate Kaplan-Meier and multivariate Cox regression analyses.Concise data from 1080 of 1493 participants who completed all cycles of chemotherapy were available for analysis. Of 307 patients (24.8%) whose weight changed by >= 5%, 120 patients (11.1%) lost and 187 (17.3%) gained weight. Multivariate analysis showed a significant independent effect of weight change on OS (P = .039), but not on disease-free survival (P = .111). Both weight change groups had a worse OS compared to patients with stable weight (weight gain: hazard ratio, 1.55; 95% confidence interval, 1.01-2.40; P = .047; weight loss: hazard ratio, 1.55; 95% CI, 0.97-2.47; P = .067).Weight change of > 5% during adjuvant chemotherapy in patients with high-risk early breast cancer is associated with poor OS.
EVALuna2:56149

Prognostic relevance of Ki-67 in the primary tumor for survival after a diagnosis of distant metastasis - Loehberg, Christian R.; Almstedt, Katrin; Jud, Sebastian; Haeberle, Lothar; Fasching, Peter; Hack, Carolin; Lux, Michael P.; Thiel, Falk; Schrauder, Michael G.; Brunner, Michaela; Bayer, Christian M.; Hein, Alexander; et al. (Breast Cancer Research and Treatment, 2013)
Prediction of the prognosis for metastatic breast cancer patients depends on molecular subtypes similar to those found in patients with primary breast cancer. Several studies have shown that estrogen receptor (ER) and progesterone receptor (PR) status determine the course of the disease and the prognosis. As Ki-67 helps to differentiate molecular subtypes in patients with primary breast cancer, the aim of this study was to assess the prognostic relevance of Ki-67 in the primary tumor in relation to its prognostic relevance for patients with metastatic breast cancer. A total of 467 patients with invasive breast cancer were identified in the database of a single breast cancer center, in whom Ki-67 had been assessed in tumor material from the breast at the time of the primary diagnosis and who had developed a metastasis at any time during the subsequent course. For these patients, tumor and patient characteristics were used to determine prognostic factors relative to overall survival after the diagnosis of distant metastases. Ki-67 was added to this model to investigate whether this might improve the prediction of overall survival. In the multivariate Cox model, age at diagnosis, body mass index, nodal status, tumor size, ER and PR status, and time from diagnosis to metastasis were identified as relevant prognostic factors. Adding Ki-67 to the model improved the prediction of overall survival. There was also a significant and relevant interaction with the PR status. In patients with a low-proliferation primary tumor, a high level of PR expression would indicate an extraordinarily good prognosis (HR 0.39; 95 % CI, 0.23-0.66). In patients with higher-proliferation primary tumors, PR status was not capable of differentiating prognostic groups. Ki-67 is useful in addition to known prognostic factors for breast cancer. It is able to indicate a group of women with a poorer prognosis, specifically in the group of patients with PR-positive breast cancer. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Ki-67; Metastatic breast cancer; Progesterone receptor; Prognosis; Proliferation

Prognostic relevance of the HER2 status of circulating tumor cells in metastatic breast cancer patients screened for participation in the DETECT study program - Müller, V.; Banys-Paluchowski, M.; Friedl, T. W.P.; Fasching, Peter; Schneeweiss, A.; Hartkopf, A.; Wallwiener, D.; Rack, B.; Meier-Stiegen, F.; Huober, J.; Rübner, Matthias; Hoffmann, O.; et al. (ESMO Open, 2021)
Background: Circulating tumor cells (CTCs) have been reported to predict clinical outcome in metastatic breast cancer (MBC). Biology of CTCs may differ from that of the primary tumor and HER2-positive CTCs are found in some patients with HER2-negative tumors. Patients and methods: Patients with HER2-negative MBC were screened for participation in DETECT III and IV trials before the initiation of a new line of therapy. Blood samples were analyzed using CELLSEARCH. CTCs were labeled with an anti-HER2 antibody and classified according to staining intensity (negative, weak, moderate, or strong staining). Results: Screening blood samples were analyzed in 1933 patients with HER2-negative MBC. As many as 1217 out of the 1933 screened patients (63.0%) had ≥1 CTC per 7.5 ml blood; ≥5 CTCs were detected in 735 patients (38.0%; range 1-35 078 CTCs, median 8 CTCs). HER2 status of CTCs was assessed in 1159 CTC-positive patients; ≥1 CTC with strong HER2 staining was found in 174 (15.0%) patients. The proportion of CTCs with strong HER2 staining among all CTCs of an individual patient ranged between 0.06% and 100% (mean 15.8%). Patients with estrogen receptor (ER)- and progesterone receptor (PR)-positive tumors were more likely to harbor ≥1 CTC with strong HER2 staining. CTC status was significantly associated with overall survival (OS). Detection of ≥1 CTC with strong HER2 staining was associated with shorter OS [9.7 (7.1-12.3) versus 16.5 (14.9-18.1) months in patients with CTCs with negative-to-moderate HER2 staining only, P = 0.013]. In multivariate analysis, age, ER status, PR status, Eastern Cooperative Oncology Group performance status, therapy line, and CTC status independently predicted OS. Conclusion: CTC detection in patients with HER2-negative disease is a strong prognostic factor. Presence of ≥1 CTC with strong HER2 staining was associated with shorter OS, supporting a biological role of HER2 expression on CTCs.
CRIS-Team Scopus Importer:2021-12-17
Keywords: breast cancer; circulating tumor cell; HER2 status; liquid biopsy; survival

Prognostic relevance of the HER2 status of circulating tumor cells in metastatic breast cancer patients screened for participation in the DETECT study program - Muller, Volkmar; Banys-Paluchowski, Maggie; Friedl, Thomas W. P.; Fasching, Peter; Schneeweiss, Andreas; Hartkopf, Andreas; Wallwiener, Diethelm; Rack, Brigitte; Meier-Stiegen, Franziska; Huober, Jens; Rübner, Matthias; Hoffmann, Oliver; et al. (Cancer Research, 2021)
CRIS-Team WoS Importer:2021-03-26

Progression-free survival and overall survival in patients with advanced her2-positive breast cancer treated with trastuzumab emtansine (T-dm1) after previous treatment with pertuzumab - Michel, Laura L.; Hartkopf, Andreas D.; Fasching, Peter; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; Beckmann, Matthias; et al. (Cancers, 2020)
The approval of trastuzumab emtansine (T-DM1) was conducted without pertuzumab as previous therapy. Efficacy data on T-DM1 following pertuzumab treatment are therefore limited. This study explores this issue in a real-world setting. Within the prospective PRAEGNANT (Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Advanced Setting) metastatic breast cancer registry (NCT02338167), patients in all therapy lines receiving any kind of treatment were eligible for inclusion. This report describes patient characteristics and progression-free survival (PFS) in human epidermal growth factor receptor 2 (HER2)-positive patients receiving T-DM1 after pertuzumab treatment. Seventy-six patients were identified, 39 of whom received T-DM1 as second-line therapy, 25 as third-line, and 12 as fourth-line therapy or higher. Pertuzumab was mostly administered as a first-line treatment (n = 61; 80.3%). The median PFS in all patients was 3.5 months (95% CI: 2.8–7.8); in second-line treatment, 7.7 months (95% CI: 2.8–11.0); in third-line, 3.4 months (95% CI: 2.3–not reached (NR)); and in fourth-line therapy or higher, 2.7 months (95% CI: 1.2–NR). T-DM1 was mainly administered second-line after pertuzumab, but also in more heavily pretreated patients. The PFS in higher therapy lines appears to be shorter than in second-line.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Advanced breast cancer; Chemotherapy; HER2 c-erbB2; HER2/neu; Metastatic; Pertuzumab; T-DM1; Trastuzumab

PROTAC Drugs in Cancer Care - Fasching, Peter (Clinical Advances in Hematology and Oncology, 2024)
CRIS-Team Scopus Importer:2024-05-24

Q-TWiST analysis of pembrolizumab combined with chemotherapy as first-line treatment of metastatic TNBC that expresses PD-L1 - Fasching, Peter; Huang, M.; Haiderali, A.; Pan, W.; Hu, P.; Chaudhuri, M.; De Tilleghem, C. Le Bailly; Cappoen, N.; O'Shaughnessy, J. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Q-TWiST analysis of pembrolizumab combined with chemotherapy as first-line treatment of metastatic triple-negative breast cancer that expresses PD-L1 - Huang, Min; O'Shaughnessy, Joyce; Haiderali, Amin; Pan, Wilbur; Hu, Peter; Chaudhuri, Mitashri; Le Bailly De Tilleghem, Celine; Cappoen, Nicolas; Fasching, Peter (European Journal of Cancer, 2022)
Objective: In the KEYNOTE-355 (KN355) trial, pembrolizumab in combination with chemotherapy demonstrated superior efficacy and manageable safety compared with chemotherapy alone in patients with previously untreated locally recurrent inoperable and metastatic triple-negative breast cancer (mTNBC) with PD-L1 positive (Combined Positive Score [CPS]≥ 10) tumours. This study aimed to evaluate the clinical benefits and risks of pembrolizumab measured by quality-adjusted survival in the trial population. Methods: The study used data from the final analysis of KN355. The Quality-adjusted Time Without Symptoms of disease progression or Toxicity of treatment (Q-TWiST) analysis was used to compare treatments of pembrolizumab plus chemotherapy versus chemotherapy alone. Patients’ survival time was partitioned into three health states — toxicity before disease progression (TOX), time without symptoms or toxicity before disease progression (TWiST), and relapse (REL). Utilities for these health states were estimated using EuroQol-5 Dimensions, 3 Levels (EQ-5D-3L) data collected in KN355. Q-TWiST was derived as the utility-weighted sum of the mean health state durations. Results: Patients randomised to pembrolizumab plus chemotherapy had 3.7 months greater Q-TWiST (relative gain of 18%; P = 0.003) compared to those randomised to chemotherapy at the median follow-up of 44 months, and 4.3 months greater Q-TWiST (relative gain of 20%; P = 0.004) at the maximum follow-up of 52 months. The Q-TWiST gain increased with longer follow-up time. Conclusions: Pembrolizumab plus chemotherapy was associated with statistically significant and clinically important improvement in Q-TWiST compared to chemotherapy in previously untreated PD-L1–positive mTNBC.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Metastatic triple-negative breast cancer; Pembrolizumab plus chemotherapy; Q-TWiST; Quality-adjusted survival

Quality-adjusted survival with ribociclib plus fulvestrant (R plus F) versus placebo plus fulvestrant (P plus F) in postmenopausal women (PMW) HR+/HER2-advanced breast cancer (ABC) based on the MONALEESA-3 trial - Jerusalem, G.; Delea, T.; Martin Jimenez, M.; De Laurentiis, M.; Nusch, A.; Beck, J. T.; Chan, A.; Im, S-A.; Neven, P.; Lonshteyn, A.; Chandiwana, D.; Lanoue, B.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Quality-Adjusted Survival with Ribociclib Plus Fulvestrant Versus Placebo Plus Fulvestrant in Postmenopausal Women with HR±HER2− Advanced Breast Cancer in the MONALEESA-3 Trial - Jerusalem, Guy; Delea, Thomas E.; Martin, Migule; De Laurentiis, Michelino; Nusch, Arnd; Beck, J. Thaddeus; Chan, Arlene; Im, Seock Ah; Neven, Patrick; Lonshteyn, Alexander; Chandiwana, David; Lanoue, Brad; et al. (Clinical Breast Cancer, 2022)
Background: MONALEESA-3 demonstrated an overall survival (OS) benefit for ribociclib plus fulvestrant (R+F) in postmenopausal women with hormone receptor (HR) positive, HER2 negative advanced breast cancer (ABC). This study estimated quality-adjusted (QA) survival outcomes for patients receiving R+F vs. placebo (P)+F in MONALEESA-3. Methods: Kaplan-Meier OS was partitioned into health states: (1) toxicity (TOX)=time spent with grade 3 –4 adverse events before progression (DP); (2) progression (PROG)=time between DP and death; and (3) time without symptoms or toxicity (TWiST)=time not in TOX or PROG. QA time was calculated by combining estimated mean time in each health state with treatment-group specific health-state utility values estimated using EQ-5D-5L questionnaire. Outcomes included QA progression-free survival (QAPFS), QAOS, and QA TWiST (Q-TWiST). Q-TWiST was calculated with health-state utility values for TOX and PROG defined relative to TWiST. Results: Mean PFS and OS were significantly greater with R+F vs. P+F (difference 0.56 and 0.19 years). Mean time in TOX and TWiST were greater with R+F; mean time in PROG was greater with P+F. QAPFS was 0.45 years (95% CI 0.27 –0.63) greater with R+F than P+F (P <.001). QAOS was numerically greater with R+F vs. P+F (0.16 years, 95% CI 0.07 –0.45, P = .0569). Q-TWiST was 0.23 years greater with R+F (95% CI 0.07 –0.45, P = .0069). In a sensitivity analysis using an estimate of disutility for PROG, the difference in QAOS was 0.23 years (95% CI 0.08 –0.41, P = .0022). Conclusion: R+F in postmenopausal women with HR+/HER2- ABC improves QAPFS, resulting in clinically important improvements in Q-TWiST and may improve QAOS.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Breast cancer; Fulvestrant; Postmenopausal; Quality of life; Ribociclib; Survival

Quality-Assured Analysis of PIK3CA Mutations in Hormone Receptor–Positive/Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer Tissue: A Story About the Need for Proficiency Testing for High-Quality Molecular Biomarker Reporting in Precision Medicine - Schmidt, Carolin; Stöhr, Robert; Dimitrova, Lora; Beckmann, Matthias; Rübner, Matthias; Fasching, Peter; Denkert, Carsten; Lehmann, Ulrich; Vollbrecht, Claudia; Haller, Florian; Hartmann, Arndt; Erber, Ramona (Journal of Molecular Diagnostics, 2024)
In precision oncology, reliable testing of predictive molecular biomarkers is a prerequisite for optimal patient treatment. Interlaboratory comparisons are a crucial tool to verify diagnostic performance and reproducibility of one's approach. Herein is described the design and results of the first recurrent, internationally performed PIK3CA (phosphatidylinositol-4,5-bisphosphate 3 kinase catalytic subunit α) breast cancer tissue external quality assessment (EQA), organized by German Quality in Pathology GmbH and started in 2021. After the internal pretesting phase performed by the (lead) panel institutes, in both 2021 and 2022, each EQA test set comprised n = 10 tissue samples of hormone receptor–positive, human epidermal growth factor receptor 2–negative invasive breast cancer that had to be analyzed and reported by the participants. In 2021, the results were evaluated separately for German-speaking countries (part 1) and international laboratories (part 2). In 2022, the EQA was performed across the European Union. The EQA success rates were 84.6% (n = 11/13), 88.6% (n = 39/44), and 87.9% (n = 29/33) for EQA 2021 part 1, part 2, and EQA 2022, respectively. The most commonly used methods were next-generation sequencing and mutation-/allele-specific qualitative PCR-based assays. In summary, this recurrent PIK3CA EQA proved to be a suitable approach to obtain an international overview of methods used for PIK3CA mutation analysis, to evaluate them qualitatively, and identify the strengths and weaknesses of individual methods.
CRIS-Team Scopus Importer:2024-05-31

Quality of Life and Treatment-Related Side Effects in Patients With HR+/HER2- Advanced Breast Cancer: Findings From a Multicountry Survey - Cardoso, Fatima; Rihani, Julie; Harmer, Victoria; Harbeck, Nadia; Casas, Ana; Rugo, Hope S.; Fasching, Peter; Moore, Adam; de Courcy, Joanna; Pathak, Purnima; Haftchenary, Sina; Aubel, Dawn; et al. (Oncologist, 2023)
BACKGROUND: Quality of life (QOL) is a critical factor in decision-making for advanced breast cancer (ABC). There is a need to improve how QOL and treatment-related side effects (SEs) that impact it are clinically assessed. We examined healthcare professionals' (HCPs') and patients' perspectives on the importance of QOL discussions and the impact of SEs on QOL in clinical settings. PATIENTS AND METHODS: A cross-sectional online survey was conducted (7/2020-5/2021) among oncologists, nurses, and patients with HR+/HER2- ABC in 7 countries. RESULTS: The survey was completed by 502 HCPs and 467 patients. Overall, 88% of oncologists and 49% of patients recalled QOL discussions at follow-up. In the first- through fourth-line (1L, 2L, 3L, and 4L) settings, respectively, 48%, 57%, 79%, and 85% of oncologists reported QOL was very important; 73% and 45% of patients receiving 1L and 2L treatment and 40% receiving 3L+ treatment indicated QOL was important. Patients reported that insomnia, anxiety, back pain, fatigue, diarrhea, hot flashes, low sexual interest, and loss of appetite had a moderate/severe impact on QOL. Of patients experiencing certain SEs, ≥64% did not discuss them with HCPs until there was a moderate/severe impact on QOL. In patients receiving a CDK4/6 inhibitor, SEs, including insomnia, diarrhea, back pain, and fatigue, had a moderate/severe impact on QOL. CONCLUSIONS: This survey discovered disconnects between HCPs and patients with ABC on the importance of QOL discussions and the impact of SEs on QOL. These data support the use of ABC-specific QOL questionnaires that closely monitor SEs impacting QOL.
CRIS-Team Scopus Importer:2023-10-20
Keywords: advanced breast cancer; physician/patient communication; qualitative research; quality of life; survey

Quality of life with talazoparib after platinum or multiple cytotoxic non-platinum regimens in patients with advanced breast cancer and germline BRCA1/2 mutations: patient-reported outcomes from the ABRAZO phase 2 trial - Hurvitz, S. A.; Quek, R. G. W.; Turner, N. C.; Telli, M. L.; Rugo, H. S.; Mailliez, A.; Ettl, J.; Grischke, E.; Mina, L. A.; Balmana, Judith; Fasching, Peter; Bhattacharyya, H.; et al. (European Journal of Cancer, 2018)
BACKGROUND: Talazoparib (1 mg/day) exhibited promising efficacy and safety in patients with advanced breast cancer during ABRAZO (NCT02034916); this study evaluated patient-reported outcomes (PROs). PATIENTS AND METHODS: ABRAZO is a two-cohort, two-stage, phase 2 study of talazoparib in patients with advanced breast cancer after a response to prior platinum-based therapy (cohort 1 [C1], n = 49) or ≥3 platinum-free cytotoxic-based regimens (cohort 2 [C2], n = 35). PROs were assessed on day 1 (baseline), every 6 weeks for an initial 24 weeks, and every 12 weeks thereafter until progression, using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (QLQ-C30) and its breast cancer module, QLQ-BR23. RESULTS: Global health status/quality of life (GHS/QoL) was maintained from baseline across all time points for both C1 and C2. For C1 and C2, median time to deterioration (TTD) of GHS/QoL (95% confidence interval [CI]) was 2.8 (2.1, 3.0) and 5.5 (4.2, 5.7) months, respectively. Median TTD for all QLQ-C30 functional scales for C1 and C2 ranged 2.1-3.1 months and 4.2-5.6 months, respectively; median TTD for all QLQ-BR23 symptom scales ranged 2.6-4.0 months and 4.2-5.6 months, respectively. There were no statistically significant differences in estimated overall change from baseline in the GHS/QoL scale for both cohorts (C1: -2.6 [95% CI, -7.8, 2.5]; C2: 1.2 [95% CI, -5.5, 8.0]). Significant overall improvements in the breast symptoms and arm symptoms and the future perspective of patients in C1 and C2 were observed, despite the statistically significant and clinically meaningful overall deterioration among patients regarding their role functioning (in C1) and dyspnoea symptoms (in C2). CONCLUSION: Despite the statistically significant and clinically meaningful overall deterioration among patients regarding their role functioning (in C1) and dyspnoea symptoms (in C2), patients in both C1 and C2 reported significant overall improvements in their breast symptoms, arm symptoms and future perspective, and their GHS/QoL was maintained from baseline.
EVALuna2:202806

RAD51B in Familial Breast Cancer - Pelttari, Liisa M.; Khan, Sofia; Vuorela, Mikko; Kiiski, Johanna I.; Vilske, Sara; Nevanlinna, Viivi; Ranta, Salla; Schleutker, Johanna; Winqvist, Robert; Kallioniemi, Anne; Doerk, Thilo; Bogdanova, Natalia V.; et al. (PLoS ONE, 2016)
Common variation on 14q24.1, close to RAD51B, has been associated with breast cancer: rs999737 and rs2588809 with the risk of female breast cancer and rs1314913 with the risk of male breast cancer. The aim of this study was to investigate the role of RAD51B variants in breast cancer predisposition, particularly in the context of familial breast cancer in Finland. We sequenced the coding region of RAD51B in 168 Finnish breast cancer patients from the Helsinki region for identification of possible recurrent founder mutations. In addition, we studied the known rs999737, rs2588809, and rs1314913 SNPs and RAD51B haplotypes in 44,791 breast cancer cases and 43,583 controls from 40 studies participating in the Breast Cancer Association Consortium (BCAC) that were genotyped on a custom chip (iCOGS). We identified one putatively pathogenic missense mutation c.541C>T among the Finnish cancer patients and subsequently genotyped the mutation in additional breast cancer cases (n = 5259) and population controls (n = 3586) from Finland and Belarus. No significant association with breast cancer risk was seen in the meta-analysis of the Finnish datasets or in the large BCAC dataset. The association with previously identified risk variants rs999737, rs2588809, and rs1314913 was replicated among all breast cancer cases and also among familial cases in the BCAC dataset. The most significant association was observed for the haplotype carrying the risk-alleles of all the three SNPs both among all cases (odds ratio (OR): 1.15, 95% confidence interval (CI): 1.11-1.19, P = 8.88 x 10-16) and among familial cases (OR: 1.24, 95% CI: 1.16-1.32, P = 6.19 x 10-11), compared to the haplotype with the respective protective alleles. Our results suggest that loss-of-function mutations in RAD51B are rare, but common variation at the RAD51B region is significantly associated with familial breast cancer risk.
EVALuna2:33327

RAD51 Testing in Patients with Early HER2-Negative Breast Cancer and Homologous Recombination Deficiency: A Post Hoc Analysis of the GeparOLA Trial - Villacampa, Guillermo; Llop-Guevara, Alba; Filmann, Natalie; Herencia-Ropero, Andrea; Fasching, Peter; Karn, Thomas; Marmé, Frederik; Klare, Peter; Müller, Volkmar; Stefek, Andrea; Schem, Christian; Uleer, Christoph; et al. (Clinical Cancer Research, 2025)
PURPOSE: The randomized GeparOLA trial reported comparable pathologic complete response (pCR) rates with neoadjuvant treatment containing olaparib versus carboplatin. In this study, we evaluate the association between functional homologous recombination deficiency (HRD) by RAD51 foci and pCR and the potential of improving patient selection by combining RAD51 and stromal tumor-infiltrating lymphocytes. PATIENTS AND METHODS: This is a post hoc blinded biomarker analysis from the randomized GeparOLA trial. Patients with early-stage HER2-negative breast cancer and HRD assessed by Myriad MyChoice or BRCA1/BRCA2 mutations were randomized 1:1 to receive (i) paclitaxel plus olaparib or (ii) paclitaxel plus carboplatin, both followed by epirubicin/cyclophosphamide. Functional HRD was predefined as a RAD51 score ≤10% (RAD51-low). RESULTS: Overall, 90 of 97 (92.8%) samples were evaluable for RAD51 testing, and 72 of 90 (80.0%) were RAD51-low. The pCR rate in patients with RAD51-low tumors was 66.7% (48/72), whereas it decreased to 22.2% (4/18) in those with RAD51-high. In the multivariable model including clinicopathologic factors and treatment, the RAD51 score remained significantly associated with pCR (OR = 12.03; 95% confidence interval, 2.60-55.73; P = 0.002). Patients with RAD51-low and high stromal tumor-infiltrating lymphocytes in their tumors achieved a pCR rate of 75.0% (27/36). Similar results were observed for olaparib or carboplatin. In the exploratory disease-free survival analysis, no differences were observed between RAD51 groups (high vs. low: HR = 0.85; 95% confidence interval, 0.25-2.97). CONCLUSIONS: In a preselected population with HRD, according to a genetic test, RAD51 testing identifies patients with different pCR rates under PARP inhibitor-based or platinum-based therapies. Future biomarker-driven studies should consider this information to refine stratification factors and to improve patient selection.
CRIS-Team Scopus Importer:2025-03-28

Radiotherapy statements of the 18th St. Gallen International Breast Cancer Consensus Conference—a German expert perspective - Krug, David; Banys-Paluchowski, Maggie; Brucker, Sara Y.; Denkert, Carsten; Ditsch, Nina; Fasching, Peter; Haidinger, Renate; Harbeck, Nadia; Heil, Jörg; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; et al. (Strahlentherapie und Onkologie, 2024)
Purpose: To summarize the radiotherapy-relevant statements of the 18th St. Gallen Breast Cancer Consensus Conference and interpret the findings in light of German guideline recommendations. Methods: Statements and voting results from the 18th St. Gallen International Breast Cancer Consensus Conference were collected and analyzed according to their relevance for the radiation oncology community. The voting results were discussed in two hybrid meetings among the authors of this manuscript on March 18 and 19, 2023, in light of the German S3 guideline and the 2023 version of the Arbeitsgemeinschaft Gynäkologische Onkologie (AGO) guidelines. Results and conclusion: There was a high level of agreement between the radiotherapy-related statements of the 18th St. Gallen International Breast Cancer Consensus Conference and the German S3 and AGO guidelines. Discrepancies include the impact of number of lymph node metastases for the indication for postmastectomy radiotherapy.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Breast-conserving surgery; Ductal carcinoma in situ; Guideline; Hypofractionation; Radiation oncology

Randomised, open-label, phase II study comparing the efficacy and the safety of cabazitaxel versus weekly paclitaxel given as neoadjuvant treatment in patients with operable triple-negative or luminal B/HER2-negative breast cancer (GENEVIEVE) - Kuemmel, Sherko; Paepke, Stefan; Huober, Jens; Schem, Christian; Untch, Michael; Blohmer, Jens Uwe; Eiermann, Wolfgang; Gerber, Bernd; Hanusch, Claus; Hilfrich, Joern; Jackisch, Christian; Schneeweiss, Andreas; et al. (European Journal of Cancer, 2017)
BACKGROUND: The GENEVIEVE study compared the pathological complete response (pCR) rate (ypT0/is ypN0/+) in patients with operable human epidermal growth factor receptor 2 (HER2)-negative breast cancer (BC) treated with either cabazitaxel or paclitaxel. METHODS: GENEVIEVE was a prospective, multicentre, randomised, open-label, phase II study comparing the efficacy and the safety of four 3-weekly cycles cabazitaxel versus 12 weeks of paclitaxel given as neoadjuvant treatment. Primary end-point was the pCR rate defined as the complete absence of invasive carcinoma on histological examination of the breast irrespective of lymph node involvement (ypT0/is, ypN0/+) after the taxane treatment. Patients could receive an anthracycline-based therapy thereafter. RESULTS: Overall, 333 patients were randomised and started treatment with 74.7% and 83.2% of patients completing treatment in the cabazitaxel and paclitaxel arms, respectively. Patients in cabazitaxel arm had a significantly lower pCR rate compared to the paclitaxel arm (1.2% versus 10.8%; p = 0.001). A total of 42 (25.3%) patients in the cabazitaxel arm and 17 (10.2%) in the paclitaxel arm had at least one serious adverse event (p < 0.001). Dose reductions were observed in 9.6% patients in the cabazitaxel arm compared to 11.4% in the paclitaxel arm (p = 0.721). Main reason for dose reductions was non-haematological toxicities in 3.0% versus 7.8% (p = 0.087), respectively. CONCLUSIONS: The GENEVIEVE study showed no short-term effect of cabazitaxel in triple-negative or luminal B/HER2-negative primary BC, while there seemed to be no differences in drug exposure and patient compliance between the two arms. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov NCT01779479.
EVALuna2:36185

Randomized, open-label, phase II study comparing the efficacy and the safety of cabazitaxel versus weekly paclitaxel given as neoadjuvant treatment in patients with operable triple negative or luminal B/HER2 normal breast cancer (GENEVIEVE) - Paepke, S.; Huober, J.; Sherko, K.; Eidtmann, H.; Untch, M.; Costa, S. Dan; Blohmer, J. U.; Eiermann, W.; Gerber, B.; Hanusch, C.; Hilfrich, J.; Jackisch, C.; et al. (2016)
EVALuna2:33541

RANK and RANKL Expression in Tumors of Patients with Early Breast Cancer - Behrens, Annika; Wurmthaler, Lena; Heindl, Felix; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hack, Carolin; Emons, Julius; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Rübner, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction The receptor activator of nuclear factor-κB (RANK) pathway was associated with the pathogenesis of breast cancer. Several studies attempted to link the RANK/RANKL pathway to prognosis; however, with inconsistent outcomes. We aimed to further contribute to the knowledge about RANK/RANKL as prognostic factors in breast cancer. Within this study, protein expression of RANK and its ligand, RANKL, in the tumor tissue was analyzed in association with disease-free survival (DFS) and overall survival (OS) in a study cohort of patients with early breast cancer. Patients and Methods 607 samples of female primary and early breast cancer patients from the Bavarian Breast Cancer Cases and Controls Study were analyzed to correlate the RANK and RANKL expression with DFS and OS. Therefore, expression was quantified using immunohistochemical staining of a tissue microarray. H-scores were determined with the cut-off value of 8.5 for RANK and 0 for RANKL expression, respectively. Results RANK and RANKL immunohistochemistry were assessed by H-score. Both biomarkers did not correlate (ρ = -0.04). According to molecular subtypes, triple-negative tumors and HER2-positive tumors showed a higher number of RANK-positive tumors (H-score ≥ 8.5), however, no subtype-specific expression of RANKL could be detected. Higher RANKL expression tended to correlate with a better prognosis. However, RANK and RANKL expression could not be identified as statistically significant prognostic factors within the study cohort. Conclusions Tumor-specific RANK and RANKL expressions are not applicable as prognostic factors for DFS and OS, but might be associated with subtype-specific breast cancer progression.
CRIS-Team Scopus Importer:2023-12-22
Keywords: breast cancer; immunohistochemistry; prognosis; RANK; RANKL

RANK Expression as an Independent Predictor for Response to Neoadjuvant Chemotherapy in Luminal-Like Breast Cancer: A Translational Insight from the GeparX Trial - Link, Theresa; Blohmer, Jens Uwe; Schmitt, Wolfgang D.; Kuhlmann, Jan Dominik; Just, Marianne; Untch, Michael; Stoetzer, Oliver J.; Fasching, Peter; Thill, Marc; Reinisch, Mattea; Schneeweiss, Andreas; Wimberger, Pauline; et al. (Clinical Cancer Research, 2023)
Purpose: The GeparX study investigated whether denosumab as add-on treatment to nab-paclitaxel–based neoadjuvant chemotherapy (NACT) with two different schedules (125 mg/m2 weekly vs. day 1, 8 every 22 days) may increase pathologic complete response (pCR) rate. The addition of denosumab to NACT did not improve pCR rates as recently published. In this study, we investigated whether receptor activator of nuclear factor-kappa B (RANK) expression, as part of the denosumab target pathway: (i) may retrospectively identify a subgroup of patients with additional clinical benefit of denosumab or (ii) may predict response to nab-paclitaxel NACT. Experimental Design: RANK protein was IHC-stained on pre-therapeutic core biopsies from patients of the GeparX study (n ¼ 667) with the antibody RANK/Envision System HRP (DAB) and was analyzed for the percentage of membranous RANK tumor cell staining (>5% RANKhigh vs. ≤5% RANKlow). Results: We could not identify any patient subgroup with differential response under denosumab add-on treatment in patients with RANKhigh expression [139/667, 20.8%; OR, 0.86; 95% confidence interval (CI), 0.44–1.68; P ¼ 0.667] or RANKlow expression (528/667 (79.2%) OR, 1.10; 95% CI, 0.78–1.56; P ¼ 0.589; Pinteraction ¼ 0.528). However, the pCR rate was higher in the RANKhigh subgroup compared with RANKlow (50% vs. 39%; OR, 1.52; 95% CI, 1.04–2.21; P ¼ 0.037). RANK expression constituted an independent predictor of response to NACT frequently in patients with luminal-like subtype (HRþ/HER2−; OR, 2.98; 95% CI, 1.30–6.79; P ¼ 0.010). No predictive value of RANK expression among the different nab-paclitaxel regimens was observed. Conclusion: We report RANK expression to be an independent predictive biomarker for response to NACT in patients with luminal-like breast cancer.
CRIS-Team Scopus Importer:2023-12-08

RANKL and OPG and their influence on breast volume changes during pregnancy in healthy women - Wunderle, Marius; Rübner, Matthias; Häberle, Lothar; Schwenke, Eva; Hack, Carolin; Bayer, Christian M.; Koch, Martin; Schwitulla, Judith; Schulz-Wendtland, Rüdiger; Kozieradzki, Ivona; Lux, Michael P.; Beckmann, Matthias; et al. (Scientific Reports, 2020)
Breast cancer risk is reduced by number of pregnancies and breastfeeding duration, however studies of breast changes during or after pregnancy are rare. Breast volume changes - although not linked to breast cancer risk - might be an interesting phenotype in this context for correlative studies, as changes of breast volume vary between pregnant women. Serum receptor activator of nuclear factor kappa B ligand (RANKL) and its antagonist osteoprotegerin (OPG) were measured prospectively before gestational week 12, and three-dimensional breast volume assessments were performed. A linear regression model including breast volume at the start of pregnancy, RANKL, OPG, and other factors was used to predict breast volume at term. The mean breast volume was 413 mL at gestational week 12, increasing by a mean of 99 mL up to gestational week 40. In addition to body mass index and breast volume at the beginning of pregnancy, RANKL and OPG appeared to influence breast volume with a mean increase by 32 mL (P = 0.04) and a mean reduction by 27 mL (P = 0.04), respectively. Linking the RANKL/RANK/OPG pathway with breast volume changes supports further studies aiming at analysing breast changes during pregnancy with regard to breast cancer risk.
CRIS-Team Scopus Importer:2020-03-31

Rare germline copy number variants (CNVs) and breast cancer risk - Dennis, Joe; Tyrer, Jonathan P.; Walker, Logan C.; Michailidou, Kyriaki; Dorling, Leila; Bolla, Manjeet K.; Wang, Qin; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Arndt, Volker; et al. (Communications Biology, 2022)
Germline copy number variants (CNVs) are pervasive in the human genome but potential disease associations with rare CNVs have not been comprehensively assessed in large datasets. We analysed rare CNVs in genes and non-coding regions for 86,788 breast cancer cases and 76,122 controls of European ancestry with genome-wide array data. Gene burden tests detected the strongest association for deletions in BRCA1 (P = 3.7E-18). Nine other genes were associated with a p-value < 0.01 including known susceptibility genes CHEK2 (P = 0.0008), ATM (P = 0.002) and BRCA2 (P = 0.008). Outside the known genes we detected associations with p-values < 0.001 for either overall or subtype-specific breast cancer at nine deletion regions and four duplication regions. Three of the deletion regions were in established common susceptibility loci. To the best of our knowledge, this is the first genome-wide analysis of rare CNVs in a large breast cancer case-control dataset. We detected associations with exonic deletions in established breast cancer susceptibility genes. We also detected suggestive associations with non-coding CNVs in known and novel loci with large effects sizes. Larger sample sizes will be required to reach robust levels of statistical significance.
CRIS-Team Scopus Importer:2022-02-04

Rationale and trial design of NATALEE: a Phase III trial of adjuvant ribociclib + endocrine therapy versus endocrine therapy alone in patients with HR+/HER2− early breast cancer - Slamon, Dennis J.; Fasching, Peter; Hurvitz, Sara; Chia, Stephen; Crown, John; Martín, Miguel; Barrios, Carlos H.; Bardia, Aditya; Im, Seock Ah; Yardley, Denise A.; Untch, Michael; Huang, Chiun Sheng; et al. (Therapeutic Advances in Medical Oncology, 2023)
Background: Ribociclib has demonstrated a statistically significant overall survival benefit in pre- and postmenopausal patients with hormone receptor positive/human epidermal growth factor receptor 2 negative (HR+/HER2−) advanced breast cancer. New Adjuvant Trial with Ribociclib [LEE011] (NATALEE) is a trial evaluating the efficacy and safety of adjuvant ribociclib plus endocrine therapy (ET) versus ET alone in patients with HR+/HER2− early nonmetastatic breast cancer (EBC). Methods/design: NATALEE is a multicenter, randomized, open-label, Phase III trial in patients with HR+/HER2− EBC. Eligible patients include women, regardless of menopausal status, and men aged ⩾18 years. Select patients with stage IIA, stage IIB, or stage III disease (per the anatomic classification in the AJCC Cancer Staging Manual, 8th edition) with an initial diagnosis ⩽18 months prior to randomization are eligible. Patients receiving standard (neo)adjuvant ET are eligible if treatment was initiated ⩽12 months before randomization. Patients undergo 1:1 randomization to ribociclib 400 mg/day (3 weeks on/1 week off) +ET (letrozole 2.5 mg/day or anastrozole 1 mg/day [investigator’s discretion] plus goserelin [men or premenopausal women]) or ET alone. Ribociclib treatment duration is 36 months; ET treatment duration is ⩾60 months. The primary end point is invasive disease-free survival. Discussion: The 36-month treatment duration of ribociclib in NATALEE is extended compared with that in other adjuvant cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitor trials and is intended to maximize efficacy due to longer duration of CDK4/6 inhibition. Compared with the 600-mg/day dose used in advanced breast cancer, the reduced ribociclib dose used in NATALEE may improve tolerability while maintaining efficacy. NATALEE includes the broadest population of patients with HR+/HER2− EBC of any Phase III trial currently evaluating adjuvant CDK4/6 inhibitor treatment. Trial registration: ClinicalTrials.gov identifier: NCT03701334 (https://clinicaltrials.gov/ct2/show/NCT03701334)
CRIS-Team Scopus Importer:2023-06-30
Keywords: adjuvant therapy; CDK4/6 inhibitors; HR+/HER2– early breast cancer; NATALEE; ribociclib

Real-world effectiveness of ribociclib 1 aromatase inhibitor, or endocrine monotherapy, or chemotherapy as first-line treatment in postmenopausal women with HR-positive, HER2-negative locally advanced or metastatic breast cancer: The RIBANNA study - Fasching, Peter; Decker, T.; Guderian, G.; Heim, J.; Jackisch, C.; Lueck, H-J.; Lueftner, D.; Marme, F.; Reimer, T.; Woeckel, A. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Real-world efficacy of ribociclib plus aromatase inhibitor/fulvestrant, or endocrine monotherapy, or chemotherapy as first-line treatment in women with HR-positive, HER2-negative locally advanced or metastatic breast cancer: Third interim analysis from the RIBANNA study - Wockel, Achim; Brucker, Cosima; Decker, Thomas; Falbrede, Jorg; Forstbauer, Helmut; Gohler, Thomas; Hoffmann, Oliver; Jackisch, Christian; Janssen, Jan; Kohler, Andreas; Ludtke-Heckenkamp, Kerstin; Luftner, Diana; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Reconstructing tumor history in breast cancer: signatures of mutational processes and response to neoadjuvant chemotherapy☆ - Denkert, C.; Untch, M.; Benz, S.; Schneeweiss, A.; Weber, K. E.; Schmatloch, S.; Jackisch, C.; Sinn, H. P.; Golovato, J.; Karn, T.; Marmé, F.; Link, T.; et al. (Annals of Oncology, 2021)
Background: Different endogenous and exogenous mutational processes act over the evolutionary history of a malignant tumor, driven by abnormal DNA editing, mutagens or age-related DNA alterations, among others, to generate the specific mutational landscape of each individual tumor. The signatures of these mutational processes can be identified in large genomic datasets. We investigated the hypothesis that genomic patterns of mutational signatures are associated with the clinical behavior of breast cancer, in particular chemotherapy response and survival, with a particular focus on therapy-resistant disease. Patients and methods: Whole exome sequencing was carried out in 405 pretherapeutic samples from the prospective neoadjuvant multicenter GeparSepto study. We analyzed 11 mutational signatures including biological processes such as APOBEC-mutagenesis, homologous recombination deficiency (HRD), mismatch repair deficiency and also age-related or tobacco-induced alterations. Results: Different subgroups of breast carcinomas were defined mainly by differences in HRD-related and APOBEC-related mutational signatures and significant differences between hormone-receptor (HR)-negative and HR-positive tumors as well as correlations with age, Ki-67 and immunological parameters were observed. We could identify mutational processes that were linked to increased pathological complete response rates to neoadjuvant chemotherapy with high significance. In univariate analyses for HR-positive tumors signatures, S3 (HRD, P < 0.001) and S13 (APOBEC, P = 0.001) as well as exonic mutation rate (P = 0.002) were significantly correlated with increased pathological complete response rates. The signatures S3 (HRD, P = 0.006) and S4 (tobacco, P = 0.011) were prognostic for reduced disease-free survival of patients with chemotherapy-resistant tumors. Conclusion: The results of this investigation suggest that the clinical behavior of a tumor, in particular, response to neoadjuvant chemotherapy and disease-free survival of therapy-resistant tumors, could be predicted by the composition of mutational signatures as an indicator of the individual genomic history of a tumor. After additional validations, mutational signatures might be used to identify tumors with an increased response rate to neoadjuvant chemotherapy and to define therapy-resistant subgroups for future therapeutic interventions.
CRIS-Team Scopus Importer:2021-03-05
Keywords: breast cancer; mutational signatures; neoadjuvant therapy; prognosis; response; whole exome sequencing

Reduction of Serious Adverse Events (SAE) under palbociclib treatment in patients using an interactive eHealth system - Schmidt, M.; Degenhardt, T.; Fasching, Peter; Lueftner, D.; Mueller, V.; Thomssen, C.; Schem, C.; Witzel, I.; Decker, T.; Tesch, H.; Kuemmel, S.; Uleer, C.; et al. (EUROPEAN JOURNAL OF CANCER, 2020)
CRIS-Team WoS Importer:2020-11-13

Reduction of Serious Adverse Events (SAE) under palbociclib treatment in patients using an interactive eHealth system - Schmidt, M.; Degenhardt, T.; Fasching, Peter; Lüftner, D.; Müller, V.; Thomssen, C.; Schem, C.; Witzel, I.; Decker, T.; Tesch, H.; Kümmel, S.; Uleer, C.; et al. (European Journal of Cancer, 2020)
CRIS-Team Scopus Importer:2020-10-16

Refined cut-off for TP53 immunohistochemistry improves prediction of TP53 mutation status in ovarian mucinous tumors: implications for outcome analyses - Kang, Eun Young; Cheasley, Dane; LePage, Cecile; Wakefield, Matthew J.; da Cunha Torres, Michelle; Rowley, Simone; Salazar, Carolina; Xing, Zhongyue; Allan, Prue; Bowtell, David D.L.; Mes-Masson, Anne Marie; Provencher, Diane M.; et al. (Modern Pathology, 2021)
TP53 mutations are implicated in the progression of mucinous borderline tumors (MBOT) to mucinous ovarian carcinomas (MOC). Optimized immunohistochemistry (IHC) for TP53 has been established as a proxy for the TP53 mutation status in other ovarian tumor types. We aimed to confirm the ability of TP53 IHC to predict TP53 mutation status in ovarian mucinous tumors and to evaluate the association of TP53 mutation status with survival among patients with MBOT and MOC. Tumor tissue from an initial cohort of 113 women with MBOT/MOC was stained with optimized IHC for TP53 using tissue microarrays (75.2%) or full sections (24.8%) and interpreted using established criteria as normal or abnormal (overexpression, complete absence, or cytoplasmic). Cases were considered concordant if abnormal IHC staining predicted deleterious TP53 mutations. Discordant tissue microarray cases were re-evaluated on full sections and interpretational criteria were refined. The initial cohort was expanded to a total of 165 MBOT and 424 MOC for the examination of the association of survival with TP53 mutation status, assessed either by TP53 IHC and/or sequencing. Initially, 82/113 (72.6%) cases were concordant using the established criteria. Refined criteria for overexpression to account for intratumoral heterogeneity and terminal differentiation improved concordance to 93.8% (106/113). In the expanded cohort, 19.4% (32/165) of MBOT showed evidence for TP53 mutation and this was associated with a higher risk of recurrence, disease-specific death, and all-cause mortality (overall survival: HR = 4.6, 95% CI 1.5-14.3, p = 0.0087). Within MOC, 61.1% (259/424) harbored a TP53 mutation, but this was not associated with survival (overall survival, p = 0.77). TP53 IHC is an accurate proxy for TP53 mutation status with refined interpretation criteria accounting for intratumoral heterogeneity and terminal differentiation in ovarian mucinous tumors. TP53 mutation status is an important biomarker to identify MBOT with a higher risk of mortality.
CRIS-Team Scopus Importer:2021-02-05

Relevance of tumour-infiltrating lymphocytes, PD-1 and PD-L1 in patients with high-risk, nodal-metastasised breast cancer of the German Adjuvant Intergroup Node–positive study - Noske, Aurelia; Möbus, Volker; Weber, Karsten; Schmatloch, Sabine; Weichert, Wilko; Köhne, Claus Henning; Solbach, Christine; Ingold Heppner, Barbara; Steiger, Katja; Müller, Volkmar; Fasching, Peter; Karn, Thomas; et al. (European Journal of Cancer, 2019)
Background: Immune cell infiltration in breast cancer is important for the patient's prognosis and response to systemic therapies including immunotherapy. We sought to investigate the prevalence of tumour-infiltrating lymphocytes (TILs)and their association with immune checkpoints such as programmed cell death 1 (PD-1)and programmed cell death ligand 1 (PD-L1)in high-risk, node-positive breast cancer of the adjuvant German Adjuvant Intergroup Node–positive (GAIN-1)trial. Patients and methods: We evaluated TILs by haematoxylin and eosin staining and PD-1 and PD-L1 (SP263 assay)expression by immunohistochemistry in 1318 formalin-fixed, paraffin-embedded breast carcinomas. The association of TILs with PD-1, PD-L1, molecular intrinsic subtypes, outcome and therapy regimens (dose-dense [dd]epirubicin, paclitaxel and cyclophosphamide [EPC]and dd epirubicin, cyclophosphamide, paclitaxel and capecitabine [EC-PwX])was statistically tested. Results: Overall TILs density was significantly associated with the expression of PD-1 and PD-L1 in immune cells (each p < 0.0001)and PD-L1 in tumour cells (p = 0.0051). TILs were more common in triple-negative breast cancer (TNBC)and human epidermal growth factor receptor 2 (HER2)HER2-positive tumours (each p < 0.0001). On multivariate Cox regression analyses, patients with breast cancer without TILs had an unfavourable disease-free survival (DFS)in the EPC arm compared with the EC-PwX arm (hazard ratio [HR]= 0.69 [0.44–1.06], p = 0.0915); but no differences were seen in tumours with TILs (HR = 1.24 [0.92–1.67], p = 0.1566, interaction p = 0.0336). PD-1–positive immune cells in TNBC were associated with a significantly better DFS (HR = 0.50 [0.25–0.99], p = 0.0457). PD-L1 expression had no impact on patient outcome. Conclusions: TILs predict the benefit of intensified ddEPC compared with ddEC-PwX therapy in node-positive, high-risk breast cancer. TILs, PD-1 and PD-L1 are linked to each other indicating tumour immunogenicity. Moreover, PD-1–positive immune cells have a positive prognostic impact in TNBC. Clinical trial: NCT00196872.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Adjuvant; Breast cancer; PD-1; PD-L1; Prognosis; Therapy prediction; TILs

Reliability of an e-PRO Tool of EORTC QLQ-C30 for Measurement of Health-Related Quality of Life in Patients With Breast Cancer: Prospective Randomized Trial - Wallwiener, Markus; Matthies, Lina; Simoes, Elisabeth; Keilmann, Lucia; Hartkopf, Andreas D.; Sokolov, Alexander N.; Walter, Christina B.; Sickenberger, Nina; Wallwiener, Stephanie; Feisst, Manuel; Gaß, Paul; Fasching, Peter; et al. (Journal of Medical Internet Research, 2017)
BACKGROUND: Breast cancer represents the most common malignant disease in women worldwide. As currently systematic palliative treatment only has a limited effect on survival rates, the concept of health-related quality of life (HRQoL) is gaining more and more importance in the therapy setting of metastatic breast cancer. One of the major patient-reported outcomes (PROs) for measuring HRQoL in patients with breast cancer is provided by the European Organization for Research and Treatment of Cancer (EORTC). Currently, paper-based surveys still predominate, as only a few reliable and validated electronic-based questionnaires are available. Facing the possibilities associated with evolving digitalization in medicine, validation of electronic versions of well-established PRO is essential in order to contribute to comprehensive and holistic oncological care and to ensure high quality in cancer research. OBJECTIVE: The aim of this study was to analyze the reliability of a tablet-based measuring application for EORTC QLQ-C30 in German language in patients with adjuvant and (curative) metastatic breast cancer. METHODS: Paper- and tablet-based questionnaires were completed by a total of 106 female patients with adjuvant and metastatic breast cancer recruited as part of the e-PROCOM study. All patients were required to complete the electronic- (e-PRO) and paper-based versions of the HRQoL EORTC QLQ-C30 questionnaire. A frequency analysis was performed to determine descriptive sociodemographic characteristics. Both dimensions of reliability (parallel forms reliability [Wilcoxon test] and test of internal consistency [Spearman rho and agreement rates for single items, Pearson correlation and Kendall tau for each scale]) were analyzed. RESULTS: High correlations were shown for both dimensions of reliability (parallel forms reliability and internal consistency) in the patient's response behavior between paper- and electronic-based questionnaires. Regarding the test of parallel forms reliability, no significant differences were found in 27 of 30 single items and in 14 of 15 scales, whereas a statistically significant correlation in the test of consistency was found in all 30 single items and all 15 scales. CONCLUSIONS: The evaluated e-PRO version of the EORTC QLQ-C30 is reliable for patients with both adjuvant and metastatic breast cancer, showing a high correlation in almost all questions (and in many scales). Thus, we conclude that the validated paper-based PRO assessment and the e-PRO tool are equally valid. However, the reliability should also be analyzed in other prospective trials to ensure that usability is reliable in all patient groups. TRIAL REGISTRATION: ClinicalTrials.gov NCT03132506; https://clinicaltrials.gov/ct2/show/NCT03132506 (Archived by WebCite at http://www.webcitation.org/6tRcgQuou).
EVALuna2:36167

Replication of Epigenetic Postpartum Depression Biomarkers and Variation with Hormone Levels - Osborne, Lauren; Clive, Makena; Kimmel, Mary; Gispen, Fiona; Guintivano, Jerry; Brown, Tori; Cox, Olivia; Judy, Jennifer; Meilman, Samantha; Braier, Aviva; Beckmann, Matthias; Kornhuber, Johannes; et al. (Neuropsychopharmacology, 2016)
DNA methylation variation at HP1BP3 and TTC9B is modified by estrogen exposure in the rodent hippocampus and was previously shown to be prospectively predictive of postpartum depression (PPD) when modeled in antenatal blood. The objective of this study was to replicate the predictive efficacy of the previously established model in women with and without a previous psychiatric diagnosis and to understand the effects of changing hormone levels on PPD biomarker loci. Using a statistical model trained on DNA methylation data from N=51 high-risk women, we prospectively predicted PPD status in an independent N=51 women using first trimester antenatal gene expression levels of HP1BP3 and TTC9B, with an area under the receiver operator characteristic curve (AUC) of 0.81 (95% CI: 0.69-0.92, p<5 × 10(-4)). Modeling DNA methylation of these genes in N=240 women without a previous psychiatric diagnosis resulted in a cross-sectional prediction of PPD status with an AUC of 0.81 (95% CI: 0.68-0.93, p=0.01). TTC9B and HP1BP3 DNA methylation at early antenatal time points showed moderate evidence for association to the change in estradiol and allopregnanolone over the course of pregnancy, suggesting that epigenetic variation at these loci may be important for mediating hormonal sensitivity. In addition both loci showed PPD-specific trajectories with age, possibly mediated by age-associated hormonal changes. The data add to the growing body of evidence suggesting that PPD is mediated by differential gene expression and epigenetic sensitivity to pregnancy hormones and that modeling proxies of this sensitivity enable accurate prediction of PPD.
EVALuna2:23791

Reproducibility of mRNA-Based Testing of ESR1, PGR, ERBB2, and MKI67 Expression in Invasive Breast Cancer-A Europe-Wide External Quality Assessment - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Rübner, Matthias; Stöhr, Robert; Beckmann, Matthias; Zentgraf, Miriam; Popp, Verena; Weidler, Jodi; Simon, Iris; Becker, Steffi; Hübner, Hanna; et al. (Cancers, 2021)
Simple Summary Four biomarkers [estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2], are used to stratify breast cancer (BC) into subtypes predictive of therapy response. In a Europe-wide external quality assessment, we compared performance of an mRNA-based method [Xpert(R) Breast Cancer STRAT4 (CE-IVD)] for determining ESR1, PGR, ERBB2, and MKI67 expression against the gold standard [immunohistochemistry (IHC)/HER2 in situ hybridization (ISH)]. The coordinating center (CC) and five European laboratories tested ten breast cancer samples. STRAT4 binary (positive or negative) results of each marker were compared with the gold standard. ESR1 and ERBB2 mRNA results were concordant with IHC/ISH in all single analyses. In contrast, PGR and MKI67 results were discordant in a few cases, which had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. STRAT4 assay may be a reproducible method. However, cases with expression values close to cut-offs should be carefully reviewed. Estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2 immunohistochemistry (IHC) together with HER2 in situ hybridization (ISH) are utilized to classify invasive breast cancer (IBC) into predictive molecular subtypes. As IHC evaluation may be hampered by analytical errors, gene expression assays could offer a reliable alternative. In this first Europe-wide external quality assessment (EQA) study, we investigated performance of mRNA-based Xpert(R) Breast Cancer STRAT4 (CE-IVD) in five European laboratories. The cohort comprised ten pre-therapy IBC core biopsies diagnosed in the coordinating center (CC). STRAT4 binary (positive or negative) mRNA results of each marker (ESR1, PGR, ERBB2, MKI67) were compared with the gold standard IHC/ISH performed by the CC. Sensitivity, specificity, and accuracy of ESR1 and ERBB2 mRNA were 100% for all samples. In contrast, PGR expression was falsely negative for one case by two sites and MKI67 falsely negative for two cases (respectively by four and one sites). These cases had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. Our EQA shows that STRAT4 mRNA assay may be a reproducible method to evaluate ER, PgR, HER2, and Ki-67 status. However, cases with expression values close to assay cut-offs should be carefully reviewed.
CRIS-Team WoS Importer:2021-10-08

Reproductive profiles and risk of breast cancer subtypes: a multi-center case-only study - Brouckaert, Olivier; Rudolph, Anja; Laenen, Annouschka; Keeman, Renske; Bolla, Manjeet K.; Wang, Qin; Soubry, Adelheid; Wildiers, Hans; Andrulis, Irene L.; Arndt, Volker; Beckmann, Matthias; Benitez, Javier; et al. (Breast Cancer Research, 2017)
BACKGROUND: Previous studies have shown that reproductive factors are differentially associated with breast cancer (BC) risk by subtypes. The aim of this study was to investigate associations between reproductive factors and BC subtypes, and whether these vary by age at diagnosis. METHODS: We used pooled data on tumor markers (estrogen and progesterone receptor, human epidermal growth factor receptor-2 (HER2)) and reproductive risk factors (parity, age at first full-time pregnancy (FFTP) and age at menarche) from 28,095 patients with invasive BC from 34 studies participating in the Breast Cancer Association Consortium (BCAC). In a case-only analysis, we used logistic regression to assess associations between reproductive factors and BC subtype compared to luminal A tumors as a reference. The interaction between age and parity in BC subtype risk was also tested, across all ages and, because age was modeled non-linearly, specifically at ages 35, 55 and 75 years. RESULTS: Parous women were more likely to be diagnosed with triple negative BC (TNBC) than with luminal A BC, irrespective of age (OR for parity = 1.38, 95% CI 1.16-1.65, p = 0.0004; p for interaction with age = 0.076). Parous women were also more likely to be diagnosed with luminal and non-luminal HER2-like BCs and this effect was slightly more pronounced at an early age (p for interaction with age = 0.037 and 0.030, respectively). For instance, women diagnosed at age 35 were 1.48 (CI 1.01-2.16) more likely to have luminal HER2-like BC than luminal A BC, while this association was not significant at age 75 (OR = 0.72, CI 0.45-1.14). While age at menarche was not significantly associated with BC subtype, increasing age at FFTP was non-linearly associated with TNBC relative to luminal A BC. An age at FFTP of 25 versus 20 years lowered the risk for TNBC (OR = 0.78, CI 0.70-0.88, p < 0.0001), but this effect was not apparent at a later FFTP. CONCLUSIONS: Our main findings suggest that parity is associated with TNBC across all ages at BC diagnosis, whereas the association with luminal HER2-like BC was present only for early onset BC.
EVALuna2:36119

Response and prognosis after neoadjuvant chemotherapy in 1,051 patients with infiltrating lobular breast carcinoma - Loibl, Sibylle; Volz, Cristina; Mau, Christine; Blohmer, Jens-Uwe; Costa, Serban D.; Eidtmann, Holger; Fasching, Peter; Gerber, Bernd; Hanusch, Claus; Jackisch, Christian; Kuemmel, Sherko; Huober, Jens; et al. (Breast Cancer Research and Treatment, 2014)
Invasive lobular carcinomas (ILC) show better clinical behaviour compared with other histological types, but significantly lower pathological complete response (pCR) rates after neoadjuvant chemotherapy (NACT). We investigated whether factors influencing pCR rate in ILC after NACT can be identified and whether clinical outcome is different. 9,020 breast cancer patients from nine German neoadjuvant trials with known histological type were pooled. 11.7 % of tumours were ILC. Endpoints were: pCR rate, surgery type and survival. ILC was associated with older age, larger tumour size, lymph node negativity, lower grade and positive hormone-receptor-status (HR). Patients with ILC achieved a significantly lower pCR rate compared with non-ILC patients (6.2 vs. 17.4 %, P < 0.001). The pCR rate was 4.2 % in ILC/HR+/G1-2, 7.0 % in ILC with either HR- or G3, and 17.8 % in ILC/HR-/G3. Mastectomy rate was higher in ILC compared with non-ILC patients irrespective of response to NACT (pCR: 27.4 vs. 16.6 %, P = 0.037 and non-pCR: 41.8 % vs. 31.5 %, P < 0.0001). Age and HR independently predicted pCR in ILC. In ILC patients, pCR did not predict distant disease free (DDFS) and loco-regional disease free survival (LRFS), but overall survival (OS). Non-pCR patients with ILC had significantly better DDFS (P = 0.018), LRFS (P < 0.0001) and OS (P = 0.044) compared with non-ILC patients. Patients with ILC had a low chance of obtaining a pCR and this is not well correlated with further outcome. The mastectomy rate was considerably high in ILC patients even after obtaining a pCR. We, therefore, suggest to offer NACT mainly to ILC patients with HR-negative tumours.
EVALuna2:17507

Response to "screening depression during and after pregnancy using the EPDS" - Hein, Alexander; Fasching, Peter; Goecke, Tamme W. (Archives of Gynecology and Obstetrics, 2014)
EVALuna2:17514

Results from CONTESSA: A phase 3 study of tesetaxel plus a reduced dose of capecitabine versus capecitabine alone in patients with HER2-, hormone receptor plus (HR plus ) metastatic breast cancer (MBC) who have previously received a taxane - O'Shaughnessy, Joyce; Schwartzberg, Lee; Piccart, Martine; Rugo, Hope S.; Yardley, Denise A.; Cortes, Javier; Untch, Michael; Harbeck, Nadia; Wright, Gail S.; Bondarenko, Igor; Glaspy, John; Nowecki, Zbigniew; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Results of TRIO-14, a phase II, multicenter, randomized, placebo-controlled trial of carboplatin-paclitaxel versus carboplatin-paclitaxel-ganitumab in newly diagnosed epithelial ovarian cancer - Konecny, G. E.; Hendrickson, A. E.Wahner; Davidson, T. M.; Winterhoff, B. J.; Ma, S.; Mahner, S.; Sehouli, J.; Fasching, Peter; Feisel-Schwickardi, G.; Poelcher, M.; Roman, L. D.; Rody, A.; et al. (Gynecologic Oncology, 2021)
Purpose: Insulin-like growth factor (IGF) signaling is implicated in pathogenesis and chemotherapy resistance of epithelial ovarian cancer (EOC). We explored efficacy and safety of adding ganitumab, a monoclonal antibody targeting IGF-1R, to carboplatin/paclitaxel (CP) chemotherapy in patients with primary EOC. Design: Patients were randomly assigned to receive CP/ganitumab (18 mg/kg q3w) or CP/placebo for 6 cycles followed by 6 cycles of single agent ganitumab/placebo maintenance therapy as front-line therapy. Primary endpoint was progression free survival. Secondary endpoints were time to progression and overall survival. Pretreatment samples were prospectively collected for retrospective biomarker analyses. Results: 170 patients enrolled. 165 patients assessable for toxicity. Median PFS was 15.7 months with CP/ganitumab and 16.7 months with CP/placebo (HR 1.23; 95% CI 0.82–1.83, P = 0.313). All grade neutropenia (84.1% vs 71.4%), thrombocytopenia (75.3% vs 57.1%) and hyperglycemia (15.9% vs 2.6%) were more common in the ganitumab group compared to the placebo group. Ganitumab/placebo related serious adverse events were reported in 26.1% of the patients with ganitumab and in 6.5% with placebo. Non-progression related fatal events were more common with ganitumab (5 versus 2 patients). The ganitumab group experienced more dose delays which resulted in lower relative dose intensity of chemotherapy in the experimental group. In an exploratory model IGFBP2 expression was predictive of ganitumab response (treatment interaction; PFS, P = 0.03; OS, P = 0.01). Conclusion: Addition of ganitumab to CP chemotherapy in primary EOC did not improve PFS. Our results do not support further study of ganitumab in unselected EOC patients.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Ganitumab; IGFR1 inhibitor; Insulin-like growth factor; Ovarian cancer; Targeted therapy

Return of individual genomic research results within the PRAEGNANT multicenter registry study - Hübner, Hanna; Rübner, Matthias; Kurbacher, Christian; Hadji, Peyman; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Uhrig, Sabrina; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; et al. (Breast Cancer Research and Treatment, 2022)
Purpose: The PRAEGNANT study is a registry study for metastatic breast cancer patients, focusing on biomarker detection. Recently, within this study, genetic alterations in 37 breast cancer predisposition genes were analyzed and genetic findings were detected for 396 participants. The aim of this project was to return genetic results to the physicians and to analyze actions taken (e.g., disclosure of results to patients, validation of results, clinical impact, and impact on the patient’s quality of life) using a questionnaire. Methods: 235 questionnaires were sent out to the study centers, with each questionnaire representing one patient with a genetic finding. The questionnaire consisted of twelve questions in the German language, referring to the disclosure of results, validation of test results, and their impact on treatment decisions and on the patient’s quality of life. Results: 135 (57.5%) questionnaires were completed. Of these, 46 (34.1%) stated that results were returned to the patients. In 80.0% (N = 36) of cases where results were returned, the patient had not been aware of the finding previously. For 27 patients (64.3%), genetic findings had not been validated beforehand. All validation procedures (N = 15) were covered by the patients’ health insurance. For 11 (25.0%) patients, physicians reported that the research results influenced current or future decision-making on treatment, and for 37.8% (N = 17) the results influenced whether family members will be genetically tested. Conclusion: This study provides novel insights into the return of research results and into clinical and personal benefits of disclosure of genetic findings within a German registry.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Breast cancer; Genetic testing; Incidental findings; Research results; Return of results

Ribecca - a phase 3b, multi-center, open label study for women with estrogen receptor positive, locally advanced or metastatic breast cancer treated with ribociclib (lee011) in combination with letrozole: Final results - Reinisch, Mattea; Nusch, Arndt; Decker, Thomas; Hartkopf, Andreas; Heinrich, Bernhard J.; Kurbacher, Christian M.; Fuchs, Roswitha; Tesch, Hans; Krabisch, Petra; Brucker, Sara Y.; Fehm, Tanja; Janni, Wolfgang; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Ribociclib plus Endocrine Therapy in Early Breast Cancer - Slamon, Dennis; Lipatov, Oleg; Nowecki, Zbigniew; McAndrew, Nicholas; Kukielka-Budny, Bozena; Stroyakovskiy, Daniil; Yardley, Denise A.; Huang, Chiun Sheng; Fasching, Peter; Crown, John; Bardia, Aditya; Chia, Stephen; et al. (New England Journal of Medicine, 2024)
Background Ribociclib has been shown to have a significant overall survival benefit in patients with hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer. Whether this benefit in advanced breast cancer extends to early breast cancer is unclear. Methods In this international, open-label, randomized, phase 3 trial, we randomly assigned patients with HR-positive, HER2-negative early breast cancer in a 1:1 ratio to receive ribociclib (at a dose of 400 mg per day for 3 weeks, followed by 1 week off, for 3 years) plus a nonsteroidal aromatase inhibitor (NSAI; letrozole at a dose of 2.5 mg per day or anastrozole at a dose of 1 mg per day for ≥5 years) or an NSAI alone. Premenopausal women and men also received goserelin every 28 days. Eligible patients had anatomical stage II or III breast cancer. Here we report the results of a prespecified interim analysis of invasive disease-free survival, the primary end point; other efficacy and safety results are also reported. Invasive disease-free survival was evaluated with the use of the Kaplan-Meier method. The statistical comparison was made with the use of a stratified log-rank test, with a protocol-specified stopping boundary of a one-sided P-value threshold of 0.0128 for superior efficacy. Results As of the data-cutoff date for this prespecified interim analysis (January 11, 2023), a total of 426 patients had had invasive disease, recurrence, or death. A significant invasive disease-free survival benefit was seen with ribociclib plus an NSAI as compared with an NSAI alone. At 3 years, invasive disease-free survival was 90.4% with ribociclib plus an NSAI and 87.1% with an NSAI alone (hazard ratio for invasive disease, recurrence, or death, 0.75; 95% confidence interval, 0.62 to 0.91; P=0.003). Secondary end points - distant disease-free survival and recurrence-free survival - also favored ribociclib plus an NSAI. The 3-year regimen of ribociclib at a 400-mg starting dose plus an NSAI was not associated with any new safety signals. Conclusions Ribociclib plus an NSAI significantly improved invasive disease-free survival among patients with HR-positive, HER2-negative stage II or III early breast cancer. (Funded by Novartis; NATALEE ClinicalTrials.gov number, NCT03701334.)
CRIS-Team Scopus Importer:2024-04-12
Keywords: Breast Cancer; Hematology/Oncology; Treatments in Oncology

Ribociclib plus fulvestrant for advanced breast cancer: Health-related quality-of-life analyses from the MONALEESA-3 study - Fasching, Peter; Beck, J. Thaddeus; Chan, Arlene; De Laurentiis, Michele; Esteva, Francisco J.; Jerusalem, Guy; Neven, Patrick; Pivot, Xavier; Bianchi, Giulia V.; Martin, Miguel; Chandiwana, David; Lanoue, Brad; et al. (BREAST, 2020)
Purpose: In the MONALEESA-3 Phase III trial of patients with hormone receptor–positive human epidermal growth factor receptor–negative advanced breast cancer, ribociclib plus fulvestrant significantly improved progression-free survival (PFS) and overall survival (OS). Here, we present patient-reported outcomes from the trial, including health-related quality of life (HRQOL). Methods: Patients were randomized (2:1) to receive ribociclib plus fulvestrant or placebo plus fulvestrant. Time to definitive 10% deterioration (TTD) from baseline in HRQOL (global health status [GHS] from the EORTC QLQ-C30 questionnaire) and pain (BPI-SF questionnaire) were assessed using Kaplan-Meier estimates; a stratified Cox regression model was used to estimate the hazard ratio (HR) and 95% CIs. Results: Deterioration ≥10% in the EORTC-QLQ-C30 GHS was observed in 33% of patients in the ribociclib group vs 34% of patients in the placebo (reference) group (HR for TTD ≥ 10% = 0.81 [95% CI, 0.62–1.1]). Similar findings were noted for TTD ≥5% (HR = 0.79 [95% CI, 0.61–1.0]) and TTD ≥15% (HR = 0.81 [95% CI, 0.60–1.08]). TTD ≥10% in emotional functioning (HR = 0.76 [95% CI, 0.57–1.01]) trended in favor of the ribociclib group, whereas results for fatigue and pain were similar between arms. TTD ≥10% in BPI-SF pain severity index score (HR = 0.77 [95% CI, 0.57–1.05]) and worst pain item score (HR = 0.81 [95% CI, 0.58–1.12]) trended in favor of ribociclib vs placebo. Conclusions: In addition to significantly prolonging PFS and OS compared with placebo plus fulvestrant, adding ribociclib to fulvestrant maintains HRQOL.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Breast cancer; Metastatic; Patient-reported outcomes; Quality of life

Ribociclib plus fulvestrant for postmenopausal women with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer in the phase III randomized MONALEESA-3 trial: updated overall survival - Slamon, D. J.; Neven, P.; Chia, S.; Jerusalem, G.; De Laurentiis, M.; Im, S.; Petrakova, K.; Valeria Bianchi, G.; Martín, M.; Nusch, A.; Sonke, G. S.; De la Cruz-Merino, L.; et al. (Annals of Oncology, 2021)
Background: Ribociclib plus fulvestrant demonstrated significant progression-free survival (PFS) and overall survival (OS) benefits in patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative (HR+/HER2−) advanced breast cancer (ABC). Here we present a new landmark in survival follow-up for a phase III cyclin-dependent kinases 4 and 6 inhibitor clinical trial in patients with ABC (median, 56.3 months). Patients and methods: This phase III, randomized, double-blind, placebo-controlled trial was conducted at 174 sites (30 countries). Patients were men and postmenopausal women (age ≥18 years) with histologically/cytologically confirmed HR+/HER2− ABC. Patients could have received ≤1 line of endocrine therapy (ET) but no chemotherapy for ABC. Patients, assigned 2:1, were stratified by the presence/absence of liver/lung metastases and previous ET. Patients received intramuscular fulvestrant (500 mg, day 1 of each 28-day cycle plus day 15 of cycle 1) with oral ribociclib (600 mg/day, 3 weeks on, 1 week off) or placebo. Efficacy analyses were by intention to treat. Safety was assessed in patients receiving ≥1 dose study treatment. OS was a secondary endpoint. MONALEESA-3 is registered with ClinicalTrials.gov (NCT02422615; no longer enrolling). Results: Between 18 June 2015 and 10 June 2016, 726 patients were randomly assigned (484, ribociclib; 242, placebo). At data cut-off (30 October 2020), median OS (mOS) was 53.7 months (ribociclib) versus 41.5 months (placebo) [hazard ratio (HR), 0.73; 95% confidence interval (CI) 0.59-0.90]. Subgroup analyses were consistent with overall population. In the first-line setting, most patients in the ribociclib arm (∼60%) lived longer than median follow-up; mOS was 51.8 months in the placebo arm (HR, 0.64; 95% CI 0.46-0.88). In the second-line setting, mOS was 39.7 months (ribociclib) versus 33.7 months (placebo) (HR, 0.78; 95% CI 0.59-1.04). No apparent drug–drug interaction between ribociclib and fulvestrant or new safety signals were observed. Conclusions: This analysis reported extended OS follow-up in MONALEESA-3. mOS was ∼12 months longer in patients with HR+/HER2− ABC treated with ribociclib plus fulvestrant compared with fulvestrant monotherapy.
CRIS-Team Scopus Importer:2021-08-06
Keywords: advanced breast cancer; CDK4/6 inhibitor; overall survival; ribociclib

Risk factors for locoregional recurrence (LRR) after neoadjuvant chemotherapy: Pooled analysis of prospective neoadjuvant breast cancer (BC) trials - Werutsky, G.; Untch, M.; Hanusch, C.; Fasching, Peter; Blohmer, J. -U.; Seiler, S.; Denkert, C.; Tesch, H.; Jackisch, C.; Gerber, B.; Schneeweiss, A.; Link, T.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Risk of Ovarian Cancer and the NF-?B Pathway: Genetic Association with IL1A and TNFSF10 - Charbonneau, Bridget; Block, Matthew S.; Bamlet, William R.; Vierkant, Robert A.; Kalli, Kimberly R.; Fogarty, Zachary; Rider, David N.; Sellers, Thomas A.; Tworoger, Shelley S.; Poole, Elizabeth; Risch, Harvey A.; Salvesen, Helga B.; et al. (Cancer Research, 2014)
A missense single-nucleotide polymorphism (SNP) in the immune modulatory gene IL1A has been associated with ovarian cancer risk (rs17561). Although the exact mechanism through which this SNP alters risk of ovarian cancer is not clearly understood, rs17561 has also been associated with risk of endometriosis, an epidemiologic risk factor for ovarian cancer. Interleukin-1? (IL1A) is both regulated by and able to activate NF-?B, a transcription factor family that induces transcription of many proinflammatory genes and may be an important mediator in carcinogenesis. We therefore tagged SNPs in more than 200 genes in the NF-?B pathway for a total of 2,282 SNPs (including rs17561) for genotype analysis of 15,604 cases of ovarian cancer in patients of European descent, including 6,179 of high-grade serous (HGS), 2,100 endometrioid, 1,591 mucinous, 1,034 clear cell, and 1,016 low-grade serous, including 23,235 control cases spanning 40 studies in the Ovarian Cancer Association Consortium. In this large population, we confirmed the association between rs17561 and clear cell ovarian cancer [OR, 0.84; 95% confidence interval (CI), 0.76-0.93; P = 0.00075], which remained intact even after excluding participants in the prior study (OR, 0.85; 95% CI, 0.75-0.95; P = 0.006). Considering a multiple-testing-corrected significance threshold of P < 2.5 × 10(-5), only one other variant, the TNFSF10 SNP rs6785617, was associated significantly with a risk of ovarian cancer (low malignant potential tumors OR, 0.85; 95% CI, 0.79-0.91; P = 0.00002). Our results extend the evidence that borderline tumors may have a distinct genetic etiology. Further investigation of how these SNPs might modify ovarian cancer associations with other inflammation-related risk factors is warranted. Cancer Res; 74(3); 852-61. ©2013 AACR.
EVALuna2:9204

Risk of postmenopausal hormone therapy and patient history factors for the survival rate in women with endometrial carcinoma - Hein, Alexander; Schneider, Michael; Renner, Stefan; Fasching, Peter; Fießler, Cornelia; Titz, Susanna; Hartmann, Arndt; Beckmann, Matthias; Thiel, Falk C. (Archives of Gynecology and Obstetrics, 2019)
Purpose: Postmenopausal hormone therapy (HT) is known to affect the development of hormone-dependent endometrial carcinoma (type I EC). Several studies on breast and ovarian carcinoma have shown that HT influences the molecular profile and prognostic behavior of these tumors. This study aimed to investigate the influence of prior HT and other risk factors on the prognosis in a cohort of patients with invasive endometrial carcinoma (EC). Methods: Among 525 patients diagnosed with EC between 1987 and 2010, 426 postmenopausal patients were identified. Information regarding HT was available in 287 of these patients, 78 of whom had a history of HT and 209 of whom did not. Both overall survival (OS) and progression-free survival (PFS) were analyzed. In addition to OS and PFS, risk factors such as age at diagnosis, postmenopausal HT, body mass index (BMI), diabetes mellitus, tumor stage, EC type (I or II), and recurrences were analyzed. Results: Relative to HT alone, women with EC and a history of HT had a longer survival than those with no HT. However, the Cox proportional hazards model showed that it was not HT itself, but rather other characteristics in the HT group that were causally associated with longer survival. Conclusions: Age (the older, the worse) and tumor stage (the higher, the worse) were significant influences on overall survival. Patients with HT also had lower BMIs, less diabetes, more type I EC, and fewer recurrences in comparison with the non-HT group. With regard to the PFS, it made no difference whether the patient was receiving HT.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Endometrial carcinoma; Estrogen; Hormone replacement therapy; Hormone therapy; Overall survival; Progesterone; Prognosis; Risk factors

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

Robot-assisted liver resection - Aselmann, H.; Moeller, T.; Kersebaum, J. -N.; Egberts, J. H.; Croner, R.; Brunner, Michaela; Grützmann, Robert; Becker, T. (Chirurg, 2017)
Robotic liver resection can overcome some of the limitations of laparoscopic liver surgery; therefore, it is a promising tool to increase the proportion of minimally invasive liver resections. The present article gives an overview of the current literature. Furthermore, the results of a nationwide survey on robotic liver surgery among hospitals in Germany with a DaVinci system used in general visceral surgery and the perioperative results of two German robotic centers are presented.
EVALuna2:15283

Robotic-Assisted Liver Surgery - Croner, R.; Perrakis, Aristotelis; Grützmann, Robert; Hohenberger, Werner; Brunner, Michaela (Zentralblatt für Chirurgie, 2016)
The advantages of minimally invasive liver resections for selected patients are evident. Robots provide new innovations that will influence minimally invasive liver surgery in the future. This article presents our initial experience with this technology in our patient population. Material und Methods: In 14 patients with benign or malignant liver tumours, robotic-assisted liver surgery was performed. Selection criteria were compensated liver function and resection of <= 3 liver segments. Chronic liver disease or previous abdominal surgery were no exclusion criteria.Malignant liver tumours were removed in 10 patients (71 %) and benign symptomatic liver tumors in 3 patients (21 %), respectively, with histopathologically negative margins (R0). One patient suffering from HCC underwent intraoperative ablation. In one case (7 %) conversion was necessary. Mean operation time was 296 min (120-458 min); mean estimated blood loss was 319 ± 298 ml. The mean hospital stay of the patients was 8 days (3-17 days). Three patients (21 %) suffered from postoperative complications, which were manageable by conservative treatment (Clavien-Dindo I) in 2 cases (14 %). One patient (7 %) needed endoscopic treatment for postoperative bile leak (Clavien-Dindo III a). No patient died intra- or perioperatively.Robotic-assisted liver surgery is a safe procedure, which provides patients with all benefits of minimally invasive surgery. This highly advanced technology requires surgeons to strive for an increasing level of specialisation, in addition to being well-trained in liver surgery. Hence, a clear definition of the procedures and standardised teaching programs are necessary.
EVALuna2:15228

Robotic liver surgery for minor hepatic resections: a comparison with laparoscopic and open standard procedures - Croner, Roland S.; Perrakis, Aristotelis; Hohenberger, Werner; Brunner, Michaela (Langenbecks Archives of Surgery, 2016)
Minimally invasive liver surgery is increasing worldwide. The benefit of the robot in this scenario is currently controversially discussed. We compared our robotic cases vs. laparoscopic and open minor hepatic resections and share the experience.From 2011 to 2015, ten patients underwent robotic and 19 patients underwent laparoscopic minor liver resections in the Department of Surgery, University Hospital Erlangen. These patients were compared to a case-matched control group of 53 patients. The perioperative prospectively collected data were analyzed retrospectively.Blood loss was significantly decreased in the robotic (306 ml) and laparoscopic (356 ml) vs. the open (903 ml) surgery group (p = 0.001). Mean tumor size was 4.1-4.8 cm in all groups (p = 0.571). Negative surgical margins were present in 94 % of the open and 100 % of the laparoscopic and robotic group (p = 0.882). Time for surgery was enlarged for robotic (321 min) vs. laparoscopic (242 min) and open (186 min) surgery (p = 0.001). Postoperative hospitalization was decreased after robotic (7 days) and laparoscopic (8 days) vs. open (10 days) surgery (p = 0.004). Total morbidity was 17 % for open, 16 % for laparoscopic, and 1 % for robotic cases (p = 0.345). Postoperative pain medication and elevation of liver enzymes were remarkably lower after minimally invasive vs. open procedures.Minimally invasive liver surgery can be performed safely for minor hepatic resections and should be considered whenever possible. Minor liver resections can be performed by standard laparoscopy equivalent to robotic procedures. Nevertheless, the robot adds a technical upgrade which may have benefits for challenging cases and major liver surgery.
EVALuna2:15231

rs2735383, located at a microRNA binding site in the 3'UTR of NBS1, is not associated with breast cancer risk - Liu, Jingjing; Loncar, Ivona; Collee, J. Margriet; Bolla, Manjeet K.; Dennis, Joe; Michailidou, Kyriaki; Wang, Qin; Andrulis, Irene L.; Barile, Monica; Beckmann, Matthias; Behrens, Sabine; Benitez, Javier; et al. (Scientific Reports, 2016)
NBS1, also known as NBN, plays an important role in maintaining genomic stability. Interestingly, rs2735383 G > C, located in a microRNA binding site in the 3'-untranslated region (UTR) of NBS1, was shown to be associated with increased susceptibility to lung and colorectal cancer. However, the relation between rs2735383 and susceptibility to breast cancer is not yet clear. Therefore, we genotyped rs2735383 in 1,170 familial non-BRCA1/2 breast cancer cases and 1,077 controls using PCR-based restriction fragment length polymorphism (RFLP-PCR) analysis, but found no association between rs2735383CC and breast cancer risk (OR = 1.214, 95% CI = 0.936-1.574, P = 0.144). Because we could not exclude a small effect size due to a limited sample size, we further analyzed imputed rs2735383 genotypes (r2 > 0.999) of 47,640 breast cancer cases and 46,656 controls from the Breast Cancer Association Consortium (BCAC). However, rs2735383CC was not associated with overall breast cancer risk in European (OR = 1.014, 95% CI = 0.969-1.060, P = 0.556) nor in Asian women (OR = 0.998, 95% CI = 0.905-1.100, P = 0.961). Subgroup analyses by age, age at menarche, age at menopause, menopausal status, number of pregnancies, breast feeding, family history and receptor status also did not reveal a significant association. This study therefore does not support the involvement of the genotype at NBS1 rs2735383 in breast cancer susceptibility.
EVALuna2:33244

rs495139 in the TYMS-ENOSF1 Region and Risk of Ovarian Carcinoma of Mucinous Histology - Kelemen, Linda E.; Earp, Madalene; Fridley, Brooke L.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Ekici, Arif Bülent; Hein, Alexander; Lambrechts, Diether; Lambrechts, Sandrina; Van Nieuwenhuysen, Els; Vergote, Ignace; et al. (International Journal of Molecular Sciences, 2018)
Thymidylate synthase (TYMS) is a crucial enzyme for DNA synthesis. TYMS expression is regulated by its antisense mRNA, ENOSF1. Disrupted regulation may promote uncontrolled DNA synthesis and tumor growth. We sought to replicate our previously reported association between rs495139 in the TYMS-ENOSF1 3' gene region and increased risk of mucinous ovarian carcinoma (MOC) in an independent sample. Genotypes from 24,351 controls to 15,000 women with invasive OC, including 665 MOC, were available. We estimated per-allele odds ratios (OR) and 95% confidence intervals (CI) using unconditional logistic regression, and meta-analysis when combining these data with our previous report. The association between rs495139 and MOC was not significant in the independent sample (OR = 1.09; 95% CI = 0.97⁻1.22; p = 0.15; N = 665 cases). Meta-analysis suggested a weak association (OR = 1.13; 95% CI = 1.03⁻1.24; p = 0.01; N = 1019 cases). No significant association with risk of other OC histologic types was observed (p = 0.05 for tumor heterogeneity). In expression quantitative trait locus (eQTL) analysis, the rs495139 allele was positively associated with ENOSF1 mRNA expression in normal tissues of the gastrointestinal system, particularly esophageal mucosa (r = 0.51, p = 1.7 × 10-28), and nonsignificantly in five MOC tumors. The association results, along with inconclusive tumor eQTL findings, suggest that a true effect of rs495139 might be small.
EVALuna2:35118

Sacral nerve stimulation for faecal incontinence in patients with sacral malformation - Brunner, Michaela; Cui, Z.; Matzel, Klaus (International Journal of Colorectal Disease, 2017)
Sacral nerve stimulation (SNS) is a common and effective treatment for faecal incontinence (FI), but accessibility of the sacral nerves is mandatory. In some cases, electrode placement fails for unknown reasons. A frequent cause could be sacral malformations, which have a high incidence (up to 24.1%) and can be unsuspected.We report two patients with FI consequent to congenital anorectal malformation and associated sacral malformation. Despite partial sacral agenesis, SNS was feasible in both. They benefitted greatly from SNS, with an improved ability to postpone the urge up to at least 15 min, reduced incontinence episodes (at least 50%), and significantly better quality of life.SNS may be feasible in patients with FI, even in the presence of sacral malformation. However, clinicians should be aware of the attendant technical difficulties. Preoperative imaging, preferably with MRI of the sacrum, is advisable. If the sacral spinal nerves are inaccessible technically, pudendal nerve stimulation could be considered, if anatomy permits.
EVALuna2:15239

Safety and immunogenicity of neoadjuvant treatment using WT1-immunotherapeutic in combination with standard therapy in patients with WT1-positive Stage II/III breast cancer: a randomized Phase I study - Higgins, M.; Curigliano, Giuseppe; Dieras, V.; Kuemmel, S.; Kunz, G.; Fasching, Peter; Campone, M.; Bachelot, T.; Krivorotko, P.; Chan, S.; Ferro, A.; Schwartzberg, L.; et al. (Breast Cancer Research and Treatment, 2017)
PURPOSE: This Phase I, multicenter, randomized study (ClinicalTrials.gov NCT01220128) evaluated the safety and immunogenicity of recombinant Wilms' tumor 1 (WT1) protein combined with the immunostimulant AS15 (WT1-immunotherapeutic) as neoadjuvant therapy administered concurrently with standard treatments in WT1-positive breast cancer patients. METHODS: Patients were treated in 4 cohorts according to neoadjuvant treatment (A: post-menopausal, hormone receptor [HR]-positive patients receiving aromatase inhibitors; B: patients receiving chemotherapy; C: HER2-overexpressing patients on trastuzumab-chemotherapy combination; D: HR-positive/HER2-negative patients on chemotherapy). Patients (cohorts A-C) were randomized (2:1) to receive 6 or 8 doses of WT1-immunotherapeutic or placebo together with standard neoadjuvant treatment in a double-blind manner; cohort D patients received WT1-immunotherapeutic in an open manner. Safety was assessed throughout the study. WT1-specific antibodies were assessed pre- and post-vaccination. RESULTS: Sixty-two patients were randomized; 60 received ≥ one dose of WT1-immunotherapeutic. Two severe toxicities were reported: diarrhea (cohort C; also reported as a grade 3 serious adverse event) and decreased left ventricular ejection fraction (cohort B; also reported as a grade 2 adverse event). Post-dose 4 of WT1-immunotherapeutic, 10/10 patients from cohort A, 0/8 patients from cohort B, 6/11 patients from cohort C, and 2/3 patients from cohort D were humoral responders. The sponsor elected to close the trial prematurely. CONCLUSIONS: Concurrent administration of WT1-immunotherapeutic and standard neoadjuvant therapy was well tolerated and induced WT1-specific antibodies in patients receiving neoadjuvant aromatase inhibitors. In patients on neoadjuvant chemotherapy or trastuzumab-chemotherapy combination, the humoral response was impaired or blunted, likely due to either co-administration of corticosteroids and/or the chemotherapies themselves.
EVALuna2:36200

Safety interim analysis (SIA) of the phase III postneoadjuvant SASCIA study evaluating sacituzumab govitecan (SG) in patients (pts) with primary HER2-negative breast cancer (BC) at high relapse risk after neoadjuvant chemotherapy (NACT) - Marme, Frederik; Hanusch, Claus; Furlanetto, Jenny; Morris, Patrick; Link, Theresa; Denkert, Carsten; Fasching, Peter; Jackisch, Christian; Antolin, Silvia; Solbach, Christine; Aftimos, Philippe; Huober, Jens; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Safety interim analysis (SIA) of the phase III postneoadjuvant SASCIA study evaluating sacituzumab govitecan (SG) in patients with primary HER2-negative breast cancer (BC) at high relapse risk after neoadjuvant treatment - Marme, F.; Hanusch, C.; Furlanetto, J.; Morris, P.; Link, T.; Denkert, C.; Fasching, Peter; Jackisch, C.; Antolin, S.; Solbach, C.; Aftimos, P.; Huober, J.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Salivary and hair cortisol as biomarkers of emotional and behavioral symptoms in 6–9 year old children - Golub, Yulia; Kuitunen-Paul, Sören; Panaseth, Kerstin; Stonawski, Valeska; Frey, Stefan; Steigleder, Ruth; Grimm, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; et al. (Physiology & behavior, 2019)
The aim of the present work is to investigate the association of salivary and cumulative cortisol levels with emotional and behavioral symptoms in a Franconian Cognition and Emotion Studies (FRANCES) general population cohort of 158 6- to 9 year old children. Salivary cortisol values were measured by one-day diurnal cortisol profile, whereas cumulative cortisol was estimated via one-month hair cortisol concentrations (rHCC). Nearly all significant associations of clinical symptoms with child cortisol indices were age dependent: We report emotional symptoms being associated with lower rHCC in younger children (6.06–7.54 years). In older children (7.55–9.41 years) behavioral problems were further associated with higher rHCC and lower salivary cortisol awakening responses. In summary, child clinical symptoms were stronger associated with markers of hair cortisol compared to salivary cortisol. To picture developmental mechanisms, we suggest longitudinal designs for cortisol measures of stress systems in children and adolescents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Behavioral symptoms; Emotional symptoms; FRANCES; Hair cortisol; HPA axis; Salivary cortisol

Saliva samples as a source of DNA for high throughput genotyping: an acceptable and sufficient means in improvement of risk estimation throughout mammographic diagnostics - Poehls, U. G.; Hack, Caroline; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (European Journal of Medical Research, 2018)
BACKGROUND: Breast cancer screening programs seem to be an insufficient tool for women at high genetic risk for breast cancer. These women are not adequately monitored yet. Genetic testing may improve clearly the quality of breast cancer prevention programs. At present, blood samples are favored for obtaining high-quality DNA; however, DNA can also be obtained by collecting saliva. The aim of this study was, on the one hand, to determine whether saliva sampling is a practicable means to obtain sufficient quantity and quality of DNA and, on the other hand, whether it is accepted by patients throughout mammographic diagnostics. METHODS: 67 consecutive women with diagnostic need for mammography with or without a family history for breast cancer were asked for their basic willingness to undergo a genetic testing by saliva sample in addition to standard diagnostics. Saliva samples were analyzed in terms of DNA quantity and quality. RESULTS: 64 (95.6%) women agreed to provide a saliva sample; 3 of them denied participation. And even 63 out of 64 (98.4%) were interested in their specific results. 45 out of 64 samples contained a DNA concentration above 50 ng/µl, 12 samples were between 25 and 50 ng/µl and only 7 of them were under 25 ng/µl with the standard extraction procedure. CONCLUSION: A high number of patients seem to accept salvia samples as a risk assessment tool in breast diagnostics and are interested in their specific risk situation. At the same time, it could be demonstrated that it is an effective way to provide high-quality DNA for breast cancer gene analysis. However, it remains to be shown whether it would be possible to integrate it with the same acceptance in a nationwide breast cancer screening program.
EVALuna2:34632

SARS-CoV-2 Infection in Pregnancy - a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian; Titzmann, Adriana; Schneider, Michael; Stelzl, Patrick; Kehl, Sven; Fasching, Peter; Beckmann, Matthias; Enßer, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 2019-nCoV; coronavirus; COVID-19; pregnancy; SARS-CoV-2

Sebaceous breast carcinoma: report of a rare histological special subtype - Wachter, David; Rauh, C.; Wenkel, Evelyn; Fasching, Peter; Beckmann, Matthias; Hartmann, Arndt (Pathologe, 2014)
We report on a case of sebaceous carcinoma of the breast as a rare histological special subtype of breast cancer. Because these tumors are uncommon, differential diagnostic considerations and the exclusion of Muir-Torre syndrome are emphasized. Finally possible mechanisms of development and therapeutic strategies for this carcinoma are discussed.
EVALuna2:6578

Self-reported Improvement in Side Effects and Quality of Life With Integrative Medicine in Breast Cancer Patients - Hack, Carolin; Hackl, Janina; Huettner, Nina B. M.; Langemann, Hanna; Schwitulla, Judith; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Integrative Cancer Therapies, 2018)
PURPOSE: Although the demand from patients for integrative medicine is increasing, complementary medicine services are still quite heterogeneous and have not been incorporated into clinical routine. The aim of this study was to systematically evaluate improvements in side effects and quality of life associated with a hospital-based integrative medicine program in the modern breast cancer patient care setting. METHODS: In a cross-sectional study, integrative health counseling and treatment were evaluated in women with breast cancer. Over a 15-month period, data for 75 patients from an integrative medicine consultancy service with standardized operating procedures were collected at the University Breast Center for Franconia. At baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. In the follow-up, patient-reported outcomes related to side effects of conventional cancer treatment and patients' quality of life were analyzed. RESULTS: Among 60 patients with the therapy goal of reducing the side effects of conventional treatment, 46 (76.7%) were successful. Among 57 patients hoping to improve disease-related quality of life, 46 (82%) reported success. Whereas patients with metastatic disease achieved a reduction in the side effects of conventional therapy, quality-of-life improvements were predominantly achieved by patients with a good treatment prognosis. CONCLUSIONS: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in all phases of tumor disease. Integrative treatment services should be included as part of patient care in clinical routine work to offer patients the maximum quality of care and safety with complementary therapies.
EVALuna2:209953

Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics - Seuß, Hannes; Dankerl, Peter; Ihle, Matthias; Grandjean, Andrea; Hammon, Rebecca; Kaestle, Nicola; Fasching, Peter; Maier, Christian; Christoph, Jan; Sedlmayr, Martin; Uder, Michael; Hammon, Matthias; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Projects involving collaborations between different institutions require data security via selective de-identification of words or phrases. A semi-automated de-identification tool was developed and evaluated on different types of medical reports natively and after adapting the algorithm to the text structure. Materials and Methods A semi-automated de-identification tool was developed and evaluated for its sensitivity and specificity in detecting sensitive content in written reports. Data from 4671 pathology reports (4105 + 566 in two different formats), 2804 medical reports, 1008 operation reports, and 6223 radiology reports of 1167 patients suffering from breast cancer were de-identified. The content was itemized into four categories: direct identifiers (name, address), indirect identifiers (date of birth/operation, medical ID, etc.), medical terms, and filler words. The software was tested natively (without training) in order to establish a baseline. The reports were manually edited and the model re-trained for the next test set. After manually editing 25, 50, 100, 250, 500 and if applicable 1000 reports of each type re-training was applied. Results In the native test, 61.3 % of direct and 80.8 % of the indirect identifiers were detected. The performance (P) increased to 91.4 % (P25), 96.7 % (P50), 99.5 % (P100), 99.6 % (P250), 99.7 % (P500) and 100 % (P1000) for direct identifiers and to 93.2 % (P25), 97.9 % (P50), 97.2 % (P100), 98.9 % (P250), 99.0 % (P500) and 99.3 % (P1000) for indirect identifiers. Without training, 5.3 % of medical terms were falsely flagged as critical data. The performance increased, after training, to 4.0 % (P25), 3.6 % (P50), 4.0 % (P100), 3.7 % (P250), 4.3 % (P500), and 3.1 % (P1000). Roughly 0.1 % of filler words were falsely flagged. Conclusion Training of the developed de-identification tool continuously improved its performance. Training with roughly 100 edited reports enables reliable detection and labeling of sensitive data in different types of medical reports. Key Points: · Collaborations between different institutions require de-identification of patients' data. · Software-based de-identification of content-sensitive reports grows in importance as a result of 'Big data'. · A de-identification software was developed and tested natively and after training. · The proposed de-identification software worked quite reliably, following training with roughly 100 edited reports. · A final check of the texts by an authorized person remains necessary. Citation Format · Seuss H, Dankerl P, Ihle M et al. Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics. Fortschr Röntgenstr 2017; 189: 661 - 671.
EVALuna2:14623

Semi-automated delineation of breast cancer tumors and subsequent materialization using three-dimensional printing (rapid prototyping) - Schulz-Wendtland, Rüdiger; Harz, Markus; Meier-Meitinger, Martina; Brehm, Barbara; Wacker, Till; Hahn, Horst K.; Wagner, Florian; Wittenberg, Thomas; Beckmann, Matthias; Uder, Michael; Fasching, Peter; Emons, Julius (Journal of Surgical Oncology, 2017)
Three-dimensional (3D) printing has become widely available, and a few cases of its use in clinical practice have been described. The aim of this study was to explore facilities for the semi-automated delineation of breast cancer tumors and to assess the feasibility of 3D printing of breast cancer tumors.In a case series of five patients, different 3D imaging methods-magnetic resonance imaging (MRI), digital breast tomosynthesis (DBT), and 3D ultrasound-were used to capture 3D data for breast cancer tumors. The volumes of the breast tumors were calculated to assess the comparability of the breast tumor models, and the MRI information was used to render models on a commercially available 3D printer to materialize the tumors.The tumor volumes calculated from the different 3D methods appeared to be comparable. Tumor models with volumes between 325 mm(3) and 7,770 mm(3) were printed and compared with the models rendered from MRI. The materialization of the tumors reflected the computer models of them.3D printing (rapid prototyping) appears to be feasible. Scenarios for the clinical use of the technology might include presenting the model to the surgeon to provide a better understanding of the tumor's spatial characteristics in the breast, in order to improve decision-making in relation to neoadjuvant chemotherapy or surgical approaches. J. Surg. Oncol. 2017;115:238-242. © 2016 Wiley Periodicals, Inc.
EVALuna2:14618

Serum carbonic anhydrase IX as predictive marker for efficacy of bevacizumab: a biomarker analysis from the GeparQuinto phase III neoadjuvant breast cancer trial - Janning, M.; Mueller,; Vettorazzi, E.; Cubas-Cordova, M.; Gensch,; Ben Batalla,; Eulenburg, Zu C.; Schem, C.; Fasching, Peter; Schnappauf, B.; Karn, Thomas; Fehm, T.; et al. (2016)
EVALuna2:33318

Sex-specific association between prenatal androgenization (second-to-fourth digit length ratio) and frontal brain volumes in adolescents - Lenz, Bernd; Gerhardt, Sarah; Boroumand-Jazi, Rafat; Eichler, Anna; Buchholz, Verena Nadine; Fasching, Peter; Kornhuber, Johannes; Banaschewski, Tobias; Flor, Herta; Guldner, Stella; Prignitz, Maren; Nees, Frauke (European archives of psychiatry and clinical neuroscience, 2022)
Prenatal androgenization associates sex-dependently with behavior and mental health in adolescence and adulthood, including risk-taking, emotionality, substance use, and depression. However, still little is known on how it affects underlying neural correlates, like frontal brain control regions. Thus, we tested whether prenatal androgen load is sex-dependently related to frontal cortex volumes in a sex-balanced adolescent sample. In a cross-sectional magnetic resonance imaging study, we examined 61 adolescents (28 males, 33 females; aged 14 or 16 years) and analyzed associations of frontal brain region volumes with the second-to-fourth digit length ratio (2D:4D), an established marker for prenatal androgenization, using voxel-based morphometry in a region-of-interest approach. Lower 2D:4D (indicative of higher prenatal androgen load) correlated significantly with smaller volumes of the right anterior cingulate cortex (r-ACC; beta = 0.45) in male adolescents and with larger volumes of the left inferior frontal gyrus orbital part (l-IFGorb; beta = - 0.38) in female adolescents. The regression slopes of 2D:4D on the r-ACC also differed significantly between males and females. The study provides novel evidence that prenatal androgenization may influence the development of the frontal brain in a sex- and frontal brain region-specific manner. These effects might contribute to the well-known sex differences in risk-taking, emotionality, substance use, and depression. Future research is needed to elucidate the role of prenatal androgenization within the biopsychosocial model.
CRIS-Team WoS Importer:2022-12-23

Shared heritability and functional enrichment across six solid cancers - Jiang, Xia; Finucane, Hilary K.; Schumacher, Fredrick R.; Schmit, Stephanie L.; Tyrer, Jonathan P.; Han, Younghun; Michailidou, Kyriaki; Lesseur, Corina; Kuchenbaecker, Karoline B.; Dennis, Joe; Conti, David V.; Casey, Graham; et al. (Nature Communications, 2019)
Quantifying the genetic correlation between cancers can provide important insights into the mechanisms driving cancer etiology. Using genome-wide association study summary statistics across six cancer types based on a total of 296,215 cases and 301,319 controls of European ancestry, here we estimate the pair-wise genetic correlations between breast, colorectal, head/neck, lung, ovary and prostate cancer, and between cancers and 38 other diseases. We observed statistically significant genetic correlations between lung and head/neck cancer (r g = 0.57, p = 4.6 × 10 −8 ), breast and ovarian cancer (r g = 0.24, p = 7 × 10 −5 ), breast and lung cancer (r g = 0.18, p =1.5 × 10 −6 ) and breast and colorectal cancer (r g = 0.15, p = 1.1 × 10 −4 ). We also found that multiple cancers are genetically correlated with non-cancer traits including smoking, psychiatric diseases and metabolic characteristics. Functional enrichment analysis revealed a significant excess contribution of conserved and regulatory regions to cancer heritability. Our comprehensive analysis of cross-cancer heritability suggests that solid tumors arising across tissues share in part a common germline genetic basis.
CRIS-Team Scopus Importer:2019-05-02

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Smartphone-Based Colorimetric Analysis of Urine Test Strips for At-Home Prenatal Care - Flaucher, Madeleine; Nissen, Michael; Jäger, Katharina; Titzmann, Adriana; Pontones, Constanza; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Gradl, Stefan; Eskofier, Björn (IEEE Journal of Translational Engineering in Health and Medicine, 2022)
Objective: Clinical urine tests are a key component of prenatal care. As of now, urine test strips are evaluated through a time consuming, often error-prone and operator-dependent visual color comparison of test strips and reference cards by medical staff. Methods and procedures: This work presents an automated pipeline for urinalysis with urine test strips using smartphone camera images in home environments, combining several image processing and color combination techniques. Our approach is applicable to off-the-shelf test strips in home conditions with no additional hardware required. For development and evaluation of our pipeline we collected image data from two sources: i) A user study (26 participants, 150 images) and ii) a lab study (135 images). Results: We trained a region-based convolutional neural network that is able to detect the urine test strip location and orientation in images with a wide variety of light conditions, backgrounds and perspectives with an accuracy of 85.5%. The reference card can be robustly detected through a feature matching approach in 98.6% of the images. Color comparison by Hue channel (0.81 F1-Score), Matching factor (0.80 F1-Score) and Euclidean distance (0.70 F1-Score) were evaluated to determine the urinalysis results. Conclusion: We show that an automated smartphone-based colorimetric analysis of urine test strips in a home environment is feasible. It facilitates examinations and provides the possibility to shift care into an at-home environment. Clinical impact: The findings demonstrate that routine urine examinations can be transferred into the home environment using a smartphone. Simultaneously, human error is avoided, accuracy is increased and medical staff is relieve

Smartphone pregnancy apps: systematic analysis of features, scientific guidance, commercialization, and user perception - Nissen, Michael; Huang, Shih-Yuan; Jäger, Katharina; Flaucher, Madeleine; Titzmann, Adriana; Bleher, Hannah; Pontones, Constanza; Hübner, Hanna; Danzberger, Nina; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (BMC Pregnancy and Childbirth, 2024)
Background Over 50% of pregnant women use pregnancy applications (apps). Some app s lack credibility, information accuracy, and evidence-based clinical advice, containing potentially harmful functionality. Previous studies have only conducted a limited analysis of pregnancy app functionalities, expert involvement/evidence-based content, used commercialization techniques, and user perception. Methods We used the keyword “pregnancy” to scrape (automatically extract) apps and app information from Apple App Store and Google Play. Unique functionalities were derived from app descriptions and user reviews. App descriptions were screened for evidence-based content and expert involvement, and apps were subsequently analyzed in detail. Apps were opened and searched for used commercialization techniques, such as advertisements or affiliate marketing. Automated text analysis (natural language processing) was used on app reviews to assess users’ perception of evidence-based content/expert involvement and commercialization techniques. Results In total, 495 apps were scraped. 226 remained after applying exclusion criteria. Out of these, 36 represented 97%/88% of the total market share (Apple App Store/Google Play), and were thus considered for review. Overall, 49 distinct functionalities were identified, out of which 6 were previously unreported. Functionalities for fetal kick movement counting were found. All apps are commercial. Only 15 apps mention the involvement of medical experts. 10.3% of two-stars user reviews include commercial topics, and 0.6% of one-/two-/three-/five stars user reviews include references to scientific content accuracy. Conclusion Problematic features and inadequate advice continue to be present in pregnancy apps. App developers should adopt an evidence-based development approach and avoid implementing as many features as possible, potentially at the expense of their quality or over-complication (“feature creep”). Financial incentives, such as grant programs, could support adequate content quality. Caregivers play a key role in pregnant individuals’ decision-making, should be aware of potential dangers, and could guide them to trustworthy app

Smart sensing in pregnancy: a survey-based evaluation of readiness to use wearable sensory applications in prenatal care - Weidenthaler, Filip; Danzberger, Nina; Pontones, Constanza; Titzmann, Adriana; Hein, Alexander; Beckmann, Matthias; Fasching, Peter; Huebner, H. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Sniper: A novel hypermethylation biomarker panel for liquid biopsy based early breast cancer detection - Mijnes, Jolein; Tiedemann, Janina; Eschenbruch, Julian; Gasthaus, Janina; Bringezu, Sarah; Bauerschlag, Dirk; Maass, Nicolai; Arnold, Norbert; Weimer, Jörg; Anzeneder, Tobias; Fasching, Peter; Rübner, Matthias; et al. (Oncotarget, 2019)
Introduction: Mammography is the gold standard for early breast cancer detection, but shows important limitations. Blood-based approaches on basis of cell-free DNA (cfDNA) provide minimally invasive screening tools to characterize epigenetic alterations of tumor suppressor genes and could serve as a liquid biopsy, complementing mammography. Methods: Potential biomarkers were identified from The Cancer Genome Atlas (TCGA), using HumanMethylation450-BeadChip data. Promoter methylation status was evaluated quantitatively by pyrosequencing in a serum test cohort (n = 103), a serum validation cohort (n = 368) and a plasma cohort (n = 125). Results: SPAG6, NKX2-6 and PER1 were identified as novel biomarker candidates. ITIH5 was included on basis of our previous work. In the serum test cohort, a panel of SPAG6 and ITIH5 showed 63% sensitivity for DCIS and 51% sensitivity for early invasive tumor (pT1, pN0) detection at 80% specificity. The serum validation cohort revealed 50% sensitivity for DCIS detection on basis of NKX2-6 and ITIH5. Furthermore, an inverse correlation between methylation frequency and cfDNA concentration was uncovered. Therefore, markers were tested in a plasma cohort, achieving a 64% sensitivity for breast cancer detection using SPAG6, PER1 and ITIH5. Conclusions: Although liquid biopsy remains challenging, a combination of SPAG6, NKX2-6, ITIH5 and PER1 (SNiPER) provides a promising tool for blood-based breast cancer detection.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Breast cancer; Discriminative CpG dinucleotides; Early detection; Hypermethylation; Liquid biopsy

SNP-SNP interaction analysis of NF-?B signaling pathway on breast cancer survival - Jamshidi, Maral; Fagerholm, Rainer; Khan, Sofia; Aittomaki, Kristiina; Czene, Kamila; Darabi, Hatef; Li, Jingmei; Andrulis, Irene L.; Chang-Claude, Jenny; Devilee, Peter; Fasching, Peter; Michailidou, Kyriaki; et al. (Oncotarget, 2015)
In breast cancer, constitutive activation of NF-?B has been reported, however, the impact of genetic variation of the pathway on patient prognosis has been little studied. Furthermore, a combination of genetic variants, rather than single polymorphisms, may affect disease prognosis. Here, in an extensive dataset (n = 30,431) from the Breast Cancer Association Consortium, we investigated the association of 917 SNPs in 75 genes in the NF-?B pathway with breast cancer prognosis. We explored SNP-SNP interactions on survival using the likelihood-ratio test comparing multivariate Cox' regression models of SNP pairs without and with an interaction term. We found two interacting pairs associating with prognosis: patients simultaneously homozygous for the rare alleles of rs5996080 and rs7973914 had worse survival (HRinteraction 6.98, 95% CI=3.3-14.4, P=1.42E-07), and patients carrying at least one rare allele for rs17243893 and rs57890595 had better survival (HRinteraction 0.51, 95% CI=0.3-0.6, P = 2.19E-05). Based on in silico functional analyses and literature, we speculate that the rs5996080 and rs7973914 loci may affect the BAFFR and TNFR1/TNFR3 receptors and breast cancer survival, possibly by disturbing both the canonical and non-canonical NF-?B pathways or their dynamics, whereas, rs17243893-rs57890595 interaction on survival may be mediated through TRAF2-TRAIL-R4 interplay. These results warrant further validation and functional analyses.
EVALuna2:17574

Socioeconomic status and depression during and after pregnancy in the Franconian Maternal Health Evaluation Studies (FRAMES) - Hein, Alexander; Rauh, Claudia; Engel, Anne; Häberle, Lothar; Dammer, Ulf; Voigt, Franziska; Fasching, Peter; Faschingbauer, Florian; Burger, Pascal; Beckmann, Matthias; Kornhuber, Johannes; Goecke, Tamme W. (Archives of Gynecology and Obstetrics, 2014)
Depression during and after pregnancy can have a negative impact on women's quality of life and on the development of the newborn child. Interventions have been shown to have a positive influence on both mothers and children. Predictive factors for depressive symptoms might possibly be able to identify groups that are at high risk. The aim of this study was to investigate the value of socioeconomic factors in predicting depressive symptoms during and after pregnancy.Depressiveness was measured using the German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) at three time-points, in a prospective cohort study (n = 1,100). Visit 1 (Q1) was at study entry in the third trimester of the pregnancy, visit 2 (Q2) was shortly after birth, and visit 3 (Q3) was 6-8 months after birth. Depression scores were associated with socioeconomic factors and time in linear mixed models.Parity status, education status, monthly income, residential property status, and partnership status, as well as interactions between them, were found to be predictive factors for EPDS scores. The strongest factor influencing depressive symptoms was partnership status. Women who did not have an intact partnership had EPDS scores that were on average four points higher than in women with a partner at all three study visits (P < 0.000001).Socioeconomic factors define subgroups that have different depression scores during and after pregnancy. Partnership status appears to be one of the most important influencing factors and could be useful for identifying women who should be offered an intervention to prevent possible negative effects on the mother or child.
EVALuna2:17434

Sorafenib in combination with docetaxel as first-line therapy for HER2-negative metastatic breast cancer: Final results of the randomized, double-blind, placebo-controlled phase II MADONNA study - Mavratzas, A.; Baek, S.; Gerber, B.; Schmidt, Marcus; Moebus,; Foerster, F.; Grischke, E. M.; Fasching, Peter; Strumberg, D.; Solomayer, E.; Klare, P.; Windemuth-Kieselbach, C.; et al. (BREAST, 2019)
Background: This multicenter, double-blind phase II study assessed the antitumor activity and toxicity profile of docetaxel with the antiangiogenic multikinase inhibitor sorafenib or matching placebo as a first-line treatment in patients with metastatic or locally advanced HER2-negative breast cancer. Patients and methods: Patients were randomized 1:1 to receive docetaxel 100 mg/m 2 on day 1 every 3 weeks in combination with sorafenib 400 mg bid or placebo on days 2–18 of each cycle until tumor progression, or unacceptable toxicity. Sorafenib/placebo could be continued at the investigator's discretion if docetaxel was stopped due to toxicity. Primary endpoint was progression free survival (PFS). Results: From October 2008 to December 2013, 102 patients were randomized; 98 patients were evaluable. The trial was prematurely terminated due to slow accrual. Due to increased toxicity the dose of docetaxel was reduced to 75 mg/m 2 and an increasing sorafenib dosing schedule was implemented as part of a protocol amendment. The addition of sorafenib to docetaxel did not improve PFS (8.2 vs. 7.3 months for docetaxel/placebo; HR 0.84, log rank p = 0.43), but led to higher rates of early treatment discontinuation. There were no statistically significant differences between sorafenib dosing schedules. Conclusions: Addition of sorafenib to taxane-based first-line chemotherapy in patients with metastatic breast cancer failed to improve PFS and resulted in increased toxicity.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Antiangiogenic agents; Docetaxel; Metastatic breast cancer; Sorafenib

Spatial expression of claudin 18.2 in matched primaries and metastases of tubo-ovarian carcinoma of all subtypes - Wagner, Paul; Gaß, Paul; Pöschke, Patrik; Eckstein, Markus; Gloßner, Laura; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Emons, Julius; Erber, Ramona (Virchows Archiv, 2024)
Physiologically, claudin 18 splice variant 2 (CLDN18.2) expression is restricted to the gastric epithelium, but its expression has been detected in solid cancers. Zolbetuximab, a chimeric IgG1 antibody targeting CLDN18.2, has demonstrated promising effects in patients suffering from CLDN18.2-positive, HER2-negative locally advanced gastric cancer and is currently being studied further. To date, little is known about CLDN18.2 expression in other histological subtypes of tubo-ovarian carcinoma (TOC) and their matching metastases. Using a cohort of all histological TOC subtypes, we investigated the immunohistochemical (IHC) CLDN18.2 expression in both TOCs (n = 536), their matching metastatic tissue (n = 385) and in 93 metastases without primary. Tissue microarrays comprised both the tumor center and periphery. IHC positivity was defined as biomarker expression of ≥ 75% in tumor cells with moderate-to-strong membranous staining. Overall CLDN18.2 positivity was 4.1% (21/515) in the TOC centers and 3.6% (18/498) in their peripheries. In primaries of mucinous tubo-ovarian carcinoma (MTOC), CLDN18.2 positivity rates were 45% (18/40) and 36.6% (15/41), respectively. Positivity rates for the corresponding metastases were 33% (4/12, center) and 27% (3/11, periphery). The expression was relatively homogenous throughout all tumor sites. With no expression in 99.5% of nonmucinous tumors, CLDN18.2 positivity was almost exclusively seen in the mucinous subtype. In tubo-ovarian carcinoma, CLDN18.2 expression was, with rare exceptions, restricted to the mucinous subtype. Among them, 33% of metastasized MTOCs presented with CLDN18.2 positivity. Hence, CLDN18.2 might display a promising target for personalized therapy in patients with advanced MTOC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: CLDN18.2; Immunohistochemistry; Mucinous tubo-ovarian carcinoma; Targeted therapy; Tubo-ovarian cancer

Specific microRNA signatures in exosomes of triple-negative and HER2-positive breast cancer patients undergoing neoadjuvant therapy within the GeparSixto trial - Stevic, Ines; Mueller, Volkmar; Weber, Karsten; Fasching, Peter; Karn, Thomas; Marme, Frederic; Schem, Christian; Stickeler, Elmar; Denkert, Carsten; Van Mackelenbergh, Marion; Salat, Christoph; Schneeweiss, Andreas; et al. (BMC Medicine, 2018)
BACKGROUND: The focus of this study is to identify particular microRNA (miRNA) signatures in exosomes derived from plasma of 435 human epidermal growth factor receptor 2 (HER2)-positive and triple-negative (TN) subtypes of breast cancer (BC). METHODS: First, miRNA expression profiles were determined in exosomes derived from the plasma of 15 TNBC patients before neoadjuvant therapy using a quantitative TaqMan real-time PCR-based microRNA array card containing 384 different miRNAs. Forty-five miRNAs associated with different clinical parameters were then selected and mounted on microRNA array cards that served for the quantification of exosomal miRNAs in 435 BC patients before therapy and 20 healthy women. Confocal microscopy, Western blot, and ELISA were used for exosome characterization. RESULTS: Quantification of 45 exosomal miRNAs showed that compared with healthy women, 10 miRNAs in the entire cohort of BC patients, 13 in the subgroup of 211 HER2-positive BC, and 17 in the subgroup of 224 TNBC were significantly deregulated. Plasma levels of 18 exosomal miRNAs differed between HER2-positive and TNBC subtypes, and 9 miRNAs of them also differed from healthy women. Exosomal miRNAs were significantly associated with the clinicopathological and risk factors. In uni- and multivariate models, miR-155 (p = 0.002, p = 0.003, respectively) and miR-301 (p = 0.002, p = 0.001, respectively) best predicted pathological complete response (pCR). CONCLUSION: Our findings show a network of deregulated exosomal miRNAs with specific expression patterns in exosomes of HER2-positive and TNBC patients that are also associated with clinicopathological parameters and pCR within each BC subtype.
EVALuna2:210019

Spectrum and Frequency of Germline FANCM Protein-Truncating Variants in 44,803 European Female Breast Cancer Cases - Figlioli, Gisella; Billaud, Amandine; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; Lush, Michael; Kvist, Anders; Adank, Muriel A.; Ahearn, Thomas U.; Antonenkova, Natalia N.; Auvinen, Päivi; Behrens, Sabine; et al. (Cancers, 2023)
FANCM germline protein truncating variants (PTVs) are moderate-risk factors for ER-negative breast cancer. We previously described the spectrum of FANCM PTVs in 114 European breast cancer cases. In the present, larger cohort, we report the spectrum and frequency of four common and 62 rare FANCM PTVs found in 274 carriers detected among 44,803 breast cancer cases. We confirmed that p.Gln1701* was the most common PTV in Northern Europe with lower frequencies in Southern Europe. In contrast, p.Gly1906Alafs*12 was the most common PTV in Southern Europe with decreasing frequencies in Central and Northern Europe. We verified that p.Arg658* was prevalent in Central Europe and had highest frequencies in Eastern Europe. We also confirmed that the fourth most common PTV, p.Gln498Thrfs*7, might be a founder variant from Lithuania. Based on the frequency distribution of the carriers of rare PTVs, we showed that the FANCM PTVs spectra in Southwestern and Central Europe were much more heterogeneous than those from Northeastern Europe. These findings will inform the development of more efficient FANCM genetic testing strategies for breast cancer cases from specific European populations.
CRIS-Team Scopus Importer:2023-07-28
Keywords: breast cancer predisposition; breast cancer risk factors; FANCM PTVs spectrum; protein truncating variants; PTVs

Standard Changing News der Senologie und Gynäkologischen Onkologie - Rauh, Claudia; Jud, Sebastian; Hein, Alexander; Hack, Carolin; Fasching, Peter; Beckmann, Matthias; Lux, Michael P. (Klinikarzt, 2017)
CRIS-Team Scopus Importer:2021-07-19

Standardized evaluation of tumor-infiltrating lymphocytes in breast cancer: results of the ring studies of the international immuno-oncology biomarker working group - Denkert, Carsten; Wienert, Stephan; Poterie, Audrey; Loibl, Sibylle; Budczies, Jan; Badve, Sunil; Bago-Horvath, Zsuzsanna; Bane, Anita; Bedri, Shahinaz; Brock, Jane; Chmielik, Ewa; Christgen, Matthias; et al. (Modern Pathology, 2016)
Multiple independent studies have shown that tumor-infiltrating lymphocytes (TIL) are prognostic in breast cancer with potential relevance for response to immune-checkpoint inhibitor therapy. Although many groups are currently evaluating TIL, there is no standardized system for diagnostic applications. This study reports the results of two ring studies investigating TIL conducted by the International Working Group on Immuno-oncology Biomarkers. The study aim was to determine the intraclass correlation coefficient (ICC) for evaluation of TIL by different pathologists. A total of 120 slides were evaluated by a large group of pathologists with a web-based system in ring study 1 and a more advanced software-system in ring study 2 that included an integrated feedback with standardized reference images. The predefined aim for successful ring studies 1 and 2 was an ICC above 0.7 (lower limit of 95% confidence interval (CI)). In ring study 1 the prespecified endpoint was not reached (ICC: 0.70; 95% CI: 0.62-0.78). On the basis of an analysis of sources of variation, we developed a more advanced digital image evaluation system for ring study 2, which improved the ICC to 0.89 (95% CI: 0.85-0.92). The Fleiss' kappa value for <60 vs ≥60% TIL improved from 0.45 (ring study 1) to 0.63 in RS2 and the mean concordance improved from 88 to 92%. This large international standardization project shows that reproducible evaluation of TIL is feasible in breast cancer. This opens the way for standardized reporting of tumor immunological parameters in clinical studies and diagnostic practice. The software-guided image evaluation approach used in ring study 2 may be of value as a tool for evaluation of TIL in clinical trials and diagnostic practice. The experience gained from this approach might be applicable to the standardization of other diagnostic parameters in histopathology.
EVALuna2:33063

Standards Used by a Clinical and Scientific Endometriosis Center for the Diagnosis and Therapy of Patients with Endometriosis - Burghaus, Stefanie; Hildebrandt, Thomas; Fahlbusch, Christine; Heusinger, Katharina; Antoniadis, Sophia; Lermann, Johannes; Hackl, Janina; Häberle, Lothar; Renner, Stefan P.; Fasching, Peter; Beckmann, Matthias; Blum, Simon (Geburtshilfe und Frauenheilkunde, 2019)
Endometriosis is one of the most common benign gynecological diseases. The extremely heterogeneous complex of symptoms complicates the diagnosis and treatment of this disease. In most patients, there is a latency period of several years between the first occurrence of symptoms and the definitive diagnosis. This paper aims (1) to evaluate standards for the diagnosis and treatment of patients with (symptoms suspicious for) endometriosis in terms of feasibility, and (2) to assess the potential use of data collected by a certified clinical and scientific endometriosis center to answer scientific questions. Standards for outpatient consultations were developed for a special endometriosis outpatient clinic. Between January 2014 and December 2017, a total of 1715 outpatients with a suspicion of endometriosis presented to this special endometriosis outpatient clinic; the diagnosis and treatment of patients was carried out in accordance with the developed standards. Data of this patient cohort obtained from patient records created during outpatient consultations and from a questionnaire recorded in an Oracle-based database was analyzed. The patient cohort was also compared with another patient cohort who had attended different outpatient clinics and had been diagnosed intraoperatively with endometriosis. 41.8% of patients examined during special outpatient consultations had surgery for suspicion or recurrence of endometriosis. Endometriosis was confirmed in 81.5% of cases. Pain symptoms were the main indication for surgery in 70.1% of cases compared to 45.1% of cases in the comparison group. The structured approach used in the special endometriosis outpatient clinic is a key aspect of the care provided by the certified clinical and scientific endometriosis center. It ensures that patients are diagnosed and treated in accordance with guideline recommendations, that diagnosis and treatment comply with certification requirements, and that the collected data can be used to answer scientific questions.
CRIS-Team Scopus Importer:2019-06-04
Keywords: diagnostic; endometriosis; lower abdominal pain; sterility

Status quo and future directions of digitalization in gynecology and obstetrics in Germany: a survey of the commission Digital Medicine of the German Society for Gynecology and Obstetrics - Pfob, André; Hillen, Christoph; Seitz, Katharina; Griewing, Sebastian; Becker, Sven; Bayer, Christian; Wagner, Uwe; Fasching, Peter; Wallwiener, Markus (Archives of Gynecology and Obstetrics, 2024)
Purpose: Digitalization plays a critical role and is beginning to impact every part of the patient journey, from drug discovery and data collection to treatment and patient-reported outcomes. We aimed to evaluate the status quo and future directions of digital medicine in the specialty of gynecology and obstetrics in Germany. Methods: An anonymous questionnaire was distributed via the German Society of Gynecology and Obstetrics newsletter in December 2022. The questionnaire covered the domains baseline demographic information, telemedicine, digital health applications (DIGAs), and future expectations. Results: In all, 91 participants completed the survey. Median age was 34 years; 67.4% (60 of 89) were female and 32.6% (29 of 89) were male. About 10% (9 of 88) have prescribed DIGAs to date and 14% (12 of 86) offer telemedical appointments. Among those who do not use digital medicine, very few plan to do so in the near future. Reasons include missing software interfaces, lack of time to try out new things, lack of knowledge, lack of monetary compensation (66.3%), and employee concerns. A majority agreed that digitalization will help to save time and improve patient care and that intelligent algorithms will aid clinicians in providing patient care to women. Conclusions: The status quo and future directions of digital medicine in gynecology and obstetrics in Germany are characterized by contradicting expectations regarding the benefits of digital medicine and its actual implementation in clinical routine. This represents an important call to action to meet the requirements of modern patient care.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Artificial intelligence; Digital health; eHealth; Gynecology and obstetrics; Implementation

Style-Extracting Diffusion Models for Semi-supervised Histopathology Segmentation - Öttl, Mathias; Wilm, Frauke; Steenpaß, Jana; Qiu, Jingna; Rübner, Matthias; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Kainz, Bernhard; Breininger, Katharina (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2025)
Deep learning-based image generation has seen significant advancements with diffusion models, notably improving the quality of generated images. Despite these developments, generating images with unseen characteristics beneficial for downstream tasks has received limited attention. To bridge this gap, we propose Style-Extracting Diffusion Models, featuring two conditioning mechanisms. Specifically, we utilize 1) a style conditioning mechanism which allows to inject style information of previously unseen images during image generation and 2) a content conditioning which can be targeted to a downstream task, e.g., layout for segmentation. We introduce a trainable style encoder to extract style information from images, and an aggregation block that merges style information from multiple style inputs. This architecture enables the generation of images with unseen styles in a zero-shot manner, by leveraging styles from unseen images, resulting in more diverse generations. In this work, we use the image layout as target condition and first show the capability of our method on a natural image dataset as a proof-of-concept. We further demonstrate its versatility in histopathology, where we combine prior knowledge about tissue composition and unannotated data to create diverse synthetic images with known layouts. This allows us to generate additional synthetic data to train a segmentation network in a semi-supervised fashion. We verify the added value of the generated images by showing improved segmentation results and lower performance variability between patients when synthetic images are included during segmentation training. The code of the method is publicly available at https://github.com/OettlM/STEDM.
Created from Fastlane, Scopus look-up

Superpixel Pre-segmentation of HER2 Slides for Efficient Annotation - Öttl, Mathias; Mönius, Jana; Marzahl, Christian; Rübner, Matthias; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Informatik aktuell, 2022)
Supervised deep learning has shown state-of-the-art performance for medical image segmentation across different applications, including histopathology and cancer research; however, the manual annotation of such data is extremely laborious. In this work, we explore the use of superpixel approaches to compute a pre-segmentation of HER2 stained images for breast cancer diagnosis that facilitates faster manual annotation and correction in a second step. Four methods are compared: standard simple linear iterative clustering (SLIC) as a baseline, a domain adapted SLIC, and superpixels based on feature embeddings of a pretrained ResNet-50 and a denoising autoencoder. To tackle oversegmentation, we propose to hierarchically merge superpixels, based on their content in the respective feature space. When evaluating the approaches on fully manually annotated images, we observe that the autoencoder-based superpixels achieve a 23% increase in boundary F1 score compared to the baseline SLIC superpixels. Furthermore, the boundary F1 score increases by 73% when hierarchical clustering is applied on the adapted SLIC and the autoencoder-based superpixels. These evaluations show encouraging first results for a pre-segmentation for efficient manual refinement without the need for an initial set of annotated training data.<br
CRIS-Team Scopus Importer:2022-05-06

Supportive Infusions in Integrative Breast and Gynecological Oncology - Report on Patients' Satisfaction and Self-reported Effects and Side Effects - Hack, Carolin; Antoniadis, Sophia; Beckmann, Matthias; Brandl, Anna; Fasching, Peter; Hackl, Janina; Langemann, Hanna; Stock, Katja; Weber, Natalie; Theuser, Anna-Katharin (Geburtshilfe und Frauenheilkunde, 2018)
Background During cancer therapy, many patients suffer from malnutrition or vitamin deficiency. Treatment for nutrition-related deficiencies should therefore include nutritional therapy and possibly oral or intravenous substitution of micronutrients. Little information exists on multinutrient infusion therapies. The aim of this study was to develop standardized infusion protocols for integrative medicine infusions with micronutrients (IMed infusions) and to report on side effects of the treatment and patients' satisfaction with it. Methods For the IMed consultancy service, four special formulas for intravenous use were developed in cooperation with the pharmacy at Erlangen University Hospital. A retrospective cross-sectional study was conducted between October 2015 and January 2018 in which 45 patients with gynecological or breast cancer (BC) and IMed infusion therapy were included. Follow-up data were obtained from 20 patients using a standardized questionnaire on IMed infusions. Results A total of 280 IMed infusions were administered in the study period. The majority of the patients received an IMed regeneration infusion (78%). The majority of the patients had BC and were receiving chemotherapy. Most patients reported a high or very high level of satisfaction with the organization (60%), general treatment (65%) and counseling (85%). Subjective improvement in their disease-related and therapy-induced symptoms, such as fatigue, polyneuropathy and physical efficiency, was reported by 70% of the patients, while 75% reported a subjective increase in quality of life. Side effects were rare and minor. Conclusions Therapy with IMed infusions in women with BC or gynecological cancer requires the same standards set for drug therapy. Although vitamins represent dietary supplements, appropriate assessment of the patient's medical history is needed and patients must receive appropriate information. For this purpose, standardized processes, as in the context of an IMed consultancy service, are helpful.
EVALuna2:209954

Surgical outcome after neoadjuvant chemotherapy and bevacizumab: results from the GeparQuinto study (GBG 44) - Gerber, Bernd; Von Minckwitz, Gunter; Eidtmann, Holger; Rezai, Mahdi; Fasching, Peter; Tesch, Hans; Eggemann, Holm; Schrader, Iris; Kittel, Kornelia; Hanusch, Claus; Solbach, Christine; Jackisch, Christian; et al. (Annals of Surgical Oncology, 2014)
Bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor, has shown increased pathological complete response rates when added to neoadjuvant chemotherapy. In various cancer types, bevacizumab treatment was accompanied by an increased risk of bleedings and other surgical complications. We assessed associated surgical complications.In the GeparQuinto trial, 1,948 patients were randomized to receive four cycles epirubicin/cyclophosphamide (EC, 90/600 mg/m(2) q3w) followed by four cycles docetaxel (D, 100 mg/m(2) q3w) each with (ECB-DB) or without (EC-D) bevacizumab (B, 15 mg/kg q3w) concurrent with chemotherapy. Surgery had to be performed not earlier than 28 days after the last bevacizumab infusion, but within days 21 and 35 after the last chemotherapy.In 743 (38.1 %) patients, a surgical complication (bleedings, hematomas, necrosis, wound infections, abscess) was documented prospectively. Baseline characteristics of the patients were well balanced between both arms. The breast-conserving surgery (BCS) rate (N = 502) was 69.1 % (EC-D) and 71.9 % (ECB-DB; p = 0.464). The first surgical procedure was performed at a median of 29 (EC-D) and 34 days (ECB-DB) after last chemotherapy with or without bevacizumab infusion (p < 0.001). Surgical complications were documented in 38 (10.9 %; EC-D) and 59 (15.0 %; ECB-DB) patients (p = 0.103). Surgical complications were significantly higher after ECD-DB only in patients treated with BCS (N = 53; p = 0.029) or in those requiring repeat surgery in order achieve clear margins (N = 23; p = 0.037) compared to the EC-D group.Addition of bevacizumab to neoadjuvant chemotherapy might be associated with an increased risk for surgical complications in patients treated with BCS or after repeated surgeries.
EVALuna2:17510

Survival after adding capecitabine and trastuzumab to neoadjuvant anthracycline-taxane-based chemotherapy for primary breast cancer (GBG 40–GeparQuattro) - Von Minckwitz, G.; Rezai, M.; Fasching, Peter; Huober, J.; Tesch, H.; Bauerfeind, I.; Hilfrich, J.; Eidtmann, H.; Gerber, B.; Hanusch, C.; Blohmer, J. U.; Costa, S. D.; et al. (Annals of Oncology, 2014)
The GeparQuattro study showed that adding capecitabine or prolonging the duration of anthracycline-taxane-based neoadjuvant chemotherapy from 24 to 36 weeks did not increase pathological complete response (pCR) rates. Trastuzumab-treated patients with HER2-positive disease showed a higher pCR rate than patients with HER2-negative disease treated with chemotherapy alone. We here present disease-free (DFS) and overall survival (OS) analyses.Patients (n = 1495) with cT >= 3 tumors, or negative hormone-receptor status, or positive hormone-receptor and clinically node-positive disease received four times epirubicin/cyclophosphamide and were thereafter randomly assigned to four times docetaxel (Taxotere), or four times docetaxel/capecitabine over 24 weeks, or four times docetaxel followed by capecitabine over 36 weeks. Patients with HER2-positive tumors received 1 year of trastuzumab, starting with the first chemotherapy cycle. Follow-up was available for a median of 5.4 years.Outcome was not improved for patients receiving capecitabine (HR 0.92; P = 0.463 for DFS and HR 93; P = 0.618 for OS) as well as for patients receiving 36 weeks of chemotherapy (HR 0.97; P = 0.818 for DFS and HR 0.97; P = 0.825 for OS). Trastuzumab-treated patients with HER2-positive disease showed similar DFS (P = 0.305) but a significantly better adjusted OS (P = 0.040) when compared with patients with HER2-negative disease treated with chemotherapy alone. Recorded long-term cardiac toxicity was low.Long-term results, similar to the results of pCR, do not support the use of capecitabine in the neoadjuvant setting in addition to an anthracycline-taxane-based chemotherapy. However, the results support previous data showing a benefit of trastuzumab as predicted by higher pCR rates.
EVALuna2:17517

Survival after neoadjuvant chemotherapy with or without bevacizumab or everolimus for HER2-negative primary breast cancer (GBG 44-GeparQuinto)+ - Von Minckwitz, G.; Loibl, S.; Untch, M.; Eidtmann, H.; Rezai, M.; Fasching, Peter; Tesch, H.; Eggemann, H.; Schrader, I.; Kittel, K.; Hanusch, C.; Huober, J.; et al. (Annals of Oncology, 2014)
The GeparQuinto study showed that adding bevacizumab to 24 weeks of anthracycline-taxane-based neoadjuvant chemotherapy increases pathological complete response (pCR) rates overall and specifically in patients with triple-negative breast cancer (TNBC). No difference in pCR rate was observed for adding everolimus to paclitaxel in nonearly responding patients. Here, we present disease-free (DFS) and overall survival (OS) analyses.Patients (n = 1948) with HER2-negative tumors of a median tumor size of 4 cm were randomly assigned to neoadjuvant treatment with epirubicin/cyclophosphamide followed by docetaxel (EC-T) with or without eight infusions of bevacizumab every 3 weeks before surgery. Patients without clinical response to EC ± Bevacizumab were randomized to 12 weekly cycles paclitaxel with or without everolimus 5 mg/day. To detect a hazard ratio (HR) of 0.75 (? = 0.05, ? = 0.8) 379 events had to be observed in the bevacizumab arms.With a median follow-up of 3.8 years, 3-year DFS was 80.8% and 3-year OS was 89.7%. Outcome was not different for patients receiving bevacizumab (HR 1.03; P = 0.784 for DFS and HR 0.974; P = 0.842 for OS) compared with patients receiving chemotherapy alone. Patients with TNBC similarly showed no improvement in DFS (HR = 0.99; P = 0.941) and OS (HR = 1.02; P = 0.891) when treated with bevacizumab. No other predefined subgroup (HR+/HER2-; locally advanced (cT4 or cN3) or not; cT1-3 or cT4; pCR or not) showed a significant benefit. No difference in DFS (HR 0.997; P = 0.987) and OS (HR 1.11; P = 0.658) was observed for nonearly responding patients receiving paclitaxel with or without everolimus overall as well as in subgroups.Long-term results, in opposite to the results of pCR, do not support the neoadjuvant use of bevacizumab in addition to an anthracycline-taxane-based chemotherapy or everolimus in addition to paclitaxel for nonearly responding patients.NCT 00567554, www.clinicaltrials.gov.
EVALuna2:17516

Survival Analysis After Neoadjuvant Chemotherapy With Trastuzumab or Lapatinib in Patients With Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer in the GeparQuinto (G5) Study (GBG 44) - Untch, Michael; Von Minckwitz, Gunter; Gerber, Bernd; Schem, Christian; Rezai, Mahdi; Fasching, Peter; Tesch, Hans; Eggemann, Holm; Hanusch, Claus; Huober, Jens; Solbach, Christine; Jackisch, Christian; et al. (Journal of Clinical Oncology, 2018)
Purpose The GeparQuinto phase III trial demonstrated a lower pathologic complete response (pCR; pT0 ypN0) rate when lapatinib was added to standard anthracycline-taxane chemotherapy compared with trastuzumab in patients with human epidermal growth factor receptor 2 (HER2) -positive breast cancer. Here, we report the long-term outcomes. Methods Patients with HER2-positive tumors (n = 615) received neoadjuvant treatment with epirubicin (E) plus cyclophosphamide (C), followed by docetaxel (T) in combination with either lapatinib (L) or trastuzumab (H; ECH-TH arm: n = 307; ECL-TL arm: n = 308). All patients received adjuvant trastuzumab for a total of 12 months and 18 months in the ECH-TH and ECL-TL arms, respectively. Median follow-up was 55 months. Results Three-year disease-free survival (DFS), distant DFS (DDFS), and overall survival (OS) were not significantly different between the two treatment arms. Long-term outcomes correlated with pCR (DFS: hazard ratio [HR], 0.63; P = .042; DDFS: HR, 0.55; P = .021; and OS: HR, 0.31; P = .004). A benefit only for OS was observed in patients who were treated with trastuzumab and achieved pCR versus no pCR (HR, 0.15; P = .010), whereas no difference was found in patients with pCR versus without pCR in the lapatinib arm. DFS and DDFS remained unchanged in both treatment arms according to hormone receptor status, whereas OS was significantly better in hormone receptor-positive patients who were treated with neoadjuvant lapatinib (HR, 0.32; P = .019), followed by adjuvant trastuzumab. No difference was observed in hormone receptor-negative patients; however, the small number of events limits this interpretation. Within the hormone receptor-negative cohort, pCR was significantly associated with DFS, DDFS, and OS ( P = .002, .005, and .002, respectively). Conclusion pCR correlated with long-term outcome. In patients with hormone receptor-positive tumors, prolonged anti-HER2 treatment-neoadjuvant lapatinib for 6 months, followed by adjuvant trastuzumab for 12 months-significantly improved survival compared with anti-HER2 treatment with trastuzumab alone.
EVALuna2:56157

Survival analysis of carboplatin added to an anthracycline/taxane-based neoadjuvant chemotherapy and HRD score as predictor of response-final results from GeparSixto - Loibl, S.; Weber, K. E.; Timms, K. M.; Elkin, E. P.; Hahnen, E.; Fasching, Peter; Lederer, Bianca; Denkert, C.; Schneeweiss, A.; Braun, S.; Salat, C. T.; Rezai, M.; et al. (Annals of Oncology, 2018)
Background: In the neoadjuvant GeparSixto study, adding carboplatin to taxane- and anthracycline-based chemotherapy improved pathological complete response (pCR) rates in patients with triple-negative breast cancer (TNBC). Here, we present survival data and the potential prognostic and predictive role of homologous recombination deficiency (HRD). Patients and methods: Patients were randomized to paclitaxel plus nonpegylated liposomal doxorubicin (Myocet®) (PM) or PM plus carboplatin (PMCb). The secondary study end points disease-free survival (DFS) and overall survival (OS) were analyzed. Median follow-up was 47.3 months. HRD was among the exploratory analyses in GeparSixto and was successfully measured in formalin-fixed, paraffin-embedded tumor samples of 193/315 (61.3%) participants with TNBC. Homologous recombination (HR) deficiency was defined as HRD score ≥42 and/or presence of tumor BRCA mutations (tmBRCA). Results: A significantly better DFS (hazard ratio 0.56, 95% CI 0.34-0.93; P = 0.022) was observed in patients with TNBC when treated with PMCb. The improvement of OS with PMCb was not statistically significant. Additional carboplatin did not improve DFS or OS in patients with HER2-positive tumors. HR deficiency was detected in 136 (70.5%) of 193 triple-negative tumors, of which 82 (60.3%) showed high HRD score without tmBRCA. HR deficiency independently predicted pCR (ypT0 ypN0) [odds ratio (OR) 2.60, 95% CI 1.26-5.37, P = 0.008]. Adding carboplatin to PM significantly increased the pCR rate from 33.9% to 63.5% in HR deficient tumors (P = 0.001), but only marginally in HR nondeficient tumors (from 20.0% to 29.6%, P = 0.540; test for interaction P = 0.327). pCR rates with carboplatin were also higher (63.2%) than without carboplatin (31.7%; OR 3.69, 1.46-9.37, P = 0.005) in patients with high HRD score but no tmBRCA. DFS rates were improved with addition of carboplatin, both in HR nondeficient (hazard ratio 0.44, 0.17-1.17, P = 0.086) and HR deficient tumors (hazard ratio 0.49, 0.23-1.04, P = 0.059). Conclusions: The addition of carboplatin to neoadjuvant PM improved DFS significantly in TNBC. Long-term survival analyses support the neoadjuvant use of carboplatin in TNBC. HR deficiency in TNBC and HRD score in non-tmBRCA TNBC are predictors of response. HRD does not predict for carboplatin benefit.
EVALuna2:202797

Survival analysis of the randomised phase III GeparOcto trial comparing neoadjuvant chemotherapy of intense dose-dense epirubicin, paclitaxel, cyclophosphamide versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triple-negative breast cancer) for patients with high-risk early breast cancer - Schneeweiss, Andreas; Michel, Laura L.; Möbus, Volker; Tesch, Hans; Klare, Peter; Hahnen, Eric; Denkert, Carsten; Kast, Karin; Pohl-Rescigno, Esther; Hanusch, Claus; Link, Theresa; Untch, Michael; et al. (European Journal of Cancer, 2021)
Background: GeparOcto demonstrated that pathological complete response (pCR) of intense dose-dense epirubicin, paclitaxel and cyclophosphamide (iddEPC) was comparable to weekly paclitaxel/non-pegylated liposomal doxorubicin (plus carboplatin (PM(Cb) in triple-negative breast cancer [TNBC]) in high-risk early breast cancer (BC). Here, we report time-to-event secondary end-points. Patients and methods: Patients were randomised to receive 18 weeks of E (150 mg/m2) followed by P (225 mg/m2) followed by C (2000 mg/m2), each q2w or weekly P (80 mg/m2) plus M (20 mg/m2) plus, in TNBC, Cb (AUC 1.5). Patients with human epidermal growth factor receptor 2-positive (HER2+)BC received trastuzumab (6[loading dose 8]mg/kg q3w) and pertuzumab (420[840]mg q3w) with P and C cycles. Results: 945 patients started treatment (iddEPC n = 470; PM(Cb) n = 475). After a median follow-up of 47.0 (range 1.6–61.5) months, 162 (75 in iddEPC; 87 in PM(Cb)) invasive disease-free survival (iDFS) events and 79 (41 in iddEPC; 38 in PM(Cb)) deaths were reported. No significant difference was observed in 4-year iDFS (81.9% iddEPC versus 79.7% PM(Cb), HR = 1.16 [95%CI 0.85–1.59], log-rank p = 0.334) or 4-year overall survival (OS) (90.3% iddEPC versus 90.6% PM(Cb), HR = 0.90 [95%CI 0.58–1.40], log-rank p = 0.637) overall and in HER2+ and TNBC subgroups. HR+/HER2- BC patients, however, had significantly better 4-year iDFS (77.9% iddEPC versus 62.5% PM, HR = 2.11 [95%CI 1.08–4.10], log-rank p = 0.025) and 4-year OS with iddEPC (94.7% iddEPC versus 80.1% PM, HR = 3.26 [95%CI 1.06–10.00], log-rank p = 0.029). Conclusion: While there was no difference in survival for the entire cohort, the HR+/HER2-subgroup significantly benefits from iddEPC. This supports the concept of an additional effect of NACT beyond pCR in patients with HR+/HER2- BC. ClinicalTrials.gov identifier: NCT02125344.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Breast cancer; Dose-dense; Neoadjuvant chemotherapy; Survival

Survival analysis of the randomized phase III GeparOcto trial comparing neoadjuvant chemotherapy (NACT) of iddEPC versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triplenegative breast cancer, TNBC) (PM(Cb)) for patients (pts) with highrisk early breast cancer (BC) - Schneeweiss, A.; Moebus, V.; Tesch, H.; Klare, P.; Denkert, C.; Kast, K.; Hanusch, C.; Link, T.; Untch, M.; Jackisch, C.; Blohmer, J-U.; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

Systematic Comparison of ECG Delineation Algorithm Performance on Smartwatch Data - Jäger, Katharina; Nissen, Michael; Flaucher, Madeleine; Graf, Luisa; Joanidopoulos, Joana; Anneken, Lars; Hübner, Hanna; Goossens, Chloe; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; et al. (IEEE Access, 2024)
Cardiovascular diseases are the leading cause of global mortality, necessitating early detection and continuous monitoring for timely interventions. Smartwatches with electrocardiogram (ECG) recording capabilities enable real-time, at-home cardiac monitoring. Specific ECG characteristics can provide insights into cardiovascular diseases. The delineation of ECGs, which is the identification of fiducial points (such as onsets, offsets, and peaks), is a time-consuming task. Automated ECG delineation can enhance this process, but existing research comparing available algorithms is limited. Furthermore, to the best of our knowledge, none have addressed single-lead ECGs from smartwatches, which can be noisy and unfiltered. Thus, this study evaluates the best-performing open-source algorithm for single-lead and smartwatch ECG data. We used two public datasets (Lobachevsky University Database, QT Database) and two smartwatch datasets (SmartHeartWatch Dataset, SMART Start Dataset) including two devices (AppleWatch, Withings ScanWatch). Algorithms from three toolkits (NeuroKit, ECGKit, ECGdeli) were assessed based on the time deviation between algorithm outputs and reference annotations, sensitivity, true positives, and false negatives. Results were further evaluated against the Common Standards for Quantitative Electrocardiography (CSE) recommendations. ECGdeli outperformed the other algorithms. For QRS on- and offset, ECGkit shows comparable sensitivity, but otherwise lower scores. NeuroKit consistently shows lower sensitivity across all four data sets, however, the temporal deviation between detected point and reference was higher. Overall, sensitivity scores were higher for Apple Watch data compared to Withings ScanWatch data. This study demonstrates that segmentation algorithms are applicable to single-lead smartwatch ECG data, with ECGdeli being the most stable overall, and NeuroKit recommended for scenarios prioritizing the temporal accuracy of detected points.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Cardiovascular Diseases; ECG Segmentation; Mobile Health; Wearable Devices

Systemic Therapy of Premenopausal Patients with Early Stage Hormone Receptor-Positive, HER2-Negative Breast Cancer - Controversies and Standards in Healthcare - Müller, Volkmar; Fasching, Peter; Nabieva, Naiba; Fehm, Tanja N.; Thill, Marc; Schmidt, Marcus; Kühn, Thorsten; Banys-Paluchowski, Maggie; Belleville, Erik; Juhasz-Böss, Ingolf; Untch, Michael; Kolberg, Hans Christian; et al. (Geburtshilfe und Frauenheilkunde, 2023)
In patients with existing ovarian function, there are some special aspects to adjuvant endocrine therapy in premenopausal patients with hormone receptor-positive, HER2-negative (HR pos./HER2 neg.) breast cancer. Treatment options include tamoxifen with or without a GnRH analog, and aromatase inhibitors with a GnRH analog. Furthermore, ovarian function is affected by previous chemotherapy. Both aromatase inhibitors (+GnRH analogs) and GnRH analogs in combination with tamoxifen are supposed to be indicated for patients at increased risk of recurrence. However, national and international guidelines and therapy recommendations do not provide a clear definition of intermediate or high risk; as a result, therapy decisions are often made for each patient on an individual basis. This is also reflected in the considerable variability at national and international levels, e.g., with regard to the use of aromatase inhibitors + GnRH analogs. This review summarizes the data on completed studies (e.g., SOFT, TEXT, EBCTCG meta-analyses) and the current multigene testing studies (TailorX, RxPonder, ADAPT), discusses the rationale for current studies (e.g., CLEAR-B), and looks ahead to future questions.
CRIS-Team Scopus Importer:2023-06-23
Keywords: aromatase inhibitor; breast cancer; GnRH; premenopausal therapy; tamoxifen

Targeted Intraoperative Radiation Therapy Tumor Bed Boost During Breast-Conserving Surgery After Neoadjuvant Chemotherapy in TNBC and HER2 Positive Breast Cancer - Kolberg, H. C.; Loevey, G.; Akpolat-Basci, L.; Stephanou, M.; Fasching, Peter; Untch, M.; Liedtke, C.; Bulsara, M.; Vaidya, J. S. (2016)
EVALuna2:33059

Targeted Intraoperative Radiotherapy Tumour Bed Boost during Breast-Conserving Surgery after Neoadjuvant Chemotherapy - a Subgroup Analysis of Hormone Receptor-Positive HER2-Negative Breast Cancer - Kolberg, Hans-Christian; Loevey, Gyoergy; Akpolat-Basci, Leyla; Stephanou, Miltiades; Fasching, Peter; Untch, Michael; Hoffmann, Oliver; Bulsara, Max; Vaidya, Jayant S.; Liedtke, Cornelia (Breast Care, 2017)
Introduction: In a previous study our group showed a beneficial effect of targeted intraoperative radiotherapy (TARGIT-IORT) as an intraoperative boost on overall survival after neoadjuvant chemotherapy (NACT) compared to an external boost (EBRT). In this study we present the results of a detailed subgroup analysis of the hormone receptor (HR)-positive HER2-negative patients. Methods: In this cohort study involving 46 patients with HR-positive HER2-negative breast cancer after NACT, we compared the outcomes of 21 patients who received an IORT boost to those of 25 patients treated with an EBRT boost. All patients received whole breast radiotherapy. Results: Median follow-up was 49 months. Whereas disease-free-survival and breast cancer-specific mortality were not significantly different between the groups, the 5-year Kaplan-Meier estimate of overall mortality was significantly lower by 21% with IORT, p = 0.028. Non-breast cancer-specific mortality was significantly lower by 16% with IORT, p = 0.047. Conclusion: Although our results have to be interpreted with caution, we have shown that the improved overall survival demonstrated previously could be reproduced in the HR-positive HER2-negative subgroup. These data give further support to the inclusion of such patients in the TARGIT-B (Boost) randomised trial that is testing whether IORT boost is superior to EBRT boost.
EVALuna2:36209

Targeted intraoperative radiotherapy tumour bed boost during breast-conserving surgery after neoadjuvant chemotherapy - Kolberg, Hans-Christian; Loevey, Gyoergy; Akpolat-Basci, Leyla; Stephanou, Miltiades; Fasching, Peter; Untch, Michael; Liedtke, Cornelia; Bulsara, Max; Vaidya, Jayant S. (Strahlentherapie und Onkologie, 2017)
INTRODUCTION: The use of targeted intraoperative radiotherapy (TARGIT-IORT) as a tumour bed boost during breast-conserving surgery (BCS) for breast cancer has been reported since 1998. We present its use in patients undergoing breast conservation following neoadjuvant therapy (NACT). METHOD: In this retrospective study involving 116 patients after NACT we compared outcomes of 61 patients who received a tumour bed boost with IORT during lumpectomy versus 55 patients treated in the previous 13 months with external (EBRT) boost. All patients received whole breast radiotherapy. Local recurrence-free survival (LRFS), disease-free survival (DFS), distant disease-free survival (DDFS), breast cancer mortality (BCM), non-breast cancer mortality (NBCM) and overall mortality (OS) were compared. RESULTS: Median follow up was 49 months. The differences in LRFS, DFS and BCM were not statistically significant. The 5‑year Kaplan-Meier estimate of OS was significantly better by 15% with IORT: IORT 2 events (96.7%, 95%CI 87.5-99.2), EBRT 9 events (81.7%, 95%CI 67.6-90.1), hazard ratio (HR) 0.19 (0.04-0.87), log rank p = 0.016, mainly due to a reduction of 10.1% in NBCM: IORT 100%, EBRT 89.9% (77.3-95.7), HR (not calculable), log rank p = 0.015. The DDFS was as follows: IORT 3 events (95.1%, 85.5-98.4), EBRT 12 events (69.0%, 49.1-82.4), HR 0.23 (0.06-0.80), log rank p = 0.012. CONCLUSION: IORT during lumpectomy after neoadjuvant chemotherapy as a tumour bed boost appears to give results that are not worse than external beam radiotherapy boost. These data give further support to the inclusion of such patients in the TARGIT-B (boost) randomised trial that is testing whether IORT boost is superior to EBRT boost.
EVALuna2:36210

TGFB-induced factor homeobox 1 (TGIF) expression in breast cancer - Stuerken, Christine; Moebus, Volker; Milde-Langosch, Karin; Schmatloch, Sabine; Fasching, Peter; Rueschoff, Josef; Stickeler, Elmar; Henke, Rolf-Peter; Denkert, Carsten; Hanker, Lars; Schem, Christian; Vladimirova, Valentina; et al. (BMC Cancer, 2021)
Background: Breast cancer (BC) is the most frequent female cancer and preferentially metastasizes to bone. The transcription factor TGFB-induced factor homeobox 1 (TGIF) is involved in bone metabolism. However, it is not yet known whether TGIF is associated with BC bone metastasis or patient outcome and thus of potential interest.
CRIS-Team WoS Importer:2021-09-10

The association between prenatal alcohol consumption and preschool child stress system disturbance - Grimm, Jennifer; Stemmler, Mark; Golub, Yulia; Schwenke, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Developmental Psychobiology, 2021)
Background: Drinking alcohol during pregnancy is considered a risk factor for child development; however, child biomarkers of prenatal alcohol exposure have been rarely studied. We examined whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with child cortisol concentrations at primary school age. Methods: For 137 children, prenatal alcohol exposure was operationalized by the meconium biomarker EtG and by maternal self-reports during pregnancy. Two EtG cut-offs (EtG ≥10 ng/g and EtG ≥112 ng/g) were applied. Cortisol concentrations were measured in saliva and hair samples. Results: Children with EtG ≥10 ng/g showed significantly reduced hair cortisol concentrations (HCCs) (p =.050, (Formula presented.) = 0.042). For children with EtG ≥112 ng/g, the cortisol awakening response (CAR) was significantly decreased (p =.025, (Formula presented.) = 0.070). These effects were also present in correlational analyses with continuous EtG data, speaking for partly dose-dependent effects. Especially, within the EtG ≥112 ng/g group, the basal (CAR: rp = −.642, p =.120) and cumulative (HCC: rp = −.660, p =.107) cortisol parameters were associated with child emotional symptoms at medium effect size. Conclusions: The present study showed both the biological association of intrauterine alcohol exposure with the cortisol stress system, partly dose-dependent, and the functional association with emotional and behavioral symptoms.
CRIS-Team Scopus Importer:2020-10-16
Keywords: alcohol; biomarker; child; cortisol stress system; ethyl glucuronide; hypothalamus-pituitary-adrenal axis; intrauterine alcohol exposure; meconium; pregnancy

The Benefit of a Retrospective Pregnancy Anamnesis in Child and Adolescent Psychiatry: The Reliability of Maternal Self-Report during Childhood Development - Mestermann, Stefan; Fasching, Peter; Beckmann, Matthias; Gerlach, Jennifer; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Children, 2023)
Pregnancy anamnesis is a crucial part of child and adolescent psychiatry diagnostics. In previous works, the reliability of retrospective maternal self-report on perinatal characteristics was heterogeneous. This prospective longitudinal study aimed to evaluate women’s recall of prenatal events in a within-subject design. A sample of 241 women gave a self-report on prenatal alcohol, smoking, partnership quality, pregnancy satisfaction, and obstetric complications during the 3rd trimester (t0), childhood (t1, 6–10 y), and adolescence (t2, 12–14 y). The intra-individual agreement was examined. The t0–t1–(t2) agreement was poor to substantial; this was highest for smoking and worst for obstetric complications, followed by alcohol (Fleiss’ κ = 0.719 to −0.051). There were significant t0–t1–(t2) differences for all pregnancy variables (p < 0.017), except for 3rd trimester satisfaction (p = 0.256). For alcohol (t0 25.8%, t1 17.4%, t2 41.0%) and smoking (t0 11.9%, t1 16.4%, t2 22.6%), the highest self-reported rates were found during adolescence. During childhood, fewer obstetric complications (t0 84.9%, t1 42.2%) and worse partnerships were reported (t0 M = 8.86, t1 M = 7.89). Thought to be due to social stigmata and memory effects, pregnancy self-reports cannot be precisely reproduced. Creating a respectful and trusting atmosphere is essential for mothers to give honest self-reports that are in the best interest of their children.
CRIS-Team Scopus Importer:2023-06-30
Keywords: alcohol; partnership; pregnancy; pregnancy satisfaction; prenatal; retrospective; risk perceptions; self-report; smoking

The BRCA2 c.68-7T > A variant is not pathogenic: A model for clinical calibration of spliceogenicity - Colombo, Mara; Lopez-Perolio, Irene; Meeks, Huong D.; Caleca, Laura; Parsons, Michael T.; Li, Hongyan; De Vecchi, Giovanna; Tudini, Emma; Foglia, Claudia; Mondini, Patrizia; Manoukian, Siranoush; Behar, Raquel; et al. (Human Mutation, 2018)
Although the spliceogenic nature of the BRCA2 c.68-7T > A variant has been demonstrated, its association with cancer risk remains controversial. In this study, we accurately quantified by real-time PCR and digital PCR (dPCR), the BRCA2 isoforms retaining or missing exon 3. In addition, the combined odds ratio for causality of the variant was estimated using genetic and clinical data, and its associated cancer risk was estimated by case-control analysis in 83,636 individuals. Co-occurrence in trans with pathogenic BRCA2 variants was assessed in 5,382 families. Exon 3 exclusion rate was 4.5-fold higher in variant carriers (13%) than controls (3%), indicating an exclusion rate for the c.68-7T > A allele of approximately 20%. The posterior probability of pathogenicity was 7.44 × 10-115 . There was neither evidence for increased risk of breast cancer (OR 1.03; 95% CI 0.86-1.24) nor for a deleterious effect of the variant when co-occurring with pathogenic variants. Our data provide for the first time robust evidence of the nonpathogenicity of the BRCA2 c.68-7T > A. Genetic and quantitative transcript analyses together inform the threshold for the ratio between functional and altered BRCA2 isoforms compatible with normal cell function. These findings might be exploited to assess the relevance for cancer risk of other BRCA2 spliceogenic variants.
EVALuna2:202794

The Chorioallantoic Membrane Xenograft Assay as a Reliable Model for Investigating the Biology of Breast Cancer - Ranjan, Raphela A.; Muenzner, Julienne K.; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Walther, Wolfgang; Eckstein, Markus; et al. (Cancers, 2023)
The chorioallantoic membrane (CAM) assay is an alternative in vivo model that allows for minimally invasive research of cancer biology. Using the CAM assay, we investigated phenotypical and functional characteristics (tumor grade, mitosis rate, tumor budding, hormone receptor (HR) and HER2 status, Ki-67 proliferation index) of two breast cancer cell lines, MCF-7 and MDA-MB-231, which resemble the HR+ (luminal) and triple-negative breast cancer (TNBC) subgroups, respectively. Moreover, the CAM results were directly compared with murine MCF-7- and MDA-MB-231-derived xenografts and human patient TNBC tissue. Known phenotypical and biological features of the aggressive triple-negative breast cancer cell line (MDA-MB-231) were confirmed in the CAM assay, and mouse xenografts. Furthermore, the histomorphological and immunohistochemical variables assessed in the CAM model were similar to those in human patient tumor tissue. Given the confirmation of the classical biological and growth properties of breast cancer cell lines in the CAM model, we suggest this in vivo model to be a reliable alternative test system for breast cancer research to reduce murine animal experiments.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3R; alternative in vivo model; CAM model; hormone receptor; HTB-26; MCF-7; MDA-MB-231; mouse xenograft; tumor aggressiveness

The clinical data intelligence project - Sonntag, Daniel; Tresp, Volker; Zillner, Sonja; Hammon, Matthias; Reis, André; Fasching, Peter; Sedlmayr, Martin; Ganslandt, Thomas; Prokosch, Hans-Ulrich; Budde, Clemens; Schmidt, Danilo; Hinrichs, Carl; et al. (Informatik-Spektrum, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.IMMD.infome.thecli

The clinical relevance of serum vascular endothelial growth factor (VEGF) in correlation to circulating tumor cells and other serum biomarkers in patients with metastatic breast cancer - Banys-Paluchowski, Malgorzata; Witzel, Isabell; Riethdorf, Sabine; Pantel, Klaus; Rack, Brigitte; Janni, Wolfgang; Fasching, Peter; Aktas, Bahriye; Kasimir-Bauer, Sabine; Hartkopf, Andreas; Solomayer, Erich-Franz; Fehm, Tanja; et al. (Breast Cancer Research and Treatment, 2018)
VEGF is one of the most important angiogenesis-stimulating cytokines and has been previously shown to be overexpressed in several solid cancers. The aim of the present study was to assess the clinical relevance of serum VEGF (sVEGF) in a large cohort of metastatic breast cancer patients and to explore the relationship between sVEGF and other blood-based biomarkers.Two hundred fifty-three patients with metastatic breast cancer were enrolled in this prospective, multicentre study. Blood samples were collected before start of first-line or later-line treatment. sVEGF was quantified by a commercially available ELISA. Circulating tumor cells (CTCs) were detected using CellSearch and other biomarkers (EGFR, HER2, RAS p21, TIMP1, CAIX) by ELISA.Levels of sVEGF were determined in all patients, with a median concentration of 231 pg/ml. After a median follow-up of 19 months, median overall survival (OS) was 10.2 months in patients with sVEGF levels above the upper quartile (i.e. 367 pg/ml), while median OS has not been reached in patients with sVEGF < 367 pg/ml (p < 0.001). Median progression-free survival (PFS) was 4.8 months for patients with sVEGF >= 367 pg/ml versus 9.1 months with sVEGF levels < 367 pg/ml (p < 0.001). Patients with sVEGF levels >= 367 pg/ml and >= 5 CTCs had the shortest OS, while those with sVEGF < 367 pg/ml and non-elevated CTCs had the longest OS. CTCs, grading, line of therapy and RAS p21 were independent predictors of OS. sVEGF, line of therapy and CTCs were independent predictors of PFS in the multivariate analysis.Metastatic breast cancer patients with elevated levels of sVEGF have significantly worse clinical outcome. This finding supports the biological role of VEGF in breast cancer.Current Controlled Trials ISRCTN59722891 (DETECT).
EVALuna2:51629

The contributions of breast density and common genetic variation to breast cancer risk - Vachon, Celine M.; Pankratz, V. Shane; Scott, Christopher G.; Häberle, Lothar; Ziv, Elad; Jensen, Matthew R.; Brandt, Kathleen R.; Whaley, Dana H.; Olson, Janet E.; Heusinger, Katharina; Hack, Carolin; Jud, Sebastian; et al. (Journal of the National Cancer Institute, 2015)
We evaluated whether a 76-locus polygenic risk score (PRS) and Breast Imaging Reporting and Data System (BI-RADS) breast density were independent risk factors within three studies (1643 case patients, 2397 control patients) using logistic regression models. We incorporated the PRS odds ratio (OR) into the Breast Cancer Surveillance Consortium (BCSC) risk-prediction model while accounting for its attributable risk and compared five-year absolute risk predictions between models using area under the curve (AUC) statistics. All statistical tests were two-sided. BI-RADS density and PRS were independent risk factors across all three studies (P interaction = .23). Relative to those with scattered fibroglandular densities and average PRS (2(nd) quartile), women with extreme density and highest quartile PRS had 2.7-fold (95% confidence interval [CI] = 1.74 to 4.12) increased risk, while those with low density and PRS had reduced risk (OR = 0.30, 95% CI = 0.18 to 0.51). PRS added independent information (P < .001) to the BCSC model and improved discriminatory accuracy from AUC = 0.66 to AUC = 0.69. Although the BCSC-PRS model was well calibrated in case-control data, independent cohort data are needed to test calibration in the general population.
EVALuna2:14513

The DETECT Study Concept - Metastatic breast cancer and circulating tumor cells - Schramm, A.; Friedl, T.; Rack, B.; Trapp, E.; Fasching, Peter; Taran, F-A.; Hartkopf, A.; Schneeweiss, A.; Mueller, V.; Aktas, B.; Pantel, K.; Meier-Stiegen, F.; et al. (2016)
EVALuna2:33104

The effect of participation in neoadjuvant clinical trials on outcomes in patients with early breast cancer - Brennan, Meghan; Gaß, Paul; Häberle, Lothar; Wang, Daidong; Hartmann, Arndt; Lux, Michael P.; Beckmann, Matthias; Untch, Michael; Fasching, Peter (Breast Cancer Research and Treatment, 2018)
BACKGROUND: Clinical trials can offer novel and more advanced and/or novel treatments to cancer patients in advance of them being approved and available for all patients. While several studies have examined the effect of clinical trial participation on prognosis, there has been no clear conclusion from these studies. Therefore, we chose to test the influence of trial participation on pathological complete response (pCR) and mastectomy rates after neoadjuvant chemotherapy. METHODS: In this retrospective study, all patients treated with neoadjuvant chemotherapy from 2001 to 2014 were selected. A total of 1038 patients with complete treatment, patient, and tumor characteristics were included. A total of 260 of those were treated in clinical trials. We examined whether study participation status in addition to commonly known predictors for pCR improves prediction of pCR. Similar analyses were conducted for the mastectomy rate outcome measure. Finally, survival analyses were also conducted as part of an exploratory analysis. RESULTS: Study participation was an independent predictor of pCR in addition to commonly known predictors. Adjusted odds ratio (OR) for trial participants versus non-participants was 1.53 (95% CI 1.03-2.28). Additionally, study participation improved the prediction of mastectomy risk. The adjusted OR for trial participants versus non-participants was 0.62 (95% CI 0.42-0.90). Subgroup-specific differences concerning the impact of study participation could not be shown for either pCR or mastectomy rate. Survival comparisons could not be conducted due to large differences in follow-up data in patients participating in clinical trials versus those who did not participate; however, pCR was a predictor of prognosis in both groups. CONCLUSION: Patients taking part in neoadjuvant chemotherapy clinical trials have a higher pCR rate and a lower mastectomy risk than patients not participating in clinical trials for their cancer care. This finding is a supporting factor for trial participation in neoadjuvant chemotherapy trials.
EVALuna2:34852

The FANCM:p.Arg658* truncating variant is associated with risk of triple-negative breast cancer - Figlioli, Gisella; Bogliolo, Massimo; Catucci, Irene; Caleca, Laura; Lasheras, Sandra Viz; Pujol, Roser; Kiiski, Johanna I.; Muranen, Taru A.; Barnes, Daniel R.; Dennis, Joe; Michailidou, Kyriaki; Bolla, Manjeet K.; et al. (npj Breast Cancer, 2019)
Breast cancer is a common disease partially caused by genetic risk factors. Germline pathogenic variants in DNA repair genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 are associated with breast cancer risk. FANCM, which encodes for a DNA translocase, has been proposed as a breast cancer predisposition gene, with greater effects for the ER-negative and triple-negative breast cancer (TNBC) subtypes. We tested the three recurrent protein-truncating variants FANCM:p.Arg658*, p.Gln1701*, and p.Arg1931* for association with breast cancer risk in 67,112 cases, 53,766 controls, and 26,662 carriers of pathogenic variants of BRCA1 or BRCA2. These three variants were also studied functionally by measuring survival and chromosome fragility in FANCM−/− patient-derived immortalized fibroblasts treated with diepoxybutane or olaparib. We observed that FANCM:p.Arg658* was associated with increased risk of ER-negative disease and TNBC (OR = 2.44, P = 0.034 and OR = 3.79; P = 0.009, respectively). In a country-restricted analysis, we confirmed the associations detected for FANCM:p.Arg658* and found that also FANCM:p.Arg1931* was associated with ER-negative breast cancer risk (OR = 1.96; P = 0.006). The functional results indicated that all three variants were deleterious affecting cell survival and chromosome stability with FANCM:p.Arg658* causing more severe phenotypes. In conclusion, we confirmed that the two rare FANCM deleterious variants p.Arg658* and p.Arg1931* are risk factors for ER-negative and TNBC subtypes. Overall our data suggest that the effect of truncating variants on breast cancer risk may depend on their position in the gene. Cell sensitivity to olaparib exposure, identifies a possible therapeutic option to treat FANCM-associated tumors.
CRIS-Team Scopus Importer:2019-11-12

The Father’s Part: Influences of Paternal Psychopathology and Parenting Behavior on Child and Adolescent Well-Being - Mestermann, Stefan; Arndt, Marie; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Healthcare, 2023)
Family influences on child quality of life (QoL) are increasingly understood. Parenting behavior and parent individual psychopathology are among the established predictors of offspring mental health. However, literature often addresses these factors as ‘parental’, lacking further gender-specific differentiation while predominantly studying maternal aspects. Social and biological fathers are still underrepresented in family research. The aim of this study was to analyze paternal contributions to child well-being. A total of 197 father/mother-dyads gave a standardized self-report on parenting behavior and their own psychopathology at child primary school age (t1; 6–10 y). Ratings were compared mutually and associated with child self-rated QoL at t1 and adolescence (t2; 12–14 y). Fathers and mothers differed in psychopathology and most parenting behavior dimensions (positive parenting, involvement, responsible parenting, poor monitoring, and corporal punishment). Father psychopathology made a relevant predictive contribution to girls’ QoL at t2. Boys’ t1 QoL was significantly influenced by maternal parenting factors (positivity and corporal punishment). Compared to mothers, fathers are faced with different individual stressors; paternal parenting behavior is different, while fathers’ influences are significant, particularly for daughters. Father-addressed pre- and intervention programs in child psychotherapeutic treatment are of high relevance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: child development; father; parent-child-relations; parental influence; parenting; parenting behavior; resilience

The genetic interplay between body mass index, breast size and breast cancer risk: a Mendelian randomization analysis - Ooi, Brandon Nick Sern; Loh, Huiwen; Ho, Peh Joo; Milne, Roger L.; Giles, Graham; Gao, Chi; Kraft, Peter; John, Esther M.; Swerdlow, Anthony; Brenner, Hermann; Wu, Anna H.; Haiman, Christopher; et al. (International Journal of Epidemiology, 2019)
BACKGROUND: Evidence linking breast size to breast cancer risk has been inconsistent, and its interpretation is often hampered by confounding factors such as body mass index (BMI). Here, we used linkage disequilibrium score regression and two-sample Mendelian randomization (MR) to examine the genetic associations between BMI, breast size and breast cancer risk. METHODS: Summary-level genotype data from 23andMe, Inc (breast size, n = 33 790), the Breast Cancer Association Consortium (breast cancer risk, n = 228 951) and the Genetic Investigation of ANthropometric Traits (BMI, n = 183 507) were used for our analyses. In assessing causal relationships, four complementary MR techniques [inverse variance weighted (IVW), weighted median, weighted mode and MR-Egger regression] were used to test the robustness of the results. RESULTS: The genetic correlation (rg) estimated between BMI and breast size was high (rg = 0.50, P = 3.89x10-43). All MR methods provided consistent evidence that higher genetically predicted BMI was associated with larger breast size [odds ratio (ORIVW): 2.06 (1.80-2.35), P = 1.38x10-26] and lower overall breast cancer risk [ORIVW: 0.81 (0.74-0.89), P = 9.44x10-6]. No evidence of a relationship between genetically predicted breast size and breast cancer risk was found except when using the weighted median and weighted mode methods, and only with oestrogen receptor (ER)-negative risk. There was no evidence of reverse causality in any of the analyses conducted (P > 0.050). CONCLUSION: Our findings indicate a potential positive causal association between BMI and breast size and a potential negative causal association between BMI and breast cancer risk. We found no clear evidence for a direct relationship between breast size and breast cancer risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: body mass index; breast cancer risk; Breast size; genetic correlation; genetic epidemiology; LDSC regression; Mendelian randomization

The HER2 phenotype of circulating tumor cells in HER2-positive early breast cancer: A translational research project of a prospective randomized phase III trial - Jaeger, B. A. S.; Neugebauer, J.; Andergassen, U.; Melcher, C.; Schochter, F.; Mouarrawy, D.; Ziemendorff, G.; Clemens, M.; Abel, E. V.; Heinrich, G.; Schueller, K.; Schneeweiss, A.; et al. (PLoS ONE, 2017)
BACKGROUND: HER2 is one of the predominant therapeutic targets in breast cancer. The metastatic selection process may lead to discrepancies between the HER2 status of the primary tumor and circulating tumor cells (CTCs). This study analyzed the HER2 status of CTCs in patients with HER2-positive primary breast cancer at the time of diagnosis. Aim of the study was to assess potential discordance of HER2 status between primary tumor and CTCs, as this may have important implications for the use of HER2-targeted therapy. METHODS: The number and HER2 status of CTCs out of 30ml peripheral blood were assessed in 642 patients using the CellSearch System (Janssen Diagnostics, USA). The cutoff for CTC positivity was the presence of at least 1 CTC, and the cutoff for HER2 positivity of CTCs was the presence of at least 1 CTC with a strong HER2 staining. RESULTS: 258 (40.2%) of the 642 patients were positive for CTCs (median 2; range 1-1,689). 149 (57.8%) of these 258 patients had at least 1 CTC with strong HER2 staining. The presence of HER2-positive CTCs was not associated with tumor size (p = 0.335), histopathological grading (p = 0.976), hormone receptor status (ER: p = 0.626, PR: p = 0.263) or axillary lymph node involvement (p = 0.430). Overall, 83 (32.2%) of the CTC-positive patients exclusively had CTCs with strong HER2 staining, whereas 31 (12.0%) had only CTCs with negative HER2 staining. Within-sample variation in the HER2 status of CTCs was found in 86 (57.8%) of the 149 patients with more than 1 CTC. CONCLUSION: This study demonstrated that discordance between the HER2 expression of CTCs and that of the primary tumor frequently occurs in early breast cancer. Future follow-up evaluation will assess whether this discrepancy may contribute to trastuzumab resistance.
EVALuna2:36134

The impact of anthracyclines in intermediate and high-risk HER2-negative early breast cancer-a pooled analysis of the randomised clinical trials PlanB and SUCCESS C - De Gregorio, Amelie; Janni, Wolfgang; Friedl, Thomas W. P.; Nitz, Ulrike; Rack, Brigitte; Schneeweiss, Andreas; Kates, Ronald; Fehm, Tanja; Kreipe, Hans; Christgen, Matthias; Kuemmel, Sherko; Trapp, Elisabeth; et al. (British Journal of Cancer, 2022)
Background Anthracycline/cyclophosphamide-taxane-containing chemotherapy (AC-T) is the standard of care in the adjuvant treatment of HER2-negative early breast cancer (EBC), but recent studies suggest omission of anthracyclines for reduced toxicity without compromising efficacy. Methods Based on individual patient data (n = 5924) pooled from the randomised Phase III trials PlanB and SUCCESS C, we compared disease-free survival (DFS) and overall survival (OS) between intermediate to high-risk HER2-negative EBC-patients treated with either six cycles of docetaxel/cyclophosphamide (TC6) or an AC-T regime using univariable and adjusted multivariable Cox regression models. Results AC-T conferred no significant DFS or OS advantage in univariable (DFS: hazard ratio (HR) for TC vs. AT 1.05, 95% confidence interval (CI): 0.89-1.24, P = 0.57; OS: HR 1.00, 95% CI: 0.80-1.26, P = 1.00) and adjusted multivariable analysis (DFS: HR 1.01, 95% CI: 0.86-1.19, P = 0.91; OS: HR 0.97, 95% CI: 0.77-1.22, P = 0.79). Patients receiving TC6 had significantly fewer grade 3-4 adverse events. Exploratory subgroup analysis showed that AC-T was associated with significantly better DFS and OS in pN2/3 patients, specifically in those with lobular histology. Conclusion For most patients with HER2-negative EBC, AC-T is not associated with a survival benefit compared to TC6. However, patients with lobular pN2/pN3 tumours seem to benefit from anthracycline-containing chemotherapy.
CRIS-Team WoS Importer:2022-03-18

The impact of mammalian target of rapamycin inhibition on bone health in postmenopausal women with hormone receptor-positive advanced breast cancer receiving everolimus plus exemestane in the phase IIIb 4EVER trial - Hadji, Peyman; Stoetzer, Oliver; Decker, Thomas; Kurbacher, Christian M.; Marme, Frederik; Schneeweiss, Andreas; Mundhenke, Christoph; Distelrath, Andrea; Fasching, Peter; Lux, Michael P.; Lueftner, Diana; Janni, Wolfgang; et al. (Journal of Bone Oncology, 2019)
Background: Breast cancer and its treatments are associated with a detrimental effect on bone health. Here we report the results of an exploratory analysis assessing changes in levels of biomarkers of bone metabolism in patients enrolled in the phase IIIb 4EVER study.
CRIS-Team WoS Importer:2019-03-20

The impact of physical activity on progression-free and overall survival in metastatic breast cancer based on molecular subtype - Ziegler, Philipp; Hartkopf, Andreas D.; Wallwiener, Markus; Häberle, Lothar; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lüftner, Diana; Müller, Volkmar; Michel, Laura L.; Belleville, Erik; et al. (BMC Cancer, 2024)
Background: Although adequate physical activity has been shown to be beneficial in early breast cancer, evidence in metastatic breast cancer is sparse and contradictory, which could be related to distinct effects of physical activity on the different molecular cancer subtypes. Therefore, we here evaluated the effect of physical activity on progression-free and overall survival (PFS, OS) in metastatic breast cancer, specifically looking at molecular subtypes. Methods: International Physical Activity Questionnaire (IPAQ) questionnaires, filled out by patients enrolled in the prospective PRAEGNANT registry (NCT02338167; n = 1,270) were used to calculate metabolic equivalent task (MET) minutes, which were subsequently categorized into low (n = 138), moderate (n = 995) or high IPAQ categories (n = 137). Cox regression analyses were used to evaluate the impact of IPAQ categories and its interaction with molecular subtypes on PFS and OS. Results: Patient and tumor characteristics were equally distributed across IPAQ categories. HER2pos, HRpos and TNBC were present in 23.1%, 65.7% and 11.2% of patients, respectively. IPAQ scores did not have an impact on PFS and OS in addition to established prognostic factors, either overall or in particular molecular subtypes (PFS: p = 0.33 and OS: p = 0.08, likelihood ratio test). Exploratory analyses showed higher overall survival rates for high IPAQ categories compared to low/moderate IPAQ categories in luminal B-like breast cancer. Conclusions: Self-reported physical activity using the IPAQ questionnaire did not significantly affect PFS or OS in patients suffering from metastatic breast cancer. Nevertheless, some hypothesis-generating differences between molecular subtypes could be observed, which may be interesting to evaluate further.
CRIS-Team Scopus Importer:2024-10-25
Keywords: IPAQ; Metastatic breast cancer; Molecular subtype; Physical activity

The influence of obesity on survival in early, high-risk breast cancer: results from the randomized SUCCESS A trial - Widschwendter, Peter; Friedl, Thomas W. P.; Schwentner, Lukas; Degregorio, Nikolaus; Jaeger, Bernadette; Schramm, Amelie; Bekes, Inga; Deniz, Miriam; Lato, Krisztian; Weissenbacher, Tobias; Kost, Bernd; Andergassen, Ulrich; et al. (Breast Cancer Research, 2015)
Obese breast cancer patients have worse prognosis than normal weight patients, but the level at which obesity is prognostically unfavorable is unclear.This retrospective analysis was performed using data from the SUCCESS A trial, in which 3754 patients with high-risk early breast cancer were randomized to anthracycline- and taxane-based chemotherapy with or without gemcitabine. Patients were classified as underweight/normal weight (body mass index (BMI) < 25.0), overweight (BMI 25.0-29.9), slightly obese (BMI 30.0-34.9), moderately obese (BMI 35.0-39.9) and severely obese (BMI >= 40.0), and the effect of BMI on disease-free survival (DFS) and overall survival (OS) was evaluated (median follow-up 65 months). In addition, subgroup analyses were conducted to assess the effect of BMI in luminal A-like, luminal B-like, HER2 (human epidermal growth factor 2)-positive and triple-negative tumors.Multivariate analyses revealed an independent prognostic effect of BMI on DFS (p = 0.001) and OS (p = 0.005). Compared with underweight/normal weight patients, severely obese patients had worse DFS (hazard ratio (HR) 2.70, 95 % confidence interval (CI) 1.71-4.28, p < 0.001) and OS (HR 2.79, 95 % CI 1.63-4.77, p < 0.001), while moderately obese, slightly obese and overweight patients did not differ from underweight/normal weight patients with regard to DFS or OS. Subgroup analyses showed a similar significant effect of BMI on DFS and OS in patients with triple-negative breast cancer (TNBC), but not in patients with other tumor subtypes.Severe obesity (BMI >= 40) significantly worsens prognosis in early breast cancer patients, particularly for triple-negative tumors.Clinicaltrials.gov NCT02181101 . Registered September 2005.
EVALuna2:17573

The influence of prenatal risks on attachment, emotion regulation and emotional and behavioral problems in middle childhood: A prospective longitudinal study - Ziegler, Clara; Zalan, Vera; Eichler, Anna; Heinrich, Hartmut; Moll, Gunther; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Lenz, Bernd; Spangler, Gottfried (International Attachment Conference, 2017)

The integrative epigenomic-transcriptomic landscape of ER positive breast cancer - Gao, Yang; Jones, Allison; Fasching, Peter; Rübner, Matthias; Beckmann, Matthias; Widschwendter, Martin; Teschendorff, Andrew E. (Clinical Epigenetics, 2015)
While recent integrative analyses of copy number and gene expression data in breast cancer have revealed a complex molecular landscape with multiple subtypes and many oncogenic/tumour suppressor driver events, much less is known about the role of DNA methylation in shaping breast cancer taxonomy and defining driver events.Here, we applied a powerful integrative network algorithm to matched DNA methylation and RNA-Seq data for 724 estrogen receptor (ER)-positive (ER+) breast cancers and 111 normal adjacent tissue specimens from The Cancer Genome Atlas (TCGA) project, in order to identify putative epigenetic driver events and to explore the resulting molecular taxonomy. This revealed the existence of nine functionally deregulated epigenetic hotspots encompassing a total of 146 genes, which we were able to validate in independent data sets encompassing over 1000 ER+ breast cancers. Integrative clustering of the matched messenger RNA (mRNA) and DNA methylation data over these genes resulted in only two clusters, which correlated very strongly with the luminal-A and luminal B subtypes. Overall, luminal-A and luminal-B breast cancers shared the same epigenetically deregulated hotspots but with luminal-B cancers exhibiting increased aberrant DNA methylation patterns relative to normal tissue. We show that increased levels of DNA methylation and mRNA expression deviation from the normal state define a marker of poor prognosis. Our data further implicates epigenetic silencing of WNT signalling antagonists and bone morphogenetic proteins (BMP) as key events underlying both luminal subtypes but specially of luminal-B breast cancer. Finally, we show that DNA methylation changes within the identified epigenetic interactome hotspots do not exhibit mutually exclusive patterns within the same cancer sample, instead exhibiting coordinated changes within the sample.Our results indicate that the integrative DNA methylation and transcriptomic landscape of ER+ breast cancer is surprisingly homogeneous, defining two main subtypes which strongly correlate with luminal-A/B subtype status. In particular, we identify WNT and BMP signalling as key epigenetically deregulated tumour suppressor pathways in luminal ER+ breast cancer, with increased deregulation seen in luminal-B breast cancer.
EVALuna2:17561

The International Endometriosis Evaluation Program (IEEP Study) - A Systematic Study for Physicians, Researchers and Patients - Burghaus, Stefanie; Fehm, T.; Fasching, Peter; Blum, Simon; Renner, Stefan; Baier, F.; Brodkorb, T.; Fahlbusch, C.; Findeklee, S.; Häberle, Lothar; Heusinger, K.; Hildebrandt, T.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
INTRODUCTION: Endometriosis is a heterogeneous disease characterized by a range of different presentations. It is usually diagnosed when patients present with pain and/or infertility, but it has also been diagnosed in asymptomatic patients. Because of the different diagnostic approaches and diverse therapies, time to diagnosis can vary considerably and the definitive diagnosis may be delayed, with some cases not being diagnosed for several years. Endometriosis patients have many unmet needs. A systematic registration and follow-up of endometriosis patients could be useful to obtain an insight into the course of the disease. The validation of biomarkers could contribute to the development of diagnostic and predictive tests which could help select patients for surgical assessment earlier and offer better predictions about patients who might benefit from medical, surgical or other interventions. The aim is also to obtain a better understanding of the etiology, pathogenesis and progression of the disease. MATERIAL AND METHODS: To do this, an online multicenter documentation system was introduced to facilitate the establishment of a prospective multicenter case-control study, the IEEP (International Endometriosis Evaluation Program) study. We report here on the first 696 patients with endometriosis included in the program between June 2013 and June 2015. RESULTS: A documentation system was created, and the structure and course of the study were mapped out with regard to data collection and the collection of biomaterials. CONCLUSION: The documentation system permits the history and clinical data of patients with endometriosis to be recorded. The IEEP combines this information with biomaterials and uses it for scientific studies. The recorded data can also be used to evaluate clinical quality control measures such as the certification parameters used by the EEL (European Endometriosis League) to assess certified endometriosis centers.
EVALuna2:32966

The PI3K Pathway: Background and Treatment Approaches - Lux, Michael P.; Fasching, Peter; Schrauder, Michael G.; Hein, Alexander; Jud, Sebastian; Rauh, Claudia; Beckmann, Matthias (Breast Care, 2016)
Two-thirds of all breast cancer patients with metastases have a hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative subtype. Endocrine therapy is the treatment of choice in these patients since in addition to its effectiveness it can also maintain the patients' quality of life over a longer term. However, 44-62% of postmenopausal patients with metastatic breast carcinoma have primary tamoxifen resistance. After 3-5 years, 30-40% of the patients receiving tamoxifen treatment develop secondary resistance. Understanding the way in which resistance develops is therefore essential for developing treatment approaches that can prevent or reverse endocrine resistance. The phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway plays a central role here. As a result of the numerous interactions involved, complex issues arise that need to be taken into account in the development and use of therapeutic agents. In addition, this signaling pathway is the one that most frequently undergoes mutations in breast cancer. The prognostic and predictive significance of individual mutations has not yet been fully explained, but it might provide a basis for patient selection in clinical studies. Initial research results on the use of PI3K inhibitors suggest that this may be a highly promising therapeutic approach, with an acceptable side effect profile.
EVALuna2:33003

The prognostic relevance of urokinase-type plasminogen activator (uPA) in the blood of patients with metastatic breast cancer - Banys-Paluchowski, Malgorzata; Witzel, Isabell; Aktas, Bahriye; Fasching, Peter; Hartkopf, Andreas; Janni, Wolfgang; Kasimir-Bauer, Sabine; Pantel, Klaus; Schoen, Gerhard; Rack, Brigitte; Riethdorf, Sabine; Solomayer, Erich-Franz; et al. (Scientific Reports, 2019)
In breast cancer (BC), elevated levels of urokinase-type plasminogen activator (uPA) in tumor tissue have been confirmed as a strong prognostic factor in level-of-evidence-1 studies. The aim of the present study was to evaluate the clinical relevance of uPA levels in serum of metastatic BC patients and to compare uPA with other blood-based biomarkers. 252 patients were enrolled in this prospective, multicentre study. Blood samples were collected before begin of first-line or later-line systemic treatment. Serum uPA was quantified by a commercially available ELISA. Circulating tumor cells (CTCs) were detected using CellSearch; other biomarkers (EGFR, VEGF, HER2, RAS p21, TIMP1, CAIX) by ELISA. Using the ROC analysis, the optimal cut-off value (determined by the Youden index) of serum uPA was 2.52 ng/ml. Using this value, 26% of patients had elevated uPA levels. Patients with visceral metastasis and more than one metastatic site were significantly more likely to present with elevated uPA levels. CTC status, serum HER2, RAS p21, CAIX, TIMP1 and VEGF correlated significantly with uPA levels. Elevated uPA levels predicted shorter overall and progression-free survival in univariate analysis (median OS: 7.5 months [95%-CI 4.5-10.5 months] vs. not reached, p < 0.001; PFS:4.8 [95%CI: 3.1-6.5] vs. 9.1 [7.4-10.8] months, p < 0.001). In multivariate analysis, elevated uPA, presence of >= 5 CTCs, elevated RAS p21, higher grading and higher line of therapy were independent predictors of shorter OS, while elevated CTC counts, higher line of therapy and negative estrogen receptor status were independent predictors of shorter PFS. In conclusion, elevated uPA levels independently predict reduced overall survival and improved prognostication in patients with known CTC status. Whether high serum uPA might identify patients most likely to benefit from therapies targeting uPA, remains to be evaluated in future trials.
CRIS-Team WoS Importer:2019-03-06

Therapierelevante Biomarker in der gynäkologischen Onkologie - Ditsch, Nina; Fasching, Peter (Best Practice Onkologie, 2022)
The first biomarkers were discovered decades ago. Their prognostic and predictive value is still the subject of current research. Biomarker-based treatments represent the basis of the current and future trial landscape in gynecologic oncology, as was clearly demonstrated at this year’s ASCO Annual Meeting. The all-important question is founded in the quality of diagnostics at the immunohistochemical or molecular level. In breast cancer therapy, a HER‑2 (human epidermal growth factor receptor 2) finding was previously considered therapeutically relevant if there was an immunohistochemical (IHC) evaluation of 3+ or a fluorescence in situ hybridization (FISH)- or chromogenic in situ hybridization (CISH)-positive value. Use of the antibody–drug conjugate trastuzumab–deruxtecan, also in HER-2-low forms (IHC1+ or 2+, even if FISH/CISH negative), is now celebrated as practice changing, since significantly improved progression-free survival (PFS) and overall survival (OS) were also shown in this situation. With the accelerating use of newer therapeutics, attention should be paid to the side effects and the cost–benefit ratio. The following article provides an overview of the currently most important prognostic and predictive markers in breast, ovarian, endometrial, and cervical cancer.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Her-2; Immune checkpoint inhibitors; Immunoconjugates; Microsatellite instability; Prognosis; Trastuzumab

Therapy landscape in patients with metastatic HER2-positive breast cancer: Data from the PRAEGNANT real-world breast cancer registry - Lux, Michael P.; Nabieva, Naiba; Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (Cancers, 2019)
This study presents comprehensive real-world data on the use of anti-human epidermal growth factor receptor 2 (HER2) therapies in patients with HER2-positive metastatic breast cancer (MBC). Specifically, it describes therapy patterns with trastuzumab (H), pertuzumab + trastuzumab (PH), lapatinib (L), and trastuzumab emtansine (T-DM1). The PRAEGNANT study is a real-time, real-world registry for MBC patients. All therapy lines are documented. This analysis describes the utilization of anti-HER2 therapies as well as therapy sequences. Among 1936 patients in PRAEGNANT, 451 were HER2-positive (23.3%). In the analysis set (417 patients), 53% of whom were included in PRAEGNANT in the first-line setting, 241 were treated with H, 237 with PH, 85 with L, and 125 with T-DM1 during the course of their therapies. The sequence PH ! T-DM1 was administered in 51 patients. Higher Eastern Cooperative Oncology Group (ECOG) scores, negative hormone receptor status, and visceral or brain metastases were associated with more frequent use of this therapy sequence. Most patients received T-DM1 after treatment with pertuzumab. Both novel therapies (PH and T-DM1) are utilized in a high proportion of HER2-positive breast cancer patients. As most patients receive T-DM1 after PH, real-world data may help to clarify whether the efficacy of this sequence is similar to that in the approval study.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Advanced breast cancer; Antihormone therapy; Chemotherapy; Her2 c-ERBB2; Her2/neu; Lapatinib; Metastatic; Pertuzumab; T-DM1; Trastuzumab

Therapy of early breast cancer: current status and perspectives - Tauber, Nikolas; Amann, Niklas; Dannehl, Dominik; Deutsch, Thomas M.; Dimpfl, Moritz; Fasching, Peter; Hartkopf, Andreas; Heublein, Sabine; Hilmer, Lisbeth; Hörner, Manuel; Krawczyk, Natalia; Krückel, Annika; et al. (Archives of Gynecology and Obstetrics, 2025)
Medical advancements in breast cancer are truly remarkable. Especially in recent years, numerous new therapeutics have been approved and surgical strategies have been de-escalated for specific patient groups. In the therapeutic setting, CDK4/6 inhibitors as oral maintenance therapy in early breast cancer and immune checkpoint inhibitors (Pembrolizumab) for triple-negative breast cancer (BC) are noteworthy. In the surgical field, prospective randomized controlled trials have currently explored the possibility to deescalate axillary surgery by omitting sentinel lymph node excision (INSEMA, SOUND). As a result, there have been significant improvements in prognosis and a reduction in surgical morbidity for patients. Many exciting trials are underway, and it remains to be seen whether antibody–drug conjugates beyond trastuzumab emtansine, will find their way into the treatment lines for early-stage BC. Furthermore, the integration of artificial intelligence in both diagnostics and treatment recommendation evaluation is a promising area with great potential.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Early breast cancer; Future perspectives; HER2-positive; Hormone-receptor positive; Surgical de-escalation; Triple-negative

Therapy response and prognosis of patients with early breast cancer with low positivity for hormone receptors – An analysis of 2765 patients from neoadjuvant clinical trials - Villegas, Sonia L.; Nekljudova, Valentina; Pfarr, Nicole; Engel, Jutta; Untch, Michael; Schrodi, Simone; Holms, Frank; Ulmer, Hans U.; Fasching, Peter; Weber, Karsten E.; Albig, Christian; Heinrichs, Clemens; et al. (European Journal of Cancer, 2021)
Aim: To evaluate HER2-negative breast cancer (BC) with a low hormone receptor (HR) expression, with regard to pathological complete response (pCR) and survival, in comparison to triple-negative BC (TNBC) and strong HR-positive BC. Methods: We compared negative [oestrogen (ER) and progesterone receptor (PR) <1%], low-positive (ER and/or PR 1–9%) and strong-positive (ER or PR 10–100%) HR-expression in neoadjuvant clinical trial cohorts (n = 2765) of BC patients. End-points were disease-free survival (DFS), distant-disease free survival (DDFS) and overall survival (OS). We performed RNA sequencing on available tumour tissue samples from patients with low-HR expression (n = 38). Results: Ninety-four (3.4%) patients had low HR-positive tumours, 1769 (64.0%) had strong HR-positive tumours, and 902 (32.6%) had TNBC. There were no significant differences in pCR rates between women with low HR-positive tumours (27.7%) and women with TNBC (35.5%). DFS and DDFS were also not different [for DFS, hazard ratio 1.26, 95%-CI (confidence interval) : 0.87–1.83, log-rank test p = 0.951; for DDFS, hazard ratio 1.17, 95%-CI: 0.78–1.76, log-rank test p = 0.774]. Patients with strong HR-positive tumours had a significantly lower pCR rate (pCR 9.4%; odds ratio 0.38, 95%-CI: 0.23–0.63), but better DFS (hazard ratio 0.48, 95%-CI: 0.33–0.70) and DDFS (hazard ratio 0.49, 95%-CI: 0.33–0.74) than patients with low HR-positive tumours. Molecular subtyping (RNA sequencing) of low HR-positive tumours classified these predominantly into a basal subtype (86.8%). Conclusion: Low HR-positive, HER2-negative tumours have a similar clinical behaviour to TNBC showing high pCR rates and poor survival and also a basal-like gene expression signature. Patients with low HR-positive tumours should be regarded as candidates for therapy strategies targeting TNBC.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Breast cancer; Breast neoplasms; Cancer biomarkers; ER-negative PR-negative HER2-negative breast cancer; Hormone-dependent neoplasms; Mammary cancer; Neoadjuvant therapy; Oestrogen receptors; Progesterone receptors; Triple-negative breast cancer

The SNP rs6500843 in 16p13.3 is associated with survival specifically among chemotherapy-treated breast cancer patients - Fagerholm, Rainer; Schmidt, Marjanka K.; Khan, Sofia; Rafiq, Sajjad; Tapper, William; Aittomaki, Kristiina; Greco, Dario; Heikkinen, Tuomas; Muranen, Taru A.; Fasching, Peter; Janni, Wolfgang; Weinshilboum, Richard; et al. (Oncotarget, 2015)
We have utilized a two-stage study design to search for SNPs associated with the survival of breast cancer patients treated with adjuvant chemotherapy. Our initial GWS data set consisted of 805 Finnish breast cancer cases (360 treated with adjuvant chemotherapy). The top 39 SNPs from this stage were analyzed in three independent data sets: iCOGS (n=6720 chemotherapy-treated cases), SUCCESS-A (n=3596), and POSH (n=518). Two SNPs were successfully validated: rs6500843 (any chemotherapy; per-allele HR 1.16, 95% C.I. 1.08-1.26, p=0.0001, p(adjusted)=0.0091), and rs11155012 (anthracycline therapy; per-allele HR 1.21, 95% C.I. 1.08-1.35, p=0.0010, p(adjusted)=0.0270). The SNP rs6500843 was found to specifically interact with adjuvant chemotherapy, independently of standard prognostic markers (p(interaction)=0.0009), with the rs6500843-GG genotype corresponding to the highest hazard among chemotherapy-treated cases (HR 1.47, 95% C.I. 1.20-1.80). Upon trans-eQTL analysis of public microarray data, the rs6500843 locus was found to associate with the expression of a group of genes involved in cell cycle control, notably AURKA, the expression of which also exhibited differential prognostic value between chemotherapy-treated and untreated cases in our analysis of microarray data. Based on previously published information, we propose that the eQTL genes may be connected to the rs6500843 locus via a RBFOX1-FOXM1 -mediated regulatory pathway.
EVALuna2:17642

The UGT1A6_19_GG genotype is a breast cancer risk factor - Justenhoven, Christina; Obazee, Ofure; Winter, Stefan; Rabstein, Sylvia; Lotz, Anne; Harth, Volker; Pesch, Beate; Brüning, Thomas; Baisch, Christian; Hartikainen, Jaana M.; Mannermaa, Arto; Kosma, Veli Matti; et al. (Frontiers in Genetics, 2013)
Validation of an association between the UGT1A6_19_T>G (rs6759892) polymorphism and overall breast cancer risk. A pilot study included two population-based case-control studies from Germany (MARIE-GENICA). An independent validation study comprised four independent breast cancer case-control studies from Finland (KBCP, OBCS), Germany (BBCC), and Sweden (SASBAC). The pooled analysis included 7418 cases and 8720 controls from all six studies. Participants were of European descent. Genotyping was done by MALDI-TOF MS and statistical analysis was performed by logistic regression adjusted for age and study. The increased overall breast cancer risk for women with the UGT1A6_19_GG genotype which was observed in the pilot study was confirmed in the set of four independent study collections (OR 1.13, 95% CI 1.05-1.22; p = 0.001). The pooled study showed a similar effect (OR 1.09, 95% CI 1.04-1.14; p = 0.001). The risk effect on the basis of allele frequencies was highly significant, the pooled analysis showed an OR of 1.11 (95% CI 1.06-1.16; p = 5.8 × 10-6). We confirmed the association of UGT1A6_19_GG with increased overall breast cancer risk and conclude that our result from a well powered multi-stage study adds a novel candidate to the panel of validated breast cancer susceptibility loci. © 2013 Justenhoven, Obazee, Winter, Rabstein, Lotz, Harth, Pesch, Brüning, Baisch, Hartikainen, Mannermaa, Kosma, Kataja, Winqvist, Pylkäs, Jukkola-Vuorinen, Grip, Fasching, Beckmann, Ekici, Hein, Hall, Li, Chang-Claude, Flesch-Janys, Seibold, Rudolph, Hamann, Ko and Brauch.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer risk; Metabolism; Polymorphism; UGT1A6; Validation

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Time and Resources Needed to Document Patients with Breast Cancer from Primary Diagnosis to Follow-up - Results of a Single-center Study - Lux, Michael P.; Sell, C. S.; Fasching, Peter; Seidl-Ertel, Janine; Bani, Mayada; Schrauder, M. G.; Jud, Sebastian; Löhberg, Christian; Rauh, C.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strnad, Vratislav; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Certification of breast centers helps improve the quality of care but requires additional resources, particularly for documentation. There are currently no published data on the actual staff costs and financial resources required for such documentation. The aim of this study was to determine the time and resources required to document a patient with primary breast cancer from diagnosis to the end of follow-up, to establish a database for future strategic decisions. Material and Methods: All diagnostic and therapeutic procedures of patients with primary breast cancer were recorded at the University Breast Center of Franconia. All time points for documentation were evaluated using structured interviews. The times required to document a representative number of patients were determined and combined with the staff costs of the different professional groups, to calculate the financial resources required for documentation. Results: A total of 494 time points for documentation were identified. The study also identified 21 departments and 20 different professional groups involved in the documentation. The majority (54 %) of documentation was done by physicians. 62 % of all documentation involved outpatients. The results of different scenarios for the diagnosis, therapy and follow-up of breast cancer patients in a certified breast center showed that the time required for documentation can be as much as 105 hours, costing EUR 4135. Conclusion: This analysis shows the substantial staffing and financial costs required for documentation in certified centers. A multi-center study will be carried out to compare the costs for certified breast centers of varying sizes with the costs of non-certified care facilities.
EVALuna2:6642

Tomosynthese - Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Fasching, Peter; Uder, Michael (Chirurgische Praxis, 2016)
Full field digital mammography (FFDM) is the most important method for early diagnosis of breast cancer. The typical overlapping of normal and pathological tissue during the standard 2D projection, however, often reduces the specificity and sensitivity of the mammographic investigation. Digital breast tomosynthesis (DBT) provides on the basis of a limited number of single images with different projection angles not superimposed tomograms and may remove the unwanted masking by superimposed structures. Clinical studies show that the digital tomosynthesis has the real potential to reduce the recall rate and simultaneously increase the cancer detection rate, especially in women with dense breasts (detection and volumetry). The use of tomosynthesis seems to be superior to full field digital mammography in mammography screening. Other possibilities of the tomosynthesis are the dual energy mammography, contrast medium-enhanced mammography and intervention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast medium-enhanced mammography; Dual energy mammography; Full-field digital mammography; Intervention; Mammography screening; Tomosynthesis

Touch Imprint Cytology and Stereotactically-Guided Core Needle Biopsy of Suspicious Breast Lesions: 15-Year Follow-up - Schulz-Wendtland, Rüdiger; Fasching, Peter; Bani, Mayada; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C.; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Uder, Michael; Löhberg, Christian (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome. Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women. Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found. Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
EVALuna2:6752

Toxicity Assessment of a Phase III Study Evaluating FEC-Doc and FEC-Doc Combined with Gemcitabine as an Adjuvant Treatment for High-Risk Early Breast Cancer: the SUCCESS-A Trial - Schroeder, L.; Rack, B.; Sommer, H.; Koch, J. G.; Weissenbacher, T.; Janni, W.; Schneeweiss, A.; Rezai, M.; Lorenz, R.; Jaeger, B.; Schramm, A.; Häberle, Lothar; et al. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: This paper aims to evaluate the toxicity profile of additive gemcitabine to adjuvant taxane-based chemotherapy in breast cancer patients.Methods:Patients enrolled in this open-label randomized controlled Phase III study were treated with 3 cycles of epirubicin-fluorouracil-cyclophosphamide (FEC) chemotherapy followed by 3 cycles of docetaxel with those receiving 3 cycles of FEC followed by 3 cycles of gemcitabine-docetaxel (FEC-DG). 3690 patients were evaluated according to National Cancer Institute (NCI) toxicity criteria (CTCAE). The study medications were assessed by the occurrence of grade 3-4 adverse events, dose reductions, postponements of treatment cycles and granulocyte colony-stimulating factor (G-CSF) support.Results:No differences in neutropenia or febrile neutropenia were demonstrated. However, thrombocytopenia was significantly increased with FEC-DG treatment (2.0 vs. 0.5 %, p < 0.001), as was leukopenia (64.1 vs. 58.5 %, p < 0.001). With FEC-DG significantly more G-CSF support in cycles 4 to 6 (FEC-DG: 57.8 %, FEC-D: 36.3 %, p < 0.001) was provided. Transaminase elevation was significantly more common with FEC-DG (SGPT: 6.3 %, SGOT: 2 %), whereas neuropathy (1.2 %), arthralgia (1.6 %) and bone pain (2.6 %) were more common using FEC-D. Dose reductions > 20 % (4 vs. 2.4 %) and postponement of treatment cycles (0.9 vs. 0.4 %) were significantly more frequent in the FEC-DG arm. Eight deaths occurred during treatment in the FEC-DG arm and four in the FEC-D arm.Conclusion:The addition of gemcitabine increased hematological toxicity and was associated with more dose reductions and postponements of treatment cycles.
EVALuna2:32982

TP53-based interaction analysis identifies cis-eQTL variants for TP53BP2, FBXO28, and FAM53A that associate with survival and treatment outcome in breast cancer - Fagerholm, Rainer; Khan, Sofia; Schmidt, Marjanka K.; Garcia-Closas, Montserrat; Heikkila, Pavi; Saarela, Jani; Beesley, Jonathan; Jamshidi, Maral; Aittomaki, Kristiina; Liu, Jianjun; Ali, H. Raza; Andrulis, Irene L.; et al. (Oncotarget, 2017)
TP53 overexpression is indicative of somatic TP53 mutations and associates with aggressive tumors and poor prognosis in breast cancer. We utilized a two-stage SNP association study to detect variants associated with breast cancer survival in a TP53-dependent manner. Initially, a genome-wide study (n = 575 cases) was conducted to discover candidate SNPs for genotyping and validation in the Breast Cancer Association Consortium (BCAC). The SNPs were then tested for interaction with tumor TP53 status (n = 4,610) and anthracycline treatment (n = 17,828). For SNPs interacting with anthracycline treatment, siRNA knockdown experiments were carried out to validate candidate genes.In the test for interaction between SNP genotype and TP53 status, we identified one locus, represented by rs10916264 (p(interaction) = 3.44 × 10-5; FDR-adjusted p = 0.0011) in estrogen receptor (ER) positive cases. The rs10916264 AA genotype associated with worse survival among cases with ER-positive, TP53-positive tumors (hazard ratio [HR] 2.36, 95% confidence interval [C.I] 1.45 - 3.82). This is a cis-eQTL locus for FBXO28 and TP53BP2; expression levels of these genes were associated with patient survival specifically in ER-positive, TP53-mutated tumors. Additionally, the SNP rs798755 was associated with survival in interaction with anthracycline treatment (p(interaction) = 9.57 × 10-5, FDR-adjusted p = 0.0130). RNAi-based depletion of a predicted regulatory target gene, FAM53A, indicated that this gene can modulate doxorubicin sensitivity in breast cancer cell lines.If confirmed in independent data sets, these results may be of clinical relevance in the development of prognostic and predictive marker panels for breast cancer.
EVALuna2:36150

Transcriptome-wide association study of breast cancer risk by estrogen-receptor status - Feng, Helian; Gusev, Alexander; Pasaniuc, Bogdan; Wu, Lang; Long, Jirong; Abu-Full, Zomoroda; Aittomaki, Kristiina; Andrulis, Irene L.; Anton-Culver, Hoda; Antoniou, Antonis C.; Arason, Adalgeir; Arndt, Volker; et al. (Genetic Epidemiology, 2020)
Previous transcriptome-wide association studies (TWAS) have identified breast cancer risk genes by integrating data from expression quantitative loci and genome-wide association studies (GWAS), but analyses of breast cancer subtype-specific associations have been limited. In this study, we conducted a TWAS using gene expression data from GTEx and summary statistics from the hitherto largest GWAS meta-analysis conducted for breast cancer overall, and by estrogen receptor subtypes (ER+ and ER−). We further compared associations with ER+ and ER− subtypes, using a case-only TWAS approach. We also conducted multigene conditional analyses in regions with multiple TWAS associations. Two genes, STXBP4 and HIST2H2BA, were specifically associated with ER+ but not with ER– breast cancer. We further identified 30 TWAS-significant genes associated with overall breast cancer risk, including four that were not identified in previous studies. Conditional analyses identified single independent breast-cancer gene in three of six regions harboring multiple TWAS-significant genes. Our study provides new information on breast cancer genetics and biology, particularly about genomic differences between ER+ and ER− breast cancer.
CRIS-Team Scopus Importer:2020-03-20
Keywords: breast cancer subtype; causal gene; GWAS; TWAS

Translational Highlights in Breast and Ovarian Cancer 2019 – Immunotherapy, DNA Repair, PI3K Inhibition and CDK4/6 Therapy - Hartkopf, Andreas D.; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Schuetz, Florian; Fasching, Peter; Kolberg, Hans-Christian; Welslau, Manfred; Overkamp, Friedrich; et al. (Geburtshilfe und Frauenheilkunde, 2019)
In the near future, important translational questions of clinical relevance will be adressed by studies currently in progress. On the one hand, the role of PD-L1 expression must be further understood, after it was found to be relevant in the use of atezolizumab in first-line therapy of patients with metastatic triple-negative breast cancer (TNBC). No association between efficacy and PD-L1 expression was found in a neoadjuvant study that included pembrolizumab in TNBC. The pathological complete response rate (pCR) was higher in both patient groups with and without PD-L1 expression when pembrolizumab was added to chemotherapy. Another future question is the identification of further patient groups in which efficacy of PARP inhibitors is seen, which are licensed for the pBRCA1/2 germline mutation. These include, for example, patients with mutations in other genes, which are involved in homologous recombination, or patients with tumours that show an abnormality in global tests of homologous recombination deficiencies (HRD tests). The question of whether a PARP inhibitor can be given and with which chemotherapy combination partners is currently being investigated in both breast and ovarian cancer. While the data on improved overall survival are being consolidated for the CDK4/6 inhibitors, knowledge of molecular changes during the therapy and during progression on the therapy is growing. Both the accumulation of PI3K mutations and also PTEN changes might play a part in planning subsequent therapies. This review article summarises these recent developments in breast cancer and in part also in ovarian cancer.
CRIS-Team WoS Importer:2020-01-17

Translational highlights in breast cancer research and treatment: recent developments with clinical impact - Fasching, Peter; Schneeweiss, Andreas; Kolberg, Hans-Christian; Ettl, Johannes; Fehm, Tanja N.; Overkamp, Friedrich; Lueftner, Diana (Current Opinion in Obstetrics & Gynecology, 2019)
Purpose of review Over the last decades the time which is needed to translate a preclinical finding or idea in the clinic has reduced continuously. Especially but not only for breast cancer the number of tested drugs and targeted pathways have increased immensely. In addition, the introduction of immune-oncological treatments has further advanced the possibilities for future treatments. This review focuses on recent developments in the prevention and treatment of breast cancer including results from major clinical trials and recent conferences. Recent findings Many pathways involved in the progression or treatment of breast cancer have been also identified in the cause and pathogenesis of breast cancer. Therefore, breast cancer risk can be described in much more detail, possibly leading to new prevention strategies. In breast cancer treatment the introduction of PARP inhibitors has begun. Recent trials will lead to a better understanding whether PI3K inhibitors can be developed for application in the clinic and first large randomized trials show the superiority of anti PD-1/PD-L1 treatments. Treatment strategies which were developed over the last decade are moving rapidly into the clinical use. The understanding of treatment targets and involved side effects will be important for the safe implementation of these treatments into routine practice.
CRIS-Team WoS Importer:2019-04-12

Trastuzumab Biosimilars in the Therapy of Breast Cancer – “Real World” Experiences from four Bavarian University Breast Centres - Hester, Anna; Gaß, Paul; Fasching, Peter; Kraemer, Anne Katrin; Ettl, Johannes; Diessner, Joachim; Woeckel, Achim; Egger, Tobias; Stock, Katja; Redlin, Jutta; Andraschko, Monika; Harbeck, Nadia; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Introduction With the introduction of the first trastuzumab biosimilar in the summer of 2018, biosimilar antibodies for breast cancer have found their way into the area of gynaecological oncology. The switch of anti-human epidermal growth factor receptor 2 (HER2) therapy from the reference drug Herceptin ® to a biosimilar has presented challenges to the clinics. In addition to structural and organisational measures, training of employees as well as patient briefing and acceptance were major challenges. The study presented here records - within the context of quality assurance - how the switch to a trastuzumab biosimilar was implemented at four Bavarian university clinics in the Purchasing Association of Bavarian University Pharmacies. Materials/Methods Questionnaires on treatment figures and the switching process were sent to breast centres and pharmacies of four Bavarian university clinics between July and December 2019. The neoadjuvant, adjuvant and metastasised anti-HER2 therapy with trastuzumab with or without pertuzumab was recorded, evaluated and summarised. Results In the anti-HER2-therapy, trastuzumab was used intravenously (i. v.) and subcutaneously. Between July and December 2018, all four clinics in the Purchasing Association switched the i. v. trastuzumab therapy from the reference drug (Herceptin) to a biosimilar (for 2018: Kanjinti ®). Over 200 patients were treated with trastuzumab i. v. in each of the two half-years of 2018 (before and after the switch). The spectrum of side effects and pCR rates under therapy with the biosimilar were comparable to the experiences made with the reference drug. Three out of four clinics provided training to employees and informed patients by means of a defined information leaflet. Patient acceptance was high. Summary The anti-HER2 therapy could be switched successfully and safely to trastuzumab biosimilars at the Bavarian university hospitals. This may serve as guideline for the further implementation of biosimilars. The structures necessary for this initial switching process have been prepared with trastuzumab as an example.
CRIS-Team Scopus Importer:2020-12-18
Keywords: biosimilar; breast cancer; HER2; pCR; trastuzumab

Trastuzumab Emtansine for Residual Invasive HER2-Positive Breast Cancer - Von Minckwitz, G.; Huang, C. -S.; Mano, M. S.; Loibl, S.; Mamounas, E. P.; Untch, M.; Wolmark, N.; Rastogi, P.; Schneeweiss, A.; Redondo, A.; Fischer, H. H.; Jacot, W.; et al. (New England Journal of Medicine, 2019)
BACKGROUND
CRIS-Team WoS Importer:2019-02-27

Trastuzumab versus observation for HER2 nonamplified early breast cancer with circulating tumor cells (EORTC 90091-10093, BIG 1-12, Treat CTC): a randomized phase II trial - Ignatiadis, M.; Litiere, S.; Rothe, F.; Riethdorf, S.; Proudhon, C.; Fehma, T.; Aalders, K.; Forstbauer, H.; Fasching, Peter; Brain, E.; Vuylsteke, P.; Guardiola, E.; et al. (Annals of Oncology, 2018)
Trastuzumab improves the outcome of women with HER2 positive breast cancer. We aimed to assess whether trastuzumab decreases the detection rate of circulating tumor cells (CTCs) in women with high risk, HER2 nonamplified, early breast cancer.The EORTC 90091-10093 BIG 1-12 Treat CTC is a phase II trial, conducted in 70 hospitals and 6 CTC laboratories across 5 European countries. Patients with centrally confirmed HER2 nonamplified breast cancer and >=1 centrally confirmed CTC per 15 ml of blood by CellSearch® following surgery and (neo)adjuvant chemotherapy were randomized (1 : 1) to 6 cycles of trastuzumab intravenously versus 18 weeks of observation. Randomization was stratified for center, locally confirmed estrogen receptor status and adjuvant versus neoadjuvant chemotherapy. The primary end point was rate of detection of >=1 CTC per 15 ml of blood at week 18. Secondary end points were invasive disease-free survival (iDFS) and cardiac safety.Between 30 April 2013 and 17 October 2016, 1317 patients were screened; 95 (7.2%) had detectable CTC(s), and 63 (4.8%) were randomized to trastuzumab (n = 31) or observation (n = 32). Fifty-eight patients were assessable for the primary end point, 29 in each arm. In 9 of the 58 patients, CTC(s) were still detected at week 18 : 5 in the trastuzumab and 4 in the observation arm (one-sided Fisher's exact test, P = 0.765). An Independent Data Monitoring Committee recommended stopping further accrual for futility for the primary end point. Median follow-up at database lock was 13 months (IQR 4-16.5). The 1-year iDFS was 93.8% (95% CI 77.3-98.4) in the observation versus 84.8% (95% CI 63.4-94.2) in the trastuzumab arm. No grade 2-4 cardiac events were observed in the trastuzumab arm.Trastuzumab does not decrease the detection rate of CTCs in HER2 nonamplified, nonmetastatic breast cancer.
EVALuna2:56170

Treatment and outcomes of patients in the Brain Metastases in Breast Cancer Network Registry - Witzel, I.; Laakmann, E.; Weide, R.; Neunhoeffer, T.; Park-Simon, T. -J.; Schmidt, Marcus; Fasching, Peter; Hesse, T.; Polasik, A.; Mohrmann, S.; Wuerschmidt, F.; Schem, C.; et al. (European Journal of Cancer, 2018)
Brain metastases (BMs) have a major impact on life expectancy and quality of life for many breast cancer patients. Knowledge about treatment patterns and outcomes is limited.We analysed clinical data of 1712 patients diagnosed with BMs from breast cancer between January 2000 and December 2016 at 80 institutions.Median age at diagnosis of BMs was 56 years (22-90 years). About 47.8% (n = 732) of patients had HER2-positive, 21.4% (n = 328) had triple-negative and 30.8% (n = 471) had hormone receptor (HR)-positive, HER2-negative (luminal-like) primary tumours. The proportion of patients with HER2-positive BMs decreased comparing the years 2000-2009 with 2010-2015 (51%-44%), whereas the percentage of patients with luminal-like tumours increased (28%-34%; p = 0.0331). Patients with BMs in the posterior fossa were more often HER2 positive (n = 169/314, 53.8%) than those diagnosed with triple-negative (n = 65/314, 20.7%) or luminal-like primary breast cancer (n = 80/314, 25.5%), (p < 0.0001). Median overall survival (OS) time after development of BMs for the overall cohort was 7.4 months (95% confidence interval [CI]: 6.7-8.0 months). One-year survival rate was 37.7% (95% CI: 35.2-40.1). Patients with HER2-positive tumours had the longest median OS of 11.6 months (95% CI: 10.0-13.4) compared with 5.9 months (95% CI: 5.0-7.2) for patients with luminal-like and 4.6 months (95% CI: 3.9-5.4) for patients with triple-negative tumours. Patients with HER2-positive tumours who received anti-HER2 treatment had longer median OS than those without (17.1 months versus 7.2 months, p < 0.0001).Prognosis of patients after developing BMs varies significantly according to the subtype. The outcome in this cohort is similarly poor in triple-negative and HR-positive/HER2-negative patients. Our results underline the high medical need for improvement of treatment and prevention strategies for BMs in breast cancer patients.
EVALuna2:56176

Treatment landscape and prognosis after treatment with trastuzumab emtansine - Laakmann, Elena; Emons, Julius; Taran, Florin Andrei; Janni, Wolfgang; Uhrig, Sabrina; Overkamp, Friedrich; Kolberg, Hans Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Purpose Pertuzumab and T-DM1 are two efficient anti-HER2 treatments for patients with HER2-positive advanced breast cancer. While pertuzumab is usually given in first-line treatment and T-DM1 in second-line treatment, standard therapy options seem to be exhausted up to now after the treatment of patients with these two therapy options. Therefore, it is important to have data that describes the therapy situation and prognosis after T-DM1 treatment. Methods The PRAEGNANT metastatic breast cancer registry (NCT02338167) is a prospective registry for breast cancer patients with a focus on molecular biomarkers. Patients of all therapy lines with any kind of treatment are eligible. Collected data comprises therapies, adverse events, quality of life and other patient reported outcomes. Here we report on the patient characteristics and descriptive prognostic data for HER2-positive patients who have completed a treatment with T-DM1. Therapy patterns after T-DM1 and progression-free survival are reported as well as overall survival. Results A total of 85 patients were identified for the study who were prospectively observed during therapy after the termination of T-DM1. The main reason for T-DM1 termination was progress. Following T-DM1, lapatinib, trastuzumab and chemotherapy were the main therapy choices. Median progression-free survival was 4.8 months (95% CI: 3.2-6.3) and median overall survival was 18.4 months (95% CI: 15.5-21.3). Conclusions Therapy options after T-DM1 in a real-world setting seem to exhibit a relevant clinical efficacy, supporting the concept of continuous anti-HER2 treatments in the advanced therapy setting for breast cancer patients. Novel therapies are needed to improve the rather short median progression-free survival.
CRIS-Team Scopus Importer:2020-11-20
Keywords: advanced breast cancer; antihormone therapy; chemotherapy; HER2 c-erbB2; HER2/neu; lapatinib; metastatic; pertuzumab; T-DM1; trastuzumab

Treatment landscape of advanced breast cancer patients with hormone receptor positive HER2 negative tumors - Data from the German PRAEGNANT breast cancer registry - Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Nabieva, Naiba; Taran, Florin-Andrei; Schwitulla, Judith; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (BREAST, 2018)
PURPOSE: This study describes comprehensive data from a breast cancer registry concerning the use of endocrine treatment (ET) and chemotherapy in the first, second and higher therapy lines in hormone receptor (HR) positive, HER2 negative metastatic breast cancer (MBC). METHODS: The PRAEGNANT study is a real-time registry for patients with MBC. Therapies were categorized into the following categories: chemotherapy, aromatase inhibitor (AI), tamoxifen, fulvestrant, or everolimus plus ET and reported for first, second and third line or higher therapy use. Also treatment sequences for the first, second and third therapy line were analyzed. RESULTS: This analysis includes 958 patients with HR positive, HER2 negative MBC. 42.7% were treated with a chemotherapy in the first therapy line compared to 45.9% receiving an ET. A total of 25.9% were treated with everolimus plus anti-hormone therapy in any therapy line. 34.1% were treated with fulvestrant as single agent therapy. Analyzing therapy sequences, the administration of three different chemotherapies in a row was the most frequently used pattern. CONCLUSIONS: This analysis shows that across all three first therapy lines chemotherapy is a dominant therapy for HR positive, HER2 negative MBC patients. Education about the efficacy of ET might help to increase its use and decrease the possible burden of chemotherapy related toxicities.
EVALuna2:36436

Treatment of Early Breast Cancer Patients: Evidence, Controversies, Consensus: Focusing on Systemic Therapy - German Experts' Opinions for the 16th International St. Gallen Consensus Conference (Vienna 2019) - Lüftner, Diana; Bauerfeind, Ingo; Braun, Michael; Brucker, Sara Y.; Fasching, Peter; Felberbaum, Ricardo; Hagemann, Friederike; Haidinger, Renate; Harbeck, Nadia; Hönig, Arnd; Huober, Jens; Jackisch, Christian; et al. (Breast Care, 2019)
A German working group of leading breast cancer experts have discussed the votes at the International St. Gallen Consensus Conference in Vienna for the treatment of primary breast cancer with regard to the German AGO (Ar-beitsgemeinschaft Gynäkologische Onkologie) recommendations for clinical practice in Germany. Three of the German breast cancer experts were also members of this year's St. Gallen panel. Comparing the St. Gallen recommendations with the annually updated treatment recommendations of the Gynecological Oncology Working Group (AGO Mamma 2019) and the German S3 Guideline is useful, because the recommendations of the St. Gallen panel are based on expert opinions of different countries and disciplines. The focus of this article is on systemic therapy. The motto of this year's 16th St. Gallen Consensus Conference was "Estimating the magnitude of clinical benefit." The rationale behind this motto is that, for every treatment decision, a benefit-risk assessment must be taken into consideration for each patient.
CRIS-Team Scopus Importer:2019-10-01

Treatment of Early Breast Cancer The 18th St. Gallen International Breast Cancer Consensus Conference against the Background of Current German Treatment Recommendations Behandlung des frühen Mammakarzinoms 18. Internationaler St.-Gallen-Konsens vor dem Hintergrund der aktuellen deutschen Therapieempfehlungen diskutiert - Untch, Michael; Banys-Paluchowski, Maggie; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Ditsch, Nina; Fasching, Peter; Haidinger, Renate; Heil, Jörg; Jackisch, Christian; Janni, Wolfgang; Kolberg, Hans Christian; et al. (Geburtshilfe und Frauenheilkunde, 2023)
This year's 18th St. Gallen (SG) consensus conference on the treatment of early breast cancer (SGBCC: St. Gallen International Breast Cancer Conference) focused on practice-oriented questions. The individual situation and risk-benefit assessment were discussed in great detail. As in previous years, a German working group of leading breast cancer experts presented the results of the international SGBCC 2023 against the background of German treatment recommendations – especially the updated treatment recommendations of the Arbeitsgemeinschaft Gynäkologische Onkologie e.V. (AGO) – for everyday clinical practice in Germany. The German treatment recommendations of AGO are based on the current evidence. The comparison with the clinical approach in Germany has proven useful, as the SGBCC panel consists of experts from different countries and disciplines. That is why country-specific characteristics can be incorporated into the SGBCC recommendations.
CRIS-Team Scopus Importer:2024-12-16
Keywords: (neo)adjuvant systemic therapy; early-onset breast cancer; genetics; pathology; radiotherapy; St. Gallen Consensus 2023; surgery

Treatment of Patients with Early Breast Cancer: Evidence, Controversies, Consensus: German Expert Opinions on the 17th International St. Gallen Consensus Conference - Untch, Michael; Fasching, Peter; Brucker, Sara Y.; Budach, Wilfried; Denkert, Carsten; Haidinger, Renate; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Krug, David; Kuehn, Thorsten; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This years 17th St. Gallen (SG) Consensus Conference on the Treatment of Patients with Early Breast Cancer (SG-BCC) with the title "Customizing local and systemic therapies for women with early breast cancer" focused on the challenge of targeting the treatment of early breast cancer more specifically to the individual disease situation of each patient. As in previous years, a German working group of leading breast cancer experts discussed the results of the international SG-BCC 2021 in the context of the German guideline. It is helpful to compare the SG recommendations with the recently updated treatment recommendations of the Breast Commission of the German Working Group on Gynaecological Oncology (Arbeitsgemeinschaft Gynakologische Onkologie e.V., AGO) and the S3 guideline because the SG-BCC panel comprised experts from different countries, which is why country-specific aspects can be incorporated into the SG recommendations. The German treatment recommendations of the AGO and the S3 guideline are based on current evidence. Nevertheless, any therapeutic decision must always undergo a risk-benefit analysis for the specific situation and to be discussed with the patient.
CRIS-Team WoS Importer:2021-06-18

Treatment-related amenorrhea with T-DM1 plus pertuzumab (KP) is lower than with docetaxel/carboplatin/ trastuzumab/pertuzumab (TCHP) in the phase III neoadjuvant KRISTINE trial - Hurvitz, Sara A.; Fresco, Rodrigo; Afenjar, Karen; Stroyakovskiy, Daniil; Huang, Chiun-Sheng; Wildiers, Hans; Jung, Kyung Hae; Boileau, Jean-Francois; Campone, Mario; Martin, Miguel; Valero, Vicente; Sparano, Joseph A.; et al. (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-03-26

Treatment-relevant biomarkers in gynecologic oncology - Ditsch, Nina; Fasching, Peter (Die Gynäkologie, 2022)
The first biomarkers were discovered decades ago. Their prognostic and predictive value is still the subject of current research. Biomarker-based treatments represent the basis of the current and future trial landscape in gynecologic oncology, as was clearly demonstrated at this year's ASCO Annual Meeting. The all-important question is founded in the quality of diagnostics at the immunohistochemical or molecular level. In breast cancer therapy, a HER-2 (human epidermal growth factor receptor 2) finding was previously considered therapeutically relevant if there was an immunohistochemical (IHC) evaluation of 3+ or a fluorescence in situ hybridization (FISH)- or chromogenic in situ hybridization (CISH)-positive value. Use of the antibody-drug conjugate trastuzumab-deruxtecan, also in HER-2-low forms (IHC1+ or 2+, even if FISH/CISH negative), is now celebrated as practice changing, since significantly improved progression-free survival (PFS) and overall survival (OS) were also shown in this situation. With the accelerating use of newer therapeutics, attention should be paid to the side effects and the cost-benefit ratio. The following article provides an overview of the currently most important prognostic and predictive markers in breast, ovarian, endometrial, and cervical cancer.
CRIS-Team WoS Importer:2022-09-09

Treatment with ribociclib shows favourable immunomodulatory effects in patients with hormone receptor-positive breast cancer—findings from the RIBECCA trial - Peuker, Caroline A.; Yaghobramzi, Sarvenaz; Grunert, Corinna; Keilholz, Luisa; Gjerga, Enio; Hennig, Steffen; Schaper, Sigrid; Na, Il Kang; Keller, Ulrich; Brucker, Sara; Decker, Thomas; Fasching, Peter; et al. (European Journal of Cancer, 2022)
Background: Inhibitors of the cyclin-dependent kinases 4 and 6 (CDK4/6i) have significantly improved clinical outcomes in patients with advanced hormone receptor-positive (HR+) breast cancer and have demonstrated favourable antitumour immune responses in preclinical studies. Methods: Here, we investigated peripheral immune responses to ribociclib in patients with metastatic HR+ breast cancer as a preplanned exploratory subanalysis of the RIBECCA trial (NCT03096847). Peripheral blood mononuclear cells were subjected to immune cell profiling, gene expression analysis of immune-related signatures, and deep T cell receptor profiling before treatment started and after 12 weeks of treatment with ribociclib. Results: Gene expression analysis revealed an upregulation of signatures associated with an activated adaptive immune system and a decrease in immunosuppressive cytokine signalling during treatment with ribociclib. Profiling of peripheral immune cell subpopulations showed a decrease in Treg cell frequencies, which was associated with treatment response. Furthermore, induction of CD4+ naive T cells could be seen, whereas effector and memory T cell populations remained largely unchanged. Correspondingly, T cell repertoire diversity remained mostly unchanged during treatment, although an increase in clonality could be observed in single patients. Conclusions: We show that treatment with ribociclib has significant effects on the peripheral innate and adaptive immune response in patients with HR+ breast cancer. Our data suggest that these effects lead to an activation of an already existing immune response rather than a de novo induction and make a strong case for future combination strategies of CDK4/6i with immunotherapies to enhance the adaptive immune response in HR+ breast cancer.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Adaptive immunity; Breast cancer; CDK4/6 inhibitors; Immunomodulation; Ribociclib

Triple-Negative Breast Cancer Risk Genes Identified by Multigene Hereditary Cancer Panel Testing - Shimelis, Hermela; Laduca, Holly; Hu, Chunling; Hart, Steven N.; Na, Jie; Thomas, Abigail; Akinhanmi, Margaret; Moore, Raymond M.; Brauch, Hiltrud; Cox, Angela; Eccles, Diana M.; Ewart-Toland, Amanda; et al. (Journal of the National Cancer Institute, 2018)
BACKGROUND: Germline genetic testing with hereditary cancer gene panels can identify women at increased risk of breast cancer. However, those at increased risk of triple-negative (estrogen receptor-negative, progesterone receptor-negative, human epidermal growth factor receptor-negative) breast cancer (TNBC) cannot be identified because predisposition genes for TNBC, other than BRCA1, have not been established. The aim of this study was to define the cancer panel genes associated with increased risk of TNBC. METHODS: Multigene panel testing for 21 genes in 8753 TNBC patients was performed by a clinical testing laboratory, and testing for 17 genes in 2148 patients was conducted by a Triple Negative Breast Cancer Consortium (TNBCC) of research studies. Associations between deleterious mutations in cancer predisposition genes and TNBC were evaluated using results from TNBC patients and reference controls. RESULTS: Germline pathogenic variants in BARD1, BRCA1, BRCA2, PALB2, and RAD51D were associated with high risk (odds ratio > 5.0) of TNBC and greater than 20% lifetime risk for overall breast cancer among Caucasians. Pathogenic variants in BRIP1, RAD51C, and TP53 were associated with moderate risk (odds ratio > 2) of TNBC. Similar trends were observed for the African American population. Pathogenic variants in these TNBC genes were detected in 12.0% (3.7% non-BRCA1/2) of all participants. CONCLUSIONS: Multigene hereditary cancer panel testing can identify women with elevated risk of TNBC due to mutations in BARD1, BRCA1, BRCA2, PALB2, and RAD51D. These women can potentially benefit from improved screening, risk management, and cancer prevention strategies. Patients with mutations may also benefit from specific targeted therapeutic strategies.
EVALuna2:210020

Tumor-infiltrating CD8-positive T-lymphocytes in tubo-ovarian high-grade serous cancer are associated with multiple germline variants in 22q12.1 in a genome-wide association analysis - Natanzon, Yanina; Kobel, Martin; Winham, Stacey J.; Armasu, Sebastian M.; Mccauley, Bryan M.; Vierkant, Robert A.; Cunningham, Julie M.; Bowtell, David; Campbell, Ian G.; Chang-Claude, Jenny; Defazio, Anna; Fasching, Peter; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Tumor-infiltrating lymphocytes and response prediction to neoadjuvant chemotherapy in HER2-positive breast cancer - Heppner, B. Ingold; Untch, M.; Denkert, C.; Pfitzner, B. M.; Lederer, B.; Schmidt, W.; Eidtmann, H.; Fasching, Peter; Tesch, H.; Solbach, C.; Rezai, M.; Zahm, D. -M.; et al. (2016)
EVALuna2:33543

Tumor-Infiltrating Lymphocytes: A Predictive and Prognostic Biomarker in Neoadjuvant-Treated HER2-Positive Breast Cancer - Heppner, Barbara Ingold; Untch, Michael; Denkert, Carsten; Pfitzner, Berit M.; Lederer, Bianca; Schmitt, Wolfgang; Eidtmann, Holger; Fasching, Peter; Tesch, Hans; Solbach, Christine; Rezai, Mahdi; Zahm, Dirk M.; et al. (Clinical Cancer Research, 2016)
PURPOSE: We elucidated the value of tumor-infiltrating lymphocytes (TIL) as an independent predictor for pathologic complete response (pCR) rate and as a prognostic marker for disease-free survival (DFS) in patients with HER2-positive breast cancer in the neoadjuvant setting. EXPERIMENTAL DESIGN: We evaluated stromal TILs in 498 HER2-positive breast cancer samples of the neoadjuvant GeparQuattro (G4) and GeparQuinto (G5) trials. Levels of TILs were determined as a continuous parameter per 10% increase and as lymphocyte-predominant breast cancer (LPBC; ≥ 60% TILs), and correlated with pCR rate and DFS. RESULTS: In the complete cohort, HER2-positive LPBC cases had a significantly increased pCR rates compared with non-LPBC types. They were significant predictors for pCR in univariate (10% TILs: OR 1.12, P = 0.002; LPBC: OR 2.02, P = 0.002) and multivariate analyses (10% TILs: OR 1.1, P = 0.014; LPBC: OR 1.87, P = 0.009). This effect was also detectable in the trastuzumab-treated (10% TILs: OR 1.12, P = 0.018; LPBC: OR 2.08, P = 0.013) but not in the lapatinib-treated subgroup. We identified a low-risk (pCR/LPBC) and a high-risk group (no pCR/no LPBC) regarding DFS. In triple-positive breast cancer, TILs are of more prognostic relevance than pCR. CONCLUSIONS: We could demonstrate the predictive and prognostic impact of TILs in HER2-positive breast cancer in the neoadjuvant setting. In combination with pCR rate, TILs may help to stratify prognostic subgroups, thereby guiding future therapy decisions. Clin Cancer Res; 22(23); 5747-54. ©2016 AACR.
EVALuna2:33053

Tumor mutational burden and immune infiltration as independent predictors of response to neoadjuvant immune checkpoint inhibition in early TNBC in GeparNuevo - Karn, T.; Denkert, C.; Weber, K. E.; Holtrich, U.; Hanusch, C.; Sinn, B. V.; Higgs, B. W.; Jank, P.; Sinn, H. P.; Huober, J.; Becker, C.; Blohmer, J. U.; et al. (Annals of Oncology, 2020)
Background: The predictive value of tumor mutational burden (TMB), alone or in combination with an immune gene expression profile (GEP), for response to neoadjuvant therapy in early triple negative breast cancer (TNBC) is currently not known, either for immune checkpoint blockade (ICB) or conventional chemotherapy. Patients and methods: We obtained both whole exome sequencing and RNA-Seq data from pretreatment samples of 149 TNBC of the recent neoadjuvant ICB trial, GeparNuevo. In a predefined analysis, we assessed the predictive value of TMB and a previously developed immune GEP for pathological complete remission (pCR). Results: Median TMB was 1.52 mut/Mb (range 0.02–7.65) and was significantly higher in patients with pCR (median 1.87 versus 1.39; P = 0.005). In multivariate analysis, odds ratios for pCR per mut/Mb were 2.06 [95% confidence intervals (CI) 1.33–3.20, P = 0.001] among all patients, 1.77 (95% CI 1.00–3.13, P = 0.049) in the durvalumab treatment arm, and 2.82 (95% CI 1.21–6.54, P = 0.016) in the placebo treatment arm, respectively. We also found that both continuous TMB and immune GEP (or tumor infiltrating lymphocytes) independently predicted pCR. When we stratified patients in groups based on the upper tertile of TMB and median GEP, we observed a pCR rate of 82% (95% CI 60% to 95%) in the group with both high TMB and GEP in contrast to only 28% (95% CI 16% to 43%) in the group with both low TMB and GEP. Conclusions: TMB and immune GEP add independent value for pCR prediction. Our results recommend further analysis of TMB in combination with immune parameters to individually tailor therapies in breast cancer.
CRIS-Team Scopus Importer:2020-07-10
Keywords: exome sequencing; neoadjuvant immune checkpoint inhibition; triple negative breast cancer; tumor mutational burden

Tumour-infiltrating lymphocytes and prognosis in different subtypes of breast cancer: a pooled analysis of 3771 patients treated with neoadjuvant therapy - Denkert, Carsten; Von Minckwitz, Gunter; Darb-Esfahani, Silvia; Lederer, Bianca; Heppner, Barbara I.; Weber, Karsten E.; Budczies, Jan; Huober, Jens; Klauschen, Frederick; Furlanetto, Jenny; Schmitt, Wolfgang D.; Blohmer, Jens-Uwe; et al. (Lancet Oncology, 2018)
BACKGROUND: Tumour-infiltrating lymphocytes (TILs) are predictive for response to neoadjuvant chemotherapy in triple-negative breast cancer (TNBC) and HER2-positive breast cancer, but their role in luminal breast cancer and the effect of TILs on prognosis in all subtypes is less clear. Here, we assessed the relevance of TILs for chemotherapy response and prognosis in patients with TNBC, HER2-positive breast cancer, and luminal-HER2-negative breast cancer. METHODS: Patients with primary breast cancer who were treated with neoadjuvant combination chemotherapy were included from six randomised trials done by the German Breast Cancer Group. Pretherapeutic core biopsies from 3771 patients included in these studies were assessed for the number of stromal TILs by standardised methods according to the guidelines of the International TIL working group. TILs were analysed both as a continuous parameter and in three predefined groups of low (0-10% immune cells in stromal tissue within the tumour), intermediate (11-59%), and high TILs (≥60%). We used these data in univariable and multivariable statistical models to assess the association between TIL concentration and pathological complete response in all patients, and between the amount of TILs and disease-free survival and overall survival in 2560 patients from five of the six clinical trial cohorts. FINDINGS: In the luminal-HER2-negative breast cancer subtype, a pathological complete response (pCR) was achieved in 45 (6%) of 759 patients with low TILs, 48 (11%) of 435 with intermediate TILs, and 49 (28%) of 172 with high TILs. In the HER2-positive subtype, pCR was observed in 194 (32%) of 605 patients with low TILs, 198 (39%) of 512 with intermediate TILs, and 127 (48%) of 262 with high TILs. Finally, in the TNBC subtype, pCR was achieved in 80 (31%) of 260 patients with low TILs, 117 (31%) of 373 with intermediate TILs, and 136 (50%) of 273 with high TILs (p<0·0001 for each subtype, χ2 test for trend). In the univariable analysis, a 10% increase in TILs was associated with longer disease-free survival in TNBC (hazard ratio [HR] 0·93 [95% CI 0·87-0·98], p=0·011) and HER2-positive breast cancer (0·94 [0·89-0·99], p=0·017), but not in luminal-HER2-negative tumours (1·02 [0·96-1·09], p=0·46). The increase in TILs was also associated with longer overall survival in TNBC (0·92 [0·86-0·99], p=0·032), but had no association in HER2-positive breast cancer (0·94 [0·86-1·02], p=0·11), and was associated with shorter overall survival in luminal-HER2-negative tumours (1·10 [1·02-1·19], p=0·011). INTERPRETATION: Increased TIL concentration predicted response to neoadjuvant chemotherapy in all molecular subtypes assessed, and was also associated with a survival benefit in HER2-positive breast cancer and TNBC. By contrast, increased TILs were an adverse prognostic factor for survival in luminal-HER2-negative breast cancer, suggesting a different biology of the immunological infiltrate in this subtype. Our data support the hypothesis that breast cancer is immunogenic and might be targetable by immune-modulating therapies. In light of the results in luminal breast cancer, further research investigating the interaction of the immune system with different types of endocrine therapy is warranted. FUNDING: Deutsche Krebshilfe and European Commission.
EVALuna2:34264

Two truncating variants in FANCC and breast cancer risk - Dork, Thilo; Peterlongo, Paolo; Mannermaa, Arto; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Ahearn, Thomas; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; Augustinsson, Annelie; et al. (Scientific Reports, 2019)
Fanconi anemia (FA) is a genetically heterogeneous disorder with 22 disease-causing genes reported to date. In some FA genes, monoallelic mutations have been found to be associated with breast cancer risk, while the risk associations of others remain unknown. The gene for FA type C, FANCC, has been proposed as a breast cancer susceptibility gene based on epidemiological and sequencing studies. We used the Oncoarray project to genotype two truncating FANCC variants (p.R185X and p.R548X) in 64,760 breast cancer cases and 49,793 controls of European descent. FANCC mutations were observed in 25 cases (14 with p.R185X, 11 with p.R548X) and 26 controls (18 with p.R185X, 8 with p.R548X). There was no evidence of an association with the risk of breast cancer, neither overall (odds ratio 0.77, 95%CI 0.44–1.33, p = 0.4) nor by histology, hormone receptor status, age or family history. We conclude that the breast cancer risk association of these two FANCC variants, if any, is much smaller than for BRCA1, BRCA2 or PALB2 mutations. If this applies to all truncating variants in FANCC it would suggest there are differences between FA genes in their roles on breast cancer risk and demonstrates the merit of large consortia for clarifying risk associations of rare variants.
CRIS-Team Scopus Importer:2019-09-17

Ultrasound Elastography of Pulmonary Lesions - A Feasibility Study - Adamietz, B. R.; Fasching, Peter; Jud, Sebastian; Schulz-Wendtland, Rüdiger; Anders, Katharina; Uder, Michael; Wüst, Wolfgang; Rauh, C.; Meier-Meitinger, M. (Ultraschall in der Medizin, 2014)
Introduction: The potential of sonography in the examination of lung tissue is extremely limited by the air-filled alveoles of the lung. Only in special circumstances like pleural adhesion lesions, atelectasis or pneumonia can lung tissue be visualized by B-mode sonography. Real-time elastography was primarily applied to detect and visualize pulmonary lesions. Methods and Patients: 8 patients with a total of 18 histologically proven metastases of the lung were included. All pulmonary lesions were detected by computed tomography. Sonographic examination was performed with a 7.5 MHz linear transducer (Acuson Antares premium edition, Siemens, Erlangen, Germany), including B-mode and real-time elastography (RTE). The mean distance between pleura and the lesions ranged from 0 to 2.5 cm. Two lesions were located in the upper right lobe, eleven lesions in the lower right and five in the lower left lobe. Results: RTE was able to detect and visualize all 18 pulmonary lesions in contrast to B-mode. The size and distance of the lesions from the pleura correlated with the CT findings. Conclusion: In contrast to B-mode sonography, RTE is able to detect and visualize peripheral, non-pleural adherent pulmonary lesions.
EVALuna2:14352

Unbiased high-dimensional flow cytometry identified NK and DC immune cell signature in Luminal A-type and triple negative breast cancer - Heger, Lukas; Heidkamp, Gordon Frederik; Amon, Lukas; Nimmerjahn, Falk; Bäuerle, Tobias; Maier, Andreas; Erber, Ramona; Hartmann, Arndt; Hack, Carolin; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; et al. (OncoImmunology, 2024)
Breast cancer is the most common malignancy in women worldwide and a highly heterogeneous disease. Four different subtypes are described that differ in the expression of hormone receptors as well as the growth factor receptor HER2. Treatment modalities and survival rate depend on the subtype of breast cancer. However, it is still not clear which patients benefit from immunotherapeutic approaches such as checkpoint blockade. Thus, we aimed to decipher the immune cell signature of the different breast cancer subtypes based on high-dimensional flow cytometry followed by unbiased approaches. Here, we show that the frequency of NK cells is reduced in Luminal A and B as well as triple negative breast cancer and that the phenotype of residual NK cells is changed toward regulatory CD11b−CD16− NK cells. Further, we found higher frequencies of PD-1+ CD4+ and CD8+ T cells in triple negative breast cancer. Moreover, while Luminal A-type breast cancer was enriched for CD14+ cDC2 (named type 3 DC (DC3)), CD14− cDC2 (named DC2) were more frequent in triple negative breast cancer. In contrast, HER2-enriched breast cancer did not show major alterations in the composition of the immune cell compartment in the tumor microenvironment. These findings suggest that patients with Luminal A- and B-type as well as triple negative breast cancer might benefit from immunotherapeutic approaches targeting NK cells.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breast cancer; immune cell signature; NK cells; PD-1; tumor microenvironment

Understanding the genetic complexity of puberty timing across the allele frequency spectrum - Kentistou, Katherine A.; Kaisinger, Lena R.; Stankovic, Stasa; Vaudel, Marc; Mendes de Oliveira, Edson; Messina, Andrea; Walters, Robin G.; Liu, Xiaoxi; Busch, Alexander S.; Helgason, Hannes; Thompson, Deborah J.; Santoni, Federico; et al. (Nature Genetics, 2024)
Pubertal timing varies considerably and is associated with later health outcomes. We performed multi-ancestry genetic analyses on 800,000 women, identifying 1,080 signals for age at menarche. Collectively, these explained 11% of trait variance in an independent sample. Women at the top and bottom 1% of polygenic risk exhibited 11 and 14-fold higher risks of delayed and precocious puberty, respectively. We identified several genes harboring rare loss-of-function variants in 200,000 women, including variants in ZNF483, which abolished the impact of polygenic risk. Variant-to-gene mapping approaches and mouse gonadotropin-releasing hormone neuron RNA sequencing implicated 665 genes, including an uncharacterized G-protein-coupled receptor, GPR83, which amplified the signaling of MC3R, a key nutritional sensor. Shared signals with menopause timing at genes involved in DNA damage response suggest that the ovarian reserve might signal centrally to trigger puberty. We also highlight body size-dependent and independent mechanisms that potentially link reproductive timing to later life disease.
CRIS-Team Scopus Importer:2024-07-26

Update Breast Cancer 2017 - Implementation of Novel Therapies - Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Huober, Jens B.; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2017)
In recent years, numerous new therapy options for patients with breast cancer have been developed in clinical studies, with some options already approved for routine treatment. As the speed at which innovations are introduced increases, the importance of conferences also increases, as conferences are where the data underpinning new therapies are usually presented for the first time. This review looks at publications of the ASCO (American Society of Clinical Oncology) and ESMO (European Society of Medical Oncology) conferences in 2017, summarizes them and evaluates them in the context of existing data. The focus is on new insights for neoadjuvant therapy and new treatment options in the metastatic setting, such as the use of CDK4/6 inhibitors or PARP inhibitors. The first results of treatments with checkpoint inhibitors are presented. With the patent expiry of trastuzumab, a number of study results for trastuzumab biosimilars have also been published. The digitization of patient care provides the first results on quality of life and prognosis of patients with advanced cancer. Digital communications between patients and physicians are being evaluated in several studies in Germany. As the discussion about patient-relevant endpoints for patients in the metastatic setting continues, overall survival rates from studies of big endocrine-based therapies are urgently needed. Preliminary analyses of small study cohorts offer initial insights. In the context of improving patient care, in the coming years, questions will center on which patients particularly benefit from certain therapies and which patients need particular protection from specific side effects. Questions about these predictors are raised in many scientific projects as attention increasingly focuses on this topic.
EVALuna2:36116

Update Breast Cancer 2018 (Part 1) - Primary Breast Cancer and Biomarkers - Taran, Florin-Andrei; Schneeweiss, Andreas; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Woeckel, Achim; Ettl, Johannes; et al. (Geburtshilfe und Frauenheilkunde, 2018)
This summary provides an overview of how new therapies or new aspects of established therapies relate to the latest findings. Neoadjuvant therapy, local therapy, new aspects of systemic therapy, and prognostic and predictive factors are presented. In the neoadjuvant setting, the association between pathological complete response (pCR) and prognosis is still of interest as is the identification of new molecular predictors for new therapies such as CDK4/6 inhibitors. As regards surgical treatment, the target is still to reduce the aggressiveness of surgery. To achieve this, a better understanding particularly of ductal carcinoma in situ is required. With regard to systemic therapy, more data on the best combinations and therapy sequences for existing therapies is available. Finally, the use of prognostic and predictive factors may help to avoid overtreatment and ensure that patients only receive therapies which have been shown to be effective for their specific condition and have fewer side effects.
EVALuna2:51286

Update Breast Cancer 2018 (Part 2) - Advanced Breast Cancer, Quality of Life and Prevention - Schneeweiss, Andreas; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Woeckel, Achim; Ettl, Johannes; et al. (Geburtshilfe und Frauenheilkunde, 2018)
The treatment of metastatic breast cancer has become more complicated due to increasing numbers of new therapies which need to be tested. Therapies are now being developed to treat special clinical or molecular subgroups. Even though intrinsic molecular subtypes play a major role, more and more new therapies for subgroups and histological subtypes are being developed, such as the use of PARP inhibitors to treat patients with BRCA mutations (breast and ovarian cancer). Supportive therapies are also evolving, allowing problems such as alopecia or nausea and vomiting to be treated more effectively. Treatment-related side effects have a direct impact on the prognosis of patients with metastatic breast cancer, and supportive therapy can improve compliance. Digital tools could be useful to establish better patient management systems. This overview provides an insight into recent trials and how the findings could affect routine treatment. Current aspects of breast cancer prevention are also presented.
EVALuna2:51284

Update Breast Cancer 2018 (Part 3) - Genomics, Individualized Medicine and Immune Therapies - in the Middle of a New Era: Prevention and Treatment Strategies for Early Breast Cancer - Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Overkamp, Friedrich; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lueftner, Diana; Mueller, Volkmar; et al. (Geburtshilfe und Frauenheilkunde, 2018)
In primary early breast cancer, the aim of treatment planning is to obtain an increasingly better understanding of the disease. The identification of patients with an excellent prognosis could help this group avoid unnecessary treatments. Furthermore, the planning of treatment is becoming increasingly patient-focussed. There is a growing understanding of those patients who benefit particularly from chemotherapy, as well as of those who could benefit from immunotherapy. Studies conducted on immunotherapies will be published shortly. Smaller individual studies offer an initial insight into the efficacy of checkpoint inhibitors (anti-PD1/PDL1 therapies). Not least, one of the largest breast cancer studies of all times has recently come to an end. The use of a multigene test has shown that it is sufficient to identify patients with such a good prognosis that chemotherapy is unnecessary. This review article is intended to summarise the current studies and give an outlook on current developments.
EVALuna2:51295

Update Breast Cancer 2018 (Part 4) - Genomics, Individualized Medicine and Immune Therapies - in the Middle of a New Era: Treatment Strategies for Advanced Breast Cancer - Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lueftner, Diana; Welslau, Manfred; et al. (Geburtshilfe und Frauenheilkunde, 2018)
New therapeutic developments aimed at treating women with advanced breast cancer currently focus both on identifying patients eligible for targeted therapeutic concepts and on the continuing development of immune therapies. The data on CDK4/6 inhibitors are now complete and consistent in this class of substances (palbociclib, ribociclib and abemaciclib). Further pathways under investigation are PI3K and AKT signalling pathways along with diverse approaches to their inhibition. Initial study results were also presented recently on both mechanisms of action. Insights into the PARP inhibitors, moreover, are increasing; studies in this respect are also examining in which population they can be used most effectively. This review offers a summary of the recent studies and an outline of the latest developments.
EVALuna2:51296

Update Breast Cancer 2019 Part 1-Implementation of Study Results of Novel Study Designs in Clinical Practice in Patients with Early Breast Cancer - Hartkopf, Andreas D.; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Nabieva, Naiba; Taran, Florin-Andrei; Ettl, Johannes; Lueftner, Diana; Belleville, Erik; Schuetz, Florian; Fasching, Peter; et al. (Geburtshilfe und Frauenheilkunde, 2019)
For many years, small but significant advancements have been made time and again in the prevention and treatment of early breast cancer. The so-called panel gene analyses are becoming more and more important in prevention, since the risk due to the tested genes is better understood and as a result, concepts for integration in health care can be developed. In the adjuvant situation, the first study in the so-called post-neoadjuvant situation was able to demonstrate a clear improvement in the prognosis with an absent pathological complete remission following trastuzumab or pertuzumab + trastuzumab. Additional studies with this post-neoadjuvant therapeutic concept are still being conducted at present. The CDK4/6 inhibitors which had shown a significant improvement in progression-free survival in a metastatic situation are currently being tested in the adjuvant situation in large therapeutic studies. These and other new data for the treatment or prevention of primary breast cancer are presented in this review against the backdrop of current studies.
CRIS-Team WoS Importer:2019-04-02

Update Breast Cancer 2019 Part 2-Implementation of Novel Diagnostics and Therapeutics in Advanced Breast Cancer Patients in Clinical Practice - Janni, Wolfgang; Schneeweiss, Andreas; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Tesch, Hans; Overkamp, Friedrich; Lueftner, Diana; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of patients with advanced breast cancer has developed further in recent years. In addition to therapeutic progress in the established subgroups (hormone receptor and HER2 status), there are now therapies which are geared to individual molecular characteristics, such as PARP inhibitor therapy in BRCA-mutated patients. In addition to this, tests are being developed which are intended to establish addition-al markers within subgroups in order to predict the efficacy of a therapy. PI3K mutation testing in HER2-negative, hormonereceptor- positive tumours and PD-L1 testing of immune cells in triple-negative tumours are expected to become established in clinical practice in order to select patients for the respective therapies. With new therapeutic approaches, new adverse effects also appear. The management of these adverse effects, just as those of classical therapy (supportive therapy), is essential with the introduction of new treatments in order to preserve patients ' quality of life. Knowledge regarding measures to preserve and improve quality of life has significantly increased in recent years. Lifestyle factors should be taken into account, as should modern therapeutic methods. This review summarises the latest studies and publications and evaluates them in regard to the relevance for clinical practice.
CRIS-Team WoS Importer:2019-04-02

Update Breast Cancer 2019 Part 2 - Implementation of Novel Diagnostics and Therapeutics in Advanced Breast Cancer Patients in Clinical Practice Update Mammakarzinom 2019 Teil 2 - Implementierung neuer Diagnostika und Therapien bei Patientinnen mit fortgeschrittenem Brustkrebs in der klinischen Praxis - Janni, Wolfgang; Schneeweiss, Andreas; Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin Andrei; Tesch, Hans; Overkamp, Friedrich; Lüftner, Diana; Belleville, Erik; et al. (TumorDiagnostik & Therapie, 2019)
The treatment of patients with advanced breast cancer has developed further in recent years. In addition to therapeutic progress in the established subgroups (hormone receptor and HER2 status), there are now therapies which are geared to individual molecular characteristics, such as PARP inhibitor therapy in BRCA-mutated patients. In addition to this, tests are being developed which are intended to establish additional markers within subgroups in order to predict the efficacy of a therapy. PI3K mutation testing in HER2-negative, hormonereceptor-positive tumours and PDâ€ L1 testing of immune cells in triple-negative tumours are expected to become established in clinical practice in order to select patients for the respective therapies. With new therapeutic approaches, new adverse effects also appear. The management of these adverse effects, just as those of classical therapy (supportive therapy), is essential with the introduction of new treatments in order to preserve patientsÊ¼ quality of life. Knowledge regarding measures to preserve and improve quality of life has significantly increased in recent years. Lifestyle factors should be taken into account, as should modern therapeutic methods. This review summarises the latest studies and publications and evaluates them in regard to the relevance for clinical practice.
CRIS-Team Scopus Importer:2019-09-17
Keywords: advanced; alpelisib; atezolizumab; breast cancer; metastatic; PARP; PD-L1; PI3K; supportive therapy

Update Breast Cancer 2019 Part 3 - Current Developments in Early Breast Cancer: Review and Critical Assessment by an International Expert Panel - Kolberg, Hans Christian; Schneeweiss, Andreas; Fehm, Tanja N.; Wöckel, Achim; Huober, Jens; Pontones, Constanza; Titzmann, Adriana; Belleville, Erik; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Taran, Florin Andrei; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of breast cancer patients in a curative situation is special in many ways. The local therapy with surgery and radiation therapy is a central aspect of the treatment. The complete elimination of tumour cells at the site of the primary disease must be ensured while simultaneously striving to keep the long-term effects as minor as possible. There is still focus on the continued reduction of the invasiveness of local therapy. With regard to systemic therapy, chemotherapies with taxanes, anthracyclines and, in some cases, platinum-based chemotherapies have become established in the past couple of decades. The context for use is being continually further defined. Likewise, there are questions in the case of antihormonal therapy which also still need to be further defined following the introduction of aromatase inhibitors, such as the length of therapy or ovarian suppression in premenopausal patients. Finally, personalisation of the treatment of early breast cancer patients is also being increasingly used. Prognostic tests could potentially support therapeutic decisions. It must also be considered how the possible use of new therapies, such as checkpoint inhibitors and CDK4/6 inhibitors could look in practice once study results in this regard are available. This overview addresses the backgrounds on the current votes taken by the international St. Gallen panel of experts in Vienna in 2019 for current questions in the treatment of breast cancer patients in a curative situation.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adjuvant therapy; early breast cancer; neoadjuvant therapy; St. Gallen panel of experts

Update Breast Cancer 2019 Part 3 - Current Developments in Early Breast Cancer: Review and Critical Assessment by an International Expert Panel Update Mammakarzinom 2019 Teil 3 - aktuelle Entwicklungen bei der kurativen Behandlung von Mammakarzinom-Patientinnen: Eine Übersicht und Bewertung durch ein internationales Expertenpanel - Kolberg, Hans Christian; Schneeweiss, Andreas; Fehm, Tanja N.; Wöckel, Achim; Huober, Jens; Pontones, Constanza; Titzmann, Adriana; Belleville, Erik; Lux, Michael P.; Janni, Wolfgang; Hartkopf, Andreas D.; Taran, Florin Andrei; et al. (TumorDiagnostik & Therapie, 2019)
The treatment of breast cancer patients in a curative situation is special in many ways. The local therapy with surgery and radiation therapy is a central aspect of the treatment. The complete elimination of tumour cells at the site of the primary disease must be ensured while simultaneously striving to keep the long-term effects as minor as possible. There is still focus on the continued reduction of the invasiveness of local therapy. With regard to systemic therapy, chemotherapies with taxanes, anthracyclines and, in some cases, platinum-based chemotherapies have become established in the past couple of decades. The context for use is being continually further defined. Likewise, there are questions in the case of antihormonal therapy which also still need to be further defined following the introduction of aromatase inhibitors, such as the length of therapy or ovarian suppression in premenopausal patients. Finally, personalisation of the treatment of early breast cancer patients is also being increasingly used. Prognostic tests could potentially support therapeutic decisions. It must also be considered how the possible use of new therapies, such as checkpoint inhibitors and CDK4/6 inhibitors could look in practice once study results in this regard are available. This overview addresses the backgrounds on the current votes taken by the international St. Gallen panel of experts in Vienna in 2019 for current questions in the treatment of breast cancer patients in a curative situation.
CRIS-Team Scopus Importer:2019-09-17
Keywords: adjuvant therapy; early breast cancer; neoadjuvant therapy; St. Gallen panel of experts

Update Breast Cancer 2019 Part 4 – Diagnostic and Therapeutic Challenges of New, Personalised Therapies for Patients with Early Breast Cancer - Schütz, Florian; Fasching, Peter; Welslau, Manfred; Hartkopf, Andreas D.; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Lüftner, Diana; Belleville, Erik; Kolberg, Hans Christian; Overkamp, Friedrich; et al. (Geburtshilfe und Frauenheilkunde, 2019)
The further development of therapies for women with early breast cancer is progressing far more slowly than in the case of patients with advanced breast cancer and is additionally delayed compared to developments in metastatic breast cancer. Nonetheless, significant advancements have been able to be recorded recently. This review summarises the latest developments in view of the most recent publications and professional conferences. For hormone-receptor-positive patients, new aspects for the duration of antihormone therapy and with regard to the benefits of multigene tests have been published. In the case of HER2-positive patients, the value of post-neoadjuvant therapy and de-escalation of the therapy is discussed. In patients with triple-negative breast cancer, there is a question of whether the knowledge of the biological background of a homologous recombination deficiency (HRD) helps develop new therapies for this subtype. In particular the use of a BRCA1/2 mutation or the biological characteristic HRD as a potential motive for therapy plays a role here in specifying the significance of platinum therapy and therapy with PARP inhibitors.
CRIS-Team Scopus Importer:2019-11-05
Keywords: adjuvant; antihormone therapy; breast cancer; chemotherapy; multigene tests; neoadjuvant

Update Breast Cancer 2019 Part 5 - Diagnostic and Therapeutic Challenges of New, Personalised Therapies in Patients with Advanced Breast Cancer. - Welslau, Manfred; Hartkopf, Andreas D.; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Lueftner, Diana; Belleville, Erik; Schuetz, Florian; Fasching, Peter; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2019)
Significant advancements have been made in recent years in advanced breast cancer and nearly all of them have been in the field of targeted therapy. Pertuzumab and trastuzumab-emtansine (T-DM1) have been able to be introduced in HER2-positive breast cancer. Now other anti-HER2 therapies are being developed (e.g. margetuximab, DS-8201a, pyrotinib) which can overcome other resistance mechanisms in the HER2 signalling pathway. In the field of hormone-receptor-positive breast cancer, an mTOR inhibitor and CDK4/6 inhibitors were introduced in the past. Now the introduction of the first PI3K inhibitor is forthcoming and this inhibitor will involve genetic testing of the tumour for a mutation in the PIK3CA gene. There are also significant advancements in triple-negative breast cancer: By combining chemotherapy and immunotherapy, an advantage for overall survival was able to be demonstrated in a subgroup (immune cells PD-L1-positive). The PARP inhibitor therapy for HER2-negative patients with a germ line mutation in BRCA1 or BRCA2 was also associated with an improved overall survival in a subgroup. These promising new study results are summarised in this review.
EVALuna2:206462

Update Breast Cancer 2020 Part 1 – Early Breast Cancer: Consolidation of Knowledge About Known Therapies - Schneeweiss, Andreas; Hartkopf, Andreas D.; Mueller, Volkmar; Woeckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Huober, Jens; Thill, Marc; Fasching, Peter; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2020)
This review is intended to present the latest developments in the prevention and treatment of early breast cancer. The risk of breast cancer can be increasingly better characterised with large epidemiological studies on genetic and non-genetic risk factors. Through new analyses, the evidence for high-penetrance genes as well as for low-penetrance genes was able to be improved. New data on denosumab and atezolizumab are available in the neoadjuvant situation as is a pooled appraisal of numerous studies on capecitabine in the curative situation. There is also an update to the overall survival data of pertuzumab in the adjuvant situation with a longer follow-up observation period. Finally, digital medicine is steadily finding its way into science. A recently conducted study on automated breast cancer detection using artificial intelligence establishes the basis for a future review in clinical studies.
CRIS-Team Scopus Importer:2020-03-27
Keywords: digital medicine; early breast cancer; immune therapy; prevention; prognosis; therapy

Update Breast Cancer 2020 Part 2 - Advanced Breast Cancer: New Treatments and Implementation of Therapies with Companion Diagnostics - Lüftner, Diana; Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Wöckel, Achim; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Schütz, Florian; Thill, Marc; Huober, Jens; Fasching, Peter; et al. (Geburtshilfe und Frauenheilkunde, 2020)
For patients with locally advanced or metastatic breast cancer, new and effective therapies such as CDK4/6 inhibitors, PARP inhibitors and a PD-L1 inhibitor have been introduced in recent years. This review presents an update on the available studies with their data. In addition, two innovative anti-HER2 therapies are presented (trastuzumab-deruxtecan and tucatinib) for which the results from new studies have been reported. Molecular tests offer the possibility of defining patient populations or also monitoring courses of therapy. This can help identify patients with specific characteristics in order to provide them with individually targeted therapy within the framework of studies. In a large study, the benefit of such a biomarker study was able to be described for the first time.
CRIS-Team Scopus Importer:2020-05-15
Keywords: advanced breast cancer; BRCA1/2; CDK4/6; immune therapy; metastases; mutational testing; PARP; PD-L1; therapy

Update Breast Cancer 2020 Part 3 - Early Breast Cancer - Huober, Jens; Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Thill, Marc; Fasching, Peter; Kolberg, Hans Christian; Schulmeyer, Carla; et al. (Geburtshilfe und Frauenheilkunde, 2020)
The treatment of patients with early breast cancer has always been characterised by escalation by new therapies and de-escalation through identification of better treatment regimens or introduction of better tools to estimate prognosis. Efforts in some of these areas in the last few years have led to solid data. The results of the large studies of de-escalation through use of multi-gene tests are available, as are the results of some studies that investigated the new anti-HER2 substances T-DM1 and pertuzumab in the early treatment situation. Several large-scale studies examining the role of CDK4/6 inhibitors will soon be concluded so innovations can be anticipated in this area also. This review article will summarise and classify the results of the latest publications.
CRIS-Team Scopus Importer:2020-11-27
Keywords: digital medicine; early breast cancer; immunotherapy; prevention; prognosis; treatment

Update Breast Cancer 2020 Part 4 – Advanced Breast Cancer - Tesch, Hans; Müller, Volkmar; Wöckel, Achim; Ettl, Johannes; Belleville, Erik; Schütz, Florian; Hartkopf, Andreas; Thill, Marc; Huober, Jens; Fasching, Peter; Kolberg, Hans Christian; Schulmeyer, Carla E.; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Substances with good effectiveness that intervene in specific signalling pathways have been used increasingly in recent years in the treatment of patients with advanced breast cancer, and new therapies and approaches have now been added, which actually relate to quite specific changes, such as the treatment of patients with HR+/HER2 tumours with a PIK3CA mutation. The treatment of patients with a BRCA1 or BRCA2 mutation has also been improved by the introduction of PARP inhibitors. Attempts are now being made increasingly to extend treatment indications based on molecular patterns, to identify other patients who could benefit from a treatment and to integrate the newly established treatment methods in existing therapy sequences. This review articles summarises the latest information in this connection.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Advanced breast cancer; BRCA1/2; CDK4/6; immunotherapy; metastases; mutation testing; PARP; PD-L1; treatment

Update Breast Cancer 2020 Part 5 - Moving Therapies from Advanced to Early Breast Cancer Patients - Lux, Michael P.; Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Janni, Wolfgang; Belleville, Erik; Stickeler, Elmar; Thill, Marc; Fasching, Peter; Kolberg, Hans Christian; Untch, Michael; Harbeck, Nadia; et al. (Geburtshilfe und Frauenheilkunde, 2021)
In recent years, significant progress has been made in new therapeutic approaches to breast cancer, particularly in patients with HER2-positive and HER2-negative/hormone receptor-positive (HR+) breast cancer. In the case of HER2-positive tumours, these approaches have included, in particular, treatment with pertuzumab, T-DM1, neratinib and, soon, also tucatinib and trastuzumab deruxtecan (neither of which has yet been authorised in Europe). In patients with HER2-/HR+ breast cancer, CDK4/6 inhibitors and the PIK3CA inhibitor alpelisib are of particular importance. Further novel therapies, such as Akt kinase inhibitors and oral SERDs (selective estrogen receptor down regulators), are already being investigated in ongoing clinical trials. These therapeutic agents are not only being introduced into curative, (neo-)adjuvant therapeutic settings for HER2-positive tumours; a first favourable study on abemaciclib as an adjuvant therapy has now also been published. In patients with triple-negative breast cancer, after many years of negative study results with the Trop-2 antibody drug conjugate (ADC) sacituzumab govitecan, a randomised study has been published that may represent a significant therapeutic advance. This review describes the latest developments in breast cancer subsequent to the ESMO Congress 2020.
CRIS-Team Scopus Importer:2021-05-21
Keywords: digital medicine; early breast cancer; immune therapy; prognosis; therapy

Update Breast Cancer 2021 Part 1-Prevention and Early Stages - Stickeler, Elmar; Aktas, Bahriye; Behrens, Annika; Belleville, Erik; Ditsch, Nina; Fasching, Peter; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises not only the latest evidence on prevention, but also the current research on the treatment of early-stage breast cancer patients. Recent years have seen a growing body of evidence on the risk of high- and moderate-penetrance breast cancer susceptibility genes. A large international consortium has now been able to further refine the answer to the question of the significance of the so-called panel genes. Moreover, the data on treatment selection regarding endocrine efficacy and the decision for or against chemotherapy have also been advanced markedly. There is also new data on adjuvant CDK4/6 (cyclin-dependent kinase 4/6) inhibitors, which are standard in first-line treatment in patients with metastatic HER2-negative, hormone receptor-positive (HR+) breast cancer. For other therapies such as immune checkpoint inhibitors, which have successfully improved the rate of pathologic complete response (pCR) in neoadjuvant treatment settings for patients with triple-negative breast cancer (TNBC), there is a growing understanding of the quality of life and side effects. This is especially important in situations where patients could possibly be cured without such a regimen.
CRIS-Team WoS Importer:2021-05-21

Update Breast Cancer 2021 Part 2-Advanced Stages, Long-Term Consequences and Biomarkers - Ditsch, Nina; Stickeler, Elmar; Behrens, Annika; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises and discusses significant aspects of recently published studies on patient treatment in advanced breast cancer and on biomarkers in breast cancer. In recent years, a large number of drugs for all molecular subtypes have been developed up to phase III trials. With regard to immune checkpoint inhibitors in metastasised breast cancer, the recent discussion has centred on the best candidate for combined chemotherapy. The oral taxanes could become a new type of oral chemotherapies. There is a growing body of data on biomarkers for the use of CDK4/6 inhibitors, which could also signify further development for other molecular subtypes. New substances have been developed for metastatic HER2+ breast cancer that still result in good remission even after massive prior treatment and/or cerebral metastasis. Similarly, knowledge is growing about targeted therapies with antibody-drug conjugates (ADC) against Trop-2, which could bolster our therapeutic armoury in triple-negative breast cancer (TNBC). In addition, the clinical focus is on understanding how to maintain fertility after breast cancer treatment. Here, pooled analyses provide new insights.
CRIS-Team WoS Importer:2021-05-21

Update Breast Cancer 2021 Part 3 – Current Developments in the Treatment of Early Breast Cancer: Review and Assessment of Specialised Treatment Scenarios by an International Expert Panel - Fehm, Tanja N.; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans Christian; Lüftner, Diana; Müller, Volkmar; Schütz, Florian; Thomssen, Christoph; Belleville, Erik; Behrens, Annika; et al. (Geburtshilfe und Frauenheilkunde, 2021)
The continuous availability of findings from new studies repeatedly results in updated treatment recommendations and guidelines. In the case of breast carcinoma in particular, several studies have been published in the last few years that have transformed how early and advanced breast carcinoma is being treated. However, this by no means means implies that there is agreement among all experts on specific issues. It is precisely the diversity of interpretation of guidelines and study findings that reflects the constantly changing available data and its complexity, as well as the availability of new drugs. In recent years, new substances such as pertuzumab, T-DM1, neratinib and capecitabine have become available to treat patients with early stages of breast carcinoma. Furthermore, the first results on the use of CDK4/6 inhibitors for adjuvant treatment have now been published. Last but not least, the use of multigene tests to avoid the necessity of chemotherapy in certain patients is still under discussion. This review summarises the state of the data and publishes the results of the survey completed by experts at the 2021 St. Gallen Breast Cancer Conference on early-stage breast cancer.
CRIS-Team Scopus Importer:2021-07-02
Keywords: early breast cancer; expert panel; therapy decisions

Update Breast Cancer 2021 Part 4 - Prevention and Early Stages. - Thomssen, Christoph; Fehm, Tanja N.; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lueftner, Diana; Mueller, Volkmar; Schuetz, Florian; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
This past year has seen new and effective options for further improving treatment outcome in many patients with early-stage breast cancer. Patients with hormone receptor-positive disease benefited significantly from the addition of the CDK4/6 inhibitor abemaciclib to endocrine adjuvant therapy. In triple-negative disease, data were presented for two treatment regimens. Patients with advanced disease (stage 2 and 3) benefit from neoadjuvant treatment with the immune checkpoint inhibitor pembrolizumab in combination with standard chemotherapy, regardless of PD-L1 expression. When neoadjuvant therapy has failed to achieve the desired remission in BRCA1 and BRCA2 mutations, the administration of the PARP inhibitor olaparib has demonstrated an impressive response. Other data address translational issues in HER2-positive breast cancer and neoadjuvant therapy approaches with the oral SERD giredestrant and the PARP inhibitor talazoparib. This review presents and analyses the findings of this year' s most important study outcomes.
EVALuna2:506656
Keywords: BRCA (breast cancer associated gene); breast; genetics; Her-2/neu (human epidermal growth factor receptor); hormonal receptor; breast cancer

Update Breast Cancer 2021 Part 5 - Advanced Breast Cancer. - Lueftner, Diana; Schuetz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Thomssen, Christoph; Mueller, Volkmar; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Despite the COVID 19 pandemic and mostly virtual congresses, innovation in the treatment of breast cancer patients continues at an unabated pace. This review summarises the current developments. Initial overall survival data for CDK4/6 inhibitor treatment in combination with an aromatase inhibitor as the first advanced line of therapy in treatment-naive postmenopausal patients have been published. Similarly, a trial comparing trastuzumab-deruxtecan versus trastuzumab-emtansine revealed a clear benefit regarding progression-free survival. Understanding of biomarkers making checkpoint inhibitor therapy particularly effective is increasing, and new compounds such as oral selective estrogen receptor destabilisers (SERDs) are entering clinical development and completing the first phase III trials.
EVALuna2:506657

Update Breast Cancer 2022 Part 1 - Early Stage Breast Cancer. - Welslau, Manfred; Mueller, Volkmar; Lueftner, Diana; Schuetz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Evidence relating to the treatment of breast cancer patients with early-stage disease has increased significantly in the past year. Abemaciclib, olaparib, and pembrolizumab are new drugs with good efficacy in the relevant patient groups. However, some questions remain unanswered. In particular, it remains unclear which premenopausal patients with hormone receptor-positive breast cancer should be spared unnecessary treatment. The question of the degree to which chemotherapy exerts a direct cytotoxic effect on the tumor or reduces ovarian function through chemotherapy could be of key importance. This group of patients could potentially be spared chemotherapy. New, previously experimental biomarker analysis methods, such as spatial analysis of gene expression (spatial transcriptomics) are gradually finding their way into large randomized phase III trials, such as the NeoTRIP trial. This in turn leads to a better understanding of the predictive factors of new therapies, for example immunotherapy. This review summarizes the scientific innovations from recent congresses such as the San Antonio Breast Cancer Symposium 2021 but also from recent publications.
EVALuna2:511215

Update Breast Cancer 2022 Part 2 - Advanced Stage Breast Cancer - Müller, Volkmar; Welslau, Manfred; Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; et al. (Geburtshilfe und Frauenheilkunde, 2022)
For patients with advanced breast cancer, several novel therapies have emerged in recent years, including CDK4/6 inhibitors, immune checkpoint inhibitors, PARP inhibitors, alpelisib, tucatinib and trastuzumab-deruxtecan, and sacituzumab-govitecan, which have transformed and expanded the therapeutic landscape for patients with advanced breast cancer. Some of these substances have now been approved for use in the early stages of the disease, or are expected to be approved in the near future, so the therapeutic landscape will change once again. Therefore, current scientific efforts are focused on the introduction of new substances and understanding their mechanisms of progression and efficacy. This review summarizes recent developments with reference to recent publications and conferences. Findings on the treatment of patients with HER2-positive breast cancer and brain metastases are presented, as are a number of studies looking at biomarkers in patients with HER2-negative, hormone receptor-positive breast cancer. In particular, the introduction of oral selective estrogen receptor degraders provides new opportunities to establish biomarker-based therapy. Molecular diagnostics is establishing itself as a diagnostic marker and parameter of progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: ADC; biomarker; breast cancer; metastatic; PD-L1

Update Breast Cancer 2022 Part 3 - Early-Stage Breast Cancer. - Fehm, Tanja N.; Welslau, Manfred; Mueller, Volkmar; Lueftner, Diana; Schuetz, Florian; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Belleville, Erik; Untch, Michael; Thill, Marc; et al. (Geburtshilfe und Frauenheilkunde, 2022)
This review summarizes recent developments in the prevention and treatment of patients with early-stage breast cancer. The individual disease risk for different molecular subtypes was investigated in a large epidemiological study. With regard to treatment, new data are available from long-term follow-up of the Aphinity study, as well as new data on neoadjuvant therapy with atezolizumab in HER2-positive patients. Biomarkers, such as residual cancer burden, were investigated in the context of pembrolizumab therapy. A Genomic Grade Index study in elderly patients is one of a group of studies investigating the use of modern multigene tests to identify patients with an excellent prognosis in whom chemotherapy may be avoided. These and other aspects of the latest developments in the diagnosis and treatment of breast cancer are described in this review.
EVALuna2:511790

Update Breast Cancer 2022 Part 4 - Advanced-Stage Breast Cancer. - Aktas, Bahriye; Fehm, Tanja N.; Welslau, Manfred; Mueller, Volkmar; Lueftner, Diana; Schuetz, Florian; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Belleville, Erik; Untch, Michael; et al. (Geburtshilfe und Frauenheilkunde, 2022)
For the treatment of patients with advanced HER2-negative hormone receptor-positive breast cancer, several substances have been introduced into practice in recent years. In addition, other drugs are under development. A number of studies have been published over the past year which have shown either an advantage for progression-free survival or for overall survival. This review summarizes the latest results, which have been published at current congresses or in specialist journals, and classifies them in the clinical treatment context. In particular, the importance of therapy with CDK4/6 inhibitors - trastuzumab deruxtecan, sacituzumab govitecan and capivasertib - is discussed. For trastuzumab deruxtecan, an overall survival benefit in HER2-negative breast cancer with low HER2 expression (HER2-low expression) was reported in the Destiny-Breast-04 study. Similarly, there was an overall survival benefit in the FAKTION study with capivasertib. The lack of overall survival benefit for palbociclib in the first line of therapy raises the question of clinical classification.
EVALuna2:511788

Update Breast Cancer 2022 Part 5 – Early Stage Breast Cancer - Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Beierlein, Milena; Belleville, Erik; Untch, Michael; et al. (Geburtshilfe und Frauenheilkunde, 2023)
The treatment of patients with early stage breast cancer has changed in recent years due to the introduction of pembrolizumab, olaparib, and abemaciclib. These and other drugs with the same class of active ingredient are currently in trial for various indications. This review article summarizes the latest results that have either been presented at major conferences such as the ESMO 2022 or published recently in international journals. This includes reports on newly discovered breast cancer genes, atezolizumab in neoadjuvant therapy in HER2-positive patients, long-term data from the APHINITY study, and on how preoperative peritumoral application of local anesthetics can influence the prognosis. We also present solid data on dynamic Ki-67 from the ADAPT studies.
CRIS-Team Scopus Importer:2023-03-31
Keywords: breast cancer; chemotherapy; surgery; therapy standard

Update Breast Cancer 2022 Part 6 – Advanced-Stage Breast Cancer - Lüftner, Diana; Lux, Michael P.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Beierlein, Milena; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Large-scale study programs on CDK4/6 inhibitors, targeted therapies, and antibody-drug conjugates launched in recent years have yielded results from current studies which are now being published in journals and presented at international conferences. In this context, new results are available from the major CDK4/6 inhibitor studies. Also, an increasing amount of data is being published from large-scale genomic studies on efficacy and resistance mechanisms in patients treated with CDK4/6 inhibitors. These results now form the basis for further research plans to investigate combination therapies and treatment sequencing. Based on the latest published results, sacituzumab govitecan is now available as a second antibody-drug conjugate; this brings an advantage in terms of overall survival for patients with hormone receptor-positive (HRpos)/HER2-negative (HER2neg) breast cancer. In this review article, we summarize the latest developments and place them in context according to the current status of research.
CRIS-Team Scopus Importer:2023-03-31
Keywords: advanced breast cancer; chemotherapy; therapy standard

Update Breast Cancer 2023 Part 2 - Advanced-Stage Breast Cancer. - Lux, Michael P.; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Janni, Wolfgang; Witzel, Isabell; Thomssen, Christoph; Beierlein, Milena; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2023)
In recent years, a number of new therapies have led to advances in the treatment of patients with advanced breast carcinoma. These substances are mainly CDK4/6 inhibitors and other substances that can overcome endocrine resistance, oral selective estrogen receptor degraders, antibody drug conjugates (ADCs), and PARP inhibitors. This review summarizes and evaluates the latest study results that have been published in recent months. This includes the overall survival data of the Destiny-Breast03 study, the first analysis of the CAPItello-291 study, the comparison of CDK4/6 inhibitor treatment with chemotherapy in the first line of therapy (RIGHT Choice study), the first analysis of the Destiny-Breast02 study in the treatment setting after T-DM1 treatment, and the first analysis of the Serena-2 study. Most of these studies have the potential to significantly change the therapeutic landscape for patients with advanced breast carcinoma and show that the continued rapid development of new therapies is always producing new results.
EVALuna2:540882

Update Breast Cancer 2024 Part 1 - Expert Opinion on Advanced Breast Cancer - Würstlein, Rachel; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Schütz, Florian; Fasching, Peter; Janni, Wolfgang; Witzel, Isabell; Thomssen, Christoph; Krückel, Annika; Belleville, Erik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Clinical evidence is interpreted based on clinical studies and personal experience which can lead to different interpretations of data. This makes the opinions issued by panels of experts such as the Advanced Breast Cancer Panel which convened in November 2023 for the seventh time (ABC7) particularly important. At the conference, current issues around advanced breast cancer were evaluated by an international team of experts.In 2023 the data on CDK4/6 inhibitors was so extensive that the answers to questions about the sequencing of therapy and the potential use of chemotherapy as an alternative therapy were relatively clear. Moreover, data on antibody drug conjugates which provides a good overview of their uses is available for all molecular subtypes.Some therapeutic settings, including patients with brain metastases or leptomeningeal disease, older patients, locally advanced breast cancer and visceral crises, continue to be particularly important and were discussed in structured sessions. The scientific context of some of the topics discussed at ABC7 is presented and assessed here.
CRIS-Team Scopus Importer:2024-06-14
Keywords: antibody drug conjugate; breast cancer; chemotherapy; endocrine therapy; metastatic

Update Breast Cancer 2024 Part 2-Patients with Early Stage Breast Cancer Update Mammakarzinom 2024 Teil 2 – Patientinnen mit Frühstadien des Mammakarzinoms - Janni, Wolfgang; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Jackisch, Christian; Marme, Frederik; Hörner, Manuel; Keller, Katharina; et al. (Geburtshilfe und Frauenheilkunde, 2025)
This review summarizes the latest developments for the treatment of patients with early-stage breast cancer. Most of the clinically relevant changes were the result of using immune checkpoint inhibitors to treat patients with triple-negative breast cancer (TNBC) and CDK4/6 inhibitors to treat patients with hormone receptor-positive, HER2-negative (HRpos/HER2neg) tumors and a high risk of recurrence. Recent studies are presenting more and more data with long follow-up times and integrating translational analyses to evaluate new biomarkers such as circulating tumor DNA (ctDNA). This review article summarizes the latest developments published in recent months and puts the findings in context.
CRIS-Team Scopus Importer:2025-05-30
Keywords: biomarker; breast cancer; clinical studies; early breast cancer

Update Breast Cancer 2024 Part 3-Patients with Advanced Stage Breast Cancer Update Mammakarzinom 2024 Teil 3 – Patientinnen mit fortgeschrittenen Stadien des Mammakarzinoms - Lüftner, Diana; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Jackisch, Christian; Marme, Frederik; Keller, Katharina; Hörner, Manuel; et al. (Geburtshilfe und Frauenheilkunde, 2025)
The use of CDK4/6 inhibitors, the new PI3K/AKT-kinase inhibitors, selective estrogen receptor-degraders (SERDs), antibody-drug conjugates, immune therapies and PARP inhibitors in recent years has resulted in a marked change in the therapy landscape for patients with advanced stage breast cancer. CDK4/6 inhibitors, trastuzumab deruxtecan, and sacituzumab govitecan have all been shown to provide significant overall survival benefits compared to conventional chemotherapy. Other substances are also showing promising results and hold out the hope that further analysis of the overall survival benefits will be available in the near future. The speed at which studies are now being carried out has markedly increased, and conferences and specialist journals are now constant sources of new information. This review summarizes the most recent publications and conference presentations on the treatment of patients with advanced stage breast cancer.
CRIS-Team Scopus Importer:2025-05-30
Keywords: advanced breast cancer; breast cancer; clinical studies; prognosis

Updated overall survival from the MONALEESA-3 trial in postmenopausal women with HR+/HER2− advanced breast cancer receiving first-line ribociclib plus fulvestrant - Neven, P.; Fasching, Peter; Chia, S.; Jerusalem, G.; De Laurentiis, M.; Im, S. A.; Petrakova, K.; Bianchi, G. V.; Martín, M.; Nusch, A.; Sonke, G. S.; De la Cruz-Merino, L.; et al. (Breast Cancer Research, 2023)
Background: The phase III MONALEESA-3 trial included first- (1L) and second-line (2L) patients and demonstrated a significant overall survival (OS) benefit for ribociclib + fulvestrant in patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative (HR+/HER2−) advanced breast cancer (ABC) in the final protocol-specified and exploratory (longer follow-up) OS analyses. At the time of these analyses, the full OS benefit of 1L ribociclib was not completely characterized because the median OS (mOS) was not reached. As CDK4/6 inhibitor (CDK4/6i) + endocrine therapy (ET) is now a preferred option for 1L HR+/HER2− ABC, we report an exploratory analysis (median follow-up, 70.8 months; 14.5 months longer than the prior analysis) to fully elucidate the OS benefit in the MONALEESA-3 1L population. Methods: Postmenopausal patients with HR+/HER2− ABC were randomized 2:1 to 1L/2L fulvestrant + ribociclib or placebo. OS in 1L patients (de novo disease or relapse > 12 months from completion of [neo]adjuvant ET) was assessed by Cox proportional hazards model and Kaplan–Meier methods. Progression-free survival 2 (PFS2) and chemotherapy-free survival (CFS) were analyzed. MONALEESA-3 is registered with ClinicalTrials.gov (NCT02422615). Results: At data cutoff (January 12, 2022; median follow-up time, 70.8 months), mOS was 67.6 versus 51.8 months with 1L ribociclib versus placebo (hazard ratio (HR) 0.67; 95% CI 0.50–0.90); 16.5% and 8.6% of ribociclib and placebo patients, respectively, were still receiving treatment. PFS2 (HR 0.64) and CFS (HR 0.62) favored ribociclib versus placebo. Among those who discontinued treatment, 16.7% and 35.0% on ribociclib or placebo, respectively, received a subsequent CDK4/6i. No new safety signals were observed. Conclusions: This analysis of MONALEESA-3 reports the longest mOS thus far (67.6 months) for 1L patients in a phase III ABC trial. These results in a 1L population show that the OS benefit of ribociclib was maintained through extended follow-up, further supporting its use in HR+/HER2− ABC.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Advanced breast cancer; CDK4/6 inhibitor; First line; Overall survival; Ribociclib

Updated overall survival (OS) results from the first-line (1L) population in the phase III MONALEESA-3 trial of postmenopausal patients (PTS) with HR+/HER2-advanced breast cancer (ABC) treated with ribociclib (RIB) plus fulvestrant (FUL) - Neven, P.; Fasching, Peter; Chia, S.; Jerusalem, G.; De Laurentiis, M.; Im, S. -A.; Petrakova, K.; Bianchi, G. V.; Martin Jimenez, M.; Nusch, A.; Sonke, G. S.; De La Cruz Merino, L.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-06-03

Update Mammakarzinom 2019 Teil 1 – Implementierung der Ergebnisse neuer Studienkonzepte beim frühen Mammakarzinom in die klinische Praxis - Hartkopf, Andreas D.; Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Nabieva, Naiba; Taran, Florin Andrei; Ettl, Johannes; Lüftner, Diana; Belleville, Erik; Schütz, Florian; Fasching, Peter; et al. (TumorDiagnostik & Therapie, 2019)
For many years, small but significant advancements have been made time and again in the prevention and treatment of early breast cancer. The so-called panel gene analyses are becoming more and more important in prevention, since the risk due to the tested genes is better understood and as a result, concepts for integration in health care can be developed. In the adjuvant situation, the first study in the so-called postneoadjuvant situation was able to demonstrate a clear improvement in the prognosis with an absent pathological complete remission following trastuzumab or pertuzumab + trastuzumab. Additional studies with this post-neoadjuvant therapeutic concept are still being conducted at present. The CDK4/6 inhibitors which had shown a significant improvement in progression-free survival in a metastatic situation are currently being tested in the adjuvant situation in large therapeutic studies. These and other new data for the treatment or prevention of primary breast cancer are presented in this review against the backdrop of current studies.
CRIS-Team Scopus Importer:2019-09-17
Keywords: adjuvant therapy; early breast cancer; Katherine; neoadjuvant therapy; prevention; TDM1

Updates on the role of receptor activator of nuclear factor κB/receptor activator of nuclear factor κB ligand/osteoprotegerin pathway in breast cancer risk and treatment - Bayer, Christian M.; Beckmann, Matthias; Fasching, Peter (Current Opinion in Obstetrics & Gynecology, 2017)
PURPOSE OF REVIEW: Treatment with bisphosphonates and denosumab is the standard of care in bone metastatic disease. In addition, the adjuvant therapy of denosumab or bisphosphonates is very effective to prevent loss of bone mineral density, for example in osteoporosis. However, it is still unclear if this therapy has an influence on preventing cancer. RECENT FINDINGS: Since the identification of novel genes in the 1980s, it took about 30 years until denosumab, as a fully human mAb against receptor activator of nuclear factor (NF)-κB ligand (RANKL), could be introduced to clinical practice. The discovery of the receptor activator of NF-κB/RANKL/osteoprotegerin pathway in the 1990s is an example of how modern databases of genes were utilized to discover new pathways relevant to a variety of diseases. The essential role of this pathway for the function, differentiation and survival of osteoclasts, and the influence on the bone microenvironment helped to understand the vicious circle of bone resorption and destruction in many skeletal diseases. SUMMARY: In the following review, we discuss the important role of rational targeting concerning receptor activator of NF-κB/RANKL/osteoprotegerin and the bisphosphonate therapy and provide an update for the related treatment of patients suffering from breast cancer and further implications for clinical practice and research using denosumab as a potential chemoprevention in BRCA1-related breast cancer.
EVALuna2:36158

Usability and Perception of a Wearable-Integrated Digital Maternity Record App in Germany: User Study - Nissen, Michael; Perez, Carlos A.; Jäger, Katharina; Bleher, Hannah; Flaucher, Madeleine; Hübner, Hanna; Danzberger, Nina; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Beckmann, Matthias; Eskofier, Björn; et al. (JMIR Pediatrics and Parenting, 2023)
Background: Although digital maternity records (DMRs) have been evaluated in the past, no previous work investigated usability or acceptance through an observational usability study. Objective: The primary objective was to assess the usability and perception of a DMR smartphone app for pregnant women. The secondary objective was to assess personal preferences and habits related to online information searching, wearable data presentation and interpretation, at-home examination, and sharing data for research purposes during pregnancy. Methods: A DMR smartphone app was developed. Key features such as wearable device integration, study functionalities (eg, questionnaires), and common pregnancy app functionalities (eg, mood tracker) were included. Women who had previously given birth were invited to participate. Participants completed 10 tasks while asked to think aloud. Sessions were conducted via Zoom. Video, audio, and the shared screen were recorded for analysis. Task completion times, task success, errors, and self-reported (free text) feedback were evaluated. Usability was measured through the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). Semistructured interviews were conducted to explore the secondary objective. Results: A total of 11 participants (mean age 34.6, SD 2.2 years) were included in the study. A mean SUS score of 79.09 (SD 18.38) was achieved. The app was rated “above average” in 4 of 6 UEQ categories. Sixteen unique features were requested. We found that 5 of 11 participants would only use wearables during pregnancy if requested to by their physician, while 10 of 11 stated they would share their data for research purposes. Conclusions: Pregnant women rely on their medical caregivers for advice, including on the use of mobile and ubiquitous health technology. Clear benefits must be communicated if issuing wearable devices to pregnant women. Participants that experienced pregnancy complications in the past were overall more open toward the use of wearable devices in pregnancy. Pregnant women have different opinions regarding access to, interpretation of, and reactions to alerts based on wearable data. Future work should investigate personalized concepts covering these aspects.
Created from Fastlane, Scopus look-up
Keywords: app; application; applications; apps; attitude; attitudes; data sharing; develop; development; digital; electronic; electronic maternity record; experience; experiences; feature; features; health record; health records; information behavior; information behaviour; information seeking; log; logbook; maternal; maternity; maternity log; maternity logbook; maternity record; mHealth; mobile health; online search; opinion; opinions; paper hand-held record; perception; perceptions; personal health record; perspective; perspectives; PHR; pregnancy; pregnancy app; pregnancy record; pregnant; privacy; searching; smartphone; smartphones; usability; wearable; wearables

Use of a molecular Registry (PRAEGNANT) for Patient-Selection and Biomarker-Analysis for the SHERBOC Study - Hübner, Hanna; Kurbacher, C.; Kuesters, G.; Hartkopf, A. D.; Lux, M. P.; Huober, J.; Volz, B.; Taran, F. A.; Overkamp, F.; Tesch, H.; Häberle, Lothar; Lueftner, D.; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Use of complementary and integrative medicine among German breast cancer patients: predictors and implications for patient care within the PRAEGNANT study network - Fremd, Carlo; Hack, Carolin; Schneeweiss, Andreas; Rauch, Geraldine; Wallwiener, Diethelm; Brucker, Sara Yvonne; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Tesch, Hans; Fehm, Tanja; Hadji, Peyman; et al. (Archives of Gynecology and Obstetrics, 2017)
PURPOSE: The present study aims to analyze a cohort of advanced breast cancer patients in Germany to assess their interest in complementary and alternative medicine (CAM) and patient's use of most frequent CAM methods. PATIENTS AND METHODS: Based on the PREGNANT real-time breast cancer registry which is a multicenter study in Germany, questionnaires of 580 patients with advanced breast cancer were evaluated. The implemented questionnaire for CAM asked for general interest in CAM and for patient's use of different CAM methods at present and in the past. The interest and application of CAM were analyzed for association with patients' characteristics such as tumor, patient, and therapy characteristics. RESULTS: In total, 436 out of 580 (75%) patients claimed to be interested in CAM. Further, interest in CAM is significantly correlated with younger age and absence of metastasis at the time of diagnosis. Multivariate analysis confirmed the patient's age and distant disease status at the time of diagnosis as related to interest in CAM. A total of 56.4% of patients applied any CAM method in the past. Moreover, with increasing lines of therapies, the more frequent use of CAM was observed. Hereby, praying, vitamin supplements, and other food supplements were most frequently applied. CONCLUSION: Our data demonstrate high overall interest and frequent use of CAM in advanced breast cancer patients supporting a strong demand of breast cancer patients for complementary counseling and treatments additional to the established cancer therapies. It is indispensable to implement counseling and evidence-based complementary treatments into clinical routine of cancer centers and to adapt postgraduate medical education, respectively.
EVALuna2:36145

Use of Granulocyte-colony Stimulating Factor During Chemotherapy and Its Association With CA27.29 and Circulating Tumor Cells-Results From the SUCCESS A Trial - Hepp, Philip; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Salmen, Jessica; Hagenbeck, Carsten; Jaeger, Bernadette; Widschwendter, Peter; De Gregorio, Nikolaus; Schochter, Fabienne; Mahner, Sven; Harbeck, Nadia; et al. (Clinical Breast Cancer, 2018)
Little is known about the effect of granulocyte colony-stimulating factor (G-CSF) treatment during adjuvant chemotherapy on prognostic markers. The present study explored the association between G-CSF and changes in cancer antigen (CA)27.29 and circulating tumor cell (CTC) levels during therapy.A total of 3754 node-positive or high-risk node-negative early-stage breast cancer patients were treated within the SUCCESS-A trial (simultaneous study of gemcitabine-docetaxel combination adjuvant treatment, as well as extended bisphosphonate and surveillance-trial). CA27.29 and CTCs were determined before the start and within 6 weeks after the end of chemotherapy.Overall, 1324 of the 2646 patients (50.0%) available for analysis had >= 1 G-CSF applications during chemotherapy. G-CSF application was significantly associated with CA27.29 status before and after chemotherapy (? = 30.6, df = 3; P < .001), because 238 patients (18.0%) with G-CSF treatment but only 146 (11.0%) without G-CSF treatment switched from a negative CA27.29 status before to a positive CA27.29 status after chemotherapy. In addition, patients with G-CSF application showed a significantly greater increase in CA27.29 levels after chemotherapy compared with patients without any G-CSF application during chemotherapy (Mann-Whitney U test; Z = -7.81, P < .001). No significant association was found between G-CSF application and CTC status before or after chemotherapy (? = 1.2, df = 3; P = .75).Cautious interpretation is needed regarding elevated levels of MUC-1-derived tumor markers such as CA27.29 shortly after adjuvant chemotherapy when G-CSF has been given, because G-CSF treatment was associated with increased CA27.29 levels after chemotherapy.
EVALuna2:56150

Using automated texture features to determine the probability for masking of a tumor on mammography, but not ultrasound - Haeberle, Lothar; Hack, Carolin; Heusinger, Katharina; Wagner, Florian; Jud, Sebastian; Uder, Michael; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Fasching, Peter (European Journal of Medical Research, 2017)
BACKGROUND: Tumors in radiologically dense breast were overlooked on mammograms more often than tumors in low-density breasts. A fast reproducible and automated method of assessing percentage mammographic density (PMD) would be desirable to support decisions whether ultrasonography should be provided for women in addition to mammography in diagnostic mammography units. PMD assessment has still not been included in clinical routine work, as there are issues of interobserver variability and the procedure is quite time consuming. This study investigated whether fully automatically generated texture features of mammograms can replace time-consuming semi-automatic PMD assessment to predict a patient's risk of having an invasive breast tumor that is visible on ultrasound but masked on mammography (mammography failure). METHODS: This observational study included 1334 women with invasive breast cancer treated at a hospital-based diagnostic mammography unit. Ultrasound was available for the entire cohort as part of routine diagnosis. Computer-based threshold PMD assessments ("observed PMD") were carried out and 363 texture features were obtained from each mammogram. Several variable selection and regression techniques (univariate selection, lasso, boosting, random forest) were applied to predict PMD from the texture features. The predicted PMD values were each used as new predictor for masking in logistic regression models together with clinical predictors. These four logistic regression models with predicted PMD were compared among themselves and with a logistic regression model with observed PMD. The most accurate masking prediction was determined by cross-validation. RESULTS: About 120 of the 363 texture features were selected for predicting PMD. Density predictions with boosting were the best substitute for observed PMD to predict masking. Overall, the corresponding logistic regression model performed better (cross-validated AUC, 0.747) than one without mammographic density (0.734), but less well than the one with the observed PMD (0.753). However, in patients with an assigned mammography failure risk >10%, covering about half of all masked tumors, the boosting-based model performed at least as accurately as the original PMD model. CONCLUSION: Automatically generated texture features can replace semi-automatically determined PMD in a prediction model for mammography failure, such that more than 50% of masked tumors could be discovered.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD9.usinga
Keywords: Mammographic density; Mammography screening; Masking; Risk prediction; Sensitivity; Texture analysis; Variable selection

Using Probability for Pathological Complete Response (pCR) as a Decision Support Marker for Neoadjuvant Chemotherapy in HER2 Negative Breast Cancer Patients - a Survey Among Physicians - Gaß, Paul; Untch, Michael; Mueller, Volkmar; Moebus, Volker; Thomssen, Christoph; Häberle, Lothar; Erber, Ramona; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Hartmann, Arndt; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Background: In women with early breast cancer, a pathological complete response (pCR) after neoadjuvant chemotherapy is reported to be associated with an improvement of the survival. The aim of this survey among physicians was to investigate whether the probability of achieving pCR in patients with a hormone receptor-positive, HER2-negative disease encourages physicians to recommend neoadjuvant chemotherapy. Methods: The study was conducted via an online survey that was sent to 493 physicians, who were either known as members of national guideline committees, heads of breast cancer centers, being high recruiters in clinical trials or leading a private practice. Participants were asked about a specific case that should resemble patients for whom it is unclear, whether they should be treated with chemotherapy. Results: 113 (24.5%) physicians participated at the survey, out of which 96.5% had a work experience of more than 10 years and 94.7% were board certified in their specialty. A total of 84.1% would consider pCR for a decision concerning neoadjuvant chemotherapy. With regard to the pCR probability, 2.7 and 10.6% of the participants demanded at least a pCR rate of 5 and 10%, respectively, while 25.7% were satisfied with 20% probability, and another 25.7% with a pCR rate of 30%. Conclusions: The vast majority of the long-term experienced physicians would embrace the implementation of a further method such as the prediction of pCR probability in clinical routine to support decision making regarding the necessity of neoadjuvant chemotherapy. The cut-off of around 30% pCR probability seems to be a realizable rate to distinguish patient groups.
EVALuna2:34856

Utility of the CPS + EG scoring system in triple-negative breast cancer treated with neoadjuvant chemotherapy - Marmé, Frederik; Solbach, Christine; Michel, Laura; Schneeweiss, Andreas; Blohmer, Jens Uwe; Huober, Jens; Fasching, Peter; Jackisch, Christian; Nekljudova, Valentina; Link, Theresa; Rhiem, Kerstin; Rey, Julia; et al. (European Journal of Cancer, 2021)
Background: Pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) is associated with superior survival. This association is strongest in triple-negative breast cancer (TNBC). The CPS + EG system, based on pre-treatment clinical (CS) and post-treatment pathological stage (PS), oestrogen-receptor status (E) and grade (G), leads to a refined estimate of prognosis after NACT in all-comers and hormone receptor–positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer. Here, we investigate if CPS + EG scoring provides a superior estimate of prognosis in TNBC to select patients for postneoadjuvant therapy. Methods: We calculated the CPS + EG score for 1795 patients with TNBC from 8 prospective German trials. Five-year disease-free survival (DFS) and overall survival estimates were calculated using the Kaplan-Meier method. Results: In TNBC, patients with pCR (ypT0/is ypN0, n = 822, 45.8%) had a 5-year DFS of 86%, whereas patients with residual American Joint Committee on Cancer stage I disease (n = 383; 21.3%) had a 5-year DFS of 77.5%.CPS + EG led to superior prognostic information compared with that provided by the clinical stage, but it was inferior to the prognostic information provided by the pathological stage (c-index statistics, p < 0.001). CPS + EG did not discriminate prognosis within the two best prognostic groups (score 1 and 2; n = 362; 37.2%). In contrast, pCR status added prognostic information beyond CPS + EG. Patients with a CPS + EG score of 3 had a 5-year DFS rate of 64% overall, but those with pCR had a 5-year DFS rate of 84%, and those without pCR had a 5-year DFS rate of only 49.7%. Conclusions: In TNBC, CPS + EG scoring provided inferior prognostic information compared with the pathological stage and was unable to identify patients without pCR and with a sufficiently good prognosis, who could avoid postneoadjuvant therapy. pCR remains the strongest and most clinically useful prognostic factor after NACT. Other biologic factors beyond pCR are needed in TNBC.
CRIS-Team Scopus Importer:2021-07-23
Keywords: CPS + EG; Neoadjuvant therapy; Prognosis; Triple-negative breast cancer

Utility of the CPS plus EG scoring system in triple-negative breast cancer treated with neoadjuvant chemotherapy - Marme, F.; Solbach, C.; Michel, L.; Fasching, Peter; Schneeweiss, A.; Blohmer, J. -U.; Rezai, M.; Huober, J.; Jackisch, C.; Nekljudova, V.; Link, T.; Rhiem, K.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Validation and functional follow-up of cervical cancer risk variants at the HLA locus - Eisenblätter, Rieke; Seifert, Finja; Schürmann, Peter; Beckhaus, Theresa; Hanel, Patricia; Jentschke, Matthias; Böhmer, Gerd; Strauß, Hans Georg; Hirchenhain, Christine; Schmidmayr, Monika; Müller, Florian; Hein, Alexander; et al. (HLA, 2024)
Cervical cancer is the fourth most common cancer in females. Genome-wide association studies (GWASs) have proposed cervical cancer susceptibility variants at the HLA locus on chromosome 6p21. To corroborate these findings and investigate their functional impact in cervical tissues and cell lines, we genotyped nine variants from cervical cancer GWASs (rs17190106, rs535777, rs1056429, rs2763979, rs143954678, rs113937848, rs3117027, rs3130214, and rs9477610) in a German hospital-based series of 1122 invasive cervical cancers, 1408 dysplasias, and 1196 healthy controls. rs17190106, rs1056429 and rs143954678/rs113937848 associated with cervical malignancies overall, while rs17190106 and rs535777 associated specifically with invasive cancer (OR = 0.69, 95% CI = 0.55–0.86, p = 0.001) or adenocarcinomas (OR = 1.63, 95%CI = 1.17–2.27, p = 0.004), respectively. We tested these and one previously genotyped GWAS variant, rs9272117, for potential eQTL effects on 36 gene transcripts at the HLA locus in 280 cervical epithelial tissues. The strongest eQTL pairs were rs9272117 and HLA-DRB6 (p = 1.9x10E-5), rs1056429 and HLA-DRB5 (p = 2.5x10E-4), and rs535777 and HLA-DRB1 (p = 2.7x10E-4). We also identified transcripts that were specifically upregulated (DDX39B, HCP5, HLA-B, LTB, NFKBIL1) or downregulated (HLA-C, HLA-DPB2) in HPV+ or HPV16+ samples. In comparison, treating cervical epithelial cells with proinflammatory cytokine γ-IFN led to a dose-dependent induction of HCP5, HLA-B, HLA-C, HLA-DQB1, HLA-DRB1, HLA-DRB6, and repression of HSPA1L. Taken together, these results identify relevant genes from both the MHC class I and II regions that are inflammation-responsive in cervical epithelium and associate with HPV (HCP5, HLA-B, HLA-C) and/or with genomic cervical cancer risk variants (HLA-DRB1, HLA-DRB6). They may thus constitute important contributors to the immune escape of precancerous cells after HPV-infection.
CRIS-Team Scopus Importer:2024-08-16
Keywords: cervical malignancy; eQTL; HPV; IFNG; replication; SNP; susceptibility

Validation of the MammaTyper (R) pathological complete response (pCR)-score as a predictor for response after neoadjuvant chemotherapy (NACT) in patients with early breast cancer (BC) - Fasching, Peter; Laible, M.; Weber, K. E.; Wirtz, R. M.; Denkert, C.; Schlombs, K.; Schmatloch, S.; Camara, O.; Lueck, H. J.; Huober, J.; Karn, T.; Van Mackelenbergh, M. T.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

Variable expression of the disialoganglioside gd2 in breast cancer molecular subtypes - Erber, Ramona; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Meyer, Julia; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Geppert, Carol-Immanuel; Schulz-Wendtland, Rüdiger; et al. (Cancers, 2021)
The disialoganglioside GD2 is a tumor-associated antigen that may allow for the application of targeted immunotherapies (anti-GD2 antibodies, GD2 CAR T cells) in patients with neuroblastoma and other solid tumors. We retrospectively investigated GD2 expression in a breast cancer cohort, using immunohistochemistry (IHC) and immunofluorescence (IF) on tissue microarrays (TMAs), and its impact on survival. GD2 expression on IHC (n = 568) and IF (n = 503) was investigated in relation to subtypes and patient outcome. Overall, 50.2% of the 568 IHC-assessed samples and 69.8% of the 503 IF-assessed samples were GD2-positive. The highest proportion of GD2-positive tumors was observed in luminal tumors. Significantly fewer GD2-positive cases were detected in triple-negative breast cancer (TNBC) compared with other subtypes. The proportion of GD2-expressing tumors were significantly lower in HER2-positive breast cancer in comparison with luminal tumors on IF staining (but not IHC). GD2 expression of IHC or IF was not significantly associated with disease-free or overall survival, in either the overall cohort or in individual subtypes. However, GD2 expression can be seen in more than 50% of breast cancer cases, with the highest frequency in hormone receptorpositive tumors. With this high expression frequency, patients with GD2-positive advanced breast cancer of all subtypes may benefit from GD2-targeting immunotherapies, which are currently subject to clinical testing.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Breast cancer; Disialoganglioside; GD2; Immunofluorescence; Immunohistochemistry; Prognosis

Variants in genes encoding small GTPases and association with epithelial ovarian cancer susceptibility - Earp, Madalene; Tyrer, Jonathan P.; Winham, Stacey J.; Lin, Hui-Yi; Chornokur, Ganna; Dennis, Joe; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (PLoS ONE, 2018)
Epithelial ovarian cancer (EOC) is the fifth leading cause of cancer mortality in American women. Normal ovarian physiology is intricately connected to small GTP binding proteins of the Ras superfamily (Ras, Rho, Rab, Arf, and Ran) which govern processes such as signal transduction, cell proliferation, cell motility, and vesicle transport. We hypothesized that common germline variation in genes encoding small GTPases is associated with EOC risk. We investigated 322 variants in 88 small GTPase genes in germline DNA of 18,736 EOC patients and 26,138 controls of European ancestry using a custom genotype array and logistic regression fitting log-additive models. Functional annotation was used to identify biofeatures and expression quantitative trait loci that intersect with risk variants. One variant, ARHGEF10L (Rho guanine nucleotide exchange factor 10 like) rs2256787, was associated with increased endometrioid EOC risk (OR = 1.33, p = 4.46 x 10-6). Other variants of interest included another in ARHGEF10L, rs10788679, which was associated with invasive serous EOC risk (OR = 1.07, p = 0.00026) and two variants in AKAP6 (A-kinase anchoring protein 6) which were associated with risk of invasive EOC (rs1955513, OR = 0.90, p = 0.00033; rs927062, OR = 0.94, p = 0.00059). Functional annotation revealed that the two ARHGEF10L variants were located in super-enhancer regions and that AKAP6 rs927062 was associated with expression of GTPase gene ARHGAP5 (Rho GTPase activating protein 5). Inherited variants in ARHGEF10L and AKAP6, with potential transcriptional regulatory function and association with EOC risk, warrant investigation in independent EOC study populations.
EVALuna2:34624

Ventral rectopexy with biological mesh for recurrent disorders of the posterior pelvic organ compartment - Brunner, Michaela; Roth, H.; Günther, K.; Grützmann, Robert; Matzel, Klaus E. (International Journal of Colorectal Disease, 2019)
PURPOSE: Recurrent prolapse of the posterior pelvic organ compartment presents a management challenge, with the best surgical procedure remaining unclear. We present functional outcome and patient satisfaction after laparoscopic and robotic ventral mesh rectopexy (VMR) with biological mesh in patients with recurrence. METHODS: We analyzed data from 30 patients with recurrent posterior pelvic organ prolapse who underwent VMR with biological mesh from August 2012 to January 2018. Data included patient demographics and intra- and postoperative findings; functional outcome as assessed by Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), and Cleveland Clinic Incontinence Score (CCIS); and patient satisfaction. RESULTS: CCCS, CCIS, and ODS were significantly improved at 6-12 months postoperatively and at last follow-up. Patient satisfaction (visual analog scale [VAS] 6.7 [0 to 10]), subjective symptoms (+ 3.4 [scale - 5 to + 5]), and quality of life improvement (+ 3.0 [scale from - 5 to + 5]) were high at last follow-up. The rates of morbidity and major complications were 13% and 3%, respectively. There were no mesh-related complications or deaths. Difference in type of previous surgery (abdominal or transanal/perineal) had no significant effect on results. CONCLUSIONS: VMR with biological mesh is a safe and effective option for patients with recurrent posterior pelvic organ prolapse. It reduces functional symptoms, has a low complication rate, and promotes patient satisfaction.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Biological mesh; Functional outcome; Laparoscopic ventral rectopexy; Recurrent posterior compartment prolapse; Recurrent rectal prolapse

Ventral rectopexy with biological mesh: short-term functional results - Brunner, Michaela; Roth, H.; Guenther, K.; Grützmann, Robert; Matzel, K. E. (International Journal of Colorectal Disease, 2018)
PURPOSE: Ventral mesh rectopexy (VMR) is an established, minimally invasive, nerve-sparing procedure for the treatment of various symptomatic morphological changes in the posterior pelvic compartment. We present the short-term functional outcome and patient satisfaction after laparoscopic and robotic VMR with biological mesh. METHODS: We analyzed data from 123 patients who underwent laparoscopic ventral mesh rectopexy (LVMR) or robotic ventral mesh rectopexy (RVMR) from August 2012 to January 2017. Included in these data were patient demographics, intra- and postoperative findings, Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), Cleveland Clinic Incontinence Score (CCIS), and patient satisfaction as measured by visual analog scale (0-10). RESULTS: Improvements in CCCS, CCIS, and ODS were statistically significant at 6 and 12 months (p < 0.001). Patient satisfaction was excellent at 6 and 12 months (8.2/10 and 8.3/10, respectively). The overall complication rate was 14%, with a major complication rate of 2%. No mesh-related complications were observed. The need for surgical re-intervention because of relapse, symptom persistence or recurrence, or new symptoms was 3%. Outcome appears to be similar between LVMR and RVMR. CONCLUSIONS: Both LVMR and RVMR with biological mesh are safe and effective in reducing symptoms, as measured by CCCS, CCIS, and ODS, and patient satisfaction is high.
EVALuna2:212626

Veranstaltungsbericht: 10. Wissenschaftliches Symposium der AGO-TraFo - Banys-Paluchowski, Malgorzata; Antoniadis, Sophia; Hein, Alexander; Fehm, Tanja N.; Arnold, Norbert; Fasching, Peter (Geburtshilfe und Frauenheilkunde, 2018)
CRIS-Team Scopus Importer:2021-07-19

Veranstaltungsbericht – 11. Wissenschaftliches Symposium der AGO-TraFo - Banys-Paluchowski, Malgorzata; Wunderle, Marius; Fehm, Tanja N.; Arnold, Norbert; Fasching, Peter (Geburtshilfe und Frauenheilkunde, 2019)
CRIS-Team Scopus Importer:2020-02-21

WebPPG: Feasibility and Usability of Self-Performed, Browser-Based Smartphone Photoplethysmography - Nissen, Michael; Flaucher, Madeleine; Jäger, Katharina; Hübner, Hanna; Danzberger, Nina; Titzmann, Adriana; Pontones, Constanza; Fasching, Peter; Eskofier, Björn; Leutheuser, Heike (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Smartphones enable and facilitate biomedical studies as they allow the recording of various biomedical signals, including photoplethysmograms (PPG). However, user engagement rates in mobile health studies are reduced when an application (app) needs to be installed. This could be alleviated by using installation-free web apps. We evaluate the feasibility of browser-based PPG recording, conducting the first usability study on smartphone-based PPG. We present an at-home study using a web app and library for PPG recording using the rear camera and flash. The underlying library is freely made available to researchers. 25 Android users participated, using their own smartphones. The study consisted of a demographic and anamnestic questionnaire, the signal recording itself (60 s), and a consecutive usability questionnaire. After filtering, heart rate was extracted (14/17 successful), signal-to-noise ratios assessed (0.64 ± 0.50 dB, mean ± standard deviation), and quality was visually inspected (12/17 usable for diagnosis). Recording was not supported in 9 cases. This was due to the browser's insufficient support for the flash light API. The app received a System Usability Scale score of 82 ± 9, which is above the 90th percentile. Overall, browser flash light support is the main limiting factor for broad device support. Thus, browser-based PPG is not yet widely applicable, although most participants feel comfortable with the recording itself. The utilization of the user-facing camera might represent a more promising approach. This study contributes to the development of low-barrier, user-friendly, installation-free smartphone signal acquisition. This enables profound, comprehensive data collection for research and clinical practice.Clinical relevance - WebPPG offers low-barrier remote diagnostic capabilities without the need for app installation
Created from Fastlane, Scopus look-up
Keywords: Heart rate; Limiting; Cameras; Photoplethysmography; Libraries; Recording; Usability

Whole blood microRNAs as potential biomarkers in post-operative early breast cancer patients - Alunni-Fabbroni, Marianna; Majunke, Leonie; Trapp, Elisabeth K.; Tzschaschel, Marie; Mahner, Sven; Fasching, Peter; Fehm, Tanja; Schneeweiss, Andreas; Beck, Thomas; Lorenz, Ralf; Friedl, Thomas W. P.; Janni, Wolfgang; et al. (BMC Cancer, 2018)
microRNAs (miRNAs) are considered promising cancer biomarkers, showing high reliability, sensitivity and stability. Our study aimed to identify associations between whole blood miRNA profiles, presence of circulating tumor cells (CTCs) and clinical outcome in post-operative early breast cancer patients (EBC) to assess the utility of miRNAs as prognostic markers in this setting.A total of 48 post-operative patients, recruited in frame of the SUCCESS A trial, were included in this retrospective study and tested with a panel of 8 miRNAs (miR-10b, -19a, - 21, - 22, -20a, - 127, - 155, -200b). Additional 17 female healthy donors with no previous history of cancer were included in the study as negative controls. Blood samples were collected at different time points (pre-adjuvant therapy, post-adjuvant therapy, 2 years follow up), total RNA was extracted and the relative concentration of each miRNA was measured by quantitative PCR and compared in patients stratified on blood collection time or CTC detection. Furthermore, we compared miRNA profiles of patients, for each time point separately, and healthy donors. CTCs were visualized and quantified with immunocytochemistry analysis. Data were analyzed using non-parametric statistical tests.In our experimental system, miR-19a, miR-22 and miR-127 showed the most promising results, differentiating patients at different time points and from healthy controls, while miR-20a, miR-21 and miR-200b did not show any difference among the different groups. miR-10b and miR-155 were never detectable in our experimental system. With respect to patients' clinical characteristics, we found a significant correlation between miR-200b and lymph node status and between miR-20a and tumor type. Furthermore, miR-127 correlated with the presence of CTCs. Finally, we found a borderline significance between Progression Free Survival and miR-19a levels.This pilot study suggests that profiling whole blood miRNAs could help to better stratify post-operative EBC patients without any sign of metastasis to prevent later relapse or metastatic events.
EVALuna2:56167

Willingness of Patients with Breast Cancer in the Adjuvant and Metastatic Setting to Use Electronic Surveys (ePRO) Depends on Sociodemographic Factors, Health-related Quality of Life, Disease Status and Computer Skills - Graf, Joachim; Simoes, E.; Wisslicen, K.; Rava, L.; Walter, C. B.; Hartkopf, A.; Keilmann, L.; Taran, A.; Wallwiener, S.; Fasching, Peter; Brucker, S. Y.; Wallwiener, M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Because of the often unfavorable prognosis, particularly for patients with metastases, health-related quality of life is extremely important for breast cancer patients. In recent years, data on patient-relevant endpoints is being increasingly collected electronically; however, knowledge on the acceptance and practicability of, and barriers to, this form of data collection remains limited.Material and Methods:A questionnaire was completed by 96 patients to determine to what extent existing computer skills, disease status, health-related quality of life and sociodemographic factors affect patients' potential willingness to use electronics methods of data collection (ePRO).Results:52 of 96 (55 %) patients reported a priori that they could envisage using ePRO. Patients who a priori preferred a paper-based survey (pPRO) tended to be older (ePRO 53 years vs. pPRO 62 years; p = 0.0014) and typically had lower levels of education (p = 0.0002), were in poorer health (p = 0.0327) and had fewer computer skills (p = 0.0003).Conclusion:Barriers to the prospective use of ePRO were identified in older patients and patients with a lower quality of life. Given the appropriate conditions with regard to age, education and current health status, opportunities to participate should be provided to encourage patients' willingness to take part and ensure the validity of survey results. Focusing on ease of use of ePRO applications and making applications more patient-oriented and straightforward appears to be the way forward.
EVALuna2:33539

Zoledronate for patients with invasive residual disease after anthracyclines-taxane-based chemotherapy for early breast cancer - The Phase III NeoAdjuvant Trial Add-oN (NaTaN) study (GBG 36/ABCSG 29) - Von Minckwitz, G.; Rezai, M.; Tesch, H.; Huober, J.; Gerber, B.; Zahm, D. M.; Hilfrich, J.; Costa, S. D.; Dubsky, P.; Blohmer, J. U.; Denkert, Carsten; Hanusch, C.; et al. (European Journal of Cancer, 2016)
BACKGROUND: Patients with invasive residual disease after neoadjuvant chemotherapy (NACT) are considered to have chemo-resistant breast cancer. Bisphosphonates are an established treatment for bone metastases and are of potential benefit as adjuvant treatment in early breast cancer. PATIENTS AND METHODS: Patients who had invasive tumour residuals (ypT1-4 and/or ypN+) after a minimum of four cycles of anthracycline-taxane-containing NACT were eligible for the NeoAdjuvant Trial Add-oN study. Patients were randomised within 3 years after surgery to receive zoledronate 4 mg i.v. for 5 years versus observation. Zoledronate was given every 4 weeks for the first 6 months, every 3 months for the following 2 years, and every 6 months for the last 2.5 years. Primary objective was disease-free survival. RESULTS: After a median time of 54.7 months no difference in disease-free survival was observed between the zoledronate and observation groups (hazard ratio [HR] 0.960, 95% confidence interval [CI] 0.709-1.30, log rank P=0.789). Various subgroups were examined without identifying a treatment effect of zoledronate. Patients over 55 years of age showed a HR of 0.832 in favour of zoledronate, but the result was not significant (P=0.480). A similar result was obtained for overall survival with a HR of 1.19 (95% CI 0.79-1.79; log rank P=0.408). Zoledronate was well tolerated and no new toxicity signal was identified. CONCLUSION: Postneoadjuvant treatment with zoledronate does not improve outcome in patients without pathological complete response after neoadjuvant anthracycline-taxane-based chemotherapy for early breast cancer.
EVALuna2:33068

Zukunft mammographie-basierter Bildgebung [Future of mammography-based imaging] - Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Michel, Thilo; Hartmann, Arndt; Beckmann, Matthias; Rauh, Claudia; Judt, Sebastian; Brehm, Barbara; Meier-Meitinger, Martina; Anton, Gisela; Uder, Michael; Fasching, Peter (Radiologe, 2014)
Mammography is the central diagnostic method for clinical diagnostics of breast cancer and the breast cancer screening program. In the clinical routine complementary methods, such as ultrasound, tomosynthesis and optional magnetic resonance imaging (MRI) are already combined for the diagnostic procedure. Future developments will utilize investigative procedures either as a hybrid (combination of several different imaging modalities in one instrument) or as a fusion method (the technical fusion of two or more of these methods) to implement fusion imaging into diagnostic algorithms. For screening there are reasonable hypotheses to aim for studies that individualize the diagnostic process within the screening procedure. Individual breast cancer risk prediction and individualized knowledge about sensitivity and specificity for certain diagnostic methods could be tested. The clinical implementation of these algorithms is not yet in sight. (orig.) [German] Die Mammographie ist die zentrale diagnostische Methode der klinischen symptombezogenen Abklaerung von Brusterkrankungen und des Brustkrebsscreenings. In der klinischen Diagnostik wird sie heute schon oft durch zusaetzliche Untersuchungsmethoden wie dem Ultraschall, der Tomosynthese und ggf. auch der MRT-Bildgebung unterstuetzt. Zukuenftige Entwicklungen gehen in die Richtung, dass diese Kombination aus 2 oder mehr Untersuchungsverfahren entweder in Hybrid- (Aufnahme mehrerer unterschiedlicher Bildmodalitaeten in einem einzigen Geraet) oder in Fusionsmethoden (Zusammenfuehrung und Registrierung von Bilddaten aus verschiedenen Modalitaeten) technisch professionalisiert werden. Des Weiteren koennten an subgruppenbezogene Erkrankungsrisiken und individuelle Sensitivitaeten und Spezifitaeten angepasste Diagnostikkombinationen fuer eine Screeningdiagnostik Gegenstand kuenftiger Studien sein. Wir stellen die aktuellen Entwicklungen auf diesen Gebieten und deren momentane Relevanz fuer die klinische Praxis und Entwicklungspotenzial fuer die Zukunft dar. (orig
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD9.zukunf
Keywords: MAMMOgraphy